Hypertension, Cognitive Decline, and Mild Cognitive Impairment Among Diverse Hispanics/Latinos: Study of Latinos-Investigation of Neurocognitive Aging Results (SOL-INCA). - Márquez, Freddie; Tarraf, Wassim; Stickel, Ariana M; Gonzalez, Kevin A; Testai, Fernando D; Cai, Jianwen; Gallo, Linda C; Talavera, Gregory A; Daviglus, Martha L; Wassertheil-Smoller, Sylvia; DeCarli, Charles; Schneiderman, Neil; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Hypertension can have deleterious effects on cognitive function; however, few studies have examined its effects on cognition among Hispanics/Latinos. OBJECTIVE: To assess associations between hypertension status with 1) change in cognitive performance, and 2) having mild cognitive impairment (MCI) among diverse Hispanics/Latinos. METHODS: This population-based, prospective cohort, multisite study included Hispanic/Latino adults aged 45 to 72 years in enrolled in the Hispanic Community Health Study/Study of Latinos at Visit 1 (2008-2011; mean age of 63.40±8.24 years), and the Study of Latinos-Investigation of Neurocognitive Aging at Visit 2 (2016-2018), with a mean follow-up duration of 7 years (n = 6,173). Hypertension status was assessed at both visits: normotension (no hypertension), incident hypertension (only at Visit 2), and persistent hypertension (at both visits). We examined change in cognitive performance and having MCI (only assessed at Visit 2) relative to hypertension status and adjusted for demographics and cardiovascular disease risk factors. RESULTS: Compared to normotension, persistent hypertension was associated with significantly increased decline in verbal fluency (β= -0.08; CI = [-0.16;-0.01]; p < 0.05), and processing speed (β= -0.11; CI = [-0.20;-0.02]; p < 0.05). Incident hypertension was not associated with significant change in cognitive performance. Both incident (OR = 1.70; CI = [1.16;2.50]; p < 0.01) and persistent hypertension (OR = 2.13; CI = [1.57;2.88]; p < 0.001) were associated with significantly higher odds ratios of having MCI. CONCLUSIONS: These findings indicate that persistent hypertension is associated with clinical impairment and domain-specific cognitive decline in middle-aged and older Hispanics/Latinos. It underscores the importance of monitoring blood pressure in routine healthcare visits beginning at midlife in this population to reduce the burden of cognitive decline.

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Alzheimer's Disease and Neurosyphilis: Meaningful Commonalities and Differences of Clinical Phenotype and Pathophysiological Biomarkers. - Milano, Chiara; Hoxhaj, Domeniko; Del Chicca, Marta; Pascazio, Alessia; Paoli, Davide; Tommasini, Luca; Vergallo, Andrea; Pizzanelli, Chiara; Tognoni, Gloria; Nuti, Angelo; Ceravolo, Roberto; Siciliano, Gabriele; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neurosyphilis-associated cognitive and behavioral impairment- historically coined as "general paralysis of the insane"- share clinical and neuroradiological features with the neurodegenerative disease spectrum, in particular Alzheimer's disease (AD). Anatomopathological similarities have been extensively documented, i.e., neuronal loss, fibrillary alterations, and local amyloid-β deposition. Consequently, accurate classification and timely differential diagnosis may be challenging. OBJECTIVE: To describe clinical, bio-humoral, brain MRI, FDG-PET, and amyloid-PET features in cases of neurosyphilis with an AD-like phenotypical presentation, as well as clinical outcome in terms of response to antibiotic therapy. METHODS: We selected the studies comparing patients with AD and with neurosyphilis associated cognitive impairment, to investigate candidate biomarkers classifying the two neurological diseases. RESULTS: The neuropsychological phenotype of general paralysis, characterized by episodic memory impairment and executive disfunction, substantially mimics clinical AD features. Neuroimaging often shows diffuse or medial temporal cortical atrophy, thus contributing to a high rate of misdiagnosis. Cerebrospinal fluid (CSF)-based analysis may provide supportive diagnostic value, since increased proteins or cells are often found in neurosyphilis, while published data on pathophysiological AD candidate biomarkers are controversial. Finally, psychometric testing using cross-domain cognitive tests, may highlight a wider range of compromised functions in neurosyphilis, involving language, attention, executive function, and spatial ability, which are atypical for AD. CONCLUSION: Neurosyphilis should be considered a potential etiological differential diagnosis of cognitive impairment whenever imaging, neuropsychological or CSF features are atypical for AD, in order to promptly start antibiotic therapy and delay or halt cognitive decline and disease progression.

Aspirin Use and Risk of Alzheimer's Disease: A 2-Sample Mendelian Randomization Study. - Ding, Pingjian; Gorenflo, Maria P; Zhu, Xiaofeng; Xu, Rong (J Alzheimers Dis, 2023)
BACKGROUND: Observational studies have shown inconsistent findings of the relationships between aspirin use and the risk of Alzheimer's disease (AD). OBJECTIVE: Since residual confounding and reverse causality were challenging issues inherent in observational studies, we conducted a 2-sample Mendelian randomization analysis (MR) to investigate whether aspirin use was causally associated with the risk of AD. METHODS: We conducted 2-sample MR analyses utilizing summary genetic association statistics to estimate the potential causal relationship between aspirin use and AD. Single-nucleotide variants associated with aspirin use in a genome-wide association study (GWAS) of UK Biobank were considered as genetic proxies for aspirin use. The GWAS summary-level data of AD were derived from a meta-analysis of GWAS data from the International Genomics of Alzheimer's Project (IGAP) stage I. RESULTS: Univariable MR analysis based on these two large GWAS data sources showed that genetically proxied aspirin use was associated with a decreased risk of AD (Odds Ratio (OR): 0.87; 95%CI: 0.77-0.99). In multivariate MR analyses, the causal estimates remained significant after adjusting for chronic pain, inflammation, heart failure (OR = 0.88, 95%CI = 0.78-0.98), or stroke (OR = 0.87, 95%CI = 0.77-0.99), but was attenuated when adjusting for coronary heart disease, blood pressure, and blood lipids. CONCLUSION: Findings from this MR analysis suggest a genetic protective effect of aspirin use on AD, possibly influenced by coronary heart disease, blood pressure, and lipid levels.

Association Between Oral Bacteria and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Liu, Sixin; Dashper, Stuart G; Zhao, Rui (J Alzheimers Dis, 2023)
BACKGROUND: Pre-clinical evidence implicates oral bacteria in the pathogenesis of Alzheimer's disease (AD), while clinical studies show diverse results. OBJECTIVE: To comprehensively assess the association between oral bacteria and AD with clinical evidence. METHODS: Studies investigating the association between oral bacteria and AD were identified through a systematic search of six databases PubMed, Embase, Cochrane Central Library, Scopus, ScienceDirect, and Web of Science. Methodological quality ratings of the included studies were performed. A best evidence synthesis was employed to integrate the results. When applicable, a meta-analysis was conducted using a random-effect model. RESULTS: Of the 16 studies included, ten investigated periodontal pathobionts and six were microbiome-wide association studies. Samples from the brain, serum, and oral cavity were tested. We found over a ten-fold and six-fold increased risk of AD when there were oral bacteria (OR = 10.68 95% CI: 4.48-25.43; p < 0.00001, I2 = 0%) and Porphyromonas gingivalis (OR = 6.84 95% CI: 2.70-17.31; p < 0.0001, I2 = 0%) respectively in the brain. While AD patients exhibited lower alpha diversity of oral microbiota than healthy controls, the findings of bacterial communities were inconsistent among studies. The best evidence synthesis suggested a moderate level of evidence for an overall association between oral bacteria and AD and for oral bacteria being a risk factor for AD. CONCLUSION: Current evidence moderately supports the association between oral bacteria and AD, while the association was strong when oral bacteria were detectable in the brain. Further evidence is needed to clarify the interrelationship between both individual species and bacterial communities and the development of AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Microbiota; Porphyromonas gingivalis; Risk Factors

Associations Between Ambient Air Pollution and Cognitive Abilities from Midlife to Early Old Age: Modification by APOE Genotype. - Franz, Carol E; Gustavson, Daniel E; Elman, Jeremy A; Fennema-Notestine, Christine; Hagler, Donald J; Baraff, Aaron; Tu, Xin M; Wu, Tsung-Chin; De Anda, Jaden; Beck, Asad; Kaufman, Joel D; Whitsel, Nathan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) measures of ambient air pollution are associated with accelerated age-related cognitive impairment, and Alzheimer's disease and related dementias (ADRD). OBJECTIVE: We examined associations between air pollution, four cognitive factors, and the moderating role of apolipoprotein E (APOE) genotype in the understudied period of midlife. METHODS: Participants were ∼1,100 men in the Vietnam Era Twin Study of Aging. Baseline cognitive assessments were from 2003 to 2007. Measures included past (1993-1999) and recent (3 years prior to baseline assessment) PM2.5 and NO2 exposure, in-person assessment of episodic memory, executive function, verbal fluency, and processing speed, and APOE genotype. Average baseline age was 56 years with a 12-year follow-up. Analyses adjusted for health and lifestyle covariates. RESULTS: Performance in all cognitive domains declined from age 56 to 68. Higher PM2.5 exposures were associated with worse general verbal fluency. We found significant exposure-by-APOE genotype interactions for specific cognitive domains: PM2.5 with executive function and NO2 with episodic memory. Higher PM2.5 exposure was related to worse executive function in APOE ɛ4 carriers, but not in non-carriers. There were no associations with processing speed. CONCLUSION: These results indicate negative effects of ambient air pollution exposure on fluency alongside intriguing differential modifications of cognitive performance by APOE genotype. APOE ɛ4 carriers appeared more sensitive to environmental differences. The process by which air pollution and its interaction with genetic risk for ADRD affects risk for later life cognitive decline or progression to dementia may begin in midlife.

Associations Between Local Area Deprivation and Physical Activity Participation in People with Cognitive Impairment in the North East of England. - Mc Ardle, Ríona; Hamilton, Calum; Del Din, Silvia; Kingston, Andrew; Robinson, Louise; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2023)
BACKGROUND: Promoting physical activity, such as habitual walking behaviors, in people with cognitive impairment may support their ability to remain independent with a good quality of life for longer. However, people with cognitive impairment participate in less physical activity compared to cognitively unimpaired older adults. The local area in which people live may significantly impact abilities to participate in physical activity. For example, people who live in more deprived areas may have less safe and walkable routes. OBJECTIVE: To examine this further, this study aimed to explore associations between local area deprivation and physical activity in people with cognitive impairment and cognitively unimpaired older adults (controls). METHODS: 87 participants with cognitive impairment (mild cognitive impairment or dementia) and 27 older adult controls from the North East of England were included in this analysis. Participants wore a tri-axial wearable accelerometer (AX3, Axivity) on their lower backs continuously for seven days. The primary physical activity outcome was daily step count. Individuals' neighborhoods were linked to UK government area deprivation statistics. Hierarchical Bayesian models assessed the association between local area deprivation and daily step count in people with cognitive impairment and controls. RESULTS: Key findings indicated that there was no association between local area deprivation and daily step count in people with cognitive impairment, but higher deprivation was associated with lower daily steps for controls. CONCLUSION: These findings suggest that cognitive impairment may be associated with lower participation in physical activity which supersedes the influence of local area deprivation observed in normal aging.

Cardiorespiratory Fitness Attenuates the Deleterious Effects of Sleep Apnea on Cerebral Structure and Perfusion in the Wisconsin Sleep Cohort Study. - Edmunds, Kyle J; Driscoll, Ira; Hagen, Erika W; Barnet, Jodi H; Ravelo, Laurel A; Plante, David T; Gaitán, Julian M; Lose, Sarah R; Motovylyak, Alice; Bendlin, Barbara B; Okonkwo, Ozioma C; Peppard, Paul E (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence suggests that age-related changes in cerebral health may be sensitive to vascular risk modifiers, such as physical activity and sleep. OBJECTIVE: We examine whether cardiorespiratory fitness modifies the association of obstructive sleep apnea (OSA) severity with MRI-assessed measures of cerebral structure and perfusion. METHODS: Using data from a cross-sectional sample of participants (n = 129, 51% female, age range 49.6-85.3 years) in the Wisconsin Sleep Cohort study, we estimated linear models of MRI-assessed total and regional gray matter (GM) and white matter (WM) volumes, WM hyperintensity (WMH:ICV ratio), total lesion volume, and arterial spin labeling (ASL) cerebral blood flow (CBF), using an estimated measure of cardiorespiratory fitness (CRF) and OSA severity as predictors. Participants' sleep was assessed using overnight in-laboratory polysomnography, and OSA severity was measured using the apnea-hypopnea index (AHI), or the mean number of recorded apnea and hypopnea events per hour of sleep. The mean±SD time difference between PSG data collection and MRI data collection was 1.7±1.5 years (range: [0, 4.9 years]). RESULTS: OSA severity was associated with reduced total GM volume (β=-0.064; SE = 0.023; p = 0.007), greater total WM lesion volume (interaction p = 0.023), and greater WMHs (interaction p = 0.017) in less-fit subjects. Perfusion models revealed significant differences in the association of AHI and regional CBF between fitness groups (interaction ps <  0.05). CONCLUSION: This work provides new evidence for the protective role of cardiorespiratory fitness against the deleterious effects of OSA on brain aging in late-middle age to older adults.

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Deep Reinforcement Learning-Based Retinal Imaging in Alzheimer's Disease: Potential and Perspectives. - Hui, Herbert Y H; Ran, An Ran; Dai, Jia Jia; Cheung, Carol Y (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) remains a global health challenge in the 21st century due to its increasing prevalence as the major cause of dementia. State-of-the-art artificial intelligence (AI)-based tests could potentially improve population-based strategies to detect and manage AD. Current retinal imaging demonstrates immense potential as a non-invasive screening measure for AD, by studying qualitative and quantitative changes in the neuronal and vascular structures of the retina that are often associated with degenerative changes in the brain. On the other hand, the tremendous success of AI, especially deep learning, in recent years has encouraged its incorporation with retinal imaging for predicting systemic diseases. Further development in deep reinforcement learning (DRL), defined as a subfield of machine learning that combines deep learning and reinforcement learning, also prompts the question of how it can work hand in hand with retinal imaging as a viable tool for automated prediction of AD. This review aims to discuss potential applications of DRL in using retinal imaging to study AD, and their synergistic application to unlock other possibilities, such as AD detection and prediction of AD progression. Challenges and future directions, such as the use of inverse DRL in defining reward function, lack of standardization in retinal imaging, and data availability, will also be addressed to bridge gaps for its transition into clinical use.
Keywords: Alzheimer Disease; Artificial Intelligence; Humans; Machine Learning; Magnetic Resonance Imaging; Retina

Detecting Anosognosia from the Prodromal Stage of Alzheimer's Disease. - Guieysse, Thomas; Lamothe, Roxane; Houot, Marion; Razafimahatratra, Solofo; Medani, Takfarinas; Lejeune, François-Xavier; Dreyfus, Gérard; Klarsfeld, André; Pantazis, Dimitrios; Koechlin, Etienne; Andrade, Katia (J Alzheimers Dis, 2023)
BACKGROUND: Though not originally developed for this purpose, the Healthy Aging Brain Care Monitor (HABC-M) seems a valuable instrument for assessing anosognosia in Alzheimer's disease (AD). OBJECTIVES: Our study aimed at 1) investigating the validity of the HABC-M (31 items), and its cognitive, psychological, and functional subscales, in discriminating AD patients from controls; 2) exploring whether the HABC-M discrepancy scores between the self-reports of patients/controls in these different domains and the respective ratings provided by their caregivers/informants correlate with an online measure of self-awareness; 3) determining whether the caregiver burden level, also derived from the HABC-M, could add additional support for detecting anosognosia. METHODS: The HABC-M was administered to 30 AD patients and 30 healthy controls, and to their caregivers/informants. A measure of online awareness was established from subjects' estimation of their performances in a computerized experiment. RESULTS: The HABC-M discrepancy scores distinguished AD patients from controls. The cognitive subscale discriminated the two groups from the prodromal AD stage, with an AUC of 0.88 [95% CI: 0.78;0.97]. Adding the caregiver burden level raised it to 0.94 [0.86;0.99]. Significant correlations between the HABC-M and online discrepancy scores were observed in the patients group, providing convergent validity of these methods. CONCLUSIONS: The cognitive HABC-M (six items) can detect anosognosia across the AD spectrum. The caregiver burden (four items) may corroborate the suspicion of anosognosia. The short-hybrid scale, built from these 10 items instead of the usual 31, showed the highest sensitivity for detecting anosognosia from the prodromal AD stage, which may further help with timely diagnosis.
Keywords: Agnosia; Alzheimer Disease; Brain; Caregivers; Humans; Neuropsychological Tests; Prodromal Symptoms

Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

The Effect of Exercise on Falls in People Living with Dementia: A Systematic Review. - Jehu, Deborah A; Davis, Jennifer C; Gill, Jessica; Oke, Olabamibo; Liu-Ambrose, Teresa (J Alzheimers Dis, 2023)
BACKGROUND: People living with dementia (PWD) are at a heightened risk for falls. However, the effects of exercise on falls in PWD are unclear. OBJECTIVE: To conduct a systematic review of randomized controlled trials (RCTs) examining the efficacy of exercise to reduce falls, recurrent falls, and injurious falls relative to usual care among PWD. METHODS: We included peer-reviewed RCTs evaluating any exercise mode on falls and related injuries among medically diagnosed PWD aged ≥55years (international prospective register of systematic reviews (PROSPERO) ID:CRD42021254637). We excluded studies that did not solely involve PWD and were not the primary publication examining falls. We searched the Cochrane Dementia and Cognitive Improvement Group's Specialized Register and grey literature on 08/19/2020 and 04/11/2022; topical categories included dementia, exercise, RCTs, and falls. We evaluated the risk of bias (ROB) using the Cochrane ROB Tool-2 and study quality using the Consolidated Standards of Reporting Trials. RESULTS: Twelve studies were included (n = 1,827; age = 81.3±7.0 years; female = 59.3%; Mini-Mental State Examination = 20.1±4.3 points; intervention duration = 27.8±18.5 weeks; adherence = 75.5±16.2%; attrition = 21.0±12.4%). Exercise reduced falls in two studies [Incidence Rate Ratio (IRR) range = 0.16 to 0.66; fall rate range: intervention = 1.35-3.76 falls/year, control = 3.07-12.21 falls/year]; all other studies (n = 10) reported null findings. Exercise did not reduce recurrent falls (n = 0/2) or injurious falls (n = 0/5). The RoB assessment ranged from some concerns (n = 9) to high RoB (n = 3); no studies were powered for falls. The quality of reporting was good (78.8±11.4%). CONCLUSION: There was insufficient evidence to suggest that exercise reduces falls, recurrent falls, or injurious falls among PWD. Well-designed studies powered for falls are needed.
Keywords: Dementia; Exercise; Female; Humans; Independent Living

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Effects of Striatal Amyloidosis on the Dopaminergic System and Behavior: A Comparative Study in Male and Female 5XFAD Mice. - Lansdell, Theresa A; Xu, Hui; Galligan, James J; Dorrance, Anne M (J Alzheimers Dis, 2023)
BACKGROUND: Nearly two-thirds of patients diagnosed with Alzheimer's disease (AD) are female. In addition, female patients with AD have more significant cognitive impairment than males at the same disease stage. This disparity suggests there are sex differences in AD progression. While females appear to be more affected by AD, most published behavioral studies utilize male mice. In humans, there is an association between antecedent attention-deficit/hyperactivity disorder and increased risk of dementia. Functional connectivity studies indicate that dysfunctional cortico-striatal networks contribute to hyperactivity in attention deficit hyperactivity disorder. Higher plaque density in the striatum accurately predicts the presence of clinical AD pathology. In addition, there is a link between AD-related memory dysfunction and dysfunctional dopamine signaling. OBJECTIVE: With the need to consider sex as a biological variable, we investigated the influence of sex on striatal plaque burden, dopaminergic signaling, and behavior in prodromal 5XFAD mice. METHODS: Six-month-old male and female 5XFAD and C57BL/6J mice were evaluated for striatal amyloid plaque burden, locomotive behavior, and changes in dopaminergic machinery in the striatum. RESULTS: 5XFAD female mice had a higher striatal amyloid plaque burden than male 5XFAD mice. 5XFAD females, but not males, were hyperactive. Hyperactivity in female 5XFAD mice was associated with increased striatal plaque burden and changes in dopamine signaling in the dorsal striatum. CONCLUSION: Our results indicate that the progression of amyloidosis involves the striatum in females to a greater extent than in males. These studies have significant implications for using male-only cohorts in the study of AD progression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Animals; Disease Models, Animal; Dopamine; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid

Efficacy of Souvenaid® Combined with Acetylcholinesterase Inhibitors in the Treatment of Mild Alzheimer's Disease. - García-Alberca, José María; Gris, Esther; de la Guía, Paz; Mendoza, Silvia; de la Rica, María López (J Alzheimers Dis, 2023)
BACKGROUND: Souvenaid® is a medical food that contains nutrients that can help synapse synthesis in Alzheimer's disease (AD). The potential effectiveness of combination therapy of Souvenaid with cholinesterase inhibitors (AChEI) is currently not well-known. OBJECTIVE: To look into the effect of combination therapy with Souvenaid plus AChEI in people with mild AD in the real-world. METHODS: We carried out a retrospective analysis in mild AD patients attending a memory clinic. Three groups were studied according to the treatment they received: Souvenaid alone (n = 66), AChEI alone (n = 84), and Souvenaid+AChEI (n = 70). Treatment effects were evaluated at baseline, 6 and 12 months. Cognitive functioning was assessed by Mini-Mental State Examination (MMSE), Rey Auditory Verbal Learning Test (RAVLT), Symbol Digit Modalities Test (SDMT), Boston Naming Test (BNT), Trail Making Test (TMT/A-B), Phonemic and Semantic Verbal Fluency Test (PVFT/SVFT); neuropsychiatric symptoms were evaluated by the Neuropsychiatric Inventory (NPI); functional capacity was assessed by the Bayer Activities Daily Living Scale (BAYER-S). A Mixed Model for Repeated Measures analysis was carried out to evaluate changes in outcome scores. RESULTS: After 12 months Souvenaid+AChEI showed significant improvement in MMSE (p < 0.001), RAVLT (p < 0.0001), SVFT (p = 0.002), PVFT (p = 0.007), TMTA (p = 0.039), TMTB (p = 0.001), and NPI (p < 0.0001) compared to AChEI alone. CONCLUSION: Souvenaid showed cognitive and behavioral benefits in mild AD patients. These effects increased when Souvenaid and AChEI were used in combination. This study can serve as a model for the design of prospective controlled trials that help to support the combined use of Souvenaid and antidementia drugs in AD.

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Exploring Reasons for Differential Vulnerability and Alzheimer's Disease Risk in Racial and Ethnic Minorities. - Daniel, E Valerie; Kleiman, Michael J; Galvin, James E (J Alzheimers Dis, 2023)
BACKGROUND: African American and Hispanic older adults are reported to have up to a 2-fold higher risk of Alzheimer's disease and related disorders (ADRD), but the reasons for this increased vulnerability have not been fully explored. The Vulnerability Index (VI) was designed to identify individuals who are at risk of developing cognitive impairment in the future, capturing 12 sociodemographic variables and modifiable medical comorbidities associated with higher ADRD risk. However, a prior limitation of the VI was that the original study cohort had limited diversity. We examined the association of the VI within and between non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment and different socioeconomic strata enrolled in a community-based dementia screening study. OBJECTIVE: To explore reasons for reported higher ADRD vulnerability in African Americans and Hispanics. METHODS: In a cross-sectional study of 300 non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment, we studied the association between cognitive status, the VI, and socioeconomic status (SES). RESULTS: When considering race/ethnicity, the presence of more vascular comorbidities drove greater vulnerability. When considering SES, vascular comorbidities played a less prominent role suggesting resources and access to care drives risk. The VI had differential effects on cognitive performance with the greatest effect in the earlier stages of impairment. CONCLUSION: Findings from this study provide a deeper understanding of the differential risk of ADRD in multicultural older adults captured by the VI and how barriers to healthcare access may increase vulnerability in racial/ethnic minorities.
Keywords: Aged; Alzheimer Disease; Cross-Sectional Studies; Ethnic and Racial Minorities; Ethnicity; Humans; White People

From Association to Intervention: The Alzheimer's Disease-Associated Processes and Targets (ADAPT) Ontology. - Daly, Timothy; Henry, Vincent; Bourdenx, Mathieu (J Alzheimers Dis, 2023)
BACKGROUND: Many putative causes and risk factors have been associated with outcomes in Alzheimer's disease (AD) but all attempts at disease-modifying treatment have failed to be clinically significant. Efforts to address this "association-intervention" mismatch have tended to focus on the novel design of interventions. OBJECTIVE: Here, we instead deal with the notion of association in depth. We introduce the concept of disease-associated process (DAP) as a flexible concept that can unite different areas of study of AD from genetics to epidemiology to identify disease-modifying targets. METHODS: We sort DAPs using three properties: specificity for AD, frequency in patients, and pathogenic intensity for dementia before using a literature review to apply these properties in three ways. Firstly, we describe and visualize known DAPs. Secondly, we exemplify qualitative specificity analysis with the DAPs of tau protein pathology and autophagy to reveal their differential implication in AD. Finally, we use DAP properties to define the terms "risk factor," "cause," and "biomarker." RESULTS: We show how DAPs fit into our collaborative disease ontology, the Alzheimer's Disease-Associated Processes and Targets (ADAPT) ontology. We argue that our theoretical system can serve as a democratic research forum, offering a more biologically adequate view of dementia than reductionist models. CONCLUSION: The ADAPT ontology is a tool that could help to ground debates around priority setting using objective criteria for the identifying of targets in AD. Further efforts are needed to address issues of how biomedical research into AD is prioritized and funded.
Keywords: Alzheimer Disease; Biomarkers; Biomedical Research; Humans

Hypermethylation at CREBBP Is Associated with Cognitive Impairment in a Mexican American Cohort. - Abraham Daniel, Ann; Silzer, Talisa; Sun, Jie; Zhou, Zhengyang; Hall, Courtney; Phillips, Nicole; Barber, Robert (J Alzheimers Dis, 2023)
BACKGROUND: The aging Mexican American (MA) population is the fastest growing ethnic minority group in the US. MAs have a unique metabolic-related risk for Alzheimer's disease (AD) and mild cognitive impairment (MCI), compared to non-Hispanic whites (NHW). This risk for cognitive impairment (CI) is multifactorial involving genetics, environmental, and lifestyle factors. Changes in environment and lifestyle can alter patterns and even possibly reverse derangement of DNA methylation (a form of epigenetic regulation). OBJECTIVE: We sought to identify ethnicity-specific DNA methylation profiles that may be associated with CI in MAs and NHWs. METHODS: DNA obtained from peripheral blood of 551 participants from the Texas Alzheimer's Research and Care Consortium was typed on the Illumina Infinium® MethylationEPIC chip array, which assesses over 850K CpG genomic sites. Within each ethnic group (N = 299 MAs, N = 252 NHWs), participants were stratified by cognitive status (control versus CI). Beta values, representing relative degree of methylation, were normalized using the Beta MIxture Quantile dilation method and assessed for differential methylation using the Chip Analysis Methylation Pipeline (ChAMP), limma and cate packages in R. RESULTS: Two differentially methylated sites were significant: cg13135255 (MAs) and cg27002303 (NHWs) based on an FDR p < 0.05. Three suggestive sites obtained were cg01887506 (MAs) and cg10607142 and cg13529380 (NHWs). Most methylation sites were hypermethylated in CI compared to controls, except cg13529380 which was hypomethylated. CONCLUSION: The strongest association with CI was at cg13135255 (FDR-adjusted p = 0.029 in MAs), within the CREBBP gene. Moving forward, identifying additional ethnicity-specific methylation sites may be useful to discern CI risk in MAs.

Impact of Computerized Cognitive Training on Default Mode Network Connectivity in Subjects at Risk for Alzheimer's Disease: A 78-week Randomized Controlled Trial. - Petrella, Jeffrey R; Michael, Andrew M; Qian, Min; Nwosu, Adaora; Sneed, Joel; Goldberg, Terry E; Devanand, Davangere P; Doraiswamy, P Murali (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) represents a high risk group for Alzheimer's disease (AD). Computerized Cognitive Games Training (CCT) is an investigational strategy to improve targeted functions in MCI through the modulation of cognitive networks. OBJECTIVE: The goal of this study was to examine the effect of CCT versus a non-targeted active brain exercise on functional cognitive networks. METHODS: 107 patients with MCI were randomized to CCT or web-based crossword puzzles. Resting-state functional MRI (fMRI) was obtained at baseline and 18 months to evaluate differences in fMRI measured within- and between-network functional connectivity (FC) of the default mode network (DMN) and other large-scale brain networks: the executive control, salience, and sensorimotor networks. RESULTS: There were no differences between crosswords and games in the primary outcome, within-network DMN FC across all subjects. However, secondary analyses suggest differential effects on between-network connectivity involving the DMN and SLN, and within-network connectivity of the DMN in subjects with late MCI. Paradoxically, in both cases, there was a decrease in FC for games and an increase for the crosswords control (p < 0.05), accompanied by lesser cognitive decline in the crosswords group. CONCLUSION: Results do not support a differential impact on within-network DMN FC between games and crossword puzzle interventions. However, crossword puzzles might result in cognitively beneficial remodeling between the DMN and other networks in more severely impaired MCI subjects, parallel to the observed clinical benefits.
Keywords: Alzheimer Disease; Brain; Cognitive Dysfunction; Cognitive Training; Default Mode Network; Humans; Magnetic Resonance Imaging; Nerve Net

JAD: A Forum for Philosophy in Science. - Daly, Timothy (J Alzheimers Dis, 2023)
The Journal of Alzheimer's Disease (JAD) is already an established forum for cutting-edge science as well as ethical reflection. But I argue that beyond science and ethics, JAD is also a forum for philosophy in science, and that interdisciplinary researchers asking innovative questions about AD should publish their reflections and findings in JAD.
Keywords: Alzheimer Disease; Humans; Philosophy

Malignant Brain Aging: The Formidable Link Between Dysregulated Signaling Through Mechanistic Target of Rapamycin Pathways and Alzheimer's Disease (Type 3 Diabetes). - de la Monte, Suzanne M (J Alzheimers Dis, 2023)
Malignant brain aging corresponds to accelerated age-related declines in brain functions eventually derailing the self-sustaining forces that govern independent vitality. Malignant brain aging establishes the path toward dementing neurodegeneration, including Alzheimer's disease (AD). The full spectrum of AD includes progressive dysfunction of neurons, oligodendrocytes, astrocytes, microglia, and the microvascular systems, and is mechanistically driven by insulin and insulin-like growth factor (IGF) deficiencies and resistances with accompanying deficits in energy balance, increased cellular stress, inflammation, and impaired perfusion, mimicking the core features of diabetes mellitus. The underlying pathophysiological derangements result in mitochondrial dysfunction, abnormal protein aggregation, increased oxidative and endoplasmic reticulum stress, aberrant autophagy, and abnormal post-translational modification of proteins, all of which are signature features of both AD and dysregulated insulin/IGF-1-mechanistic target of rapamycin (mTOR) signaling. This article connects the dots from benign to malignant aging to neurodegeneration by reviewing the salient pathologies associated with initially adaptive and later dysfunctional mTOR signaling in the brain. Effective therapeutic and preventive measures must be two-pronged and designed to 1) address complex and shifting impairments in mTOR signaling through the re-purpose of effective anti-diabetes therapeutics that target the brain, and 2) minimize the impact of extrinsic mediators of benign to malignant aging transitions, e.g., inflammatory states, obesity, systemic insulin resistance diseases, and repeated bouts of general anesthesia, by minimizing exposures or implementing neuroprotective measures.
Keywords: Alzheimer Disease; Brain; Diabetes Mellitus; Humans; Insulin; Sirolimus; TOR Serine-Threonine Kinases

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Mediation of Reduced Hippocampal Volume by Cerebral Amyloid Angiopathy in Pathologically Confirmed Patients with Alzheimer's Disease. - Nagaraja, Nandakumar; Wang, Wei-En; Duara, Ranjan; DeKosky, Steven T; Vaillancourt, David (J Alzheimers Dis, 2023)
BACKGROUND: Hippocampal atrophy in cerebral amyloid angiopathy (CAA) has been reported to be similar to that in Alzheimer's disease (AD). OBJECTIVE: To evaluate if CAA pathology partly mediates reduced hippocampal volume in patients with AD. METHODS: Patients with a clinical diagnosis of AD and neuropathological confirmation of AD+/-CAA in the National Alzheimer's Coordinating Center database were included in the study. The volumes of temporal lobe structures were calculated on T1-weighted imaging (T1-MRI) using automated FreeSurfer software, from images acquired on average 5 years prior to death. Multivariate regression analysis was performed to compare brain volumes in four CAA groups. The hippocampal volume on T1-MRI was correlated with Clinical Dementia Rating sum of boxes (CDRsb) score, apolipoprotein E (APOE) genotype, and hippocampal atrophy at autopsy. RESULTS: The study included 231 patients with no (n = 45), mild (n = 70), moderate (n = 67), and severe (n = 49) CAA. Among the four CAA groups, patients with severe CAA had a smaller mean left hippocampal volume (p = 0.023) but this was not significant when adjusted for APOE ɛ4 (p = 0.07). The left hippocampal volume on MRI correlated significantly with the hippocampal atrophy grading on neuropathology (p = 0.0003). Among patients with severe CAA, the left hippocampal volume on T1-MRI: (a) decreased with an increase in the number of APOE ɛ4 alleles (p = 0.04); but (b) had no evidence of correlation with CDRsb score (p = 0.57). CONCLUSION: Severe CAA was associated with smaller left hippocampal volume on T1-MRI up to five years prior to death among patients with neuropathologically confirmed AD. This relationship was dependent on APOE ɛ4 genotype.

Midlife Neuropsychological Profiles and Associated Vascular Risk: The Bogalusa Heart Study. - De Anda-Duran, Ileana; Kolachalama, Vijaya B; Carmichael, Owen T; Hwang, Phillip H; Fernandez, Camilo; Au, Rhoda; Bazzano, Lydia A; Libon, David J (J Alzheimers Dis, 2023)
BACKGROUND: Individuals with Alzheimer's disease (AD) often present with coexisting vascular pathology that is expressed to different degrees and can lead to clinical heterogeneity. OBJECTIVE: To examine the utility of unsupervised statistical clustering approaches in identifying neuropsychological (NP) test performance subtypes that closely correlate with carotid intima-media thickness (cIMT) in midlife. METHODS: A hierarchical agglomerative and k-means clustering analysis based on NP scores (standardized for age, sex, and race) was conducted among 1,203 participants (age 48±5.3 years) from the Bogalusa Heart Study. Regression models assessed the association between cIMT ≥50th percentile and NP profiles, and global cognitive score (GCS) tertiles for sensitivity analysis. RESULTS: Three NP profiles were identified: Mixed-low performance [16%, n = 192], scores ≥1 SD below the mean on immediate, delayed free recall, recognition verbal memory, and information processing; Average [59%, n = 704]; and Optimal [26%, n = 307] NP performance. Participants with greater cIMT were more likely to have a Mixed-low profile [OR = 3.10, 95% CI (2.13, 4.53), p < 0.001] compared to Optimal. After adjusting for education and cardiovascular (CV) risks, results remained. The association with GCS tertiles was more attenuated [lowest (34%, n = 407) versus highest (33%, n = 403) tertile: adjusted OR = 1.66, 95% CI (1.07, 2.60), p = 0.024]. CONCLUSION: As early as midlife, individuals with higher subclinical atherosclerosis were more likely to be in the Mixed-low profile, underscoring the potential malignancy of CV risk as related to NP test performance, suggesting that classification approaches may aid in identifying those at risk for AD/vascular dementia spectrum illness.

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mindfulness Prevents Depression and Psychopathology in Elderly People with Mild to Moderate Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Rojas-Hernández, Jaime; Santana-Del Pino, Angelo; Céspedes Suárez, Carmen; Pellejero Silva, Mónica; Miró-Barrachina, María Teresa; Ibáñez Fernández, Ignacio; Estupiñán López, José Antonio; Borkel, Lucas F (J Alzheimers Dis, 2023)
BACKGROUND: This longitudinal study addressed whether mindfulness practice prevents psychological and behavioral symptoms, especially mood disorders, in Alzheimer's disease (AD). OBJECTIVE: To assess the incidence of depression in the course of AD and to determine which non-pharmacological treatment (NPT) is most effective in preventing psychopathological symptoms. METHODS: We conducted a longitudinal, non-inferiority and equivalence randomized clinical trial, repeated-measures design, with a control group and three experimental treatments: mindfulness, cognitive stimulation, and relaxation. Each experimental group performed three weekly sessions for two years. The pharmacological treatment of all participants was donepezil (10 mg). Participants were patients with probable AD without diagnosed depression from the public neurology services of the Canary Health Service, Spain. Psychological evaluation was performed using the Geriatric Depression Scale (GDS), Hamilton Depression Rating Scale (HDRS), and Neuropsychiatric Inventory (NPI-Q). The statistical analysis included only patients who attended at least 75% of the sessions. A nonparametric, repeated-measures analysis was performed with Kruskal-Wallis H test and between-group differences with Mann-Whitney U test with Bonferroni correction (p < 0.008). Effect size was calculated with partial eta-squared. RESULTS: The results showed significant differences with large effect sizes (η2p>0.14) between mindfulness and the rest of the experimental groups as well as the control in the GDS, HDRS, and NPI-Q scales. CONCLUSION: Compared to the other experimental groups, only mindfulness prevented the onset of depression and other psychopathologies in early-stage AD. Based on its effectiveness in maintaining cognitive functions and preventing psychopathology, we recommend mindfulness as the first-choice NPT for mild to moderate AD.
Keywords: Aged; Alzheimer Disease; Depression; Donepezil; Humans; Longitudinal Studies; Mindfulness

Montreal Cognitive Assessment in Mild Cognitive Impairment: Relationship with Cerebrospinal Fluid Biomarkers and Conversion to Dementia. - Bernardes, Catarina; Lima, Marisa; Duro, Diana; Silva-Spínola, Anuschka; Durães, João; Tábuas-Pereira, Miguel; Baldeiras, Ines; Freitas, Sandra; Santana, Isabel (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) is considered a prodromal state of dementia. Abnormal values of cerebrospinal fluid Alzheimer's disease biomarkers (CSF-AD-b) have been associated with a higher risk of conversion to dementia (due to Alzheimer's disease), but studies evaluating the ability of Montreal Cognitive Assessment (MoCA) in this task are lacking. OBJECTIVE: This study aims to investigate the relationship between MoCA and CSF-AD-b, as well as the ability of those tools to predict conversion to dementia. METHODS: Taking advantage of our MCI cohort with biological characterization on longitudinal follow-up (180 patients followed for 62.6 months during which 41.3% converted), we computed MoCA and MMSE z-scores, using Portuguese normative data. The performance in MoCA z-score was correlated with CSF-AD-b and the relative time to conversion and risk according to baseline characteristics were analyzed using Kaplan-Meier analysis and Cox regression models. RESULTS: MoCA z-scores were correlated with Aβ42 (p = 0.026), t-tau (p = 0.033), and p-tau (p = 0.01). Impaired MMSE (p < 0.001) and MoCA z-scores (p = 0.019), decreased Aβ42 (p < 0.001) and increased t-tau (p < 0.001) and p-tau (p < 0.001) were associated with shorter estimated time of conversion. Aβ42 (p < 0.001) and MMSE z-scores (p = 0.029) were independent predictors of conversion. For those with at least 9 years of education, MoCA z-score (p = 0.004) (but not MMSE) was an independent predictor of conversion as well as Aβ42. CONCLUSIONS: This study confirms the role of CSF-AD-b, namely Aβ42, in predicting conversion from MCI to dementia and suggests the utility of MoCA in predicting conversion in highly educated subjects, supporting its use in the evaluation of MCI patients.

Moral Emotions and Their Brain Structural Correlates Across Neurodegenerative Disorders. - Baez, Sandra; Trujillo-Llano, Catalina; de Souza, Leonardo Cruz; Lillo, Patricia; Forno, Gonzalo; Santamaría-García, Hernando; Okuma, Cecilia; Alegria, Patricio; Huepe, David; Ibáñez, Agustín; Decety, Jean; Slachevsky, Andrea (J Alzheimers Dis, 2023)
BACKGROUND: Although social cognition is compromised in patients with neurodegenerative disorders such as behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), research on moral emotions and their neural correlates in these populations is scarce. No previous study has explored the utility of moral emotions, compared to and in combination with classical general cognitive state tools, to discriminate bvFTD from AD patients. OBJECTIVE: To examine self-conscious (guilt and embarrassment) and other-oriented (pity and indignation) moral emotions, their subjective experience, and their structural brain underpinnings in bvFTD (n = 31) and AD (n = 30) patients, compared to healthy controls (n = 37). We also explored the potential utility of moral emotions measures to discriminate bvFTD from AD. METHODS: We used a modified version of the Moral Sentiment Task measuring the participants' accuracy scores and their emotional subjective experiences. RESULTS: bvFTD patients exhibited greater impairments in self-conscious and other-oriented moral emotions as compared with AD patients and healthy controls. Moral emotions combined with general cognitive state tools emerged as useful measures to discriminate bvFTD from AD patients. In bvFTD patients, lower moral emotions scores were associated with lower gray matter volumes in caudate nucleus and inferior and middle temporal gyri. In AD, these scores were associated with lower gray matter volumes in superior and middle frontal gyri, middle temporal gyrus, inferior parietal lobule and supramarginal gyrus. CONCLUSION: These findings contribute to a better understanding of moral emotion deficits across neurodegenerative disorders, highlighting the potential benefits of integrating this domain into the clinical assessment.
Keywords: Alzheimer Disease; Brain; Emotions; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Morals; Neuropsychological Tests

MRI Visible Perivascular Spaces and the Risk of Incident Mild Cognitive Impairment in a Community Sample. - Pase, Matthew P; Pinheiro, Adlin; Rowsthorn, Ella; Demissie, Serkalem; Hurmez, Saoresho; Aparicio, Hugo; Rodriguez-Lara, Frances; Gonzales, Mitzi M; Beiser, Alexa; DeCarli, Charles; Seshadri, Sudha; Romero, Jose Rafael (J Alzheimers Dis, 2023)
BACKGROUND: Magnetic resonance imaging (MRI) visible perivascular spaces (PVS) are associated with the risk of incident dementia but their association with the early stages of cognitive impairment remains equivocal. OBJECTIVE: We examined the association between MRI visible PVS and the risk of incident mild cognitive impairment (MCI) in the community-based Framingham Heart Study (FHS). METHODS: FHS participants aged at least 50 years free of stroke, cognitive impairment, and dementia at the time of MRI were included. PVS were rated according to severity in the basal ganglia and centrum semiovale (CSO) using established criteria. Cox regression analyses were used to relate PVS to incident MCI adjusted for demographic and cardiovascular variables. RESULTS: The mean age of the sample (1,314 participants) at MRI was 68 years (SD, 9; 54% women). There were 263 cases of incident MCI over a median 7.4 years follow-up (max, 19.8 years). MCI risk increased with higher PVS severity in the CSO. Relative to persons with the lowest severity rating, persons with the highest severity rating in the CSO had a higher risk of incident MCI (hazard ratio [HR] = 2.55; 95% confidence interval [CI], 1.48-4.37; p = 0.0007). In secondary analysis, this association seemed stronger in women. Risk of incident MCI was nominally higher for participants with the highest severity grade of PVS in the basal ganglia, though not statistically significant relative to the lowest grade (HR = 2.19; 95% CI, 0.78-6.14; p = 0.14). CONCLUSIONS: PVS burden in the CSO may be a risk marker for early cognitive impairment.

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Noninvasive Gamma Sensory Stimulation May Reduce White Matter and Myelin Loss in Alzheimer's Disease. - Da, Xiao; Hempel, Evan; Ou, Yangming; Rowe, Olivia Elizabeth; Malchano, Zach; Hajós, Mihály; Kern, Ralph; Megerian, Jonathan Thomas; Cimenser, Aylin (J Alzheimers Dis, 2023)
BACKGROUND: Patients with Alzheimer's disease (AD) demonstrate progressive white matter atrophy and myelin loss. Restoring myelin content or preventing demyelination has been suggested as a therapeutic approach for AD. OBJECTIVE: Herein, we investigate the effects of non-invasive, combined visual and auditory gamma-sensory stimulation on white matter atrophy and myelin content loss in patients with AD. METHODS: In this study, we used the magnetic resonance imaging (MRI) data from the OVERTURE study (NCT03556280), a randomized, controlled, clinical trial in which active treatment participants received daily, non-invasive, combined visual and auditory, 40 Hz stimulation for six months. A subset of OVERTURE participants who meet the inclusion criteria for detailed white matter (N = 38) and myelin content (N = 36) assessments are included in the analysis. White matter volume assessments were performed using T1-weighted MRI, and myelin content assessments were performed using T1-weighted/T2-weighted MRI. Treatment effects on white matter atrophy and myelin content loss were assessed. RESULTS: Combined visual and auditory gamma-sensory stimulation treatment is associated with reduced total and regional white matter atrophy and myelin content loss in active treatment participants compared to sham treatment participants. Across white matter structures evaluated, the most significant changes were observed in the entorhinal region. CONCLUSIONS: The study results suggest that combined visual and auditory gamma-sensory stimulation may modulate neuronal network function in AD in part by reducing white matter atrophy and myelin content loss. Furthermore, the entorhinal region MRI outcomes may have significant implications for early disease intervention, considering the crucial afferent connections to the hippocampus and entorhinal cortex.

Pathogenesis, Animal Models, and Drug Discovery of Alzheimer's Disease. - Xia, Zhao-Di; Ma, Ruo-Xin; Wen, Jin-Feng; Zhai, Yu-Fei; Wang, Yu-Qi; Wang, Feng-Yun; Liu, Dan; Zhao, Xiao-Long; Sun, Bao; Jia, Pu; Zheng, Xiao-Hui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), the most common cause of dementia, is a chronic neurodegenerative disease induced by multiple factors. The high incidence and the aging of the global population make it a growing global health concern with huge implications for individuals and society. The clinical manifestations are progressive cognitive dysfunction and lack of behavioral ability, which not only seriously affect the health and quality of life of the elderly, but also bring a heavy burden to the family and society. Unfortunately, almost all the drugs targeting the classical pathogenesis have not achieved satisfactory clinical effects in the past two decades. Therefore, the present review provides more novel ideas on the complex pathophysiological mechanisms of AD, including classical pathogenesis and a variety of possible pathogenesis that have been proposed in recent years. It will be helpful to find out the key target and the effect pathway of potential drugs and mechanisms for the prevention and treatment of AD. In addition, the common animal models in AD research are outlined and we examine their prospect for the future. Finally, Phase I, II, III, and IV randomized clinical trials or on the market of drugs for AD treatment were searched in online databases (Drug Bank Online 5.0, the U.S. National Library of Medicine, and Alzforum). Therefore, this review may also provide useful information in the research and development of new AD-based drugs.
Keywords: Alzheimer Disease; Animals; Drug Discovery; Models, Animal; Neurodegenerative Diseases; Quality of Life

Patterns of Aging Changes in Bodyweight May Predict Alzheimer's Disease. - Ukraintseva, Svetlana; Duan, Hongzhe; Holmes, Rachel; Bagley, Olivia; Wu, Deqing; Yashkin, Arseniy; Kulminski, Alexander; Akushevich, Igor; Whitson, Heather; Stallard, Eric; Yashin, Anatoliy; Arbeev, Konstantin (J Alzheimers Dis, 2023)
Relationships between patterns of aging-changes in bodyweight and AD are not fully understood. We compared mean age-trajectories of weight between those who did and did not develop late-onset-AD, and evaluated impact of age at maximum weight (AgeMax), and slope of decline in weight, on AD risk. Women with late-onset-AD had lower weight three or more decades before AD onset, and ∼10 years younger AgeMax, compared to AD-free women. APOE4 carriers had younger AgeMax and steeper slope. Older AgeMax and flatter slope predicted lower AD risk. Premature decline in weight could be a sign of accelerated physical aging contributing to AD.

Plasma Amyloid-β Homeostasis Is Associated with Body Mass Index and Weight Loss in People with Overweight and Obesity. - Brook, Emily S; D'Alonzo, Zachary J; Lam, Virginie; Chan, Dick; Dhaliwal, Satvinder Singh; Watts, Geraldb F; Mamo, John C L; Takechi, Ryusuke (J Alzheimers Dis, 2023)
BACKGROUND: Obesity is linked to a higher incidence of Alzheimer's disease (AD). Studies show that plasma amyloid-β (Aβ) dyshomeostasis, particularly low 42/40 ratio indicates a heightened risk for developing AD. However, the relationship between body mass index (BMI) and circulating plasma Aβ has not been extensively studied. OBJECTIVE: We hypothesized that people with a high BMI have altered plasma Aβ homeostasis compared with people with a lower BMI. We also tested whether reducing BMI by calorie-restriction could normalize plasma concentrations of Aβ. METHODS: Plasma concentrations of Aβ 40, Aβ 42, and Aβ 42/40 ratio were measured in 106 participants with BMIs classified as lean, overweight, or obese. From this cohort, twelve participants with overweight or obese BMIs entered a 12-week calorie-restriction weight loss program. We then tested whether decreasing BMI affected plasma Aβ concentrations. RESULTS: Plasma Aβ 42/40 ratio was 17.54% lower in participants with an obese BMI compared to lean participants (p <  0.0001), and 11.76% lower compared to participants with an overweight BMI (p <  0.0001). The weight loss regimen decreased BMI by an average of 4.02% (p = 0.0005) and was associated with a 6.5% decrease in plasma Aβ 40 (p = 0.0425). However, weight loss showed negligible correlations with plasma Aβ 40, Aβ 42, and Aβ 42/40 ratio. CONCLUSION: Obesity is associated with aberrant plasma Aβ homeostasis which may be associated with an increased risk for AD. Weight loss appears to lower Aβ 40, but large-scale longitudinal studies in addition to molecular studies are required to elucidate the underlying mechanisms of how obesity and weight loss influence plasma Aβ homeostasis.

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Posttraumatic Stress and Traumatic Brain Injury: Cognition, Behavior, and Neuroimaging Markers in Vietnam Veterans. - Marcolini, Sofia; Rojczyk, Philine; Seitz-Holland, Johanna; Koerte, Inga K; Alosco, Michael L; Bouix, Sylvain (J Alzheimers Dis, 2023)
BACKGROUND: Posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) are common in Veterans and linked to behavioral disturbances, increased risk of cognitive decline, and Alzheimer's disease. OBJECTIVE: We studied the synergistic effects of PTSD and TBI on behavioral, cognitive, and neuroimaging measures in Vietnam war Veterans. METHODS: Data were acquired at baseline and after about one-year from male Veterans categorized into: PTSD, TBI, PTSD+TBI, and Veteran controls without PTSD or TBI. We applied manual tractography to examine white matter microstructure of three fiber tracts: uncinate fasciculus (N = 91), cingulum (N = 87), and inferior longitudinal fasciculus (N = 95). ANCOVAs were used to compare Veterans' baseline behavioral and cognitive functioning (N = 285), white matter microstructure, amyloid-β (N = 230), and tau PET (N = 120). Additional ANCOVAs examined scores' differences from baseline to follow-up. RESULTS: Veterans with PTSD and PTSD+TBI, but not Veterans with TBI only, exhibited poorer behavioral and cognitive functioning at baseline than controls. The groups did not differ in baseline white matter, amyloid-β, or tau, nor in behavioral and cognitive functioning, and tau accumulation change. Progression of white matter abnormalities of the uncinate fasciculus in Veterans with PTSD compared to controls was observed; analyses in TBI and PTSD+TBI were not run due to insufficient sample size. CONCLUSIONS: PTSD and PTSD+TBI negatively affect behavioral and cognitive functioning, while TBI does not contribute independently. Whether progressive decline in uncinate fasciculus microstructure in Veterans with PTSD might account for cognitive decline should be further studied. Findings did not support an association between PTSD, TBI, and Alzheimer's disease pathology based on amyloid and tau PET.

Proteome Network Analysis Identifies Potential Biomarkers for Brain Aging. - Short, Meghan I; Fohner, Alison E; Skjellegrind, Håvard K; Beiser, Alexa; Gonzales, Mitzi M; Satizabal, Claudia L; Austin, Thomas R; Longstreth, W T; Bis, Joshua C; Lopez, Oscar; Hveem, Kristian; Selbæk, Geir; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease and related dementias (ADRD) involve biological processes that begin years to decades before onset of clinical symptoms. The plasma proteome can offer insight into brain aging and risk of incident dementia among cognitively healthy adults. OBJECTIVE: To identify biomarkers and biological pathways associated with neuroimaging measures and incident dementia in two large community-based cohorts by applying a correlation-based network analysis to the plasma proteome. METHODS: Weighted co-expression network analysis of 1,305 plasma proteins identified four modules of co-expressed proteins, which were related to MRI brain volumes and risk of incident dementia over a median 20-year follow-up in Framingham Heart Study (FHS) Offspring cohort participants (n = 1,861). Analyses were replicated in the Cardiovascular Health Study (CHS) (n = 2,117, mean 6-year follow-up). RESULTS: Two proteomic modules, one related to protein clearance and synaptic maintenance (M2) and a second to inflammation (M4), were associated with total brain volume in FHS (M2: p = 0.014; M4: p = 4.2×10-5). These modules were not significantly associated with hippocampal volume, white matter hyperintensities, or incident all-cause or AD dementia. Associations with TCBV did not replicate in CHS, an older cohort with a greater burden of comorbidities. CONCLUSIONS: Proteome networks implicate an early role for biological pathways involving inflammation and synaptic function in preclinical brain atrophy, with implications for clinical dementia.

Refining Risk for Alzheimer's Disease Among Heterozygous APOEɛ4 Carriers. - Patel, Smita; Wei, Jun; Shi, Zhuqing; Rifkin, Andrew S; Zheng, S Lilly; Gelfman, Elizabeth; Duggan, David; Helfand, Brian T; Hulick, Peter J; Xu, Jianfeng (J Alzheimers Dis, 2023)
In a large population-based cohort, we show not all heterozygous APOEɛ4 carriers are at increased risk for Alzheimer's disease (AD); a significantly higher AD proportion was only found for ɛ3/ɛ4, not ɛ2/ɛ4. Among ɛ3/ɛ4 carriers (24% in the cohort), the AD proportion differed considerably by polygenic risk score (PRS). In particular, the AD proportion was lower than the entire cohort for subjects in the bottom 20-percentile PRS and was higher than that of homozygous ɛ4 carriers for subjects at the top 5th-percentile PRS. Family history was no longer a significant predictor of AD risk after adjusting APOE and PRS.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Heterozygote; Homozygote; Humans

Retinal Functional and Structural Neural Indices: Potential Biomarkers for the Monitoring of Cerebral Neurodegeneration: The Maastricht Study. - van der Heide, Frank C T; Mokhtar, Sara; Khanna, Anjani; Said, Mozhda; Henry, Ronald M A; Kroon, Abraham A; Dagnelie, Pieter C; Eussen, Simone J P M; Berendschot, Tos T J M; Schouten, Jan S A G; Schram, Miranda T; van der Kallen, Carla J H; et al. (J Alzheimers Dis, 2023)
BACKGROUND: If retinal indices of neurodegeneration are to be biomarkers for the monitoring of cerebral neurodegeneration, it is important to establish whether potentially modifiable risk factors for dementia are associated with retinal neurodegenerative changes. OBJECTIVE: To study associations of dementia risk factors with retinal sensitivity, an index of retinal neural function, and retinal nerve fiber layer (RNFL) thickness, an index of retinal neural structure. METHODS: We used cross-sectional data from The Maastricht Study (up to 5,666 participants, 50.5% men, mean age 59.7), and investigated associations with regression analyses (adjusted for potential confounders). RESULTS: Most risk factors under study (i.e., hyperglycemia, unhealthy diet, lower cardiorespiratory fitness, smoking, alcohol consumption, and hypertension) were significantly associated with lower retinal sensitivity and lower RNFL thickness. CONCLUSION: Findings of this population-based study support the concept that retinal neural indices may be biomarkers for the monitoring of therapeutic strategies that aim to prevent early-stage cerebral neurodegeneration and, ultimately, dementia.

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Serotonin Degeneration and Amyloid-β Deposition in Mild Cognitive Impairment: Relationship to Cognitive Deficits. - Smith, Gwenn S; Kuwabara, Hiroto; Yan, Haijuan; Nassery, Najlla; Yoon, Mark; Kamath, Vidya; Kraut, Michael; Gould, Neda F; Savonenko, Alena; Coughlin, Jennifer M; Lodge, Martin; Pomper, Martin G; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neuropathological and neuroimaging studies have demonstrated degeneration of the serotonin system in Alzheimer's disease (AD). Neuroimaging studies have extended these observations to the preclinical stages of AD, mild cognitive impairment (MCI). Serotonin degeneration has been observed also in transgenic amyloid mouse models, prior to widespread cortical distribution of amyloid-β (Aβ). OBJECTIVE: The present study evaluated the regional distribution of the serotonin transporter (5-HTT) and of Aβ in individuals with MCI and healthy older controls, as well as the contribution of 5-HTT and Aβ to cognitive deficits. METHODS: Forty-nine MCI participants and 45 healthy older controls underwent positron emission tomography (PET) imaging of 5-HTT and Aβ, structural magnetic resonance imaging and neuropsychological assessments. RESULTS: Lower cortical, striatal, and limbic 5-HTT and higher cortical Aβ was observed in MCIs relative to healthy controls. Lower 5-HTT, mainly in limbic regions, was correlated with greater deficits in auditory-verbal and visual-spatial memory and semantic, not phonemic fluency. Higher cortical A β was associated with greater deficits in auditory-verbal and visual-spatial memory and in semantic, not phonemic fluency. When modeling the association between cognition, gray matter volumes and Aβ, inclusion of 5-HTT in limbic and in select cortical regions significantly improved model fit for auditory-verbal and visual-spatial memory and semantic, but not phonemic fluency. CONCLUSIONS: These results support the role of serotonin degeneration in the memory and semantic fluency deficits observed in MCI.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognition; Cognition Disorders; Cognitive Dysfunction; Humans; Mice; Positron-Emission Tomography; Serotonin

TDP-43 Pathology in the Setting of Intermediate and High Alzheimer's Disease Neuropathologic Changes: A Preliminary Evaluation Across Ethnoracial Groups. - Huie, Emily Z; Escudero, Anthony; Saito, Naomi; Harvey, Danielle; Nguyen, My-Le; Lucot, Katherine L; LaGrande, Jayne; Mungas, Dan; DeCarli, Charles; Lamar, Melissa; Schneider, Julie A; Kapasi, Alifiya; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Transactive Response DNA Binding Protein 43 kDa (TDP-43) pathology is frequently found in cases with Alzheimer's disease (AD). TDP-43 pathology is associated with hippocampal atrophy and greater AD severity denoted by cognition and clinical representation. Current TDP-43 pathology studies are predominantly based on non-Hispanic White cohorts. OBJECTIVE: We sought to evaluate the presence of TDP-43 pathology across ethnoracial groups utilizing the National Alzheimer's Coordinating Center; a database containing data from over 29 institutions across the United States. Cases (N = 1,135: Hispanics/Latinos = 29, African Americans/Black Americans = 51, Asians/Asian Americans = 10, American Indians/Alaskan Natives = 2, non-Hispanic White = 1,043) with intermediate/high AD having data on TDP-43 pathology in the amygdala, hippocampus, entorhinal cortex, and neocortex. METHODS: TDP-43 pathology frequency in each neuroanatomic region among ethnoracial groups were compared using generalized linear mixed effects models with center as a random effect adjusting for age at death, education, and gender. RESULTS: Although groups were imbalanced, there was no significant difference across ethnoracial groups based on TDP-43 pathology (p = 0.84). With respect to neuroanatomical regions evaluated, there were no significant differences across ethnoracial groups (p-values > 0.06). There were also no significant differences for age at death and gender ratios across ethnoracial groups based on TDP-43 pathology. Although not statistically significant, TDP-43 pathology was present less often in Hispanic/Latinos (34%) when compared to non-Hispanic Whites (46%). CONCLUSION: While this is a preliminary evaluation, it highlights the need for diverse cohorts and on TDP-43 pathology research across ethnoracial groups. This is the first study to our knowledge having a focus on the neuroanatomical distribution of TDP-43 deposits in Hispanic/Latino decedents with AD.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Type 2 Diabetes Comorbidity and Cognitive Decline in Patients with Alzheimer's Disease. - Davidson, Skylar; Allenback, Gayle; Decourt, Boris; Sabbagh, Marwan N (J Alzheimers Dis, 2023)
BACKGROUND: Although insulin dysregulation and resistance likely participate in Alzheimer's disease (AD) etiologies, little is known about the correlation between type 2 diabetes mellitus (T2DM) and the progression of cognitive decline in patients with AD. OBJECTIVE: To determine whether AD patients with T2DM experience more rapid cognitive decline than those without T2DM. METHODS: All cognitive performance data and the presence or absence of T2DM comorbidity in patients with AD were derived from the US National Alzheimer's Coordinating Center's (NACC) Uniform Data Set (UDS). A search of the UDS identified 3055 participants with AD who had more than one epoch completed. The data set culled clinically diagnosed AD dementia patients who were assessed for diabetes type identified during at least 1 visit. These patients were divided into 2 groups based on whether they had a diagnosis of T2DM. The data from these groups were then analyzed for differences in cognitive decline based on neuropsychological test battery scores and a Clinician Dementia Rating using a general linear model. RESULTS: Comparisons of the mean scores for 16 selected tests from the neuropsychological test battery showed no significant differences in baseline scores and scores at subsequent visits between the T2DM and nondiabetic groups. CONCLUSIONS: The results revealed no differences in cognitive decline metrics over the course of 5 visits in either study group. These data indicate that the presence of T2DM does not increase the rate of cognitive decline in AD. This finding contradicts expected disease burden and will need to be explored further.

3-Hydroxyacyl-CoA and Alcohol Dehydrogenase Activities of Mitochondrial Type 10 17β-Hydroxysteroid Dehydrogenase in Neurodegeneration Study. - He, Xue-Ying; Dobkin, Carl; Brown, W Ted; Yang, Song-Yu (J Alzheimers Dis, 2022)
BACKGROUND: Mitochondrial 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10) is necessary for brain cognitive function, but its studies were confounded by reports of Aβ-peptide binding alcohol dehydrogenase (ABAD), formerly endoplasmic reticulum-associated Aβ-peptide binding protein (ERAB), for two decades so long as ABAD serves as the alternative term of 17β-HSD10. OBJECTIVE: To determine whether those ABAD reports are true or false, even if they were published in prestigious journals. METHODS: 6xHis-tagged 17β-HSD10 was prepared and characterized by well-established experimental procedures. RESULTS: The N-terminal 6xHis tag did not significantly interfere with the dehydrogenase activities of 17β-HSD10, but the kinetic constants of its 3-hydroxyacyl-CoA dehydrogenase activity are drastically distinct from those of ABAD, and it was not involved in ketone body metabolism as previously reported for ABAD. Furthermore, it was impossible to measure its generalized alcohol dehydrogenase activities underlying the concept of ABAD because the experimental procedures described in ABAD reports violated basic chemical and/or biochemical principles. More incredibly, both authors and journals had not yet agreed to make any corrigenda of ABAD reports. CONCLUSION: Brain 17β-HSD10 plays a key role in neurosteroid metabolism and further studies in this area may lead to potential treatments of neurodegeneration including AD.

Alzheimer's Disease with Epileptiform EEG Activity: Abnormal Cortical Sources of Resting State Delta Rhythms in Patients with Amnesic Mild Cognitive Impairment. - Babiloni, Claudio; Noce, Giuseppe; Di Bonaventura, Carlo; Lizio, Roberta; Eldellaa, Ali; Tucci, Federico; Salamone, Enrico M; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Famá, Francesco; Arnaldi, Dario; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnesic mild cognitive impairment due to Alzheimer's disease (ADMCI) typically show a "slowing" of cortical resting-state eyes-closed electroencephalographic (rsEEG) rhythms. Some of them also show subclinical, non-convulsive, and epileptiform EEG activity (EEA) with an unclear relationship with that "slowing." OBJECTIVE: Here we tested the hypothesis that the "slowing" of rsEEG rhythms is related to EEA in ADMCI patients. METHODS: Clinical and instrumental datasets in 62 ADMCI patients and 38 normal elderly (Nold) subjects were available in a national archive. No participant had received a clinical diagnosis of epilepsy. The eLORETA freeware estimated rsEEG cortical sources. The area under the receiver operating characteristic curve (AUROCC) indexed the accuracy of eLORETA solutions in the classification between ADMCI-EEA and ADMCI-noEEA individuals. RESULTS: EEA was observed in 15% (N = 8) of the ADMCI patients. The ADMCI-EEA group showed: 1) more abnormal Aβ 42 levels in the cerebrospinal fluid as compared to the ADMCI-noEEA group and 2) higher temporal and occipital delta ( CONCLUSION: It can be speculated that in ADMCI-EEA patients, AD-related amyloid neuropathology may be related to an over-excitation in neurophysiological low-frequency (delta) oscillatory mechanisms underpinning cortical arousal and quiet vigilance.

Anticholinergic Drug Burden and Neurocognitive Performance in the Study of Latinos-Investigation of Neurocognitive Aging. - Posis, Alexander Ivan B; Tarraf, Wassim; Gonzalez, Kevin A; Soria-Lopez, Jose A; Léger, Gabriel C; Stickel, Ariana M; Daviglus, Martha L; Lamar, Melissa; Zeng, Donglin; González, Hector M (J Alzheimers Dis, 2022)
BACKGROUND: Studies of cumulative anticholinergic drug burden on cognitive function and impairment are emerging, yet few for Hispanics/Latinos. OBJECTIVE: To examine associations between anticholinergic use and neurocognitive performance outcomes among diverse Hispanics/Latinos. METHODS: This prospective cohort study included diverse Hispanic/Latino participants, enrolled in the Study of Latinos-Investigation of Neurocognitive, from New York, Chicago, Miami, and San Diego (n = 6,249). Survey linear regression examined associations between anticholinergic use (measured during baseline [Visit 1] and average 7-year follow up [Visit 2]) with global cognition, episodic learning, memory, phonemic fluency, processing speed, executive functioning, and average 7-year change. RESULTS: Anticholinergic use was associated with lower cognitive global cognition (β= -0.21; 95% CI [-0.36; -0.05]), learning (β= -0.27; 95% CI [-0.47; -0.07]), memory (β= -0.22; 95% CI [-0.41; -0.03]), and executive functioning (β= -0.22; 95% CI [-0.40; -0.03]) scores, particularly among those who took anticholinergics at both visits. Anticholinergic use was associated with faster decline in global cognition, learning, and verbal fluency (β: -0.28 [95% CI: -0.55, -0.01]; β: -0.28 [95% CI: -0.55, -0.01]; β: -0.25, [95% CI -0.47, -0.04], respectively). Sex modified associations between anticholinergic use with global cognition, learning, and executive functioning (F3 = 3.59, F3 = 2.84, F3 = 3.88, respectively). CONCLUSION: Anticholinergic use was associated with lower neurocognitive performance, especially among those who used anticholinergics at both visits, among a study population of diverse Hispanics/Latinos. Findings will support evidence-based decisions regarding anticholinergic prescriptions and efforts to minimize cognitive impact.

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Association of Aspirin Use with Reduced Risk of Developing Alzheimer's Disease in Elderly Ischemic Stroke Patients: A Retrospective Cohort Study. - Gorenflo, Maria P; Davis, Pamela B; Kendall, Ellen K; Olaker, Veronica R; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
BACKGROUND: Currently there are no effective therapies to prevent or halt the development of Alzheimer's disease (AD). Multiple risk factors are involved in AD, including ischemic stroke (IS). Aspirin is often prescribed following IS to prevent blood clot formation. Observational studies have shown inconsistent findings with respect to the relationship between aspirin use and the risk of AD. OBJECTIVE: To investigate the relationship between aspirin therapy after IS and the new diagnosis of AD in elderly patients. METHODS: This retrospective cohort study leveraged a large database that contains over 90 million electronic health records to compare the hazard rates of AD after IS in elderly patients prescribed aspirin versus those not prescribed aspirin after propensity-score matching for relevant confounders. RESULTS: At 1, 3, and 5 years after first IS, elderly patients prescribed aspirin were less likely to develop AD than those not prescribed aspirin: Hazard Ratio = 0.78 [0.65,0.94], 0.8 1 [0.70,0.94], and 0.76 [0.70,0.92]. CONCLUSION: Our findings suggest that aspirin use may prevent AD in patients with IS, a subpopulation at high risk of developing the disease.

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of Carotid Intima Media Thickening with Future Brain Region Specific Amyloid-β Burden. - Baradaran, Hediyeh; Peloso, Gina M; Polak, Joseph F; Killiany, Ronald J; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa; Romero, Jose R; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Carotid atherosclerosis is associated with cognitive impairment and dementia, though there is limited evidence of a direct link between carotid disease and amyloid-β (Aβ) burden. OBJECTIVE: We studied the association of baseline and progressive carotid intima media thickness (CIMT) with Aβ on 11C-Pittsburgh Compound B (PiB) to determine if those with carotid atherosclerosis would have higher Aβ burden. METHODS: We studied 47 participants from the Framingham Offspring cohort with carotid ultrasounds measuring CIMT at their 6th clinic examination (aged 49.5±5.7 years) and an average of 9.6 years later, and PiB imaging measuring Aβ on average 22.1 years post baseline. We used multivariate linear regression analyses to relate baseline, follow-up, mean, and progression of internal carotid artery (ICA) and common carotid artery (CCA) CIMT to Aβ in brain regions associated with Alzheimer's disease (AD) and related dementias (ADRD), adjusting for age, sex, and other vascular risk factors. RESULTS: Participants with higher mean ICA IMT had more Aβ in the precuneus (beta±standard error [β±SE]: 0.466±0.171 mm, p = 0.01) and the frontal, lateral, and retrosplenial regions (β±SE: 0.392±0.164 mm, p = 0.022) after adjusting for age, sex, vascular risk factors, and medication use. We did not find an association between any CCA IMT measures and Aβ or progression of ICA or CCA IMT and Aβ. CONCLUSION: Carotid atherosclerosis, as measured by ICA IMT, is associated with increased Aβ burden later in life. These findings support a link between vascular disease and AD/ADRD pathophysiology.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

Associations Between Brainstem Volume and Alzheimer's Disease Pathology in Middle-Aged Individuals of the Framingham Heart Study. - Jacobs, Heidi I L; O'Donnell, Adrienne; Satizabal, Claudia L; Lois, Cristina; Kojis, Daniel; Hanseeuw, Bernard J; Thibault, Emma; Sanchez, Justin S; Buckley, Rachel F; Yang, Qiong; DeCarli, Charles; Killiany, Ron; et al. (J Alzheimers Dis, 2022)
The brainstem is among the first regions to accumulate Alzheimer's disease (AD)-related hyperphosphorylated tau pathology during aging. We aimed to examine associations between brainstem volume and neocortical amyloid-β or tau pathology in 271 middle-aged clinically normal individuals of the Framingham Heart Study who underwent MRI and PET imaging. Lower volume of the medulla, pons, or midbrain was associated with greater neocortical amyloid burden. No associations were detected between brainstem volumes and tau deposition. Our results support the hypothesis that lower brainstem volumes are associated with initial AD-related processes and may signal preclinical AD pathology.

Associations Between Vascular Risk Factor and Perivascular Spaces in Adults with Intact Cognition, Mild Cognitive Impairment, and Dementia. - Rundek, Tatjana; Del Brutto, Victor; Goryawala, Mohammed; Dong, Chuanhui; Agudelo, Christian; Saporta, Anita Seixas; Merritt, Stacy; Camargo, Christian; Ariko, Taylor; Loewenstein, David A; Duara, Ranjan; Haq, Ihtsham (J Alzheimers Dis, 2022)
BACKGROUND: Perivascular spaces (PVS) are fluid-filled compartments surrounding small intracerebral vessels that transport fluid and clear waste. OBJECTIVE: We examined associations between PVS count, vascular and neurodegenerative risk factors, and cognitive status among the predominantly Hispanic participants of the FL-VIP Study of Alzheimer's Disease Risk. METHODS: Using brain MRI (n = 228), we counted PVS in single axial image through the basal ganglia (BG) and centrum semiovale (CSO). PVS per region were scored as 0 (none), 1 (<10), 2 (11-20), 3 (21-40), and 4 (>40). Generalized linear models examined PVS associations with vascular risk factors and a composite vascular comorbidity risk (VASCom) score. RESULTS: Our sample (mean age 72±8 years, 61% women, 60% Hispanic, mean education 15±4 years, 33% APOE4 carriers) was 59% hypertensive, 21% diabetic, 66% hypercholesteremic, and 30% obese. Mean VASCom score was 2.3±1.6. PVS scores ranged from 0-4 in the BG (mean 1.3±0.7) and CSO (mean 1.2±0.9), and 0-7 combined (mean 2.5±1.4). In multivariable regression models, BG PVS was associated with age (β= 0.03/year, p <  0.0001), Hispanic ethnicity (β= 0.29, p = 0.01), education (β= 0.04/year, p = 0.04), and coronary bypass surgery (β= 0.93, p = 0.02). CSO PVS only associated with age (β= 0.03/year, p <  0.01). APOE4 and amyloid-β were not associated with PVS. CONCLUSION: BG PVS may be a marker of subclinical cerebrovascular disease. Further research is needed to validate associations and identify mechanisms linking BG PVS and cerebrovascular disease markers. PVS may be a marker of neurodegeneration despite our negative preliminary findings and more research is warranted. The association between BG PVS and Hispanic ethnicity also requires further investigation.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Augmenting Imaging Biomarker Performance with Blood-Based Gene Expression Levels for Predicting Alzheimer's Disease Progression. - Dobromyslin, Vitaly I; Megherbi, Dalila B (J Alzheimers Dis, 2022)
BACKGROUND: Structural brain imaging metrics and gene expression biomarkers have previously been used for Alzheimer's disease (AD) diagnosis and prognosis, but none of these studies explored integration of imaging and gene expression biomarkers for predicting mild cognitive impairment (MCI)-to-AD conversion 1-2 years into the future. OBJECTIVE: We investigated advantages of combining gene expression and structural brain imaging features for predicting MCI-to-AD conversion. Selection of the differentially expressed genes (DEGs) for classifying cognitively normal (CN) controls and AD patients was benchmarked against previously reported results. METHODS: The current work proposes integrating brain imaging and blood gene expression data from two public datasets (ADNI and ANM) to predict MCI-to-AD conversion. A novel pipeline for combining gene expression data from multiple platforms is proposed and evaluated in the two independents patient cohorts. RESULTS: Combining DEGs and imaging biomarkers for predicting MCI-to-AD conversion yielded 0.832-0.876 receiver operating characteristic (ROC) area under the curve (AUC), which exceeded the 0.808-0.840 AUC from using the imaging features alone. With using only three DEGs, the CN versus AD predictive model achieved 0.718, 0.858, and 0.873 cross-validation AUC for the ADNI, ANM1, and ANM2 datasets. CONCLUSION: For the first time we show that combining gene expression and imaging biomarkers yields better predictive performance than using imaging metrics alone. A novel pipeline for combining gene expression data from multiple platforms is proposed and evaluated to produce consistent results in the two independents patient cohorts. Using an improved feature selection, we show that predictive models with fewer gene expression probes can achieve competitive performance.

Avoiding Over-Reliance on Multi-Domain Interventions for Dementia Prevention. - Daly, Timothy; Mastroleo, Ignacio; Migliaccio, Raffaella (J Alzheimers Dis, 2022)
Given the unknown therapeutic value of targeting Alzheimer's disease pathology and the discovery of robust risk factors for dementia, non-pharmacological risk reduction (RR) is increasingly offered as an alternative to targeting Alzheimer's disease pathology. While RR will surely be a useful tool to make public health gains, we propose solutions to three possible issues with over-reliance on multi-domain interventions to achieve RR: limited individual impact, an exclusive focus on later life, and overlooking social determinants of dementia. We argue in favor of a broader debate within the research community and greater society about how different therapeutic avenues should be explored.
Keywords: Alzheimer Disease; Humans; Risk Factors; Risk Reduction Behavior

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

Cancer and Vascular Comorbidity Effects on Dementia Risk and Neuropathology in the Oldest-Old. - Lachner, Christian; Day, Gregory S; Camsari, Gamze Balci; Kouri, Naomi; Ertekin-Taner, Nilufer; Boeve, Bradley F; Labuzan, Sydney A; Lucas, John A; Thompson, E Aubrey; Siddiqui, Habeeba; Crook, Julia E; Cabrera-Rodriguez, Janisse N; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Dementia, vascular disease, and cancer increase with age, enabling complex comorbid interactions. Understanding vascular and cancer contributions to dementia risk and neuropathology in oldest-old may improve risk modification and outcomes. OBJECTIVE: Investigate vascular and cancer contributions to dementia and neuropathology in oldest-old. METHODS: Longitudinal clinicopathologic study of prospectively followed Mayo Clinic participants dying≥95 years-old who underwent autopsy. Participants were stratified by dementia status and compared according to demographics, vascular risk factors, cancer, and neuropathology. RESULTS: Participants (n = 161; 83% female; 99% non-Hispanic whites)≥95 years (95-106 years-old) with/without dementia did not differ based on demographics. APOE ɛ2 frequency was higher in no dementia (20/72 [28%]) versus dementia (11/88 [12%]; p = 0.03), but APOE ɛ4 frequency did not differ. Coronary artery disease was more frequent in no dementia (31/72 [43%]) versus dementia (23/89 [26%]; p = 0.03) associated with 56% lower dementia odds (odds ratio [OR] = 0.44 [confidence interval (CI) = 0.19-0.98]; p = 0.04) and fewer neuritic/diffuse plaques. Diabetes had an 8-fold increase in dementia odds (OR = 8.42 [CI = 1.39-163]; p = 0.02). Diabetes associated with higher cerebrovascular disease (Dickson score; p = 0.05). Cancer associated with 63% lower dementia odds (OR = 0.37 [CI = 0.17-0.78]; p <  0.01) and lower Braak stage (p = 0.01). CONCLUSION: Cancer exposure in the oldest-old was associated with lower odds of dementia and tangle pathology, whereas history of coronary artery disease was associated with lower odds of dementia and amyloid-β plaque pathology. History of diabetes mellitus was associated with increased odds of dementia and cerebrovascular disease pathology. Cancer-related mechanisms and vascular risk factor reduction strategies may alter dementia risk and neuropathology in oldest-old.

Cerebrospinal Fluid Sphingomyelins in Alzheimer's Disease, Neurodegeneration, and Neuroinflammation. - Morrow, Autumn; Panyard, Daniel J; Deming, Yuetiva K; Jonaitis, Erin; Dong, Ruocheng; Vasiljevic, Eva; Betthauser, Tobey J; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Bayfield, Anna; Van Hulle, Carol A; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Sphingomyelin (SM) levels have been associated with Alzheimer's disease (AD), but the association direction has been inconsistent and research on cerebrospinal fluid (CSF) SMs has been limited by sample size, breadth of SMs examined, and diversity of biomarkers available. OBJECTIVE: Here, we seek to build on our understanding of the role of SM metabolites in AD by studying a broad range of CSF SMs and biomarkers of AD, neurodegeneration, and neuroinflammation. METHODS: Leveraging two longitudinal AD cohorts with metabolome-wide CSF metabolomics data (n = 502), we analyzed the relationship between the levels of 12 CSF SMs, and AD diagnosis and biomarkers of pathology, neurodegeneration, and neuroinflammation using logistic, linear, and linear mixed effects models. RESULTS: No SMs were significantly associated with AD diagnosis, mild cognitive impairment, or amyloid biomarkers. Phosphorylated tau, neurofilament light, α-synuclein, neurogranin, soluble triggering receptor expressed on myeloid cells 2, and chitinase-3-like-protein 1 were each significantly, positively associated with at least 5 of the SMs. CONCLUSION: The associations between SMs and biomarkers of neurodegeneration and neuroinflammation, but not biomarkers of amyloid or diagnosis of AD, point to SMs as potential biomarkers for neurodegeneration and neuroinflammation that may not be AD-specific.

Comparative Analysis of Alzheimer's Disease Cerebrospinal Fluid Biomarkers Measurement by Multiplex SOMAscan Platform and Immunoassay-Based Approach. - Timsina, Jigyasha; Gomez-Fonseca, Duber; Wang, Lihua; Do, Anh; Western, Dan; Álvarez, Ignacio; Aguilar, Miquel; Pastor, Pau; Henson, Rachel L; Herries, Elizabeth; Xiong, Chengjie; Schindler, Suzanne E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The SOMAscan assay has an advantage over immunoassay-based methods because it measures a large number of proteins in a cost-effective manner. However, the performance of this technology compared to the routinely used immunoassay techniques needs to be evaluated. OBJECTIVE: We performed comparative analyses of SOMAscan and immunoassay-based protein measurements for five cerebrospinal fluid (CSF) proteins associated with Alzheimer's disease (AD) and neurodegeneration: NfL, Neurogranin, sTREM2, VILIP-1, and SNAP-25. METHODS: We compared biomarkers measured in ADNI (N = 689), Knight-ADRC (N = 870), DIAN (N = 115), and Barcelona-1 (N = 92) cohorts. Raw protein values were transformed using z-score in order to combine measures from the different studies. sTREM2 and VILIP-1 had more than one analyte in SOMAscan; all available analytes were evaluated. Pearson's correlation coefficients between SOMAscan and immunoassays were calculated. Receiver operating characteristic curve and area under the curve were used to compare prediction accuracy of these biomarkers between the two platforms. RESULTS: Neurogranin, VILIP-1, and NfL showed high correlation between SOMAscan and immunoassay measures (r >  0.9). sTREM2 had a fair correlation (r >  0.6), whereas SNAP-25 showed weak correlation (r = 0.06). Measures in both platforms provided similar predicted performance for all biomarkers except SNAP-25 and one of the sTREM2 analytes. sTREM2 showed higher AUC for SOMAscan based measures. CONCLUSION: Our data indicate that SOMAscan performs as well as immunoassay approaches for NfL, Neurogranin, VILIP-1, and sTREM2. Our study shows promise for using SOMAscan as an alternative to traditional immunoassay-based measures. Follow-up investigation will be required for SNAP-25 and additional established biomarkers.

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

A Comparison of Well-Being of Carers of People with Dementia and Their Ability to Manage Before and During the COVID-19 Pandemic: Findings from the IDEAL Study. - Gamble, Laura D; Parker, Sophie; Quinn, Catherine; Bennett, Holly Q; Martyr, Anthony; Sabatini, Serena; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Allan, Louise; Burns, Alistair; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Social restriction measures imposed to curb the spread of COVID-19 in the United Kingdom impacted on carers of people with dementia, limiting access to support services and increasing perceived burden of caring. Few studies have compared data collected both during and before the pandemic to examine the effect of these changes. OBJECTIVE: To explore whether the COVID-19 pandemic affected the well-being of carers of people with dementia living in the community, and their ability to cope with their caring responsibilities. METHODS: Analysis was conducted on two groups of carers who were enrolled in the IDEAL programme; the 'pre-pandemic group' (n = 312), assessed at two time points prior to the pandemic, and the 'pandemic group', assessed prior to and several months into the pandemic (n = 156). For the pre-pandemic group, carers were matched 2:1 to carers in the pandemic group on certain characteristics. Differences in change over time between the two groups on self-reported well-being, quality of life, coping, perceived competence, and role captivity, were investigated using mixed effect modelling. RESULTS: Compared to the pre-pandemic group, those in the pandemic group appeared to cope better and had more stable self-rated competency and role captivity. They did not differ in terms of well-being or quality of life. CONCLUSIONS: Despite reports of negative impacts on carers early in the pandemic, the findings suggest the pandemic had little negative longer-term impact on carers of people with dementia, and in fact they appeared to have a more positive attitude towards coping several months into the pandemic.
Keywords: Adaptation, Psychological; Caregivers; COVID-19; Dementia; Humans; Pandemics; Quality of Life

Demonstration of Clinical Meaningfulness of the Integrated Alzheimer's Disease Rating Scale (iADRS): Association Between Change in iADRS Scores and Patient and Caregiver Health Outcomes. - Wessels, Alette M; Belger, Mark; Johnston, Joseph A; Yu, Youying; Rentz, Dorene M; Dowsett, Sherie A; Chandler, Julie (J Alzheimers Dis, 2022)
BACKGROUND: The integrated Alzheimer's Disease Rating Scale (iADRS) is a validated cognitive/functional composite that effectively captures cognitive and functional decline over a broad spectrum of disease. The clinical meaningfulness of change on iADRS can be supported by establishing an association with changes on important health outcome measures. OBJECTIVE: To evaluate the relationship between change on the iADRS and changes in health outcomes in individuals with mild cognitive impairment (MCI) due to Alzheimer's disease (AD), or mild or moderate AD dementia using placebo data from four AD clinical trials and data from one AD observational study. METHODS: Analysis of covariate (ANCOVA) models were used to estimate the relationship between 18-month change on the iADRS and changes on health outcome measures (related to cost, quality of life, and caregiver burden). The regression coefficients for the iADRS were used to compute impact of natural disease progression and disease-modifying treatment on health outcomes. Additional ANCOVAs were conducted to understand whether cognition and/or function was the underlying explanation of any association between iADRS and health outcome change. RESULTS: Across datasets and disease stages, a worsening on the iADRS was significantly associated with increased societal costs, caregiver burden (time and distress) and worsening in measures of patient quality of life. CONCLUSION: Decline on the iADRS was associated with worsening in health outcome measures. These findings suggest that the iADRS can be used in clinical trials as a proxy measure of clinically meaningful outcomes of AD progression.
Keywords: Alzheimer Disease; Caregivers; Clinical Trials as Topic; Cognitive Dysfunction; Humans; Observational Studies as Topic; Outcome Assessment, Health Care; Quality of Life

Dimethyl Fumarate is a Potential Therapeutic Option for Alzheimer's Disease. - Sun, Xiaodi; Suo, Xinjun; Xia, Xianyou; Yu, Chunshui; Dou, Yan (J Alzheimers Dis, 2022)
BACKGROUND: Dimethyl fumarate (DMF) has been approved for clinical treatment of multiple sclerosis based on its antioxidant and anti-inflammatory effects by activating the Nrf2 pathway. Since both oxidative stress and inflammation are involved in Alzheimer's disease (AD), DMF is a potential therapeutic option for AD. OBJECTIVE: This study aims to test the therapeutic effects of DMF on AD model mice and to reveal its underlying molecular mechanisms. METHODS: Cell viability assay and in vitro immunofluorescence imaging were used to evaluate the antioxidant effect of DMF on embryonic mouse hippocampal neurons. Behavioral test and brain magnetic resonance imaging were used to assess the therapeutic effects of DMF on spatial learning and memory as well as hippocampal volume in AD model mice with and without Nrf2 knockdown. Western blotting was used to analyze the expression of antioxidant enzymes and molecules associated with AD-related pathological pathways. RESULTS: DMF inhibits reactive oxygen species overproduction and protects neurons without Nrf2 knockdown from death. DMF reduces amyloid-β induced memory impairment and hippocampal atrophy in AD model mice rather than in Nrf2 knockdown AD mice. DMF delays the progression of AD by activating the Nrf2 pathway to enhance the expression of downstream antioxidant enzymes and inhibits lipid peroxidation, apoptosis, inflammation, mitochondrial dysfunction and amyloid-β deposition. CONCLUSION: These results indicate that DMF is a potential therapeutic option for AD through its antioxidant, anti-inflammatory, anti-apoptotic, and other anti-AD effects by activating the Nrf2 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Antioxidants; Cell Survival; Dimethyl Fumarate; Disease Models, Animal; Hippocampus; Inflammation; Male; Memory Disorders; Mice; Mice, Inbred C57BL; Neurons; NF-E2-Related Factor 2; NF-kappa B; Oxidative Stress; Protective Agents; Reactive Oxygen Species

Effects of a 6-Month Multifaceted Diet and Exercise Intervention on Cognition in Older Adults at Risk of Cognitive Decline: The PONDER Double-Blind, Placebo-Controlled Randomized Trial. - Macpherson, Helen; Brownell, Sarah; Harris, Elizabeth; Duckham, Rachel L; O'Connell, Stella; Meyer, Barbara J; Mirzaee, Sam; Daly, Robin M (J Alzheimers Dis, 2022)
BACKGROUND: Multidomain interventions which incorporate exercise and dietary supplementation to target both cognitive and physical health domains may be an important approach to delay cognitive decline. OBJECTIVE: The Protein Omega-3 aNd vitamin D Exercise Research (PONDER) study investigated the effects of a 6-month multifaceted intervention in community-dwelling older adults with subjective memory impairment on cognition (primary outcome), physical function, and body composition with a further 6-month follow up for cognition (secondary outcomes). METHODS: Single-center, community-based, parallel-group, randomized, double-blind placebo-controlled trial involving a 6-month multifaceted intervention with a further follow-up at 12 months. A total of 147 participants [mean age 70.2 years (SD 6.1), 70% female] were randomized to a multimodal exercise program consisting of twice-weekly supervised resistance and aerobic training, combined with a daily omega-3 (900 mg EPA, 600 mg DHA), vitamin D (1000 IU) and protein (20 g) supplement (n = 73), or a control condition (n = 74) comprising stretching/flexibility sessions combined with a placebo. The primary outcome was a composite CogState measure and Trail-Making Test B-A. RESULTS: There were no significant between-group differences in the change of cognition at 6 or 12 months or physical function outcomes at 6 months, but the intervention significantly improved total lean mass compared to controls [0.72 kg (95% CI 0.26-1.19), p = 0.001]. CONCLUSION: A multi-faceted intervention including an omega-3, vitamin D and protein-enriched supplement with twice-weekly exercise training did not provide any benefits to cognitive or physical function in older adults with subjective memory impairment, despite improvements in lean mass.

Evoked Cortical Depolarizations Before and After the Amyloid Plaque Accumulation: Voltage Imaging Study. - Zhu, Mei Hong; Jogdand, Aditi H; Jang, Jinyoung; Nagella, Sai C; Das, Brati; Milosevic, Milena M; Yan, Riqiang; Antic, Srdjan D (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease (AD), synaptic dysfunction is thought to occur many years before the onset of cognitive decline. OBJECTIVE: Detecting synaptic dysfunctions at the earliest stage of AD would be desirable in both clinic and research settings. METHODS: Population voltage imaging allows monitoring of synaptic depolarizations, to which calcium imaging is relatively blind. We developed an AD mouse model (APPswe/PS1dE9 background) expressing a genetically-encoded voltage indicator (GEVI) in the neocortex. GEVI was restricted to the excitatory pyramidal neurons (unlike the voltage-sensitive dyes). RESULTS: Expression of GEVI did not disrupt AD model formation of amyloid plaques. GEVI expression was stable in both AD model mice and Control (healthy) littermates (CTRL) over 247 days postnatal. Brain slices were stimulated in layer 2/3. From the evoked voltage waveforms, we extracted several parameters for comparison AD versus CTRL. Some parameters (e.g., temporal summation, refractoriness, and peak latency) were weak predictors, while other parameters (e.g., signal amplitude, attenuation with distance, and duration (half-width) of the evoked transients) were stronger predictors of the AD condition. Around postnatal age 150 days (P150) and especially at P200, synaptically-evoked voltage signals in brain slices were weaker in the AD groups versus the age- and sex-matched CTRL groups, suggesting an AD-mediated synaptic weakening that coincides with the accumulation of plaques. However, at the youngest ages examined, P40 and P80, the AD groups showed differentially stronger signals, suggesting "hyperexcitability" prior to the formation of plaques. CONCLUSION: Our results indicate bidirectional alterations in cortical physiology in AD model mice; occurring both prior (P40-80), and after (P150-200) the amyloid deposition.

Functional Neurophysiological Biomarkers of Early-Stage Alzheimer's Disease: A Perspective of Network Hyperexcitability in Disease Progression. - Tok, Sean; Ahnaou, Abdallah; Drinkenburg, Wilhelmus (J Alzheimers Dis, 2022)
Network hyperexcitability (NH) has recently been suggested as a potential neurophysiological indicator of Alzheimer's disease (AD), as new, more accurate biomarkers of AD are sought. NH has generated interest as a potential indicator of certain stages in the disease trajectory and even as a disease mechanism by which network dysfunction could be modulated. NH has been demonstrated in several animal models of AD pathology and multiple lines of evidence point to the existence of NH in patients with AD, strongly supporting the physiological and clinical relevance of this readout. Several hypotheses have been put forward to explain the prevalence of NH in animal models through neurophysiological, biochemical, and imaging techniques. However, some of these hypotheses have been built on animal models with limitations and caveats that may have derived NH through other mechanisms or mechanisms without translational validity to sporadic AD patients, potentially leading to an erroneous conclusion of the underlying cause of NH occurring in patients with AD. In this review, we discuss the substantiation for NH in animal models of AD pathology and in human patients, as well as some of the hypotheses considering recently developed animal models that challenge existing hypotheses and mechanisms of NH. In addition, we provide a preclinical perspective on how the development of animal models incorporating AD-specific NH could provide physiologically relevant translational experimental data that may potentially aid the discovery and development of novel therapies for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Biomarkers; Disease Progression; Humans; Nervous System Physiological Phenomena; Neurophysiology; tau Proteins

Glucometabolic Changes Are Associated with Structural Gray Matter Alterations in Prodromal Dementia. - Gentreau, Mélissa; Reynes, Christelle; Sabatier, Robert; Maller, Jerome J; Meslin, Chantal; Deverdun, Jeremy; Le Bars, Emmanuelle; Raymond, Michel; Berticat, Claire; Artero, Sylvaine (J Alzheimers Dis, 2022)
BACKGROUND: Glucometabolic changes, such as high glycemic load (GL) diet and insulin resistance (IR), are potential risk factor of Alzheimer's disease (AD). Yet, the effect of these factors on brain alterations that contribute to AD pathology has not been clearly demonstrated. OBJECTIVE: We aimed to assess the relationship of GL and IR with gray matter volumes involved in prodromal dementia. METHODS: GL and Triglyceride-Glucose (TyG) index, an IR surrogate marker, were calculated in 497 participants who underwent magnetic resonance imaging (MRI). The gray matter volumes most related to prodromal dementia/mild cognitive impairment (diagnosed in 18/158 participants during the 7-year follow-up) were identified using a data-driven machine learning algorithm. RESULTS: Higher GL diet was associated with reduced amygdala volume. The TyG index was negatively associated with the hippocampus, amygdala, and putamen volumes. CONCLUSION: These results suggest that GL and IR are associated with lower gray matter volumes in brain regions involved in AD pathology.

High Soluble Amyloid-β42 Predicts Normal Cognition in Amyloid-Positive Individuals with Alzheimer's Disease-Causing Mutations. - Sturchio, Andrea; Dwivedi, Alok K; Malm, Tarja; Wood, Matthew J A; Cilia, Roberto; Sharma, Jennifer S; Hill, Emily J; Schneider, Lon S; Graff-Radford, Neill R; Mori, Hiroshi; Nübling, Georg; El Andaloussi, Samir; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In amyloid-positive individuals at risk for Alzheimer's disease (AD), high soluble 42-amino acid amyloid-β (Aβ42) levels are associated with normal cognition. It is unknown if this relationship applies longitudinally in a genetic cohort. OBJECTIVE: To test the hypothesis that high Aβ42 preserves normal cognition in amyloid-positive individuals with Alzheimer's disease (AD)-causing mutations (APP, PSEN1, or PSEN2) to a greater extent than lower levels of brain amyloid, cerebrospinal fluid (CSF) phosphorylated tau (p-tau), or total tau (t-tau). METHODS: Cognitive progression was defined as any increase in Clinical Dementia Rating (CDR = 0, normal cognition; 0.5, very mild dementia; 1, mild dementia) over 3 years. Amyloid-positivity was defined as a standard uptake value ratio (SUVR) ≥1.42 by Pittsburgh compound-B positron emission tomography (PiB-PET). We used modified Poisson regression models to estimate relative risk (RR), adjusted for age at onset, sex, education, APOE4 status, and duration of follow-up. The results were confirmed with multiple sensitivity analyses, including Cox regression. RESULTS: Of 232 mutation carriers, 108 were PiB-PET-positive at baseline, with 43 (39.8% ) meeting criteria for progression after 3.3±2.0 years. Soluble Aβ42 levels were higher among CDR non-progressors than CDR progressors. Higher Aβ42 predicted a lower risk of progression (adjusted RR, 0.36; 95% confidence interval [CI], 0.19-0.67; p = 0.002) better than lower SUVR (RR, 0.81; 95% CI, 0.68-0.96; p = 0.018). CSF Aβ42 levels predicting lower risk of progression increased with higher SUVR levels. CONCLUSION: High CSF Aβ42 levels predict normal cognition in amyloid-positive individuals with AD-causing genetic mutations.

HMGCS2-Induced Autophagic Degradation of Tau Involves Ketone Body and ANKRD24. - Hu, Li-Tian; Xie, Xiao-Yong; Zhou, Gui-Feng; Wen, Qi-Xin; Song, Li; Luo, Biao; Deng, Xiao-Juan; Pan, Qiu-Ling; Chen, Guo-Jun (J Alzheimers Dis, 2022)
BACKGROUND: Accumulation of hyperphosphorylated Tau (pTau) contributes to the formation of neurofibrillary tangles in Alzheimer's disease (AD), and targeting Tau/pTau metabolism has emerged as a therapeutic approach. We have previously reported that mitochondrial 3-hydroxy-3-methylglutaryl-COA synthase 2 (HMGCS2) is involved in AD by promoting autophagic clearance of amyloid-β protein precursor via ketone body-associated mechanism, whether HMGCS2 may also regulate Tau metabolism remains elusive. OBJECTIVE: The present study was to investigate the role of HMGCS2 in Tau/p degradation. METHODS: The protein levels of Tau and pTau including pT217 and pT181, as well as autophagic markers LAMP1 and LC3-II were assessed by western blotting. The differentially regulated genes by HMGCS2 were analyzed by RNA sequencing. Autophagosomes were assessed by transmission electron microscopy. RESULTS: HMGCS2 significantly decreased Tau/pTau levels, which was paralleled by enhanced formation of autophagic vacuoles and prevented by autophagic regulators chloroquine, bafilomycin A1, 3-methyladenine, and rapamycin. Moreover, HMGCS2-induced alterations of LAMP1/LC3-II and Tau/pTau levels were mimicked by ketone body acetoacetate or β-hydroxybutyrate. Further RNA-sequencing identified ankyrin repeat domain 24 (ANKRD24) as a target gene of HMGCS2, and silencing of ANKRD24 reduced LAMP1/LC3-II levels, which was accompanied by the altered formation of autophagic vacuoles, and diminished the effect of HMGCS2 on Tau/pTau. CONCLUSION: HMGCS2 promoted autophagic clearance of Tau/pTau, in which ketone body and ANKRD24 played an important role.

Impact of COVID-19 on 'Living Well' with Mild-to-Moderate Dementia in the Community: Findings from the IDEAL Cohort. - Clare, Linda; Martyr, Anthony; Gamble, Laura D; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; Hillman, Alexandra; Litherland, Rachael; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Negative impacts of the COVID-19 pandemic on people with dementia have been widely-documented, but most studies have relied on carer reports and few have compared responses to information collected before the pandemic. OBJECTIVE: We aimed to explore the impact of the pandemic on community-dwelling individuals with mild-to-moderate dementia and compare responses with pre-pandemic data. METHODS: During the second wave of the pandemic, we conducted structured telephone interviews with 173 people with dementia and 242 carers acting as informants, all of whom had previously participated in the IDEAL cohort. Where possible, we benchmarked responses against pre-pandemic data. RESULTS: Significant perceived negative impacts were identified in cognitive and functional skills and ability to engage in self-care and manage everyday activities, along with increased levels of loneliness and discontinuity in sense of self and a decline in perceived capability to 'live well'. Compared to pre-pandemic data, there were lower levels of pain, depression, and anxiety, higher levels of optimism, and better satisfaction with family support. There was little impact on physical health, mood, social connections and relationships, or perceptions of neighborhood characteristics. CONCLUSION: Efforts to mitigate negative impacts of pandemic-related restrictions and restore quality of life could focus on reablement to address the effects on participation in everyday activities, creating opportunities for social contact to reduce loneliness, and personalized planning to reconnect people with their pre-COVID selves. Such efforts may build on the resilience demonstrated by people with dementia and carers in coping with the pandemic.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Neighborhood Characteristics; Quality of Life; SARS-CoV-2

Impaired Experience-Dependent Refinement of Place Cells in a Rat Model of Alzheimer's Disease. - Broussard, John I; Redell, John B; Maynard, Mark E; Zhao, Jing; Moore, Anthony; Mills, Rachel W; Hood, Kimberly N; Underwood, Erica; Roysam, Badrinath; Dash, Pramod K (J Alzheimers Dis, 2022)
BACKGROUND: Hippocampal place cells play an integral role in generating spatial maps. Impaired spatial memory is a characteristic pathology of Alzheimer's disease (AD), yet it remains unclear how AD influences the properties of hippocampal place cells. OBJECTIVE: To record electrophysiological activity in hippocampal CA1 neurons in freely-moving 18-month-old male TgF344-AD and age-matched wild-type (WT) littermates to examine place cell properties. METHODS: We implanted 32-channel electrode arrays into the CA1 subfield of 18-month-old male WT and TgF344-AD (n = 6/group) rats. Ten days after implantation, single unit activity in an open field arena was recorded across days. The spatial information content, in-field firing rate, and stability of each place cell was compared across groups. Pathology was assessed by immunohistochemical staining, and a deep neural network approach was used to count cell profiles. RESULTS: Aged TgF344-AD rats exhibited hippocampal amyloid-β deposition, and a significant increase in Iba1 immunoreactivity and microglia cell counts. Place cells from WT and TgF344-AD rat showed equivalent spatial information, in-field firing rates, and place field stability when initially exposed to the arena. However, by day 3, the place cells in aged WT rats showed characteristic spatial tuning as evidenced by higher spatial information content, stability, and in-field firing rates, an effect not seen in TgF344-AD rats. CONCLUSION: These findings support the notion that altered electrophysiological properties of place cells may contribute to the learning and memory deficits observed in AD.

Improved Alzheimer's Disease versus Frontotemporal Lobar Degeneration Differential Diagnosis Combining EEG and Neurochemical Biomarkers: A Pilot Study. - Laton, Jorne; Van Schependom, Jeroen; Goossens, Joery; Wiels, Wietse; Sieben, Anne; De Deyn, Peter Paul; Goeman, Johan; Streffer, Johannes; van der Zee, Julie; Martin, Jean-Jacques; Van Broeckhoven, Christine; De Vos, Maarten; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Distinguishing between Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) results in poor diagnostic accuracy. OBJECTIVE: To investigate the utility of electroencephalography (EEG)-based biomarkers in comparison and in addition to established cerebrospinal fluid (CSF) biomarkers in the AD versus FTLD differential diagnosis. METHODS: The study cohort comprised 37 AD and 30 FTLD patients, of which 17 AD and 9 FTLD patients had definite diagnoses. All participants had CSF neurochemical (NCM) biomarker analyses (Aβ1-42, T-tau, P-tau181, and Nf-L) and underwent 19-channel resting-state EEG. From the EEG spectra, dominant frequency peaks were extracted in four regions resulting in four dominant frequencies. This produced eight features (4 NCM + 4 EEG). RESULTS: When NCM and EEG markers were combined, the diagnostic accuracy increased significantly. In the whole group, the accuracy went up from 79% (NCM) to almost 82%, while in the definite group only, it went up from around 85% to almost 95% . Two differences in the occurrence of the dominant EEG frequency were discovered: people lacking a clear dominant peak almost all had definite AD, while people with two peaks more often had FTLD. CONCLUSION: Combining EEG with NCM biomarkers resulted in differential diagnostic accuracies of 82% in clinically diagnosed AD and FTD patients and of 95% in patients having a definite diagnosis, which was significantly better than with EEG or NCM biomarkers alone. This suggests that NCM and EEG markers are complementary, revealing different aspects of the disease and therefore confirms again their relevance in developing additional diagnosis tools.

Incidence and Outcomes of SARS-CoV-2 Infection in Older Adults Living with Dementia: A Population-Based Cohort Study. - Cascini, Silvia; Agabiti, Nera; Marino, Claudia; Acampora, Anna; Balducci, Maria; Calandrini, Enrico; Davoli, Marina; Bargagli, Anna Maria (J Alzheimers Dis, 2022)
BACKGROUND: The identification of risk factors for SARS-CoV-2 infection and mortality in patients with dementia is a key aspect to support clinical decisions and public health interventions. OBJECTIVE: To assess the incidence of SARS-CoV-2 infection and COVID-19 related death in a cohort of patients with dementia residing in the Lazio region and to investigate predicting factors for both infection and mortality. METHODS: This population-based study used information from administrative databases and the SARS-CoV-2 infection surveillance system. Patients with dementia (age ≥65) were enrolled as of December 31, 2019 and followed-up until February 28, 2021. Cumulative risk of infection and death within 60 days of infection onset, and age-standardized incidence (SIR) and mortality (SMR) ratios were calculated. Logistic regression models were applied to identify factors associated with infection and mortality. RESULTS: Among 37,729 dementia patients, 2,548 had a diagnosis of SARS-CoV-2 infection. The crude risk of infection was 6.7% . An increase in risk of infection was observed both in women (SIR 1.72; 95% CI 1.64-1.80) and men (SIR 1.43; 95% CI 1.33-1.54). Pneumonia, cerebrovascular and blood diseases, femur fracture, anxiety, antipsychotic and antithrombotic use were associated with an increased risk of infection. The crude risk of death was 31.0%, the SMRs 2.32 (95% CI 2.05-2.65) for men, and 2.82 (95% CI 2.55-3.11) for women. Factors associated with mortality included: male gender, age ≥85, symptoms at the diagnosis, antipsychotic and systemic antibiotics treatment. CONCLUSION: These findings emphasize the need of close and tailored monitoring of dementia patients to reduce the impact of COVID-19 on this fragile population.

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Integrating the Synergy of the Gut Microbiome into Regenerative Medicine: Relevance to Neurological Disorders. - Preethy, Senthilkumar; Ranganathan, Natarajan; Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Ikewaki, Nobunao; Abraham, Samuel J K (J Alzheimers Dis, 2022)
A new paradigm of cell therapy-based approaches as a solution to several diseases caused by damage or loss of cells/tissues leading to organ failure heralded the birth of a new branch in medicine called regenerative medicine (RM), which was further fueled by in vitro cell expansion and tissue engineering (TE) technologies, including the ability to grow embryonic stem cells, induce pluripotent stem cells, and so on. RM addresses organ failure by repair, regeneration, or restoration, rejuvenation using cells, stem cells, or progenitor cells as tools having added cell-derived products also as a tool, and extracellular matrix component-based support, either direct or indirect (e.g., matrix induced autologous chondrocyte implantation) using scaffolds. Now, the main objective of RM is to solve the functional loss of cells that have evolved from cells as tools to cell-derived factors and scaffolds per se as tools. In this context, an important yet indispensable group of cells that constitute the major portion of the human body in terms of the number of cells having several essential roles to play, both directly and indirectly, starting from digestion and the immune system to the growing evidence of influencing neuronal function, aging, and carcinogenesis has been ignored. We would like to focus on these in this review as they should essentially be considered as a tool of RM, especially for neurological disorders for their vital role. What we are indicating is the second genome or the gut microbiome.
Keywords: Gastrointestinal Microbiome; Humans; Nervous System Diseases; Regenerative Medicine; Stem Cells; Tissue Engineering

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.

Mild Traumatic Brain Injury is Related to Elevated Cerebrospinal Fluid Tau in Alzheimer's Disease Dementia. - LoBue, Christian; Kelley, Brendan J; Hart, John; Helphrey, Jessica; Schaffert, Jeff; Cullum, C Munro; Peters, Matthew E; Douglas, Peter M (J Alzheimers Dis, 2022)
Few studies have examined an association between mild traumatic brain injury (mTBI) and Alzheimer's disease (AD). For this reason, we compared an AD dementia group with an mTBI history (n = 10) to a matched AD control group (n = 20) on measures of cognitive function, cerebral glucose metabolism, and markers of amyloid and tau deposition. Only a trend and medium-to-large effect size for higher phosphorylated and total tau was identified for the mTBI group. A history of mTBI may be associated with greater tau in AD, indicating a potential pathway for increasing risk for AD, though further evaluation with larger samples is needed.

Non-Alcoholic Fatty Liver Disease, Liver Fibrosis, and Regional Amyloid-β and Tau Pathology in Middle-Aged Adults: The Framingham Study. - Weinstein, Galit; O'Donnell, Adrienne; Davis-Plourde, Kendra; Zelber-Sagi, Shira; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Liver steatosis and fibrosis are emerging as risk factors for multiple extrahepatic health conditions; however, their relationship with Alzheimer's disease pathology is unclear. OBJECTIVE: To examine whether non-alcoholic fatty liver disease (NAFLD) and FIB-4, a non-invasive index of advanced fibrosis, are associated with brain amyloid-β (Aβ) and tau pathology. METHODS: The study sample included Framingham Study participants from the Offspring and Third generation cohorts who attended exams 9 (2011-2014) and 2 (2008-2011), respectively. Participants underwent 11C-Pittsburgh Compound-B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging and abdomen computed tomography, or had information on all components of the FIB-4 index. Linear regression models were used to assess the relationship of NAFLD and FIB-4 with regional tau and Aβ, adjusting for potential confounders and multiple comparisons. RESULTS: Of the subsample with NAFLD information (N = 169; mean age 52±9 y; 57% males), 57 (34%) had NAFLD. Of the subsample with information on liver fibrosis (N = 177; mean age 50±10 y; 51% males), 34 (19%) had advanced fibrosis (FIB-4 >  1.3). Prevalent NAFLD was not associated with Aβ or tau PET. However, FIB-4 index was significantly associated with increased rhinal tau (β= 1.03±0.33, p = 0.002). Among individuals with prevalent NAFLD, FIB-4 was related to inferior temporal, parahippocampal gyrus, entorhinal and rhinal tau (β= 2.01±0.47, p <  0.001; β= 1.60±0.53, p = 0.007, and β= 1.59±0.47, p = 0.003 and β= 1.60±0.42, p = 0.001, respectively) and to Aβ deposition overall and in the inferior temporal and parahippocampal regions (β= 1.93±0.47, p <  0.001; β= 1.59±0.38, p <  0.001, and β= 1.52±0.54, p = 0.008, respectively). CONCLUSION: This study suggests a possible association between liver fibrosis and early Alzheimer's disease pathology, independently of cardio-metabolic risk factors.

A Novel Panel of Plasma Proteins Predicts Progression in Prodromal Alzheimer's Disease. - Araújo, Daniella Castro; Veloso, Adriano Alonso; Gomes, Karina Braga; de Souza, Leonardo Cruz; Ziviani, Nivio; Caramelli, Paulo (J Alzheimers Dis, 2022)
BACKGROUND: A cheap and minimum-invasive method for early identification of Alzheimer's disease (AD) pathogenesis is key to disease management and the success of emerging treatments targeting the prodromal phases of the disease. OBJECTIVE: To develop a machine learning-based blood panel to predict the progression from mild cognitive impairment (MCI) to dementia due to AD within a four-year time-to-conversion horizon. METHODS: We created over one billion models to predict the probability of conversion from MCI to dementia due to AD and chose the best-performing one. We used Alzheimer's Disease Neuroimaging Initiative (ADNI) data of 379 MCI individuals in the baseline visit, from which 176 converted to AD dementia. RESULTS: We developed a machine learning-based panel composed of 12 plasma proteins (ApoB, Calcitonin, C-peptide, CRP, IGFBP-2, Interleukin-3, Interleukin-8, PARC, Serotransferrin, THP, TLSP 1-309, and TN-C), and which yielded an AUC of 0.91, accuracy of 0.91, sensitivity of 0.84, and specificity of 0.98 for predicting the risk of MCI patients converting to dementia due to AD in a horizon of up to four years. CONCLUSION: The proposed machine learning model was able to accurately predict the risk of MCI patients converting to dementia due to AD in a horizon of up to four years, suggesting that this model could be used as a minimum-invasive tool for clinical decision support. Further studies are needed to better clarify the possible pathophysiological links with the reported proteins.

Obesity-Associated Neurodegeneration Pattern Mimics Alzheimer's Disease in an Observational Cohort Study. - Morys, Filip; Potvin, Olivier; Zeighami, Yashar; Vogel, Jacob; Lamontagne-Caron, Rémi; Duchesne, Simon; Dagher, Alain (J Alzheimers Dis, 2022)
BACKGROUND: Excess weight in adulthood leads to health complications such as diabetes, hypertension, or dyslipidemia. Recently, excess weight has also been related to brain atrophy and cognitive decline. Reports show that obesity is linked with Alzheimer's disease (AD)-related changes, such as cerebrovascular damage or amyloid-β accumulation. However, to date no research has conducted a direct comparison between brain atrophy patterns in AD and obesity. OBJECTIVE: Here, we compared patterns of brain atrophy and amyloid-β/tau protein accumulation in obesity and AD using a sample of over 1,300 individuals from four groups: AD patients, healthy controls, obese otherwise healthy individuals, and lean individuals. METHODS: We age- and sex-matched all groups to the AD-patients group and created cortical thickness maps of AD and obesity. This was done by comparing AD patients with healthy controls, and obese individuals with lean individuals. We then compared the AD and obesity maps using correlation analyses and permutation-based tests that account for spatial autocorrelation. Similarly, we compared obesity and AD brain maps with amyloid-β and tau protein maps from other studies. RESULTS: Obesity maps were highly correlated with AD maps but were not correlated with amyloid-β/tau protein maps. This effect was not accounted for by the presence of obesity in the AD group. CONCLUSION: Our research confirms that obesity-related grey matter atrophy resembles that of AD. Excess weight management could lead to improved health outcomes, slow down cognitive decline in aging, and lower the risk for AD.

The Outcome of Patients with Amyloid-Negative Amnestic Mild Cognitive Impairment. - Cardoso, Sandra; Silva, Dina; Alves, Luísa; Guerreiro, Manuela; Mendonça, Alexandre de (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) are usually at an initial stage of Alzheimer's disease (AD). However, some patients with aMCI do not present biomarkers of amyloid pathology characteristic of AD. The significance of amyloid-negative aMCI is not presently clear. OBJECTIVE: To know the etiology and prognosis of amyloid-negative aMCI. METHODS: Patients who fulfilled criteria for aMCI and were amyloid negative were selected from a large cohort of non-demented patients with cognitive complaints and were followed with clinical and neuropsychological assessments. RESULTS: Few amyloid-negative aMCI had evidence of neurodegeneration at the baseline, as reflected in cerebrospinal fluid elevated tau protein levels. About half of the patients remained essentially stable for long periods of time. Others manifested a psychiatric disorder that was not apparent at baseline, namely major depression or bipolar disorder. Remarkably, about a quarter of patients developed neurodegenerative disorders other than AD, mostly frontotemporal dementia or Lewy body disease. CONCLUSION: Amyloid-negative aMCI is a heterogeneous condition. Many patients remain clinically stable, but others may later manifest psychiatric conditions or evolve to neurodegenerative disorders. Prudence is needed when communicating to the patient and family the results of biomarkers, and clinical follow-up should be advised.

Plasma Cholesterol Levels as Potential Nutritional Biomarkers for Lewy Body Dementia. - Dou, Yuchao; Liu, Shuai; Li, Yuqing; Wu, Hao; Chen, Hui; Ji, Yong (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between cholesterol level and the risk of developing Alzheimer's disease has been well established, but the relationship between cholesterol level and Lewy body dementia (LBD) is still not well known. OBJECTIVE: The aim of this case-control study was to explore the association between blood cholesterol levels and LBD in Chinese older adults. METHODS: A total of 65 patients with LBD and 110 older adult controls were enrolled during the study period. The levels of triglyceride, total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and fasting glucose were measured separately. The associations between LBD, blood cholesterol levels, and fasting glucose levels were assessed using multiple binary logistic regression analyses adjusted for multiple covariates. RESULTS: Increased plasma LDL-C levels and lower HDL-C levels were independently associated with the risk of LBD in models adjusted for age, sex, education, alcohol use status, smoking status, and vascular disorders. Higher fasting glucose levels may be associated with the risk of LBD. CONCLUSION: The results of this study suggest that elevated levels of LDL-C and reduced levels of HDL-C were associated with LBD development and therefore are potential nutritional risk factors for LBD. Adjusting diet and individualized and effective cholesterol-lowering therapy in high-risk adults may aid in the prevention or management of LBD.

Plasma Myeloperoxidase as a Potential Biomarker of Patient Response to Anti-Dementia Treatment in Alzheimer's Disease. - Wright, Joy R; Deen, Quazi Fahm E; Stevenson, Anna; Telford-Cooke, Leolie; Parker, Craig; Martin-Ruiz, Carmen; Steinert, Joern R; Kalaria, Raj N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2022)
BACKGROUND: Myeloperoxidase (MPO), a neutrophil-derived pro-inflammatory protein, co-localizes with amyloid-β (Aβ) plaques in Alzheimer's disease (AD). Anti-dementia treatment may facilitate efflux of Aβ and associated plaque proteins from the brain to the peripheral circulation, therefore providing potential biomarkers for the monitoring of donor response to drug treatment. OBJECTIVE: We investigated the diagnostic utility of MPO as a biomarker of AD, and how anti-dementia treatment alters plasma MPO concentration. METHODS: Thirty-two AD patients were recruited, and plasma collected pre-drug administration (baseline), and 1- and 6-months post-treatment. All patients received cholinesterase inhibitors (ChEIs). At baseline and 6 months, patients underwent neuropsychological assessment. Forty-nine elderly healthy individuals with normal cognitive status served as controls. Plasma MPO concentration was measured by ELISA. RESULTS: AD drug naïve patients had similar plasma MPO concentration to their control counterparts (p >  0.05). Baseline MPO levels positively correlated with Neuropsychiatric Inventory score (r = 0.5080; p = 0.011) and carer distress (r = 0.5022; p = 0.012). Following 1-month ChEI treatment, 84.4% of AD patients exhibited increased plasma MPO levels (p <  0.001), which decreased at 6 months (p <  0.001). MPO concentration at 1 month was greatest in AD patients whose memory deteriorated during the study period (p = 0.028), and for AD patients with deterioration in Cornell assessment score (p = 0.044). CONCLUSION: Whereas baseline MPO levels did not differentiate between healthy and AD populations, baseline MPO positively correlated with initial Neuropsychiatric Inventory evaluation. Post-treatment, transient MPO upregulation in ChEI-treated patients may reflect worse therapeutic outcome. Further studies are required to assess the potential of plasma MPO as an AD therapeutic biomarker.

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Potential Mechanisms Underlying Resistance to Dementia in Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Kok, Frédérique K; van Leerdam, Suzanne L; de Lange, Elizabeth C M (J Alzheimers Dis, 2022)
Alzheimer's disease (AD) is the most common form of dementia and typically characterized by the accumulation of amyloid-β plaques and tau tangles. Intriguingly, there also exists a group of elderly which do not develop dementia during their life, despite the AD neuropathology, the so-called non-demented individuals with AD neuropathology (NDAN). In this review, we provide extensive background on AD pathology and normal aging and discuss potential mechanisms that enable these NDAN individuals to remain cognitively intact. Studies presented in this review show that NDAN subjects are generally higher educated and have a larger cognitive reserve. Furthermore, enhanced neural hypertrophy could compensate for hippocampal and cingulate neural atrophy in NDAN individuals. On a cellular level, these individuals show increased levels of neural stem cells and 'von Economo neurons'. Furthermore, in NDAN brains, binding of Aβ oligomers to synapses is prevented, resulting in decreased glial activation and reduced neuroinflammation. Overall, the evidence stated here strengthens the idea that some individuals are more resistant to AD pathology, or at least show an elongation of the asymptomatic state of the disease compared to others. Insights into the mechanisms underlying this resistance could provide new insight in understanding normal aging and AD itself. Further research should focus on factors and mechanisms that govern the NDAN cognitive resilience in order to find clues on novel biomarkers, targets, and better treatments of AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Hippocampus; Humans; Plaque, Amyloid; Synapses

Pre-Diagnostic Symptoms of Young-Onset Dementia in the General Practice up to Five Years Before Diagnosis. - Hendriks, Stevie; Peetoom, Kirsten; Tange, Huibert; van Bokhoven, Marloes A; van der Flier, Wiesje M; Bakker, Christian; Papma, Janne M; Koopmans, Raymond; Verhey, Frans; Köhler, Sebastian; de Vugt, Marjolein (J Alzheimers Dis, 2022)
BACKGROUND: Young-onset dementia (YOD) has many underlying etiologies, leading to a large heterogeneity in first symptoms. This makes it difficult for general practitioners (GPs) to recognize YOD. OBJECTIVE: Identify early symptoms that are more common in the pre-diagnostic phase of YOD. METHODS: We performed a case-control study nested in a primary-care registry on 89 cases and 162 matched controls, where we compared symptoms of people with YOD up to 5 years before diagnosis to their matched control group without YOD. The variables included in this study were International Classification of Primary Care codes and symptoms extracted from written GP notes and categorized in groups. We used Generalized Equation Estimation to analyze symptom's time-trajectories and logistic regression and ROC-curves to analyze differences in number of symptom categories reported. RESULTS: Cognitive symptoms were more common in people with YOD 5 years before diagnosis, affective symptoms 4 years before diagnosis, social symptoms 3 years, behavioral symptoms 2 years, and daily functioning disturbances 1 year before diagnosis. The ROC-curve suggested that reporting two or more symptom categories at the GP gave the best trade-off between sensitivity (85%) and specificity (77% ), for the highest percentage of correctly diagnosed persons. CONCLUSION: This study showed people with YOD present differently than people without YOD. However, it may still be difficult for GPs to use these symptom categories to distinguish people with YOD, since the symptoms also occur in people with other diseases. A combination of reported symptom categories increases the probability of an underlying cause of YOD.

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

The Role of Amyloid, Tau, and APOE Genotype on the Relationship Between Informant-Reported Sleep Disturbance and Alzheimer's Disease Risks. - Kim, Hyun; Levine, Alina; Cohen, Daniel; Gehrman, Philip; Zhu, Xi; Devanand, Davangere P; Lee, Seonjoo; Goldberg, Terry E (J Alzheimers Dis, 2022)
BACKGROUND: The association between sleep and Alzheimer's disease (AD) biomarkers are well-established, but little is known about how they interact to change the course of AD. OBJECTIVE: To determine the potential interaction between sleep disturbance and Aβ, tau, and APOE4 on brain atrophy and cognitive decline. METHODS: Sample included 351 participants (mean age 72.01 ± 6.67, 50.4%female) who were followed for approximately 5 years as part of the Alzheimer's Disease Neuroimaging Initiative. Informant-reported sleep disturbance (IRSD) was measured using the Neuropsychiatric Inventory (NPI). Changes in magnetic resonance imaging (MRI)-measured AD signature brain regions and cognitive performance and IRSD's interaction with cerebrospinal fluid amyloid-β (Aβ42) and p-Tau depositions and APOE4 status were examined using the linear mixed models. RESULTS: Baseline IRSD was not significantly associated with the rate of atrophy after adjusting for covariates (age, sex, education, total NPI severity score, and sleep medications). However, there was a significant interaction between IRSD and AD biomarkers on faster atrophy rates in multiple brain regions, including the cortical and middle temporal volumes. Post-hoc analyses indicated that Aβ and p-Tau/Aβ predicted a faster decline in these regions/domains in IRSD, compared with biomarker-negative individuals with IRSD (ps≤0.001). There was a significant IRSD*APOE4 interaction for brain atrophy rate (ps≤0.02) but not for cognition. CONCLUSION: IRSD may increase the future risk of AD by contributing to faster brain atrophy and cognitive decline when combined with the presence of AD biomarkers and APOE4. Early intervention for sleep disturbance could help reduce the risk of developing AD.

The Role of Amyloid-β, Tau, and α-Synuclein Proteins as Putative Blood Biomarkers in Patients with Cerebral Amyloid Angiopathy. - Piccarducci, Rebecca; Caselli, Maria Chiara; Zappelli, Elisa; Ulivi, Leonardo; Daniele, Simona; Siciliano, Gabriele; Ceravolo, Roberto; Mancuso, Michelangelo; Baldacci, Filippo; Martini, Claudia (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is a cerebrovascular disorder characterized by the deposition of amyloid-β protein (Aβ) within brain blood vessels that develops in elderly people and Alzheimer's disease (AD) patients. Therefore, the investigation of biomarkers able to differentiate CAA patients from AD patients and healthy controls (HC) is of great interest, in particular in peripheral fluids. OBJECTIVE: The current study aimed to detect the neurodegenerative disease (ND)-related protein (i.e., Aβ 1 - 40, Aβ 1 - 42, tau, and α-synuclein) levels in both red blood cells (RBCs) and plasma of CAA patients and HC, evaluating their role as putative peripheral biomarkers for CAA. METHODS: For this purpose, the proteins' concentration was quantified in RBCs and plasma by homemade immunoenzymatic assays in an exploratory cohort of 20 CAA patients and 20 HC. RESULTS: The results highlighted a significant increase of Aβ 1 - 40 and α-synuclein concentrations in both RBCs and plasma of CAA patients, while higher Aβ 1 - 42 and t-tau levels were detected only in RBCs of CAA individuals compared to HC. Moreover, Aβ 1 - 42/Aβ 1 - 40 ratio increased in RBCs and decreased in plasma of CAA patients. The role of these proteins as candidate peripheral biomarkers easily measurable with a blood sample in CAA needs to be confirmed in larger studies. CONCLUSION: In conclusion, we provide evidence concerning the possible use of blood biomarkers for contributing to CAA diagnosis and differentiation from other NDs.

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Positive Modulator of HGF/MET, Fosgonimeton, in Healthy Volunteers and Subjects with Alzheimer's Disease: Randomized, Placebo-Controlled, Double-Blind, Phase I Clinical Trial. - Hua, Xue; Church, Kevin; Walker, William; L'Hostis, Philippe; Viardot, Geoffrey; Danjou, Philippe; Hendrix, Suzanne; Moebius, Hans J (J Alzheimers Dis, 2022)
BACKGROUND: Fosgonimeton (ATH-1017) is being developed as a first-in-class regenerative therapy for people with Alzheimer's disease (AD) and dementia; potentially improving dementia symptoms and altering disease progression by reversing synaptic disconnection and neuronal loss. OBJECTIVE: This randomized, double-blind, placebo-controlled phase I trial (NCT03298672) evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of fosgonimeton. METHODS: Fosgonimeton was administered once daily via subcutaneous injection to 88 subjects. The single ascending dose study enrolled healthy young male subjects (n = 48; age, 33.4±6.3 years; dose, 2, 6, 20, 40, 60, or 90 mg); the multiple ascending dose study enrolled healthy elderly subjects (n = 29; age, 63.8±4.0 years; dose, 20, 40, 60, or 80 mg; 9-day duration); and the fixed-dose study enrolled AD subjects (n = 11; age, 69.2±7.1 years; dose, 40 mg; 9-day duration). Quantitative electroencephalogram (qEEG) and event-related potential (ERP) P300 measured neurophysiological signals following fosgonimeton treatment, supporting brain penetration and target engagement. RESULTS: Fosgonimeton and placebo were shown to be safe and well-tolerated across all doses. Pharmacokinetic results for fosgonimeton were dose-proportional, with no sex effect or accumulation over 9 days. The main effect of fosgonimeton on qEEG was acute and sustained gamma power induction. In AD subjects, there was a significant effect toward ERP P300 latency normalization compared with placebo (p = 0.027; n = 7 at 40 mg fosgonimeton versus n = 4 placebo). CONCLUSION: These results support the continued development of fosgonimeton as a novel therapeutic for people with AD and dementia. The fast-onset normalization of ERP P300 latency in AD subjects suggests enhancement of synaptic function and potential procognitive effects.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Dose-Response Relationship, Drug; Double-Blind Method; Healthy Volunteers; Hepatocyte Growth Factor; Humans; Male

Salivary Proteomics Reveals Significant Changes in Relation to Alzheimer's Disease and Aging. - Contini, Cristina; Serrao, Simone; Manconi, Barbara; Olianas, Alessandra; Iavarone, Federica; Bizzarro, Alessandra; Masullo, Carlo; Castagnola, Massimo; Messana, Irene; Diaz, Giacomo; Cabras, Tiziana (J Alzheimers Dis, 2022)
BACKGROUND: Aging is a risk factor for several pathologies as Alzheimer's disease (AD). Great interest exists, therefore, in discovering diagnostic biomarkers and indicators discriminating biological aging and health status. To this aim, omic investigations of biological matrices, as saliva, whose sampling is easy and non-invasive, offer great potential. OBJECTIVE: Investigate the salivary proteome through a statistical comparison of the proteomic data by several approaches to highlight quali-/quantitative variations associated specifically either to aging or to AD occurrence, and, thus, able to classify the subjects. METHODS: Salivary proteomic data of healthy controls under-70 (adults) and over-70 (elderly) years old, and over-70 AD patients, obtained by liquid chromatography/mass spectrometry, were analyzed by multiple Mann-Whitney test, Kendall correlation, and Random-Forest (RF) analysis. RESULTS: Almost all the investigated proteins/peptides significantly decreased in relation to aging in elderly subjects, with or without AD, in comparison with adults. AD subjects exhibited the highest levels of α-defensins, thymosin β4, cystatin B, S100A8 and A9. Correlation tests also highlighted age/disease associated differences. RF analysis individuated quali-/quantitative variations in 20 components, as oxidized S100A8 and S100A9, α-defensin 3, P-B peptide, able to classify with great accuracy the subjects into the three groups. CONCLUSION: The findings demonstrated a strong change of the salivary protein profile in relation to the aging. Potential biomarkers candidates of AD were individuated in peptides/proteins involved in antimicrobial defense, innate immune system, inflammation, and in oxidative stress. RF analysis revealed the feasibility of the salivary proteome to discriminate groups of subjects based on age and health status.

Single Nucleus Transcriptome Data from Alzheimer's Disease Mouse Models Yield New Insight into Pathophysiology. - Weller, Andrew E; Ferraro, Thomas N; Doyle, Glenn A; Reiner, Benjamin C; Crist, Richard C; Berrettini, Wade H (J Alzheimers Dis, 2022)
BACKGROUND: 5XFAD humanized mutant mice and Trem2 knockout (T2KO) mice are two mouse models relevant to the study of Alzheimer's disease (AD)-related pathology. OBJECTIVE: To determine hippocampal transcriptomic and polyadenylation site usage alterations caused by genetic mutations engineered in 5XFAD and T2KO mice. METHODS: Employing a publicly available single-nucleus RNA sequencing dataset, we used Seurat and Sierra analytic programs to identify differentially expressed genes (DEGs) and differential transcript usage (DTU), respectively, in hippocampal cell types from each of the two mouse models. We analyzed cell type-specific DEGs further using Ingenuity Pathway Analysis (IPA). RESULTS: We identified several DEGs in both neuronal and glial cell subtypes in comparisons of wild type (WT) versus 5XFAD and WT versus T2KO mice, including Ttr, Fth1, Pcsk1n, Malat1, Rpl37, Rtn1, Sepw1, Uba52, Mbp, Arl6ip5, Gm26917, Vwa1, and Pgrmc1. We also observed DTU in common between the two comparisons in neuronal and glial subtypes, specifically in the genes Prnp, Rbm4b, Pnisr, Opcml, Cpne7, Adgrb1, Gabarapl2, Ubb, Ndfip1, Car11, and Stmn4. IPA identified 3 statistically significant canonical pathways that appeared in multiple cell types and that overlapped between 5XFAD and T2KO comparisons to WT, including 'FXR/RXR Activation', 'LXR/RXR Activation', and 'Acute Phase Response Signaling'. CONCLUSION: DEG, DTU, and IPA findings, derived from two different mouse models of AD, highlight the importance of energy imbalance and inflammatory processes in specific hippocampal cell types, including subtypes of neurons and glial cells, in the development of AD-related pathology. Additional studies are needed to further characterize these findings.

The Spectrum of Alzheimer-Type Pathology in Cognitively Normal Individuals. - Walker, Jamie M; Dehkordi, Shiva Kazempour; Schaffert, Jeff; Goette, William; White Iii, Charles L; Richardson, Timothy E; Zare, Habil (J Alzheimers Dis, 2022)
BACKGROUND: The strongest risk factor for the development of Alzheimer's disease (AD) is age. The progression of Braak stage and Thal phase with age has been demonstrated. However, prior studies did not include cognitive status. OBJECTIVE: We set out to define normative values for Alzheimer-type pathologic changes in individuals without cognitive decline, and then define levels that would qualify them to be resistant to or resilient against these changes. METHODS: Utilizing neuropathology data obtained from the National Alzheimer's Coordinating Center (NACC), we demonstrate the age-related progression of Alzheimer-type pathologic changes in cognitively normal individuals (CDR = 0, n = 542). With plots generated from these data, we establish standard lines that may be utilized to measure the extent to which an individual's Alzheimer-type pathology varies from the estimated normal range of pathology. RESULTS: Although Braak stage and Thal phase progressively increase with age in cognitively normal individuals, the Consortium to Establish a Registry for Alzheimer's Disease neuritic plaque score and Alzheimer's disease neuropathologic change remain at low levels. CONCLUSION: These findings suggest that an increasing burden of neuritic plaques is a strong predictor of cognitive decline, whereas, neurofibrillary degeneration and amyloid-β (diffuse) plaque deposition, both to some degree, are normal pathologic changes of aging that occur in almost all individuals regardless of cognitive status. Furthermore, we have defined the amount of neuropathologic change in cognitively normal individuals that would qualify them to be "resilient" against the pathology (significantly above the normative values for age, but still cognitively normal) or "resistant" to the development of pathology (significantly below the normative values for age).

Visually Identified Tau 18F-MK6240 PET Patterns in Symptomatic Alzheimer's Disease. - Krishnadas, Natasha; Huang, Kun; Schultz, Stephanie A; Doré, Vincent; Bourgeat, Pierrick; Goh, Anita M Y; Lamb, Fiona; Bozinovski, Svetlana; Burnham, Samantha C; Robertson, Joanne S; Laws, Simon M; Maruff, Paul; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease, heterogeneity has been observed in the postmortem distribution of tau neurofibrillary tangles. Visualizing the topography of tau in vivo may facilitate clinical trials and clinical practice. OBJECTIVE: This study aimed to investigate whether tau distribution patterns that are limited to mesial temporal lobe (MTL)/limbic regions, and those that spare MTL regions, can be visually identified using 18F-MK6240, and whether these patterns are associated with different demographic and cognitive profiles. METHODS: Tau 18F-MK6240 PET images of 151 amyloid-β positive participants with mild cognitive impairment (MCI) and dementia were visually rated as: tau negative, limbic predominant (LP), MTL-sparing, and Typical by two readers. Groups were evaluated for differences in age, APOE ɛ4 carriage, hippocampal volumes, and cognition (MMSE, composite memory and non-memory scores). Voxel-wise contrasts were also performed. RESULTS: Visual rating resulted in 59.6% classified as Typical, 17.9% as MTL-sparing, 9.9% LP, and 12.6% as tau negative. Intra-rater and inter-rater reliability was strong (Cohen's kappa values of 0.89 and 0.86 respectively). Tracer retention in a "hook"-like distribution on sagittal sequences was observed in the LP and Typical groups. The visually classified MTL-sparing group had lower APOE ɛ4 carriage and relatively preserved hippocampal volumes. Higher MTL tau was associated with greater amnestic cognitive impairment. High cortical tau was associated with greater impairments on non-memory domains of cognition, and individuals with high cortical tau were more likely to have dementia than MCI. CONCLUSION: Tau distribution patterns can be visually identified using 18F-MK6240 PET and are associated with differences in APOE ɛ4 carriage, hippocampal volumes, and cognition.

Accelerometer-Measured, Habitual Physical Activity and Circulating Brain-Derived Neurotrophic Factor: A Cross-Sectional Study. - Spartano, Nicole L; Himali, Jayandra J; Trinquart, Ludovic; Yang, Qiong; Weinstein, Galit; Satizabal, Claudia L; Dukes, Kimberly A; Beiser, Alexa S; Murabito, Joanne M; Vasan, Ramachandran S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: One of the mechanisms suggested to link physical activity (PA) to favorable brain health is through stimulation of neural growth factors such as brain-derived neurotrophic factor (BDNF). Acute bouts of PA stimulate circulating BDNF levels. OBJECTIVE: In this investigation, we assessed whether habitual, accelerometer-measured PA levels were related to circulating BDNF levels in a middle-aged cohort. METHODS: In the Framingham Heart Study Third Generation cohort, 1,769 participants provided reliable accelerometry data and were not missing BDNF measurement and platelet counts. In a cross-sectional analysis, using multivariable regression, we related PA measures to serum BDNF levels, adjusting for age, sex, smoking status, platelet count, depression status, and accelerometer wear time. RESULTS: Our study participants (mean age 47±9 years, 50.8% women) spent an average of 22.3 mins/day moderate-to-vigorous (MV)PA. Most PA variables (steps, MVPA, light activity, and sedentary time) were not related to BDNF levels (p > 0.05). We observed a non-linear trend, where 15-50 mins/week vigorous activity was associated with lower BDNF compared to those with 0 min vigorous activity (β= -0.049±0.024, p = 0.05), but with no significant associations at lower or higher vigorous activity levels. In smokers, MVPA was also associated with lower BDNF levels (β= -0.216±0.079, p = 0.01). CONCLUSION: Our study reveals that circulating BDNF is not chronically elevated in individuals with higher levels of habitual PA in middle-aged adults from the community and may even be chronically suppressed with higher PA in subgroups, including current smokers. These results do not contradict previous studies demonstrating that circulating BDNF rises acutely after PA.

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Apolipoprotein E ɛ4 (APOE ɛ4) Allele is Associated with Long Sleep Duration Among Elderly with Cognitive Impairment. - Basta, Maria; Zaganas, Ioannis; Simos, Panagiotis; Koutentaki, Eirini; Dimovasili, Christina; Mathioudakis, Lambros; Bourbouli, Mara; Panagiotakis, Symeon; Kapetanaki, Stefania; Vgontzas, Alexandros (J Alzheimers Dis, 2021)
BACKGROUND: Apolipoprotein E gene (APOE) ɛ4 allele increases the risk for Alzheimer's disease (AD). Furthermore, among patients with cognitive impairment, longer sleep duration is associated with worse cognitive performance. To date, literature examining the associations between APOE ɛ4 allele and objective sleep duration is limited. OBJECTIVE: Our aim was to assess the association between APOE ɛ4 and objective sleep duration, among patients with mild cognitive impairment (MCI) and AD. A sub-sample of 89 patients with AD (n = 49) and MCI (n = 40) were recruited from a large, population-based cohort of 3,140 elders (>60 years) residing on Crete, Greece. METHODS: All participants underwent medical history/physical examination, extensive neuropsychiatric and neuropsychological evaluation, 3-day 24 h actigraphy and APOE ɛ4 allele genotyping. Comparisons of sleep duration variables between APOE ɛ4 allele carriers and non-carriers were assessed using ANCOVA, controlling for confounders. RESULTS: The sample included 18 APOE ɛ4 carriers and 71 non-carriers, aged 78.6±6.6 and 78.2±6.5 years, respectively. Comparisons between the APOE ɛ4 carriers and non-carriers revealed no significant differences in terms of demographic and clinical variables. In terms of objective sleep duration across the two groups, APOE ɛ4 carriers compared to non-carriers had significantly longer nighttime Total Sleep Time (nTST) (7.7±1.4 versus 7.2±1.3  h, respectively, p = 0.011), as well as 24 h TST (8.5±1.6 versus 7.8±1.5  h, respectively, p = 0.012). CONCLUSION: Among patients with MCI and AD, APOE ɛ4 carriers have longer objective nighttime and 24 h sleep duration compared to non-carriers. These findings further support that objective long sleep duration is a genetically-driven pre-clinical marker associated with worse prognosis in elderly with cognitive impairment.

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

B Vitamins Prevent Iron-Associated Brain Atrophy and Domain-Specific Effects of Iron, Copper, Aluminum, and Silicon on Cognition in Mild Cognitive Impairment. - Jakubowski, Hieronim; Zioła-Frankowska, Anetta; Frankowski, Marcin; Perła-Kaján, Joanna; Refsum, Helga; de Jager, Celeste A; Smith, A David (J Alzheimers Dis, 2021)

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Blood-Based ATN Biomarkers of Alzheimer's Disease: A Meta-Analysis. - Koychev, Ivan; Jansen, Katrin; Dette, Alina; Shi, Liu; Holling, Heinz (J Alzheimers Dis, 2021)
BACKGROUND: The Amyloid Tau Neurodegeneration (ATN) framework was proposed to define the biological state underpinning Alzheimer's disease (AD). Blood-based biomarkers offer a scalable alternative to the costly and invasive currently available biomarkers. OBJECTIVE: In this meta-analysis we sought to assess the diagnostic performance of plasma amyloid (Aβ40, Aβ42, Aβ42/40 ratio), tangle (p-tau181), and neurodegeneration (total tau [t-tau], neurofilament light [NfL]) biomarkers. METHODS: Electronic databases were screened for studies reporting biomarker concentrations for AD and control cohorts. Biomarker performance was examined by random-effect meta-analyses based on the ratio between biomarker concentrations in patients and controls. RESULTS: 83 studies published between 1996 and 2020 were included in the analyses. Aβ42/40 ratio as well as Aβ42 discriminated AD patients from controls when using novel platforms such as immunomagnetic reduction (IMR). We found significant differences in ptau-181 concentration for studies based on single molecule array (Simoa), but not for studies based on IMR or ELISA. T-tau was significantly different between AD patients and control in IMR and Simoa but not in ELISA-based studies. In contrast, NfL differentiated between groups across platforms. Exosome studies showed strong separation between patients and controls for Aβ42, t-tau, and p-tau181. CONCLUSION: Currently available assays for sampling plasma ATN biomarkers appear to differentiate between AD patients and controls. Novel assay methodologies have given the field a significant boost for testing these biomarkers, such as IMR for Aβ, Simoa for p-tau181. Enriching samples through extracellular vesicles shows promise but requires further validation.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurodegenerative Diseases; Neurofibrillary Tangles; Neurofilament Proteins; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

Central Obesity, Cardiometabolic Risk, and Cognitive Change in the Study of Latinos: Investigation of Neurocognitive Aging. - Stickel, Ariana M; Tarraf, Wassim; Gonzalez, Kevin A; Isasi, Carmen R; Kaplan, Robert; Gallo, Linda C; Zeng, Donglin; Cai, Jianwen; Pirzada, Amber; Daviglus, Martha L; Goodman, Zachary T; Schneiderman, Neil; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The relationships between obesity and cognitive decline in aging are mixed and understudied among Hispanics/Latinos. OBJECTIVE: To understand associations between central obesity, cognitive aging, and the role of concomitant cardiometabolic abnormalities among Hispanics/Latinos. METHODS: Participants included 6,377 diverse Hispanics/Latinos enrolled in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and SOL-Investigation for Neurocognitive Aging (SOL-INCA). Participants were 45 years and older at the first cognitive testing session (Visit 1). Cognitive outcomes (z-score units) included global composite and domain specific (learning, memory, executive functioning, processing speed) measures at a second visit (SOL-INCA, on average, 7 years later), and 7-year change. We used survey linear regression to examine associations between central obesity (waist circumference≥88 cm and≥102 cm for women and men, respectively) and cognition. We also tested whether the relationships between obesity and cognition differed by cardiometabolic status (indication of/treatment for 2 + of the following: high triglycerides, hypertension, hyperglycemia, low high-density lipoprotein cholesterol). RESULTS: Central obesity was largely unassociated with cognitive outcomes, adjusting for covariates. However, among individuals with central obesity, cardiometabolic abnormality was linked to poorer cognitive function at SOL-INCA (ΔGlobalCognition =-0.165, p < 0.001) and to more pronounced cognitive declines over the average 7 years (ΔGlobalCognition = -0.109, p < 0.05); this was consistent across cognitive domains. CONCLUSION: Central obesity alone was not associated with cognitive function. However, presence of both central obesity and cardiometabolic abnormalities was robustly predictive of cognition and 7-year cognitive declines, suggesting that in combination these factors may alter the cognitive trajectories of middle-aged and older Hispanics/Latinos.

Cerebrospinal Fluid Proteome Changes in Older Non-Cardiac Surgical Patients with Postoperative Cognitive Dysfunction. - VanDusen, Keith W; Li, Yi-Ju; Cai, Victor; Hall, Ashley; Hiles, Sarah; Thompson, J Will; Moseley, M Arthur; Cooter, Mary; Acker, Leah; Levy, Jerrold H; Ghadimi, Kamrouz; Quiñones, Quintin J; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Postoperative cognitive dysfunction (POCD), a syndrome of cognitive deficits occurring 1-12 months after surgery primarily in older patients, is associated with poor postoperative outcomes. POCD is hypothesized to result from neuroinflammation; however, the pathways involved remain unclear. Unbiased proteomic analyses have been used to identify neuroinflammatory pathways in multiple neurologic diseases and syndromes but have not yet been applied to POCD. OBJECTIVE: To utilize unbiased mass spectrometry-based proteomics to identify potential neuroinflammatory pathways underlying POCD. METHODS: Unbiased LC-MS/MS proteomics was performed on immunodepleted cerebrospinal fluid (CSF) samples obtained before, 24 hours after, and 6 weeks after major non-cardiac surgery in older adults who did (n = 8) or did not develop POCD (n = 6). Linear mixed models were used to select peptides and proteins with intensity differences for pathway analysis. RESULTS: Mass spectrometry quantified 8,258 peptides from 1,222 proteins in > 50%of patient samples at all three time points. Twelve peptides from 11 proteins showed differences in expression over time between patients with versus withoutPOCD (q < 0.05), including proteins previously implicated in neurodegenerative disease pathophysiology. Additionally, 283 peptides from 182 proteins were identified with trend-level differences (q < 0.25) in expression over time between these groups. Among these, pathway analysis revealed that 50 were from 17 proteins mapping to complement and coagulation pathways (q = 2.44*10-13). CONCLUSION: These data demonstrate the feasibility of performing unbiased mass spectrometry on perioperative CSF samples to identify pathways associated with POCD. Additionally, they provide hypothesis-generating evidence for CSF complement and coagulation pathway changes in patients with POCD.

Cognitive Effects of Aerobic Exercise in Alzheimer's Disease: A Pilot Randomized Controlled Trial. - Yu, Fang; Vock, David M; Zhang, Lin; Salisbury, Dereck; Nelson, Nathaniel W; Chow, Lisa S; Smith, Glenn; Barclay, Terry R; Dysken, Maurice; Wyman, Jean F (J Alzheimers Dis, 2021)
BACKGROUND: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer's disease (AD) dementia. OBJECTIVE: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. METHODS: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20-50 minutes, 3 times a week for six months. The control was light-intensity stretching. Cognition was assessed at baseline, 3, 6, 9, and 12 months using the AD Assessment Scale-Cognition (ADAS-Cog). Discrete cognitive domains were measured using the AD Uniform Data Set battery. RESULTS: The participants were 77.4±6.8 years old with 15.6±2.9 years of education, and 55%were male. The 6-month change in ADAS-Cog was 1.0±4.6 (cycling) and 0.1±4.1 (stretching), which were both significantly less than the natural 3.2±6.3-point increase observed naturally with disease progression. The 12-month change was 2.4±5.2 (cycling) and 2.2±5.7 (control). ADAS-Cog did not differ between groups at 6 (p = 0.386) and 12 months (p = 0.856). There were no differences in the 12-month rate of change in ADAS-Cog (0.192 versus 0.197, p = 0.967), memory (-0.012 versus -0.019, p = 0.373), executive function (-0.020 versus -0.012, p = 0.383), attention (-0.035 versus -0.033, p = 0.908), or language (-0.028 versus -0.026, p = 0.756). CONCLUSION: Exercise may reduce decline in global cognition in older adults with mild-to-moderate AD dementia. Aerobic exercise did not show superior cognitive effects to stretching in our pilot trial, possibly due to the lack of power.

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Could Altered Evoked Pain Responsiveness Be a Phenotypic Biomarker for Alzheimer's Disease Risk? A Cross-Sectional Analysis of Cognitively Healthy Individuals. - Romano, Raymond R; Carter, Michael A; Dietrich, Mary S; Cowan, Ronald L; Bruehl, Stephen P; Monroe, Todd B (J Alzheimers Dis, 2021)
BACKGROUND: This study evaluated whether the apolipoprotein ɛ4 (APOE4) allele, a genetic marker associated with increased risk of developing late-onset Alzheimer's disease (AD), was associated with differences in evoked pain responsiveness in cognitively healthy subjects. OBJECTIVE: The aim was to determine whether individuals at increased risk of late-onset AD based on APOE allele genotype differ phenotypically in their response to experimentally-induced painful stimuli compared to those who do not have at least one copy of the ɛ4 allele. METHODS: Forty-nine cognitively healthy subjects aged 30-89 years old with the APOE4 allele (n = 12) and without (n = 37) were assessed for group differences in pain thresholds and affective (unpleasantness) responses to experimentally-induced thermal pain stimuli. RESULTS: Statistically significant main effects of APOE4 status were observed for both the temperature at which three different pain intensity percepts were reached (p = 0.040) and the level of unpleasantness associated with each (p = 0.014). APOE4 positive participants displayed lower overall pain sensitivity than those who were APOE4 negative and also greater overall levels of pain unpleasantness regardless of intensity level. CONCLUSION: Cognitively healthy APOE4 carriers at increased risk of late-onset AD demonstrated reduced thermal pain sensitivity but greater unpleasantness to thermal pain stimuli relative to individuals at lower risk of late-onset AD. These results suggest that altered evoked pain perception could potentially be used as a phenotypic biomarker of late-onset AD risk prior to disease onset. Additional studies of this issue may be warranted.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cross-Sectional Studies; Female; Genetic Association Studies; Hot Temperature; Humans; Male; Middle Aged; Pain Perception; Phenotype; Risk Factors

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers' Poor Mental Health. - Pongan, Elodie; Dorey, Jean-Michel; Borg, Céline; Getenet, Jean Claude; Bachelet, Romain; Lourioux, Charles; Laurent, Bernard; Rey, Romain; Rouch, Isabelle (J Alzheimers Dis, 2021)
BACKGROUND: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers' mental health, the two being linked. OBJECTIVE: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psychological symptoms of dementia (BPSD) and caregivers' mental health in the context of COVID-19. METHODS: The study was conducted among caregivers of PWD living at home in France. Caregivers were interviewed via an anonymous cross-sectional online survey during the first lockdown between April 15 and June 15, 2020. RESULTS: Three hundred and eighty-nine caregivers accompanying a relative living at home participated in the study; 43.3%of the PWD presented a worsening of BPSD during the lockdown. With multivariate logistic regressions, a significant association was observed between "more BPSD" and burden, anxiety and depression, between "BPSD equivalent" and anxiety and depression, and between "emerging BPSD" and only depression. CONCLUSION: The lockdown seems to have an impact on behavioral disorders in PWD and these disorders are associated with poorer mental health of caregivers. Our findings suggest attention should be given to caregivers of PWD who have BPSD before lockdown and the need for continued consultations and professional help in case of new lockdowns.
Keywords: Aged; Aged, 80 and over; Caregivers; Communicable Disease Control; COVID-19; Cross-Sectional Studies; Dementia; Female; France; Humans; Male; Mental Disorders; Mental Health; Middle Aged; Surveys and Questionnaires

Deaths with Dementia in Indigenous and Non-Indigenous Australians: A Nationwide Study. - Waller, Michael; Buckley, Rachel F; Masters, Colin L; Nona, Francis R; Eades, Sandra; Dobson, Annette J (J Alzheimers Dis, 2021)
BACKGROUND: The prevalence of dementia is generally reported to be higher among Indigenous peoples. OBJECTIVE: The rates and coding of dementia mortality were compared between Indigenous and non-Indigenous Australians. METHODS: De-identified individual records on causes of death for all people aged 40 years or more who died in Australia between 2006 and 2014 (n = 1,233,084) were used. There were 185,237 records with International Classification of Diseases, Tenth Revision, codes for dementia (Alzheimer's Disease, vascular dementia, or unspecified dementia) as the underlying cause of death or mentioned elsewhere on the death certificate. Death rates were compared using Poisson regression. Logistic regression was used to assess whether dementia was more likely to be classified as 'unspecified' type in Indigenous Australians. RESULTS: The rates of death with dementia were 57% higher in Indigenous Australians, compared to non-Indigenous, relative rate (RR) 1.57, 95% confidence interval (CI) (1.48, 1.66), p <  0.0001. This excess of deaths was highest at ages below 75 (RRs >  2, test for interaction p <  0.0001), and among men (test for interaction p <  0.0001). When the underreporting of Indigenous status on the death certificate was taken into account the relative rate increased to 2.17, 95% CI (2.07, 2.29). Indigenous Australians were also more likely to have their dementia coded as 'unspecified' on their death certificate (Odds Ratio 1.92, 95% CI (1.66, 2.21), p <  0.0001), compared to the non-Indigenous group. CONCLUSION: This epidemiological analysis based on population level mortality data demonstrates the higher dementia-related mortality rate for Indigenous Australians especially at younger ages.

Deciphering Alzheimer's Disease Pathogenic Pathway: Role of Chronic Brain Hypoperfusion on p-Tau and mTOR. - de la Torre, Jack C (J Alzheimers Dis, 2021)
This review examines new biomolecular findings that lend support to the hemodynamic role played by chronic brain hypoperfusion (CBH) in driving a pathway to Alzheimer's disease (AD). CBH is a common clinical feature of AD and the current topic of intense investigation in AD models. CBH is also the basis for the vascular hypothesis of AD which we originally proposed in 1993. New biomolecular findings reveal the interplay of CBH in increasing tau phosphorylation (p-Tau) in the hippocampus and cortex of AD mice, damaging fast axonal transport, increasing signaling of mammalian target of rapamycin (mTOR), impairing learning-memory function, and promoting the formation of neurofibrillary tangles, a neuropathologic hallmark of AD. These pathologic elements have been singularly linked with neurodegeneration and AD but their abnormal, collective participation during brain aging have not been fully examined. The format for this review will provide a consolidated analysis of each pathologic phase contributing to cognitive decline and AD onset, summarized in nine chronological steps. These steps galvanize each factor's active participation and contribution in constructing a biomolecular pathway to AD onset generated by CBH.

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Diagnosing Mild Cognitive Impairment Among Racially Diverse Older Adults: Comparison of Consensus, Actuarial, and Statistical Methods. - Devlin, Kathryn N; Brennan, Laura; Saad, Laura; Giovannetti, Tania; Hamilton, Roy H; Wolk, David A; Xie, Sharon X; Mechanic-Hamilton, Dawn (J Alzheimers Dis, 2021)
BACKGROUND: Actuarial and statistical methods have been proposed as alternatives to conventional methods of diagnosing mild cognitive impairment (MCI), with the aim of enhancing diagnostic and prognostic validity, but have not been compared in racially diverse samples. OBJECTIVE: We compared the agreement of consensus, actuarial, and statistical MCI diagnostic methods, and their relationship to race and prognostic indicators among diverse older adults. METHODS: Participants (N = 354; M age = 71; 68% White, 29% Black) were diagnosed with MCI or normal cognition (NC) according to clinical consensus, actuarial neuropsychological criteria (Jak/Bondi), and latent class analysis (LCA). We examined associations with race/ethnicity, longitudinal cognitive and functional change, and incident dementia. RESULTS: MCI rates by consensus, actuarial criteria, and LCA were 44%, 53%, and 41%, respectively. LCA identified three MCI subtypes (memory; memory/language; memory/executive) and two NC classes (low normal; high normal). Diagnostic agreement was substantial, but agreement of the actuarial method with consensus and LCA was weaker than the agreement between consensus and LCA. Among cases classified as MCI by actuarial criteria only, Black participants were over-represented, and outcomes were generally similar to those of NC participants. Consensus diagnoses best predicted longitudinal outcomes overall, whereas actuarial diagnoses best predicted longitudinal functional change among Black participants. CONCLUSION: Consensus diagnoses optimize specificity in predicting dementia, but among Black older adults, actuarial diagnoses may be more sensitive to early signs of decline. Results highlight the need for cross-cultural validity in MCI diagnosis and should be explored in community- and population-based samples.

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Entorhinal Perfusion Predicts Future Memory Decline, Neurodegeneration, and White Matter Hyperintensity Progression in Older Adults. - Bangen, Katherine J; Thomas, Kelsey R; Sanchez, Danielle L; Edmonds, Emily C; Weigand, Alexandra J; Delano-Wood, Lisa; Bondi, Mark W (J Alzheimers Dis, 2021)
BACKGROUND: Altered cerebral blood flow (CBF) has been linked to increased risk for Alzheimer's disease (AD). However, whether altered CBF contributes to AD risk by accelerating cognitive decline remains unclear. It also remains unclear whether reductions in CBF accelerate neurodegeneration and development of small vessel cerebrovascular disease. OBJECTIVE: To examine associations between CBF and trajectories of memory performance, regional brain atrophy, and global white matter hyperintensity (WMH) volume. METHOD: 147 Alzheimer's Disease Neuroimaging Initiative participants free of dementia underwent arterial spin labeling (ASL) magnetic resonance imaging (MRI) to measure CBF and serial neuropsychological and structural MRI examinations. Linear mixed effects models examined 5-year rate of change in memory and 4-year rate of change in regional brain atrophy and global WMH volumes as a function of baseline regional CBF. Entorhinal and hippocampal CBF were examined in separate models. RESULTS: Adjusting for demographic characteristics, pulse pressure, apolipoprotein E ɛ4 positivity, cerebrospinal fluid p-tau/Aβ ratio, and neuronal metabolism (i.e., fluorodeoxyglucose standardized uptake value ratio), lower baseline entorhinal CBF predicted faster rates of decline in memory as well as faster entorhinal thinning and WMH progression. Hippocampal CBF did not predict cognitive or brain structure trajectories. CONCLUSION: Findings highlight the importance of early cerebrovascular dysfunction in AD risk and suggest that entorhinal CBF as measured by noninvasive ASL MRI is a useful biomarker predictive of future cognitive decline and of risk of both.

Five-Year Change in Body Mass Index Predicts Conversion to Mild Cognitive Impairment or Dementia Only in APOE ɛ4 Allele Carriers. - Kadey, Kylie R; Woodard, John L; Moll, Allison C; Nielson, Kristy A; Smith, J Carson; Durgerian, Sally; Rao, Stephen M (J Alzheimers Dis, 2021)
BACKGROUND: Body mass index (BMI) has been identified as an important modifiable lifestyle risk factor for dementia, but less is known about how BMI might interact with Apolipoprotein E ɛ4 (APOE ɛ4) carrier status to predict conversion to mild cognitive impairment (MCI) and dementia. OBJECTIVE: The aim of this study was to investigate the interaction between APOE ɛ4 status and baseline (bBMI) and five-year BMI change (ΔBMI) on conversion to MCI or dementia in initially cognitively healthy older adults. METHODS: The associations between bBMI, ΔBMI, APOE ɛ4 status, and conversion to MCI or dementia were investigated among 1,289 cognitively healthy elders from the National Alzheimer's Coordinating Center (NACC) database. RESULTS: After five years, significantly more carriers (30.6%) converted to MCI or dementia than noncarriers (17.6%), p <  0.001, OR = 2.06. Neither bBMI (OR = 0.99, 95%CI = 0.96-1.02) nor the bBMI by APOE interaction (OR = 1.02, 95%CI = 0.96-1.08) predicted conversion. Although ΔBMI also did not significantly predict conversion (OR = 0.90, 95%CI = 0.78-1.04), the interaction between ΔBMI and carrier status was significant (OR = 0.72, 95%CI = 0.53-0.98). For carriers only, each one-unit decline in BMI over five years was associated with a 27%increase in the odds of conversion (OR = 0.73, 95%CI = 0.57-0.94). CONCLUSION: A decline in BMI over five years, but not bBMI, was strongly associated with conversion to MCI or dementia only for APOE ɛ4 carriers. Interventions and behaviors aimed at maintaining body mass may be important for long term cognitive health in older adults at genetic risk for AD.

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

Impact of 40 Hz Transcranial Alternating Current Stimulation on Cerebral Tau Burden in Patients with Alzheimer's Disease: A Case Series. - Dhaynaut, Maeva; Sprugnoli, Giulia; Cappon, Davide; Macone, Joanna; Sanchez, Justin S; Normandin, Marc; Guehl, Nicolas; Koch, Giacomo; Paciorek, Rachel; Connor, Ann; Press, Daniel; Johnson, Keith; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by diffuse amyloid-β (Aβ) and phosphorylated Tau (p-Tau) aggregates as well as neuroinflammation. Exogenously-induced 40 Hz gamma oscillations have been showing to reduce Aβ and p-Tau deposition presumably via microglia activation in AD mouse models. OBJECTIVE: We aimed to translate preclinical data on gamma-induction in AD patients by means of transcranial alternating current stimulation (tACS). METHODS: Four participants with mild-to-moderate AD received 1 h of daily 40 Hz (gamma) tACS for 4 weeks (Monday to Friday) targeting the bitemporal lobes (20 h treatment duration). Participant underwent Aβ, p-Tau, and microglia PET imaging with [11C]-PiB, [18F]-FTP, and [11C]-PBR28 respectively, before and after the intervention along with electrophysiological assessment. RESULTS: No adverse events were reported, and an increase in gamma spectral power on EEG was observed after the treatment. [18F]-FTP PET revealed a significant decrease over 2% of p-Tau burden in 3/4 patients following the tACS treatment, primarily involving the temporal lobe regions targeted by tACS and especially mesial regions (e.g., entorhinal cortex). The amount of intracerebral Aβ as measured by [11C]-PiB was not significantly influenced by tACS, whereas 1/4 reported a significant decrease of microglia activation as measured by [11C]-PBR28. CONCLUSION: tACS seems to represent a safe and feasible option for gamma induction in AD patients, with preliminary evidence of a possible effect on protein clearance partially mimicking what is observed in animal models. Longer interventions and placebo control conditions are needed to fully evaluate the potential for tACS to slow disease progression.

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Infectious Disease Burden and the Risk of Alzheimer's Disease: A Population-Based Study. - Douros, Antonios; Santella, Christina; Dell'Aniello, Sophie; Azoulay, Laurent; Renoux, Christel; Suissa, Samy; Brassard, Paul (J Alzheimers Dis, 2021)
BACKGROUND: Previous studies suggested a link between various infectious pathogens and the development of Alzheimer's disease (AD), posing the question whether infectious disease could present a novel modifiable risk factor. OBJECTIVE: To assess whether infectious disease burden due to clinically apparent infections is associated with an increased risk of AD. METHODS: We conducted a population-based nested case-control study using the United Kingdom Clinical Practice Research Datalink. We included all dementia-free subjects ≥50 years of age enrolling in the database between January 1988 and December 2017. Each case of AD identified during follow-up was matched with up to 40 controls. Conditional logistic regression estimated adjusted odds ratios (ORs) with 95% confidence intervals (CIs) of AD associated with ≥1 infection diagnosed >  2 years before the index date compared with no infection during the study period. We further stratified by time since first infection and cumulative number of infections. RESULTS: The cohort included overall 4,262,092 individuals (mean age at cohort entry 60.4 years; 52% female). During a median follow-up of 10.5 years, 40,455 cases of AD were matched to 1,610,502 controls. Compared with having no burden of infectious disease, having a burden of infectious disease was associated with an increase in the risk of AD (OR, 1.05; 95% CI, 1.02 to 1.08). The risk increased with longer time since first infection, peaking after 12-30 years (OR, 1.11; 95% CI, 1.05-1.17). The risk did not increase with cumulative number of infections. CONCLUSION: The overall risk of AD associated with infectious disease burden was small but increased gradually with longer time since first infection.

An Introduction to Ultrasensitive Assays for Plasma Tau Detection. - Ding, Xu-Long; Tuo, Qing-Zhang; Lei, Peng (J Alzheimers Dis, 2021)
The detection of plasma tau and its phosphorylation is technically challenging due to the relatively low sensitivity. However, in Alzheimer's disease and other tauopathies, it is hypothesized that tau in the biofluid may serve as a biomarker. In recent years, several ultrasensitive assays have been developed, which can successfully detect tau and its phosphorylation in various biofluids, and collectively demonstrated the prognostic and diagnostic value of plasma tau/phosphorylated tau. Here we have summarized the principle of four ultrasensitive assays newly developed suitable for plasma tau detection, namely single-molecule array, immunomagnetic reduction assay, enhanced immunoassay using multi-arrayed fiber optics, and meso scale discovery assay, with their advantages and applications. We have also compared these assays with traditional enzyme-linked-immunosorbent serologic assay, hoping to facilitate future tau-based biomarker discovery for Alzheimer's disease and other neurodegenerative diseases.
Keywords: Alzheimer Disease; Biological Assay; Biomarkers; Enzyme-Linked Immunosorbent Assay; Humans; Phosphorylation; tau Proteins

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

The Locus Coeruleus in Aging and Alzheimer's Disease: A Postmortem and Brain Imaging Review. - Beardmore, Rebecca; Hou, Ruihua; Darekar, Angela; Holmes, Clive; Boche, Delphine (J Alzheimers Dis, 2021)
The locus coeruleus (LC), a tiny nucleus in the brainstem and the principal site of noradrenaline synthesis, has a major role in regulating autonomic function, arousal, attention, and neuroinflammation. LC dysfunction has been linked to a range of disorders; however particular interest is given to the role it plays in Alzheimer's disease (AD). The LC undergoes significant neuronal loss in AD, thought to occur early in the disease process. While neuronal loss in the LC has also been suggested to occur in aging, this relationship is less clear as the findings have been contradictory. LC density has been suggested to be indicative of cognitive reserve and the evidence for these claims will be discussed. Recent imaging techniques allowing visualization of the LC in vivo using neuromelanin-sensitive MRI are developing our understanding of the role of LC in aging and AD. Tau pathology within the LC is evident at an early age in most individuals; however, the relationship between tau accumulation and neuronal loss and why some individuals then develop AD is not understood. Neuromelanin pigment accumulates within LC cells with age and is proposed to be toxic and inflammatory when released into the extracellular environment. This review will explore our current knowledge of the LC changes in both aging and AD from postmortem, imaging, and experimental studies. We will discuss the reasons behind the susceptibility of the LC to neuronal loss, with a focus on the role of extracellular neuromelanin and neuroinflammation caused by the dysfunction of the LC-noradrenaline pathway.
Keywords: Aging; Alzheimer Disease; Animals; Autopsy; Brain Stem; Humans; Locus Coeruleus; Magnetic Resonance Imaging; Melanins; Mice; Norepinephrine; Rats; tau Proteins

Loneliness, Not Social Support, Is Associated with Cognitive Decline and Dementia Across Two Longitudinal Population-Based Cohorts. - Freak-Poli, Rosanne; Wagemaker, Nina; Wang, Rui; Lysen, Thom S; Ikram, M Arfan; Vernooij, Meike W; Dintica, Christina S; Vernooij-Dassen, Myrra; Melis, Rene J M; Laukka, Erica J; Fratiglioni, Laura; Xu, Weili; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Poor social health is likely associated with cognitive decline and risk of dementia; however, studies show inconsistent results. Additionally, few studies separate social health components or control for mental health. OBJECTIVE: To investigate whether loneliness and social support are independently associated with cognitive decline and risk of dementia, and whether depressive symptoms confound the association. METHODS: We included 4,514 participants from the population-based Rotterdam Study (RS; aged 71±7SD years) followed up to 14 years (median 10.8, interquartile range 7.4-11.6), and 2,112 participants from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K; aged 72±10SD years) followed up to 10 years (mean 5.9±1.6SD). At baseline, participants were free of major depression and scored on the Mini-Mental State Examination (MMSE) ≥26 for RS and ≥25 for SNAC-K. We investigated loneliness, perceived social support, and structural social support (specifically marital status and number of children). In both cohorts, dementia was diagnosed and cognitive function was repeatedly assessed with MMSE and a global cognitive factor (g-factor). RESULTS: Loneliness was prospectively associated with a decline in the MMSE in both cohorts. Consistently, persons who were lonely had an increased risk of developing dementia (RS: HR 1.34, 95%CI 1.08-1.67; SNAC-K: HR 2.16, 95%CI 1.12-4.17). Adjustment for depressive symptoms and exclusion of the first 5 years of follow-up did not alter results. Neither perceived or structural social support was associated with cognitive decline or dementia risk. CONCLUSION: Loneliness, not social support, predicted cognitive decline and incident dementia independently of depressive symptoms.

Longitudinal Trajectories in Cortical Thickness and Volume Atrophy: Superior Cognitive Performance Does Not Protect Against Brain Atrophy in Older Adults. - Gardener, Samantha L; Weinborn, Michael; Sohrabi, Hamid R; Doecke, James D; Bourgeat, Pierrick; Rainey-Smith, Stephanie R; Shen, Kai-Kai; Fripp, Jurgen; Taddei, Kevin; Maruff, Paul; Salvado, Olivier; Savage, Greg; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Previous research has identified a small subgroup of older adults that maintain a high level of cognitive functioning well into advanced age. Investigation of those with superior cognitive performance (SCP) for their age is important, as age-related decline has previously been thought to be inevitable. OBJECTIVE: Preservation of cortical thickness and volume was evaluated in 76 older adults with SCP and 100 typical older adults (TOAs) assessed up to five times over six years. METHODS: Regions of interest (ROIs) found to have been associated with super-aging status (a construct similar to SCP status) in previous literature were investigated, followed by a discovery phase analyses of additional regions. SCPs were aged 70 + at baseline, scoring at/above normative memory (CVLT-II) levels for demographically similar individuals aged 30-44 years old, and in the unimpaired range for all other cognitive domains over the course of the study. RESULTS: In linear mixed models, following adjustment for multiple comparisons, there were no significant differences between rates of thinning or volume atrophy between SCPs and TOAs in previously identified ROIs, or the discovery phase analyses. With only amyloid-β negative individuals in the analyses, again there were no significant differences between SCPs and TOAs. CONCLUSION: The increased methodological rigor in classifying groups, together with the influence of cognitive reserve, are discussed as potential factors accounting for our findings as compared to the extant literature on those with superior cognitive performance for their age.

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Modifiable Barriers for Recruitment and Retention of Older Adults Participants from Underrepresented Minorities in Alzheimer's Disease Research. - Indorewalla, Khushnoo K; O'Connor, Maureen K; Budson, Andrew E; Guess DiTerlizzi, Christina; Jackson, Jonathan (J Alzheimers Dis, 2021)
Clinical Alzheimer's disease (AD) trials currently face a critical shortfall of thousands of eligible participants, which inflates the duration and cost of the clinical study as well as threatens the scientific merit of promising clinical interventions. This recruitment crisis is further compounded by the fact that underrepresented and marginalized populations-particularly those identifying as a racial or ethnic minority, those with low socioeconomic status, or living in rural areas-have been historically underrepresented in ongoing AD clinical trials despite overwhelming evidence that such populations are at increased risk for developing dementia. As a result of various recruitment barriers, current AD clinical studies frequently reflect a decreasingly representative segment of the US population, which threatens the overall generalizability of these findings. The current narrative review provides an updated examination and critique of common recruitment barriers and potential solutions, as well as a discussion of theoretical approaches that may address barriers disproportionately experienced by underrepresented communities. AD clinical researchers are encouraged to take purposive action aimed at increasing diversity of enrolled AD clinical trial cohorts by actively identifying and quantifying barriers to research participation-especially recruitment barriers and health disparities that disproportionately prevent underrepresented and marginalized populations from participating in research. Furthermore, researchers are encouraged to closely track which individuals who express interest in AD research ultimately enroll in research studies to examine whether AD research participation is appropriately representative of the intended population for whom these new and novel AD interventions are being designed.
Keywords: Alzheimer Disease; Clinical Trials as Topic; Humans; Minority Groups; Patient Selection

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

Neurotrophic Treatment Initiated During Early Postnatal Development Prevents the Alzheimer-Like Behavior and Synaptic Dysfunction. - Wei, Wei; Liu, Yinghua; Dai, Chunling; Baazaoui, Narjes; Tung, Yunn-Chyn; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by impairments in synaptic plasticity and cognitive performance. Cognitive dysfunction and loss of neuronal plasticity are known to begin decades before the clinical diagnosis of the disease. The important influence of congenital genetic mutations on the early development of AD provides a novel opportunity to initiate treatment during early development to prevent the Alzheimer-like behavior and synaptic dysfunction. OBJECTIVE: To explore strategies for early intervention to prevent Alzheimer's disease. METHODS: In the present study, we investigated the effect of treatment during early development with a ciliary neurotrophic factor (CNTF) derived peptidergic compound, P021 (Ac-DGGLAG-NH2) on cognitive function and synaptic plasticity in 3xTg-AD transgenic mouse model of AD. 3xTg-AD and genetic background-matched wild type female mice were treated from birth to postnatal day 120 with P021 in diet or as a control with vehicle diet, and cognitive function and molecular markers of neuroplasticity were evaluated. RESULTS: P021 treatment during early development prevented cognitive impairment and increased expressions of pCREB and BDNF that activated downstream various signaling cascades such as PLC/PKC, MEK/ERK and PI3K/Akt, and ameliorated synaptic protein deficit in 4-month-old 3xTg-AD mice. CONCLUSION: These findings indicate that treatment with the neurotrophic peptide mimetic such as P021 during early development can be an effective therapeutic strategy to rescue synaptic deficit and cognitive impairment in familial AD and related tauopathies.

NLRP3 Inflammasome: A Starring Role in Amyloid-β- and Tau-Driven Pathological Events in Alzheimer's Disease. - Van Zeller, Mariana; Dias, Diogo; Sebastião, Ana M; Valente, Cláudia A (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease commonly diagnosed among the elderly population. AD is characterized by the loss of synaptic connections, neuronal death, and progressive cognitive impairment, attributed to the extracellular accumulation of senile plaques, composed by insoluble aggregates of amyloid-β (Aβ) peptides, and to the intraneuronal formation of neurofibrillary tangles shaped by hyperphosphorylated filaments of the microtubule-associated protein tau. However, evidence showed that chronic inflammatory responses, with long-lasting exacerbated release of proinflammatory cytokines by reactive glial cells, contribute to the pathophysiology of the disease. NLRP3 inflammasome (NLRP3), a cytosolic multiprotein complex sensor of a wide range of stimuli, was implicated in multiple neurological diseases, including AD. Herein, we review the most recent findings regarding the involvement of NLRP3 in the pathogenesis of AD. We address the mechanisms of NLRP3 priming and activation in glial cells by Aβ species and the potential role of neurofibrillary tangles and extracellular vesicles in disease progression. Neuronal death by NLRP3-mediated pyroptosis, driven by the interneuronal tau propagation, is also discussed. We present considerable evidence to claim that NLRP3 inhibition, is undoubtfully a potential therapeutic strategy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Astrocytes; Humans; Inflammasomes; Inflammation; Microglia; NLR Family, Pyrin Domain-Containing 3 Protein; Tauopathies

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

PINK1 Activation Attenuates Impaired Neuronal-Like Differentiation and Synaptogenesis and Mitochondrial Dysfunction in Alzheimer's Disease Trans-Mitochondrial Cybrid Cells. - Du, Fang; Yu, Qing; Yan, Shirley ShiDu (J Alzheimers Dis, 2021)
BACKGROUND: Mitochondrial dysfunction, bioenergetic deficit, and extensive oxidative stress underlie neuronal perturbation during the early stage of Alzheimer's disease (AD). Previously, we demonstrated that decreased PTEN-induced putative kinase 1 (PINK1) expression is associated with AD pathology in AD-affected human brains and AD mice. OBJECTIVE: In the present study, we highlight the essential role of PINK1 in AD-relevant mitochondrial perturbation and neuronal malfunction. METHODS: Using trans-mitochondrial "cybrid" (cytoplasmic hybrid) neuronal cells, whose mitochondria are transferred from platelets of patients with sporadic AD, we observed the effect of PINK1 in neuronal-like differentiation and synaptogenesis and mitochondrial functions. RESULTS: In AD cybrid cells, the downregulation of PINK1 is correlated to the alterations in mitochondrial morphology and function and deficit in neuronal-like differentiation. Restoring/increasing PINK1 by lentivirus transduction of PINK1 robustly attenuate mitochondrial defects and rescue neurite-like outgrowth. Importantly, defective PINK1 kinase activity fails to reverse these detrimental effects. Mechanistically, AD cybrid cells reveal a significant decrease in PINK1-dependent phosphorylated mitofusin (Mfn) 2, a key mitochondrial membrane protein that participates in mitochondrial fusion, and an insufficient autophagic activity for clearance of dysfunctional mitochondria. Overexpression of PINK1, but not mutant PINK1 elevates phosphorylation of Mfn2 and autophagy signaling LC3-II. Accordingly, PINK1-overexpressed AD cybrids exhibit increases in mitochondrial length and density and suppressed reactive oxygen species. These results imply that activation of PINK1 protects against AD-affected mitochondrial dysfunction and impairment in neuronal maturation and differentiation. CONCLUSION: PINK1-mediated mitophagy is important for maintaining mitochondrial health by clearance of dysfunctional mitochondria and therefore, improves energy homeostasis in AD.

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Plasma EFEMP1 Is Associated with Brain Aging and Dementia: The Framingham Heart Study. - McGrath, Emer R; Himali, Jayandra J; Levy, Daniel; Yang, Qiong; DeCarli, Charles S; Courchesne, Paul; Satizabal, Claudia L; Finney, Rebecca; Vasan, Ramachandran S; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: Epidermal growth factor containing fibulin extracellular matrix protein-1 (EFEMP1) has been associated with increased white matter hyperintensities (WMH) burden and disorders of premature aging and may have a shared pathophysiological role in the development of WMH and dementia. OBJECTIVE: To determine the association between plasma EFEMP1 levels and MRI markers of vascular brain injury and incident all-cause and Alzheimer's disease (AD) dementia. METHODS: We measured plasma EFEMP1 levels in 1597 [53% women, mean age 68.7 (SD 5.7) years] dementia-free Framingham Offspring cohort participants between 1998-2001 and subsequently followed them for incident dementia. Secondary outcomes included stroke, structural MRI brain measures and neurocognitive test performance. RESULTS: During a median 11.8 [Q1, Q3 : 7.1, 13.3] year follow-up, 131 participants developed dementia. The highest quintile of plasma EFEMP1, compared to the bottom four quintiles, was associated with an increased risk of time to incident all-cause dementia (HR 1.77, 95% CI 1.18-2.64) and AD dementia (HR 1.76, 95% CI 1.11-2.81) but not with markers of vascular brain injury (WMH, covert brain infarcts or stroke). Higher circulating EFEMP1 concentrations were also cross-sectionally associated with lower total brain (β±SE, -0.28±0.11, p = 0.01) and hippocampal volumes (-0.006±0.003, p = 0.04) and impaired abstract reasoning (Similarities test, -0.18±0.08, p = 0.018 per standard deviation increment in EFEMP1). CONCLUSION: Elevated circulating EFEMP1 is associated with an increased risk of all-cause and AD dementia, smaller hippocampal and total brain volumes, and poorer cognitive performance. EFEMP1 may play an important biological role in the development of AD dementia. Further studies to validate these findings are warranted.

Porphyromonas gingivalis (W83) Infection Induces Alzheimer's Disease-Like Pathophysiology in Obese and Diabetic Mice. - Bahar, Bojlul; Kanagasingam, Shalini; Tambuwala, Murtaza M; Aljabali, Alaa A A; Dillon, Stephanie A; Doaei, Saeid; Welbury, Richard; Chukkapalli, Sasanka S; Singhrao, Sim K (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease(s) and metabolic illnesses negatively impact the quality of life and, eventually mental health. OBJECTIVE: This study investigated the effect of Porphyromonas gingivalis (W83) oral infection on the development of Alzheimer's disease (AD) pathophysiology in a wild-type obese, diabetic (db/db) mouse model. METHODS: The db/db mice were either orally infected with P. gingivalis and Fusobacterium nucleatum or sham infected for 16 weeks. The presence of amyloid-β (Aβ) and neurofibrillary tangles (NFTs) were assessed using a silver impregnation technique and subsequently by immunohistochemistry for tau and neuroinflammation. The mRNA abundance of a panel of 184 genes was performed using quantitative real-time PCR, and the differentially expressed genes were analyzed by Ingenuity Pathway Analysis. RESULTS: While no Aβ plaques and NFTs were evident by silver impregnation, immunohistochemistry (glial cell markers) of the P. gingivalis-infected mice tissue sections exhibited neuroinflammation in the form of reactive microglia and astrocytes. Anti-tau immunopositivity, in addition to cells, was prominent in thickened axons of hippocampal CA neurons. The mRNA abundance of crucial genes in the insulin signaling pathway (INSR, IGF1, IRS, IDE, PIK3R, SGK1, GYS, GSK3B, AKT1) were upregulated, potentially exacerbating insulin resistance in the brain by P. gingivalis oral infection. Increased mRNA abundance of several kinases, membrane receptors, transcription factors, and pro-inflammatory mediators indicated hyperactivation of intracellular cascades with potential for tau phosphorylation and Aβ release in the same infection group. CONCLUSION: P. gingivalis W83 infection of db/db mice provides a disease co-morbidity model with the potential to reproduce AD pathophysiology with induced periodontal disease.

Primary Prevention of Dementia: An Ethical Review. - Horstkötter, Dorothee; Deckers, Kay; Köhler, Sebastian (J Alzheimers Dis, 2021)
Dementia poses important medical and societal challenges, and of all health risks people face in life, dementia is one of the most feared. Recent research indicates that up to about 40% of all cases of dementia might be preventable. A series of environmental, social, and medical risk-factors have been identified that should be targeted from midlife onwards when people are still cognitively healthy. At first glance, this seems not merely advisable, but even imperative. However, these new developments trigger a series of new ethical questions and concerns which have hardly been addressed to date. Pro-active ethical reflection, however, is crucial to ensure that the interests and well-being of those affected, ultimately all of us, are adequately respected. This is the goal of the current contribution. Against the background of a concrete case in primary dementia prevention, it provides a systematic overview of the current ethical literature and sketches an ethical research agenda. First, possible benefits of increased well-being must be balanced with the burdens of being engaged in particularly long-term interventions for which it is unclear whether they will ever pay out on a personal level. Second, while knowledge about one's options to maintain brain health might empower people, it might also undermine autonomy, put high social pressure on people, medicalize healthy adults, and stigmatize those who still develop dementia. Third, while synergistic effects might occur, the ideals of dementia prevention might also conflict with other health and non-health related values people hold in life.
Keywords: Dementia; Ethical Review; Humans; Life Style; Primary Prevention

Promoting Successful Cognitive Aging: A Ten-Year Update. - Krivanek, Taylor J; Gale, Seth A; McFeeley, Brittany M; Nicastri, Casey M; Daffner, Kirk R (J Alzheimers Dis, 2021)
A decade has passed since we published a comprehensive review in this journal addressing the topic of promoting successful cognitive aging, making this a good time to take stock of the field. Because there have been limited large-scale, randomized controlled trials, especially following individuals from middle age to late life, some experts have questioned whether recommendations can be legitimately offered about reducing the risk of cognitive decline and dementia. Despite uncertainties, clinicians often need to at least make provisional recommendations to patients based on the highest quality data available. Converging lines of evidence from epidemiological/cohort studies, animal/basic science studies, human proof-of-concept studies, and human intervention studies can provide guidance, highlighting strategies for enhancing cognitive reserve and preventing loss of cognitive capacity. Many of the suggestions made in 2010 have been supported by additional research. Importantly, there is a growing consensus among major health organizations about recommendations to mitigate cognitive decline and promote healthy cognitive aging. Regular physical activity and treatment of cardiovascular risk factors have been supported by all of these organizations. Most organizations have also embraced cognitively stimulating activities, a heart-healthy diet, smoking cessation, and countering metabolic syndrome. Other behaviors like regular social engagement, limiting alcohol use, stress management, getting adequate sleep, avoiding anticholinergic medications, addressing sensory deficits, and protecting the brain against physical and toxic damage also have been endorsed, although less consistently. In this update, we review the evidence for each of these recommendations and offer practical advice about behavior-change techniques to help patients adopt brain-healthy behaviors.
Keywords: Cognition; Cognitive Aging; Diet, Healthy; Exercise; Healthy Aging; Healthy Lifestyle; Humans

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

Relation of a Socioeconomic Index with Cognitive Function and Neuroimaging in Hypertensive Individuals. - Paradela, Regina Silva; Ferreira, Naomi Vidal; Nucci, Mariana Penteado; Cabella, Brenno; Martino, Luiza Menoni; Torres, Laura Aló; Costa, Danielle Irigoyen da; Consolim-Colombo, Fernanda Marciano; Suemoto, Claudia Kimie; Irigoyen, Maria Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Socioeconomic factors are important contributors to brain health. However, data from developing countries (where social inequalities are the most prominent) are still scarce, particularly about hypertensive individuals. OBJECTIVE: To evaluate the relationship between socioeconomic index, cognitive function, and cortical brain volume, as well as determine whether white matter hyperintensities are mediators of the association of the socioeconomic index with cognitive function in hypertensive individuals. METHODS: We assessed 92 hypertensive participants (mean age = 58±8.6 years, 65.2%female). Cognitive evaluation and neuroimaging were performed and clinical and sociodemographic data were collected using questionnaires. A socioeconomic index was created using education, income, occupation (manual or non-manual work), and race. The associations of the socioeconomic index with cognitive performance and brain volume were investigated using linear regression models adjusted for age, sex, time of hypertension since diagnosis, and comorbidities. A causal mediation analysis was also conducted. RESULTS: Better socioeconomic status was associated with better visuospatial ability, executive function, and global cognition. We found associations between a better socioeconomic index and a higher parietal lobe volume. White matter hyperintensities were also not mediators in the relationship between the socioeconomic index and cognitive performance. CONCLUSION: Socioeconomic disadvantages are associated with worse cognitive performance and brain volume in individuals with hypertension.

Relationships Between Cognition and Neuropathological Tau in Alzheimer's Disease Assessed by 18F Flortaucipir PET. - Devous, Michael D; Fleisher, Adam S; Pontecorvo, Michael J; Lu, Ming; Siderowf, Andrew; Navitsky, Michael; Kennedy, Ian; Southekal, Sudeepti; Harris, Thomas S; Mintun, Mark A (J Alzheimers Dis, 2021)
BACKGROUND: Tau neurofibrillary tangle burden increases with Alzheimer's disease (AD) stage and correlates with degree of cognitive impairment. Tau PET imaging could facilitate understanding the relationship between tau pathology and cognitive impairment. OBJECTIVE: Evaluate the relationship between 18F flortaucipir uptake patterns and cognition across multiple cognitive domains. METHODS: We acquired flortaucipir PET scans in 84 amyloid-positive control, mild cognitive impairment (MCI), and AD subjects. Flortaucipir standardized uptake value ratio (SUVr) values were obtained from a neocortical volume of interest (VOI), a precuneus VOI, and VOIs defined by the correlation between flortaucipir SUVr images and domain-specific cognitive tests. Cognitive assessments included Mini-Mental State Exam (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-cog), and a neuropsychological test battery (i.e., Wechsler Memory Scale-Revised Logical Memory (WMS-R), Trail Making Test, Boston Naming Test, Digit Symbol Substitution Test, Animal List Generation, WMS-R Digit Span, American National Adult Reading Test, Clock Drawing Test, Judgment of Line Orientation, and WMS-R Logical Memory II (Delayed Recall)) and the Functional Activities Questionnaire (FAQ). Correlation analyses compared regional and voxel-wise VOIs to cognitive scores. RESULTS: Subjects included 5 controls, 47 MCI, and 32 AD subjects. Significant correlations were seen between both flortaucipir and florbetapir SUVrs and MMSE, ADAS-Cog, and FAQ. Cognitive impairment was associated with increased flortaucipir uptake in regionally specific patterns consistent with the neuroanatomy underlying specific cognitive tests. CONCLUSION: Flortaucipir SUVr values demonstrated significant inverse correlations with cognitive scores in domain-specific patterns. Findings support the hypothesis that PET imaging of neuropathologic tau deposits may reflect underlying neurodegeneration in AD.

Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.

Reliability of Telephone and Videoconference Methods of Cognitive Assessment in Older Adults with and without Dementia. - Hunter, Matthew B; Jenkins, Natalie; Dolan, Clare; Pullen, Hannah; Ritchie, Craig; Muniz-Terrera, Graciela (J Alzheimers Dis, 2021)
BACKGROUND: Telephone and videoconference administration of cognitive tests introduce additional sources of variance compared to in-person testing. Reviews of test-retest reliability have included mixed neurocognitive and psychiatric populations with limited consideration of methodological and statistical contributions. OBJECTIVE: We reviewed reliability estimates from comparison studies of older adults with and without dementia, considering test-retest analyses and study methods. METHODS: Medline, Embase, PsycINFO, and Web of Science were systematically searched from 1 January 2000 to 9 June 2020 for original articles comparing telephone or videoconference administered cognitive instruments to in-person administration in older adults with and without dementia or mild cognitive impairment. RESULTS: Of 4,125 articles, 23 were included: 11 telephone (N = 2 dementia cohorts) and 12 videoconference (N = 4 dementia cohorts). Telephone administered subtest scores trended in the same direction as in-person with comparable means. Person-level data were scarce. Data on dementia was only available for MMSE, with resulting subtle modality bias. MMSE, SMMSE, Letter Fluency, and HVLT-R in healthy to mild-moderate Alzheimer's disease were particularly reliable for videoconference administration. Other tests show promise but require more observations and comprehensive analyses. Most studies used high-speed stable videoconferencing hardware resulting in a lack of ecological validity for home administration. CONCLUSION: Remote administration is often consistent with in-person administration but variable and limited at the person/test level. Improved statistical design and inclusion of dementia related cohorts in telephone studies is recommended. Reliability evidence is stronger for videoconferencing but with limited applicability to home administration and severe dementia. Improved reporting of administrative procedures is recommended.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Dementia; Geriatric Assessment; Humans; Neuropsychological Tests; Remote Consultation; Reproducibility of Results; Telephone; Videoconferencing

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Risk Variants in Three Alzheimer's Disease Genes Show Association with EEG Endophenotypes. - Macedo, Ana; Gómez, Carlos; Rebelo, Miguel Ângelo; Poza, Jesús; Gomes, Iva; Martins, Sandra; Maturana-Candelas, Aarón; Pablo, Víctor Gutiérrez-de; Durães, Luis; Sousa, Patrícia; Figueruelo, Manuel; Rodriguez, Maria; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Dementia due to Alzheimer's disease (AD) is a complex neurodegenerative disorder, which much of heritability remains unexplained. At the clinical level, one of the most common physiological alterations is the slowing of oscillatory brain activity, measurable by electroencephalography (EEG). Relative power (RP) at the conventional frequency bands (i.e., delta, theta, alpha, beta-1, and beta-2) can be considered as AD endophenotypes. OBJECTIVE: The aim of this work is to analyze the association between sixteen genes previously related with AD: APOE, PICALM, CLU, BCHE, CETP, CR1, SLC6A3, GRIN2 β, SORL1, TOMM40, GSK3 β, UNC5C, OPRD1, NAV2, HOMER2, and IL1RAP, and the slowing of the brain activity, assessed by means of RP at the aforementioned frequency bands. METHODS: An Iberian cohort of 45 elderly controls, 45 individuals with mild cognitive impairment, and 109 AD patients in the three stages of the disease was considered. Genomic information and brain activity of each subject were analyzed. RESULTS: The slowing of brain activity was observed in carriers of risk alleles in IL1RAP (rs10212109, rs9823517, rs4687150), UNC5C (rs17024131), and NAV2 (rs1425227, rs862785) genes, regardless of the disease status and situation towards the strongest risk factors: age, sex, and APOE ɛ4 presence. CONCLUSION: Endophenotypes reduce the complexity of the general phenotype and genetic variants with a major effect on those specific traits may be then identified. The found associations in this work are novel and may contribute to the comprehension of AD pathogenesis, each with a different biological role, and influencing multiple factors involved in brain physiology.

Selective Impairment of Long-Range Default Mode Network Functional Connectivity as a Biomarker for Preclinical Alzheimer's Disease in People with Down Syndrome. - DiProspero, Natalie D; Keator, David B; Phelan, Michael; van Erp, Theo G M; Doran, Eric; Powell, David K; Van Pelt, Kathryn L; Schmitt, Frederick A; Head, Elizabeth; Lott, Ira T; Yassa, Michael A (J Alzheimers Dis, 2021)
BACKGROUND: Down syndrome (DS) is associated with increased risk for Alzheimer's disease (AD). In neurotypical individuals, clinical AD is preceded by reduced resting state functional connectivity in the default mode network (DMN), but it is unknown whether changes in DMN connectivity predict clinical onset of AD in DS. OBJECTIVE: Does lower DMN functional connectivity predict clinical onset of AD and cognitive decline in people with DS? METHODS: Resting state functional MRI (rsfMRI), longitudinal neuropsychological, and clinical assessment data were collected on 15 nondemented people with DS (mean age = 51.66 years, SD = 5.34 years, range = 42-59 years) over four years, during which 4 transitioned to dementia. Amyloid-β (Aβ) PET data were acquired on 13 of the 15 participants. Resting state fMRI, neuropsychological, and clinical assessment data were also acquired on an independent, slightly younger unimpaired sample of 14 nondemented people with DS (mean age = 44.63 years, SD = 7.99 years, range = 38-61 years). RESULTS: Lower functional connectivity between long-range but not short-range DMN regions predicts AD diagnosis and cognitive decline in people with DS. Aβ accumulation in the inferior parietal cortex is associated with lower regional DMN functional connectivity. CONCLUSION: Reduction of long-range DMN connectivity is a potential biomarker for AD in people with DS that precedes and predicts clinical conversion.

Serum Uric Acid May Aggravate Alzheimer's Disease Risk by Affecting Amyloidosis in Cognitively Intact Older Adults: The CABLE Study. - Li, Lin-Lin; Ma, Ya-Hui; Bi, Yan-Lin; Sun, Fu-Rong; Hu, Hao; Hou, Xiao-He; Xu, Wei; Shen, Xue-Ning; Dong, Qiang; Tan, Lan; Yang, Jiu-Long; Yu, Jin-Tai (J Alzheimers Dis, 2021)
BACKGROUND: Serum uric acid (SUA) affects the reaction of oxidative stress and free radicals in the neurodegenerative processes. However, whether SUA impacts Alzheimer's disease (AD) pathology remains unclear. OBJECTIVE: We aimed to explore whether high SUA levels can aggravate the neurobiological changes of AD in preclinical AD. METHODS: We analyzed cognitively intact participants (n = 839, age 62.16 years) who received SUA and cerebrospinal fluid (CSF) biomarkers (amyloid-β [Aβ], total tau [t-Tau], and phosphorylated tau [p-Tau]) measurements from the Chinese Alzheimer's Biomarker and LifestylE (CABLE) database using multivariable-adjusted linear models. RESULTS: Levels of SUA in the preclinical AD elevated compared with the healthy controls (p = 0.007) and subjects with amyloid pathology had higher concentration of SUA than controls (p = 0.017). Roughly, equivalent levels of SUA displayed among cognitively intact individuals with or without tau pathology and neurodegeneration. CSF Aβ1 - 42 (p = 0.019) and Aβ1 - 42/Aβ1 - 40 (p = 0.027) were decreased and CSF p-Tau/Aβ1 - 42 (p = 0.009) and t-Tau/Aβ1 - 42 (p = 0.043) were increased with the highest (>  75th percentile) SUA when compared to lowest SUA, implying a high burden of cerebral amyloidosis in individuals with high SUA. Sensitivity analyses using the usual threshold to define hyperuricemia and precluding drug effects yielded robust associations. Nevertheless, the quadratic model did not show any U-shaped relationships between them. CONCLUSION: SUA may aggravate brain amyloid deposition in preclinical AD, which corroborated the detrimental role of SUA.

Sleep Deprivation, a Link Between Post-Traumatic Stress Disorder and Alzheimer's Disease. - Delic, Vedad; Ratliff, Whitney A; Citron, Bruce A (J Alzheimers Dis, 2021)
An estimated 5 million Americans are living with Alzheimer's disease (AD), and there is also a significant impact on caregivers, with an additional 16 million Americans providing unpaid care for individuals with AD and other dementias. These numbers are projected to increase in the coming years. While AD is still without a cure, continued research efforts have led to better understanding of pathology and potential risk factors that could be exploited to slow disease progression. A bidirectional relationship between sleep deprivation and AD has been suggested and is well supported by both human and animal studies. Even brief episodes of inadequate sleep have been shown to cause an increase in amyloidβ and tau proteins, both well-established contributors toAD pathology. Sleep deprivation is also the most common consequence of post-traumatic stress disorder (PTSD). Patients with PTSD frequently present with sleep disturbances and also develop dementia at twice the rate of the general population accounting for a disproportionate representation of AD among U.S. Veterans. The goal of this review is to highlight the relationship triad between sleep deprivation, AD, and PTSD as well as their impact on molecular mechanisms driving AD pathology.
Keywords: Alzheimer Disease; Animals; Humans; Sleep Deprivation; Stress Disorders, Post-Traumatic

Sustained Hippocampal Neural Plasticity Questions the Reproducibility of an Amyloid-β-Induced Alzheimer's Disease Model. - Paulo, Sara L; Ribeiro-Rodrigues, Leonor; Rodrigues, Rui S; Mateus, Joana M; Fonseca-Gomes, João; Soares, Rita; Diógenes, Maria J; Solá, Susana; Sebastião, Ana M; Ribeiro, Filipa F; Xapelli, Sara (J Alzheimers Dis, 2021)
BACKGROUND: The use of Alzheimer's disease (AD) models obtained by intracerebral infusion of amyloid-β (Aβ) has been increasingly reported in recent years. Nonetheless, these models may present important challenges. OBJECTIVE: We have focused on canonical mechanisms of hippocampal-related neural plasticity to characterize a rat model obtained by an intracerebroventricular (icv) injection of soluble amyloid-β42 (Aβ42). METHODS: Animal behavior was evaluated in the elevated plus maze, Y-Maze spontaneous or forced alternation, Morris water maze, and open field, starting 2 weeks post-Aβ42 infusion. Hippocampal neurogenesis was assessed 3 weeks after Aβ42 injection. Aβ deposition, tropomyosin receptor kinase B levels, and neuroinflammation were appraised at 3 and 14 days post-Aβ42 administration. RESULTS: We found that immature neuronal dendritic morphology was abnormally enhanced, but proliferation and neuronal differentiation in the dentate gyrus was conserved one month after Aβ42 injection. Surprisingly, animal behavior did not reveal changes in cognitive performance nor in locomotor and anxious-related activity. Brain-derived neurotrophic factor related-signaling was also unchanged at 3 and 14 days post-Aβ icv injection. Likewise, astrocytic and microglial markers of neuroinflammation in the hippocampus were unaltered in these time points. CONCLUSION: Taken together, our data emphasize a high variability and lack of behavioral reproducibility associated with these Aβ injection-based models, as well as the need for its further optimization, aiming at addressing the gap between preclinical AD models and the human disorder.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

Urban Air Pollution Nanoparticles from Los Angeles: Recently Decreased Neurotoxicity. - Zhang, Hongqiao; D'Agostino, Carla; Forman, Henry Jay; Cacciottolo, Mafalda; Thorwald, Max; Mack, William J; Liu, Qinghai; Shkirkova, Kristina; Lamorie-Foote, Krista; Sioutas, Constantinos; Pirhadi, Milad; Mack, Wendy Jean; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution is widely associated with accelerated cognitive decline at later ages and risk of Alzheimer's disease (AD). Correspondingly, rodent models demonstrate the neurotoxicity of ambient air pollution and its components. Our studies with nano-sized particulate matter (nPM) from urban Los Angeles collected since 2009 have shown pro-amyloidogenic and pro-inflammatory responses. However, recent batches of nPM have diminished induction of the glutamate receptor GluA1 subunit, Iba1, TNFα, Aβ42 peptide, and white matter damage. The same methods, materials, and mouse genotypes were used throughout. OBJECTIVE: Expand the nPM batch comparisons and evaluate archived brain samples to identify the earliest change in nPM potency. METHODS: Batches of nPM were analyzed by in vitro cell assays for NF-κB and Nrf2 induction for comparison with in vivo responses of mouse brain regions from mice exposed to these batches, analyzed by PCR and western blot. RESULTS: Five older nPM batches (2009-2017) and four recent nPM batches (2018, 2019) for NF-κB and Nrf2 induction showed declines in nPM potency after 2017 that paralleled declines of in vivo activity from independent exposures in different years. CONCLUSION: Transcription-based in vitro assays of nPM corresponded to the loss of in vivo potency for inflammatory and oxidative responses. These recent decreases of nPM neurotoxicity give a rationale for evaluating possible benefits to the risk of dementia and stroke in Los Angeles populations.

White Matter Connectivity in Incident Mild Cognitive Impairment: A Diffusion Spectrum Imaging Study of World Trade Center Responders at Midlife. - Huang, Chuan; Kritikos, Minos; Clouston, Sean A P; Deri, Yael; Serrano-Sosa, Mario; Bangiyev, Lev; Santiago-Michels, Stephanie; Gandy, Sam; Sano, Mary; Bromet, Evelyn J; Luft, Benjamin J (J Alzheimers Dis, 2021)
BACKGROUND: Individuals who participated in response efforts at the World Trade Center (WTC) following 9/11/2001 are experiencing elevated incidence of mild cognitive impairment (MCI) at midlife. OBJECTIVE: We hypothesized that white matter connectivity measured using diffusion spectrum imaging (DSI) would be restructured in WTC responders with MCI versus cognitively unimpaired responders. METHODS: Twenty responders (mean age 56; 10 MCI/10 unimpaired) recruited from an epidemiological study were characterized using NIA-AA criteria alongside controls matched on demographics (age/sex/occupation/race/education). Axial DSI was acquired on a 3T Siemen's Biograph mMR scanner (12-channel head coil) using a multi-band diffusion sequence. Connectometry examined whole-brain tract-level differences in white matter integrity. Fractional anisotropy (FA), mean diffusivity (MD), and quantified anisotropy were extracted for region of interest (ROI) analyses using the Desikan-Killiany atlas. RESULTS: Connectometry identified both increased and decreased connectivity within regions of the brains of responders with MCI identified in the corticothalamic pathway and cortico-striatal pathway that survived adjustment for multiple comparisons. MCI was also associated with higher FA values in five ROIs including in the rostral anterior cingulate; lower MD values in four ROIs including the left rostral anterior cingulate; and higher MD values in the right inferior circular insula. Analyses by cognitive domain revealed nominal associations in domains of response speed, verbal learning, verbal retention, and visuospatial learning. CONCLUSIONS: WTC responders with MCI at midlife showed early signs of neurodegeneration characterized by both increased and decreased white matter diffusivity in regions commonly affected by early-onset Alzheimer's disease.
Keywords: Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Emergency Responders; Female; Humans; Incidence; Male; Middle Aged; September 11 Terrorist Attacks; White Matter

Age of Migration and Cognitive Function Among Older Latinos in the United States. - Garcia, Marc A; Ortiz, Kasim; Arévalo, Sandra P; Diminich, Erica D; Briceño, Emily; Vega, Irving E; Tarraf, Wassim (J Alzheimers Dis, 2020)
BACKGROUND: Age of migration has been shown to have a robust association with Latino immigrant health outcomes; however, the relationship between timing of migration and cognition is less understood. OBJECTIVE: To examine associations between race/ethnicity, nativity, age of migration, and cognitive aging among US-born (USB) non-Latino Whites (NLW) and USB and foreign-born Latinos 50 years and older. METHODS: We used longitudinal biennial data from the Health and Retirement Study (HRS; 2006-2014) to fit generalized linear and linear latent growth curve models for: 1) global cognition (Modified Telephone Interview for Cognitive Status; TICS-M); 2) memory and attention subdomains of TICS-M; and 3) cognitive dysfunction. We also tested for sex modifications. RESULTS: In age and sex adjusted models, all Latino subgroups, independent of nativity and age of migration, had lower global and domain-specific cognitive scores and higher propensity of cognitive impairment classification compared to USB-NLWs. Differences between USB Latinos, but not other Latino subgroups, and USB-NLWs remained after full covariate adjustment. Latinas, independent of nativity or age of migration, had poorer cognitive scores relative to NLW females. Differences between all Latinos and USB-NLWs were principally expressed at baseline. Racial/ethnic, nativity, and age of migration grouping was not associated with slope (nor explained variance) of cognitive decline. CONCLUSION: Older US-born Latinos, regardless of sex exhibit poorer cognitive function than older USB-NLWs and foreign-born Latinos. Social determinants that differentially affect cognitive function, particularly those that compensate for education and sex differences among US-born Latinos and foreign-born Latinos, require further exploration.

Alzheimer's Disease-Like Neurodegeneration in Porphyromonas gingivalis Infected Neurons with Persistent Expression of Active Gingipains. - Haditsch, Ursula; Roth, Theresa; Rodriguez, Leo; Hancock, Sandy; Cecere, Thomas; Nguyen, Mai; Arastu-Kapur, Shirin; Broce, Sean; Raha, Debasish; Lynch, Casey C; Holsinger, Leslie J; Dominy, Stephen S; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Porphyromonas gingivalis (P. gingivalis) and its gingipain virulence factors have been identified as pathogenic effectors in Alzheimer's disease (AD). In a recent study we demonstrated the presence of gingipains in over 90% of postmortem AD brains, with gingipains localizing to the cytoplasm of neurons. However, infection of neurons by P. gingivalis has not been previously reported. OBJECTIVE: To demonstrate intraneuronal P. gingivalis and gingipain expression in vitro after infecting neurons derived from human inducible pluripotent stem cells (iPSC) with P. gingivalis for 24, 48, and 72 h. METHODS: Infection was characterized by transmission electron microscopy, confocal microscopy, and bacterial colony forming unit assays. Gingipain expression was monitored by immunofluorescence and RT-qPCR, and protease activity monitored with activity-based probes. Neurodegenerative endpoints were assessed by immunofluorescence, western blot, and ELISA. RESULTS: Neurons survived the initial infection and showed time dependent, infection induced cell death. P. gingivalis was found free in the cytoplasm or in lysosomes. Infected neurons displayed an accumulation of autophagic vacuoles and multivesicular bodies. Tau protein was strongly degraded, and phosphorylation increased at T231. Over time, the density of presynaptic boutons was decreased. CONCLUSION: P. gingivalis can invade and persist in mature neurons. Infected neurons display signs of AD-like neuropathology including the accumulation of autophagic vacuoles and multivesicular bodies, cytoskeleton disruption, an increase in phospho-tau/tau ratio, and synapse loss. Infection of iPSC-derived mature neurons by P. gingivalis provides a novel model system to study the cellular mechanisms leading to AD and to investigate the potential of new therapeutic approaches.

Amyloid-β in Alzheimer's Disease: A Study of Citation Practices of the Amyloid Cascade Hypothesis Between 1992 and 2019. - Daly, Timothy; Houot, Marion; Barberousse, Anouk; Agid, Yves; Epelbaum, Stéphane (J Alzheimers Dis, 2020)
The amyloid cascade hypothesis (ACH) has dominated contemporary biomedical research into Alzheimer's disease (AD) since the 1990 s but still lacks definitive confirmation by successful clinical trials of anti-amyloid medicines in human AD. In this uncertain period regarding the centrality of amyloid-β (Aβ) in AD pathophysiology, and with the community apparently divided about the ACH's validity, we used citation practices as a proxy for measuring how researchers have invested their belief in the hypothesis between 1992 and 2019. We sampled 445 articles citing Hardy & Higgins (1992, "HH92") and classified the polarity of their HH92 citation according to Greenberg (2009)'s citation taxonomy of positive, neutral, and negative citations, and then tested four hypotheses. We identified two major attitudes towards HH92: a majority (62%) of neutral attitudes with consistent properties across the time period, and a positive attitude (35%), tending to cite HH92 earlier on within the bibliography as time went by, tending to take HH92 as an established authority. Despite the majority of neutral HH92 citations, there was a positive majority of attitudes toward different versions of the ACH and anti-amyloid therapeutic strategies (65%), suggesting that the ACH has been dominant and has undergone significant refinement since 1992. Finally, of those 110 original articles within the sample also testing the ACH empirically, an overwhelming majority (89%) returned a pro-ACH test result, suggesting that the ACH's central claim is reproducible. Further studies will quantify the extent to which results from different methods within such original studies convergence to provide a robust conclusion vis-à-vis Aβ's pathogenicity in AD.

Animal Models of Alzheimer's Disease Should Be Controlled for Roseolovirus. - Denner, Joachim; Tanzi, Rudolph; Jacobson, Steve (J Alzheimers Dis, 2020)
Animal models to study Alzheimer's disease (AD) pathogenesis are under development. Since herpesviruses have been postulated to be capable of triggering the pathogenic process, AD animal models (mouse, pig, and non-human primates) should be controlled for the presence of these viruses. Only virus-free models allow studying the genetic factors and the effect of adding viruses. Roseoloviruses such as human herpesvirus 6 and the related viruses in the animals are the main topic of this commentary.

APOEɛ4-TOMM40L Haplotype Increases the Risk of Mild Cognitive Impairment Conversion to Alzheimer's Disease. - Cardoso, Remy; Lemos, Carolina; Oliveiros, Bárbara; Rosário Almeida, Maria; Baldeiras, Ines; Fragão Pereira, Cláudia; Santos, Ana; Duro, Diana; Vieira, Daniela; Santana, Isabel; Resende Oliveira, Catarina (J Alzheimers Dis, 2020)
BACKGROUND: Mild cognitive impairment (MCI) has been considered as a pre-dementia stage, although the factors leading to Alzheimer's disease (AD) conversion remain controversial. OBJECTIVE: Evaluate whether TOMM40 poly-T (TOMM40' 523) polymorphism is associated with the risk and conversion time from MCI to AD and secondly with AD cerebrospinal fluid (CSF) biomarkers, disentangling the APOE genotype. METHODS: 147 AD patients, 102 MCI patients, and 105 cognitively normal controls were genotyped for poly-T polymorphism. MCI patients were subdivided into two groups, the group of patients that converted to AD (MCI-AD) and the group of those that remained stable (MCI-S). RESULTS: TOMM40' 523 L allele was significantly more frequent in the MCI-AD group and having at least one L allele significantly increased the risk of conversion from MCI to AD (OR = 8.346, p <  0.001, 95% CI: 2.830 to 24.617). However, when adjusted for the presence of APOEɛ4 allele, both the L allele and ɛ4 allele lost significance in the model (p >  0.05). We then analyzed the APOEɛ4-TOMM40' 523 haplotype and observed that patients carrying this haplotype had significantly higher risk (OR = 5.83; 95% CI = 2.30-14.83) and mean lower times of conversion to AD (p = 0.003). This haplotype was also significantly associated with a biomarker profile compatible with AD (p = 0.007). CONCLUSION: This study shows that the APOEɛ4-TOMM40' 523 haplotype is associated with a higher risk and shorter times of conversion from MCI to AD, possibly driven by CSF biomarkers and mitochondrial dysfunction.

Brain Volume Predicts Behavioral and Psychological Symptoms in Alzheimer's Disease. - Boublay, Nawele; Bouet, Romain; Dorey, Jean-Michel; Padovan, Catherine; Makaroff, Zaza; Federico, Denis; Gallice, Isabelle; Barrellon, Marie-Odile; Robert, Philippe; Moreaud, Olivier; Rouch, Isabelle; Krolak-Salmon, Pierre (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are frequent and troublesome for patients and caregivers. Considering possible preventive approaches, a better understanding of underlying neural correlates of BPSD is crucial. OBJECTIVE: The aim is to assess whether brain regional volume predicts behavioral changes in mild AD. METHODS: This work took part from the PACO study, a multicenter and prospective study that included 252 patients with mild AD from 2009 to 2014. Fifty-three patients were retained. Forty healthy matched control subjects from the ADNI cohort were included as controls. Voxel-based morphometry analysis was conducted to assess regional brain volume using baseline MRI scans as a predictor of future behavioral changes over a period of 18 months. Behavior was assessed at baseline and longitudinally at 6-month intervals using the shortened form of the Neuropsychiatric Inventory (NPI). RESULTS: The volume of 23 brain structures in frontal, temporal, parietal, occipital, subcortical regions and cerebellum predicted the evolution of NPI scores. Frontal volume was the most powerful predictor with frontal gyri, anterior cingulate cortex, and orbital gyri being particularly involved. CONCLUSION: To our knowledge, this is the first study assessing regional brain volumes as predictors of behavioral changes considered at earlier stages of AD. Up to 23 brain structures were associated with an increased risk of developing BPSD. Frontal lobe volume was the strongest predictor of future evolution of NPI. The involvement of multiple structures in the prediction of behavior suggests a role of the main large-scale networks involved in cognition.

Characterizing Clinical and Neuropathological Traits of APOE Haplotypes in African Americans and Europeans. - Mezlini, Aziz M; Magdamo, Colin; Merrill, Emily; Chibnik, Lori B; Blacker, Deborah L; Hyman, Bradley T; Das, Sudeshna (J Alzheimers Dis, 2020)
BACKGROUND: The APOEɛ4 allele is the largest genetic risk factor for late-onset Alzheimer's disease (AD). Recent literature suggested that the contribution of APOEɛ4 to AD risk could be population-specific, with ɛ4 conferring a lower risk to Blacks or African Americans. OBJECTIVE: To investigate the effect of APOE haplotypes on AD risk in individuals with European ancestry (EU) and Blacks or African Americans (AA). METHODS: We selected data from 1) the National Alzheimer's Coordinating Center: a total of 3,486 AD cases and 4,511 controls (N = 7,997, 60% female) with genotypes from the Alzheimer's Disease Genetics Consortium (ADGC), and 2) the Rush University Religious Orders Study and Memory and Aging Project (ROSMAP) cohort with 578 AD and 670 controls (N = 1,248, 60% female). Using ɛ3 homozygotes as the reference, we compared the association of various APOE haplotypes with the clinical and neuropathological correlates of dementia in AA and EU. RESULTS: In both cohorts, we find no difference in the odds or age of onset of AD among the ɛ4-linked haplotypes defined by rs769449 within either AA or EU. Additionally, while APOEɛ4 was associated with a faster rate of decline, no differences were found in rate of decline, clinical or neuropathological features among the ɛ4-linked haplotypes. Further analysis with other variants near the APOE locus failed to identify any effect modification. CONCLUSION: Our study finds similar effects of the ɛ4-linked haplotypes defined by rs769449 on AD as compared to ɛ3 in both AA and EU. Future studies are required to understand the heterogeneity of APOE conferred risk of AD among various genotypes and populations.

Common Bacterial Infections and Risk of Dementia or Cognitive Decline: A Systematic Review. - Muzambi, Rutendo; Bhaskaran, Krishnan; Brayne, Carol; Davidson, Jennifer A; Smeeth, Liam; Warren-Gash, Charlotte (J Alzheimers Dis, 2020)
BACKGROUND: Bacterial infections may be associated with dementia, but the temporality of any relationship remains unclear. OBJECTIVES: To summarize existing literature on the association between common bacterial infections and the risk of dementia and cognitive decline in longitudinal studies. METHODS: We performed a comprehensive search of 10 databases of published and grey literature from inception to 18 March 2019 using search terms for common bacterial infections, dementia, cognitive decline, and longitudinal study designs. Two reviewers independently performed the study selection, data extraction, risk of bias and overall quality assessment. Data were summarized through a narrative synthesis as high heterogeneity precluded a meta-analysis. RESULTS: We identified 3,488 studies. 9 met the eligibility criteria; 6 were conducted in the United States and 3 in Taiwan. 7 studies reported on dementia and 2 investigated cognitive decline. Multiple infections were assessed in two studies. All studies found sepsis (n = 6), pneumonia (n = 3), urinary tract infection (n = 1), and cellulitis (n = 1) increased dementia risk (HR 1.10; 95% CI 1.02-1.19) to (OR 2.60; 95% CI 1.84-3.66). The range of effect estimates was similar when limited to three studies with no domains at high risk of bias. However, the overall quality of evidence was rated very low. Studies on cognitive decline found no association with infection but had low power. CONCLUSION: Our review suggests common bacterial infections may be associated with an increased risk of subsequent dementia, after adjustment for multiple confounders, but further high-quality, large-scale longitudinal studies, across different healthcare settings, are recommended to further explore this association.

Comorbidity of Cerebrovascular and Alzheimer's Disease in Aging. - Xia, Ying; Yassi, Nawaf; Raniga, Parnesh; Bourgeat, Pierrick; Desmond, Patricia; Doecke, James; Ames, David; Laws, Simon M; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph; Maruff, Paul; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease often coexists with Alzheimer's disease (AD). While both diseases share common risk factors, their interrelationship remains unclear. Increasing the understanding of how cerebrovascular changes interact with AD is essential to develop therapeutic strategies and refine biomarkers for early diagnosis. OBJECTIVE: We investigate the prevalence and risk factors for the comorbidity of amyloid-β (Aβ) and cerebrovascular disease in the Australian Imaging, Biomarkers and Lifestyle Study of Ageing, and further examine their cross-sectional association. METHODS: A total of 598 participants (422 cognitively normal, 89 with mild cognitive impairment, 87 with AD) underwent positron emission tomography and structural magnetic resonance imaging for assessment of Aβ deposition and cerebrovascular disease. Individuals were categorized based on the comorbidity status of Aβ and cerebrovascular disease (V) as Aβ-V-, Aβ-V+, Aβ+V-, or Aβ+V+. RESULTS: Advancing age was associated with greater likelihood of cerebrovascular disease, high Aβ load and their comorbidity. Apolipoprotein E ɛ4 carriage was only associated with Aβ positivity. Greater total and regional WMH burden were observed in participants with AD. However, no association were observed between Aβ and WMH measures after stratification by clinical classification, suggesting that the observed association between AD and cerebrovascular disease was driven by the common risk factor of age. CONCLUSION: Our observations demonstrate common comorbid condition of Aβ and cerebrovascular disease in later life. While our study did not demonstrate a convincing cross-sectional association between Aβ and WMH burden, future longitudinal studies are required to further confirm this.

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

Computational Modeling of Catecholamines Dysfunction in Alzheimer's Disease at Pre-Plaque Stage. - Caligiore, Daniele; Silvetti, Massimo; D'Amelio, Marcello; Puglisi-Allegra, Stefano; Baldassarre, Gianluca (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) etiopathogenesis remains partially unexplained. The main conceptual framework used to study AD is the Amyloid Cascade Hypothesis, although the failure of recent clinical experimentation seems to reduce its potential in AD research. OBJECTIVE: A possible explanation for the failure of clinical trials is that they are set too late in AD progression. Recent studies suggest that the ventral tegmental area (VTA) degeneration could be one of the first events occurring in AD progression (pre-plaque stage). METHODS: Here we investigate this hypothesis through a computational model and computer simulations validated with behavioral and neural data from patients. RESULTS: We show that VTA degeneration might lead to system-level adjustments of catecholamine release, triggering a sequence of events leading to relevant clinical and pathological signs of AD. These changes consist first in a midfrontal-driven compensatory hyperactivation of both VTA and locus coeruleus (norepinephrine) followed, with the progression of the VTA impairment, by a downregulation of catecholamine release. These processes could then trigger the neural degeneration at the cortical and hippocampal levels, due to the chronic loss of the neuroprotective role of norepinephrine. CONCLUSION: Our novel hypothesis might contribute to the formulation of a wider system-level view of AD which might help to devise early diagnostic and therapeutic interventions.

The Contribution of Vascular Pathology Toward Cognitive Impairment in Older Individuals with Intermediate Braak Stage Tau Pathology. - Robinson, Andrew C; Roncaroli, Federico; Chew-Graham, Stephen; Davidson, Yvonne S; Minshull, James; Horan, Michael A; Payton, Antony; Pendleton, Neil; Mann, David M A (J Alzheimers Dis, 2020)
BACKGROUND: The pathological features of Alzheimer's disease (AD) are well described but little is known as to how both neurodegeneration and vascular changes might interact in causing cognitive impairment. OBJECTIVE: The present study aims to investigate relationships between vascular and AD pathology in cognitively healthy and cognitively impaired individuals with a particular emphasis on those at intermediate Braak tau stages. METHODS: We investigated the interplay between Braak tau stage and measures of vascular pathology as described by the vascular cognitive impairment neuropathology guidelines (VCING) in 185 brains from the Brains for Dementia Research programme and The University of Manchester Longitudinal Study of Cognition in Healthy Old Age. VCING asserts that at least one large (>10 mm) infarct, moderate/severe occipital leptomeningeal cerebral amyloid angiopathy, and moderate/severe arteriosclerosis in occipital white matter accurately predicts the contribution of cerebrovascular pathology to cognitive impairment. RESULTS: We found that the extent of arteriosclerosis in the occipital white matter did not differ between cognitive groups at intermediate (III-IV) Braak stages whereas moderate/severe leptomeningeal occipital cerebral amyloid angiopathy was greater in cognitively impaired than normal individuals at Braak stage III-IV. This finding remained significant after controlling for effects of age, sex, CERAD score, Thal phase, presence/severity of primary age-related tauopathy, presence/severity of limbic-predominant age-related TDP43 encephalopathy and small vessel disease in basal ganglia. CONCLUSION: Interventions targeting cerebral amyloid angiopathy may contribute to delay the onset of cognitive impairment in individuals with intermediate Alzheimer's type pathology.

Day-to-Day Home Blood Pressure Variability is Associated with Cerebral Small Vessel Disease Burden in a Memory Clinic Population. - de Heus, Rianne A A; Reumers, Stacha F I; van der Have, Alba; Tumelaire, Maxime; Tully, Phillip J; Claassen, Jurgen A H R (J Alzheimers Dis, 2020)
BACKGROUND: High visit-to-visit blood pressure variability (BPV) has been associated with cognitive decline and cerebral small vessel disease (cSVD), in particular cerebrovascular lesions. Whether day-to-day BPV also relates to cSVD has not been investigated. OBJECTIVE: To investigate the cross-sectional association between day-to-day BPV and total cSVD MRI burden in older memory clinic patients. METHODS: We included outpatients referred to our memory clinic, who underwent cerebral MRI as part of their diagnostic assessment. We determined the validated total cSVD score (ranging from 0-4) by combining four markers of cSVD that were visually rated. Home blood pressure (BP) measurements were performed for one week, twice a day, according to international guidelines. BPV was defined as the within-subject coefficient of variation (CV; standard deviation/mean BP*100). We used multivariable ordinal logistic regression analyses adjusted for age, sex, smoking, diabetes, antihypertensive medication, history of cardiovascular disease, and mean BP. RESULTS: For 82 patients (aged 71.2±7.9 years), mean home BP was 140/79±15/9 mmHg. Dementia and mild cognitive impairment were diagnosed in 46% and 34%, respectively. 78% had one or more markers of cSVD. Systolic CV was associated with cSVD burden (adjusted odds ratio per point increase in CV = 1.29, 95% confidence interval = 1.04-1.60, p = 0.022). There were no differences in diastolic CV and mean BP between the cSVD groups. When we differentiated between morning and evening BP, only evening BPV remained significantly associated with total cSVD burden. CONCLUSION: Day-to-day systolic BPV is associated with cSVD burden in memory clinic patients. Future research should indicate whether lowering BPV should be included in BP management in older people with memory complaints.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Dyadic Group Exercises for Persons with Memory Deficits and Care Partners: Mixed-Method Findings from the Paired Preventing Loss of Independence through Exercise (PLIÉ) Randomized Trial. - Mehling, E Wolf; Scott, M Travis; Duffy, James; Whitmer, A Rachel; Chesney, A Margaret; Boscardin, W John; Barnes, E Deborah (J Alzheimers Dis, 2020)
BACKGROUND: Non-pharmacological therapies for persons with dementia (PWD) are needed. OBJECTIVE: To develop and test the Paired Preventing Loss of Independence through Exercise (PLIÉ) program, an integrative group movement program for PWD and care partners (CPs). METHODS: Participants were randomized to immediate or delayed start to Paired PLIÉ in community-based classes (1 hour, 2 days/week, 12 weeks, 3 home visits). Co-primary outcomes included standard measures of cognition, physical function,and quality of life (PWD) and caregiver burden (CPs) assessed by blinded assessors, analyzed using linear mixed models to calculate effect sizes for outcome changes during Paired PLIÉ, controlling for randomization group. Anonymous satisfaction surveys included satisfaction ratings and thematic analysis of open-ended responses. RESULTS: Thirty dyads enrolled, 24 (80%) completed. PWD (mean age 80; 55% female) experienced significant improvement in self-rated quality of life (Effect Size+0.23; p = 0.016) when participating in Paired PLIÉ, while CPs experienced a non-significant increase in burden (-0.23, p = 0.079). Changes in physical and cognitive function in PWD were not significant. All CPs returning the satisfaction survey (n = 20) reported being moderately-to-highly satisfied with the program. Thematic analyses identified physical (e.g., sit-to-stand, more energy), emotional (enjoyment), and social benefits (peer-to-peer interaction) for PWD and CPs; challenges were primarily related to getting to the in-person classes. CONCLUSION: Paired PLIÉ is a promising integrative group movement program that warrants further study. It is feasible and may improve self-rated quality of life in PWD. Although CPs may experience increased burden due to logistical challenges, most reported high satisfaction and physical, emotional, and social benefits.

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Effects of Probiotic Supplementation on Short Chain Fatty Acids in the AppNL-G-F Mouse Model of Alzheimer's Disease. - Kaur, Harpreet; Golovko, Svetlana; Golovko, Mikhail Y; Singh, Surjeet; Darland, Diane C; Combs, Colin K (J Alzheimers Dis, 2020)
BACKGROUND: The intestinal microbiota and its metabolites, particularly short-chain fatty acids (SCFAs), have been implicated in immune function, host metabolism, and even behavior. OBJECTIVE: This study was performed to investigate whether probiotic administration influences levels of intestinal microbiota and their metabolites in a fashion that may attenuate brain changes in a mouse model of Alzheimer's disease (AD). METHODS: C57BL/6 wild-type (WT) mice were compared to AppNL-G-Fmice. The animals were treated with either vehicle or probiotic (VSL#3) for 8 weeks. Fecal microbiome analysis along with Aβ, GFAP, Iba-1, c-Fos, and Ki-67 immunohistochemistry was done. SCFAs were analyzed in serum and brains using UPLC-MS/MS. RESULTS: Probiotic (VSL#3) supplementation for 2 months resulted in altered microbiota in both WT and AppNL-G-Fmice. An increase in serum SCFAs acetate, butyrate, and lactate were found in both genotypes following VSL#3 treatment. Propionate and isobutyrate were only increased in AppNL-G-Fmice. Surprisingly, VSL#3 only increased lactate and acetate in brains of AppNL-G-Fmice. No significant differences were observed between vehicle and VSL#3 fed AppNL-G-Fhippocampal immunore activities of Aβ, GFAP, Iba-1, and Ki-67. However, hippocampal c-Fos staining increased in VSL#3 fed AppNL-G-Fmice. CONCLUSION: These data demonstrate intestinal dysbiosis in the AppNL-G-Fmouse model of AD. Probiotic VSL#3 feeding altered both serum and brain levels of lactate and acetate in AppNL-G-Fmice correlating with increased expression of the neuronal activity marker, c-Fos.

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Epilepsy in Neurodegenerative Dementias: A Clinical, Epidemiological, and EEG Study. - Arnaldi, Dario; Donniaquio, Andrea; Mattioli, Pietro; Massa, Federico; Grazzini, Matteo; Meli, Riccardo; Filippi, Laura; Grisanti, Stefano; Famá, Francesco; Terzaghi, Michele; Girtler, Nicola; Brugnolo, Andrea; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Seizures are common in patients with dementia but precise epidemiologic data of epilepsy in neurodegenerative dementia is lacking. OBJECTIVE: The first aim of the study was to investigate prevalence and clinical characteristics of epilepsy in a large cohort of patients with neurodegenerative dementias. Subsequently, we explored clinical, neuropsychological, and quantitative electroencephalogram (qEEG) data of Alzheimer's disease (AD) patients with epilepsy (AD-EPI) as compared to AD patients without epilepsy (AD-CTR). METHODS: We retrospectively evaluated consecutive patients with a diagnosis of a neurodegenerative dementia and a clinically diagnosed epilepsy that required antiepileptic drugs (AED). All patients underwent baseline comprehensive neuropsychological assessment. A follow-up of at least one year was requested to confirm the dementia diagnosis. In AD patients, qEEG power band analysis was performed. AD-CTR and AD-EPI patients were matched for age, Mini-Mental State Examination score, and gender. RESULTS: Thirty-eight out of 2,054 neurodegenerative dementia patients had epilepsy requiring AED. The prevalence of epilepsy was 1.82% for AD, 1.28% for the behavioral variant of frontotemporal dementia (bvFTD), 2.47% for dementia with Lewy bodies (DLB), and 12% for primary progressive aphasia. Epilepsy were more drug-responsive in AD than in non-AD dementias. Finally, no significant differences were found in neuropsychological and qEEG data between AD-EPI and AD-CTR patients. CONCLUSION: In our cohort, AD, FTD, and DLB dementias have similar prevalence of epilepsy, even if AD patients were more responsive to AED. Moreover, AD-EPI patients did not have significant clinical, neuropsychological qEEG differences compared with AD-CTR patients.

An Exploratory Phase IIa Study of the PPAR delta/gamma Agonist T3D-959 Assessing Metabolic and Cognitive Function in Subjects with Mild to Moderate Alzheimer's Disease. - Chamberlain, Stanley; Gabriel, Hoda; Strittmatter, Warren; Didsbury, John (J Alzheimers Dis, 2020)
BACKGROUND: T3D-959 is a chemically unique, brain penetrant, dual PPAR delta/gamma agonist with 15-fold higher PPAR delta selectivity. Ubiquitous brain expression of PPAR delta, its critical role in regulating glucose and lipid metabolism, and the Alzheimer's disease (AD)-like phenotype of PPAR delta null mice motivated this study. OBJECTIVE: To determine safety and tolerability of multiple doses of T3D-959 in subjects with mild to moderate AD, examine systemic and central drug pharmacology and in an exploratory manner, perform cognitive assessments. METHODS: Thirty-four subjects with mild-to-moderate AD were orally administered 3, 10, 30, or 90 mg of T3D-959 daily for 14 days. There was no inclusion of a placebo arm. Safety and tolerability were monitored. Systemic drug pharmacology was examined via plasma metabolomics LC-MS-MS analysis, cerebral drug pharmacology via FDG-PET measures of changes in Relative CMRgl (R CMRgl, AD-effected regions relative to brain reference regions), and cognitive function assessed before and after drug treatment and again one week after completion of drug treatment, by ADAS-cog11 and the Digit Symbol Substitution Test (DSST). RESULTS: T3D-959 was in general safe and well tolerated. Single point pharmacokinetics at the Tmax showed dose dependent exposure. Plasma metabolome profile changes showed dose-dependent systemic effects on lipid metabolism and metabolism related to insulin sensitization. Relative FDG-PET imaging demonstrated dose-dependent, regional, effects of T3D-959 on R CMRgl based on the use of multiple reference regions. ADAS-cog11 and DSST cognitive assessments showed improvements with possible ApoE genotype association and pharmacodynamics related to the mechanism of drug action. CONCLUSIONS: Exploratory data from this Phase IIa clinical trial supports further clinical investigation of T3D-959 in a larger placebo-controlled clinical study.

Fascicle- and Glucose-Specific Deterioration in White Matter Energy Supply in Alzheimer's Disease. - Roy, Maggie; Rheault, François; Croteau, Etienne; Castellano, Christian-Alexandre; Fortier, Mélanie; St-Pierre, Valérie; Houde, Jean-Christophe; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C; Descoteaux, Maxime (J Alzheimers Dis, 2020)
BACKGROUND: White matter energy supply to oligodendrocytes and the axonal compartment is crucial for normal axonal function. Although gray matter glucose hypometabolism is extensively reported in Alzheimer's disease (AD), glucose and ketones, the brain's two main fuels, are rarely quantified in white matter in AD. OBJECTIVE: Using adual-tracer PET method combined with a fascicle-specific diffusion MRI approach, robust to white matter hyper intensities and crossing fibers, we aimed to quantify both glucose and ketone metabolismin specific white matter fascicles associated with mild cognitive impairment (MCI; n = 51) and AD (n = 13) compared to cognitively healthy age-matched controls (Controls; n = 14). METHODS: Eight white matter fascicles of the limbic lobe and corpus callosum were extracted and analyzed into fascicle profiles of five sections. Glucose (18F-fluorodeoxyglucose) and ketone (11C-acetoacetate) uptake rates, corrected for partial volume effect, were calculated along each fascicle. RESULTS: The only fascicle with significantly lower glucose uptake in AD compared to Controls was the left posterior cingulate segment of the cingulum (-22%; p = 0.016). Non-significantly lower glucose uptake in this fascicle was also observed in MCI. In contrast to glucose, ketone uptake was either unchanged or higher in sections of the fornix and parahippocampal segment of the cingulum in AD. CONCLUSION: To our knowledge, this is the first report of brain fuel uptake calculated along white matter fascicles in humans. Energetic deterioration in white matter in AD appears to be specific to glucose and occurs first in the posterior cingulum.

Functional Connectivity Alterations of the Temporal Lobe and Hippocampus in Semantic Dementia and Alzheimer's Disease. - Schwab, Simon; Afyouni, Soroosh; Chen, Yan; Han, Zaizhu; Guo, Qihao; Dierks, Thomas; Wahlund, Lars-Olof; Grieder, Matthias (J Alzheimers Dis, 2020)
BACKGROUND: Semantic memory impairments in semantic dementia are attributed to atrophy and functional disruption of the anterior temporal lobes. In contrast, the posterior medial temporal neurodegeneration found in Alzheimer's disease is associated with episodic memory disturbance. The two dementia subtypes share hippocampal deterioration, despite a relatively spared episodic memory in semantic dementia. OBJECTIVE: To unravel mutual and divergent functional alterations in Alzheimer's disease and semantic dementia, we assessed functional connectivity between temporal lobe regions in Alzheimer's disease (n = 16), semantic dementia (n = 23), and healthy controls (n = 17). METHODS: In an exploratory study, we used a functional parcellation of the temporal cortex to extract time series from 66 regions for correlation analysis. RESULTS: Apart from differing connections between Alzheimer's disease and semantic dementia that yielded reduced functional connectivity, we identified a common pathway between the right anterior temporal lobe and the right orbitofrontal cortex in both dementia subtypes. This disconnectivity might be related to social knowledge deficits as part of semantic memory decline. However, such interpretations are preferably made in a holistic context of disease-specific semantic impairments and functional connectivity changes. CONCLUSION: Despite a major limitation owed to unbalanced databases between study groups, this study provides a preliminary picture of the brain's functional disconnectivity in Alzheimer's disease and semantic dementia. Future studies are needed to replicate findings of a common pathway with consistent diagnostic criteria and neuropsychological evaluation, balanced designs, and matched data MRI acquisition procedures.

Gait Disturbances are Associated with Increased Cognitive Impairment and Cerebrospinal Fluid Tau Levels in a Memory Clinic Cohort. - Muurling, Marijn; Rhodius-Meester, Hanneke F M; Pärkkä, Juha; van Gils, Mark; Frederiksen, Kristian S; Bruun, Marie; Hasselbalch, Steen G; Soininen, Hilkka; Herukka, Sanna-Kaisa; Hallikainen, Merja; Teunissen, Charlotte E; Visser, Pieter Jelle; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Gait analysis with accelerometers is a relatively inexpensive and easy to use method to potentially support clinical diagnoses of Alzheimer's disease and other dementias. It is not clear, however, which gait features are most informative and how these measures relate to Alzheimer's disease pathology. OBJECTIVE: In this study, we tested if calculated features of gait 1) differ between cognitively normal subjects (CN), mild cognitive impairment (MCI) patients, and dementia patients, 2) are correlated with cerebrospinal fluid (CSF) biomarkers related to Alzheimer's disease, and 3) predict cognitive decline. METHODS: Gait was measured using tri-axial accelerometers attached to the fifth lumbar vertebra (L5) in 58 CN, 58 MCI, and 26 dementia participants, while performing a walk and dual task. Ten gait features were calculated from the vertical L5 accelerations, following principal component analysis clustered in four domains, namely pace, rhythm, time variability, and length variability. Cognitive decline over time was measured using MMSE, and CSF biomarkers were available in a sub-group. RESULTS: Linear mixed models showed that dementia patients had lower pace scores than MCI patients and CN subjects (p < 0.05). In addition, we found associations between the rhythm domain and CSF-tau, especially in the dual task. Gait was not associated with CSF Aβ42 levels and cognitive decline over time as measured with the MMSE. CONCLUSION: These findings suggest that gait-particularly measures related to pace and rhythm-are altered in dementia and have a direct link with measures of neurodegeneration.

The Impact of Amyloid-β or Tau on Cognitive Change in the Presence of Severe Cerebrovascular Disease. - Jang, Hyemin; Kim, Hee Jin; Sim Choe, Yeong; Kim, Soo-Jong; Park, Seongbeom; Kim, Yeshin; Woon Kim, Ko; Hyoung Lyoo, Chul; Cho, Hanna; Hoon Ryu, Young; Choi, Jae Yong; DeCarli, Charles; et al. (J Alzheimers Dis, 2020)
BACKGROUND: As Alzheimer's disease (AD) and cerebral small vessel disease (CSVD) commonly coexist, the interaction between two has been of the considerable interest. OBJECTIVE: We determined whether the association of Aβ and tau with cognitive decline differs by the presence of significant CSVD. METHODS: We included 60 subcortical vascular cognitive impairment (SVCI) from Samsung Medical Center and 82 Alzheimer's disease-related cognitive impairment (ADCI) from ADNI, who underwent Aβ (florbetaben or florbetapir) and tau (flortaucipir, FTP) PET imaging. They were retrospectively assessed for 5.0±3.9 and 5.6±1.9 years with Clinical Dementia Rating-sum of boxes (CDR-SB)/Mini-Mental State Examination (MMSE). Mixed effects models were used to investigate the interaction between Aβ/tau and group on CDR-SB/MMSE changes. RESULTS: The frequency of Aβ positivity (45% versus 54.9%, p = 0.556) and mean global FTP SUVR (1.17±0.21 versus 1.16±0.17, p = 0.702) were not different between the two groups. We found a significant interaction effect of Aβ positivity and SVCI group on CDR-SB increase/MMSE decrease (p = 0.013/p <  0.001) change, and a significant interaction effect of global FTP uptake and SVCI group on CDR-SB increase/MMSE decrease (p <  0.001 and p = 0.030) change. Finally, the interaction effects of regional tau and group were prominent in the Braak III/IV (p = 0.001) and V/VI (p = 0.003) not in Braak I/II region (p = 0.398). CONCLUSION: The association between Aβ/tau and cognitive decline is stronger in SVCI than in ADCI. Therefore, our findings suggested that Aβ positivity or tau burden (particularly in the Braak III/IV or V/VI regions) and CSVD might synergistically affect cognitive decline.

In Vivo Validation of a Small Molecule Inhibitor of Tau Self-Association in htau Mice. - Davidowitz, Eliot J; Krishnamurthy, Pavan K; Lopez, Patricia; Jimenez, Heidy; Adrien, Leslie; Davies, Peter; Moe, James G (J Alzheimers Dis, 2020)
Tau oligomers have been shown to transmit tau pathology from diseased neurons to healthy neurons through seeding, tau misfolding, and aggregation that is thought to play an influential role in the progression of Alzheimer's disease (AD) and related tauopathies. To develop a small molecule therapeutic for AD and related tauopathies, we have developed in vitro and cellular assays to select molecules inhibiting the first step in tau aggregation, the self-association of tau into oligomers. In vivo validation studies of an optimized lead compound were independently performed in the htau mouse model of tauopathy that expresses the human isoforms of tau without inherited tauopathy mutations that are irrelevant to AD. Treated mice did not show any adverse events related to the compound. The lead compound significantly reduced the level of self-associated tau and total and phosphorylated insoluble tau aggregates. The dose response was linear with respect to levels of compound in the brain. A confirmatory study was performed with male htau mice that gave consistent results. The results validated our screening approach by showing that targeting tau self-association can inhibit the entire tau aggregation pathway by using the selected and optimized lead compound whose activity translated from in vitro and cellular assays to an in vivo model of tau aggregation.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Music Playlists for People with Dementia: Trialing A Guide for Caregivers. - Garrido, Sandra; Dunne, Laura; Stevens, Catherine J; Chang, Esther (J Alzheimers Dis, 2020)
BACKGROUND: Music programs have the potential to provide an effective non-pharmacological tool for caregivers to reduce depression and agitation and increase quality of life in people with dementia. However, where such programs are not facilitated by a trained music therapist, caregivers need greater access to information about how to use music most effectively in response to key challenges to care, and how to pre-empt and manage adverse responses. OBJECTIVE: This study reports on the trial of a Guide for use of music with 45 people with dementia and their caregivers in residential care facilities and home-based care. METHODS: The study used a pre-post experimental design in which participants were randomly allocated to a treatment group or a waitlist control group. RESULTS: Improvements to quality of life were found in the experimental group over the 6-week period. Significant increases in Interest, Responsiveness, Initiation, Involvement, and Enjoyment were reported for individual listening sessions. CONCLUSION: The Guide can provide an effective protocol for caregivers to follow in selecting music to manage particular challenges to care, confirming the need for caregivers to be prepared to monitor and manage potential negative responses.

Neuroimaging in Vascular Cognitive Impairment and Dementia: A Systematic Review. - Frantellizzi, Viviana; Pani, Arianna; Ricci, Maria; Locuratolo, Nicoletta; Fattapposta, Francesco; De Vincentis, Giuseppe (J Alzheimers Dis, 2020)
Cerebrovascular diseases are well established causes of cognitive impairment. Different etiologic entities, such as vascular dementia (VaD), vascular cognitive impairment, subcortical (ischemic) VaD, and vascular cognitive disorder, are included in the umbrella definition of vascular cognitive impairment and dementia (VCID). Because of the variability of VCID clinical presentation, there is no agreement on criteria defining the neuropathological threshold of this disorder. In fact, VCID is characterized by cerebral hemodynamic alteration which ranges from decreased cerebral blood flow to small vessels disease and involves a multifactorial process that leads to demyelination and gliosis, including blood-brain barrier disruption, hypoxia, and hypoperfusion, oxidative stress, neuroinflammation and alteration on neurovascular unit coupling, cerebral microbleeds, or superficial siderosis. Numerous criteria for the definition of VaD have been described: the National Institute of Neurological Disorders and Stroke Association Internationale pour Recherche'-et-l'Enseignement en Neurosciences criteria, the State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria, DSM-V criteria, the Diagnostic Criteria for Vascular Cognitive Disorders (a VASCOG Statement), and Vascular Impairment of Cognition Classification Consensus Study. Neuroimaging is fundamental for definition and diagnosis of VCID and should be used to assess the extent, location, and type of vascular lesions. MRI is the most sensible technique, especially if used according to standardized protocols, even if CT plays an important role in several conditions. Functional neuroimaging, in particular functional MRI and PET, may facilitate differential diagnosis among different forms of dementia. This systematic review aims to explore the state of the art and future perspective of non-invasive diagnostics of VCID.

New BACE1 Chimeric Peptide Inhibitors Selectively Prevent AβPPβ Cleavage Decreasing Amyloid-β Production and Accumulation in Alzheimer's Disease Models. - Resende, Rosa; Ferreira-Marques, Marisa; Moreira, Patrícia; Coimbra, Judite R M; Baptista, Salete J; Isidoro, Ciro; Salvador, Jorge A R; Dinis, Teresa C P; Pereira, Cláudia F; Santos, Armanda E (J Alzheimers Dis, 2020)
BACKGROUND: A disease-modifying therapy for Alzheimer's disease (AD) is still an unmet clinical need. The formation of amyloid-β (Aβ) requires the initial cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (beta-site AβPP cleaving enzyme 1), which is a prime therapeutic target for AD. OBJECTIVE: We aimed to design and develop a selective BACE1 inhibitor suitable to AD treatment. METHODS: The new BACE1 inhibitors consist on a chimeric peptide including a sequence related to the human Swedish mutant form of AβPP (AβPPswe) conjugated with the TAT carrier that facilitates cell membrane permeation and the crossing of the blood-brain barrier. Additionally to the chimeric peptide in the L-form, we developed a D-retro in verso chimeric peptide. The latter strategy, never used with BACE1 inhibitors, is considered to favor a significantly higher half-life and lower immunogenicity. RESULTS: We found that both chimeric peptides inhibit recombinant BACE1 activity and decrease Aβ40/42 production in Neuro-2a (N2A) cells expressing AβPPswe without inducing cytotoxicity. The intraperitoneal administration of these peptides to 3xTg-AD mice decreased plasma and brain Aβ40/42 levels, as well as brain soluble AβPPβ production. Also, a reduction of insoluble Aβ was observed in the brain after chronic treatment. Noteworthy, the chimeric peptides selectively inhibited the AβPPβ cleavage relatively to the proteolysis of other BACE1 substrates such as close homologue of L1 (CHL1) and seizure-related gene 6 (SEZ6). CONCLUSIONS: Overall these new BACE1 chimeric peptideshold promising potential as a selective disease-modifying therapy for AD.

A New Serum Biomarker Set to Detect Mild Cognitive Impairment and Alzheimer's Disease by Peptidome Technology. - Abe, Koji; Shang, Jingwei; Shi, Xiaowen; Yamashita, Toru; Hishikawa, Nozomi; Takemoto, Mami; Morihara, Ryuta; Nakano, Yumiko; Ohta, Yasuyuki; Deguchi, Kentaro; Ikeda, Masaki; Ikeda, Yoshio; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Because dementia is an emerging problem in the world, biochemical markers of cerebrospinal fluid (CSF) and radio-isotopic analyses are helpful for diagnosing Alzheimer's disease (AD). Although blood sample is more feasible and plausible than CSF or radiological biomarkers for screening potential AD, measurements of serum amyloid- β (Aβ), plasma tau, and serum antibodies for Aβ1 - 42 are not yet well established. OBJECTIVE: We aimed to identify a new serum biomarker to detect mild cognitive impairment (MCI) and AD in comparison to cognitively healthy control by a new peptidome technology. METHODS: With only 1.5μl of serum, we examined a new target plate "BLOTCHIP®" plus a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) to discriminate control (n = 100), MCI (n = 60), and AD (n = 99). In some subjects, cognitive Mini-Mental State Examination (MMSE) were compared to positron emission tomography (PET) with Pittsburgh compound B (PiB) and the serum probability of dementia (SPD). The mother proteins of candidate serum peptides were examined in autopsied AD brains. RESULTS: Apart from Aβ or tau, the present study discovered a new diagnostic 4-peptides-set biomarker for discriminating control, MCI, and AD with 87% of sensitivity and 65% of specificity between control and AD (***p < 0.001). MMSE score was well correlated to brain Aβ deposition and to SPD of AD. The mother proteins of the four peptides were upregulated for coagulation, complement, and plasticity (three proteins), and was downregulated for anti-inflammation (one protein) in AD brains. CONCLUSION: The present serum biomarker set provides a new, rapid, non-invasive, highly quantitative and low-cost clinical application for dementia screening, and also suggests an alternative pathomechanism of AD for neuroinflammation and neurovascular unit damage.

Normal Pressure Hydrocephalus in Down Syndrome: The Report of Two Cases. - Marano, Massimo; Pompucci, Angelo; Motolese, Francesco; Rossi, Mariagrazia; Coletta, Ernesto; Di Lazzaro, Vincenzo; Fasano, Alfonso; Petrella, Gianpaolo (J Alzheimers Dis, 2020)
Down syndrome (DS) is the most common cause of intellectual disability in infants and has a well-known relationship with the Alzheimer's disease. The association between DS and the other pathologies of senescence, such as normal pressure hydrocephalus (NPH), has been poorly investigated. This series included two DS patients with NPH. In both cases, NPH symptoms were initially misdiagnosed as DS associated senescence. Patients were treated with ventricular-peritoneal shunt, showing a sustained improvement (1 and 4 years of follow-up). To our knowledge, this is the first description of the occurrence of NPH in adult patients with DS and surgical outcomes.

Odor Identification Impairment and Change with Cholinesterase Inhibitor Treatment in Mild Cognitive Impairment. - Devanand, D P; Liu, Xinhua; Chunga, Richard E; Cohen, Hannah; Andrews, Howard; Schofield, Peter W; Stern, Yaakov; Huey, Edward D; Choi, Jongwoo; Pelton, Gregory H (J Alzheimers Dis, 2020)
BACKGROUND: Anticholinergic challenge can induce odor identification impairment that indicates Alzheimer's disease (AD) pathology, and short-term change in odor identification impairment with cholinesterase inhibitor (CheI) treatment may predict longer term cognitive outcomes. OBJECTIVE: In patients with mild cognitive impairment (MCI) treated prospectively with donepezil, a CheI, for 52 weeks, to determine if 1) acute decline in odor identification ability with anticholinergic challenge can predict cognitive improvement, and 2) change in odor identification over 8 weeks can predict cognitive improvement. METHODS: MCI was diagnosed clinically without AD biomarkers. At baseline, the University of Pennsylvania Smell identification Test (UPSIT) was administered before and after an anticholinergic atropine nasal spray challenge. Donepezil was started at 5 mg daily, increased to 10 mg daily if tolerated, and this dose was maintained for 52 weeks. Main outcomes were ADAS-Cog total score and Selective Reminding Test (SRT) total immediate recall score measured at baseline, 26 and 52 weeks. RESULTS: In 100 study participants, mean age 70.14 (SD 9.35) years, atropine-induced decrease in UPSIT score at baseline was not associated with change in ADAS-Cog or SRT scores over 52 weeks. Change in UPSIT score from 0 to 8 weeks did not show a significant association with change in the ADAS-Cog or SRT measures over 52 weeks. CONCLUSION: These negative findings in a relatively large sample of patients with MCI did not replicate results in much smaller samples. Change in odor identification with anticholinergic challenge, and over 8 weeks, may not be useful predictors of cognitive improvement with CheI in patients with MCI.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Oxidized Products of Omega-6 and Omega-3 Long Chain Fatty Acids Are Associated with Increased White Matter Hyperintensity and Poorer Executive Function Performance in a Cohort of Cognitively Normal Hypertensive Older Adults. - Shinto, Lynne; Lahna, David; Murchison, Charles F; Dodge, Hiroko; Hagen, Kirsten; David, Jason; Kaye, Jeffrey; Quinn, Joseph F; Wall, Rachel; Silbert, Lisa C (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease is a common cause of dementia in older adults, and potentially preventable with early intervention. Oxylipins are produced from the oxidation of long-chain polyunsaturated fatty acids (PUFA) possessing potent vascular effects. Oxylipins generated from the cytochrome P450 pathway are enzymatically converted to diols by soluble epoxide hydrolase (sEH); sEH products have been associated with small vessel ischemic disease. Little is known about oxylipins' impact on markers of dementia risk. OBJECTIVE: An exploratory examination of the association between omega-6 and omega-3 derived oxylipins, brain MRI, and cognition. METHODS: Thirty-seven non-demented participants with controlled hypertension (mean age 65.6 years) were enrolled in a dementia prevention study investigating fish oil and lipoic acid on preserving cognitive function. Baseline associations between plasma oxylipins, white matter hyperintensity (WMH), and Trails-B were examined using linear regression. P450-derived diol/epoxide ratio was an indirect measure of sEH activity. RESULTS: Omega-6 derived 9-HODE was associated with increased WMH (p = 0.017) and reduced grey matter volume (p = 0.02). Omega-6 P450-derived diol/epoxide ratio 9,10-DiHOME/9,10-EpOME was associated with increased WMH (p = 0.035) and poorer performance on Trails-B (p = 0.05); ratio14,15-DHET/14,15-EET was associated with increased WMH (p = 0.045). Omega-3 P450-derived diol/epoxide ratio 19,20-DiHDPE/19,20-EpDPE was associated with increased WMH (p = 0.04) and poorer performance on Trails-B (p = 0.04). Arachidonic acid was associated with better performance on Trails-B (p = 0.012); Omega-3 derived 16,17-EpDPE was associated with decreased WMH (p = 0.005). CONCLUSIONS: With the exception of arachidonic acid, it was specific oxylipin products, not their parent PUFAs, that were associated with unfavorable and favorable MRI and cognitive markers of dementia risk.

Potential of FTIR Spectroscopy Applied to Exosomes for Alzheimer's Disease Discrimination: A Pilot Study. - Martins, Tânia Soares; Magalhães, Sandra; Rosa, Ilka Martins; Vogelgsang, Jonathan; Wiltfang, Jens; Delgadillo, Ivonne; Catita, José; da Cruz E Silva, Odete A B; Nunes, Alexandra; Henriques, Ana Gabriela (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) diagnosis is based on psychological and imaging tests but can also include monitoring cerebrospinal fluid (CSF) biomarkers. However, CSF based-neurochemical approaches are expensive and invasive, limiting their use to well-equipped settings. In contrast, blood-based biomarkers are minimally invasive, cost-effective, and a widely accessible alternative. Blood-derived exosomes have recently emerged as a reliable AD biomarker source, carrying disease-specific cargo. Fourier-transformed infrared (FTIR) spectroscopy meets the criteria for an ideal diagnostic methodology since it is rapid, easy to implement, and has high reproducibility. This metabolome-based technique is useful for diagnosing a broad range of diseases, although to our knowledge, no reports for FTIR spectroscopy applied to exosomes in AD exist. In this ground-breaking pilot study, FTIR spectra of serum and serum-derived exosomes from two independent cohorts were acquired and analyzed using multivariate analysis. The regional UA-cohort includes 9 individuals, clinically diagnosed with AD, mean age of 78.7 years old; and the UMG-cohort comprises 12 individuals, clinically diagnosed with AD (based on molecular and/or imaging data), mean age of 73.2 years old. Unsupervised principal component analysis of FTIR spectra of serum-derived exosomes revealed higher discriminatory value for AD cases when compared to serum as a whole. Consistently, the partial least-squares analysis revealed that serum-derived exosomes present higher correlations than serum. In addition, the second derivative peak area calculation also revealed significant differences among Controls and AD cases. The results obtained suggest that this methodology can discriminate cases from Controls and thus be potential useful to assist in AD clinical diagnosis.

The Prevalence of Dementia: A Systematic Review and Meta-Analysis. - Cao, Qing; Tan, Chen-Chen; Xu, Wei; Hu, Hao; Cao, Xi-Peng; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2020)
Dementia is a severe neurodegenerative disorder and it can be categorized into several subtypes by different pathogenic causes. We sought to comprehensively analyzed the prevalence of dementia from perspectives of geographic region (Asia, Africa, South America, and Europe/North America), age, and gender. We searched PubMed and EMBASE for relevant articles on dementia published from January 1985 to August 2019. In these studies, analyses were stratified by geographic region, age, and gender. Meta-regression was conducted to identify if there were significant differences between groups. We included forty-seven studies. Among the individuals aged 50 and over in the community, the pooled prevalence for all-cause dementia, Alzheimer's disease, and vascular dementia were 697 (CI95%: 546-864) per 10,000 persons, 324 (CI95%: 228-460) per 10,000 persons, and 116 (CI95%: 86-157) per 10,000 persons, respectively. In our study, the prevalence of all-type dementia in individuals aged 100 years and older (6,592 per 10,000 cases) is 244 times higher than in those aged 50-59 (27 per 10,000 cases). The number of people living with dementia approximately doubles every five years. The prevalence was greater in women than in men (788 cases versus 561 cases per 10,000 persons) in overall analysis. In individuals aged 60 to 69 years, AD prevalence in females was 1.9 times greater than that in males (108 cases versus 56 cases per 10,000 persons), while the prevalence of VaD was 1.8 times greater in males than in females (56 cases versus 32 cases per 10,000 persons). Prevalence rate was higher in Europe and North America than in Asia, Africa, and South America.

The Rhythmicity of Clock Genes is Disrupted in the Choroid Plexus of the APP/PS1 Mouse Model of Alzheimer's Disease. - Furtado, André; Astaburuaga, Rosario; Costa, Ana; Duarte, Ana C; Gonçalves, Isabel; Cipolla-Neto, José; Lemos, Manuel C; Carro, Eva; Relógio, Angela; Santos, Cecília R A; Quintela, Telma (J Alzheimers Dis, 2020)
BACKGROUND: The choroid plexus (CP), which constitutes the blood-cerebrospinal fluid barrier, was recently identified as an important component of the circadian clock system. OBJECTIVE: The fact that circadian rhythm disruption is closely associated to Alzheimer's disease (AD) led us to investigate whether AD pathology can contribute to disturbances of the circadian clock in the CP. METHODS: For this purpose, we evaluated the expression of core-clock genes at different time points, in 6- and 12-month-old female and male APP/PS1 mouse models of AD. In addition, we also assessed the effect of melatonin pre-treatment in vitro before amyloid-β stimulus in the daily pattern of brain and muscle Arnt-like protein 1 (Bmal1) expression. RESULTS: Our results showed a dysregulation of circadian rhythmicity of Bmal1 expression in female and male APP/PS1 transgenic 12-month-old mice and of Period 2 (Per2) expression in male mice. Besides, a significant circadian pattern of Bmal1 occurs in the intermittent melatonin pre-treatment group, showing that melatonin can reset the CP circadian clock. CONCLUSION: These results demonstrated a connection between AD and the disruption of circadian rhythm in the CP, representing an attractive target for disease prevention and/or treatment.

Selective Peripheral Taste Dysfunction in APP/PS1 Mutant Transgenic Mice. - Wood, Ryan M; Garcia, Zacnite; Daniels, Nathan; Landon, Shannon M; Humayun, Saima; Lee, Hyoung-gon; Macpherson, Lindsey J (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies indicate that taste dysfunction occurs early in the development of Alzheimer's disease. It is debatable whether the deficit in taste is due primarily to peripheral sensory mechanisms or to central processing, or a combination of the two. OBJECTIVE: The aim of our current study is to combine behavior and histological data in APP/PS1 transgenic mice to determine whether APP/PS1 transgenic mice show deficits in unconditioned taste preference and avoidance behaviors and whether taste impairments are due to defects in the peripheral taste system and/or problems with central processing of taste information. METHODS: The APP/PS1 transgenic mutant mice were used as a model of Alzheimer's disease. We employed a brief-access gustometer test to assess immediate orosensory taste responses of APP/PS1 mice. We used immunohistochemistry to examine tongue, gustatory ganglion, and brain tissues to determine a cytological basis for behavioral deficits. RESULTS: There is a significant, selective reduction of bitter taste sensitivity in APP/PS1 mice. These mice also have a loss of TRPM5-expressing taste receptor cells in the circumvallate papillae of the tongue. While we observed no overt loss of neuron cell bodies within the primary gustatory sensory neurons, degeneration of the neurons' peripheral axons innervating the taste bud may play a role in the observed loss of TRPM5-expressing taste receptor cells. CONCLUSION: This data supports a potential role for peripheral taste dysfunction in AD through the selective loss of taste receptor cells. Further study is necessary to delineate the mechanisms and pathological significance of this deficit in AD.

Serum Hepcidin Levels in Cognitively Normal Older Adults with High Neocortical Amyloid-β Load. - Chatterjee, Pratishtha; Mohammadi, Maryam; Goozee, Kathryn; Shah, Tejal M; Sohrabi, Hamid R; Dias, Cintia B; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Pedrini, Steve; Ashton, Nicholas J; Hye, Abdul; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Hepcidin, an iron-regulating hormone, suppresses the release of iron by binding to the iron exporter protein, ferroportin, resulting in intracellular iron accumulation. Given that iron dyshomeostasis has been observed in Alzheimer's disease (AD) together with elevated serum hepcidin levels, the current study examined whether elevated serum hepcidin levels are an early event in AD pathogenesis by measuring the hormone in cognitively normal older adults at risk of AD, based on high neocortical amyloid-β load (NAL). METHODS: Serum hepcidin levels in cognitively normal participants (n = 100) aged between 65-90 years were measured using ELISA. To evaluate NAL, all participants underwent 18F-florbetaben positron emission tomography. A standard uptake value ratio (SUVR) RESULTS: Serum hepcidin was significantly higher in participants with high NAL compared to those with low NAL before and after adjusting for covariates: age, gender, and APOEɛ4 carriage (p < 0.05). A receiver operating characteristic curve based on a logistic regression of the same covariates, the base model, distinguished high from low NAL (area under the curve, AUC = 0.766), but was outperformed when serum hepcidin was added to the base model (AUC = 0.794) and further improved with plasma Aβ42/40 ratio (AUC = 0.829). CONCLUSION: The present findings indicate that serum hepcidin is increased in individuals at risk for AD and contribute to the body of evidence supporting iron dyshomeostasis as an early event of AD. Further, hepcidin may add value to a panel of markers that contribute toward identifying individuals at risk of AD; however, further validation studies are required.

Severity Distribution of Alzheimer's Disease Dementia and Mild Cognitive Impairment in the Framingham Heart Study. - Yuan, Jing; Maserejian, Nancy; Liu, Yulin; Devine, Sherral; Gillis, Cai; Massaro, Joseph; Au, Rhoda (J Alzheimers Dis, 2020)
BACKGROUND: Studies providing Alzheimer's disease (AD) prevalence data have largely neglected to characterize the proportion of AD that is mild, moderate, or severe. Estimates of the severity distribution along the AD continuum, including the mild cognitive impairment (MCI) stage, are important to plan research and allocate future resources, particularly resources targeted at particular stages of disease. OBJECTIVE: To characterize the distribution of severity of AD dementia and MCI among prevalent cases in the population-based Framingham Heart Study. METHODS: Participants (aged 50-94) with prevalent MCI or AD dementia clinical syndrome were cross-sectionally selected from three time-windows of the population-based Framingham Heart Study in 2004-2005 (n = 381), 2006-2007 (n = 422), and 2008-2009 (n = 389). Summary estimates of the severity distribution were achieved by pooling results across time-windows. Diagnosis and severity were assessed by consensus dementia review. MCI-progressive was determined if the participant had documented progression to AD dementia clinical syndrome using longitudinal data. RESULTS: Among AD dementia participants, the pooled percentages were 50.4%for mild, 30.3%for moderate, and 19.3%for severe. Among all MCI and AD participants, the pooled percentages were 29.5%, 19.6%, 25.7%, and 45.2%for MCI-not-progressive, MCI-progressive, mild AD dementia, and the combined group of MCI-progressive and mild AD dementia, respectively. Distributions by age and sex were presented. CONCLUSION: The finding that half of the people living with AD have mild disease underscores the need for research and interventions to slow decline or prevent progression of this burdensome disease.

Sleep-Wake Cycle in Alzheimer's Disease Is Associated with Tau Pathology and Orexin Dysregulation. - Liguori, Claudio; Spanetta, Matteo; Izzi, Francesca; Franchini, Flaminia; Nuccetelli, Marzia; Sancesario, Giulia Maria; Di Santo, Simona; Bernardini, Sergio; Mercuri, Nicola Biagio; Placidi, Fabio (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is mainly characterized by a progressive deterioration of cognition, but sleep-wake cycle disturbances frequently occur. Irregular sleep-wake cycle, insomnia, and daytime napping usually occur in patients with AD in the course of the disease. OBJECTIVE: The aim of the present study was to verify the sleep-wake cycle in mild to moderate AD patients compared to controls, and to evaluate the relationship between the sleep-wake cycle impairment and the neuropsychological testing, CSF AD biomarkers, and CSF orexin concentrations. METHODS: Mild to moderate AD patients were enrolled and underwent 14-day actigraphic recording, sleep diary, neuropsychological testing, and CSF biomarkers analysis. All patients were compared to controls. RESULTS: Eighteen AD patients were compared to ten controls. AD patients showed the alteration of the sleep-wake cycle, featured by sleep dysregulation and daytime wake fragmentation, with respect to controls. Considering the correlation analysis, we documented the correlation between tau proteins and orexin CSF levels and sleep-wake cycle dysregulation. CONCLUSION: This study confirmed the dysregulation of sleep-wake cycle in AD patients, as reflected by the daytime wake fragmentation, irregular sleep-wake rhythm, and nocturnal sleep impairment. This sleep-wake cycle disorder correlates with AD neuropathological in vivo features and brain orexin activity. Hence, we suppose that a more marked AD pathology coupled with orexinergic system dysregulation may promote sleep-wake cycle impairment in AD patients.

Specific Neuropsychiatric Symptoms Are Associated with Faster Progression in Alzheimer's Disease: Results of the Prospective Dementia Registry (PRODEM-Austria). - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Dal-Bianco, Peter; Ransmayr, Gerhard; Benke, Thomas; Mosbacher, Jochen; Höller, Yvonne; Schmidt, Reinhold (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms (NPS) occur frequently in the course of Alzheimer's disease (AD) and are suspected to be associated with a faster dementia progression. Numerous reports have defined specific subsyndromes, summarized in clusters of items of the Neuropsychiatric Inventory (NPI). OBJECTIVE: This study investigated the influence of specific NPI subsyndromes and clinical patient characteristics on dementia progression. METHODS: Data of the prospective registry on dementia in Austria (PRODEM) were retrospectively analyzed. Cognitive functioning was determined at baseline and 2 yearly follow-up visits using the Mini-Mental State Examination (MMSE) and the Consortium to Establish a Registry for Alzheimer's dementia neuropsychological test battery (CERAD). To assess NPS, the NPI was used: NPI items were classified in three subsyndromes (psychotic cluster, behavioral cluster, emotional cluster). RESULTS: Out of the 662 included patients (mean age 76.4±8.4 years), 43% completed follow-up visits for two years. Significant correlation between higher scores in all three subsyndromes and worse cognitive performance were found for MMSE score, naming, and verbal fluency. Results of linear mixed model analysis revealed lower age and higher scores in the psychotic cluster as significant predictors of changes in MMSE with time. CONCLUSION: In this study, we report the influence of psychotic subsyndromes and lower age on faster MMSE decline in early AD. These results emphasize the importance of not only assessing but also differentiating neuropsychiatric symptoms in subsyndromes in the early stages of AD as a possible predictor of disease progression.

Structural Brain Changes in Pre-Clinical FTD MAPT Mutation Carriers. - Domínguez-Vivero, Clara; Wu, Liwen; Lee, Seonjoo; Manoochehri, Masood; Cines, Sarah; Brickman, Adam M; Rizvi, Batool; Chesebro, Anthony; Gazes, Yunglin; Fallon, Emer; Lynch, Timothy; Heidebrink, Judith L; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Frontotemporal dementia (FTD) is the second most common cause of early-onset neurodegenerative dementia. Several studies have focused on early imaging changes in FTD patients, but once subjects meet full criteria for the FTD diagnosis, structural changes are generally widespread. OBJECTIVE: This study aims to determine the earliest structural brain changes in asymptomatic MAPT MUTATION carriers. METHODS: This is a cross-sectional multicenter study comparing global and regional brain volume and white matter integrity in a group of MAPT mutation preclinical carriers and controls. Participants belong to multiple generations of six families with five MAPT mutations. All participants underwent a medical examination, neuropsychological tests, genetic analysis, and a magnetic resonance scan (3T, scout, T1-weighted image followed by EPI (BOLD), MPRAGE, DTI, FLAIR, and ASL sequences). RESULTS: Volumes of five cortical and subcortical areas were strongly correlated with mutation status: temporal lobe (left amygdala, left temporal pole), cingulate cortex (left rostral anterior cingulate gyrus, right posterior cingulate), and the lingual gyrus in the occipital lobe. We did not find significant differences in whole brain volume, white matter hyperintensities volume, and white matter integrity using DTI analysis. CONCLUSION: Temporal lobe, cingulate cortex and the lingual gyrus seem to be early targets of the disease and may serve as biomarkers for FTD prior to overt symptom onset.

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

Utility of MemTrax and Machine Learning Modeling in Classification of Mild Cognitive Impairment. - Bergeron, Michael F; Landset, Sara; Zhou, Xianbo; Ding, Tao; Khoshgoftaar, Taghi M; Zhao, Feng; Du, Bo; Chen, Xinjie; Wang, Xuan; Zhong, Lianmei; Liu, Xiaolei; Ashford, J Wesson (J Alzheimers Dis, 2020)
BACKGROUND: The widespread incidence and prevalence of Alzheimer's disease and mild cognitive impairment (MCI) has prompted an urgent call for research to validate early detection cognitive screening and assessment. OBJECTIVE: Our primary research aim was to determine if selected MemTrax performance metrics and relevant demographics and health profile characteristics can be effectively utilized in predictive models developed with machine learning to classify cognitive health (normal versus MCI), as would be indicated by the Montreal Cognitive Assessment (MoCA). METHODS: We conducted a cross-sectional study on 259 neurology, memory clinic, and internal medicine adult patients recruited from two hospitals in China. Each patient was given the Chinese-language MoCA and self-administered the continuous recognition MemTrax online episodic memory test on the same day. Predictive classification models were built using machine learning with 10-fold cross validation, and model performance was measured using Area Under the Receiver Operating Characteristic Curve (AUC). Models were built using two MemTrax performance metrics (percent correct, response time), along with the eight common demographic and personal history features. RESULTS: Comparing the learners across selected combinations of MoCA scores and thresholds, Naïve Bayes was generally the top-performing learner with an overall classification performance of 0.9093. Further, among the top three learners, MemTrax-based classification performance overall was superior using just the top-ranked four features (0.9119) compared to using all 10 common features (0.8999). CONCLUSION: MemTrax performance can be effectively utilized in a machine learning classification predictive model screening application for detecting early stage cognitive impairment.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Waist Circumference and Domain-Specific Cognitive Function Among Non-Demented Japanese Older Adults Stratified by Sex: Results from the Takashima Cognition Study. - Waki, Takashi; Tanaka-Mizuno, Sachiko; Takashima, Naoyuki; Takechi, Hajime; Hayakawa, Takehito; Miura, Katsuyuki; Ueshima, Hirotsugu; Kita, Yoshikuni; Dodge, Hiroko H (J Alzheimers Dis, 2020)
BACKGROUND: While being obese in mid-life is associated with an increased risk of dementia and cognitive decline in late-life, being obese in late-life is shown to be associated with a lower risk of these outcomes in some studies. This phenomenon is known as the "obesity paradox", but the underlying reasons and potential sex difference have not been well understood. OBJECTIVE: To investigate the association between cognition and waist circumference (WC), an alternative measure of body fat which can be measured easier than body mass index (BMI), among older adults in each generation of late-life for men and women separately. METHODS: Three hundred thirty-five participants were used in the current study who were identified by random sampling of residents aged 65-74, 75-84, and 85 + years in Takashima County, Shiga Prefecture, Japan during 2005-2006. Associations between WC and domain-specific cognitive functions measured by 12 neuropsychological tests were examined using multivariable linear regression models with covariates: age, education, and hypertension. RESULTS: Larger WC was associated with better attention/working memory among 65-74-year old women and with better learning/acquisition among 65-74-year-old men, while larger WC was associated with worse learning/acquisition, memory, attention/working memory, and language/fluency among 75-84-year old men. CONCLUSION: We found age and sex differences in the association between WC and domain-specific cognitive functions. Among older old men (age 75-84) larger WC had negative effects on various domains including memory, attention, language, and executive functions, while we did not find any negative effects of larger WC on cognition among women in any age groups.

Adverse Vascular Risk Relates to Cerebrospinal Fluid Biomarker Evidence of Axonal Injury in the Presence of Alzheimer's Disease Pathology. - Osborn, Katie E; Alverio, Jonathan M; Dumitrescu, Logan; Pechman, Kimberly R; Gifford, Katherine A; Hohman, Timothy J; Blennow, Kaj; Zetterberg, Henrik; Jefferson, Angela L (J Alzheimers Dis, 2019)
BACKGROUND: Vascular risk factors promote cerebral small vessel disease and neuropathological changes, particularly in white matter where large-caliber axons are located. How Alzheimer's disease pathology influences the brain's vulnerability in this regard is not well understood. OBJECTIVE: Systemic vascular risk was assessed in relation to cerebrospinal fluid concentrations of neurofilament light, a biomarker of large-caliber axonal injury, evaluating for interactions by clinical and protein markers of Alzheimer's disease. METHODS: Among Alzheimer's Disease Neuroimaging Initiative participants with normal cognition (n = 117), mild cognitive impairment (n = 190), and Alzheimer's disease (n = 95), linear regression related vascular risk (as measured by the modified Framingham Stroke Risk Profile) to neurofilament light, adjusting for age, sex, education, and cognitive diagnosis. Interactions were assessed by cognitive diagnosis, and by cerebrospinal fluid markers of Aβ42, hyperphosphorylated tau, and total tau. RESULTS: Vascular risk and neurofilament light were not related in the main effect model (p = 0.08). However, interactions emerged for total tau (p = 0.01) and hyperphosphorylated tau (p = 0.002) reflecting vascular risk becoming more associated with cerebrospinal fluid neurofilament light in the context of greater concentrations of tau biomarkers. An interaction also emerged for the Alzheimer's disease biomarker profiles (p = 0.046) where in comparison to the referent 'normal' biomarker group, individuals with abnormal levels of both Aβ42 and total tau showed stronger associations between vascular risk and neurofilament light. CONCLUSION: Older adults may be more vulnerable to axonal injury in response to higher vascular risk burdens in the context of concomitant Alzheimer's disease pathology.

APOE Effect on Amyloid-β PET Spatial Distribution, Deposition Rate, and Cut-Points. - Toledo, Jon B; Habes, Mohamad; Sotiras, Aristeidis; Bjerke, Maria; Fan, Yong; Weiner, Michael W; Shaw, Leslie M; Davatzikos, Christos; Trojanowski, John Q (J Alzheimers Dis, 2019)
There are conflicting results regarding how APOE genotype, the strongest genetic risk factor for Alzheimer's disease (AD), influences spatial and longitudinal amyloid-β (Aβ) deposition and its impact on the selection of biomarker cut-points. In our study, we sought to determine the impact of APOE genotype on cross-sectional and longitudinal florbetapir positron emission tomography (PET) amyloid measures and its impact in classification of patients and interpretation of clinical cohort results. We included 1,019 and 1,072 Alzheimer's Disease Neuroimaging Initiative participants with cerebrospinal fluid Aβ1 - 42 and florbetapir PET values, respectively. 623 of these subjects had a second florbetapir PET scans two years after the baseline visit. We evaluated the effect of APOE genotype on Aβ distribution pattern, pathological biomarker cut-points, cross-sectional clinical associations with Aβ load, and longitudinal Aβ deposition rate measured using florbetapir PET scans. 1) APOEɛ4 genotype influences brain amyloid deposition pattern; 2) APOEɛ4 genotype does not modify Aβ biomarker cut-points estimated using unsupervised mixture modeling methods if white matter and brainstem references are used (but not when cerebellum is used as a reference); 3) findings of large differences in Aβ biomarker value differences based on APOE genotype are due to increased probability of having AD neuropathology and are most significant in mild cognitive impairment subjects; and 4) APOE genotype and age (but not gender) were associated with increased Aβ deposition rate. APOEɛ4 carrier status affects rate and location of brain Aβ deposition but does not affect choice of biomarker cut-points if adequate references are selected for florbetapir PET processing.

Association between Adipokines and Biomarkers of Alzheimer's Disease: A Cross-Sectional Study. - Letra, Liliana; Matafome, Paulo; Rodrigues, Tiago; Duro, Diana; Lemos, Raquel; Baldeiras, Ines; Patrício, Miguel; Castelo-Branco, Miguel; Caetano, Gina; Seiça, Raquel; Santana, Isabel (J Alzheimers Dis, 2019)
BACKGROUND: Adipose tissue dysfunction has been implicated in the pathophysiology of Alzheimer's disease. However, the involvement of adipokines, particularly adiponectin, remains unclear. OBJECTIVE: To compare serum and cerebrospinal fluid (CSF) levels of adiponectin, leptin and leptin-to-adiponectin ratio in patients within the spectrum of Alzheimer's disease and evaluate their relationship with classical biomarkers and their value as markers of progression. METHODS: Amnestic mild cognitive impairment (MCI, n = 71) and Alzheimer's dementia (AD, n = 53) subjects were consecutively recruited for serum and CSF adiponectin and leptin determination using an analytically validated commercial enzyme-linked immunosorbent assay (ELISA). Correlations were explored using adjusted Spearman's correlation coefficients. A logistic regression model and ROC analysis were performed to evaluate the staging predictive value of adipokines. RESULTS: Serum adiponectin was 33% higher in AD when compared to MCI patients. Adiponectin CSF levels, similar in both groups, were positively correlated with Aβ42 and cognitive function, though only in women. The area under the ROC curve was 0.673 (95% CI:0.57-0.78) for serum adiponectin as predictor of dementia stage and the cut-off 10.85μg/ml maximized the sum of specificity (87%) and sensitivity (44%). CONCLUSION: Although longitudinal studies are required, we hypothesize that higher serum adiponectin in AD patients constitutes a strategy to compensate possible central signaling defects. In addition, adiponectin might be specifically assigned to neuroprotective functions in women and eventually involved in the female-biased incidence of Alzheimer's disease.

Can Subjective Memory Complaints Identify Aβ Positive and Aβ Negative Amnestic Mild Cognitive Impairment Patients? - Mendes, Tiago; Cardoso, Sandra; Guerreiro, Manuela; Maroco, João; Silva, Dina; Alves, Luísa; Schmand, Ben; Gerardo, Bianca; Lima, Marisa; Santana, Isabel; de Mendonça, Alexandre (J Alzheimers Dis, 2019)
BACKGROUND: The use of biomarkers, in particular amyloid-β (Aβ) changes, has allowed the possibility to identify patients with subjective memory complaints (SMCs) and amnestic mild cognitive impairment (aMCI) who suffer from Alzheimer's disease (AD). Since it is unfeasible that all patients with aMCI could presently undergo biomarkers assessment, it would be important that SMCs might contribute to identify the aMCI patients who have AD amyloid pathology. OBJECTIVES: To know whether aMCI patients with amyloid biomarkers (Aβ+) present greater SMCs as compared to those without amyloid biomarkers (Aβ-). METHODS: Participants were selected from a cohort of nondemented patients with cognitive complaints and a comprehensive neuropsychological evaluation, on the basis of 1) diagnosis of aMCI; 2) detailed assessment of memory difficulties with the SMC Scale; and 3) known amyloid status. The amyloid status was determined on the basis of either CSF Aβ1-42 concentration or amyloid PET imaging. RESULTS: Of the 176 patients with aMCI studied, 90 were Aβ+ and 86 were Aβ-. The two groups did not differ in terms of age, gender, and education. The SMC total score was not significantly different in the Aβ+ aMCI patients (9.48±4.18) when compared to the Aβ- aMCI patients (10.52±4.57). The Aβ+ aMCI patients had lower scores on the MMSE and memory/learning tests, but not on the Geriatric Depression Scale, when comparing to the Aβ- aMCI patients. CONCLUSIONS: Evaluating SMCs does not seem helpful to identify, among patients with aMCI, those who have AD.

Cerebrospinal Fluid Level of Aquaporin4: A New Window on Glymphatic System Involvement in Neurodegenerative Disease? - Arighi, Andrea; Di Cristofori, Andrea; Fenoglio, Chiara; Borsa, Stefano; D'Anca, Marianna; Fumagalli, Giorgio Giulio; Locatelli, Marco; Carrabba, Giorgio; Pietroboni, Anna Margherita; Ghezzi, Laura; Carandini, Tiziana; Colombi, Annalisa; et al. (J Alzheimers Dis, 2019)
Aquaporin4 (AQP4) is a water channel protein located at astrocyte foot processes that plays a role in glymphatic system, a highly organized fluid transport pathway which seems to be involved in Alzheimer's disease (AD) and normal pressure hydrocephalus (NPH) pathophysiology. Cerebrospinal fluid (CSF) AQP4 levels were determined in 11 patients with AD, 10 patients with NPH, and 9 controls. We found significantly reduced AQP4 in AD patients, a trend in reduction in NPH patients, and a correlation between AQP4 and amyloid-β CSF levels. This study indicates the potential role of AQP4 and glymphatic system in neurodegenerative diseases pathophysiology.

The Clinical Phenotype of Vascular Cognitive Impairment in Patients with Type 2 Diabetes Mellitus. - Groeneveld, Onno N; Moneti, Costanza; Heinen, Rutger; de Bresser, Jeroen; Kuijf, Hugo J; Exalto, Lieza G; Boomsma, Jooske M F; Kappelle, L Jaap; Barkhof, Frederik; Prins, Niels D; Scheltens, Philip; van der Flier, Wiesje M; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes mellitus (T2DM) increases the risk of vascular cognitive impairment (VCI). It is unknown which type of vascular lesions and co-morbid etiologies, in particular Alzheimer's disease pathology, are associated with T2DM in patients with VCI, and how this relates to cognition and prognosis. OBJECTIVE: To compare brain MRI and cerebrospinal fluid (CSF) markers, cognition, and prognosis in patients with possible VCI with and without T2DM. METHODS: We included 851 memory clinic patients with vascular brain injury on MRI (i.e., possible VCI) from a prospective cohort study (T2DM: n = 147, 68.4±7.9 years, 63% men; no T2DM: n = 704, 67.6±8.5 years, 52% men). At baseline, we assessed between-group differences in brain MRI abnormalities, CSF markers of Alzheimer's disease, and cognitive profile. After two years follow-up, we compared occurrence of cognitive decline, stroke, and death. RESULTS: The distribution of clinical diagnoses did not differ between patients with and without T2DM. T2DM patients had more pronounced brain atrophy (total and white matter volume), and more lacunar infarcts, whereas microbleeds were less common (all p <  0.05). CSF amyloid-β levels were similar between the groups. T2DM patients performed worse on working memory (effect size: - 0.17, p = 0.03) than those without, whereas performance on other domains was similar. During follow-up, risk of further cognitive decline was not increased in T2DM.∥Conclusion: In patients with possible VCI, presence of T2DM is related to more pronounced brain atrophy and a higher burden of lacunar infarcts, but T2DM does not have a major impact on cognitive profile or prognosis.∥.

Clinico-Neuropathological Findings in the Oldest Old from the Georgia Centenarian Study. - Tanprasertsuk, Jirayu; Johnson, Elizabeth J; Johnson, Mary Ann; Poon, Leonard W; Nelson, Peter T; Davey, Adam; Martin, Peter; Barbey, Aron K; Barger, Kathryn; Wang, Xiang-Dong; Scott, Tammy M (J Alzheimers Dis, 2019)
BACKGROUND: Centenarian studies are important sources for understanding of factors that contribute to longevity and healthy aging. Clinico-neuropathological finding is a key in identifying pathology and factors contributing to age-related cognitive decline and dementia in the oldest old. OBJECTIVE: To characterize the cross-sectional relationship between neuropathologies and measures of premortem cognitive performance in centenarians. METHODS: Data were acquired from 49 centenarians (≥98 years) from the Georgia Centenarian Study. Cognitive assessment from the time point closest to mortality was used ( RESULTS: Wide ranges of AD-type neuropathological changes were observed in both non-demented and demented subjects. Neocortical NFT and Braak staging were related to clinical dementia rating. Neocortical NFT and NP, Braak and NIARI staging, cerebral and ventricular atrophy, HS, CAA, and TDP-43 proteinopathy were differentially associated with poor performance in multiple cognitive domains and activities of daily living. CONCLUSION: AD-type pathology was associated with severe dementia and poor cognition but was not the only variable that explained cognitive impairment, indicating the complexity and heterogeneity of pathophysiology of dementia in the oldest old.

Early-Stage Alzheimer's Disease Is Associated with Simultaneous Systemic and Central Nervous System Dysregulation of Insulin-Linked Metabolic Pathways. - de la Monte, Suzanne M; Tong, Ming; Daiello, Lori A; Ott, Brian R (J Alzheimers Dis, 2019)
BACKGROUND: Brain insulin resistance is a well-recognized abnormality in Alzheimer's disease (AD) and the likely mediator of impaired glucose utilization that emerges early and progresses with disease severity. Moreover, the rates of mild cognitive impairment (MCI) or AD are significantly greater in people with diabetes mellitus or obesity. OBJECTIVE: This study was designed to determine whether systemic and central nervous system (CNS) insulin resistant disease states emerge together and thus may be integrally related. METHODS: Insulin-related molecules were measured in paired human serum and cerebrospinal fluid (CSF) samples from 19 with MCI or early AD, and 21 controls using a multiplex ELISA platform. RESULTS: In MCI/AD, both the CSF and serum samples had significantly altered mean levels of C-peptide (both elevated), Visfatin, incretins, PAI-1, ghrelin, and leptin, whereas only CSF showed a significant reduction in insulin and only serum had increased glucagon levels. Although the overall CSF and serum responses reflected insulin resistance together with insulin deficiency, the specific alterations measured in CSF and serum were different. CONCLUSION: In MCI and early-stage AD, CNS and systemic insulin-related metabolic dysfunctions, including insulin resistance, occur simultaneously, suggesting that they are integrally related and possibly mediated similar pathogenic factors.

Ethical Issues in the Treatment of Late-Stage Alzheimer's Disease. - Watt, Andrew D; Jenkins, Nicole L; McColl, Gawain; Collins, Steven; Desmond, Patricia M (J Alzheimers Dis, 2019)
There is hope that the continuing efforts of researchers will yield a disease-modifying drug for Alzheimer's disease. Such a drug is likely to be capable of halting, or significantly slowing, the underlying pathological processes driving cognitive decline; however, it is unlikely to be capable of restoring brain function already lost through the pathological process. A therapy capable of halting Alzheimer's disease, while not providing restoration of function, may prompt serious ethical questions. For example, is there a stage in the disease process when it becomes too late for therapeutic intervention to commence? And who bears the responsibility of making such a decision? Conversations regarding the ethics of treating neurodegenerative conditions with non-restorative drugs have been largely absent within both clinical and research communities. Such discussions are urgently required to ensure that patients' rights and well-being are protected when such therapeutic options become available.

Evaluation of Associations of Alzheimer's Disease Risk Variants that Are Highly Expressed in Microglia with Neuropathological Outcome Measures. - Sakae, Nobutaka; Heckman, Michael G; Vargas, Emily R; Carrasquillo, Minerva M; Murray, Melissa E; Kasanuki, Koji; Ertekin-Taner, Nilufer; Younkin, Steven G; Dickson, Dennis W (J Alzheimers Dis, 2019)
A number of Alzheimer's disease (AD) susceptibility loci are expressed abundantly in microglia. We examined associations between AD risk variants in genes that are highly expressed in microglia and neuropathological outcomes, including cerebral amyloid angiopathy (CAA) and microglial activation, in 93 AD patients. We observed significant associations of CAA pathology with APOEɛ4 and PTK2B rs28834970. Nominally significant associations with measures of microglial activation in white matter were observed for variants in PTK2B, PICALM, and CR1. Our findings suggest that several AD risk variants may also function as disease modifiers through amyloid-β metabolism and white matter microglial activity.

Evaluation of Medicare Claims Data as a Tool to Identify Dementia. - Lee, Eunjung; Gatz, Margaret; Tseng, Chiuchen; Schneider, Lon S; Pawluczyk, Sonia; Wu, Anna H; Deapen, Dennis (J Alzheimers Dis, 2019)
BACKGROUND: Medicare claims record linkage has been used to identify diagnosed dementia cases in order to estimate dementia prevalence and cost of care. Claims records in the 1990 s and early 2000 s have been found to provide 85% - ∼90% sensitivity and specificity. OBJECTIVE: Considering that dementia awareness has improved over time, we sought to examine sensitivity and specificity of more recent Medicare claims records against a standard criterion, clinical diagnosis of dementia. METHODS: For a sample of patients evaluated at the University of Southern California Alzheimer Disease Research Center (ADRC), we performed database linkage with Medicare claims files for a six-year period, 2007-2012. We used clinical diagnosis at the ADRC as the criterion diagnosis in order to calculate sensitivity and specificity. RESULTS: Medicare claims correctly identified 85% of dementia patients and 77% of individuals with normal cognition. About half of patients clinically diagnosed with mild cognitive impairment had dementia diagnoses in Medicare claims. Misclassified dementia patients (i.e., missed diagnosis by Medicare claims) had more favorable Mini-Mental State Examination and Clinical Dementia Rating scores and were less likely to present behavioral symptoms than correctly-classified dementia patients. CONCLUSIONS: Database linkage to Medicare claims records is an efficient and reasonably accurate tool to identify dementia cases in a population-based cohort. However, possibilities of obtaining biased results due to misclassification of dementia status need to be carefully considered to use Medicare claims diagnosis for etiologic research studies. Additional confirmation of dementia diagnosis may also be considered. A larger study is warranted to confirm our findings.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

Gender and Educational Differences in the Association between Lifestyle and Cognitive Decline over 10 Years: The Doetinchem Cohort Study. - Deckers, Kay; Nooyens, Astrid; van Boxtel, Martin; Verhey, Frans; Verschuren, Monique; Köhler, Sebastian (J Alzheimers Dis, 2019)
BACKGROUND: Several modifiable risk factors for cognitive decline have been identified, but whether differences by gender and educational level exist is unclear. OBJECTIVE: The present study aims to clarify this by prospectively investigating the relationship between health and lifestyle factors and cognitive functioning in different subgroups defined by gender and educational level. METHODS: 2,347 cognitive healthy individuals (mean age = 54.8, SD = 6.8, range: 41-71; 51.8% female; 26.2% low education) from the Doetinchem Cohort Study were examined for cognitive function at baseline, and at 5- and 10-year follow-up. Health- and lifestyle factors were captured by a poly-environmental risk score labelled 'LIfestyle for BRAin Health' (LIBRA). This score consists of 12 modifiable risk and protective factors for cognitive decline and dementia, with higher scores indicating greater risk (range: -2.7 to +12.7). Heterogeneity in associations between LIBRA and decline in verbal memory, cognitive flexibility, and mental speed between males and females and individuals with different levels of education were assessed in linear mixed models. RESULTS: Overall, higher LIBRA scores predicted faster decline in verbal memory, cognitive flexibility, and mental speed over 10 years. Higher LIBRA scores were further associated with increased risk for incident cognitive impairment (one-point increase in LIBRA: HR = 1.09, 1.04-1.14, p = 0.001). In general, these effects were similar across gender and educational level. CONCLUSION: A composite risk score comprising unhealthy lifestyle and relatively poor health in midlife is significantly associated with a worse course of cognition 10 years later. These associations were for the most part unrelated to gender or educational differences.

Genome-Wide Methylation of Mild Cognitive Impairment in Mexican Americans Highlights Genes Involved in Synaptic Transport, Alzheimer's Disease-Precursor Phenotypes, and Metabolic Morbidities. - Pathak, Gita A; Silzer, Talisa K; Sun, Jie; Zhou, Zhengyang; Daniel, Ann A; Johnson, Leigh; O'Bryant, Sid; Phillips, Nicole R; Barber, Robert C (J Alzheimers Dis, 2019)
The Mexican American population is among the fastest growing aging population and has a younger onset of cognitive decline. This group is also heavily burdened with metabolic conditions such as hypertension, diabetes, and obesity. Unfortunately, limited research has been conducted in this group. Understanding methylation alterations, which are influenced by both genetic and lifestyle factors, is key to identifying and addressing the root cause for mild cognitive impairment, a clinical precursor for dementia. We conducted an epigenome-wide association study on a community-based Mexican American population using the Illumina EPIC array. Following rigorous quality control measures, we identified 10 CpG sites to be differentially methylated between normal controls and individuals with mild cognitive impairment annotated to PKIB, KLHL29, SEPT9, OR2C3, CPLX3, BCL2L2-PABPN1, and CCNY. We found four regions to be differentially methylated in TMEM232, SLC17A8, ALOX12, and SEPT8. Functional gene-set analysis identified four gene-sets, RIN3, SPEG, CTSG, and UBE2L3, as significant. The gene ontology and pathway analyses point to neuronal cell death, metabolic dysfunction, and inflammatory processes. We found 1,450 processes to be enriched using empirical Bayes gene-set enrichment. In conclusion, the functional overlap of differentially methylated genes associated with cognitive impairment in Mexican Americans implies cross-talk between metabolically-instigated systemic inflammation and disruption of synaptic vesicular transport.

Glial Fibrillary Acidic Protein in Serum is Increased in Alzheimer's Disease and Correlates with Cognitive Impairment. - Oeckl, Patrick; Halbgebauer, Steffen; Anderl-Straub, Sarah; Steinacker, Petra; Huss, André M; Neugebauer, Hermann; von Arnim, Christine A F; Diehl-Schmid, Janine; Grimmer, Timo; Kornhuber, Johannes; Lewczuk, Piotr; Danek, Adrian; et al. (J Alzheimers Dis, 2019)
Reliable blood biomarkers for Alzheimer's disease (AD) are missing. We measured astroglial GFAP in patients with AD (n = 28), frontotemporal dementia (bvFTD, n = 35), Parkinson's disease (n = 11), Lewy body dementias (n = 19), and controls (n = 34). Serum GFAP was increased in AD (p < 0.001) and DLB/PDD (p < 0.01), and cerebrospinal fluid GFAP was increased in all neurodegenerative diseases (p < 0.001). Serum GFAP correlated with the Mini-Mental State Examination score (r= -0.42, p < 0.001) and might be a follow-up marker in clinical trials. Sensitivity and specificity of serum GFAP for AD versus bvFTD was 89% and 79% and might be the first blood biomarker in the differential diagnosis of AD and bvFTD.

Global Metabolic Shifts in Age and Alzheimer's Disease Mouse Brains Pivot at NAD +/NADH Redox Sites. - Dong, Yue; Brewer, Gregory J (J Alzheimers Dis, 2019)
Age and Alzheimer's disease (AD) share some common features such as cognitive impairments, memory loss, metabolic disturbances, bioenergetic deficits, and inflammation. Yet little is known on how systematic shifts in metabolic networks depend on age and AD. In this work, we investigated the global metabolomic alterations in non-transgenic (NTg) and triple-transgenic (3xTg-AD) mouse brain hippocampus as a function of age by using untargeted Ultrahigh Performance Liquid Chromatography-tandem Mass Spectroscopy (UPLC-MS/MS). We observed common metabolic patterns with aging in both NTg and 3xTg-AD brains involved in energy-generating pathways, fatty acids oxidation, glutamate, and sphingolipid metabolism. We found age-related downregulation of metabolites from reactions in glycolysis that consumed ATP and in the TCA cycle, especially at NAD +/NADH-dependent redox sites, where age- and AD-associated limitations in the free NADH may alter reactions. Conversely, metabolites increased in glycolytic reactions in which ATP is produced. With age, inputs to the TCA cycle were increased including fatty acid β-oxidation and glutamine. Overall age- and AD-related changes were >  2-fold when comparing the declines of upstream metabolites of NAD +/NADH-dependent reactions to the increases of downstream metabolites (p = 10 - 5, n = 8 redox reactions). Inflammatory metabolites such as ceramides and sphingosine-1-phosphate also increased with age. Age-related decreases in glutamate, GABA, and sphingolipid were seen which worsened with AD genetic load in 3xTg-AD brains, possibly contributing to synaptic, learning- and memory-related deficits. The data support the novel hypothesis that age- and AD-associated metabolic shifts respond to NAD(P) +/NAD(P)H redox-dependent reactions, which may contribute to decreased energetic capacity.

Greater Regional Cortical Thickness is Associated with Selective Vulnerability to Atrophy in Alzheimer's Disease, Independent of Amyloid Load and APOE Genotype. - Li, Chunfei; Duara, Ranjan; Loewenstein, David A; Izquierdo, Walter; Cabrerizo, Mercedes; Barker, Warren; Adjouadi, Malek (J Alzheimers Dis, 2019)
BACKGROUND: Regional cortical thickness (rCTh) among cognitively normal (CN) adults (rCThCN) varies greatly between brain regions, as does the vulnerability to neurodegeneration. OBJECTIVE: The goal of this study was to: 1) rank order rCThCN for various brain regions, and 2) explore their vulnerability to neurodegeneration in Alzheimer's disease (AD) within these brain regions. METHODS: The relationship between rCTh among the CN group (rCThCN) and the percent difference in CTh (% CThDiff) in each region between the CN group and AD patients was examined. Pearson correlation analysis was performed accounting for amyloid-β (Aβ) protein and APOE genotype using 210 age, gender, and APOE matched CN (n = 105, age range: 56-90) and AD (n = 105, age range: 56-90) ADNI participants. RESULTS: Strong positive correlations were observed between rCThCN and % CThDiff accounting for Aβ deposition and APOE status. Regions, such as the entorhinal cortex, which had the greatest CTh in the CN state, were also the regions which had the greatest % CThDiff. CONCLUSIONS: Regions with the greatest CTh at the CN stage are found to aggregate in disease prone regions of AD, namely in the medial temporal lobe, including the temporal pole, ERC, parahippocampal gyrus, fusiform and the middle and inferior temporal gyrus. Although rCTh has been found to vary considerably across the different regions of the brain, our results indicate that regions with the greatest CTh at the CN stage are actually regions which have been found to be most vulnerable to neurodegeneration in AD.

Higher Body Mass Index Is Associated with Lower Cortical Amyloid-β Burden in Cognitively Normal Individuals in Late-Life. - Thirunavu, Vineeth; McCullough, Austin; Su, Yi; Flores, Shaney; Dincer, Aylin; Morris, John C; Cruchaga, Carlos; Benzinger, Tammie L S; Gordon, Brian A (J Alzheimers Dis, 2019)
BACKGROUND: Both low and high body mass index (BMI) have been associated with an increased risk of dementia, including that caused by Alzheimer's disease (AD). Specifically, high middle-age BMI or a low late-age BMI has been considered a predictor for the development of AD dementia. Less studied is the relationship between BMI and AD pathology. OBJECTIVE: We explored the association between BMI and cortical amyloid-β (Aβ) burden in cognitively normal participants that were either in mid-life (45-60 years) or late-life (>60). METHODS: We analyzed cross-sectional baseline data from the Knight Alzheimer Disease Research Center (ADRC) at Washington University. Aβ pathology was measured in 373 individuals with Aβ PET imaging and was quantified using Centiloid units. We split the cohort into mid- and late-life groups for analyses (n = 96 and n = 277, respectively). We ran general linear regression models to predict Aβ levels from BMI while controlling for age, sex, years of education, and APOE4 status. Analyses were also conducted to test the interaction between BMI and APOE4 genotype and between BMI and sex. RESULTS: Higher BMI was associated with lower cortical Aβ burden in late-life (β= -0.81, p = 0.0066), but no relationship was found in mid-life (β= 0.04, p > 0.5). The BMI×APOE4+ and BMI×male interaction terms were not significant in the mid-life (β= 0.28, p = 0.41; β= 0.64, p = 0.13) or the late-life (β= 0.17, p > 0.5; β= 0.50, p = 0.43) groups. CONCLUSION: Higher late-life BMI is associated with lower cortical Aβ burden in cognitively normal individuals.

Impacts of Overweight and Obesity in Older Age on the Risk of Dementia: A Systematic Literature Review and a Meta-Analysis. - Danat, Isaac M; Clifford, Angela; Partridge, Martin; Zhou, Weiju; Bakre, Aishat T; Chen, Anthony; McFeeters, Danielle; Smith, Tina; Wan, Yuhui; Copeland, John; Anstey, Kaarin J; Chen, Ruoling (J Alzheimers Dis, 2019)
BACKGROUND: It is unclear whether overweight and obesity in older age reduces or increases the risk of incident dementia. OBJECTIVE: To assess the impacts of overweight and obesity in older age on incident dementia. METHODS: We searched cohort studies reporting body weight measured in older age and dementia through PubMed, Embase, Medline, PyschInfo, and Cochrane library until July 2016. Sixteen articles were identified for the review. We pooled data from them and a new unpublished study from China, to calculate relative risk (RR) of incident dementia in relation to body mass index (BMI) and waist circumference (WC). RESULTS: All 16 cohort studies were undertaken in high income countries, with follow-up periods ranging between 3 to 18 years. Thirteen studies showed an inverse association between BMI and dementia, and three studies demonstrated a positive association. Pooled RR of dementia in relation to continuous BMI from 14 studied populations, including the new Chinese data, was 0.97 (95% CI 0.95-1.00); in those followed up CONCLUSION: The current evidence did not support a paradox on beneficial impacts of overweight and obesity in older age on incident dementia. More studies with long term follow up are needed to clarify the association of body weight in older age with dementia risk.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Inhibition of Calpain Protects Against Tauopathy in Transgenic P301S Tau Mice. - Liu, Mengyu; Wang, Luwen; Gao, Ju; Dong, Qing; Perry, George; Ma, Xuemei; Wang, Xinglong (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) and other tauopathies are characterized by intracellular accumulation of microtubule-associated tau protein leading to neurodegeneration. Calpastatin is the endogenous inhibitor of calpain, a calcium-dependent cysteine protease that has been increasingly implicated in tauopathies. In this study, we generated a neuron specific calpastatin overexpressing knock-in transgenic mouse model and crossed it with the PS19 tauopathy mouse model expressing human P301S mutant tau protein. The forced expression of calpastatin in neurons significantly alleviated tau hyperphosphorylation measured by immunocytochemistry and immunoblot. The genetic inhibition of calpain by calpastatin also greatly suppressed characteristic hippocampal neuron loss and widespread astrogliosis and microgliosis in PS19 mice. Consistently, PS19 mice with neuronal calpastatin overexpression exhibited remarkably alleviated cognitive deficits, muscle weakness, skeletal muscle atrophy, and neuromuscular denervation, together implying the neuroprotective effects of neuronal calpastatin in PS19 mice of tauopathy. In sum, this study provides additional evidence supporting the pathological role of calpain in neurodegenerative diseases associated with tau pathology, and suggests that targeting calpain is likely a promising therapeutic approach for these devastating diseases.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

A Meta-Analysis of Alzheimer's Disease Brain Transcriptomic Data. - Patel, Hamel; Dobson, Richard J B; Newhouse, Stephen J (J Alzheimers Dis, 2019)
BACKGROUND: Microarray technologies have identified imbalances in the expression of specific genes and biological pathways in Alzheimer's disease (AD) brains. However, there is a lack of reproducibility across individual AD studies, and many related neurodegenerative and mental health disorders exhibit similar perturbations. OBJECTIVE: Meta-analyze publicly available transcriptomic data from multiple brain-related disorders to identify robust transcriptomic changes specific to AD brains. METHODS: Twenty-two AD, eight schizophrenia, five bipolar disorder, four Huntington's disease, two major depressive disorder, and one Parkinson's disease dataset totaling 2,667 samples and mapping to four different brain regions (temporal lobe, frontal lobe, parietal lobe, and cerebellum) were analyzed. Differential expression analysis was performed independently in each dataset, followed by meta-analysis using a combining p-value method known as Adaptively Weighted with One-sided Correction. RESULTS: Meta-analysis identified 323, 435, 1,023, and 828 differentially expressed genes specific to the AD temporal lobe, frontal lobe, parietal lobe, and cerebellum brain regions, respectively. Seven of these genes were consistently perturbed across all AD brain regions with SPCS1 gene expression pattern replicating in RNA-Seq data. A further nineteen genes were perturbed specifically in AD brain regions affected by both plaques and tangles, suggesting possible involvement in AD neuropathology. In addition, biological pathways involved in the "metabolism of proteins" and viral components were significantly enriched across AD brains. CONCLUSION: This study identified transcriptomic changes specific to AD brains, which could make a significant contribution toward the understanding of AD disease mechanisms and may also provide new therapeutic targets.

Methionine Sulfoxide Reductase-B3 Risk Allele Implicated in Alzheimer's Disease Associates with Increased Odds for Brain Infarcts. - Conner, Sarah C; Benayoun, Laurent; Himali, Jayandra J; Adams, Stephanie L; Yang, Qiong; DeCarli, Charles; Blusztajn, Jan K; Beiser, Alexa; Seshadri, Sudha; Delalle, Ivana (J Alzheimers Dis, 2019)
Genome-wide association studies identified a single nucleotide polymorphism (SNP) in the MSRB3 gene encoding Methionine Sulfoxide Reductase-B3 (MsrB3) to be associated with the risk for low hippocampal volume and late onset Alzheimer's disease (AD). Subsequently, we identified AD-associated abnormal patterns of neuronal and vascular MsrB3 expression in postmortem hippocampi. The present study investigated the relationship between the MSRB3 SNP rs61921502, G (minor/risk allele) and MRI measures of brain injury including total brain volume, hippocampal volume, and white matter hyperintensities using linear regression models; the presence of brain infarcts using logistic regression models; and the incidence of stroke, dementia, and AD using Cox proportional hazards models in 2,038 Framingham Heart Study Offspring participants with MRI administered close to examination cycle 7 (1998-2001). Participants with neurological conditions that impede evaluation of vascular pathology by MRI, i.e., brain tumors, multiple sclerosis, and major head trauma, were excluded from the study. When adjusted for age and age squared at MRI exam, sex, and presence of Apolipoproteinɛ4 allele (APOE4), individuals with MSRB3 rs61921502 minor allele had increased odds for brain infarcts on MRI compared to those with no minor allele. However, in stratified analyses, MSRB3 rs61921502 minor allele was significantly associated with increased odds for MRI brain infarcts only in the absence of APOE4.

Modifiable Risk Factors Discriminate Memory Trajectories in Non-Demented Aging: Precision Factors and Targets for Promoting Healthier Brain Aging and Preventing Dementia. - McFall, G Peggy; McDermott, Kirstie L; Dixon, Roger A (J Alzheimers Dis, 2019)
BACKGROUND: Non-demented cognitive aging trajectories are characterized by vast level and slope differences and a spectrum of outcomes, including dementia. OBJECTIVE: The goal of AD risk management (and its corollary, promoting healthy brain aging) is aided by two converging objectives: 1) classifying dynamic distributions of non-demented cognitive trajectories, and 2) identifying modifiable risk-elevating and risk-reducing factors that discriminate stable or normal trajectory patterns from declining or pre-impairment patterns. METHOD: Using latent class growth analysis we classified three episodic memory aging trajectories for n = 882 older adults (baseline Mage=71.6, SD=8.9, range = 53-95, female=66%): Stable (SMA; above average level, sustained slope), Normal (NMA; average level, moderately declining slope), and Declining (DMA; below average level, substantially declining slope). Using random forest analyses, we simultaneously assessed 17 risk/protective factors from non-modifiable demographic, functional, psychological, and lifestyle domains. Within two age strata (Young-Old, Old-Old), three pairwise prediction analyses identified important discriminating factors. RESULTS: Prediction analyses revealed that different modifiable risk predictors, both shared and unique across age strata, discriminated SMA (i.e., education, depressive symptoms, living status, body mass index, heart rate, social activity) and DMA (i.e., lifestyle activities [cognitive, self-maintenance, social], grip strength, heart rate, gait) groups. CONCLUSION: Memory trajectory analyses produced empirical classes varying in level and slope. Prediction analyses revealed different predictors of SMA and DMA that also varied by age strata. Precision approaches for promoting healthier memory aging-and delaying memory impairment-may identify modifiable factors that constitute specific targets for intervention in the differential context of age and non-demented trajectory patterns.

Neuronal Exosome-Derived Human Tau is Toxic to Recipient Mouse Neurons in vivo. - Winston, Charisse N; Aulston, Brent; Rockenstein, Edward M; Adame, Anthony; Prikhodko, Olga; Dave, Kishan N; Mishra, Priyanka; Rissman, Robert A; Yuan, Shauna H (J Alzheimers Dis, 2019)
Progressive accumulation of aggregation-prone proteins, amyloid-β (Aβ) and hyperphosphorylated tau (p-tau), are the defining hallmarks of Alzheimer's disease (AD). The mechanisms by which Aβ and p-tau are transmitted throughout the diseased brain are not yet completely understood. Interest in exosome research has grown dramatically over the past few years, specifically due to their potential role as biomarkers for staging of neurodegenerative diseases, including AD. Despite their diagnostic utility, the pathogenic potential of exosomes has yet to be fully elucidated. In this study, we use a series of recombinant tau antibodies to characterize a new model of human tau in vivo. Exosome suspensions derived from neuronally-differentiated, human induced pluripotent stem cells that express the repeat domain of tau P301L and V337M mutations (NiPSCEs) were injected into the wild-type mouse brain and pathological changes were characterized by immunostaining at one- (1 m) and two-month (2 m) post-injection. We found that tau inclusions were present throughout the brain at 2 m post-injection, which were detectable using antibodies raised against full-length tau (K9JA) and misfolded tau (MC1). Furthermore, we found that phosphorylated tau immunoreactivity was elevated 1 m post-injection, which was surprisingly normalized after 2 m. Finally, we observed extensive degeneration of neuronal dendrites in both ipsilateral and contralateral hippocampi in NiPSCE treated mice. In summary, we demonstrate that exosomes are sufficient to cause long-distance propagation of tau pathology and neurodegeneration in vivo. These novel findings support an active role of exosomes in AD pathogenesis.

NP03, a Microdose Lithium Formulation, Blunts Early Amyloid Post-Plaque Neuropathology in McGill-R-Thy1-APP Alzheimer-Like Transgenic Rats. - Wilson, Edward N; Do Carmo, Sonia; Welikovitch, Lindsay A; Hall, Hélène; Aguilar, Lisi Flores; Foret, Morgan K; Iulita, M Florencia; Jia, Dan Tong; Marks, Adam R; Allard, Simon; Emmerson, Joshua T; Ducatenzeiler, Adriana; et al. (J Alzheimers Dis, 2019)
Epidemiological, preclinical, and clinical studies have suggested a role for microdose lithium in reducing Alzheimer's disease (AD) risk by modulating key mechanisms associated with AD pathology. The novel microdose lithium formulation, NP03, has disease-modifying effects in the McGill-R-Thy1-APP transgenic rat model of AD-like amyloidosis at pre-plaque stages, before frank amyloid-β (Aβ) plaque deposition, during which Aβ is primarily intraneuronal. Here, we are interested in determining whether the positive effects of microdose lithium extend into early Aβ post-plaque stages. We administered NP03 (40μg Li/kg; 1 ml/kg body weight) to McGill-R-Thy1-APP transgenic rats for 12 weeks spanning the transition phase from plaque-free to plaque-bearing. The effect of NP03 on remote working memory was assessed using the novel object recognition task. Levels of human Aβ38, Aβ40, and Aβ42 as well as levels of pro-inflammatory mediators were measured in brain-extracts and plasma using electrochemiluminescent assays. Mature Aβ plaques were visualized with a thioflavin-S staining. Vesicular acetylcholine transporter (VAChT) bouton density and levels of chemokine (C-X-C motif) ligand 1 (CXCL1), interleukin-6 (IL-6), and 4-hydroxynonenal (4-HNE) were probed using quantitative immunohistochemistry. During the early Aβ post-plaque stage, we find that NP03 rescues functional deficits in object recognition, reduces loss of cholinergic boutons in the hippocampus, reduces levels of soluble and insoluble cortical Aβ42 and reduces hippocampal Aβ plaque number. In addition, NP03 reduces markers of neuroinflammation and cellular oxidative stress. Together these results indicate that microdose lithium NP03 is effective at later stages of amyloid pathology, after appearance of Aβ plaques.

Serum Insulin-Like Growth Factor I Deficiency Associates to Alzheimer's Disease Co-Morbidities. - Zegarra-Valdivia, Jonathan A; Santi, Andrea; Fernández de Sevilla, Maria Estrella; Nuñez, Angel; Torres Aleman, Ignacio (J Alzheimers Dis, 2019)
Increasing evidence supports the notion that Alzheimer's disease (AD), a condition that presents heterogeneous pathological disturbances, is also associated to perturbed metabolic function affecting insulin and insulin-like growth factor I (IGF-I). While impaired insulin activity leading to insulin resistance has been associated to AD, whether altered IGF-I function affects the disease is not entirely clear. Despite the limitations of mouse models to mimic AD pathology, we took advantage that serum IGF-I deficient mice (LID mice) present many functional perturbations present in AD, most prominently cognitive loss, which is reversed by treatment with systemic IGF-I. We analyzed whether these mice display other pathological traits that are usual co-morbidities of AD. We found that LID mice not only display cognitive disturbances, but also show altered mood and sociability, increased susceptibility to epileptiform activity, and a disturbed sleep/wake cycle. Collectively, these data suggest that reduced IGF-I activity contributes to heterogeneous deficits commonly associated to AD. We suggest that impaired IGF-I activity needs to be taken into consideration when modeling this condition.

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling. - Chen, Ci-Di; Zeldich, Ella; Khodr, Christina; Camara, Kaddy; Tung, Tze Yu; Lauder, Emma C; Mullen, Patrick; Polanco, Taryn J; Liu, Yen-Yu; Zeldich, Dean; Xia, Weiming; Van Nostrand, William E; et al. (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a compound library for inhibitors of AβPP dimerization, and identified a compound that reduces Aβ levels. In the present study, we have identified an analog, compound Y10, which also reduced Aβ. Initial kinase profiling assays identified the receptor tyrosine kinase cKit as a putative Y10 target. To elucidate the precise mechanism involved, AβPP phosphorylation was examined by IP-western blotting. We found that Y10 inhibits cKit phosphorylation and increases AβPP phosphorylation mainly on tyrosine residue Y743, according to AβPP751 numbering. A known cKit inhibitor and siRNA specific to cKit were also found to increase AβPP phosphorylation and lower Aβ levels. We also investigated a cKit downstream signaling molecule, the Shp2 phosphatase, and found that known Shp2 inhibitors and siRNA specific to Shp2 also increase AβPP phosphorylation, suggesting that the cKit signaling pathway is also involved in AβPP phosphorylation and Aβ production. We further found that inhibitors of both cKit and Shp2 enhance AβPP surface localization. Thus, regulation of AβPP phosphorylation by small molecules should be considered as a novel therapeutic intervention for AD.

Stem Cell-Derived Neurons as Cellular Models of Sporadic Alzheimer's Disease. - Foveau, Bénédicte; Correia, Ana Sofia; Hébert, Sébastien S; Rainone, Sara; Potvin, Olivier; Kergoat, Marie-Jeanne; Belleville, Sylvie; Duchesne, Simon; LeBlanc, Andréa C (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) occurs as either an autosomal dominant inherited disease or sporadically. While familial mutant genes can be expressed in cells or in animal models to assess dysregulated functions, sporadic AD cannot be replicated in models given our lack of understanding of causality. Furthermore, the study of sporadic forms of AD is difficult given the inaccessibility of brain tissues in living individuals and the manifestation of symptoms years after the onset of disease. Here, the objective was to assess if induced pluripotent stem cell-derived neurons from well-ascertained sporadic AD individuals could represent potential cellular models to determine the underlying molecular mechanisms of disease. We used cryopreserved peripheral blood mononuclear cells from three well-ascertained sporadic AD and three non-cognitively impaired (NCI) individuals of the CIMA-Q cohort to obtain iPSC-derived neurons. Microtubule associated protein 2 was decreased in AD neurons, whereas expression of AD-associated amyloid precursor protein, tau, and amyloid-β peptide was similar in AD and NCI individuals. RNA sequencing identified several upregulated and downregulated mRNAs in AD relative to NCI neurons. Of these, complement Factor H (CFH), signal regulatory protein beta1 (SIRPB1), and insulin like growth factor binding protein 5 (IGFBP5) were previously associated with AD. In addition, several transcription factors not previously associated with AD, but involved in neuronal proliferation and differentiation were differentially expressed. The results identify novel avenues for the study of the underlying causes of sporadic AD and support the establishment of additional lines to identify mechanisms of disease in sporadic AD individuals.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Transcriptome Changes in the Alzheimer's Disease Middle Temporal Gyrus: Importance of RNA Metabolism and Mitochondria-Associated Membrane Genes. - Piras, Ignazio S; Krate, Jonida; Delvaux, Elaine; Nolz, Jennifer; Mastroeni, Diego F; Persico, Antonio M; Jepsen, Wayne M; Beach, Thomas G; Huentelman, Matthew J; Coleman, Paul D (J Alzheimers Dis, 2019)
We used Illumina Human HT-12 v4 arrays to compare RNA expression of middle temporal gyrus (MTG; BA21) in Alzheimer's disease (AD = 97) and non-demented controls (ND = 98). A total of 938 transcripts were highly differentially expressed (adj p < 0.01; log2 FC ≥ |0.500|, with 411 overexpressed and 527 underexpressed in AD. Our results correlated with expression profiling in neurons from AD and ND obtained by laser capture microscopy in MTG from an independent dataset (log2 FC correlation: r = 0.504; p = 2.2e-16). Additionally, selected effects were validated by qPCR. ANOVA analysis yielded no difference between genders in response to AD, but some gender specific genes were detected (e.g., IL8 and AGRN in males, and HSPH1 and GRM1 in females). Several transcripts were associated with Braak staging (e.g., AEBP1 and DNALI1), antemortem MMSE (e.g., AEBP1 and GFAP), and tangle density (e.g., RNU1G2, and DNALI1). At the pathway level, we detected enrichment of synaptic vesicle processes and GABAergic transmission genes. Finally, applying the Weighted Correlation Network Analysis, we identified four expression modules enriched for neuronal and synaptic genes, mitochondria-associated membrane, chemical stimulus and olfactory receptor and non-coding RNA metabolism genes. Our results represent an extensive description of MTG mRNA profiling in a large sample of AD and ND. These data provide a list of genes associated with AD, and correlated to neurofibrillary tangles density. In addition, these data emphasize the importance of mitochondrial membranes and transcripts related to olfactory receptors in AD.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

Ultrasensitive Detection of Plasma Amyloid-β as a Biomarker for Cognitively Normal Elderly Individuals at Risk of Alzheimer's Disease. - Chatterjee, Pratishtha; Elmi, Mitra; Goozee, Kathryn; Shah, Tejal; Sohrabi, Hamid R; Dias, Cintia B; Pedrini, Steve; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Taddei, Kevin; Vanderstichele, Hugo; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Aberrant amyloid-β (Aβ) deposition in the brain occurs two decades prior to the manifestation of Alzheimer's disease (AD) clinical symptoms and therefore brain Aβ load measured using PET serves as a gold standard biomarker for the early diagnosis of AD. However, the uneconomical nature of PET makes blood markers, that reflect brain Aβ deposition, attractive candidates for investigation as surrogate markers. OBJECTIVE: Investigation of plasma Aβ as a surrogate marker for brain Aβ deposition in cognitively normal elderly individuals. METHODS: Plasma Aβ40 and Aβ42 concentrations were measured using the ultrasensitive Single Molecule Array (Simoa) assay in 95 cognitively normal elderly individuals, who have all undergone PET to assess brain Aβ deposition. Based on the standard uptake value ratios (SUVR) obtained from PET imaging, using the tracer 18F-Florbetaben, plasma Aβ was compared between 32 participants assessed to have low brain Aβ load (Aβ-, SUVR <1.35) and 63 assessed to have high brain Aβ load (Aβ+, SUVR ≥1.35). RESULTS: Plasma Aβ42/Aβ40 ratios were lower in the Aβ+ group compared to the Aβ-group. Plasma Aβ40 and Aβ42 levels were not significantly different between Aβ-and Aβ+ groups, although a trend of higher plasma Aβ40 was observed in the Aβ+ group. Additionally, plasma Aβ42/Aβ40 ratios along with the known AD risk factors, age and APOEɛ4 status, resulted in Aβ+ participants being distinguished from Aβ-participants based on an area under the receiver operating characteristic curve shown to be 78%. CONCLUSION: Plasma Aβ ratios in this study are a potential biomarker for brain Aβ deposition and therefore, for preclinical AD. However, this method to measure plasma Aβ needs further development to increase the accuracy of this promising AD blood biomarker.

An UNC5C Allele Predicts Cognitive Decline and Hippocampal Atrophy in Clinically Normal Older Adults. - Yang, Hyun-Sik; Chhatwal, Jasmeer P; Xu, Jishu; White, Charles C; Hanseeuw, Bernard; Rabin, Jennifer S; Papp, Kathryn V; Buckley, Rachel F; Schultz, Aaron P; Properzi, Michael J; Gatchel, Jennifer R; Amariglio, Rebecca E; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The UNC5C rs3846455G allele has been linked to poor cognitive resilience against age-related neuropathologies, but this association remains to be replicated, and the allele's effect on hippocampal neurodegeneration needs to be examined. OBJECTIVE: To further validate the association between rs3846455G and faster cognitive decline, especially among cognitively normal older adults, and to assess whether rs3846455G predicts accelerated hippocampal volume loss in older adults. METHODS: We assessed participants in the Harvard Aging Brain Study (HABS), a longitudinal cohort study of older adults who were clinically normal at baseline. To avoid bias from population admixture, analyses were limited to participants of European descent with longitudinal neuroimaging data (n = 174). Linear mixed effect models were used to examine the effect of rs3846455G on longitudinal change of the Preclinical Alzheimer Cognitive Composite (PACC) and MRI-measured bilateral hippocampal volume, adjusting for baseline amyloid-β (Aβ) measured by the cortical Pittsburgh Compound B PET distributed volume ratio. We also tested whether hippocampal atrophy mediates the association between rs3846455G and greater PACC decline through a mediation analysis. RESULTS: rs3846455G was associated with greater PACC decline (β= -0.087/year, 95% CI -0.169 to -0.005, p = 0.039) after controlling for baseline Aβ. Further, rs3846455G predicted accelerated hippocampal atrophy after controlling for baseline Aβ (β= -57.3 mm3/year, 95% CI -102.8 to -11.9, p = 0.014). The association between rs3846455G and greater PACC decline was partially mediated by accelerated hippocampal atrophy (mediated effect (relative scale) = -0.014, 95% CI -0.032 to -6.0×10-4, p = 0.039). CONCLUSION: UNC5C rs3846455G predicts greater cognitive decline and accelerated hippocampal atrophy in clinically normal older adults.

Vascular Burden Score Impacts Cognition Independent of Amyloid PET and MRI Measures of Alzheimer's Disease and Vascular Brain Injury. - DeCarli, Charles; Villeneuve, Sylvia; Maillard, Pauline; Harvey, Danielle; Singh, Baljeet; Carmichael, Owen; Fletcher, Evan; Olichney, John; Farias, Sarah; Jagust, William; Reed, Bruce; Mungas, Dan (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: To determine the impact of vascular burden on rates of decline in episodic memory and executive function. We hypothesize that greater vascular burden will have an additive negative impact on cognition after accounting for baseline cognitive impairment, positron emission tomography (PET) amyloid burden, and magnetic resonance imaging (MRI) measures. METHODS: Individuals were followed an average of 5 years with serial cognitive assessments. Predictor variables include vascular burden score (VBS), quantitative brain MRI assessment, and amyloid imaging. Subjects consisted of 65 individuals, 53% of whom were male, aged 73.2±7.2 years on average with an average of 15.5±3.3 years of educational achievement. RESULTS: Baseline cognitive impairment was significantly associated poorer episodic memory (p < 0.0001), smaller hippocampal volume (p < 0.0001), smaller brain volume (p = 0.0026), and greater global Pittsburg Imaging Compound B (PiB) index (p = 0.0008). Greater amyloid burden was associated with greater decline in episodic memory over time (β= -0.20±0.07, p < 0.005). VBS was significantly associated with the level of executive function performance (β= -0.14±0.05, p < 0.005) and there was a significant negative interaction between VBS, cognitive impairment, and PiB index (β= -0.065±0.03, p = 0.03). CONCLUSIONS: Our results find a significant influence of VBS independent of standard MRI measures and cerebral amyloid burden on executive function. In addition, VBS reduced the amount of cerebral amyloid burden needed to result in cognitive impairment. We conclude that the systemic effects of vascular disease as reflected by the VBS independently influence cognitive ability.

Vascular Mild Cognitive Impairment: Identifying Disease in Community-Dwelling Older Adults, Reducing Risk Factors, and Providing Support. The Osaki-Tajiri and Kurihara Projects. - Meguro, Kenichi; Dodge, Hiroko H (J Alzheimers Dis, 2019)
Vascular mild cognitive impairment (MCI) is a critical disease. Its prognosis includes not only onset of vascular dementia, but also death by cardiovascular disease. The vascular risk factors for vascular MCI are treatable, and appropriate treatment can prevent or delay the progression to dementia. Therefore, this group is an excellent candidate for secondary prevention. However, community-dwelling older adults with vascular MCI are often undetected and are not clinically identified until they develop frank dementia. Furthermore, older adults with undetected vascular MCI often have decreased ability to follow their medication regimens and this poor medication adherence worsens their vascular comorbidities. This vicious cycle needs to be prevented through community-based interventions. There is evidence that treatment of hypertension or diabetes mellitus could lead to a reduced incidence of vascular MCI and dementia. In this review article, we first explain the background and etiology of vascular MCI. We then summarize phenotype of subcortical vascular dementia which is often unrecognized or "hidden" in the community. Then we introduce the Osaki-Tajiri and Kurihara Projects which have been conducted in Northern Japan, as an example of prevention projects aimed to identify early-stage vascular MCI in the community, reduce the risk factors and facilitate their treatment. Early identification of vascular MCI in the community could lead to a large reduction in the dementia burden worldwide. The outreach efforts presented here could be useful in developing secondary prevention strategies targeted to vascular MCI.

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

The 20-Year Voyage Aboard the Journal of Alzheimer's Disease: Docking at 'Type 3 Diabetes', Environmental/Exposure Factors, Pathogenic Mechanisms, and Potential Treatments. - de la Monte, Suzanne M; Tong, Ming; Wands, Jack R (J Alzheimers Dis, 2018)
The Journal of Alzheimer's Disease (JAD), founded in 1998, played a pivotal role in broadening the field of research on Alzheimer's disease (AD) by publishing a diverse range of clinical, pathological, molecular, biochemical, epidemiological, experimental, and review articles from its birth. This article recounts my own journey as an author who contributed articles to JAD over the 20 years of the journal's existence. In retrospect, it seems remarkable that a considerable body of work that originated from our group marks a trail that began with studies of vascular, stress, and mitochondrial factors in AD pathogenesis, exploded into the concept of 'Type 3 Diabetes', and continued with the characterization of how environmental, exposure, and lifestyle factors promote neurodegeneration and which therapeutic strategies could reverse the neurodegeneration cascade.

ABCA7 Downregulation Modifies Cellular Cholesterol Homeostasis and Decreases Amyloid-β Peptide Efflux in an in vitro Model of the Blood-Brain Barrier. - Lamartinière, Yordenca; Boucau, Marie-Christine; Dehouck, Lucie; Krohn, Markus; Pahnke, Jens; Candela, Pietra; Gosselet, Fabien; Fenart, Laurence (J Alzheimers Dis, 2018)
The role of ABCA7 in brain homeostasis and Alzheimer's disease (AD) is currently under intense scrutiny, since it has been reported that polymorphisms in the Abca7 gene and a loss of function of the protein are closely linked to excessive accumulation of amyloid peptides and disturbed cholesterol homeostasis. The blood-brain barrier (BBB), which isolates the brain from the blood compartment, is involved in both of these processes. We therefore hypothesized that ABCA7 downregulation might affect cholesterol and amyloid exchanges at the BBB. Using siRNA and primary cultures of mouse endothelial cells purified from brain microvessels and seeded on Transwell ® inserts, we investigated the role of ABCA7 in cholesterol and amyloid exchanges across the BBB. Our results showed that a decrease in ABCA7 expression at the BBB provokes in vitro a reduction in ABCA1 expression and a decrease in APOE secretion. In vitro, these decreases reduce cholesterol exchange across the BBB, particularly for high-density lipoproteins and ApoA-I particles. When ABCA7 was absent, we observed a reduction in Aβ peptide basolateral-to-apical transport in the presence of ApoA-I, with non-significant changes in the expression levels of Rage, Lrp1, Abcb1, Abcc1, and Abcg2. Our study in murine BBB model highlighted a putative new role for ABCA7 in AD via the protein's involvement in cholesterol metabolism and amyloid clearance at the BBB.

Aberrant Cortical Event-Related Potentials During Associative Learning in Rat Models for Presymptomatic Stages of Alzheimer's Disease. - Nouriziabari, Bardia; Sarkar, Susmita; Tanninen, Stephanie E; Dayton, Robert D; Klein, Ronald L; Takehara-Nishiuchi, Kaori (J Alzheimers Dis, 2018)
Trace eyeblink conditioning is a hippocampus-dependent associative learning paradigm which is impaired in patients with Alzheimer's disease (AD) and animal AD models. Learning in this paradigm accompanies changes in oscillatory activity in forebrain regions, some of which are loci of pathogenic changes in prodromal AD stages. These observations motivated us to examine how cortical event-related potentials (ERPs) during this paradigm are affected by two features of the asymptomatic, AD-related brain abnormality, entorhinal tau accumulation and mild cholinergic deficit. Adult rats received viral overexpression of P301L mutant human tau in the entorhinal cortex, low-dose scopolamine treatment, or both. Electroencephalograms were recorded with epidural electrodes on the surface of the frontal, parietal, and temporal cortices during differential and reversal trace eyeblink conditioning. All rats developed conditioned responses to one of two stimuli (auditory or visual) paired with mild eyelid shock (CS+), but not to the other stimulus presented alone (CS-). They were also able to adjust the response when the stimulus contingency was reversed. With learning, the amplitude of several ERP components in the frontal and temporal cortices came to differentiate the CS+ from CS-. Scopolamine affected the learning-related change in temporal P2 and other learning-unrelated components in three regions. Entorhinal tau overexpression primary affected the amplitude of temporal visual ERPs and learning-unrelated frontal and temporal auditory ERP components. The double manipulation only affected two components of temporal auditory ERPs. Thus, cortical ERPs during differential associative learning are sensitive to asymptomatic brain abnormality associated with AD.

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

Accuracy of Inferred APOE Genotypes for a Range of Genotyping Arrays and Imputation Reference Panels. - Lupton, Michelle K; Medland, Sarah E; Gordon, Scott D; Goncalves, Tabatha; MacGregor, Stuart; Mackey, David A; Young, Terri L; Duffy, David L; Visscher, Peter M; Wray, Naomi R; Nyholt, Dale R; Bain, Lisa; et al. (J Alzheimers Dis, 2018)
Cohort studies investigating aging and dementia require APOE genotyping. We compared directly measured APOE genotypes to 'hard-call' genotypes derived from imputing genome-wide genotyping data from a range of platforms using several imputation panels. Older GWAS arrays imputed to 1000 Genomes Project (1KGP) phases and the Haplotype Reference Consortium (HRC) reference panels were able to achieve concordance rates of over 98% with stringent quality control (hard-call-threshold 0.8). However, this resulted in high levels of missingness (>12% with 1KGP and 5% with HRC). With recent GWAS arrays, concordance of 99% could be obtained with relatively lenient QC, resulting in no missingness.

Added Diagnostic Value of Cerebrospinal Fluid Biomarkers for Differential Dementia Diagnosis in an Autopsy-Confirmed Cohort. - Niemantsverdriet, Ellis; Feyen, Bart F E; Le Bastard, Nathalie; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Bjerke, Maria; Engelborghs, Sebastiaan (J Alzheimers Dis, 2018)
BACKGROUND: Differential dementia diagnosis remains a challenge due to overlap of clinical profiles, which often results in diagnostic doubt. OBJECTIVE: Determine the added diagnostic value of cerebrospinal fluid (CSF) biomarkers for differential dementia diagnosis as compared to autopsy-confirmed diagnosis. METHODS: Seventy-one dementia patients with autopsy-confirmed diagnoses were included in this study. All neuropathological diagnoses were established according to standard neuropathological criteria and consisted of Alzheimer's disease (AD) or other dementias (NONAD). CSF levels of Aβ1 - 42, T-tau, and P-tau181 were determined and interpreted based on the IWG-2 and NIA-AA criteria, separately. A panel of three neurologists experienced with dementia made clinical consensus dementia diagnoses. Clinical and CSF biomarker diagnoses were compared to the autopsy-confirmed diagnoses. RESULTS: Forty-two patients (59%) had autopsy-confirmed AD, whereas 29 patients (41%) had autopsy-confirmed NONAD. Of the 24 patients with an ambiguous clinical dementia diagnosis, a correct diagnosis would have been established in 67% of the cases applying CSF biomarkers in the context of the IWG-2 or the NIA-AA criteria respectively. CONCLUSION: AD CSF biomarkers have an added diagnostic value in differential dementia diagnosis and can help establishing a correct dementia diagnosis in case of ambiguous clinical dementia diagnoses.

The Added Value of Diffusion-Weighted MRI-Derived Structural Connectome in Evaluating Mild Cognitive Impairment: A Multi-Cohort Validation1. - Wang, Qi; Guo, Lei; Thompson, Paul M; Jack, Clifford R; Dodge, Hiroko; Zhan, Liang; Zhou, Jiayu (J Alzheimers Dis, 2018)
T1-weighted MRI has been extensively used to extract imaging biomarkers and build classification models for differentiating Alzheimer's disease (AD) patients from healthy controls, but only recently have brain connectome networks derived from diffusion-weighted MRI been used to model AD progression and various stages of disease such as mild cognitive impairment (MCI). MCI, as a possible prodromal stage of AD, has gained intense interest recently, since it may be used to assess risk factors for AD. Little work has been done to combine information from both white matter and gray matter, and it is unknown how much classification power the diffusion-weighted MRI-derived structural connectome could provide beyond information available from T1-weighted MRI. In this paper, we focused on investigating whether diffusion-weighted MRI-derived structural connectome can improve differentiating healthy controls subjects from those with MCI. Specifically, we proposed a novel feature-ranking method to build classification models using the most highly ranked feature variables to classify MCI with healthy controls. We verified our method on two independent cohorts including the second stage of Alzheimer's Disease Neuroimaging Initiative (ADNI2) database and the National Alzheimer's Coordinating Center (NACC) database. Our results indicated that 1) diffusion-weighted MRI-derived structural connectome can complement T1-weighted MRI in the classification task; 2) the feature-rank method is effective because of the identified consistent T1-weighted MRI and network feature variables on ADNI2 and NACC. Furthermore, by comparing the top-ranked feature variables from ADNI2, NACC, and combined dataset, we concluded that cross-validation using independent cohorts is necessary and highly recommended.

Age-Dependent Changes to Sphingolipid Balance in the Human Hippocampus are Gender-Specific and May Sensitize to Neurodegeneration. - Couttas, Timothy A; Kain, Nupur; Tran, Collin; Chatterton, Zac; Kwok, John B; Don, Anthony S (J Alzheimers Dis, 2018)
The greatest risk factor for developing Alzheimer's disease (AD) is aging. The major genetic risk factor for AD is the ɛ4 allele of the APOE gene, encoding the brain's major lipid transport protein, apolipoprotein E (ApoE). The research community is yet to decipher why the ApoE4 variant pre-disposes to AD, and how aging causes the disease. Studies have shown deregulated levels of sphingolipids, including decreased levels of the neuroprotective signaling lipid sphingosine 1-phosphate (S1P), and increased ceramide content, in brain tissue and serum of people with pre-clinical or very early AD. In this study we investigated whether sphingolipid levels are affected as a function of age or APOE genotype, in the hippocampus of neurologically normal subjects over the age of 65. Lipids were quantified in 80 postmortem tissue samples using liquid chromatography tandem mass spectrometry (LC-MS/MS). Sphingolipid levels were not significantly affected by the presence of one ɛ4 or ɛ2 allele. However, ceramide, sphingomyelin, and sulfatide content was very significantly correlated with age in the hippocampus of males. On the other hand, S1P, normalized to its non-phosphorylated precursor sphingosine, was inversely correlated with age in females. Our results therefore establish gender-specific differences in sphingolipid metabolism in the aging human brain. Ceramide is a pro-apoptotic lipid, and heavily implicated as a driver of insulin resistance in metabolic tissues. S1P is a neuroprotective lipid that supports glutamatergic neurotransmission. Increasing ceramide and decreasing S1P levels may contribute significantly to a pro-neurodegenerative phenotype in the aging brain.

Alterations in the Plasma Levels of Specific Choline Phospholipids in Alzheimer's Disease Mimic Accelerated Aging. - Dorninger, Fabian; Moser, Ann B; Kou, Jianqiu; Wiesinger, Christoph; Forss-Petter, Sonja; Gleiss, Andreas; Hinterberger, Margareta; Jungwirth, Susanne; Fischer, Peter; Berger, Johannes (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disease and of continuously rising prevalence. The identification of easy-to-measure biomarkers capable to assist in the prediction and early diagnosis of AD is currently a main research goal. Lipid metabolites in peripheral blood of human patients have recently gained major attention in this respect. Here, we analyzed plasma of 174 participants (not demented at baseline; mean age: 75.70±0.44 years) of the Vienna Transdanube Aging (VITA) study, a longitudinal, population-based birth cohort study, at baseline and after 90 months or at diagnosis of probable AD. We determined the levels of specific choline phospholipids, some of which have been suggested as potential biomarkers for the prediction of AD. Our results show that during normal aging the levels of lysophosphatidylcholine, choline plasmalogen, and lyso-platelet activating factor increase significantly. Notably, we observed similar but more pronounced changes in the group that developed probable AD. Thus, our results imply that, in terms of choline-containing plasma phospholipids, the conversion to AD mimics an accelerated aging process. We conclude that age, even in the comparatively short time frame between 75 and 82.5 years, is a crucial factor in the quest for plasma lipid biomarkers for AD that must be carefully considered in future studies and trials.

Altered Expression of Circulating Cdc42 in Frontotemporal Lobar Degeneration. - Saraceno, Claudia; Catania, Marcella; Paterlini, Anna; Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Binetti, Giuliano; Di Fede, Giuseppe; Caroppo, Paola; Benussi, Luisa; Ghidoni, Roberta; Bolognin, Silvia (J Alzheimers Dis, 2018)
The term frontotemporal lobar degeneration (FTLD) defines a group of heterogeneous conditions histologically characterized by neuronal degeneration, inclusions of various proteins, and synaptic loss. However, the molecular mechanisms contributing to these alterations are still unknown. As the Rho-GTPase family member Cell division cycle 42 (Cdc42) plays a key role in the regulation of actin cytoskeleton dynamics and spine formation, we investigated whether Cdc42 protein levels were altered in the disease. Cdc42 was increased in the frontal cortex of FTLD patients compared to age-matched controls, but also in Alzheimer's disease (AD) patients included in the data-set. On the other hand, the pool of circulating Cdc42 in the plasma was altered in FTLD but not in AD patients. Interestingly, the stratification of the FTLD patients according to the different clinical variants showed a specific decrease of Cdc42 expression in the behavioral subgroup. This data support a role of Cdc42 in FTLD and specifically in the behavioral variant.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; cdc42 GTP-Binding Protein; Female; Frontotemporal Lobar Degeneration; Humans; Male; Middle Aged

Altered microRNA, mRNA, and Protein Expression of Neurodegeneration-Related Biomarkers and Their Transcriptional and Epigenetic Modifiers in a Human Tau Transgenic Mouse Model in Response to Developmental Lead Exposure. - Masoud, Anwar M; Bihaqi, Syed W; Alansi, Bothaina; Dash, Miriam; Subaiea, Gehad M; Renehan, William E; Zawia, Nasser H (J Alzheimers Dis, 2018)
Amyloid deposits originating from the amyloid-β protein precursor (AβPP) and aggregates of the microtubule associated protein tau (MAPT) are the hallmarks of Alzheimer's disease (AD). Animal studies have demonstrated a link between early life exposure to lead (Pb) and latent overexpression of the AβPP and MAPT genes and their products via epigenetic reprogramming. The present study monitored APP gene and epigenetic mediators and transcription factors known to regulate it. Western blot analysis and quantitative polymerase chain reaction (qPCR) were used to study the mRNA, miRNA, and proteins levels of AβPP, specificity protein 1 (SP1; a transcriptional regulator of amyloid and tau pathway), and epigenetic intermediates namely: DNA methyltransferase (DNMT) 1, DNMT3a and Methyl- CpG protein binding 2 (MeCP2) in the cerebral cortex of transgenic mice (Knock-in for human MAPT). These transgenic mice were developmentally exposed to Pb and the impact on mRNA, miRNA, and protein levels was scrutinized on postnatal days (PND) 20 and 50. The data revealed a consistent inverse relationship between miRNA and protein levels for SP1 and AβPP both in the basal and exposed conditions, which may influence the levels of their corresponding proteins. On the other hand, the relationship between miRNA and protein levels was not correlative for DNMT1 and DNMT3a. MeCP2 miRNA protein levels corresponded only following environmental exposure. These results suggest that developmental exposure to Pb and subsequent AβPP protein levels may be controlled through transcriptional regulators and epigenetic mechanisms that mainly involve miRNA regulation.

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease: Advances in Drug Development. - Piton, Morgane; Hirtz, Christophe; Desmetz, Caroline; Milhau, Jacqueline; Lajoix, Anne Dominique; Bennys, Karim; Lehmann, Sylvain; Gabelle, Audrey (J Alzheimers Dis, 2018)
As of 2018, Alzheimer's disease (AD) is the most common form of neurodegenerative dementia. It contributes to a progressive neuron loss, deterioration of memory, and cognitive impairment. Current therapies may provide a symptomatic benefit, but do not treat the underlying process. Ongoing researches focus on understanding the causal mechanisms and finding neuropathological hallmarks of AD. Therapeutic approaches targeting senile plaques or neurofibrillary tangles have not yet resulted in a significant cognitive improvement. However, recent data according to the analysis of AD clinical trials (clinicaltrials.gov database) show promising results. This literature review aims at summarizing the recent advances and at highlighting the most promising results of the ongoing researches. It compares the merits of small-molecules, antibodies, cell, and gene-based therapies and emphasizes the need for treatment at earlier stages of the disease.

Amyloid-Mediated Cholinergic Dysfunction in Motor Impairment Related to Alzheimer's Disease. - Schirinzi, Tommaso; Di Lorenzo, Francesco; Sancesario, Giulia Maria; Di Lazzaro, Giulia; Ponzo, Viviana; Pisani, Antonio; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro (J Alzheimers Dis, 2018)
BACKGROUND: Although motor disturbances parallel the course of dementia, worsening both quality of life and social costs, the pathogenesis remains still unclear. OBJECTIVE: Through the combination of cerebrospinal fluid (CSF) biomarkers assessment and transcranial magnetic stimulation (TMS) protocols, here we provided a cross-sectional study to understand pathogenic mechanisms of Alzheimer's disease (AD)-related early motor disturbances. METHODS: The motor phenotype, as defined with Unified Parkinson's Disease Rating Scale (UPDRS) part 2-3, Rating Scale for Gait Evaluation in Cognitive Deterioration (RSEGCD) and Tinetti scale, together with CSF profile of amyloid-β 42 (Aβ42), total-tau, and phosphorylated-tau were determined in 37 AD patients and compared to 18 patients with vascular dementia (VaD). A TMS protocol of short afferent inhibition (SAI) was further applied on a subset of AD patients. Clinical, biochemical, and neurophysiological data were then compared and correlated in order to find significant associations. RESULTS: AD patients exhibited subtle locomotor impairment and slight extrapyramidal signs. Main motor features (UPDRS part 3, RSGECD, and Tinetti scale scores) correlate with Aβ42 levels but not with t-tau and p-tau. AD patients also presented SAI impairment directly related to UPDRS part 3 score and Aβ42 levels. Motor disturbances of VaD group did not differ statistically from AD and did not correlate with CSF biomarkers. CONCLUSIONS: The association of motor disturbances with low Aβ42 CSF levels and individual SAI suggests that amyloid-mediated degeneration of cholinergic system may account for early AD-related motor impairment, providing interesting insights either for frailty stratification of patients or personalized therapies.

Amyloid-β/Drug Interactions from Computer Simulations and Cell-Based Assays. - Nguyen, Phuong H; Del Castillo-Frias, Maria P; Berthoumieux, Olivia; Faller, Peter; Doig, Andrew J; Derreumaux, Philippe (J Alzheimers Dis, 2018)
Targeting the early oligomers formed by the amyloid-β (Aβ) peptide of 40 and 42 amino acids is considered one promising therapeutic approach for Alzheimer's disease (AD). In vitro experiments and computer simulations are often used in synergy to reveal the modes of interactions of drugs. In this account, we present our contribution to understanding how small molecules bind to Aβ40/Aβ42 peptides, based either on extensive coarse-grained and all-atom simulations, or a variety of experimental techniques. We conclude by offering several perspectives on the future of this field to design more efficient drugs.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

Assessing Working Memory in Mild Cognitive Impairment with Serial Order Recall. - Emrani, Sheina; Libon, David J; Lamar, Melissa; Price, Catherine C; Jefferson, Angela L; Gifford, Katherine A; Hohman, Timothy J; Nation, Daniel A; Delano-Wood, Lisa; Jak, Amy; Bangen, Katherine J; Bondi, Mark W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Working memory (WM) is often assessed with serial order tests such as repeating digits backward. In prior dementia research using the Backward Digit Span Test (BDT), only aggregate test performance was examined. OBJECTIVE: The current research tallied primacy/recency effects, out-of-sequence transposition errors, perseverations, and omissions to assess WM deficits in patients with mild cognitive impairment (MCI). METHODS: Memory clinic patients (n = 66) were classified into three groups: single domain amnestic MCI (aMCI), combined mixed domain/dysexecutive MCI (mixed/dys MCI), and non-MCI where patients did not meet criteria for MCI. Serial order/WM ability was assessed by asking participants to repeat 7 trials of five digits backwards. Serial order position accuracy, transposition errors, perseverations, and omission errors were tallied. RESULTS: A 3 (group)×5 (serial position) repeated measures ANOVA yielded a significant group×trial interaction. Follow-up analyses found attenuation of the recency effect for mixed/dys MCI patients. Mixed/dys MCI patients scored lower than non-MCI patients for serial position 3 (p < 0.003) serial position 4 (p < 0.002); and lower than both group for serial position 5 (recency; p < 0.002). Mixed/dys MCI patients also produced more transposition errors than both groups (p < 0.010); and more omissions (p < 0.020), and perseverations errors (p < 0.018) than non-MCI patients. CONCLUSIONS: The attenuation of a recency effect using serial order parameters obtained from the BDT may provide a useful operational definition as well as additional diagnostic information regarding working memory deficits in MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Neuropsychological Tests; Regression Analysis; Serial Learning

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

Association between Peripheral Leptin and Adiponectin Levels and Cognitive Decline in Patients with Neurocognitive Disorders ≥65 Years. - Gilbert, Thomas; Roche, Sylvain; Blond, Emilie; Bar, Jean-Yves; Drai, Jocelyne; Cuerq, Charlotte; Haution-Bitker, Marine; Ecochard, René; Bonnefoy, Marc (J Alzheimers Dis, 2018)
BACKGROUND: There is evidence that adipokines have roles in brain functioning and cognitive decline. OBJECTIVE: Assess the role of leptin and adiponectin levels in predicting changes in neuro-cognitive disorders (NCD). METHODS: The study included 205 patients over 65 years of age presenting for a one-day hospitalization for current assessment of cognitive function. Peripheral blood leptin and adiponectin levels were measured at admission. Demographic variables, body mass index (BMI), and history of hypertension were also recorded. Cognitive function was assessed by the Mini-Mental State Examination (MMSE) at admission and at later scheduled visits over a median follow-up period of 14.5 months. Conventional univariate comparisons were made between diagnosis groups (Alzheimer's disease (AD), mild NCD, vascular/mixed dementia). Changes in MMSE scores over time were examined with regard to the above variables using a linear mixed model. RESULTS: The mean BMI was significantly lower (by 2 kg/m2, p = 0.01) in patients with AD than in patients with either mild-NCD or vascular/mixed dementia. Leptin levels were significantly higher (p = 0.043) and adiponectin levels significantly lower (p = 0.045) in patients with mild-NCD than in patients with major-NCD (AD or vascular/mixed dementia). However, the mixed model suggested no influence of the baseline levels of these two biomarkers on the course of cognitive decline. CONCLUSION: The present study confirms the associations between leptin and adiponectin and AD or AD-related disorders but did not confirm that these peptides may be used as predictive biomarkers of cognitive decline.

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Association of Plasma Neurofilament Light Chain with Neocortical Amyloid-β Load and Cognitive Performance in Cognitively Normal Elderly Participants. - Chatterjee, Pratishtha; Goozee, Kathryn; Sohrabi, Hamid R; Shen, Kaikai; Shah, Tejal; Asih, Prita R; Dave, Preeti; ManYan, Candice; Taddei, Kevin; Chung, Roger; Zetterberg, Henrik; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The disruption of neurofilament, an axonal cytoskeletal protein, in neurodegenerative conditions may result in neuronal damage and its release into the cerebrospinal fluid and blood. In Alzheimer's disease (AD), neurofilament light chain (NFL), a neurofilament subunit, is elevated in the cerebrospinal fluid and blood. OBJECTIVE: Investigate the association of plasma NFL with preclinical-AD features, such as high neocortical amyloid-β load (NAL) and subjective memory complaints, and cognitive performance in cognitively normal older adults. METHODS: Plasma NFL concentrations were measured employing the single molecule array platform in participants from the Kerr Anglican Retirement Village Initiative in Ageing Health cohort, aged 65- 90 years. Participants underwent a battery of neuropsychological testing to evaluate cognitive performance and were categorized as low NAL (NAL-, n = 65) and high NAL (NAL+, n = 35) assessed via PET, and further stratified into subjective memory complainers (SMC; nNAL- = 51, nNAL+ = 25) and non-SMC (nNAL- = 14, nNAL+ = 10) based on the Memory Assessment Clinic- Questionnaire. RESULTS: Plasma NFL inversely correlated with cognitive performance. No significant difference in NFL was observed between NAL+ and NAL- participants; however, within APOEɛ4 non-carriers, higher NAL was observed in individuals with NFL concentrations within quartiles 3 and 4 (versus quartile 1). Additionally, within the NAL+ participants, SMC had a trend of higher NFL compared to non-SMC. CONCLUSION: Plasma NFL is inversely associated with cognitive performance in elderly individuals. While plasma NFL may not reflect NAL in individuals with normal global cognition, the current observations indicate that onset of axonal injury, reflected by increased plasma NFL, within the preclinical phase of AD may contribute to the pathogenesis of AD.

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations between the Frailty Index and Brain Atrophy: The Treviso Dementia (TREDEM) Registry. - Gallucci, Maurizio; Piovesan, Cinzia; Di Battista, Maria Elena (J Alzheimers Dis, 2018)
BACKGROUND: Frailty is a condition which is characterized by a reduction in the homeostatic reserves of the individual and which entails an increased vulnerability to stressful endogenous and exogenous agents. The Frailty Index (FI), proposed by Rockwood, was designed following an accumulation of deficits model: the greater the number of deficits in a given individual, the greater the degree of frailty. OBJECTIVE: The aim of this study was to verify the existence of associations between FI and cerebral atrophy. METHODS: The TREDEM Register (Treviso Dementia) provided retrospective observational data from 1,584 patients. The FI was calculated based on 50 variables comprising diseases, disability, behavioral disturbances, and blood chemistry parameters. The severity of atrophy in the cortical and subcortical regions, such as the amplitude of the lateral ventricles, were detected by computerized axial tomography (CAT). Multiple logistic regression models using the stepwise backward method were used to analyze possible associations between FI and atrophy. RESULTS: For each increment of one hundredth of the FI, the probability of cortical atrophy increases by 2%. The female gender is a protective factor for cortical and subcortical atrophy. At each increase of one percent of the FI, the probability of a severe degree of cortical atrophy increases by 3%. The FI was significantly associated with frontal and temporal cortical atrophy. The relationship between overall subcortical atrophy and the FI was not significant, whereas it was the one with the severe degree of subcortical atrophy. The FI is significantly associated with the atrophy of the peri-insular subcortical region. Similar associations were found considering only demented patients. CONCLUSION: The FI is associated with the presence, degree, and some localization of cerebral atrophy in a population of cognitive-decline patients.

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) Scale: Comprehensive Assessment of Psychopathology in Down Syndrome. - Dekker, Alain D; Sacco, Silvia; Carfi, Angelo; Benejam, Bessy; Vermeiren, Yannick; Beugelsdijk, Gonny; Schippers, Mieke; Hassefras, Lyanne; Eleveld, José; Grefelman, Sharina; Fopma, Roelie; Bomer-Veenboer, Monique; et al. (J Alzheimers Dis, 2018)
People with Down syndrome (DS) are prone to develop Alzheimer's disease (AD). Behavioral and psychological symptoms of dementia (BPSD) are core features, but have not been comprehensively evaluated in DS. In a European multidisciplinary study, the novel Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) scale was developed to identify frequency and severity of behavioral changes taking account of life-long characteristic behavior. 83 behavioral items in 12 clinically defined sections were evaluated. The central aim was to identify items that change in relation to the dementia status, and thus may differentiate between diagnostic groups. Structured interviews were conducted with informants of persons with DS without dementia (DS, n = 149), with questionable dementia (DS+Q, n = 65), and with diagnosed dementia (DS+AD, n = 67). First exploratory data suggest promising interrater, test-retest, and internal consistency reliability measures. Concerning item relevance, group comparisons revealed pronounced increases in frequency and severity in items of anxiety, sleep disturbances, agitation & stereotypical behavior, aggression, apathy, depressive symptoms, and eating/drinking behavior. The proportion of individuals presenting an increase was highest in DS+AD, intermediate in DS+Q, and lowest in DS. Interestingly, among DS+Q individuals, a substantial proportion already presented increased anxiety, sleep disturbances, apathy, and depressive symptoms, suggesting that these changes occur early in the course of AD. Future efforts should optimize the scale based on current results and clinical experiences, and further study applicability, reliability, and validity. Future application of the scale in daily care may aid caregivers to understand changes, and contribute to timely interventions and adaptation of caregiving.

Behavioral Variant Frontotemporal Dementia Performance on a Range of Saccadic Tasks. - Douglass, Amanda; Walterfang, Mark; Velakoulis, Dennis; Abel, Larry (J Alzheimers Dis, 2018)
BACKGROUND: Saccadic paradigms display changes across a number of degenerative conditions reflecting changes in the oculomotor pathway which in some conditions have been linked to disease presentation. OBJECTIVE: To examine a novel range of saccadic paradigms in behavioral variant frontotemporal dementia (bvFTD). METHODS: Prosaccade, predictive, self-paced, memory-guided, and anti-saccade tasks were examined in bvFTD patients and controls. RESULTS: A significant increase in latency for the bvFTD group was seen in all tasks. Self-paced saccades are reduced in number, memory-guided saccades display an increase in errors. Predictive saccades show an increased latency that does not remain when prosaccade latency changes are accounted for. While changes were seen across a range of paradigms, no individual task completely separated bvFTD from control participants. CONCLUSION: bvFTD patients as a group display a number of changes on saccadic testing which may reflect the frontal lobe changes seen in this condition.

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Bioactive Food Abates Metabolic and Synaptic Alterations by Modulation of Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Syeda, Tauqeerunnisa; Sanchez-Tapia, Mónica; Pinedo-Vargas, Laura; Granados, Omar; Cuervo-Zanatta, Daniel; Rojas-Santiago, Eleazar; Díaz-Cintra, Sof A; Torres, Nimbe; Perez-Cruz, Claudia (J Alzheimers Dis, 2018)
Recent investigations have demonstrated an important role of gut microbiota (GM) in the pathogenesis of Alzheimer's disease (AD). GM modulates a host's health and disease by production of several substances, including lipopolysaccharides (LPS) and short-chain fatty acids (SCFAs), among others. Diet can modify the composition and diversity of GM, and ingestion of a healthy diet has been suggested to lower the risk to develop AD. We have previously shown that bioactive food (BF) ingestion can abate neuroinflammation and oxidative stress and improve cognition in obese rats, effects associated with GM composition. Therefore, BF can impact the gut-brain axis and improved behavior. In this study, we aim to explore if inclusion of BF in the diet may impact central pathological markers of AD by modulation of the GM. Triple transgenic 3xTg-AD (TG) female mice were fed a combination of dried nopal, soy, chia oil, and turmeric for 7 months. We found that BF ingestion improved cognition and reduced Aβ aggregates and tau hyperphosphorylation. In addition, BF decreased MDA levels, astrocyte and microglial activation, PSD-95, synaptophysin, GluR1 and ARC protein levels in TG mice. Furthermore, TG mice fed BF showed increased levels of pGSK-3β. GM analysis revealed that pro-inflammatory bacteria were more abundant in TG mice compared to wild-type, while BF ingestion was able to restore the GM's composition, LPS, and propionate levels to control values. Therefore, the neuroprotective effects of BF may be mediated, in part, by modulation of GM and the release of neurotoxic substances that alter brain function.

Biological, Neuroimaging, and Neurophysiological Markers in Frontotemporal Dementia: Three Faces of the Same Coin. - Borroni, Barbara; Benussi, Alberto; Premi, Enrico; Alberici, Antonella; Marcello, Elena; Gardoni, Fabrizio; Di Luca, Monica; Padovani, Alessandro (J Alzheimers Dis, 2018)
Frontotemporal dementia (FTD) is a heterogeneous clinical, genetic, and neuropathological disorder. Clinical diagnosis and prediction of neuropathological substrates are hampered by heterogeneous pictures. Diagnostic markers are key in clinical trials to differentiate FTD from other neurodegenerative dementias. In the same view, identifying the neuropathological hallmarks of the disease is key in light of future disease-modifying treatments. The aim of the present review is to unravel the progress in biomarker discovery, discussing the potential applications of available biological, imaging, and neurophysiological markers.

Blood Inflammatory Mediators and Cognitive Decline in Alzheimer's Disease: A Two Years Longitudinal Study. - Julian, Adrien; Rioux-Bilan, Agnès; Ragot, Stéphanie; Krolak-Salmon, Pierre; Berrut, Gilles; Dantoine, Thierry; Hommet, Caroline; Hanon, Olivier; Page, Guylène; Paccalin, Marc (J Alzheimers Dis, 2018)
Peripheral inflammatory processes are involved in Alzheimer's disease (AD). We aimed to determine whether plasma inflammatory mediator levels at diagnosis are associated with cognitive decline through a 2-year follow-up in AD patients. Patients (n = 109, mean age 79.44 (6.82) years) were included at diagnosis with MMSE scores between 16 and 25, with C-reactive protein <10 mg/L, and without any acute or chronic inflammation status. Plasma IL-1β, IL-6, TNF-α, and CCL5 were measured using Luminex X-MAP technology at baseline, and after one year and two years of follow-up. The mean values of IL-1β, IL-6, TNF-α, and CCL5 at diagnosis were 0.3, 1.94, 6.57, and 69,615.81 pg/mL, respectively. Mean cognitive decline in MMSE was 3.35 points. No correlation between plasmatic value of IL-1β, IL-6, TNF-α, or CCL5 at diagnosis and cognitive decline during the two years of follow-up was found. Cognitive decline in AD does not appear to be predictable by the tested inflammatory mediators.

A Blood Test for Alzheimer's Disease: Progress, Challenges, and Recommendations. - Kiddle, Steven J; Voyle, Nicola; Dobson, Richard J B (J Alzheimers Dis, 2018)
Ever since the discovery of APOEɛ4 around 25 years ago, researchers have been excited about the potential of a blood test for Alzheimer's disease (AD). Since then researchers have looked for genetic, protein, metabolite, and/or gene expression markers of AD and related phenotypes. However, no blood test for AD is yet being used in the clinical setting. We first review the trends and challenges in AD blood biomarker research, before giving our personal recommendations to help researchers overcome these challenges. While some degree of consistency and replication has been seen across independent studies, several high-profile studies have seemingly failed to replicate. Partly due to academic incentives, there is a reluctance in the field to report predictive ability, to publish negative findings, and to independently replicate the work of others. If this can be addressed, then we will know sooner whether a blood test for AD or related phenotypes with clinical utility can be developed.

Brazilian Green Propolis Prevents Cognitive Decline into Mild Cognitive Impairment in Elderly People Living at High Altitude. - Zhu, Aiqin; Wu, Zhou; Zhong, Xin; Ni, Junjun; Li, Yinglan; Meng, Jie; Du, Can; Zhao, Xue; Nakanishi, Hiroshi; Wu, Shizheng (J Alzheimers Dis, 2018)
BACKGROUND: Systemic inflammation is known as a risk factor of cognitive decline. OBJECTIVE: To investigate the effects of propolis on cognitive decline and systemic inflammation in elderly people living at high altitude. METHODS: Sixty participants (average 72.8 years) living at altitude (2,260 meters) were randomized to receive propolis (0.83 g, n = 30) or placebo (n = 30) for 24 months. Cognitive outcomes were assessed using MMSE and serum cytokine levels were measured for 24 months in a double-blind study. RESULTS: MMSE scores were 26.17 at baseline and 23.87 at 24 months in placebo group. Compared to placebo group, improvements of MMSE scores were significant in propolis-treated subjects (p = 0.007) with a response emerging over time (time points×group interaction, p = 0.016). In addition, the serum IL-1β and IL-6 levels were significantly different across treatments (p < 0.0001) showing upward and downward trends in placebo- and propolis-treated subjects, respectively (p < 0.0001). Serum levels of TNF-α were not significantly different across treatment (p = 0.0528) but with a response emerging over time (time points×group interaction, p = 0.016). In contrast, serum levels of TGFβ1 were significantly different across treatments (p < 0.0001) showing downward and upward trends in placebo- and propolis-treated subjects, respectively. Serum levels of IL-10 were significant for the effect of groups (p = 0.0411). Furthermore, MMSE scores correlated with the decrease in IL-1β and the increase in TGFβ1 in serum. CONCLUSION: Elderly people living at high altitude developed to MCI in 24 months with exacerbation of systemic inflammation. Ingestion of propolis (>12 months) protected against cognitive decline after systemic inflammation was reduced.

Call for a Uniform Strategy of Collecting Alzheimer's Disease Costs: A Review and Meta-Analysis. - Maresova, Petra; Dolejš, Josef; Kuca, Kamil (J Alzheimers Dis, 2018)
BACKGROUND: There is now a general attempt in developed countries to implement strategic plans to fight against Alzheimer's disease and other dementia disorders. Among others, attention is paid to the issues of registers and calculations of economic burden. Currently available calculations of costs are difficult to compare. The problem is a different breakdown of cost categories and non-unified monitoring of cost types. OBJECTIVE: The aim of this paper is to note the problem of poor availability and inconsistencies in cost monitoring. Furthermore, the intersection of cost items that are comparable and consistently monitored in expert studies are specified. METHODS: The Web of Science, Elsevier Science Direct, PubMed, and Scopus databases are used in a systematic review. Two independent reviewers screened the identified records and selected relevant articles published in the period from 2010 to 2016. A meta-analysis of costs is performed in four categories related to patients suffering from Alzheimer's disease. RESULTS: The resulting estimation of total costs per patient per month through meta-analysis is € 3,896, with 95% CI [2078, 5713]. The highest costs arise from informal care following non-medical and medical care. CONCLUSION: The results confirm assumption that inconsistencies in cost monitoring of the treatment and care of people with dementia exists in Europe. Homogeneity could be assumed only in the medical costs of severe patients. Heterogeneity is assumed in non-medical costs, informal costs. Cost items should be defined and collected more precisely for future more precise monitoring of the economic burden.

Can 11C-PiB-PET Relative Delivery R1 or 11C-PiB-PET Perfusion Replace 18F-FDG-PET in the Assessment of Brain Neurodegeneration? - Oliveira, Francisco P M; Moreira, Ana Paula; de Mendonça, Alexandre; Verdelho, Ana; Xavier, Carolina; Barroca, Dalila; Rio, Joana; Cardoso, Eva; Cruz, Ângela; Abrunhosa, Antero; Castelo-Branco, Miguel (J Alzheimers Dis, 2018)
BACKGROUND: Pittsburgh Compound B (PiB) positron emission tomography (PET) is used to visualize in vivo amyloid plaques in the brain. Frequently the PiB examinations are complemented with a fluorodeoxyglucose (FDG) PET scan to further assess neurodegeneration. OBJECTIVE: Our goal is to identify alternative correlates of FDG images by assessing which kinetic methods originate PiB derived relative delivery ratio (R1) images that can be correlated with the FDG images, and to compare them with PiB perfusion (pPiB) images obtained from the early-phase of PiB acquisition. METHODS: We selected 52 patients with cognitive impairment who underwent a dynamic PiB and FDG acquisitions. To compute the R1 images, two simplified reference tissue models (SRTM and SRTM2) and two multi-linear reference tissue models (MRTM and MRTM2) were used. The pPiB images were obtained in two different time intervals. RESULTS: All six types of images were of good quality and highly correlated with the FDG images (mean voxelwise within-subjects r > 0.92). The higher correlation was found for FDG-R1(MRTM). Regarding the voxelwise regional correlation, the higher mean all brain correlations was r = 0.825 for FDG-R1(MRTM) and statistically significant in the whole brain analysis. CONCLUSION: All R1 and pPiB images here tested have potential to assess the metabolic impact of neurodegeneration almost as reliably as the FDG images. However, this is not enough to validate these images for a single-subject analysis compared with the FDG image, and thus they cannot yet be used clinically to replace the FDG image before such evaluation.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Caregiving and Caregiver Burden in Dementia Home Care: Results from the Prospective Dementia Registry (PRODEM) of the Austrian Alzheimer Society. - Ransmayr, Gerhard; Hermann, Philipp; Sallinger, Katharina; Benke, Thomas; Seiler, Stephan; Dal-Bianco, Peter; Marksteiner, Josef; Defrancesco, Michaela; Sanin, Günter; Struhal, Walter; Guger, Michael; Vosko, Milan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Comprehensive studies on caregiver burden (CB) of persons caring for dementia patients differ methodologically and show variable results. OBJECTIVE: Analysis of known and hypothesized factors of CB in home care of dementia patients. METHODS: Multicenter longitudinal study comprising 585 persons caring mostly for Alzheimer's disease patients (age median 77.25 years, Mini-Mental State Examination raw score median 23) using the Zarit Caregiver Burden Interview (CBI). Known patient-related determinants of CB were studied, such as dementia severity (Clinical Dementia Rating, CDR), neuropsychological deficits (CERAD-Plus), neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI), disability (Disability Assessment for Dementia, DAD), dependency (Dependency Scale, DS), and moreover, unclarified potential factors (age, sex, education of patients; age, sex, occupational status of the caregivers; family relationship). Psychological and somatic effects of CB were analyzed (factor analysis). RESULTS: Caregiver age was median 61. Female caregivers prevailed (67.8%). Median CBI sum score (CBIss) was 16 at baseline. After two years, CBIss was 22 and 37% of the caregivers reported mild to moderate (CBIss 21-40), 16.8% moderate to severe or severe (≥41), and 46.2% absent to little CB (CBIss ≤ 20). CB correlated positively with NPI, CDR, DS scores, disability (DAD), years of education of the patients, and proximity of patient and caregiver sex (female), and negatively with caregiver age. Caregivers reported restrictions of time, health problems, and negative emotions. CONCLUSION: The findings are applicable to identify persons at risk for substantial CB and its consequences. There is demand for personal, psychological, and medical support of caregivers and increasing male participation.

Cerebrospinal Fluid Biomarkers are Differentially Related to Structural and Functional Changes in Dementia of the Alzheimer's Type. - Malpas, Charles B; Saling, Michael M; Velakoulis, Dennis; Desmond, Patricia; Hicks, Rodney J; Zetterberg, Henrik; Blennow, Kaj; O'Brien, Terence J (J Alzheimers Dis, 2018)
The two cardinal pathologies of Alzheimer's disease (AD) develop according to distinct anatomical trajectories. Cerebral tau-related pathology first accumulates in the mesial temporal region, while amyloid-related pathology first appears in neocortex. The eventual distributions of these pathologies reflect their anatomical origins. An implication is that the cardinal pathologies might exert preferential effects on the structurofunctional brain changes observed in AD. We investigated this hypothesis in 39 patients with dementia of the Alzheimer's type. Interrelationships were analyzed between cerebrospinal fluid biomarkers of the cardinal pathologies, volumetric brain changes using magnetic resonance imaging, and brain metabolism using [18F]-FDG-PET. Amyloid-related pathology was preferentially associated with structurofunctional changes in the precuneus and lateral temporal regions. Tau-related pathology was not associated with changes in these regions. These findings support the hypothesis that tau- and amyloid-pathology exert differential effects on structurofunctional changes in the AD brain. These findings have implications for future therapeutic trials and hint at a more complex relationship between the cardinal pathologies and disruption of brain networks.

Cerebrospinal Fluid Levels of Angiotensin-Converting Enzyme Are Associated with Amyloid-β42 Burden in Alzheimer's Disease. - Rocha, Natalia P; Toledo, Andre; Corgosinho, Laiane T S; de Souza, Leonardo C; Guimarães, Henrique C; Resende, Elisa P F; Braz, Nayara F T; Gomes, Karina B; Simoes E Silva, Ana C; Caramelli, Paulo; Teixeira, Antônio L (J Alzheimers Dis, 2018)
This study was designed to determine whether the levels of renin-angiotensin system (RAS) components are associated with Alzheimer's disease (AD) pathology. Cerebrospinal fluid levels of Angiotensin (Ang) II, Ang-(1-7), angiotensin-converting enzyme (ACE), ACE2, Amyloid-β (Aβ)40, Aβ42, total tau (hTau), and phospho-tau (pTau) were measured in 18 patients with AD and 10 controls. Patients with AD presented decreased levels of ACE when compared with controls. We found a significant positive correlation between ACE and Aβ42 levels among patients. Our results strengthen the hypothesis that ACE is associated with Aβ pathology in AD.

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Cerebrovascular Disease and Neurodegeneration in Alzheimer's Disease with and without a Strong Family History: A Pilot Magnetic Resonance Imaging Study in Dominican Republic. - Piriz, Angel; Reyes, Dolly; Narkhede, Atul; Guzman, Vanessa A; Viqar, Fawad; Meier, Irene B; Budge, Mariana; Mena, Pedro; Dashnaw, Stephen; Lee, Joseph; Reitz, Christiane; Gutierrez, Jose; et al. (J Alzheimers Dis, 2018)
The incidence and prevalence of Alzheimer's disease (AD) dementia are higher among Caribbean Hispanics than among non-Hispanic Whites. The causes of this health disparity remain elusive, partially because of the relative limited capacity for biomedical research in the developing countries that comprise Caribbean Latin America. To begin to address this issue, we were awarded a Development Research Award from the US NIH and Fogarty International Center in order to establish the local capacity to integrate magnetic resonance imaging (MRI) into studies of cognitive aging and dementia in Dominican Republic, establish collaborations with Dominican investigators, and conduct a pilot study on the role of cerebrovascular markers in the clinical expression of AD. Ninety older adult participants with and without AD dementia and with and without a strong family history of AD dementia received MRI scans and clinical evaluation. We quantified markers of cerebrovascular disease (white matter hyperintensities [WMH], presence of infarct, and presence of microbleed) and neurodegeneration (entorhinal cortex volume) and compared them across groups. Patients with AD dementia had smaller entorhinal cortex and greater WMH volumes compared with controls, regardless of family history status. This study provides evidence for the capacity to conduct MRI studies of cognitive aging and dementia in Dominican Republic. The results are consistent with the hypothesis that small vessel cerebrovascular disease represents a core feature of AD dementia, as affected participants had elevated WMH volumes irrespective of family history status.

Change in Fitness and the Relation to Change in Cognition and Neuropsychiatric Symptoms After Aerobic Exercise in Patients with Mild Alzheimer's Disease. - Sobol, Nanna A; Dall, Christian Have; Høgh, Peter; Hoffmann, Kristine; Frederiksen, Kristian Steen; Vogel, Asmus; Siersma, Volkert; Waldemar, Gunhild; Hasselbalch, Steen G; Beyer, Nina (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity has the potential to improve physical function in patients with Alzheimer's disease (AD) and may contribute to modify disease processes and cognitive function. OBJECTIVE: The aim of this study was to investigate 1) the effect of moderate-high-intensity aerobic exercise on cardiorespiratory fitness, i.e., peak oxygen uptake (VO2peak) determined by direct breath-by-breath cardiopulmonary exercise test, and 2) the association between changes in VO2peak and changes in cognition and neuropsychiatric symptoms in patients with mild AD. METHODS: The study is based on secondary outcome analyses from the large single-blinded multi-center study ADEX (Preserving Cognition, Quality of Life, Physical Health and Functional Ability in Alzheimer's Disease: The Effect of Physical Exercise). A preselected sub-group of 55 participants (age 52-83 years), 29 from the intervention group (IG) and 26 from the control group (CG), was included. IG performed 16 weeks of supervised moderate-to-high intensity aerobic exercise. Assessments of VO2peak, mental speed and attention (Symbol Digit Modalities Test, SDMT), and neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI) were performed at baseline and at 16 weeks. RESULT: VO2peak increased 13% in the IG and a between-group difference in mean change (3.92 ml/kg/min, 95% CI 6.34-1.51, p = 0.003) was present in favor of the IG. Combined data from IG and CG showed positive associations between changes in VO2peak and changes in NPI (Rho = - 0.41, p = 0.042) and changes in SDMT (Rho = 0.36, p = 0.010), respectively. CONCLUSION: Aerobic exercise improves VO2peak in community-dwelling patients with mild AD. Furthermore, changes in VO2peak appear to be associated to changes in cognition and neuropsychiatric symptoms.

Chronic Lithium Treatment Increases Telomere Length in Parietal Cortex and Hippocampus of Triple-Transgenic Alzheimer's Disease Mice. - Cardillo, Giancarlo de Mattos; De-Paula, Vanessa de Jesus Rodrigues; Ikenaga, Eliza Hiromi; Costa, Luciana Rodrigues; Catanozi, Sergio; Schaeffer, Evelin Lisete; Gattaz, Wagner Farid; Kerr, Daniel Shikanai; Forlenza, Orestes Vicente (J Alzheimers Dis, 2018)
Telomere length (TL) is a biomarker of cell aging, and its shortening has been linked to several age-related diseases. In Alzheimer's disease (AD), telomere shortening has been associated with neuroinflammation and oxidative stress. The majority of studies on TL in AD were based on leucocyte DNA, with little information about its status in the central nervous system. In addition to other neuroprotective effects, lithium has been implicated in the maintenance of TL. The present study aims to determine the effect of chronic lithium treatment on TL in different regions of the mouse brain, using a triple-transgenic mouse model (3xTg-AD). Eighteen transgenic and 22 wild-type (Wt) male mice were treated for eight months with chow containing 1.0 g (Li1) or 2.0 g (Li2) of lithium carbonate/kg, or standard chow (Li0). DNA was extracted from parietal cortex, hippocampus and olfactory epithelium and TL was quantified by real-time PCR. Chronic lithium treatment was associated with longer telomeres in the hippocampus (Li2, p = 0.0159) and in the parietal cortex (Li1, p = 0.0375) of 3xTg-AD compared to Wt. Our findings suggest that chronic lithium treatment does affect telomere maintenance, but the magnitude and nature of this effect depend on the working concentrations of lithium and characteristics of the tissue. This effect was observed when comparing 3xTg-AD with Wt mice, suggesting that the presence of AD pathology was required for the lithium modulation of TL.

Circulating miR-127-3p as a Potential Biomarker for Differential Diagnosis in Frontotemporal Dementia. - Piscopo, Paola; Grasso, Margherita; Puopolo, Maria; D'Acunto, Emanuela; Talarico, Giuseppina; Crestini, Alessio; Gasparini, Marina; Campopiano, Rosa; Gambardella, Stefano; Castellano, Anna Elisa; Bruno, Giuseppe; Denti, Michela A; et al. (J Alzheimers Dis, 2018)
Given the heterogeneous nature of frontotemporal dementia (FTD), sensitive biomarkers are greatly needed for the accurate diagnosis of this neurodegenerative disorder. Circulating miRNAs have been reported as promising biomarkers for neurodegenerative disorders and processes affecting the central nervous system, especially in aging. The objective of the study was to evaluate if some circulating miRNAs linked with apoptosis (miR-29b-3p, miR-34a-5p, miR-16-5p, miR-17-5p, miR-107, miR-19b-3p, let-7b-5p, miR-26b-5p, and 127-3p) were able to distinguish between FTD patients and healthy controls. For this study, we enrolled 127 subjects, including 54 patients with FTD, 20 patients with Alzheimer's disease (AD), and 53 healthy controls. The qRT-PCR analysis showed a downregulation of miR-127-3p in FTD compared to controls, while the levels of other miRNAs remained unchanged. Then, miR-127-3p expression was also analyzed in AD patients, finding a different expression between two patient groups. A receiver operating characteristic curve was then created for miR-127-3p to discriminate FTD versus AD (AUC: 0.8986), and versus healthy controls (AUC: 0.8057). In conclusion, miR-127-3p could help to diagnose FTD and to distinguish it from AD.

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Clinical Evaluation of Amyloid-Related Imaging Abnormalities in Bapineuzumab Phase III Studies. - Brashear, H Robert; Ketter, Nzeera; Bogert, Jennifer; Di, Jianing; Salloway, Stephen P; Sperling, Reisa (J Alzheimers Dis, 2018)
BACKGROUND: Amyloid-related imaging abnormalities with effusion or edema (ARIA-E) reported in patients with mild-to-moderate Alzheimer's disease in bapineuzumab phase III studies. OBJECTIVES: Assess symptoms, clinical severity, and ARIA-E outcomes, and to evaluate effects on cognition and function. METHODS: A centralized systematic sequential locked procedure and scoring system for assessment of magnetic resonance imaging scans in 1,331 APOE ɛ4 noncarriers and 1,121 carriers was conducted by experienced and trained pairs of neuroradiologists. RESULTS: Treatment-emergent ARIA-E occurred in 15.8% of bapineuzumab and 0.8% placebo-treated patients. In all treated APOE ɛ4 noncarriers, the percentage of patients with ARIA-E was 5.6%, 13.4%, and 19.9% in the 0.5, 1.0, and 2.0 mg/kg groups respectively, and the incidence of symptomatic ARIA-E was 1.5%, 1.5%, and 7.8%, respectively. In carriers, ARIA-E occurred in 21.2% in the 0.5 mg/kg group, and symptomatic ARIA-E occurred in 2.4%. The clinical severity of ARIA-E in those patients in whom it was detected during the study was mild in 57.1%, 61.3%, and 50.0% of cases in 0.5, 1.0, and 2.0 mg/kg noncarriers respectively, and in 73.8% of cases in 0.5 mg/kg carriers. Vascular risk factors did not appear to increase susceptibility to ARIA-E. Rate of decline in cognition and function measured by changes in ADAS-Cog/11 and DAD total scores did not meaningfully differ in patients with ARIA-E versus those without ARIA-E. Extent of cognitive decline was similar over all visit intervals. CONCLUSIONS: Overall, ARIA-E was mild and asymptomatic. ARIA-E did not demonstrate clinically meaningful acute or chronic impact on cognition or function.Registration: NCT00574132 (Bapineuzumab-301), NCT00575055 (Bapineuzumab-302).

A Clinically-Translatable Machine Learning Algorithm for the Prediction of Alzheimer's Disease Conversion in Individuals with Mild and Premild Cognitive Impairment. - Grassi, Massimiliano; Perna, Giampaolo; Caldirola, Daniela; Schruers, Koen; Duara, Ranjan; Loewenstein, David A (J Alzheimers Dis, 2018)
BACKGROUND: Available therapies for Alzheimer's disease (AD) can only alleviate and delay the advance of symptoms, with the greatest impact eventually achieved when provided at an early stage. Thus, early identification of which subjects at high risk, e.g., with MCI, will later develop AD is of key importance. Currently available machine learning algorithms achieve only limited predictive accuracy or they are based on expensive and hard-to-collect information. OBJECTIVE: The current study aims to develop an algorithm for a 3-year prediction of conversion to AD in MCI and PreMCI subjects based only on non-invasively and effectively collectable predictors. METHODS: A dataset of 123 MCI/PreMCI subjects was used to train different machine learning techniques. Baseline information regarding sociodemographic characteristics, clinical and neuropsychological test scores, cardiovascular risk indexes, and a visual rating scale for brain atrophy was used to extract 36 predictors. Leave-pair-out-cross-validation was employed as validation strategy and a recursive feature elimination procedure was applied to identify a relevant subset of predictors. RESULTS: 16 predictors were selected from all domains excluding sociodemographic information. The best model resulted a support vector machine with radial-basis function kernel (whole sample: AUC = 0.962, best balanced accuracy = 0.913; MCI sub-group alone: AUC = 0.914, best balanced accuracy = 0.874). CONCLUSIONS: Our algorithm shows very high cross-validated performances that outperform the vast majority of the currently available algorithms, and all those which use only non-invasive and effectively assessable predictors. Further testing and optimization in independent samples will warrant its application in both clinical practice and clinical trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Atrophy; Brain; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Machine Learning; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Regression Analysis; Sensitivity and Specificity; Support Vector Machine

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

A Clinicopathological Investigation of White Matter Hyperintensities and Alzheimer's Disease Neuropathology. - Alosco, Michael L; Sugarman, Michael A; Besser, Lilah M; Tripodis, Yorghos; Martin, Brett; Palmisano, Joseph N; Kowall, Neil W; Au, Rhoda; Mez, Jesse; DeCarli, Charles; Stein, Thor D; McKee, Ann C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMH) on magnetic resonance imaging (MRI) have been postulated to be a core feature of Alzheimer's disease. Clinicopathological studies are needed to elucidate and confirm this possibility. OBJECTIVE: This study examined: 1) the association between antemortem WMH and autopsy-confirmed Alzheimer's disease neuropathology (ADNP), 2) the relationship between WMH and dementia in participants with ADNP, and 3) the relationships among cerebrovascular disease, WMH, and ADNP. METHODS: The sample included 82 participants from the National Alzheimer's Coordinating Center's Data Sets who had quantitated volume of WMH from antemortem FLAIR MRI and available neuropathological data. The Clinical Dementia Rating (CDR) scale (from MRI visit) operationalized dementia status. ADNP+ was defined by moderate to frequent neuritic plaques and Braak stage III-VI at autopsy. Cerebrovascular disease neuropathology included infarcts or lacunes, microinfarcts, arteriolosclerosis, atherosclerosis, and cerebral amyloid angiopathy. RESULTS: 60/82 participants were ADNP+. Greater volume of WMH predicted increased odds for ADNP (p = 0.037). In ADNP+ participants, greater WMH corresponded with increased odds for dementia (CDR≥1; p = 0.038). WMH predicted cerebral amyloid angiopathy, microinfarcts, infarcts, and lacunes (ps < 0.04). ADNP+ participants were more likely to have moderate-severe arteriolosclerosis and cerebral amyloid angiopathy compared to ADNP-participants (ps < 0.04). CONCLUSIONS: This study found a direct association between total volume of WMH and increased odds for having ADNP. In patients with Alzheimer's disease, FLAIR MRI WMH may be able to provide key insight into disease severity and progression. The association between WMH and ADNP may be explained by underlying cerebrovascular disease.

Cognitive Decline in Preclinical Alzheimer's Disease: Amyloid-Beta versus Tauopathy. - Huber, Colin M; Yee, Connor; May, Taylor; Dhanala, Apoorva; Mitchell, Cassie S (J Alzheimers Dis, 2018)
We perform a large-scale meta-analysis of 51 peer-reviewed 3xTg-AD mouse publications to compare Alzheimer's disease (AD) quantitative clinical outcome measures, including amyloid-β (Aβ), total tau, and phosphorylated tau (pTau), with cognitive performance in Morris water maze (MWM) and Novel Object Recognition (NOR). "High" levels of Aβ (Aβ40, Aβ42) showed significant but weak trends with cognitive decline (MWM: slope = 0.336, R2 = 0.149, n = 259, p < 0.001; NOR: slope = 0.156, R2 = 0.064, n = 116, p < 0.05); only soluble Aβ or directly measured Aβ meaningfully contribute. Tau expression in 3xTg-AD mice was within 10-20% of wild type and not associated with cognitive decline. In contrast, increased pTau is directly and significantly correlated with cognitive decline in MWM (slope = 0.408, R2 = 0.275, n = 371, p < < 0.01) and NOR (slope = 0.319, R2 = 0.176, n = 113, p < 0.05). While a variety of pTau epitopes (AT8, AT270, AT180, PHF-1) were examined, AT8 correlated most strongly with cognition (slope = 0.586, R2 = 0.521, n = 185, p < < 0.001). Multiple linear regression confirmed pTau is a stronger predictor of MWM performance than Aβ. Despite pTau's lower physical concentration than Aβ, pTau levels more directly and quantitatively correlate with 3xTg-AD cognitive decline. pTau's contribution to neurofibrillary tangles well after Aβ levels plateau makes pTau a viable treatment target even in late-stage clinical AD. Principal component analysis, which included hyperphosphorylation induced by kinases (pGSK3β, GSK3β, CDK5), identified phosphorylated ser9 GSK3β as the primary contributor to MWM variance. In summary, meta-analysis of cognitive decline in preclinical AD finds tauopathy more impactful than Aβ. Nonetheless, complex AD interactions dictate successful therapeutics harness synergy between Aβ and pTau, possibly through the GSK3 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Disease Models, Animal; Maze Learning; Mice; Reaction Time; Recognition (Psychology); tau Proteins

Cognitive Training Improves Ratio Processing and Decision Making in Patients with Mild Cognitive Impairment. - Burgio, Francesca; Delazer, Margarete; Meneghello, Francesca; Pertl, Marie-Theres; Semenza, Carlo; Zamarian, Laura (J Alzheimers Dis, 2018)
BACKGROUND: Patients with mild cognitive impairment (MCI) show lower decision making and ratio processing abilities as compared to healthy peers. OBJECTIVE: To evaluate whether cognitive training on number processing and/or executive functions improves performance on ratio processing and decision making under risk. METHODS: In a controlled cross-over study, patients with MCI (n = 23; mean MMSE 26.48, SD 2.43) underwent a week of numerical training followed by a week of executive-functions training (subgroup A), or vice versa (subgroup B). Before training (T1), patients performed experimental tasks of decision making (Game of Dice Task, GDT; Probability-Associated Gambling task, PAG-60 task) and of ratio processing as well as a neuropsychological background assessment. Experimental tasks were also administered after the first (T2) and the second (T3) training week. RESULTS: The numerical training and the training of executive functions had a differential effect on experimental tasks of ratio processing. Only the numerical training proved to be effective. The effects of the two training types on decision making under risk were less clear-cut. While no changes over time were observed in the GDT, performance on the PAG-60 task improved in both training subgroups. These improvements were apparent in one subgroup after a period of executive-functions training, in the other subgroup after both training weeks. That means, improvements are not attributable to one specific training type. CONCLUSION: Patients with MCI can profit from a cognitive training on number processing and executive functions. Improvements are reflected in higher ratio processing abilities and more advantageous decisions after training. These results are consistent with assumptions of current cognitive models.

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Combined Socio-Behavioral Evaluation Improves the Differential Diagnosis Between the Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: In Search of Neuropsychological Markers. - Dodich, Alessandra; Cerami, Chiara; Cappa, Stefano F; Marcone, Alessandra; Golzi, Valeria; Zamboni, Michele; Giusti, Maria Cristina; Iannaccone, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Current diagnostic criteria for behavioral variant of frontotemporal dementia (bvFTD) and typical Alzheimer's disease (AD) include a differential pattern of neuropsychological impairments (episodic memory deficit in typical AD and dysexecutive syndrome in bvFTD). There is, however, large evidence of a frequent overlap in neuropsychological features, making the differential diagnosis extremely difficult. OBJECTIVES: In this retrospective study, we evaluated the diagnostic value of different cognitive and neurobehavioral markers in bvFTD and AD patient groups. METHODS: We included 95 dementia patients with a clinical and biomarker evidence of bvFTD (n = 48) or typical AD (n = 47) pathology. A clinical 2-year follow-up confirmed clinical classification. Performances at basic cognitive tasks (memory, executive functions, visuo-spatial, language) as well as social cognition skills and neurobehavioral profiles have been recorded. A stepwise logistic regression model compared the neuropsychological profiles between groups and assessed the accuracy of cognitive and neurobehavioral markers in discriminating bvFTD from AD. RESULTS: Statistical comparison between patient groups proved social cognition and episodic memory impairments as main cognitive signatures of bvFTD and AD neuropsychological profiles, respectively. Only half of bvFTD patients showed attentive/executive deficits, questioning their role as cognitive marker of bvFTD. Notably, the large majority of bvFTD sample (i.e., 70%) poorly performed at delayed recall tasks. Logistic regression analysis identified social cognition performances, Frontal Behavioral Inventory and Mini-Mental State Examination scores as the best combination in distinguishing bvFTD from AD. CONCLUSION: Social cognition tasks and socio-behavioral questionnaires are recommended in clinical settings to improve the accuracy of early diagnosis of bvFTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognition; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Logistic Models; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Retrospective Studies; Social Skills

Comparing the Electronic and Standard Versions of the Montreal Cognitive Assessment in an Outpatient Memory Disorders Clinic: A Validation Study. - Berg, Jody-Lynn; Durant, January; Léger, Gabriel C; Cummings, Jeffrey L; Nasreddine, Ziad; Miller, Justin B (J Alzheimers Dis, 2018)
The Montreal Cognitive Assessment (MoCA) has become widely used as a brief test of cognitive function in patients with neurological disease. More convenient application of the MoCA might increase its use and enhance its utility. An electronic version of the MoCA has recently been developed. To establish validity of the electronic version (eMoCA), discrepancy scores, concordance correlation coefficients (CCC), and root mean squared differences (RMSD) were calculated between each administration method in a sample of 43 new adult patients presenting with primary memory complaints. The CCC was 0.84 and the RMSD was 2.27, with 76% of the sample having a difference score within 2 points. Overall, this study establishes adequate convergent validity between the MoCA and eMoCA among an adult population presenting with memory concerns.

Comparison of Different Hypotheses Regarding the Spread of Alzheimer's Disease Using Markov Random Fields and Multimodal Imaging. - Dyrba, Martin; Grothe, Michel J; Mohammadi, Abdolreza; Binder, Harald; Kirste, Thomas; Teipel, Stefan J (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by a cascade of pathological processes that can be assessed in vivo using different neuroimaging methods. Recent research suggests a systematic sequence of pathogenic events on a global biomarker level, but little is known about the associations and dependencies of distinct lesion patterns on a regional level. Markov random fields are a probabilistic graphical modeling approach that represent the interaction between individual random variables by an undirected graph. We propose the novel application of this approach to study the interregional associations and dependencies between multimodal imaging markers of AD pathology and to compare different hypotheses regarding the spread of the disease. We retrieved multimodal imaging data from 577 subjects enrolled in the Alzheimer's Disease Neuroimaging Initiative. Mean amyloid load (AV45-PET), glucose metabolism (FDG-PET), and gray matter volume (MRI) were calculated for the six principle nodes of the default mode network- a functional network of brain regions that appears to be preferentially targeted by AD. Multimodal Markov random field models were developed for three different hypotheses regarding the spread of the disease: the "intraregional evolution model", the "trans-neuronal spread" hypothesis, and the "wear-and-tear" hypothesis. The model likelihood to reflect the given data was evaluated using tenfold cross-validation with 1,000 repetitions. The most likely graph structure contained the posterior cingulate cortex as main hub region with edges to various other regions, in accordance with the "wear-and-tear" hypothesis of disease vulnerability. Probabilistic graphical models facilitate the analysis of interactions between several variables in a network model and therefore afford great potential to complement traditional multiple regression analyses in multimodal neuroimaging research.

Complexity and Selectivity of γ-Secretase Cleavage on Multiple Substrates: Consequences in Alzheimer's Disease and Cancer. - Medoro, Alessandro; Bartollino, Silvia; Mignogna, Donatella; Passarella, Daniela; Porcile, Carola; Pagano, Aldo; Florio, Tullio; Nizzari, Mario; Guerra, Germano; Di Marco, Roberto; Intrieri, Mariano; Raimo, Gennaro; et al. (J Alzheimers Dis, 2018)
The processing of the amyloid-β protein precursor (AβPP) by β- and γ-secretases is a pivotal event in the genesis of Alzheimer's disease (AD). Besides familial mutations on the AβPP gene, or upon its overexpression, familial forms of AD are often caused by mutations or deletions in presenilin 1 (PSEN1) and 2 (PSEN2) genes: the catalytic components of the proteolytic enzyme γ-secretase (GS). The "amyloid hypothesis", modified over time, states that the aberrant processing of AβPP by GS induces the formation of specific neurotoxic soluble amyloid-β (Aβ) peptides which, in turn, cause neurodegeneration. This theory, however, has recently evidenced significant limitations and, in particular, the following issues are debated: 1) the concept and significance of presenilin's "gain of function" versus "loss of function"; and 2) the presence of several and various GS substrates, which interact with AβPP and may influence Aβ formation. The latter consideration is suggestive: despite the increasing number of GS substrates so far identified, their reciprocal interaction with AβPP itself, even in the AD field, is significantly unexplored. On the other hand, GS is also an important pharmacological target in the cancer field; inhibitors or GS activity are investigated in clinical trials for treating different tumors. Furthermore, the function of AβPP and PSENs in brain development and in neuronal migration is well known. In this review, we focused on a specific subset of GS substrates that directly interact with AβPP and are involved in its proteolysis and signaling, by evaluating their role in neurodegeneration and in cell motility or proliferation, as a possible connection between AD and cancer.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Neoplasms; Presenilin-1

Comprehensive Characterization of the Pyroglutamate Amyloid-β Induced Motor Neurodegenerative Phenotype of TBA2.1 Mice. - Dunkelmann, Tina; Schemmert, Sarah; Honold, Dominik; Teichmann, Kerstin; Butzküven, Elke; Demuth, Hans-Ulrich; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; Willbold, Dieter; Willuweit, Antje (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and is being intensively investigated using a broad variety of animal models. Many of these models express mutant versions of human amyloid-β protein precursor (AβPP) that are associated with amyloid-β protein (Aβ)-induced early onset familial AD. Most of these models, however, do not develop bold neurodegenerative pathology and the respective phenotypes. Nevertheless, this may well be essential for their suitability to identify therapeutically active compounds that have the potential for a curative or at least disease-modifying therapy in humans. In this study, the new transgenic mouse model TBA2.1 was explored in detail to increase knowledge about the neurodegenerative process induced by the presence of pyroglutamate modified human Aβ3-42 (pEAβ3-42). Analysis of the sensorimotor phenotype, motor coordination, Aβ pathology, neurodegeneration, and gliosis revealed formation and progression of severe pathology and phenotypes including massive neuronal loss in homozygous TBA2.1 mice within a few months. In contrast, the start of a slight phenotype was observed only after 21 months in heterozygous mice. These data highlight the role of pEAβ3-42 in the disease development and progression of AD. Based on the findings of this study, homozygous TBA2.1 mice can be utilized to gain deeper understanding in the underlying mechanisms of pEAβ3-42 and might be suitable as an animal model for treatment studies targeting toxic Aβ species, complementary to the well described transgenic AβPP mouse models.

Is Computerized Working Memory Training Effective in Healthy Older Adults? Evidence from a Multi-Site, Randomized Controlled Trial. - Simon, Sharon S; Tusch, Erich S; Feng, Nicole C; Håkansson, Krister; Mohammed, Abdul H; Daffner, Kirk R (J Alzheimers Dis, 2018)
BACKGROUND: Developing effective interventions to attenuate age-related cognitive decline and prevent or delay the onset of dementia are major public health goals. Computerized cognitive training (CCT) has been marketed increasingly to older adults, but its efficacy remains unclear. Working memory (WM), a key determinant of higher order cognitive abilities, is susceptible to age-related decline and a relevant target for CCT in elders. OBJECTIVE: To evaluate the efficacy of CCT focused on WM compared to an active control condition in healthy older adults. METHODS: Eighty-two cognitively normal adults from two sites (USA and Sweden) were randomly assigned to Cogmed Adaptive or Non-Adaptive (active control) CCT groups. Training was performed in participants' homes, five days per week over five weeks. Changes in the performance of the Cogmed trained tasks, and in five neuropsychological tests (Trail Making Test Part A and Part B, Digit Symbol, Controlled Oral Word Association Test and Semantic Fluency) were used as outcome measures. RESULTS: The groups were comparable at baseline. The Adaptive group showed robust gains in the trained tasks, and there was a time-by-group interaction for the Digit Symbol test, with significant improvement only after Adaptive training. In addition, the magnitude of the intervention effect was similar at both sites. CONCLUSION: Home-based CCT Adaptive WM training appears more effective than Non-Adaptive training in older adults from different cultural backgrounds. We present evidence of improvement in trained tasks and on a demanding untrained task dependent upon WM and processing speed. The benefits over the active control group suggest that the Adaptive CCT gains were linked to providing a continuously challenging level of WM difficulty.

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

A Decade of Blood Biomarkers for Alzheimer's Disease Research: An Evolving Field, Improving Study Designs, and the Challenge of Replication. - Shi, Liu; Baird, Alison L; Westwood, Sarah; Hye, Abdul; Dobson, Richard; Thambisetty, Madhav; Lovestone, Simon (J Alzheimers Dis, 2018)
Blood-based biomarkers represent a less invasive and potentially cheaper approach for aiding Alzheimer's disease (AD) detection compared with cerebrospinal fluid and some neuroimaging biomarkers. Acknowledging that many in the field have made great progress, here we review some of the work that our group has pursued to identify and validate blood-based proteomic biomarkers through both case control and AD pathology endophenotype-based approaches. Our focus is primarily to identify a minimally invasive and hopefully cost-effective blood-based biomarker to reduce screen failure in clinical trials where participants have prodromal or even pre-clinical disease. We summarize some of the key findings and approaches taken in these biomarker studies, while addressing the main challenges, including that of limited replication in the field, and discuss opportunities for biomarker development.

Deep Brain Stimulation of the Memory Circuit: Improving Cognition in Alzheimer's Disease. - Posporelis, Sotirios; David, Anthony S; Ashkan, Keyoumars; Shotbolt, Paul (J Alzheimers Dis, 2018)
Deep brain stimulation (DBS) is an effective invasive treatment for a wide range of neurological and psychiatric disorders. Neurosurgically implanted electrodes deliver stimulation of pre-programmed amplitude, frequency, and pulse width within deep brain structures; those settings can be adjusted at a later stage according to individual needs for optimal response. This results in variable effects dependent on the targeted region. An established treatment for movement disorders, the effectiveness of DBS in dementia remains under investigation. Translational studies have uncovered a pro-cognitive effect mediated by changes on cellular as well as network level. Several groups have attempted to examine the benefits of DBS in Alzheimer's disease; differences in inclusion criteria and methodology make generalization of results difficult. This review aims to summarize all completed and ongoing human studies of DBS in Alzheimer's disease. The results are classified by targeted anatomical structure. Future directions, as well as economical and ethical arguments, are explored in the final section.

Deep Brain Stimulation Targeting the Fornix for Mild Alzheimer Dementia (the ADvance Trial): A Two Year Follow-up Including Results of Delayed Activation. - Leoutsakos, Jeannie-Marie S; Yan, Haijuan; Anderson, William S; Asaad, Wael F; Baltuch, Gordon; Burke, Anna; Chakravarty, M Mallar; Drake, Kristen E; Foote, Kelly D; Fosdick, Lisa; Giacobbe, Peter; Mari, Zoltan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Given recent challenges in developing new treatments for Alzheimer dementia (AD), it is vital to explore alternate treatment targets, such as neuromodulation for circuit dysfunction. We previously reported an exploratory Phase IIb double-blind trial of deep brain stimulation targeting the fornix (DBS-f) in mild AD (the ADvance trial). We reported safety but no clinical benefits of DBS-f versus the delayed-on (sham) treatment in 42 participants after one year. However, secondary post hoc analyses of the one-year data suggested a possible DBS-f benefit for participants≥65 years. OBJECTIVE: To examine the long-term safety and clinical effects of sustained and delayed-on DBS-f treatment of mild AD after two years. METHODS: 42 participants underwent implantation of DBS-f electrodes, with half randomized to active DBS-f stimulation (early on) for two years and half to delayed-on (sham) stimulation after 1 year to provide 1 year of active DBS-f stimulation (delayed on). We evaluated safety and clinical outcomes over the two years of the trial. RESULTS: DBS-f had a favorable safety profile with similar rates of adverse events across both trial phases (years 1 and 2) and between treatment arms. There were no differences between treatment arms on any primary clinical outcomes. However, post-hoc age group analyses suggested a possible benefit among older (>65) participants. CONCLUSION: DBS-f was safe. Additional study of mechanisms of action and methods for titrating stimulation parameters will be needed to determine if DBS has potential as an AD treatment. Future efficacy studies should focus on patients over age 65.

Diagnosis of Mild Cognitive Impairment Due to Alzheimer's Disease with Transcranial Magnetic Stimulation. - Padovani, Alessandro; Benussi, Alberto; Cantoni, Valentina; Dell'Era, Valentina; Cotelli, Maria Sofia; Caratozzolo, Salvatore; Turrone, Rosanna; Rozzini, Luca; Alberici, Antonella; Altomare, Daniele; Depari, Alessandro; Flammini, Alessandra; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Considering the increasing evidence that disease-modifying treatments for Alzheimer's disease (AD) must be administered early in the disease course, the development of diagnostic tools capable of accurately identifying AD at early disease stages has become a crucial target. In this view, transcranial magnetic stimulation (TMS) has become an effective tool to discriminate between different forms of neurodegenerative dementia. OBJECTIVE: To determine whether a TMS multi-paradigm approach can be used to correctly identify mild cognitive impairment (MCI) due to AD (AD MCI). METHODS: A sample of 69 subjects with MCI were included and classified as AD MCI or MCI unlikely due to AD (non-AD MCI) based on 1) extensive neurological and neuropsychological evaluation, 2) MRI imaging, and 3) cerebrospinal fluid analysis or/and amyloid PET imaging. A paired-pulse TMS multi-paradigm approach assessing short interval intracortical inhibition-facilitation (SICI-ICF), dependent on GABAergic and glutamatergic intracortical circuits, respectively, and short latency afferent inhibition (SAI), dependent on cholinergic circuits, was performed. RESULTS: We observed a significant impairment of SAI and unimpaired SICI and ICF in AD MCI as compared to non-AD MCI. According to ROC curve analysis, the SICI-ICF / SAI index differentiated AD MCI from non-AD MCI with a specificity of 87.9% and a sensitivity of 94.4%. CONCLUSIONS: The assessment of intracortical connectivity with TMS could aid in the characterization of MCI subtypes, correctly identifying AD pathophysiology. TMS can be proposed as an adjunctive, non-invasive, inexpensive, and time-saving screening tool in MCI differential diagnosis.

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Diaphanous 1 (DIAPH1) is Highly Expressed in the Aged Human Medial Temporal Cortex and Upregulated in Myeloid Cells During Alzheimer's Disease. - Derk, Julia; Bermudez Hernandez, Keria; Rodriguez, Moises; He, Meilun; Koh, Hyunwook; Abedini, Andisheh; Li, Huilin; Fenyö, David; Schmidt, Ann Marie (J Alzheimers Dis, 2018)
BACKGROUND: The receptor for advanced glycation end products (RAGE) is linked to cellular stress and inflammation during Alzheimer's disease (AD). RAGE signals through Diaphanous-1 (DIAPH1); however, the expression of DIAPH1 in the healthy and AD human brain has yet to be methodically addressed. OBJECTIVE: To delineate the cell- and disease-state specific expression of DIAPH1 in the human medial temporal cortex during healthy aging and AD. METHODS: We used semi-quantitative immunohistochemistry in the human medial temporal cortex paired with widefield and confocal microscopy and automated analyses to determine colocalization and relative expression of DIAPH1 with key cell markers and molecules in the brains of subjects with AD versus age-matched controls. RESULTS: We report robust colocalization of DIAPH1 with myeloid cells and increased expression during AD, which strongly correlated to increased neutral lipids and morphology of inflamed myeloid cells. DIAPH1 moderately colocalized with markers of endothelial cells, astrocytes, neurons, and oligodendrocytes. DISCUSSION: Our findings localize DIAPH1 particularly to myeloid cells in the CNS, especially in AD in the locations of lipid droplet accumulation, thereby implicating RAGE-DIAPH1 signaling in dysregulated lipid metabolism and morphological changes of inflamed myeloid cells in this disorder.

Differences in Dementia Beliefs between Non-Demented Public Screeners and In-Home Screeners and Their Potential Impact on Future Dementia Screening Intention: The Nakajima Study. - Yuki-Nozaki, Sohshi; Noguchi-Shinohara, Moeko; Domoto, Chiaki; Ikeda, Yoshihisa; Samuraki, Miharu; Iwasa, Kazuo; Yokogawa, Masami; Asai, Kimiko; Komai, Kiyonobu; Nakamura, Hiroyuki; Yamada, Masahito (J Alzheimers Dis, 2018)
In many cohort studies of dementia, while differences in sociodemographic characters between responders and non-responders of dementia screening have been reported, differences in dementia beliefs have been relatively less known. The aims of this study were to clarify dementia beliefs and to explore potential impacts on an intention to attend a future dementia screening in public screeners and in-home screeners, respectively. We performed a cross-sectional population-based study using a question about an intention to attend a future dementia screening and a questionnaire on dementia beliefs. Subjects were all residents aged 65 years or older in the north area of Nakajima, Japan (n = 385). All subjects were asked to attend a public dementia screening first. An in-home dementia screening was subsequently conducted in subjects with non-responders to a public screening. The questionnaire consisted of four dementia beliefs: "perceived susceptibility," "perceived severity," "perceived barriers," and "perceived benefits." Public screeners significantly expressed an intention to attend a future dementia screening more than in-home screeners (p = 0.002). In in-home screeners, low "perceived severity" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 0.51 (0.32-0.80)]. In both public and in-home screeners, high "perceived benefits" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 2.13 (1.46-3.10); adjusted OR (95% CI) = 2.56 (1.22-5.35), respectively]. It is necessary to reduce "perceived severity" among in-home screeners to increase dementia screening participants.

Different Abnormalities of Cortical Neural Synchronization Mechanisms in Patients with Mild Cognitive Impairment due to Alzheimer's and Chronic Kidney Diseases: An EEG Study. - Lizio, Roberta; Babiloni, Claudio; Del Percio, Claudio; Losurdo, Antonia; Vernò, Lucia; De Tommaso, Marina; Montemurno, Anna; Dalfino, Giuseppe; Cirillo, Pietro; Soricelli, Andrea; Ferri, Raffaele; Noce, Giuseppe; et al. (J Alzheimers Dis, 2018)
This study tested whether resting state alpha rhythms (8-13 Hz) may characterize mild cognitive impairment due to Alzheimer's disease (ADMCI) compared with MCI due to chronic kidney disease (CKDMCI). Clinical and resting state eyes-closed electroencephalographic (rsEEG) rhythms from 40 ADMCI, 29 CKDMCI, and 45 cognitively normal elderly (Nold) subjects were available in a national archive. Age, gender, and education were matched in the three groups, and Mini-Mental State Evaluation (MMSE) score was paired in the ADMCI and CKDMCI groups. Delta (<4 Hz), theta (4-8 Hz), alpha 1 (8-10.5 Hz), alpha 2 (10.5-13 Hz), beta 1 (13-20 Hz), beta 2 (20-30 Hz), and gamma (30-40 Hz) cortical sources were estimated by eLORETA freeware and classified across individuals by area under the receiver operating characteristic curve (AUROCC). Compared with Nold group, posterior alpha 1 source activities were more reduced in ADMCI than CKDMCI group. In contrast, widespread delta source activities were greater in CKDMCI than ADMCI group. These source activities correlated with the MMSE score and correctly classified between Nold and all MCI individuals (AUROCC = 0.8-0.85) and between ADMCI and CKDMCI subjects (AUROCC = 0.75). These results suggest that early AD affects cortical neural synchronization at alpha frequencies underpinning brain arousal and low vigilance in the quiet wakefulness. In contrast, CKD may principally affect cortical neural synchronization at the delta frequencies. Future prospective cross-validation studies will have to test these candidate rsEEG markers for clinical applications and drug discovery.

Different Cognitive Frailty Models and Health- and Cognitive-related Outcomes in Older Age: From Epidemiology to Prevention. - Panza, Francesco; Lozupone, Madia; Solfrizzi, Vincenzo; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; D'Urso, Francesca; Stallone, Roberta; Petruzzi, Massimo; Giannelli, Gianluigi; Quaranta, Nicola; Bellomo, Antonello; et al. (J Alzheimers Dis, 2018)
Frailty, a critical intermediate status of the aging process that is at increased risk for negative health-related events, includes physical, cognitive, and psychosocial domains or phenotypes. Cognitive frailty is a condition recently defined by operationalized criteria describing coexisting physical frailty and mild cognitive impairment (MCI), with two proposed subtypes: potentially reversible cognitive frailty (physical frailty/MCI) and reversible cognitive frailty (physical frailty/pre-MCI subjective cognitive decline). In the present article, we reviewed the framework for the definition, different models, and the current epidemiology of cognitive frailty, also describing neurobiological mechanisms, and exploring the possible prevention of the cognitive frailty progression. Several studies suggested a relevant heterogeneity with prevalence estimates ranging 1.0-22.0% (10.7-22.0% in clinical-based settings and 1.0-4.4% in population-based settings). Cross-sectional and longitudinal population-based studies showed that different cognitive frailty models may be associated with increased risk of functional disability, worsened quality of life, hospitalization, mortality, incidence of dementia, vascular dementia, and neurocognitive disorders. The operationalization of clinical constructs based on cognitive impairment related to physical causes (physical frailty, motor function decline, or other physical factors) appears to be interesting for dementia secondary prevention given the increased risk for progression to dementia of these clinical entities. Multidomain interventions have the potential to be effective in preventing cognitive frailty. In the near future, we need to establish more reliable clinical and research criteria, using different operational definitions for frailty and cognitive impairment, and useful clinical, biological, and imaging markers to implement intervention programs targeted to improve frailty, so preventing also late-life cognitive disorders.

Differential Effect of APOE ɛ4 Status and Elevated Pulse Pressure on Functional Decline in Cognitively Normal Older Adults. - Werhane, Madeleine L; Thomas, Kelsey R; Edmonds, Emily C; Bangen, Katherine J; Tran, My; Clark, Alexandra L; Nation, Daniel A; Gilbert, Paul E; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: The APOE ɛ4 allele and increased vascular risk have both been independently linked to cognitive impairment and dementia. Since few studies have characterized how these risk factors affect everyday functioning, we investigated the relationship between APOE ɛ4 genotype and elevated pulse pressure (PP) on functional change in cognitively normal participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI). METHODS: 738 normally aging participants underwent APOE genotyping, and baseline PP was calculated from blood pressure indices. The Functional Activities Questionnaire (FAQ) was completed by participants' informant at baseline and 6, 12, 24, 36, and 48-month follow-up visits. Multiple linear regression and multilevel modeling were used to examine the effects of PP and APOE ɛ4 genotype on cross-sectional and longitudinal FAQ scores, respectively. RESULTS: Adjusting for demographic and clinical covariates, results showed that both APOE ɛ4 status and elevated PP predicted greater functional difficulty trajectories across four years of follow-up. Interestingly, however, elevated PP was associated with greater functional decline over time in ɛ4 non-carriers versus carriers. CONCLUSION: Results show that, although APOE ɛ4 status is the prominent predictor of functional difficulty for ɛ4 carriers, an effect of arterial stiffening on functional difficulty was observed in non-carriers. Future studies are needed in order to clarify the etiology of the association between PP and different brain aging processes, and further explore its utility as a marker of dementia risk. The present study underscores the importance of targeting modifiable risk factors such as elevated PP to prevent or slow functional decline and pathological brain aging.

Differentiating between Alzheimer's Disease and Vascular Cognitive Impairment: Is the "Memory Versus Executive Function" Contrast Still Relevant? - Andriuta, Daniela; Roussel, Martine; Barbay, Mélanie; Despretz-Wannepain, Sandrine; Godefroy, Olivier (J Alzheimers Dis, 2018)
BACKGROUND: The contrast between memory versus executive function impairments is commonly used to differentiate between neurocognitive disorders (NCDs) due to Alzheimer's disease (AD) and vascular cognitive impairment (VCI). We reconsidered this question because of the current use of AD biomarkers and the recent revision of the criteria for AD, VCI, and dysexecutive syndrome. OBJECTIVE: To establish and compare the neuropsychological profiles in AD (i.e., with positive CSF biomarkers) and in VCI. METHODS: We included 62 patients with mild or major NCDs due to pure AD (with positive CSF biomarker assays), and 174 patients (from the GRECogVASC cohort) with pure VCI. The neuropsychological profiles were compared after stratification for disease severity (mild or major NCD). We defined a memory-executive function index (the mean z score for the third free recall and the delayed free recall in the Free and Cued Selective Reminding Test minus the mean z score for category fluency and the completion time in the Trail Making Test part B) and determined its diagnostic accuracy. RESULTS: Compared with VCI patients, patients with AD had significantly greater memory impairments (p = 0.001). Executive function was impaired to a similar extent in the two groups (p = 0.11). Behavioral executive disorders were more prominent in the AD group (p = 0.001). Although the two groups differed significant with regard to the memory-executive function index (p < 0.001), the latter's diagnostic accuracy was only moderate (sensitivity: 63%, specificity: 87%). CONCLUSION: Although the contrast between memory and executive function impairments was supported at the group level it does not reliably discriminate between AD and VCI at the individual level.

Dipeptidyl-Peptidase Activity of Meprin β Links N-truncation of Aβ with Glutaminyl Cyclase-Catalyzed pGlu-Aβ Formation. - Schlenzig, Dagmar; Cynis, Holger; Hartlage-Rübsamen, Maike; Zeitschel, Ulrike; Menge, Katja; Fothe, Anja; Ramsbeck, Daniel; Spahn, Claudia; Wermann, Michael; Roßner, Steffen; Buchholz, Mirko; Schilling, Stephan; et al. (J Alzheimers Dis, 2018)
The formation of amyloid-β (Aβ) peptides is causally involved in the development of Alzheimer's disease (AD). A significant proportion of deposited Aβ is N-terminally truncated and modified at the N-terminus by a pGlu-residue (pGlu-Aβ). These forms show enhanced neurotoxicity compared to full-length Aβ. Although the truncation may occur by aminopeptidases after formation of Aβ, recently discovered processing pathways of amyloid-β protein precursor (AβPP) by proteases such as meprin β may also be involved. Here, we assessed a role of meprin β in forming Aβ3-40/42, which is the precursor of pGlu-Aβ3-40/42 generated by glutaminyl cyclase (QC). Similar to QC, meprin β mRNA is significantly upregulated in postmortem brain from AD patients. A histochemical analysis supports the presence of meprin β in neurons and astrocytes in the vicinity of pGlu-Aβ containing deposits. Cleavage of AβPP-derived peptides by meprin β in vitro results in peptides Aβ1-x, Aβ2-x, and Aβ3-x. The formation of N-truncated Aβ by meprin β was also corroborated in cell culture. A subset of the generated peptides was converted into pGlu-Aβ3-40 by an addition of glutaminyl cyclase, supporting the preceding formation of Aβ3-40. Further analysis of the meprin β cleavage revealed a yet unknown dipeptidyl-peptidase-like activity specific for the N-terminus of Aβ1-x. Thus, our data suggest that meprin β contributes to the formation of N-truncated Aβ by endopeptidase and exopeptidase activity to generate the substrate for QC-catalyzed pGlu-Aβ formation.

Dissecting the Role of 5-Lipoxygenase in the Homocysteine-Induced Alzheimer's Disease Pathology. - Di Meco, Antonio; Li, Jian-Guo; Praticò, Domenico (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) affects over 40 million patients around the world and poses a huge economic burden on society since no effective therapy is available yet. While the cause(s) for the most common sporadic form of the disease are still obscure, lifestyle and different environmental factors have emerged as modulators of AD susceptibility. Hyperhomocysteinemia (HHCY), a condition of high circulating levels of homocysteine, is an independent but modifiable risk factor for AD. Studies in AD mouse models have linked HHCY with memory impairment, amyloidosis, tau pathology, synaptic dysfunction, and neuroinflammation. However, the exact mechanism by which HHCY affects AD pathogenesis is unclear. The 5-lipoxygenase (5LO) is a protein upregulated in postmortem AD brains and plays a functional role in AD pathogenesis. Recently, in vitro and in vivo studies showed that HHCY effects on amyloid-β and tau pathology, synapse and memory impairments are dependent on the activation of the 5LO enzymatic pathway, since its genetic absence or pharmacological inhibition prevents them. HHCY induces 5LO gene upregulation by lowering the methylation of its promoter, which results in increased translation and transcription of its mRNA. Based on these findings, we propose that epigenetic modification of 5LO represents the missing biological link between HHCY and AD pathogenesis, and for this reason it represents a viable therapeutic target to prevent AD development in individuals bearing this risk factor.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

Distribution of Cerebrospinal Fluid Biomarker Profiles in Patients Explored for Cognitive Disorders. - Paquet, Claire; Bouaziz-Amar, Elodie; Cognat, Emmanuel; Volpe-Gillot, Lisette; Haddad, Victor; Mahieux, Florence; Dekimeche, Siham; Defontaines, Benedicte; Chabriat, Hugues; Belin, Catherine; Texeira, Antonio; Goutagny, Stephane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: CSF Alzheimer's disease (AD) biomarkers allow classifying individuals based on their levels of amyloid and neurodegeneration pathologies. OBJECTIVE: To investigate the distribution of AD biomarker profiles from patients suffering from cognitive disorders. METHODS: We analyzed 3001 patients with cognitive disorders and referred by 18 French memory clinics located in and around Paris. Patients were classified as normal, amyloidosis (A+/N-), amyloidosis and neurodegeneration (A+/N+) or suspected non-AD pathophysiology (SNAP), according to their CSF levels of biomarkers. Analysis were performed for the overall population and stratified by gender, age quintiles, and Mini-Mental State Examination (MMSE) score quintiles. Results were compared to previous findings in cohorts of healthy elderly adults. RESULTS: 37% of the sample were classified as A+/N+, 22% were classified A+/N-, and 15% as SNAP. The A+/N+ profile was associated with female gender, advanced age, and lower MMSE score, while the A+/N-profile was observed more frequently in men and the distribution was stable across age and MMSE. The SNAP profile showed no association with gender or age, was less frequent in patients with lower MMSE, and had a lower repartition than the one previously reported in asymptomatic populations. CONCLUSIONS: While A+/N+ patients had the clinical characteristics typically observed in AD, A+/N-patients had a different epidemiological pattern (higher frequency in men, no association with advanced age or lower MMSE). The SNAP profile was less frequent than previously reported in the general elderly population, suggesting that this profile is not a frequent cause of memory impairment in this population.

Early and Selective Activation and Subsequent Alterations to the Unfolded Protein Response in Down Syndrome Mouse Models. - Lanzillotta, Chiara; Tramutola, Antonella; Meier, Shelby; Schmitt, Frederick; Barone, Eugenio; Perluigi, Marzia; Di Domenico, Fabio; Abisambra, Jose F (J Alzheimers Dis, 2018)
Down syndrome (DS) is the most common chromosomal disorder and the leading genetic cause of intellectual disability in humans, which results from the triplication of chromosome 21. DS individuals have an increased risk of developing Alzheimer's disease (AD)-like pathology and dementia by the age of 40 due to the triplication of several genes involved in the formation of amyloid plaques and tau tangles. Further, DS and AD are characterized by the aberrant accumulation of unfolded/misfolded proteins resulting from over-burdened protein quality control systems. The accumulation of misfolded proteins in the endoplasmic reticulum (ER) triggers a cellular stress response called the unfolded protein response (UPR). Long-term activation of the UPR mediates neuronal dysfunction in AD. We hypothesized that the UPR is impacted in a mouse model of DS. To test this, we performed gene and protein expression analysis of ER stress markers in the Ts65Dn mouse model of DS at 3, 9, and 18 months. We identified activation of the PERK pathway in Ts65Dn DS mice at 3 months of age compared to euploid controls. We also determined that the early and overt UPR activation decreased with age, the UPR signal was significantly reduced by 18 months. Our data suggest that UPR activation in DS mouse models occurs early before consistent brain neurodegeneration and might be an essential contributor to dys-proteostasis.

Early Tau Burden Correlates with Higher Rate of Atrophy in Transentorhinal Cortex. - Xie, Long; Das, Sandhitsu R; Wisse, Laura E M; Ittyerah, Ranjit; Yushkevich, Paul A; Wolk, David A (J Alzheimers Dis, 2018)
Neurofibrillary tangle (NFT) pathology is linked to neurodegeneration in the medial temporal lobe (MTL). Using a tailored pipeline, we correlated atrophy rate, as measured from retrospective longitudinal MRI, with NFT burden, measured from 18F-AV-1451 PET, within MTL regions of earliest NFT pathology. In amyloid-β positive but not amyloid-β negative individuals, we found significant correlation between 18F-AV-1451 uptake and atrophy rate that was strongest in the transentorhinal cortex, the first region with NFT pathology. This supports the role of NFTs in driving neurodegeneration and the utility of 18F-AV-1451 PET and structural measurement of transentorhinal cortex in tracking early tau-mediated disease progression.

Effect of Fluvoxamine on Amyloid-β Peptide Generation and Memory. - Kim, Woojin Scott; Fu, YuHong; Dobson-Stone, Carol; Hsiao, Jen-Hsiang T; Shang, Kani; Hallupp, Marianne; Schofield, Peter R; Garner, Brett; Karl, Tim; Kwok, John B J (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by abnormal amyloid-β (Aβ) peptide accumulation beginning decades before symptom onset. An effective prophylactic treatment aimed at arresting the amyloidogenic pathway would therefore need to be initiated prior to the occurrence of Aβ pathology. The SIGMAR1 gene encodes a molecular chaperone that modulates processing of the amyloid-β protein precursor (AβPP). Fluvoxamine is a selective serotonin reuptake inhibitor and a potent SIGMAR1 agonist. We therefore hypothesized that fluvoxamine treatment would reduce Aβ production and improve cognition. We firstly investigated the impact of SIGMAR1 on AβPP processing, and found that overexpression and knockdown of SIGMAR1 significantly affected γ-secretase activity in SK-N-MC neuronal cells. We then tested the impact of fluvoxamine on Aβ production in an amyloidogenic cell model, and found that fluvoxamine significantly reduced Aβ production by inhibiting γ-secretase activity. Finally, we assessed the efficacy of long-term treatment (i.e., ∼8 months) of 10 mg/kg/day fluvoxamine in the J20 amyloidogenic mouse model; the treatment was initiated prior to the occurrence of predicted Aβ pathology. Physical examination of the animals revealed no overt pathology or change in weight. We conducted a series of behavioral tests to assess learning and memory, and found that the fluvoxamine treatment significantly improved memory function as measured by novel object recognition task. Two other tests revealed no significant change in memory function. In conclusion, fluvoxamine has a clear impact on γ-secretase activity and AβPP processing to generate Aβ, and may have a protective effect on cognition in the J20 mice.

Effects of Exergaming in People with Dementia: Results of a Systematic Literature Review. - van Santen, Joeke; Dröes, Rose-Marie; Holstege, Marije; Henkemans, Olivier Blanson; van Rijn, Annelies; de Vries, Ralph; van Straten, Annemieke; Meiland, Franka (J Alzheimers Dis, 2018)
BACKGROUND: Physical exercise benefits functioning, health, and well-being. However, people living with dementia in particular hardly engage in exercise. Exergaming (exercise and gaming) is an innovative, fun, and relatively safe way of exercising in a virtual reality or gaming environment. It may help people living with dementia overcome barriers they can experience regarding regular exercise activities. OBJECTIVE: This systematic literature review aims to provide an overview of the cost-effectiveness of exergaming and its effects on physical, cognitive, emotional, and social functioning, as well as the quality of life in people living with dementia. METHODS: PubMed, Embase, Cinahl, PsycINFO, the Cochrane Library, and the Web of Science Core Collection were searched. Selection of studies was carried out by at least two independent researchers. RESULTS: Three studies were found to be eligible and were included in this review. Two of these showed some statistically significant effects of exergaming on physical, cognitive, and emotional functioning in people living with dementia, although based on a very small sample. No articles were found about the cost-effectiveness of exergaming. CONCLUSIONS: Only a few controlled studies have been conducted into the effectiveness of exergaming, and these show very little significant benefits. More well-designed studies are necessary to examine the effects of exergaming.

Elevation of Plasma Amyloid-β Level is More Significant in Early Stage of Cognitive Impairment: A Population-Based Cross-Sectional Study. - Wang, Jin; Qiao, Fan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Jiang, Yu; Huo, Kang; Deng, Meiying; Wang, Jingyi; Qu, Qiumin (J Alzheimers Dis, 2018)
BACKGROUND: Aggregation and deposition of amyloid-β (Aβ) in the brain is the main pathological change of Alzheimer's disease (AD). Decreased Aβ42 in the cerebrospinal fluid has been confirmed as a biomarker of AD; however, the relationship between plasma Aβ and cognitive impairment is currently unclear. OBJECTIVE: The aim was to explore the relationship between plasma Aβ and cognitive impairment in a cross-sectional study. METHODS: A total of 1,314 subjects (age above 40) from a village in the suburbs of Xi'an, China were enrolled between October 8, 2014 and March 30, 2015. A validated Chinese version of the Mini-Mental State Examination and neuropsychological battery were used to assess cognition. Levels of plasma Aβ42 and Aβ40 were tested using commercial enzyme-linked immunosorbent assay. Relationship of plasma Aβ and cognitive impairment was analyzed using logistic regression analysis. RESULTS: Of the enrolled subjects, 1,180 (89.80%) had normal cognition, 85 (6.47%) had possible cognitive impairment and 49 (3.73%) had probable cognitive impairment. Logistic regression analysis showed that the Aβ42/Aβ40 ratio (OR = 4.042, 95% CI: 1.248-11.098, p = 0.012) and plasma Aβ42 (OR = 1.036, 95% CI: 1.003-1.071, p = 0.031) was higher in the possible cognitive impairment than that in the normal cognition group. Furthermore, the plasma Aβ42/Aβ40 ratio was higher in the possible cognitive impairment group than that in the probable cognitive impairment group (OR = 0.029, 95% CI: 0.002-0.450, p = 0.011). CONCLUSIONS: Levels of plasma Aβ42 and Aβ42/Aβ40 ratio were elevated in patients with possible cognitive impairment, indicating that plasma Aβ42 and Aβ42/Aβ40 ratio increases may be more pronounced in early stage of cognitive impairment.

The Emergence of a New Conceptual Framework for Alzheimer's Disease. - Dubois, Bruno (J Alzheimers Dis, 2018)
The New Criteria for the diagnosis of Alzheimer's disease (AD), published by a group of experts in 2007, have resulted in a revolution in the comprehension of the disease. Before 2007, the diagnosis of AD dementia was done through a process of exclusion: it was considered in the case of patients with a dementia syndrome without identified etiologies. This traditional algorithm had three major limitations that penalize the disease: 1) a low accuracy of the performance which may share responsibility for negative results in clinical trials; 2) a late identification of the patients only when they reach the threshold of dementia which may delay the activation of optimal care; and last but not least, 3) an absence of clear recognition of AD as a disease because of the lack of specific arguments for its identification. Since 2007, the disease has gained a clear definition based on positive evidence: a specific clinical phenotype (the amnestic syndrome of the hippocampal type) and the presence of biomarkers, considered as a biological signature of the disease. Thanks to these positive arguments, AD is a clinically and biologically well-delineated disease, no longer defined as "probable". It is now possible to certify that a given patient has or does not have the disease. Like diabetes, cancer, hyperthyroidism or any other disorder, AD has now a clear definition with well-defined borders. The disease has entered the world of medicine with identified diseases with a biological fingerprint. This is the story of this adventure that we will present now.

Endocytosis and Transcytosis of Amyloid-β Peptides by Astrocytes: A Possible Mechanism for Amyloid-β Clearance in Alzheimer's Disease. - Domínguez-Prieto, Marta; Velasco, Ana; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) peptides, Aβ40, Aβ42, and recently Aβ25 - 35, have been directly implicated in the pathogenesis of Alzheimer's disease (AD). We have previously shown that all three peptides decrease neuronal viability, but Aβ40 also promotes synaptic disassembling. In this work, we have studied the effects of these peptides on astrocytes in primary culture and found that the three Aβ peptides were internalized by astrocytes and significantly decreased astrocyte viability, while increasing ROS production. Aβ peptide internalization is temperature-dependent, a fact that supports the idea that Aβ peptides are actively endocytosed by astrocytes. However, inhibiting caveolae formation by methyl-beta-cyclodextrin or by silencing caveolin-1 with RNA interference did not prevent Aβ endocytosis, which suggests that Aβ peptides do not use caveolae to enter astrocytes. Conversely, inhibition of clathrin-coated vesicle formation by chlorpromazine or by silencing clathrin with RNA interference significantly decreased Aβ internalization and partially reverted the decrease of astrocyte viability caused by the presence of Aβ. These results suggest that Aβ is endocytosed by clathrin-coated vesicles in astrocytes. Aβ-loaded astrocytes, when co-incubated with non-treated astrocytes in separate wells but with the same incubation medium, promoted cell death in non-treated astrocytes; a fact that was associated with the presence of Aβ inside previously unloaded astrocytes. This phenomenon was inhibited by the presence of chlorpromazine in the co-incubation medium. These results suggest that astrocyte may perform Aβ transcytosis, a process that could play a role in the clearance of Aβ peptides from the brain to cerebrospinal fluid.

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

The Ethyl Acetate Extract of Leaves of Ugni molinae Turcz. Improves Neuropathological Hallmarks of Alzheimer's Disease in Female APPswe/PS1dE9 Mice Fed with a High Fat Diet. - Jara-Moreno, Daniela; Castro-Torres, Rubn D; Ettcheto, Miren; Auladell, Carme; Kogan, Marcelo J; Folch, Jaume; Verdaguer, Ester; Cano, Amanda; Busquets, Oriol; Delporte, Carla; Camins, Antoni (J Alzheimers Dis, 2018)
The most common type of dementia is Alzheimer's disease (AD), a progressive neurodegenerative disease characterized by impairment in cognitive performance in aged individuals. Currently, there is no effective pharmacological treatment that cures the disease due to the lack of knowledge on the actual mechanisms involved in its pathogenesis. In the last decades, the amyloidogenic hypothesis has been the most studied theory trying to explain the origin of AD, yet it does not address all the concerns relating to its development. In the present study, a possible new preclinical treatment of AD was evaluated using the ethyl acetate extract (EAE) of leaves of Ugni molinae Turcz. (synonym Myrtus ugni Molina Family Myrtacea). The effects were assessed on female transgenic mice from a preclinical model of familial AD (APPswe/PS1dE9) combined with a high fat diet. This preclinical model was selected due to the already available experimental and observational data proving the relationship between obesity, gender, metabolic stress, and cognitive dysfunction; related to characteristics of sporadic AD. According to chemical analyses, EAE would contain polyphenols such as tannins, flavonoid derivatives, and phenolic acids, as well as pentacyclic triterpenoids that exhibit neuroprotective, anti-inflammatory, and antioxidant effects. In addition, the treatment evidenced its capacity to prevent deterioration of memory capacity and reduction of progression speed of AD neuropathology.

Evaluating Peripersonal Space through the Functional Transcranial Doppler: Are We Paving the Way for Early Detecting Mild Cognitive Impairment to Dementia Conversion? - Marra, Angela; Naro, Antonino; Chillura, Antonino; Bramanti, Alessia; Maresca, Giuseppa; De Luca, Rosaria; Manuli, Alfredo; Bramanti, Placido; Calabrò, Rocco Salvatore (J Alzheimers Dis, 2018)
BACKGROUND: Identifying the patients with mild cognitive impairment (MCI) who may develop dementia (MDC) is challenging. The study of peripersonal space (PPS) by using functional transcranial Doppler (fTCD) could be used for this purpose. OBJECTIVE: To identify changes in cerebral blood flow (CBF) during motor tasks targeting PPS, which can predict MDC. METHODS: We evaluated the changes in CBF in 22 patients with MCI and 23 with dementia [Alzheimer's disease (AD) and vascular dementia (VaD)] during a motor task (passive mobilization, motor imagery, and movement observation) in which the hand of the subject moved forward and backward the face. RESULTS: CBF increased when the hand approached the face and decreased when the hand moved from the face in the healthy controls (HCs). CBF changed were detectable only in patients with MCI but not in those with the AD and those who were MDC after 8-month follow-up. On the other hand, the patients with VaD presented a paradoxical response to the motor task (i.e., a decrease of CBF rather than an increase, as observed in HCs and MCI). Therefore, we found a modulation of PPS-related CBF only in HCs and patients with stable MCI (at the 8-month follow-up). CONCLUSIONS: fTCD may allow preliminarily differentiating and following-up the patients with MCI and MDC, thus allowing the physician to plan beforehand more individualized cognitive rehabilitative training.

Evaluation of Ocular Perfusion in Alzheimer's Disease Using Optical Coherence Tomography Angiography. - Lahme, Larissa; Esser, Eliane Luisa; Mihailovic, Natasa; Schubert, Friederike; Lauermann, Jost; Johnen, Andreas; Eter, Nicole; Duning, Thomas; Alnawaiseh, Maged (J Alzheimers Dis, 2018)
BACKGROUND: There is increasing evidence for the involvement of cerebrovascular factors in Alzheimer's disease (AD). OBJECTIVE: To evaluate retinal and optic nerve head perfusion in patients with AD using optical coherence tomography angiography (OCTA), and to analyze the correlations of quantitative OCTA metrics with AD pathology and vascular cerebral lesions in AD patients. METHODS: 36 eyes of 36 patients with AD (study group) and 38 eyes of 38 healthy subjects (control group) were prospectively included in this study. OCTA was performed using RTVue XR Avanti with AngioVue. In addition, patients underwent a detailed ophthalmological and neurological examination including Mini-Mental State Examination, cerebral magnetic resonance imaging, and amyloid-β (Aβ) and tau levels in the cerebrospinal fluid (CSF). RESULTS: The flow density in the superficial retinal OCT angiogram of the macula in the study group was significantly lower compared to the control group (p = 0.001). There was a significant correlation between the flow density in the superficial retinal OCT angiogram of the macula, as measured using OCTA, and the Fazekas scale (Spearman's correlation coefficient = -0.520; p = 0.003). There was no significant correlation between the Aβ or tau levels in the CSF and the flow density data. CONCLUSION: Patients with AD showed a reduced flow density in the radial peripapillary capillaries layer and in the superficial retinal OCT angiogram when compared with healthy controls. The reduced retinal flow density measured using OCTA is not specifically associated with AD pathology but is associated with the vascular cerebral lesions in AD.

Executive Dysfunction Detected with the Frontal Assessment Battery in Alzheimer's Disease Versus Vascular Dementia. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Addante, Filomena; Solfrizzi, Vincenzo; Cantarini, Chiara; Mangiacotti, Antonio; Lauriola, Michele; Cascavilla, Leandro; Paris, Francesco; Lozupone, Madia; Daniele, Antonio; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and vascular dementia (VaD) lead to progressive decline in executive function. We estimated the prevalence of executive dysfunction in AD and VaD patients, investigating cognitive, functional, and clinical correlates and also using a multidimensional approach based on a standardized comprehensive geriatric assessment (CGA). We included 215 patients (115 AD patients and 100 VaD patients) consecutively evaluated with a complete cognitive and affective assessment, a CGA, and the Frontal Assessment Battery (FAB) with six subtests investigating conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. The prevalence of dysexecutive syndrome screened with a FAB score <12 points was high in both AD (97 patients) and VaD (77 patients) (84.3% versus 77.0%, p = 0.171). AD patients were significantly younger, with higher grade of cognitive impairment and less severe comorbidity and polypharmacy than VaD patients. AD patients showed a significantly higher impairment in FAB total score and five FAB subtests (conceptualization, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy) than VaD patients. These findings were largely confirmed in a sub-analysis conducted subdividing the sample in mild and moderate-to-severe demented patients and suggesting that in moderate-to-severe AD there was higher impairment in FAB total score and four FAB subtests (conceptualization, sensitivity to interference, inhibitory control, and environmental autonomy). Executive dysfunction could be greater in AD patients with moderate-to-severe dementia compared to VaD patients, although our groups were also not matched for age, comorbidity or polypharmacy, which could also exert an effect.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Comorbidity; Dementia, Vascular; Executive Function; Female; Frontal Lobe; Geriatric Assessment; Humans; Logistic Models; Male; Polypharmacy; Severity of Illness Index

Exposure to Strong Anticholinergic Medications and Dementia-Related Neuropathology in a Community-Based Autopsy Cohort. - Gray, Shelly L; Anderson, Melissa L; Hanlon, Joseph T; Dublin, Sascha; Walker, Rod L; Hubbard, Rebecca A; Yu, Onchee; Montine, Thomas J; Crane, Paul K; Sonnen, Josh A; Keene, C Dirk; Larson, Eric B (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic medication exposure has been associated with increased risk for dementia. No study has examined the association between anticholinergic medication use and neuropathologic lesions in a community-based sample. OBJECTIVE: To examine the relationship between anticholinergic exposure and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N = 420), we ascertained use of anticholinergic medications over a 10-year period from automated pharmacy data and calculated total standardized daily doses (TSDD). We used modified Poisson regression to calculate adjusted relative risks (RRs) and 95% confidence intervals (CIs) for the association between anticholinergic exposure and dementia-associated neuropathology. Inverse probability weighting was used to account for selection into the autopsy cohort. RESULTS: Heavy anticholinergic exposure (≥1,096 TSDD) was not associated with greater neuropathologic changes of Alzheimer's disease; the adjusted RRs for heavy use of anticholinergics (≥1,096 TSDD) compared to no use were 1.22 (95% CI 0.81-1.88) for neuritic plaque scores and 0.89 (0.47-1.66) for extent of neurofibrillary degeneration. Moderate (91-1,095 TSDD) and heavy use of anticholinergics was associated with a significantly lower cerebral microinfarct burden compared with no use with adjusted RRs of 0.44 (0.21-0.89) and 0.24 (0.09-0.62), respectively. Anticholinergic exposure was not associated with macroscopic infarcts or atherosclerosis. CONCLUSIONS: Use of anticholinergic medications is not associated with Alzheimer's disease-related neuropathologic changes but is associated with lower cerebral microinfarct burden. Further research into biological mechanisms underlying the anticholinergic-dementia link is warranteds.

Expression Profiling of Cytokine, Cholinergic Markers, and Amyloid-β Deposition in the APPSWE/PS1dE9 Mouse Model of Alzheimer's Disease Pathology. - Reale, Marcella; D'Angelo, Chiara; Costantini, Erica; Di Nicola, Marta; Yarla, Nagnedra Sastry; Kamal, Mohammad Amjad; Salvador, Nieves; Perry, George (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD), a neurodegenerative disease, is associated with dysfunction of the olfactory and the entorhinal cortex of the brain that control memory and cognitive functions and other daily activities. Pro-inflammatory cytokines, amyloid-β (Aβ), and the cholinergic system play vital roles in the pathophysiology of AD. However, the role of changes in cholinergic system components, Aβ accumulation, and cytokines in both the olfactory and entorhinal cortex is not known clearly. OBJECTIVE: The present study is aimed to evaluate the changes of cholinergic system components, Aβ accumulation, and cytokines in both the olfactory bulb (OB) and entorhinal cortex (EC) of young and aged APPSWE/PS1dE9 transgenic (Tg) mice. METHODS: We have explored the changes of cholinergic system components, Aβ accumulation, and expression profiling of cytokines in the OB and EC of aged APPswe transgenic mice and age-matched wild type mice using quantitative Real-Time PCR assays and immunohistochemistry techniques. RESULTS: In aged Tg mice, a significant increase of expression of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and chemokine MCP1 (p < 0.001, p < 0.001, and p = 0.001, respectively) and a significant reduction of nAChRα4 (p = 0.048) and AChE (p = 0.023) was observed when compared with age-matched wild type mice. Higher levels of AChE and BuChE are expressed in OB and EC of the APPSWE/PS1dE9 of Tg mice. Aβ accumulation was observed in OB and EC of the APPSWE/PS1dE9 of Tg mice. CONCLUSION: The study demonstrates the expression profiling of pro-inflammatory cytokines and cholinergic markers as well as Aβ accumulation in OB and EC of the APPSWE/PS1dE9 Tg mice. Moreover, the study also demonstrated that the APPSWE/PS1dE9 Tg mice can be useful as a mouse model to understand the role of pro-inflammatory cytokines and cholinergic markers in pathophysiology of AD.

Forgetting Rate on the Recency Portion of a Word List Differentiates Mild to Moderate Alzheimer's Disease from Other Forms of Dementi. - Turchetta, Chiara Stella; Perri, Roberta; Fadda, Lucia; Caruso, Giulia; De Simone, Maria Stefania; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (J Alzheimers Dis, 2018)
Patients with Alzheimer's disease (AD) demonstrate a disproportionately larger forgetting rate in episodic memory tasks. Previous studies documented that, in comparison with healthy controls, the increased forgetting manifested by AD patients in word list recall tasks is confined to the recency portion of the list with normal forgetting rates on the primacy and mid-list portions. In this study we compared the primacy, mid-list, and recency ratios, obtained by dividing the immediate and delayed recall of words in position 1-4, 5-11, and 12-15 of a 15-word list, in different groups of demented patients, i.e., AD, frontal variant of frontotemporal dementia (fvFTD), Lewy body disease (LBD), subcortical ischemic vascular dementia (SIVD), and a group of normal controls (NC). The aim was to investigate whether the above reported forgetting pattern would differentiate AD performance from that of other dementia groups. Results of the statistical analysis showed that only the recency ratio differentiated AD from patients in the other dementia groups. Consistently, hierarchical logistic regression analyses demonstrated that the recency ratio discriminated between AD patients and individuals affected by other forms of dementia. In particular, the discrimination power was high in differentiating AD from fvFTD patients but was less accurate in differentiating AD from LBD and SIVD patients. We assume that the increased forgetting in AD patients is due to a deficit in memory consolidation mechanisms (specific to AD) that prevent the terminal items in a list from being transferred from a temporary short-term memory store to a stable long-term memory store.

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Frontotemporal Dementia and Chorea Associated with a Compound Heterozygous TREM2 Mutation. - Redaelli, Veronica; Salsano, Ettore; Colleoni, Lara; Corbetta, Paola; Tringali, Giovanni; Del Sole, Angelo; Giaccone, Giorgio; Rossi, Giacomina (J Alzheimers Dis, 2018)
Frontotemporal dementia (FTD) is clinically characterized by behavioral changes, language impairment, and executive dysfunction. FTD usually belongs to the frontotemporal lobar degeneration (FTLD) disease group, and its familial forms are dominantly inherited and linked to a group of genes relevant to frontal and temporal brain pathology, such as MAPT, GRN, C9ORF72, TARDBP, CHMP2B, VCP, and FUS. However, FTD can also be associated with different clinical or pathological phenotypes caused by mutations in other genes, whose heredity can be dominant or recessive. In this work we report on a familial case of FTD characterized by behavioral changes and aphasia, very early onset and very long duration, choreic movements, and white matter lesions at magnetic resonance imaging. We performed a wide-range genetic analysis, using a next generation sequencing approach, to evaluate a number of genes involved in neurodegeneration. We found a previously unreported compound heterozygous mutation in TREM2, that is commonly associated with the recessively inherited Nasu-Hakola disease. We discuss the differential diagnosis to be taken into account in cases of FTD presenting with atypical features.

Frontotemporal Dementia Misdiagnosed for Post-Treatment Lyme Disease Syndrome or vice versa? A Treviso Dementia (TREDEM) Registry Case Report. - Di Battista, Maria Elena; Dell'Acqua, Carola; Baroni, Luciana; Fenoglio, Chiara; Galimberti, Daniela; Gallucci, Maurizio (J Alzheimers Dis, 2018)
We describe the case of a 61-year-old woman diagnosed with Borreliosis at the age of 57. Subsequently, the patient developed depression, anxiety, and behavioral disturbances. A lumbar puncture excluded the condition of Neuroborreliosis. The diagnostic workup included: an MRI scan, a 18F-FDG PET, a 123I-ioflupane-SPECT, an amyloid-β PET, a specific genetic analysis, and a neuropsychological evaluation. Based on our investigation, the patient was diagnosed with probable behavioral-frontotemporal dementia (bvFTD), whereas in the previous years, the patient had been considered firstly as a case of Post-Treatment-Lyme Disease and, secondly, a psychiatric patient. We believe that, in the present case, such initial symptoms of Borrelia infection may have superimposed on those of bvFTD rather than playing as a contributory cause.

Gait in Mild Alzheimer's Disease: Feasibility of Multi-Center Measurement in the Clinic and Home with Body-Worn Sensors: A Pilot Study. - Mc Ardle, Ríona; Morris, Rosie; Hickey, Aodhán; Del Din, Silvia; Koychev, Ivan; Gunn, Roger N; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; et al. (J Alzheimers Dis, 2018)
Gait is emerging as a potential diagnostic tool for cognitive decline. The 'Deep and Frequent Phenotyping for Experimental Medicine in Dementia Study' (D&FP) is a multicenter feasibility study embedded in the United Kingdom Dementia Platform designed to determine participant acceptability and feasibility of extensive and repeated phenotyping to determine the optimal combination of biomarkers to detect disease progression and identify early risk of Alzheimer's disease (AD). Gait is included as a clinical biomarker. The tools to quantify gait in the clinic and home, and suitability for multi-center application have not been examined. Six centers from the National Institute for Health Research Translational Research Collaboration in Dementia initiative recruited 20 individuals with early onset AD. Participants wore a single wearable (tri-axial accelerometer) and completed both clinic-based and free-living gait assessment. A series of macro (behavioral) and micro (spatiotemporal) characteristics were derived from the resultant data using previously validated algorithms. Results indicate good participant acceptability, and potential for use of body-worn sensors in both the clinic and the home. Recommendations for future studies have been provided. Gait has been demonstrated to be a feasible and suitable measure, and future research should examine its suitability as a biomarker in AD.

Gene Transfer Induced Hypercholesterolemia in Amyloid Mice. - Grames, Mychal S; Dayton, Robert D; Lu, Xiaohong; Schilke, Robert M; Alexander, J Steven; Orr, A Wayne; Barmada, Sami J; Woolard, Matthew D; Klein, Ronald L (J Alzheimers Dis, 2018)
A risk factor for cardiovascular disease (CVD), mutant PCSK9, was expressed in APP/PS1 mice to study the CVD-Alzheimer's disease inter-relationship. Cholesterol levels were elevated by 5-6-fold from 3 to 13 weeks after PCSK9 gene transfer. We tested whether hypercholesterolemia would increase amyloid-β plaques at a relatively early stage of plaque deposition. Plaque burden was increased in the hippocampus of PCSK9 treated mice though the increase was modest compared to the large elevation in cholesterol. Elevating cholesterol via gene transfer could be valuable in a variety of disease models compared to making crosses with germ-line transgenic mouse models of CVD.

Generation of a New Tau Knockout (tauΔex1) Line Using CRISPR/Cas9 Genome Editing in Mice. - Tan, Daniel C S; Yao, Sherilyn; Ittner, Arne; Bertz, Josefine; Ke, Yazi D; Ittner, Lars M; Delerue, Fabien (J Alzheimers Dis, 2018)
Alzheimer's disease and other dementias present with tau pathology. Several mouse lines with knockout of the tau-encoding Mapt gene have been reported, yet findings often differed between lines and sites. Here, we report a new tau knockout strain (tauΔex1), generated by CRISPR/Cas9-mediated genome editing of intron -1/exon 1 of Mapt in C57Bl/6J mice. TauΔex1 mice had no overt phenotype, but, in line with previous models, they showed a significantly reduced susceptibility to excitotoxic seizures, with normal memory formation in young mice. This new in vivo resource will be made freely available to the research community.

Genetic Interaction with Plasma Lipids on Alzheimer's Disease in the Framingham Heart Study. - Peloso, Gina M; Beiser, Alexa S; DeStefano, Anita L; Seshadri, Sudha (J Alzheimers Dis, 2018)
Epidemiological and genetic studies have pointed to the role of cholesterol in Alzheimer's disease (AD). We explored the interaction of a genetic risk score (GRS) of AD risk alleles with mid-life plasma lipid levels (LDL-C, HDL-C, and triglycerides) on risk for AD in the Framingham Heart Study (FHS). Mid-life (between the ages of 40-60 years old) lipid levels were obtained from individuals in the FHS Original and Offspring cohorts (157 cases and 2,882 controls) with genetic data and AD status available. Cox proportional hazards regression was performed to test the interaction between mid-life lipid levels and an AD GRS, as well as the individual contributing SNPs, on risk of incident AD adjusting for age, sex, and cohort. We found a significant interaction between a GRS of AD loci and log triglyceride levels on risk of clinical AD (p = 0.006), but no interaction of the GRS with HDL-C (p = 0.458) or LDL-C (p = 0.366). We then tested the interaction between the individual SNPs contributing to the GRS and log triglycerides. We found two SNPs that had interactions with triglycerides on AD risk that reached a p-value < 0.05 (rs11218343 and APOEɛ4). The association between some AD SNPs and risk of AD may be modified by triglyceride levels. Furthermore, sequential testing of a GRS with a set of traits on disease followed by testing individual SNPs for interaction provides a framework for narrowing the associations that need to be tested for interaction analyses. Replication is needed to confirm these findings.

Genetic Risk for Age-Related Cognitive Impairment Does Not Predict Cognitive Performance in Middle Age. - Korthauer, Laura E; Awe, Elizabeth; Frahmand, Marijam; Driscoll, Ira (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by memory loss and executive dysfunction, which correspond to structural changes to the medial temporal lobes (MTL) and prefrontal cortex (PFC), respectively. Given the overlap in cognitive deficits between healthy aging and the earliest stages of AD, early detection of AD remains a challenge. The goal of the present study was to study MTL- and PFC-dependent cognitive functioning in middle-aged individuals at genetic risk for AD or cognitive impairment who do not currently manifest any clinical symptoms. Participants (N = 150; aged 40-60 years) underwent genotyping of 47 single nucleotide polymorphisms (SNPs) in six genes previously associated with memory or executive functioning: APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT. They completed two MTL-dependent tasks, the virtual Morris Water Task (vMWT) and transverse patterning discriminations task (TPDT), and the PFC-dependent reversal learning task. Although age was associated with poorer performance on the vMWT and TPDT within this middle-aged sample, there were no genotype-associated differences in cognitive performance. Although the vMWT and TPDT may be sensitive to age-related changes in cognition, carriers of APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT risk alleles do not exhibit alteration in MTL- and PFC-dependent functioning in middle age compared to non-carriers.

Glia Maturation Factor and Mast Cell-Dependent Expression of Inflammatory Mediators and Proteinase Activated Receptor-2 in Neuroinflammation. - Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Ahmed, Mohammad Ejaz; Zaheer, Smita; Kumar, Keerthana Kuppamma; Yelam, Anudeep; Kaur, Harleen; Dubova, Iuliia; Raikwar, Sudhanshu P; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Parkinson's disease (PD) is characterized by the presence of inflammation-mediated dopaminergic neurodegeneration in the substantia nigra. Inflammatory mediators from activated microglia, astrocytes, neurons, T-cells and mast cells mediate neuroinflammation and neurodegeneration. Administration of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induces PD like motor deficits in rodents. 1-methyl-4-phenylpyridinium (MPP+), a toxic metabolite of MPTP activates glial cells, neurons and mast cells to release neuroinflammatory mediators. Glia maturation factor (GMF), mast cells and proteinase activated receptor-2 (PAR-2) are implicated in neuroinflammation. Alpha-synuclein which induces neurodegeneration increases PAR-2 expression in the brain. However, the exact mechanisms are not yet understood. In this study, we quantified inflammatory mediators in the brains of MPTP-administered wild type (Wt), GMF-knockout (GMF-KO), and mast cell knockout (MC-KO) mice. Additionally, we analyzed the effect of MPP+, GMF, and mast cell proteases on PAR-2 expression in astrocytes and neurons in vitro. Results show that the levels of interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and the chemokine (C-C motif) ligand 2 (CCL2) were lesser in the brains of GMF-KO mice and MC-KO mice when compared to Wt mice brain after MPTP administration. Incubation of astrocytes and neurons with MPP+, GMF, and mouse mast cell protease-6 (MMCP-6) and MMCP-7 increased the expression of PAR-2. Our studies show that the absence of mast cells and GMF reduce the expression of neuroinflammatory mediators in the brain. We conclude that GMF along with mast cell interactions with glial cells and neurons during neuroinflammation can be explored as a new therapeutic target for PD and other neuroinflammatory disorders.

Hedonic Assessment of Odors: A Comparison of Two Sensory Scales for Use with Alzheimer's Disease Patients and Elderly Individuals. - Atanasova, Boriana; Mondon, Karl; Dreyfuss, Lise; Beaufils, Emilie; Desmidt, Thomas; Hommet, Caroline; El-Hage, Wissam; Belzung, Catherine (J Alzheimers Dis, 2018)
BACKGROUND: Several clinical studies concerning the olfactory function of patients with cognitive impairment have used sensory scales to investigate hedonic perception. However, no study has focused on the choice of the most appropriate sensory hedonic scale for the individuals with neurodegenerative disorders or other psychiatric diseases involving cognitive deficits. OBJECTIVE: The aim of this study was to investigate the ability of patients with Alzheimer's disease (AD) to use two hedonic scales (category scale and linear scale) and compare their discriminatory capacity, repeatability, and ease of use. This should allow us to identify the most appropriate hedonic scale for patients with AD. METHODS: We recruited 18 patients with mild to moderate AD, and 20 healthy volunteers matched for gender, age, smoking status, and educational level. The participants underwent a clinical assessment and hedonic evaluation of three odorants (pleasant, unpleasant, and neutral), using a five-point category scale and a 10-cm linear scale with a marked mid-point. RESULTS: AD patients were able to use hedonic scales as well as paired healthy elderly subjects. The linear scale performed slightly better in terms of ease of use for both patients and healthy controls and discriminatory capacity for AD patients. The results for AD patients and controls with both scales were repeatable. CONCLUSION: The linear scale may be more appropriate for AD patients pending further studies involving a larger population of patients, using several odorants.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Linear Models; Male; Olfaction Disorders; Olfactory Perception; Severity of Illness Index; Smell

Higher Blood Vitamin C Levels are Associated with Reduction of Apolipoprotein E E4-related Risks of Cognitive Decline in Women: The Nakajima Study. - Noguchi-Shinohara, Moeko; Abe, Chiemi; Yuki-Nozaki, Sohshi; Dohmoto, Chiaki; Mori, Ayaka; Hayashi, Koji; Shibata, Syutaro; Ikeda, Yoshihisa; Sakai, Kenji; Iwasa, Kazuo; Yokogawa, Masami; Ishimiya, Mai; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Antioxidants like vitamins C and E may minimize the risk for Alzheimer's disease. OBJECTIVE: We examined whether vitamins C and E modify the apolipoprotein E (APOE) E4-related risks for developing cognitive decline. METHODS: We conducted a population-based prospective study including Japanese residents aged 65 years from Nakajima, Japan. The participants received an evaluation of cognitive function and underwent blood tests including tests for vitamins C and E levels and APOE phenotypes. The APOE E4-by-gender-by-vitamin C or E interactions on developing cognitive decline were analyzed. RESULTS: Of 606 participants with normal cognitive function determined using a baseline survey (2007-2008), 349 completed the follow up survey between 2014 and 2016. In women with APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin C concentration tertile [multivariate OR 0.10 (95% CI 0.01-0.93)] compared with the lowest tertile. In men without APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin E concentration tertile [multivariate OR 0.19 (0.05-0.74)] as compared with the lowest tertile. CONCLUSION: Our results demonstrate significant beneficial effects of vitamins C and E in reducing the risk of cognitive decline in women with APOE E4 and men without APOE E4, respectively.

Imaging Biomarkers of Neurodegeneration in Alzheimer's Disease: Distinct Contributions of Cortical MRI Atrophy and FDG-PET Hypometabolism. - Benvenutto, Agnès; Giusiano, Bernard; Koric, Lejla; Gueriot, Claude; Didic, Mira; Felician, Olivier; Guye, Maxime; Guedj, Eric; Ceccaldi, Mathieu (J Alzheimers Dis, 2018)
BACKGROUND: Neurodegeneration biomarkers are routinely used in the diagnosis of Alzheimer's disease (AD). OBJECTIVE: To evaluate the respective contributions of two neuroimaging biomarkers, structural MRI and 18FDG-PET, in the assessment of neurodegeneration in AD dementia. METHODS: Patients with mild AD dementia diagnosed based on clinical and cerebrospinal fluid criteria and cognitively healthy subjects, from the Marseille cohort ADAge with cognitive, structural MRI and 18FDG-PET assessments, were included. Extent of atrophy on MRI and of hypometabolism on 18FDG-PET were individually evaluated in each patient using a voxel-based analysis on whole-brain approach and compared to healthy subjects. Patients were divided in distinct groups according to their atrophy extent on the one hand and to their hypometabolism extent on the other, then, to their imaging profile combining the extent of the two biomarkers. RESULTS: Fifty-two patients were included. The MMSE score was significantly lower in the "Extensive hypometabolism" group than in the "Limited hypometabolism" group (respectively 19.5/30 versus 23/30). A lower Innotest Amyloid Tau Index was associated with an extensive hypometabolism (p = 0.04). There were more patients with low educational level in the "Extensive atrophy" group, while a higher educational level was more found in the "Limited atrophy" group (p = 0.005). CONCLUSION: 18FDG-PET hypometabolism extent is associated with the pathological processes and clinical severity of AD, while MRI atrophy seems to be influenced by the cognitive reserve. In the context of mild AD dementia, these two biomarkers of neurodegeneration are thus not interchangeable and require to be considered in combination rather than in isolation.

Immunohistochemical Analysis of Activin Receptor-Like Kinase 1 (ACVRL1/ALK1) Expression in the Rat and Human Hippocampus: Decline in CA3 During Progression of Alzheimer's Disease. - Adams, Stephanie L; Benayoun, Laurent; Tilton, Kathy; Mellott, Tiffany J; Seshadri, Sudha; Blusztajn, Jan Krzysztof; Delalle, Ivana (J Alzheimers Dis, 2018)
The pathophysiology of Alzheimer's disease (AD) includes signaling defects mediated by the transforming growth factor β-bone morphogenetic protein-growth and differentiation factor (TGFβ-BMP-GDF) family of proteins. In animal models of AD, administration of BMP9/GDF2 improves memory and reduces amyloidosis. The best characterized type I receptor of BMP9 is ALK1. We characterized ALK1 expression in the hippocampus using immunohistochemistry. In the rat, ALK1 immunoreactivity was found in CA pyramidal neurons, most frequently and robustly in the CA2 and CA3 fields. In addition, there were sporadic ALK1-immunoreactive cells in the stratum oriens, mainly in CA1. The ALK1 expression pattern in human hippocampus was similar to that of rat. Pyramidal neurons within the CA2, CA3, and CA4 were strongly ALK1-immunoreactive in hippocampi of cognitively intact subjects with no neurofibrillary tangles. ALK1 signal was found in the axons of alveus and fimbria, and in the neuropil across CA fields. Relatively strongest ALK1 neuropil signal was observed in CA1 where pyramidal neurons were occasionally ALK1-immunoractive. As in the rat, horizontally oriented neurons in the stratum oriens of CA1 were both ALK1- and GAD67-immunoreactive. Analysis of ALK1 immunoreactivity across stages of AD pathology revealed that disease progression was characterized by overall reduction of the ALK1 signal in CA3 in advanced, but not early, stages of AD. These data suggest that the CA3 pyramidal neurons may remain responsive to the ALK1 ligands, e.g., BMP9, during initial stages of AD and that ALK1 may constitute a therapeutic target in early and moderate AD.

Impact of Amyloid PET Imaging in the Memory Clinic: A Systematic Review and Meta-Analysis. - Shea, Yat-Fung; Barker, Warren; Greig-Gusto, Maria T; Loewenstein, David A; Duara, Ranjan; DeKosky, Steven T (J Alzheimers Dis, 2018)
BACKGROUND: Patients with cognitive impairment or dementias of uncertain etiology are frequently referred to a memory disorders specialty clinic. The impact of and role for amyloid PET imaging (Aβ-PET) may be most appropriate in this clinical setting. OBJECTIVE: The primary objective of this study was to perform a systematic review and meta-analysis of the impact of Aβ-PET on etiological diagnosis and clinical management in the memory clinic setting. METHODS: A search of the literature on the impact of Aβ-PET in the memory clinic setting between 1 January 2004 and 12 February 2018 was conducted. Meta-analysis using a random effects model was performed to determine the pooled estimate of the impact of Aβ-PET in the changes of diagnoses and changes in management plan. RESULTS: After rigorous review, results from 13 studies were extracted, involving 1,489 patients. Meta-analysis revealed a pooled effect of change in diagnoses of 35.2% (95% CI 24.6-47.5). Sub-analyses showed that the pooled effect in change in diagnoses if Aβ-PET was used under the appropriate use criteria (AUC) or non-AUC criteria were 47.8% (95% CI 25.9-70.5) and 29.6% (95% CI: 21.5-39.3), respectively. The pooled effect of a change of diagnosis from Alzheimer's disease (AD) to non-AD and from non-AD to AD were 22.7% (95% CI: 17.1-29.5) and 25.6% (95% CI: 17.6-35.8), respectively. The pooled effect leading to a change of management was 59.6% (95% CI 39.4-77.0). CONCLUSIONS: Aβ-PET has a highly significant impact on both changes in diagnosis and management among patients being seen at a specialty memory clinic.

Impact of Olfactory Priming on Food Intake in an Alzheimer's Disease Unit. - Sulmont-Rossé, Claire; Gaillet, Marie; Raclot, Carine; Duclos, Michel; Servelle, Maud; Chambaron, Stéphanie (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is often associated with feeding difficulties and changes in eating behavior with may lead to malnutrition. In French nursing homes, AD patients may live in special care units that better meet dementia residents' needs. However, meals are often delivered to AD patients by using meal trays coming from central kitchens. This led to the disappearance of cues that could help residents to foresee mealtime, such as the smell of food odors. The aim of the present study was to assess the impact of odorizing the dining room of AD Units with a meat odor before lunch on subsequent food intake and eating behavior. Thirty-two residents (>75 years old) from three AD Units were included in the study. They participated in two control lunches and two primed lunches, for which a meat odor was diffused in the dining room 15 minutes before the arrival of the meal tray (olfactory priming). Results of the first replication showed a significant effect of olfactory priming, with a 25% increase in meat and vegetable consumption compared to the control condition. Behavioral measurements also showed a significant increase of resident's interest toward the meal in the primed lunch. However, this effect was no longer observed when the priming session was replicated two weeks later with the same priming odor and the same menu. Although further research is needed to understand why this priming effect cannot be replicated, our experiment is one of the very first to investigate the effect of food odor priming on subsequent food intake in AD patients in a real-life setting.

Impact of Total Knee Arthroplasty with General Anesthesia on Brain Networks: Cognitive Efficiency and Ventricular Volume Predict Functional Connectivity Decline in Older Adults. - Huang, Haiqing; Tanner, Jared; Parvataneni, Hari; Rice, Mark; Horgas, Ann; Ding, Mingzhou; Price, Catherine (J Alzheimers Dis, 2018)
Using resting state functional magnetic resonance imaging (RS-fMRI), we explored: 1) pre- to post-operative changes in functional connectivity in default mode, salience, and central executive networks after total knee arthroplasty (TKA) with general anesthesia, and 2) the contribution of cognitive/brain reserve metrics these resting state functional declines. Individuals age 60 and older electing unilateral total knee arthroplasty (TKA; n = 48) and non-surgery peers with osteoarthritis (n = 45) completed baseline cognitive testing and baseline and post-surgery (post-baseline, 48-h post-surgery) brain MRI. We acquired cognitive and brain estimates for premorbid (vocabulary, reading, education, intracranial volume) and current (working memory, processing speed, declarative memory, ventricular volume) reserve. Functional network analyses corrected for pain severity and pain medication. The surgery group declined in every functional network of interest (p < 0.001). Relative to non-surgery peers, 23% of surgery participants declined in at least one network and 15% of the total TKA sample declined across all networks. Larger preoperative ventricular volume and lower scores on preoperative metrics of processing speed and working memory predicted default mode network connectivity decline. Premorbid cognitive and premorbid brain reserve did not predict decline. Within 48 hours after surgery, at least one fourth of the older adult sample showed significant functional network decline. Metrics of current brain status (ventricular volume), working memory, and processing speed predicted the severity of default mode network connectivity decline. These findings demonstrate the relevance of preoperative cognition and brain integrity on acute postoperative functional network change.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

Impaired Spike Timing Dependent Cortico-Cortical Plasticity in Alzheimer's Disease Patients. - Di Lorenzo, Francesco; Ponzo, Viviana; Motta, Caterina; Bonní, Sonia; Picazio, Silvia; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro; Koch, Giacomo (J Alzheimers Dis, 2018)
BACKGROUND: Mechanisms of cortical plasticity have been recently investigated in Alzheimer's disease (AD) patients with transcranial magnetic stimulation protocols showing a clear impairment of long-term potentiation (LTP) cortical-like plasticity mechanisms. OBJECTIVE: We aimed to investigate mechanisms of cortico-cortical spike-timing dependent plasticity (STDP) in AD patients investigating the connections between posterior parietal cortex (PPC) and primary motor cortex (M1). METHODS: We used a cortico-cortical paired associative stimulation (cc-PAS) protocol to repeatedly activate the connection between PPC and M1 of the left-dominant hemisphere in a sample of fifteen AD patients and ten age-matched healthy subjects. PPC transcranial magnetic stimulation preceded (ccPAS +5) or followed M1 stimulation (ccPAS - 5) by 5 ms. Motor-evoked potentials (MEPs) were collected to assess the time course of the after effects of cc-PAS protocol measuring MEP amplitude as index of cortico-cortical associative plasticity. RESULTS: In healthy subjects, ccPAS - 5 protocol induced the expected long-lasting increase of MEP amplitude compatible with LTP-like cortical plasticity while PAS +5 protocol induced the opposite effect. AD patients did not show any significant modification of the amplitude of MEP after both ccPAS protocols. CONCLUSIONS: Our study shows that in AD patients the time-locked activation of human cortico-cortical connections is not able to form STDP, reflecting an impairment of a multi-factor plasticity process.

Improvement of Main Cognitive Functions in Patients with Alzheimer's Disease after Treatment with Coconut Oil Enriched Mediterranean Diet: A Pilot Study. - de la Rubia Ortí, Jose Enrique; García-Pardo, María Pilar; Drehmer, Eraci; Sancho Cantus, David; Julián Rochina, Mariano; Aguilar, Maria Asunción; Hu Yang, Iván (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder (mainly in women), and new therapies are needed. In this way, ketone bodies are a direct source of cellular energy and can be obtained from coconut oil, postulating that coconut oil could be a new non-pharmacological alternative in AD patients. OBJECTIVE: The aim of this study is to detect changes in the main cognitive functions of patients with AD after following a coconut oil enriched Mediterranean diet, and to determine whether there are differences in function of stage or sex. METHODS: A prospective, longitudinal, qualitative, analytic, experimental study was carried out in 44 patients with AD, who were randomly divided into two homogenous groups of 22 patients each: an experimental group of patients who followed a coconut oil enriched Mediterranean diet for 21 days and a control group. In order to determine the cognitive changes after the intervention, we carried out the 7 Minute Screen, which analyses temporal orientation, visuospatial and visuoconstructive abilities, and semantic and episodic memory. RESULTS: After intervention with coconut oil, improvements in episodic, temporal orientation, and semantic memory were observed, and it seems that the positive effect is more evident in women with mild-moderate state, although other improvements in males and severe state were also shown. CONCLUSIONS: The isocaloric coconut oil enriched Mediterranean diet seems to improve cognitive functions in patients with AD, with differences according to patient sex and degree of severity of the disease, although more studies in this line are needed.

Increased Insoluble Amyloid-β Induces Negligible Cognitive Deficits in Old AppNL/NL Knock-In Mice. - Salas, Isabel H; Callaerts-Vegh, Zsuzsanna; D'Hooge, Rudi; Saido, Takaomi C; Dotti, Carlos G; De Strooper, Bart (J Alzheimers Dis, 2018)
Commonly used Alzheimer's disease mouse models are based on the ectopic overexpression of the human amyloid precursor protein (APP) gene, together with a mutant presenilin gene. Surprisingly, humanized APP knock-in mouse models carrying a single APP Swedish mutation (AppNL), failed to develop amyloid plaque aggregation or cognitive deficits. Here we characterized the effect of this mutation in more advanced ages. We show that 24-month-old AppNL/NL mice, despite presenting an age dependent increase in insoluble amyloid-β oligomers in the prefrontal cortex, they do not develop amyloid plaque deposition, reactive gliosis, or cognitive deficits.

Increased Serum Acylated Ghrelin Levels in Patients with Mild Cognitive Impairment. - Cao, Xi; Zhu, Min; He, Yan; Chu, Wenzheng; Du, Yifeng; Du, Heng (J Alzheimers Dis, 2018)
Ghrelin is a stomach-derived circulating hormone. In addition to its function as an orexigenic stimulant, the role of ghrelin in the consolidation of learning and memory has been implicated in recent years. However, the status of circulating acylated ghrelin (AG, that is, the functional form of ghrelin) in the symptomatic predementia stage of Alzheimer's disease (AD) has rarely been investigated. In the current study, we examined the serum levels of acylated and total ghrelin in 22 patients with mild cognitive impairment (MCI) and 30 cognitively normal controls. We have found that patients with MCI had significantly increased serum AG levels, which were inversely associated with defected short- and long-term memory as well as language skills. Of note, the levels of total circulating ghrelin were similar between the two groups. Intriguingly, serum AG but not total ghrelin was associated with AD risk factors including the age, hypertension, and hyperlipidemia. Therefore, circulating AG may serve as a potential early systemic biomarker for AD-related cognitive impairments. Nevertheless, the simplest interpretation of the results is that the levels of circulating AG are associated with cognitive impairments in patients with MCI, thereby forming the groundwork for our future studies on the systemic mechanisms of AD pertaining to the ghrelin system.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Ghrelin; Humans; Male; Middle Aged; Risk Factors

The Independent Associations of Physical Activity and Sleep with Cognitive Function in Older Adults. - Falck, Ryan S; Best, John R; Davis, Jennifer C; Liu-Ambrose, Teresa (J Alzheimers Dis, 2018)
BACKGROUND: Current evidence suggests physical activity (PA) and sleep are important for cognitive health; however, few studies examining the role of PA and sleep for cognitive health have measured these behaviors objectively. OBJECTIVE: We cross-sectionally examined whether 1) higher PA is associated with better cognitive performance independently of sleep quality; 2) higher sleep quality is associated with better cognitive performance independently of PA; and 3) whether higher PA is associated with better sleep quality. METHODS: We measured PA, subjective sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and objective sleep quality (i.e., fragmentation, efficiency, duration, and latency) using the MotionWatch8© in community-dwelling adults (N = 137; aged 55+). Cognitive function was indexed using the Alzheimer's Disease Assessment Scale-Plus. Correlation analyses were performed to determine relationships between PA, sleep quality, and cognitive function. We then used latent variable modelling to examine the relationships of PA with cognitive function independently of sleep quality, sleep quality with cognitive function independently of PA, and PA with sleep quality. RESULTS: We found greater PA was associated with better cognitive performance independently of 1) PSQI (β= -0.03; p < 0.01); 2) sleep fragmentation (β= -0.02; p < 0.01); 3) sleep duration (β= -0.02; p < 0.01); and 4) sleep latency (β= -0.02; p < 0.01). In addition, better sleep efficiency was associated with better cognitive performance independently of PA (β= -0.01; p = 0.04). We did not find any associations between PA and sleep quality. CONCLUSIONS: PA is associated with better cognitive performance independently of sleep quality, and sleep efficiency is associated with better cognitive performance independently of PA. However, PA is not associated with sleep quality and thus PA and sleep quality may be related to cognitive performance through independent mechanisms.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

Influence of Lewy Pathology on Alzheimer's Disease Phenotype: A Retrospective Clinico-Pathological Study. - Roudil, Jennifer; Deramecourt, Vincent; Dufournet, Boris; Dubois, Bruno; Ceccaldi, Mathieu; Duyckaerts, Charles; Pasquier, Florence; Lebouvier, Thibaud (J Alzheimers Dis, 2018)
BACKGROUND: Studies have shown the frequent coexistence of Lewy pathology (LP) in Alzheimer's Disease (AD). OBJECTIVE: The aim of this study was to determine the influence of LP on the clinical and cognitive phenotype in a cohort of patients with a neuropathological diagnosis of AD. METHODS: We reviewed neuropathologically proven AD cases, reaching Braak stages V and VI in the brain banks of Lille and Paris between 1993 and 2016, and classified them according to LP extension (amygdala, brainstem, limbic, or neocortical). We then searched patient files for all available clinical and neuropsychiatric features and neuropsychological data. RESULTS: Thirty-three subjects were selected for this study, among which 16 were devoid of LP and 17 presented AD with concomitant LP. The latter were stratified into two subgroups according to LP distribution: 7 were AD with amygdala LP and 10 were AD with 'classical' (brainstem, limbic or neocortical) LP. When analyzing the incidence of each clinical feature at any point during the disease course, we found no significant difference in symptom frequency between the three groups. However, fluctuations appeared significantly earlier in patients with classical LP (2±3.5 years) than in patients without LP (7±1.7 years) or with amygdala LP (8±2.8 years; p < 0.01). There was no significant difference in cognitive profiles. CONCLUSION: Our findings suggest that the influence of LP on the clinical phenotype of AD is subtle. Core features of dementia with Lewy bodies do not allow clinical diagnosis of a concomitant LP on a patient-to-patient basis.

The In-Hospital Length of Stay after Hip Fracture in Octogenarians: Do Delirium and Dementia Shape a New Care Process? - Monacelli, Fiammetta; Pizzonia, Monica; Signori, Alessio; Nencioni, Alessio; Giannotti, Chiara; Minaglia, Cecilia; Granello di Casaleto, Tommaso; Podestà, Silvia; Santolini, Federico; Odetti, Patrizio (J Alzheimers Dis, 2018)
BACKGROUND: Hip fracture is a major health problem and a patient's biological age, comorbidity, and cognitive vulnerability have an impact on its related outcomes. Length of stay (LOS) for these highly vulnerable patients is rather long and the possible causes have not been clearly identified yet. OBJECTIVE: We aimed to assess the main clinical factors associated with protracted LOS, focusing on delirium with or without dementia in older age hip fractured patients. METHODS: 218 subjects (mean age 86.70±6.18 years), admitted to the Orthogeriatric Unit of the Ospedale Policlinico San Martino (Italy), were recruited. All patients received physical and comprehensive geriatric assessment. Days to surgery, days from surgery to rehabilitation, and LOS were recorded. In-hospital and three months' mortality were reported. RESULTS: Prevalent delirium at hospital admission was of 3.1%. 35% of patients developed incident delirium. 56.4% were affected by dementia of Alzheimer-type. In addition, 52% of patients developed delirium superimposed to dementia. Mean LOS was 13.5±4.99 days. Namely, delirium, time to surgery, and complication rate disproportionally affected LOS. The analysis with 3 months mortality, based on cognitive vulnerability profiles, showed how delirium mainly affect short-term mortality in patients with dementia. CONCLUSION: Our exploratory study originally pointed out the high incidence of delirium superimposed to dementia in orthogeriatric wards and how delirium turns to be a moderator of LOS. The results meet the need for additional research by virtue of a deeper understanding of the impact of delirium and dementia on orthogeriatric clinical management and outcomes.

Intracellular Targeting of Heat Shock Proteins in Differentiated Human Neuronal Cells Following Proteotoxic Stress. - Deane, Catherine A S; Brown, Ian R (J Alzheimers Dis, 2018)
HSPA6 (Hsp70B') is an inducible member of the Hsp70 (HSPA) family of heat shock proteins that is present in the human genome and not found in mouse and rat. Hence it is lacking in current animal models of neurodegenerative diseases. To advance knowledge of the little studied HSPA6, differentiated human neuronal SH-SY5Y cells were treated with the proteotoxic stress-inducing agent MG132. A robust induction of HSPA6 was apparent which localized to the periphery of MG132-induced protein aggregates in the neuronal cytoplasm. Components of the protein disaggregation/refolding machine that co-operate with Hsp70 also targeted the periphery of cytoplasmic protein aggregates, including DNAJB1 (Hsp40-1), HSPH1 (Hsp105α), and HSPB1 (Hsp27). These data suggest that HSPA6 is involved in the response of human neuronal cells to proteotoxic stress that is a feature of neurodegenerative diseases which have been characterized as protein misfolding disorders. Constitutively expressed HSPA8 (Hsc70) also localized tothe periphery of cytoplasmic protein aggregates following the treatment of differentiated human neuronal cells with MG132. HSPA8 could provide a rapid response to proteotoxic stress in neuronal cells, circumventing the time required to upregulate inducible Hsps.

Intracranial Transplantation of Pancreatic Islets Attenuates Cognitive and Peripheral Metabolic Dysfunctions in a Rat Model of Sporadic Alzheimer's Disease. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Taler, Michal; Dar, Shira; Azarov, Dmitry; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is often associated with brain insulin resistance and peripheral metabolic dysfunctions. Recently, we developed a model of sporadic AD associated with obesity-related peripheral metabolic abnormalities in Lewis rats using intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to assess the effect of intracranially grafted pancreatic islets on cognitive and peripheral metabolic dysfunctions in the icv-STZ Lewis rats. METHODS: AD-like dementia associated with obesity was induced in inbred Lewis rats using a single icv-STZ. Two months after icv-STZ, syngeneic islets (100 islets per recipient) were implanted in the cranial subarachnoid cavity of icv-STZ rats. Morris water maze and marble burying tests were used for studying cognitive and behavioral functions. Central and peripheral metabolic alterations were assessed by histological and biochemical assays. RESULTS: The icv-STZ induced increases in food intake, body weight, and blood levels of insulin and leptin without alteration of glucose homeostasis. Grafted islets reduced body weight gain, food consumption, peripheral insulin resistance, and hyperleptinemia. Biochemical and histological analysis of the brain revealed viable grafted islets expressing insulin and glucagon. The grafted islets did not affect expression of brain insulin receptors and peripheral glucose homeostasis. Two months after islet transplantation, cognitive and behavioral functioning in transplanted rats were significantly better than the sham-operated icv-STZ rats. No significant differences in the locomotor activity between transplanted and non-transplanted icv-STZ rats were found. CONCLUSIONS: Intracranial islet transplantation attenuates cognitive decline and peripheral metabolic dysfunctions providing a novel therapeutic approach for sporadic AD associated with peripheral metabolic dysfunctions.

Involvement of the Cingulate Cortex in Anosognosia: A Multimodal Neuroimaging Study in Alzheimer's Disease Patients. - Guerrier, Laura; Le Men, Johanne; Gane, Anaıs; Planton, Mélanie; Salabert, Anne-Sophie; Payoux, Pierre; Dumas, Hervé; Bonneville, Fabrice; Péran, Patrice; Pariente, Jérémie (J Alzheimers Dis, 2018)
BACKGROUND: Anosognosia is a frequent symptom of Alzheimer's disease (AD), but its neural substrates remain in question. OBJECTIVE: In this study, we combined neuroimaging with a neuropsychological evaluation to assess neural substrates of anosognosia. METHODS: We prospectively recruited 30 patients with probable early-stage AD and matched healthy controls. Participants underwent MRI, FDG-PET, and a neuropsychological evaluation that includes an assessment of anosognosia. In the AD group, correlations between the anosognosia score, neuroimaging modalities, and neuropsychological performance were performed. RESULTS: Atrophy and hypometabolism were correlated with the anosognosia score in the left dorsal anterior cingulate cortex. The anosognosia score was also correlated with atrophy of the cerebellar vermis, the left postcentral gyrus, and the right fusiform gyrus. No relation was found between anosognosia and the neuropsychological assessment. DISCUSSION: Structural and metabolic alteration in the dorsal anterior cingulate cortex seems to be associated with a diminution of awareness in patients with early-stage AD.

Kainic Acid Impairs the Memory Behavior of APP23 Mice by Increasing Brain Amyloid Load through a Tumor Necrosis Factor-α-Dependent Mechanism. - Ruan, Yang; Guo, Shi-Jie; Wang, Xu; Dong, Dong; Shen, Dong-Hui; Zhu, Jie; Zheng, Xiang-Yu (J Alzheimers Dis, 2018)
Kainic acid (KA) was recently identified as an epileptogenic and neuroexcitotoxic agent that is responsible for inducing learning and memory deficits in various neurodegenerative diseases, such as Alzheimer's disease (AD). However, the mechanism by which KA acts upon AD remains unclear. To this end, we presently investigated the roles of KA in processing amyloid-β protein precursor (AβPP) and amyloid-β protein (Aβ) loads during the course of AD development and progression. Specifically, KA treatment clearly caused the upregulation of tumor necrosis factor α (TNF-α) via activation of the PI3-K/AKT, ERK1/2, and p65 pathways in glial cells. TNF-α secreted from glial cells was then found to be responsible for stimulating the expression of BACE-1 and PS1/2, which resulted in the production and deposition of Aβ in neurons. Finally, the accumulation and aggregation of Aβ lead to the cognitive decline of APP23 mice. These results indicate that KA accelerates the progression of AD by inducing the crosstalk between glial cells and neurons.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

The Level of Plasma Amyloid-β40 Is Correlated with Peripheral Transport Proteins in Cognitively Normal Adults: A Population-Based Cross-Sectional Study. - Gao, Ling; Jiang, Yu; Wei, Shan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Deng, Meiying; Wang, Jingyi; Zhang, Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Transport proteins, soluble low-density lipoprotein receptor-related protein-1 (sLRP1), and soluble receptor of advanced glycation end products (sRAGE), play an important role in the clearance of plasma amyloid-β (Aβ). However, their relationship is not clear. OBJECTIVE: The aim was to explore the relationship between plasma levels of sLRP1, sRAGE, and Aβ in a cross-sectional study. METHODS: A total of 1,185 cognitively normal participants (age above 40) from a village in the suburbs of Xi'an, China were enrolled from October 8, 2014 to March 30, 2015. Plasma Aβ40, Aβ42, sLRP1, and sRAGE were tested using a commercial ELISA. Apolipoprotein E (APOE) genotyping was conducted using PCR and sequencing. The relationship between plasma levels of sLRP1, sRAGE, and Aβ was analyzed using Pearson's correlation analysis and multiple linear regression. RESULTS: In the total population, Log sLRP1 and Log sRAGE were positively correlated with plasma Aβ40 (r= 0.103, p < 0.001; r= 0.064, p = 0.027, respectively), but neither were associated with plasma Aβ42. After multivariable adjustment in the regression model, Log sLRP1 and Log sRAGE were still positively related with plasma Aβ40 (β= 2.969, p < 0.001; β= 1.936, p = 0.017, respectively) but not Aβ42. Furthermore, the positive correlations between transport proteins and plasma Aβ40 remained significant only in APOEɛ4 non-carriers after Pearson's analysis and multiple regression analysis after stratification by gene status. CONCLUSION: The concentrations of plasma sLRP1 and sRAGE had a significant impact on the level of plasma Aβ40 in cognitively normal adults, especially in APOEɛ4 non-carriers. However, the mechanism by which the transport proteins are involved in peripheral Aβ clearance and the relationship between transporters and amyloid burden in the brain needs further validation.

Lifetime Risk Factors for Functional and Cognitive Outcomes in Patients with Alzheimer's Disease. - de Oliveira, Fabricio Ferreira; de Almeida, Sandro Soares; Chen, Elizabeth Suchi; Smith, Marilia Cardoso; Naffah-Mazzacoratti, Maria da Graça; Bertolucci, Paulo Henrique Ferreira (J Alzheimers Dis, 2018)
Lifetime risk factors for cognitive and functional decline in Alzheimer's disease (AD) are not fully understood, and were prospectively evaluated in patients with low mean schooling from São Paulo, Brazil. Consecutive outpatients with late-onset AD were assessed for APOE haplotypes and the following potential baseline predictors: gender, schooling, age at dementia onset, lifetime urban living and sanitary conditions, occupational complexity, cognitive and physical activities, cerebrovascular risk factors (obesity, lifetime alcohol use and smoking, length of arterial hypertension, diabetes mellitus, and a dyslipidemic profile), use of a pacemaker, creatinine clearance, body mass index, waist circumference, head traumas with unconsciousness, treated systemic bacterial infections, amount of surgical procedures under general anesthesia, and family history of AD. Participants were followed from October 2010 to May 2017 for baseline risk factor associations with time since dementia onset for Clinical Dementia Rating and Mini-Mental State Examination score changes. For 227 patients (154 women, 119 APOE ε 4 carriers), later AD onset (mean 73.60±6.4 years-old, earlier for APOE ε 4/ε 4 carriers, p < 0.001) was the only variable hastening all endpoints, baseline creatinine clearance and lifetime alcohol use were hazardous for earlier cognitive and functional endpoints, women had earlier cognitive endpoints only, and schooling had a cumulative protective effect over later cognitive endpoints, particularly for carriers of APOE ε 4. Exclusively for carriers of APOE ε 4, head traumas with unconsciousness were hazardous for earlier cognitive endpoints, while lifetime sanitary conditions were protective regarding later cognitive endpoints. Functional and cognitive outcomes in AD represent probable interactions between effects of brain reserve and cerebral perfusion over neurodegeneration.

A Link between Subjective Perceptions of Memory and Physical Function: Implications for Subjective Cognitive Decline. - Cosentino, Stephanie; Devanand, Davangere; Gurland, Barry (J Alzheimers Dis, 2018)
Subjective impairment in memory is a frequently defining feature of subjective cognitive decline (SCD), a state hypothesized to precede objectively apparent cognitive symptoms of Alzheimer's disease (AD) and to hold promise as a non-invasive, inexpensive, preclinical indicator of AD. However, a full model of the factors that contribute to subjective memory (SM), and therefore to SCD, has yet to be articulated. While SM impairment is widely known to be associated with negative affect, the extent to which SM functioning may also reflect other factors, particularly subjective beliefs or perceptions about one's health, is not known. To examine the extent to which SM is associated with subjective perceptions of health more broadly, the current study investigated the link between SM and subjective physical functioning (independent of depressive affect, and objective cognitive and physical function) in an ethnically diverse sample of 471 older adults enrolled in the population-based Northern Manhattan Aging Project. 199 (42%) participants endorsed no difficulty on a 5-point SM index while 272 (58%) endorsed some degree of difficulty. As hypothesized, SM correlated with both depression and subjective physical function, but not with age, education, global cognition, or objective physical function. When objective and subjective physical function were entered in two separate, adjusted linear regressions predicting SM, only subjective physical function and depressive affect independently predicted SM. Subjective perceptions of memory appear to reflect individuals' broader health perceptions in part. Articulating the various correlates of SM will improve identification of SCD specific to preclinical AD.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Linear Models; Male; Memory; Neuropsychological Tests; New York City; Perception

Long-Term Severe Mental Disorders Preceding Behavioral Variant Frontotemporal Dementia: Frequency and Clinical Correlates in an Outpatient Sample. - Gambogi, Leandro Boson; Guimarães, Henrique Cerqueira; de Souza, Leonardo Cruz; Caramelli, Paulo (J Alzheimers Dis, 2018)
BACKGROUND: The behavioral variant frontotemporal dementia (bvFTD) shares some clinical features with severe mental disorders, such as bipolar affective disorder (BAD), schizophrenia (SCZ), and schizoaffective disorder (SZA), and at least for a small subgroup of patients, these conditions may share similar pathological genetic mutations. OBJECTIVES: To investigate the frequency of a past medical history satisfying diagnostic criteria for BAD, SCZ, and SZA in a bvFTD outpatient sample, and to compare the clinical profile of patients with and without a positive history. METHODS: Cross-sectional study in which participants were consecutively selected after receiving a diagnosis of probable bvFTD and had a caregiver interviewed with SCID-I. The sample was categorized into two groups: with (bvFTD+) or without (bvFTD-) prior medical history satisfying diagnostic criteria for BAD/SCZ/SZA. Subjects went through cognitive, functional, and neuropsychiatric evaluations. RESULTS: Overall, 46 bvFTD patients were included; bvFTD+ patients accounted for 36.9% of the sample. The main nosology fulfilling criteria was BAD (76.5%). The groups differed in Neuropsychiatric Inventory scores (p = 0.01), use of antipsychotics (p = 0.01), family history of psychosis (p = 0.01), presence of primitive reflexes (p = 0.04), Frontal Assessment Battery performance (p = 0.01), Ekman's facial emotion recognition test (p = 0.03), frequency of apathy (p = 0.03), and stereotyped behavior (p = 0.01). All these parameters were more frequent/worse in the bvFTD+ group. CONCLUSIONS: A prior medical history compatible with BAD/SCZ/SZA was found in more than 1/3 of this sample of bvFTD patients and was associated with subtle distinctive clinical features.

Medical and Research Consent Decision-Making Capacity in Patients with Alzheimer's Disease: A Systematic Review. - van Duinkerken, Eelco; Farme, Juliana; Landeira-Fernandez, Jesus; Dourado, Marcia C; Laks, Jerson; Mograbi, Daniel C (J Alzheimers Dis, 2018)
The capacity to make decisions is an important feature of daily living, which is closely linked to proper cognitive functioning. In conditions in which cognitive functioning becomes compromised, such as in Alzheimer's disease (AD), decision-making capacity can also get affected. Especially in AD, this has important implications, since over the course of the condition many important clinical decisions have to be made. For caregivers as well as physicians, it is sometimes difficult to determine how and when to intervene in the decision-making process. The aim of this systematic literature review was to identify studies that have evaluated medical and research consent decision-making capacity in patients with AD. Studies consistently show that decision-making capabilities are impaired in patients with AD. The cognitive and neuronal correlates of this process are, however, poorly studied. The few studies that investigated correlations have shown worse cognitive performance, mainly on the MMSE, to be related to poorer decision-making capacity. As most of these correlations have been performed in groups combining patients and controls, it remains unknown if these associations are disease specific. There is a need to study more systematically the decision-making process in relation to cognitive functioning and neural correlates to be able to develop a framework of decision-making capacity in AD, ultimately aiding clinicians and caregivers to understand and evaluate those capabilities in patients.

Memory Loss and the Onset of Alzheimer's Disease Could Be Under the Control of Extracellular Heat Shock Proteins. - Arispe, Nelson; De Maio, Antonio (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a major contemporary and escalating malady in which amyloid-β (Aβ) peptides are the most likely causative agent. Aβ peptides spontaneously tend to aggregate in extracellular fluids following a progression from a monomeric state, through intermediate forms, ending in amyloid fibers and plaques. It is generally accepted now that the neurotoxic agents leading to cellular death, memory loss, and other AD characteristics are the Aβ intermediate aggregated states. However, Aβ peptides are continuously produced, released into the extracellular space, and rapidly cleared from healthy brains. Coincidentally, members of the heat shock proteins (hsp) family are present in the extracellular medium of healthy cells and body fluids, opening the possibility that hsps and Aβ could meet and interact in the extracellular milieu of the brain. In this perspective and reflection article, we place our investigation showing that the presence of Hsp70s mitigate the formation of low molecular weight Aβ peptide oligomers resulting in a reduction of cellular toxicity, in context of the current understanding of the disease. We propose that it may be an inverse relationship between the presence of Hsp70, the stage of Aβ oligomers, neurotoxicity, and the incidence of AD, particularly since the expression and circulating levels of hsp decrease with aging. Combining these observations, we propose that changes in the dynamics of Hsp70s and Aβ concentrations in the circulating brain fluids during aging defines the control of the formation of Aβ toxic aggregates, thus determining the conditions for neuron degeneration and the incidence of AD.

Meta-Analysis of Personality Traits in Alzheimer's Disease: A Comparison with Healthy Subjects. - D'Iorio, Alfonsina; Garramone, Federica; Piscopo, Fausta; Baiano, Chiara; Raimo, Simona; Santangelo, Gabriella (J Alzheimers Dis, 2018)
BACKGROUND: The role of specific personality traits as factor risks of Alzheimer's disease (AD) has been consistently found, whereas personality traits specifically related to AD (after the diagnosis) have not been outlined yet. OBJECTIVE: A meta-analysis of published studies was performed to determine whether AD patients have a distinctive personality trait profile compared to healthy subjects (HC), similar to or different from a premorbid personality profile consistently reported in previous studies. METHODS: A systematic literature search was performed using PsycInfo (PROQUEST), PubMed, and Scopus. The meta-analysis pooled results from primary studies using Hedges' g unbiased approach. RESULTS: The meta-analysis included 10 primary studies and revealed that, when the personality was evaluated by informant-rated measures, AD patients had significantly higher levels of Neuroticism, lower levels of Openness, Agreeableness, Conscientiousness, and Extraversion than HCs. When the personality was evaluated by self-rated measures, the results obtained from informants were confirmed for Neuroticism, Openness, and Extraversion but not for Agreeableness and Conscientiousness where AD patients and HCs achieved similar scores. CONCLUSIONS: The meta-analysis revealed that high Neuroticism and low Openness and Extraversion are distinctive personality traits significantly associated with a diagnosis of AD when evaluated both self-rated and informant-rated measures. This personality trait profile is similar to premorbid one, which contributes to development of AD over time. Therefore, our findings indirectly support the idea of specific premorbid personality traits as harbingers of AD.
Keywords: Alzheimer Disease; Case-Control Studies; Humans; Personality; Personality Inventory

Metabolic Dysfunction in Alzheimer's Disease: From Basic Neurobiology to Clinical Approaches. - Clarke, Julia R; Ribeiro, Felipe C; Frozza, Rudimar L; De Felice, Fernanda G; Lourenco, Mychael V (J Alzheimers Dis, 2018)
Clinical trials have extensively failed to find effective treatments for Alzheimer's disease (AD) so far. Even after decades of AD research, there are still limited options for treating dementia. Mounting evidence has indicated that AD patients develop central and peripheral metabolic dysfunction, and the underpinnings of such events have recently begun to emerge. Basic and preclinical studies have unveiled key pathophysiological mechanisms that include aberrant brain stress signaling, inflammation, and impaired insulin sensitivity. These findings are in accordance with clinical and neuropathological data suggesting that AD patients undergo central and peripheral metabolic deregulation. Here, we review recent basic and clinical findings indicating that metabolic defects are central to AD pathophysiology. We further propose a view for future therapeutics that incorporates metabolic defects as a core feature of AD pathogenesis. This approach could improve disease understanding and therapy development through drug repurposing and/or identification of novel metabolic targets.

Metabolomics Analyses of Saliva Detect Novel Biomarkers of Alzheimer's Disease. - Huan, Tao; Tran, Tran; Zheng, Jiamin; Sapkota, Shraddha; MacDonald, Stuart W; Camicioli, Richard; Dixon, Roger A; Li, Liang (J Alzheimers Dis, 2018)
Using a non-invasive biofluid (saliva), we apply a powerful metabolomics workflow for unbiased biomarker discovery in Alzheimer's disease (AD). We profile and differentiate Cognitively Normal (CN), Mild Cognitive Impairment (MCI), and AD groups. The workflow involves differential chemical isotope labeling liquid chromatography mass spectrometry using dansylation derivatization for in-depth profiling of the amine/phenol submetabolome. The total sample (N = 109) was divided in to the Discovery Phase (DP) (n = 82; 35 CN, 25 MCI, 22 AD) and a provisional Validation Phase (VP) (n = 27; 10 CN, 10 MCI, 7 AD). In DP we detected 6,230 metabolites. Pairwise analyses confirmed biomarkers for AD versus CN (63), AD versus MCI (47), and MCI versus CN (2). We then determined the top discriminating biomarkers and diagnostic panels. A 3-metabolite panel distinguished AD from CN and MCI (DP and VP: Area Under the Curve [AUC] = 1.000). The MCI and CN groups were best discriminated with a 2-metabolite panel (DP: AUC = 0.779; VP: AUC = 0.889). In addition, using positively confirmed metabolites, we were able to distinguish AD from CN and MCI with good diagnostic performance (AUC > 0.8). Saliva is a promising biofluid for both unbiased and targeted AD biomarker discovery and mechanism detection. Given its wide availability and convenient accessibility, saliva is a biofluid that can promote diversification of global AD biomarker research.

Metformin Use Associated with Reduced Risk of Dementia in Patients with Diabetes: A Systematic Review and Meta-Analysis. - Campbell, Jared M; Stephenson, Matthew D; de Courten, Barbora; Chapman, Ian; Bellman, Susan M; Aromataris, Edoardo (J Alzheimers Dis, 2018)
BACKGROUND: Metformin, a first line antihyperglycemic medication, is an AMPK activator and has been hypothesized to act as a geroprotective agent. Studies on its association with various classifications of age-related cognitive decline have shown mixed results with positive and negative findings. OBJECTIVE: To synthesize the best available evidence on the association of metformin-use with risk, progression, and severity of dementia. METHOD: Eligible research investigated the effect of metformin on dementia, Alzheimer's disease, or any measure of cognitive impairment compared to any control group who were not receiving metformin. The initial search resulted in 862 citations from which 14 studies (seven cohort, four cross-sectional, two RCTs, and one case control) were included. RESULTS: Meta-analysis of three studies showed that cognitive impairment was significantly less prevalent in diabetic metformin (Odds ratio = 0.55, 95% CI 0.38 to 0.78), while six studies showed that dementia incidence was also significantly reduced (Hazard ratio = 0.76, 95% CI 0.39 to 0.88). Mini-Mental State Examination scores were not significantly affected by metformin-use, although both RCTs showed that metformin had a neuroprotective effect compared to placebo. Some studies found negative or neutral effects for metformin use by people with diabetes; the potential mechanism of metformin-induced vitamin B12 deficiency is discussed. CONCLUSIONS: Metformin should continue to be used as a first line therapy for diabetes in patients at risk of developing dementia or Alzheimer's disease. The use of metformin by individuals without diabetes for the prevention of dementia is not supported by the available evidence.

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

Minor Hallucinations in Alzheimer's Disease. - Ruiz, Maria; Arias, Alfonso; Sánchez-Llanos, Ernesto; Gil, Maria Pilar; López-Ortega, Ricard; Dakterzada, Faridé; Purroy, Francisco; Piñol-Ripoll, Gerard (J Alzheimers Dis, 2018)
BACKGROUND: Hallucinations may have a broad spectrum and include so-called minor hallucinations (MHs). MHs include passage hallucinations (PHs), visual illusions, and presence hallucinations (PrHs). OBJECTIVE: To determine the prevalence and characteristics of MHs in Alzheimer's disease (AD) and amnestic mild cognitive impairment (aMCI) patients, and to describe their potential relationship with cognition, behavioral symptoms, and use of psychoactive drugs. METHODS: We have recruited prospectively and consecutively 268 subjects (90 AD mild-moderate drug-naïve patients, 78 aMCI, and 100 controls). All patients responded to a semi-structured questionnaire in order to rate psychotic phenomena. Clinical, neuropsychological, and demographic data of patients with and without MH were compared with those of age, sex, and education-matched controls. RESULTS: The prevalence of MHs was 21.1% (19) in AD, 12.8% (10) in aMCI, and 3% (3) in controls (p < 0.01). The most frequent MH was PrH (9.3%), followed by PH (4.9%) and illusion (0.7%). Eight (27.8%) patients had more than one MH. After adjusting for age and gender, there was a negative correlation between the presence of MHs and MMSE score (r = -0.261; p < 0.01) and a positive correlation between MHs and Neuropsychiatric Inventory score (r = 0.237; p < 0.01). We did not observe a significant relationship between presence of MHs and the consumption of psychoactive drugs (p > 0.05). CONCLUSION: We have shown that the presence of MHs in patients with newly diagnosed, untreated AD and aMCI is more than controls. MHs were correlated with other behavioral symptoms and a worse cognitive performance. We suggest the specific interrogation for MHs as a clinical feature for this population.

miRNA 933 Expression by Endothelial Cells is Increased by 27-Hydroxycholesterol and is More Prevalent in Plasma from Dementia Patients. - Dias, Irundika H K; Brown, Caroline L; Shabir, Kiran; Polidori, M Cristina; Griffiths, Helen R (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) etiology is complex; gene and environmental risk factors may interact to predispose to disease. From single nucleotide polymorphism analyses and genome-wide association studies, a number of candidate risk genes for the onset of AD have been identified and cluster around lipid metabolism and inflammation. We hypothesized that endothelial cells which line the blood-brain barrier are likely to be critical mediators of systemic metabolism within the brain. Therefore, we have studied the effect of 27 hydroxycholesterol (27-OHC) on microvascular endothelial cell (HMVEC) redox state, inflammatory cytokine secretion, and microRNA (miR) expression. Using a transwell method, we have studied directional secretion profiles for the proinflammatory cytokines TNFα and IL-6 and confirmed that 27-OHC induces discrete and directional inflammatory molecular signatures from HMVEC. The lipids caused depletion of cellular glutathione and cytokine secretion is HMVEC-redox state-dependent. Discovery miR expression change in HMVEC with and without 27-OHC treatment was undertaken. We selected three genes for further analysis by qPCR; miR-144 and 146 expression, which are anti-inflammatory and redox regulating modulators, were not affected significantly by 27-OHC. However, increased expression of a putative neurotrophic regulatory factor miR933 in HMVEC with 27-OHC was confirmed by qPCR. In plasma from patients with dementia, all three miR were found at significantly elevated levels compared to healthy older adults. These data highlight that 27-OHC has an important regulatory effect on endothelial microvascular cells to increase expression of a miR (-933) and secretion of inflammatory cytokines that are elevated in plasma from dementia patients.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

Multisensory Stimulation and Individualized Music Sessions on Older Adults with Severe Dementia: Effects on Mood, Behavior, and Biomedical Parameters. - Maseda, Ana; Cibeira, Nuria; Lorenzo-López, Laura; González-Abraldes, Isabel; Buján, Ana; de Labra, Carmen; Millán-Calenti, José Carlos (J Alzheimers Dis, 2018)
BACKGROUND: Multisensory stimulation and individualized music have shown to be good in handling the psychological and behavioral symptoms in people with severe dementia. OBJECTIVE: Explore the effects of two nonpharmacological interventions, multisensory stimulation environment (MSSE) in a Snoezelen room and individualized music sessions, on mood, behavior, and biomedical parameters of institutionalized elderly patients with severe dementia. METHODS: Randomized trial of 21 patients aged ≥65 years randomly assigned to two groups (MSSE and individualized music). Interventions administered in two-weekly sessions lasted 30 minutes for a period of 12 weeks. Main outcomes were recorded before, during, and at the end of the intervention. RESULTS: Both groups had immediate positive effects on mood and behavior. Participants were more happy/more content (p < 0.001), talked more spontaneously (p = 0.009), related to people better (p = 0.002), were more attentive to/focused on their environment (p < 0.001), enjoyed themselves (p = 0.003), were less bored/inactive (p = 0.004), and more relaxed/content (p = 0.003). The MSSE group performed a better visual follow-up of the stimuli (p = 0.044), and the music group were more relaxed and happy (p = 0.003). A decrease in heart rate (p = 0.013) and an increase in oxygen saturation (p = 0.011) were observed from before to after interventions in both groups, with no significant differences between them. CONCLUSIONS: Both interventions seem to be effective at managing mood and behavioral disturbances in the short term and at improving physiological rates, highlighting the efficacy of nonpharmacological treatments in patients with severe dementia.

Music and Dementia: Individual Differences in Response to Personalized Playlists. - Garrido, Sandra; Stevens, Catherine J; Chang, Esther; Dunne, Laura; Perz, Janette (J Alzheimers Dis, 2018)
Personalized music playlists are increasingly being used in health-care contexts to address the psychological and behavioral symptoms in people with dementia. However, there is little understanding of how people with different mental health histories and symptoms respond differently to music. A factorial experiment was conducted to investigate the influence of depression, anxiety, apathy, and cognitive decline on affective response to music. Ninety-nine people with dementia listened to three music playlists based on personal preferences. Activation of facial action units was measured, and behavioural responses continuously observed. Results demonstrated that people with high levels of depression and with symptoms of Alzheimer's type dementia demonstrated increased levels of sadness when listening to music. People with low depression but high levels of apathy demonstrated the highest behavioral evidence of pleasure during music listening, although behavioral evidence declined with severity of cognitive impairment. It is concluded that as well as accounting for personal preferences, music interventions for people with dementia need to take mental health history and symptoms into account.

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

A Network of Genetic Effects on Non-Demented Cognitive Aging: Alzheimer's Genetic Risk (CLU + CR1 + PICALM) Intensifies Cognitive Aging Genetic Risk (COMT + BDNF) Selectively for APOEɛ4 Carriers. - Sapkota, Shraddha; Dixon, Roger A (J Alzheimers Dis, 2018)
BACKGROUND: Trajectories of complex neurocognitive phenotypes in preclinical aging may be produced differentially through selective and interactive combinations of genetic risk. OBJECTIVE: We organize three possible combinations into a "network" of genetic risk indices derived from polymorphisms associated with normal and impaired cognitive aging, as well as Alzheimer's disease (AD). Specifically, we assemble and examine three genetic clusters relevant to non-demented cognitive trajectories: 1) Apolipoprotein E (APOE), 2) a Cognitive Aging Genetic Risk Score (CA-GRS; Catechol-O-methyltransferase + Brain-derived neurotrophic factor), and 3) an AD-Genetic Risk Score (AD-GRS; Clusterin + Complement receptor 1 + Phosphatidylinositol-binding clathrin assembly protein). METHOD: We use an accelerated longitudinal design (n = 634; age range = 55-95 years) to test whether AD-GRS (low versus high) moderates the effect of increasing CA-GRS risk on executive function (EF) performance and change as stratified by APOE status (ɛ4+ versus ɛ4-). RESULTS: APOEɛ4 carriers with high AD-GRS had poorer EF performance at the centering age (75 years) and steeper 9-year decline with increasing CA-GRS but this association was not present in APOEɛ4 carriers with low AD-GRS. CONCLUSIONS: APOEɛ4 carriers with high AD-GRS are at elevated risk of cognitive decline when they also possess higher CA-GRS risk. Genetic risk from both common cognitive aging and AD-related indices may interact in intensification networks to differentially predict (1) level and trajectories of EF decline and (2) potential selective vulnerability for transitions into impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain-Derived Neurotrophic Factor; Canada; Catechol O-Methyltransferase; Clusterin; Cognitive Aging; Cognitive Dysfunction; Executive Function; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Monomeric Clathrin Assembly Proteins; Neuropsychological Tests; Receptors, Complement 3b

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

Neuro-Immuno-Gene- and Genome-Editing-Therapy for Alzheimer's Disease: Are We There Yet? - Raikwar, Sudhanshu P; Thangavel, Ramasamy; Dubova, Iuliia; Ahmed, Mohammad Ejaz; Selvakumar, Pushpavathi Govindhasamy; Kempuraj, Duraisamy; Zaheer, Smita; Iyer, Shankar; Zaheer, Asgar (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a highly complex neurodegenerative disorder and the current treatment strategies are largely ineffective thereby leading to irreversible and progressive cognitive decline in AD patients. AD continues to defy successful treatment despite significant advancements in the field of molecular medicine. Repeatedly, early promising preclinical and clinical results have catapulted into devastating setbacks leading to multi-billion dollar losses not only to the top pharmaceutical companies but also to the AD patients and their families. Thus, it is very timely to review the progress in the emerging fields of gene therapy and stem cell-based precision medicine. Here, we have made sincere efforts to feature the ongoing progress especially in the field of AD gene therapy and stem cell-based regenerative medicine. Further, we also provide highlights in elucidating the molecular mechanisms underlying AD pathogenesis and describe novel AD therapeutic targets and strategies for the new drug discovery. We hope that the quantum leap in the scientific advancements and improved funding will bolster novel concepts that will propel the momentum toward a trajectory leading to a robust AD patient-specific next generation precision medicine with improved cognitive function and excellent life quality.

Neuroprotective Effects of Ginsenoside Rf on Amyloid-β-Induced Neurotoxicity in vitro and in vivo. - Du, Yehong; Fu, Min; Wang, Yu Tian; Dong, Zhifang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the deposition of amyloid-β peptides (Aβ). Aβ accumulation leads to the formation of neurofibrillary tangles, inflammation, axonal injury, synapse loss, and neuronal apoptosis. Thus, reducing Aβ levels should exert a neuroprotective effect against AD. Ginsenoside Rf, an extract from Panax notoginseng, has potent anti-fatigue, anti-nociception, anti-oxidation, and anti-inflammation properties. However, it is unclear whether ginsenoside Rf is effective in the treatment of AD. Here, we reported that ginsenoside Rf could significantly attenuate Aβ-induced apoptosis in N2A cells, as reflected by a dramatic increase in mitochondrial membrane potential and decrease in Ca2 + concentration, reactive oxygen species, and active caspase-3 expression. Meanwhile, ginsenoside Rf could alleviate the Aβ-induced inflammation reaction, such as the decrease of interferon-gamma (IFN-γ) and active caspase-1 expression and the increase of interleukin-13. Furthermore, we also found that Rf is able to accelerate Aβ clearance and subsequently reduces Aβ level in N2A cells stably transfected with human Swedish mutant APP695 (N2A-APP). More importantly, daily Rf treatment (20 mg/kg, i.p.) throughout the experiment dramatically improved spatial learning and memory in Aβ42-induced mouse model of AD. Taken together, these results indicate that ginsenoside Rf may decrease Aβ-induced neurotoxicity and memory decline via anti-inflammatory response during AD development, suggesting that Rf may be a potential therapeutic agent for treating AD.

Neuropsychological Predictors of Long-Term (10 Years) Mild Cognitive Impairment Stability. - Alves, Luísa; Cardoso, Sandra; Maroco, João; de Mendonça, Alexandre; Guerreiro, Manuela; Silva, Dina (J Alzheimers Dis, 2018)
BACKGROUND: Although the diagnosis of mild cognitive impairment (MCI) corresponds to a condition likely to progress to dementia, essentially Alzheimer's disease, longitudinal studies have shown that some patients may not convert to dementia and maintain the diagnosis of MCI even after many years. OBJECTIVES: To determine whether patients that maintain the diagnosis of MCI in the long term (10 years) are really stable or just declining slowly, and to identify clinical and neuropsychological characteristics associated with long-term stability. METHODS: The Cognitive Complaints Cohort (CCC) was searched for MCI cases who maintained that diagnosis for at least 10 years. For each long-term-stable MCI patient, two MCI patients that converted to dementia during follow-up, matched for age and education, were selected from the same database. The baseline and last neuropsychological evaluations for long-term-stable MCI and converter MCI were compared. Baseline neuropsychological predictors of long-term stability were searched for. RESULTS: Long-term-stable MCI (n = 22) and converter MCI (n = 44) patients did not differ in terms of gender distribution, education, age at first assessment and time between symptom onset and first evaluation. Time of follow-up was on average 11 years for long-term-stable MCI and 3 years for converter MCI. The baseline and follow-up neuropsychological tests were not significantly different in long-term-stable MCI patients, whereas a general decline was observed in converter MCI patients. Higher scores on one memory test, the Word Delayed Total Recall, and on the non-verbal abstraction test, Raven's Progressive Matrices, at the baseline predicted long-term (10 years) clinical stability. CONCLUSIONS: Some patients with MCI remain clinically and neuropsychologically stable for a decade. Better performances at baseline in memory and non-verbal abstraction tests predict long-term stability.

NO-Dependent Akt Inactivation by S-Nitrosylation as a Possible Mechanism of STZ-Induced Neuronal Insulin Resistance. - Crunfli, Fernanda; Mazucanti, Caio Henrique; de Moraes, Ruan Carlos Macêdo; Costa, Andressa Pereira; Rodrigues, Alice Cristina; Scavone, Cristoforo; Torrão, Andréa da Silva (J Alzheimers Dis, 2018)
Sporadic Alzheimer's disease (sAD) is associated with energy metabolism deficiency and impairment of insulin receptor (IR) signaling in the brain. In this context, low doses of intracerebroventricular (icv) injection of streptozotocin (STZ) in rodents has been used as an experimental model of sAD which leads to an insulin-resistant brain state and neurodegeneration. However, the STZ effects on brain insulin signaling-related proteins it is not appropriately elucidated. The aim of this study was to evaluate the beginning and progression of alterations in the brain IR pathway of rats after 1, 3, 5, and 7 days of STZ injection and investigate intracellular signaling involved on STZ induced insulin resistance. We observed that STZ injection causes cognitive impairment in the animals, a temporal variation of the insulin signaling-related proteins and apoptosis cell death in the hippocampus. We also have shown that STZ causes insulin resistance and impairment on phosphoinositide 3-kinase (PI3K) activity in the Neuro-2a cells through protein kinase B (Akt) inactivation by S-nitrosylation, which could upregulate GSK3-β activity. STZ ability to cause an insulin-resistant neuron state involves NO production and ROS production which may play an important role in the mechanism linked to STZ-induced neurotoxicity. The icv injection of STZ model and STZ exposed Neuro-2a cells may be potential experimental models for assessing molecules related to the pathogenesis of sAD.

Non-Genetic Risk Factors for Degenerative and Vascular Young Onset Dementia: Results from the INSPIRED and KGOW Studies. - Cations, Monica; Draper, Brian; Low, Lee-Fay; Radford, Kylie; Trollor, Julian; Brodaty, Henry; Sachdev, Perminder; Gonski, Peter; Broe, Gerald Anthony; Withall, Adrienne (J Alzheimers Dis, 2018)
BACKGROUND: Several brain reserve, vascular risk, and other modifiable factors have been associated with late-onset dementia, but their association with young onset dementia (YOD) has not been adequately explored. OBJECTIVE: To examine the association of cognitive reserve enhancing factors, cardiovascular risk factors (including smoking), depression, alcohol use, and traumatic brain injury (TBI) with non-autosomal dominant degenerative and/or vascular YOD. METHODS: Data for this matched case-control study were taken from two larger studies conducted in NSW, Australia. One comprised all people with YOD within a geographical region, while the other exclusively included Aboriginal and Torres Strait Islander participants. Dementia diagnosis was confirmed by clinical consensus, and risk exposure was retrospectively self- and/or informant-reported. RESULTS: Participants were 96 people with YOD (58.4% with probable Alzheimer's disease) and 175 age-group, sex, and sample matched control participants. Poor educational attainment, low participation in cognitive leisure activity, stroke, transient ischemic attack, and self-reported very heavy alcohol use were related to the risk of primary degenerative and/or vascular YOD. The effect of hypertension and depression varied depending on when they occurred relative to dementia onset. Current smoking was significantly associated with risk in univariate analyses but did not retain significance in multivariate modelling. There was no association with hypercholesterolemia, diabetes, or TBI of any kind. Some compensation for low educational attainment was possible via a complex occupation later in life. CONCLUSION: Non-genetic factors have a role in YOD, though the relative importance of each factor may be different to late onset dementia. The timing and severity of exposure, as well as the potential for compensation with later protective exposures, are important considerations for potential prevention strategies.

Nutritional Intervention as a Preventive Approach for Cognitive-Related Outcomes in Cognitively Healthy Older Adults: A Systematic Review. - Solfrizzi, Vincenzo; Agosti, Pasquale; Lozupone, Madia; Custodero, Carlo; Schilardi, Andrea; Valiani, Vincenzo; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; Lamanna, Angela; Stallone, Roberta; Bellomo, Antonello; et al. (J Alzheimers Dis, 2018)
The link diet-cognitive function/dementia has been largely investigated in observational studies; however, there was a lack of evidence from randomized clinical trials (RCTs) on the prevention of late-life cognitive disorders though dietary intervention in cognitively healthy older adults. In the present article, we systematically reviewed RCTs published in the last four years (2014-2017) exploring nutritional intervention efficacy in preventing the onset of late-life cognitive disorders and dementia in cognitively healthy subjects aged 60 years and older using different levels of investigation (i.e., dietary pattern changes/medical food/nutraceutical supplementation/multidomain approach and dietary macro- and micronutrient approaches) as well as possible underlying mechanisms of nutritional prevention. From the 35 included RCTs, there was moderate evidence that intervention through dietary pattern changes, medical food/nutraceutical supplementation, and multidomain approach improved specific cognitive domains or cognitive-related blood biomarkers. There was high evidence that protein supplementation improved specific cognitive domains or functional status in prefrail older adults without effect.

An Objective Method to Accurately Measure Cardiorespiratory Fitness in Older Adults Who Cannot Satisfy Widely Used Oxygen Consumption Criteria. - Dougherty, Ryan J; Lindheimer, Jacob B; Stegner, Aaron J; Van Riper, Stephanie; Okonkwo, Ozioma C; Cook, Dane B (J Alzheimers Dis, 2018)
Cardiorespiratory fitness (CRF) is routinely investigated in older adults; however, the most appropriate CRF measure to use for this population has received inadequate attention. This study aimed to 1) evaluate the reliability and validity of the oxygen uptake efficiency slope (OUES) as a sub-maximal measurement of CRF; 2) examine demographic, risk-factor, and exercise testing differences in older adults who satisfied standardized criteria for a peak oxygen consumption (V̇O2peak) test compared to those who did not; and 3) determine the difference between directly measured V̇O2peak values and OUES-predicted V̇O2peak values. One hundred ten enrollees from the Wisconsin Registry for Alzheimer's Prevention participated in this study. Participants performed a graded maximal exercise test and wore an accelerometer for 7 days. For each participant, the OUES was calculated at 75%, 90%, and 100% of exercise duration. V̇O2peak was recorded at peak effort, and one week of physical activity behavior was measured. OUES values calculated at separate relative exercise durations displayed excellent reliability (ICC = 0.995; p < 0.001), and were strongly correlated with V̇O2peak (rrange = 0.801-0.909; p < 0.001). As hypothesized, participants who did not satisfy V̇O2peak criteria were significantly older than those who satisfied criteria (p = 0.049) and attained a directly measured V̇O2peak that was 2.31 mL·kg·min-1 less than the value that was predicted by OUES V̇O2peak (p = 0.003). Older adults are less likely to satisfy V̇O2peak criteria, which results in an underestimation of their CRF. Without adhering to standardized criteria, V̇O2peak measurement error may lead to misinterpretation of CRF and age-related associations. Here, we conclude that OUES is a reliable, valid measurement of CRF which does not require achievement of standardized criteria.
Keywords: Aged; Cardiorespiratory Fitness; Exercise Test; Female; Humans; Male; Middle Aged; Oxygen Consumption; Reproducibility of Results; Wisconsin

Odor Identification Ability Predicts PET Amyloid Status and Memory Decline in Older Adults. - Kreisl, William Charles; Jin, Peng; Lee, Seonjoo; Dayan, Ezra R; Vallabhajosula, Shankar; Pelton, Gregory; Luchsinger, Jose A; Pradhaban, Gnanavalli; Devanand, D P (J Alzheimers Dis, 2018)
BACKGROUND: Odor identification deficits occur in Alzheimer's disease (AD), as measured by the 40-item University of Pennsylvania Smell Identification Test (UPSIT). OBJECTIVE: To determine if UPSIT scores predict amyloid-β (Aβ) status, determined by 11C-Pittsburgh Compound B PET. We also compared UPSIT scores to Aβ status in predicting future memory decline. METHODS: Subjects were recruited into a longitudinal clinical prediction study. We analyzed data from those who had UPSIT, cognitive testing, PIB PET, and at least 12 months' clinical follow-up. Forty-six amnestic mild cognitive impairment patients and 25 cognitively normal controls were included. Amyloid-positivity was defined as composite PIB standardized uptake value ratio >1.5. Logistic regression and Receiver Operating Characteristic Curve analyses tested the predictive utility of impaired olfaction (defined as UPSIT score <35) and amyloid-positivity for memory decline. RESULTS: High UPSIT scores predicted absence of amyloidosis on PET, with negative predictive value of 100%. Positive predictive value of low UPSIT scores on positive Aβ status was only 41%. Both low UPSIT score (OR = 4.301, 95% CI = 1.248, 14.821, p = 0.021) and positive PET scan (OR = 20.898, 95% CI = 2.222, 196.581, p = 0.008) predicted memory decline. CONCLUSION: Individuals with high UPSIT scores are less likely to have cerebral amyloidosis or experience memory decline. Therefore, UPSIT has potential as a screening tool to determine utility of Aβ PET in clinical practice or enrollment in clinical trials. Low UPSIT score is a non-specific marker of neurodegeneration that could indicate further workup in patients with memory complaints.

Optical Depolarization of DCX-Expressing Cells Promoted Cognitive Recovery and Maturation of Newborn Neurons via the Wnt/β-Catenin Pathway. - Zhao, Ming-Liang; Chen, Shi-Jin; Li, Xiao-Hong; Wang, Li-Na; Chen, Feng; Zhong, Shi-Jiang; Yang, Cheng; Sun, Sheng-Kai; Li, Jian-Jun; Dong, Hua-Jiang; Dong, Yue-Qing; Wang, Yi; et al. (J Alzheimers Dis, 2018)
Electrical excitability by membrane depolarization is crucial for survival and maturation of newborn cells in the dentate gyrus of the hippocampus. However, traditional technology for membrane depolarization lacks temporal and spatial precision. Optogenetics can be used to activate channelrhodopsin-2 (ChR2), allowing cationic current to depolarize genetically targeted cells. In this study, we used ChR2-EGFP driven by doublecortin (DCX) to promote survival and maturation of newborn cells in the dentate gyrus after traumatic brain injury (TBI). C57BL/6 mice underwent lateral fluid percussion TBI. TBI mice were transfected with a lentivirus carrying the DCX-ChR2-EGFP gene. We observed that not only immature neurons but also type-2b intermediate progenitor (IPs) and neuroblasts expressed DCX-EGFP, indicating that DCX-expressing newborn cells could provide a long time window for electrical activity regulation. Quantitative results showed that the number of EGFP-expressing cells began to rise at 3 days after TBI and peaked at 9 days after TBI. By optical depolarization of DCX-EGFP-expressing cells between 3 and 12 days, we observed significantly improved cognitive deficits after TBI with enhanced survival and maturation of newborn cells in the dentate gyrus. We also investigated the role of optical depolarization in neural stem cells transfected with a lentivirus carrying the ChR2-DCX-EGFP gene in vitro. By administrating verapamil to block L-type calcium channels, we verified that the up-regulation of MAP2, NeuN, Neurog2, NeuroD1 and GluR2 in newborn cells was mediated by ChR2-elicted depolarization. By using β-catenin inhibitor Dkk1, we demonstrated that optical depolarization of DCX-EGFP-expressing cells facilitated survival and maturation probably through the Wnt/β-catenin signaling cascade.

Outcomes for Hospitalized Older Adults with Down Syndrome in the United States. - Mendiratta, Priya; Wei, Jeanne Y; Dayama, Neeraj; Li, Xiaocong (J Alzheimers Dis, 2018)
BACKGROUND: Patients with Down syndrome (DS) often survive into adulthood. Relatively little information is currently available regarding hospitalization outcomes among mature, older adults with DS. OBJECTIVE: To identify risk factors associated with hospital mortality rates and increased costs for hospitalized older adults with DS. METHODS: Data on hospitalized older adults with DS (≥65 years) were identified from the Nationwide Inpatient Sample database (6) from 2002 through 2012. Multivariate analyses were performed to evaluate risk factors associated with hospital mortality and hospitalization cost in these patients. RESULTS: A total of 2,134 older adults with DS were identified. A temporal increase over the 11-year period was observed in the number of older adults with DS who were hospitalized (trend p < 0.0001). However, the hospital mortality rate and post-hospital discharge to skilled nursing facilities have decreased during the same time period. Risk factors associated with increased hospital mortality included advanced age (70-79 years), female gender, admissions in the western United States, and presence of comorbid conditions (ischemic heart disease, Alzheimer's disease, and cerebrovascular accident). The mean cost was $18,241 (SD $56,105) over the 11-year period. However, no significant temporal changes in costs were noted (trend p = 0.14). CONCLUSIONS: The number of hospitalized elderly Americans with DS has increased over the 11-year period. However, hospital mortality and discharge to skilled nursing facilities have decreased during the same time period. Several demographic and co-morbid factors are associated with increased mortality. No significant differences in temporal trends in costs were noted.

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Parietal Involvement in the Semantic Variant of Primary Progressive Aphasia with Alzheimer's Disease Cerebrospinal Fluid Profile. - Bera, Géraldine; Migliaccio, Raffaella; Michelin, Thibaut; Lamari, Foudil; Ferrieux, Sophie; Nogues, Marie; Bertin, Hugo; Habert, Marie Odile; Dubois, Bruno; Teichmann, Marc; Kas, Aurélie (J Alzheimers Dis, 2018)
Semantic variant of primary progressive aphasia (svPPA) is typically associated with non-Alzheimer's disease (AD) pathology. However, some anatomopathological studies have found AD lesions in those patients. We compared brain perfusion SPECT of 18 svPPA patients with cerebrospinal fluid (CSF) biomarkers indicative of non-AD pathology (svPPA-nonAD) and three svPPA patients with CSF biomarkers indicative of underlying AD (svPPA-AD). All svPPA patients had severe left temporopolar hypoperfusion. SvPPA-nonAD had additional anterior cingulate and mediofrontal hypoperfusion, whereas svPPA-AD had greater left parietal and posterior cingulate involvement. Parietal damage in svPPA constitutes a biomarker for underlying Alzheimer pathology thus refining the classification of this PPA variant.

Pathological Correlates of Cognitive Impairment in The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. - Robinson, Andrew C; Davidson, Yvonne S; Horan, Michael A; Pendleton, Neil; Mann, David M A (J Alzheimers Dis, 2018)
The neuropathological changes responsible for cognitive impairment and dementia remain incompletely understood. Longitudinal studies with a brain donation end point allow the opportunity to examine relationships between cognitive status and neuropathology. We report on the first 97 participants coming to autopsy with sufficient clinical information from The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. This study began in 1983 and recruited 6,542 healthy individuals between 1983 and 1994, 312 of whom consented to brain donation. Alzheimer-type pathology was common throughout the cohort and generally correlated well with cognitive status. However, there was some overlap between cognitive status and measures of Alzheimer pathology with 26% of cognitively intact participants reaching either CERAD B or C, 11% reaching Thal phase 4 or 5, and 29% reaching Braak stage III- VI. Cerebral amyloid angiopathy(CAA), α-synuclein, and TDP-43 pathology was less common, but when present correlated well with cognitive status. Possession of APOEɛ4 allele(s) was associated with more severe Alzheimer-type and CAA pathology and earlier death, whereas possession of APOEɛ2 allele(s) had no effect on pathology but was more common in cognitively intact individuals. The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age cohort is pathologically representative when compared with similar studies. Cognitive impairment in life correlates strongly with all pathologies examined and the APOE status of an individual can affect pathology severity and longevity.

Patient Characteristics and Outcomes Associated with Receiving an Earlier Versus Later Diagnosis of Probable Alzheimer's Disease. - Kirson, Noam Y; Scott Andrews, J; Desai, Urvi; King, Sarah B; Schonfeld, Sophie; Birnbaum, Howard G; Ball, Daniel E; Kahle-Wrobleski, Kristin (J Alzheimers Dis, 2018)
BACKGROUND: Effectiveness of Alzheimer's disease (AD) treatments may depend critically on the timeliness of intervention. OBJECTIVE: To compare characteristics and outcomes of patients diagnosed with probable AD (prAD) based on time elapsed from first onset of cognitive decline. METHODS: Patients with ≥1 prAD diagnosis and ≥1 follow-up visit were selected from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS; 9/2005-6/2015) and stratified based on the time between the perceived onset of cognitive decline at baseline and first prAD diagnosis (i.e., earlier versus later diagnosis). Characteristics at baseline and prAD diagnosis, clinically meaningful progression, and medication use following prAD diagnosis were compared. RESULTS: Median time from perceived onset of cognitive decline to prAD diagnosis was 4.5 years (earlier diagnosis: ≤3.46; later diagnosis: >5.71). Earlier-diagnosed patients (n = 1,476) were younger at baseline (74.3 versus 76.3 years) and had better cognitive and functional scores than later-diagnosed patients (n = 1,474). At first prAD diagnosis, earlier-diagnosed patients had lower mean global Clinical Dementia Rating (CDR) score (0.8 versus 1.1), higher mean Mini-Mental State Examination (MMSE) (22.6 versus 20.0), and lower mean Functional Activities Questionnaire (11.6 versus 17.3). Earlier- and later-diagnosed patients experienced similar time to a decrease of ≥3 points in MMSE (median 23.2 versus 23.1 months, p = 0.83), but earlier-diagnosed patients had longer time to a CDR score of ≥2 points, and longer times to initiation of AD medication and antipsychotic agents (all p < 0.01). CONCLUSION: Earlier prAD diagnosis in NACC data is associated with higher cognitive function and lower functional impairment at diagnosis.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Cohort Studies; Datasets as Topic; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors

Patient Engagement: The Fundació ACE Framework for Improving Recruitment and Retention in Alzheimer's Disease Research. - Boada, Merce; Santos-Santos, Miguel A; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Cañabate, Pilar; Lafuente, Asunción; Abdelnour, Carla; Buendia, Mar; de Dios, Maria José; Morera, Amèrica; Sanabria, Ángela; Campo, Laura; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) research is at a critical time. The global society is increasingly aware of the frightening rate of growth of the human and financial burden caused by this condition and of the urgent need to halt its progression. Consequently, the scientific community holds great responsibility to quickly put in place and optimize the machinery necessary for testing new treatments or interventions. In this context demand for participants for AD research is at an all-time high. In this review, we will focus on a methodological factor that is increasingly recognized as a key factor that shapes trial populations and affects validity of results in clinical trials: patient engagement, recruitment, and retention. We outline specific problems relevant to patient engagement in AD including recruiting enough participants, difficulties in participant retention, ensuring the recruited sample is representative of the general AD population, the burden of screening failures, and new challenges related to recruiting in preclinical disease. To address the urgent need for more research studying the applicability and cost-effectiveness of different recruitment strategies across different settings and nationalities, we describe the Models of Patient Engagement for Alzheimer's Disease (MOPEAD) project, a public-private partnership promoted by the Innovative Medicine Initiative (IMI), which will provide a large multinational quantitative analysis comparing different innovative recruitment models. We also discuss strategies that address each problem and draw on the experience of Fundació ACE to argue that focusing resources on comprehensive AD centers that offer coordinated clinical and social care and participate in basic and clinical research, is an effective and efficient way of implementing many of the discussed strategies.

Patterns of Neuropsychological Dysfunction and Cortical Volume Changes in Logopenic Aphasia. - Owens, Tyler E; Machulda, Mary M; Duffy, Joseph R; Strand, Edythe A; Clark, Heather M; Boland, Sarah; Martin, Peter R; Lowe, Val J; Jack, Clifford R; Whitwell, Jennifer L; Josephs, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychological assessment can add essential information to the characterization of individuals presenting with the logopenic variant of primary progressive aphasia (lvPPA). OBJECTIVE: This study examined the neuropsychological characteristics of lvPPA patients. We also examined differences in regional and whole brain atrophy based on neuropsychological profiles. METHODS: We conducted a hierarchical cluster analysis on memory, executive functioning, and visuospatial neuropsychological test data for 56 individuals with lvPPA. We then compared resultant clusters to left middle temporal, inferior parietal, and superior parietal regions-of-interest using multivariate analysis of covariance. We also performed voxel-level analyses. RESULTS: We identified three clusters characterized as lvPPA with no neurocognitive impairment (n = 5), lvPPA with mild neurocognitive deficits (n = 23), and lvPPA with marked cognitive deficits (n = 28). WAB-AQ was associated with left middle temporal volume. Superior parietal volumes were smaller for the lvPPA group with marked cognitive symptoms compared to the less severe groups. Voxel-level analyses showed greater atrophy in temporal, parietal, lateral occipital, and frontal regions, left worse than right. Age, disease duration, gender, WAB-AQ, and PiB-PET did not account for differences between groups. CONCLUSIONS: LvPPA patients without cognitive deficits in other domains were relatively uncommon while 50% of our sample exhibited pronounced neurocognitive deficits outside the language domain. Pronounced cognitive deficits in lvPPA are associated with widespread atrophy, left worse than right. Our study underscores the importance of examining neuropsychological function in addition to language in patients with lvPPA.

PCSK9 Concentrations in Cerebrospinal Fluid Are Not Specifically Increased in Alzheimer's Disease. - Courtemanche, Hélène; Bigot, Edith; Pichelin, Matthieu; Guyomarch, Béatrice; Boutoleau-Bretonnière, Claire; Le May, Cédric; Derkinderen, Pascal; Cariou, Bertrand (J Alzheimers Dis, 2018)
The role of PCSK9 in Alzheimer's disease (AD) is controversial. We compared cerebrospinal fluid (CSF) PCSK9 concentrations in 36 AD and 31 non-AD patients. CSF PCSK9 levels did not differ between AD and non-AD groups (2.80 versus 2.62 ng/mL). However, PCSK9 CSF levels were increased in AD and non-AD patients with other neurodegenerative process (non-AD ND, n = 20) compared to patients without neurodegenerative disorders (non-ND, n = 11): 2.80 versus 2.30 (p < 0.005) and 2.83 versus 2.30 ng/mL (p = NS), respectively. CSF PCSK9 were positively correlated with AD biomarkers (Aβ1-42, T-tau, and P-tau). PCSK9 concentrations in CSF are increased in neurodegenerative disorders rather than specifically in AD.

Periodontal Pathogens and Associated Intrathecal Antibodies in Early Stages of Alzheimer's Disease. - Laugisch, Oliver; Johnen, Andreas; Maldonado, Alejandra; Ehmke, Benjamin; Bürgin, Walter; Olsen, Ingar; Potempa, Jan; Sculean, Anton; Duning, Thomas; Eick, Sigrun (J Alzheimers Dis, 2018)
BACKGROUND: Recent studies suggest a link between periodontitis and Alzheimer's disease (AD). OBJECTIVE: Verification of the presence of periodontal pathogens and the intrathecal generation of pathogen-specific antibodies in 20 patients with AD and 20 with other forms of dementia (DEM-noAD). METHODS: Clinical periodontal indices were recorded. Cerebrospinal fluid (CSF) was analyzed for total tau protein (T-tau) and amyloid-β (Aβ1-42). In serum and CSF, antibody levels against Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Treponema species were quantified. The presence of selected bacteria and inflammatory biomarkers were determined in periodontium, serum, and CSF. RESULTS: In line with diagnoses, CSF-levels of Aβ1-42 were significantly lower in AD than DEM-noAD patients. Periodontal destruction and inflammation were omnipresent with no difference between groups. P. gingivalis, T. forsythia, and Treponema species were detected in more than 50% of subgingival biofilm samples, but neither in serum nor in the CSF. Elevated levels of anti-pathogen antibodies in CSF of 16 patients (7 AD; 9 DEM-noAD) compared to serum highlight a possibility of the intrathecal immune response to pathogens. There was no significant difference in antibodies levels against selected bacteria in CSF and serum between groups. Multivariate regression analysis and general linear models revealed an association of the T-tau level in AD group with both serum levels of anti-P. gingivalis antibodies and MCP-1/CCL-2. CONCLUSION: Periodontal pathogens may enter the brain and stimulate a local immune response. However, in patients with dementia at the age up to 70 years, periodontal pathogens do not act as a trigger for developing AD.

Personality Modulates the Efficacy of Art Intervention on Chronic Pain in a Population of Patients with Alzheimer's Disease. - Rouch, Isabelle; Pongan, Elodie; Leveque, Yohana; Tillmann, Barbara; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Krolak-Salmon, Pierre; Laurent, Bernard; Dorey, Jean-Michel (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mainly occurs in elderly individuals. Comorbidities and chronic pain are frequent in this population. Previous studies revealed that personality modulates both chronic pain (CP) andADoccurrence and evolution. Moreover, as pain treatments can induce side-effects, non-drugs treatments, such as art interventions, are interesting alternative therapies for decreasing CP in these patients. OBJECTIVE: Our aim was to assess the potential role of personality traits on art intervention efficacy for reducing CP in a population of patients with mild AD. METHODS: Design: multicenter randomized controlled trial. Fifty mild AD patients underwent a 12-week art intervention including singing and painting groups. Personality was assessed with the Big Five Inventory before the sessions. CP was measured with Numeric Rating Scale (NRS) [Usual pain (NRS-U) and most Intense pain (NRS-I)], Simple Visual Scale [Usual pain (SVS-U) and most Intense pain (SVS-I)] and Brief Pain Inventory (BPI) before and after the sessions. The influence of personality traits on CP evolution before and after art intervention was assessed with multiple linear regression models. RESULTS: A positive association was observed between neuroticism and the evolution of three CP measures including NRS-U (B = 0.34, p = 0.01), SVS-U (B = 0.20, p = 0.04), and BPI-U (B = 0.46, p = 0.02) evolution. No significant relationship was observed between neuroticism and NRS-I, SVS-I and BPI-R evolution. CONCLUSIONS: Our findings suggest that neuroticism can decrease the efficacy of group art intervention on pain in patients with mild AD. Individual therapies could be more appropriate for these patients. These results emphasize the interest of taking into account patients' personality before proposing them to participate to a group therapy.

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Physical Activity and Hippocampal Sub-Region Structure in Older Adults with Memory Complaints. - Siddarth, Prabha; Rahi, Berna; Emerson, Natacha D; Burggren, Alison C; Miller, Karen J; Bookheimer, Susan; Lavretsky, Helen; Dobkin, Bruce; Small, Gary; Merrill, David A (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) plays a major role in maintaining cognition in older adults. PA has been shown to be correlated with total hippocampal volume, a memory-critical region within the medial temporal lobe (MTL). However, research on associations between PA and MTL sub-region integrity is limited. OBJECTIVE: To examine the relationship between PA, MTL thickness, and its sub-regions, and cognitive function in non-demented older adults with memory complaints. METHODS: Twenty-nine subjects aged ≥60 years, with memory complaints were recruited for this cross-sectional study. PA was tracked for 7 days using accelerometers, and average number of steps/day determined. Subjects were categorized into two groups: those who walked ≤4000 steps/day (lower PA) and those with >4000 steps/day (higher PA). Subjects received neuropsychological testing and 3T MRI scans. Nonparametric ANCOVAs controlling for age examined differences between the two groups. RESULTS: Twenty-six subjects aged 72.7(8.1) years completed the study. The higher PA group (n = 13) had thicker fusiform gyrus (median difference = 0.11 mm, effect size (ES) = 1.43, p = 0.001) and parahippocampal cortex (median difference = 0.12 mm, ES = 0.93, p = 0.04) compared to the lower PA group. The higher PA group also exhibited superior performance in attention and information-processing speed (median difference = 0.90, ES = 1.61, p = 0.003) and executive functioning (median difference = 0.97, ES = 1.24, p = 0.05). Memory recall was not significantly different between the two groups. CONCLUSION: Older non-demented individuals complaining of memory loss who walked >4000 steps each day had thicker MTL sub-regions and better cognitive functioning than those who walked ≤4000 steps. Future studies should include longitudinal analyses and explore mechanisms mediating hippocampal related atrophy.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Executive Function; Exercise; Female; Geriatric Assessment; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory; Memory Disorders; Middle Aged; Neuropsychological Tests

Phytochemicals from Achillea fragrantissima are Modulators of AβPP Metabolism. - Bartolotti, Nancy; Disouky, Ahmed; Kalinski, Arthur; Elmann, Anat; Lazarov, Orly (J Alzheimers Dis, 2018)
Plant derivatives offer a novel and natural source of therapeutics. The desert plant Achillea fragrantissima (Forssk) Sch. Bip (Af) is characterized by protective antioxidative and anti-inflammatory properties. Here, we examined the effect of two Af-derived phytochemicals on learning and memory, amyloid-β protein precursor (AβPP) metabolism, and tau phosphorylation in the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mouse model. We observed that mice that were injected with the phytochemicals showed a trend of improvement, albeit statistically insignificant, in the Novel Object Recognition task. However, we did not observe improvement in contextual fear conditioning, suggesting that the benefits of treatment may be either indirect or task-specific. In addition, we observed an increase in the full-length form of AβPP in the brains of mice treated with Af-derived phytochemicals. Interestingly, both in vivo and in vitro, there was no change in levels of soluble Aβ, oligomeric Aβ, or the carboxyl terminus fragments of AβPP (APP-CTFs), suggesting that the increase in full length AβPP does not exacerbate AβPP pathology, but may stabilize the full-length form of the molecule. Together, our data suggest that phytochemicals present in Af may have a modest positive impact on the progression of Alzheimer's disease.

Pink1 Regulates Tyrosine Hydroxylase Expression and Dopamine Synthesis. - Lu, Lingling; Jia, Huanzhen; Gao, Ge; Duan, Chunli; Ren, Jing; Li, Yi; Yang, Hui (J Alzheimers Dis, 2018)
PTEN induced putative kinase 1 (PINK1), also known as PARK6, is causally linked to familial Parkinsonism, and heterozygous loss of PINK1 is a risk factor for sporadic Parkinson's disease. However, little is known about its physiological function. Its deficiency was shown to decrease dopamine without significant loss of dopaminergic neurons. We investigated the mechanistic basis for this observation in the present study using dopaminergic MN9D cells. We found that PINK1 knockdown resulted in dopamine content to decrease with suppressed tyrosine hydroxylase expression in cells. Conversely, PINK1 overexpression increased tyrosine hydroxylase protein level. We also found that PINK1 deficiency blocked the nuclear translocation and activity of nuclear receptor-related 1, a transcription factor regulating tyrosine hydroxylase gene expression. These data suggest that PINK1 regulates tyrosine hydroxylase gene expression and dopamine content by modulating the transcriptional activity of nuclear receptor-related 1. Taken together, our results reveal a novel function of PINK1 in dopamine homeostasis.

Positive Feedback Loops in Alzheimer's Disease: The Alzheimer's Feedback Hypothesis. - Doig, Andrew J (J Alzheimers Dis, 2018)
The dominant model for Alzheimer's disease (AD) is the amyloid cascade hypothesis, in which the accumulation of excess amyloid-β (Aβ) leads to inflammation, excess glutamate and intracellular calcium, oxidative stress, tau hyperphosphorylation and tangle formation, neuronal loss, and ultimately dementia. In a cascade, AD proceeds in a unidirectional fashion, with events only affecting downstream processes. Compelling evidence now exists for the presence of positive feedback loops in AD, however, involving oxidative stress, inflammation, glutamate, calcium, and tau. The pathological state of AD is thus a system of positive feedback loops, leading to amplification of the initial perturbation, rather than a linear cascade. Drugs may therefore be effective by targeting numerous points within the loops, rather than concentrating on upstream processes. Anti-inflammatories and anti-oxidants may be especially valuable, since these processes are involved in many loops and hence would affect numerous processes in AD.

Post Traumatic Stress Disorder Heralding the Onset of Semantic Frontotemporal Dementia. - Bonanni, Laura; Franciotti, Raffaella; Martinotti, Giovanni; Vellante, Federica; Flacco, Maria Elena; Di Giannantonio, Massimo; Thomas, Astrid; Onofrj, Marco (J Alzheimers Dis, 2018)
BACKGROUND: Post traumatic stress disorder (PTSD) is associated with cognitive decline. The dementia type following PTSD is unclear. OBJECTIVE: To assess whether PTSD is associated with a specific dementia. METHODS: Prospective study: 46 PTSD patients (DSM-IV-TR) were followed for 6-10 years with clinical, neuropsychological, imaging evaluations for possible development of dementia.Retrospective study:849 dementia patients followed during 1999-2014 (509 Alzheimer's disease, AD; 207 dementia with Lewy bodies, DLB; 90 vascular dementia, VaD; 43 frontotemporal dementia, FTD) and 287 patients with any neurological condition (including patients with/without dementia) were evaluated for the presence of PTSD in their history. RESULTS: Prospective study: 8 patients developed dementia; 1 AD, 1 DLB, 6 semantic FTD (13.0% of the PTSD population). Retrospective study: 38 patients (4.5%) had a history of PTSD; 3.5% of AD, 4.3% of DLB, 14.0% of FTD, 5.6% of VaD. The percentage was higher in FTD than in AD or DLB (χ2 = 10, p = 0.001, and χ2 = 6, p = 0.02). At difference with AD, DLB, or VaD, FTD incidence among dementia patients with PTSD history (38 patients) was higher than in the dementia population overall (16% versus 5%, χ2 = 8, p = 0.005). The impact of possible demographical/clinical confounders (age, gender, MMSE) was excluded by Poisson regression. PTSD prevalence in the comparative group without dementia matched the prevalence in the Italian general population (1.1%). PTSD prevalence in the demented comparative group matched the prevalence in our dementia retrospective cohort, 3.7%). DISCUSSION: PTSD was associated with the development of semantic FTD.

Potential Factors Associated with Cognitive Improvement of Individuals Diagnosed with Mild Cognitive Impairment or Dementia in Longitudinal Studies. - Hadjichrysanthou, Christoforos; McRae-McKee, Kevin; Evans, Stephanie; De Wolf, Frank; Anderson, Roy M (J Alzheimers Dis, 2018)
Despite the progressive nature of Alzheimer's disease and other dementias, it is observed that many individuals that are diagnosed with mild cognitive impairment (MCI) in one clinical assessment, may return back to normal cognition (CN) in a subsequent assessment. Less frequently, such 'back-transitions' are also observed in people that had already been diagnosed with later stages of dementia. In this study, an analysis was performed on two longitudinal cohort datasets provided by 1) the Alzheimer's Disease Neuroimaging Initiative (ADNI) and 2) the National Alzheimer's Coordinating Centre (NACC). The focus is on the observed improvement of individuals' clinical condition recorded in these datasets to explore potential associations with different factors. It is shown that, in both datasets, transitions from MCI to CN are significantly associated with younger age, better cognitive function, and the absence of ApoE ɛ4 alleles. Better cognitive function and in some cases the absence of ApoE ɛ4 alleles are also significantly associated with transitions from types of dementia to less severe clinical states. The effect of gender and education is not clear-cut in these datasets, although highly educated people who reach MCI tend to be more likely to show an improvement in their clinical state. The potential effect of other factors such as changes in symptoms of depression is also discussed. Although improved clinical outcomes can be associated with many factors, better diagnostic tools are required to provide insight into whether such improvements are a result of misdiagnosis, and if they are not, whether they are linked to improvements in the underlying neuropathological condition.

Potential Novel Approaches to Understand the Pathogenesis and Treat Alzheimer's Disease. - Drummond, Eleanor; Goñi, Fernando; Liu, Shan; Prelli, Frances; Scholtzova, Henrieta; Wisniewski, Thomas (J Alzheimers Dis, 2018)
There is growing genetic and proteomic data highlighting the complexity of Alzheimer's disease (AD) pathogenesis. Greater use of unbiased "omics" approaches is being increasingly recognized as essential for the future development of effective AD research, that need to better reflect the multiple distinct pathway abnormalities that can drive AD pathology. The track record of success in AD clinical trials thus far has been very poor. In part, this high failure rate has been related to the premature translation of highly successful results in animal models that mirror only limited aspects of AD pathology to humans. We highlight our recent efforts to increase use of human tissue to gain a better understanding of the AD pathogenesis subtype variety and to develop several distinct therapeutic approaches tailored to address this diversity. These therapeutic approaches include the blocking of the Aβ/apoE interaction, stimulation of innate immunity, and the simultaneous blocking of Aβ/tau oligomer toxicity. We believe that future successful therapeutic approaches will need to be combined to better reflect the complexity of the abnormal pathways triggered in AD pathogenesis.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Prevalence and Determinants of Agonistic Autoantibodies Against α1-Adrenergic Receptors in Patients Screened Positive for Dementia: Results from the Population-Based DelpHi-Study. - Thyrian, Jochen René; Hertel, Johannes; Schulze, Lara N; Dörr, Marcus; Prüss, Harald; Hempel, Petra; Bimmler, Marion; Kunze, Rudolf; Grabe, Hans Jörgen; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to assess promising biomarkers for diagnosis and treatment response in real-life settings. Despite the important role of vascular risk factors, cardiovascular biomarkers have played a minor role in dementia research. Agonistic autoantibodies (agAAB) directed against G-protein-coupled receptors (GPCR) are discussed as modulators of pathology and clinical manifestation. OBJECTIVE: 1) Describe prevalence of agAAB directed against GPCR, especially agABB against α1-adrenergic receptors (α1-AR-agAAB) and agABB directed against β2-adrenergic receptors (β2-AR-agAAB) and 2) identify factors associated with agAAB in people with dementia during routine care. METHODS: Blood samples and data from 95 subjects who screened positive for dementia from a primary care cohort, analyzed using an enzyme-linked immunosorbent assay (ELISA) for detecting agAAB. Sociodemographic and clinical data were assessed, and medical records checked. RESULTS: In 40 (42%) samples, agAAB was detected, with n = 29 (31%) representing α1-AR-agAAB and n = 21 (22%) β2-AR-agAAB. There was no association between the presence of any antibody and a formal diagnosis of dementia. However, patients with coronary heart disease were more likely (OR = 4.23) to have α1-AR-agAAB than those without coronary heart disease. There were no associations between agAAB and age, sex, education, or cognitive impairment. DISCUSSION: For the first time, we show that autoantibodies have a significant prevalence in people with dementia in a routine care setting. Previous findings were restricted to highly selective samples. We replicated the association between α1-AR-agAAB in patients with coronary heart diseases but were not able to find other factors associated with the presence of agAAB.

Prevalence of Dementia and Associated Risk Factors: A Population-Based Study in the Philippines. - Dominguez, Jacqueline; Fe de Guzman, Ma; Reandelar, Macario; Thi Phung, Thien Kieu (J Alzheimers Dis, 2018)
BACKGROUND: The Philippines is experiencing rapid demographic aging and with it, the dementia epidemic. Prevalence of dementia and associated risk factors have not been studied in the Philippines. OBJECTIVES: The study aimed to provide a reliable estimate of dementia prevalence and identify associated risk factors in the Filipino population. METHODS: 1460 participants 60 years and older were randomly selected from the Marikina City's senior registry. A multidisciplinary team (nurse, psychologist, and neurologist) administered a comprehensive assessment to the study population: health history, neurological examination, Geriatric Depression Scale, Neuropsychiatric Inventory, Disability Assessment for Dementia, Alzheimer's Disease 8, and Clinical Dementia Rating Scale. The neurologist analyzed all clinical data to diagnose dementia based on the DSM-IV criteria, Alzheimer's Disease (AD) on the NINCDS-ADRDA criteria, vascular dementia (VaD) on the Hachinski Ischemic Scale, cognitive impairment no dementia (CIND) on a CDR score of 0.5 and not fulfilling DSM-IV criteria for dementia. Risk factors were correlated with dementia prevalence using multivariate binary logistic regression. RESULTS: 1460 persons were randomly selected. 1367 agreed to participate and underwent all assessments. The response rate was 93.6%. Dementia prevalence was found to be 10.6% (95% CI 9.0 to 12.4) with the breakdown 85.5% AD, 11.7% VaD, and 2.7% other dementias. In this population, 82.0% of men and 70.4% of women had at least one cardiovascular risk factor (hypertension, diabetes, dyslipidemia, smoking), which was associated with VaD prevalence but not AD. CONCLUSION: The prevalence of dementia, CIND, and cardiovascular risk factors are high in the Philippines.

Prevalence, Safety, and Effectiveness of Oral Anticoagulant Use in People with and without Dementia or Cognitive Impairment: A Systematic Review and Meta-Analysis. - Fanning, Laura; Ryan-Atwood, Taliesin E; Bell, J Simon; Meretoja, Atte; McNamara, Kevin P; Dārziņš, Pēteris; Wong, Ian C K; Ilomäki, Jenni (J Alzheimers Dis, 2018)
BACKGROUND: Differences in management and outcomes of oral anticoagulant (OAC) use may exist for people with and without dementia or cognitive impairment (CI). OBJECTIVE: To systematically review the prevalence and safety and effectiveness outcomes of OAC use in people with and without dementia or CI. METHODS: MEDLINE, EMBASE, and CINAHL were searched for studies reporting prevalence or safety and effectiveness outcomes of OAC use for people with and without dementia, published between 2000 to September 2017. Study selection, data extraction, and quality assessment were performed by two reviewers. RESULTS: studies met pre-specified inclusion criteria (21 prevalence studies, 6 outcomes studies). People with dementia had 52% lower odds of receiving OAC compared to people without dementia. Mean OAC prevalence was 32% for people with dementia, compared to 48% without dementia. There was no difference in the composite outcome of embolic events, myocardial infarction, and all-cause death between dementia and non-dementia groups (adjusted hazard ratio (HR) 0.72, 95% CI, 0.45-1.14, p = 0.155). Bleeding rate was lower for people without dementia (HR 0.56, 95% CI, 0.37-0.85). Adverse warfarin events were more common for residents of long-term care with dementia (adjusted incidence rate ratio 1.48, 95% CI, 1.20-1.82). Community-dwelling people with dementia treated with warfarin had poorer anticoagulation control than those without dementia (mean time in therapeutic range (TTR) % ±SD, 38±26 (dementia), 61±27 (no dementia), p < 0.0001). CONCLUSION: A lower proportion of people with dementia received oral anticoagulation compared with people without dementia. People with dementia had higher bleeding risk and poorer anticoagulation control when treated with warfarin.

Prodromal Alzheimer's Disease Demonstrates Increased Errors at a Simple and Automated Anti-Saccade Task. - Holden, John G; Cosnard, Alexandre; Laurens, Brice; Asselineau, Julien; Biotti, Damien; Cubizolle, Stéphanie; Dupouy, Sandrine; Formaglio, Maıté; Koric, Lejla; Seassau, Magali; Tilikete, Caroline; Vighetto, Alain; et al. (J Alzheimers Dis, 2018)
Saccade alterations are potential early signs of Alzheimer's disease. However, uncertainty persists in how early and reliably automated saccade recording systems detect impairments. This multicenter pathophysiological case-control transversal study explored saccade execution in carefully diagnosed amnestic mild cognitive impairment patients fulfilling research criteria for prodromal Alzheimer's disease (n = 29), as compared to both aged-matched mild Alzheimer's disease patients (n = 23) and controls (n = 27). Auto-coded saccades from horizontal (gap) vertical (step) stimulus elicited pro-saccades, and anti-saccade (gap) tasks were compared across the 3 groups. Mild cognitive impairment patients committed significantly more anti-saccade errors compared to controls (46.9 versus 24.3%, p < 0.001). Conventional analyses of the auto-coded stimulus elicited saccades parameters did not distinguish the amnestic mild cognitive impairment from controls or the mild Alzheimer's disease group. However, an offline analysis of manually coded saccade latencies, using resampling statistics did reveal subtle differences among the groups. Analysis of the manually coded data revealed that the mild Alzheimer's disease group had a reliably larger self-corrected error-rate than in amnestic mild cognitive impairment and controls (p = 0.003). Analysis of the manually coded saccade latencies, using more sensitive lognormal bootstrap analysis revealed a continuum, from amnestic mild cognitive impairment to mild Alzheimer's disease, of an increased severity of impaired inhibition of stimulus elicited saccades and correct voluntary saccade initiation. Anti-saccade error rates and psychometric measures of executive and several other cognitive functions were moderately and negatively correlated. Overall, inhibitory impairments in stimulus elicited saccades, characteristic of Alzheimer's disease, may be detected early in presumed prodromal patients using a simple, automated anti-saccade task.

The Progression of Dementia and Cognitive Decline in a Dutch 2-Year Cohort Study of People with Young-Onset Dementia. - Gerritsen, Adrie A J; Bakker, Christian; Verhey, Frans R J; Bor, Hans; Pijnenburg, Yolande A L; de Vugt, Marjolein E; Koopmans, Raymond T C M (J Alzheimers Dis, 2018)
BACKGROUND: The progression of dementia in people with young-onset dementia (YOD) is relatively unknown. OBJECTIVE: To investigate the progression of dementia and cognitive decline in the three most common subtypes in YOD and to explore which factors are associated with this course. METHODS: The course of dementia was examined in 198 people with YOD. The primary outcomes were cognitive function, as assessed by the Mini-Mental State Examination (MMSE) and dementia severity, as assessed by the Global Deterioration Scale (GDS). Mixed-model analyses were used to explore factors associated with the course of dementia of the diagnostic sub-types. RESULTS: The mean overall two-year progression of dementia severity was 0.9 GDS points, this was a statistically significant change (p = 0.012) and was not significant different for the three dementia subtypes. The mean overall two-year decline in cognitive function was 1.6 points on the MMSE. The differences in cognitive decline were statistically significant (p = 0.046) among the three diagnosis groups, AD participants showed the greatest decline, of 2.3 points. In addition to lower education (p = 0.010), higher scores on the Neuropsychiatric Inventory (NPI) sub-syndromes psychosis (p < 0.001) and hyperactivity (p = 0.002) were associated with higher rates of cognitive decline. In contrast, higher scores on the NPI affect cluster were associated with lower levels of cognitive decline (p < 0.001). CONCLUSION: Different YOD subtypes show different rates of decline in cognitive functioning, and this decline seems less progressive compared to those observed in studies in late-onset AD. Further research is needed to evaluate whether managing neuropsychiatric symptoms can positively influence the decline of cognitive function.

The Progressive Acalculia Presentation of Parietal Variant Alzheimer's Disease. - Mendez, Mario F; Moheb, Negar; Desarzant, Randy E; Teng, Edmond H (J Alzheimers Dis, 2018)
BACKGROUND: Many patients with early-onset Alzheimer's disease (EOAD; age of onset <65 years) have non-amnestic presentations involving language (logopenic primary progressive aphasia, lvPPA), visuospatial abilities (posterior cortical atrophy, PCA), and even asymmetric symptoms consistent with corticobasal syndrome (CBS). An inferior parietal lobule variant of EOAD commonly presents with progressive difficulty with calculations. METHODS: We reviewed 276 EOAD patients for presentations with predominant acalculia. These patients were diagnosed with clinically probable Alzheimer's disease (AD) verified by positron emission tomography (PET) or cerebrospinal fluid amyloid-β or tau biomarkers. RESULTS: We identified 18 (9M/9F) (6.5%) EOAD patients with progressive acalculia that did not meet most criteria for lvPPA, visual PCA, or CBS. Their ages of onset and presentation were 56.6 (5.0) and 59.4 (6.5), respectively. Their acalculia was consistent with a primary acalculia ("anarithmetia") not explained by language or visuospatial impairments. Many also had anomia (14/18), ideomotor apraxia (13/18), and the complete Gerstmann's syndrome (7/18). Visual analysis of their diverse magnetic resonance imaging disclosed biparietal atrophy, disproportionately worse on the left. CONCLUSIONS: Primary acalculia may be the most common manifestation of an inferior parietal presentation of EOAD affecting the left intraparietal sulcus. This parietal variant also commonly involves progressive anomia, ideomotor apraxia, and other elements of Gerstmann's syndrome. The early recognition of patients with this variant, which is distinguishable from lvPPA, visual PCA, or CBS, would be facilitated by its recognition as a unique subtype of EOAD.

Proteomic Profiling of Mouse Brains Exposed to Blast-Induced Mild Traumatic Brain Injury Reveals Changes in Axonal Proteins and Phosphorylated Tau. - Chen, Mei; Song, Hailong; Cui, Jiankun; Johnson, Catherine E; Hubler, Graham K; DePalma, Ralph G; Gu, Zezong; Xia, Weiming (J Alzheimers Dis, 2018)
Alzheimer's disease (AD), the most prevalent form of dementia, is characterized by two pathological hallmarks: Tau-containing neurofibrillary tangles and amyloid-β protein (Aβ)-containing neuritic plaques. The goal of this study is to understand mild traumatic brain injury (mTBI)-related brain proteomic changes and tau-related biochemical adaptations that may contribute to AD-like neurodegeneration. We found that both phosphorylated tau (p-tau) and the ratio of p-tau/tau were significantly increased in brains of mice collected at 3 and 24 h after exposure to 82-kPa low-intensity open-field blast. Neurological deficits were observed in animals at 24 h and 7 days after the blast using Simple Neuroassessment of Asymmetric imPairment (SNAP) test, and axon/dendrite degeneration was revealed at 7 days by silver staining. Liquid chromatography-mass spectrometry (LC-MS/MS) was used to analyze brain tissue labeled with isobaric mass tags for relative protein quantification. The results from the proteomics and bioinformatic analysis illustrated the alterations of axonal and synaptic proteins in related pathways, including but not being limited to substantia nigra development, cortical cytoskeleton organization, and synaptic vesicle exocytosis, suggesting a potential axonal damage caused by blast-induced mTBI. Among altered proteins found in brains suffering blast, microtubule-associated protein 1B, stathmin, neurofilaments, actin binding proteins, myelin basic protein, calcium/calmodulin-dependent protein kinase, and synaptotagmin I were representative ones involved in altered pathways elicited by mTBI. Therefore, TBI induces elevated phospho-tau, a pathological feature found in brains of AD, and altered a number of neurophysiological processes, supporting the notion that blast-induced mTBI as a risk factor contributes to AD pathogenesis. LC/MS-based profiling has presented candidate target/pathways that could be explored for future therapeutic development.

Psychological and Mnemonic Benefits of Nostalgia for People with Dementia. - Ismail, Sanda; Christopher, Gary; Dodd, Emily; Wildschut, Tim; Sedikides, Constantine; Ingram, Tom A; Jones, Roy W; Noonan, Krist A; Tingley, Danielle; Cheston, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Studies with non-clinical populations show that nostalgia increases psychological resources, such as self-esteem and social connectedness. OBJECTIVES: Our objectives were to find out if the benefits of nostalgia in non-clinical populations generalize to people with dementia and if nostalgia facilitates recall of dementia-related information. METHODS: All three experiments recruited participants with mild or moderate levels of dementia. Experiment 1 tested whether nostalgia (compared to control) enhances psychological resources among 27 participants. Experiment 2 used music to induce nostalgia (compared to control) in 29 participants. Experiment 3 compared recall for self-referent dementia statements among 50 participants randomized to either a nostalgia or control condition. Findings across experiments were synthesized with integrative data analysis. RESULTS: Nostalgia (compared to control) significantly increased self-reported social connectedness, meaning in life, self-continuity, optimism, self-esteem, and positive (but not negative) affect (Experiments 1-3). Compared to controls, nostalgic participants also recalled significantly more self-referent dementia-related information (Experiment 3). CONCLUSION: This series of experiments extends social psychological research with non-clinical populations into dementia care, providing evidence that nostalgia significantly enhances psychological resources. The finding that nostalgia increased recall of self-referent statements about dementia suggests that this emotion lends participants the fortitude to face the threat posed by their illness. The finding has potentially important clinical implications both for the development of reminiscence therapy and for facilitating adjustment to a diagnosis of dementia.

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative Magnetization Transfer of White Matter Tracts Correlates with Diffusion Tensor Imaging Indices in Predicting the Conversion from Mild Cognitive Impairment to Alzheimer's Disease. - Makovac, Elena; Serra, Laura; Di Domenico, Carlotta; Marra, Camillo; Caltagirone, Carlo; Cercignani, Mara; Bozzali, Marco (J Alzheimers Dis, 2018)
Patients with amnestic mild cognitive impairment (aMCI) have higher probability to develop Alzheimer's disease (AD) than elderly controls. The detection of subtle changes in brain structure associated with disease progression and the development of tools to identify patients at high risk for dementia in a short time is crucial. Here, we used probabilistic white matter (WM) tractography to explore microstructural alterations within the main association, limbic, and commissural pathways in aMCI patients who converted to AD after 1 year follow-up (MCIconverters) and those who remained stable (MCIstable). Both diffusion tensor imaging (DTI) and quantitative magnetization transfer (qMT) parameters have been considered for a comprehensive pathophysiological characterization of the WM damage. Overall, tract-specific parameters derived from qMT and DTI at baseline were able to differentiate aMCI patients who converted to AD from those who remained stable in time. In particular, the qMT exchange rate, RMB0, of the right uncinate fasciculus was significantly decreased in MCIconverters, whereas fractional anisotropy was significantly decreased in the bilateral superior cingulum in MCIconverters compared to MCIstable. These results confirm the involvement of WM and particularly of association fibers in the progression of AD, highlighting disconnection as a potential mechanism.

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

Reduced Gray Matter Volume of the Thalamus and Hippocampal Region in Elderly Healthy Adults with no Impact of APOE ɛ4: A Longitudinal Voxel-Based Morphometry Study. - Squarzoni, Paula; Duran, Fabio Luis Souza; Busatto, Geraldo F; Alves, Tania Correa Toledo de Ferraz (J Alzheimers Dis, 2018)
BACKGROUND: Many cross-sectional voxel-based morphometry (VBM) investigations have shown significant inverse correlations between chronological age and gray matter (GM) volume in several brain regions in healthy humans. However, few VBM studies have documented GM decrements in the healthy elderly with repeated MRI measurements obtained in the same subjects. Also, the extent to which the APOE ɛ4 allele influences longitudinal findings of GM reduction in the healthy elderly is unclear. OBJECTIVE: Verify whether regional GM changes are associated with significant decrements in cognitive performance taking in account the presence of the APOE ɛ4 allele. METHODS: Using structural MRI datasets acquired in 55 cognitively intact elderly subjects at two time-points separated by approximately three years, we searched for voxels showing significant GM reductions taking into account differences in APOE genotype. RESULTS: We found global GM reductions as well as regional GM decrements in the right thalamus and left parahippocampal gyrus (p < 0.05, family-wise error corrected for multiple comparisons over the whole brain). These findings were not affected by APOE ɛ4. CONCLUSIONS: Irrespective of APOE ɛ4, longitudinal VBM analyses show that the hippocampal region and thalamus are critical sites where GM shrinkage is greater than the degree of global volume reduction in healthy elderly subjects.
Keywords: Aged; Aging; Apolipoprotein E4; Atrophy; Cross-Sectional Studies; Female; Gray Matter; Healthy Volunteers; Hippocampus; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Organ Size; Thalamus

Regional Distribution, Asymmetry, and Clinical Correlates of Tau Uptake on [18F]AV-1451 PET in Atypical Alzheimer's Disease. - Tetzloff, Katerina A; Graff-Radford, Jonathan; Martin, Peter R; Tosakulwong, Nirubol; Machulda, Mary M; Duffy, Joseph R; Clark, Heather M; Senjem, Matthew L; Schwarz, Christopher G; Spychalla, Anthony J; Drubach, Daniel A; Jack, Clifford R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Despite common pathology, Alzheimer's disease (AD) can have multiple clinical presentations which pathological studies suggest result from differences in the regional distribution of tau pathology. Positron emission tomography (PET) ligands are now available that can detect tau proteins in vivo and hence can be used to investigate the biological mechanisms underlying atypical AD. OBJECTIVE: To assess regional patterns of tau uptake on PET imaging in two atypical AD variants, posterior cortical atrophy (PCA) and logopenic progressive aphasia (lvPPA). METHODS: Eighteen PCA and 19 lvPPA subjects that showed amyloid-β deposition on PET underwent tau-PET imaging with [18F]AV-1451. Group comparisons of tau uptake in PCA and lvPPA were performed using voxel-level and regional-level analyses. We also assessed the degree of lobar tau asymmetry and correlated regional tau uptake to age and performance on clinical evaluations. RESULTS: Both syndromes showed diffuse tau uptake throughout all cortical regions, although PCA showed greater uptake in occipital regions compared to lvPPA, and lvPPA showed greater uptake in left frontal and temporal regions compared to PCA. While lvPPA showed predominant left-asymmetric tau deposition, PCA was more bilateral. Younger subjects showed greater tau uptake bilaterally in frontal and parietal lobes than older subjects, and sentence repetition, Boston naming test, simultanagnosia, and visuoperceptual function showed specific regional tau correlates. CONCLUSION: Tau deposition is closely related to clinical presentation in atypical AD with age playing a role in determining the degree of cortical tau deposition.

Relationship Between Amyloid-β Positivity and Progression to Mild Cognitive Impairment or Dementia over 8 Years in Cognitively Normal Older Adults. - Dang, Christa; Harrington, Karra D; Lim, Yen Ying; Ames, David; Hassenstab, Jason; Laws, Simon M; Yassi, Nawaf; Hickey, Martha; Rainey-Smith, Stephanie; Robertson, Joanne; Sohrabi, Hamid R; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Preclinical Alzheimer's disease (AD) is defined by cerebral amyloid-β positivity (Aβ+) in cognitively normal (CN) older adults. OBJECTIVE: To estimate the risk of progression to the symptomatic stages of AD due to PET Aβ+ and the extent that progression was influenced by other demographic, genetic, and clinical characteristics in a large prospective study. METHODS: Fine-Gray subdistribution modeling was used to examine the risk of progression from CN to MCI/dementia due to Aβ+, APOEɛ4 carriage, and their interaction in the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging CN cohort (n = 599) over 8 years. RESULTS: 17.7% Aβ+ and 8.1% Aβ-progressed over 8 years (OR: 2.43). Risk of progression for Aβ+ was 65-104% greater than Aβ-. Aβ+ APOEɛ4 carriers were at 348% greater risk than all other participants. Significant risk factors of progression in Aβ+ were age (HR: 1.05), PET SUVR (HR: 2.49) and APOE ɛ4 carriage (HR: 2.63); only age was a significant risk factor in Aβ-(HR: 1.09). Aβ-progressors were not near the threshold for Aβ+. These relationships were not moderated by hypertension, diabetes, obesity, or stroke/TIA. CONCLUSION: Aβ+ is an important prognostic marker for progression from CN to MCI/dementia in older adults and APOEɛ4 carriage provides further predictive value in the presence of Aβ+. These data suggest that Aβ-associated clinical progression is consistent with clinical-pathological models of AD, whereas progression in the absence of elevated Aβ deposition may be the result of neuropathological processes other than AD that accumulate with age.

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

Rethinking the Reserve with a Translational Approach: Novel Ideas on the Construct and the Interventions. - Serra, Laura; Gelfo, Francesca; Petrosini, Laura; Di Domenico, Carlotta; Bozzali, Marco; Caltagirone, Carlo (J Alzheimers Dis, 2018)
The concept of brain, cognitive, and neural reserves has been introduced to account for the apparent discrepancies between neurological damage and clinical manifestations. However, these ideas are yet theoretical suggestions that are not completely assimilated in the clinical routine. The mechanisms of the reserves have been extensively studied in neurodegenerative pathologies, in particular in Alzheimer's disease. Both human and animal studies addressed this topic by following two parallel pathways. The specific aim of the present review is to attempt to combine the suggestions derived from the two different research fields to deepen the knowledge about reserves. In fact, the achievement of a comprehensive theoretical framework on reserve mechanisms is an essential step to propose well-timed interventions tailored to the clinical characteristics of patients. The present review highlights the importance of addressing three main aspects: the definition of reserve proxy measures, the interaction between reserve level and therapeutic interventions, and the specific time-window of reserve efficacy.

A Retrospective Belgian Multi-Center MRI Biomarker Study in Alzheimer's Disease (REMEMBER). - Niemantsverdriet, Ellis; Ribbens, Annemie; Bastin, Christine; Benoit, Florence; Bergmans, Bruno; Bier, Jean-Christophe; Bladt, Roxanne; Claes, Lene; De Deyn, Peter Paul; Deryck, Olivier; Hanseeuw, Bernard; Ivanoiu, Adrian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) acquisition/processing techniques assess brain volumes to explore neurodegeneration in Alzheimer's disease (AD). OBJECTIVE: We examined the clinical utility of MSmetrix and investigated if automated MRI volumes could discriminate between groups covering the AD continuum and could be used as a predictor for clinical progression. METHODS: The Belgian Dementia Council initiated a retrospective, multi-center study and analyzed whole brain (WB), grey matter (GM), white matter (WM), cerebrospinal fluid (CSF), cortical GM (CGM) volumes, and WM hyperintensities (WMH) using MSmetrix in the AD continuum. Baseline (n = 887) and follow-up (FU, n = 95) T1-weighted brain MRIs and time-linked neuropsychological data were available. RESULTS: The cohort consisted of cognitively healthy controls (HC, n = 93), subjective cognitive decline (n = 102), mild cognitive impairment (MCI, n = 379), and AD dementia (n = 313). Baseline WB and GM volumes could accurately discriminate between clinical diagnostic groups and were significantly decreased with increasing cognitive impairment. MCI patients had a significantly larger change in WB, GM, and CGM volumes based on two MRIs (n = 95) compared to HC (FU>24months, p = 0.020). Linear regression models showed that baseline atrophy of WB, GM, CGM, and increased CSF volumes predicted cognitive impairment. CONCLUSION: WB and GM volumes extracted by MSmetrix could be used to define the clinical spectrum of AD accurately and along with CGM, they are able to predict cognitive impairment based on (decline in) MMSE scores. Therefore, MSmetrix can support clinicians in their diagnostic decisions, is able to detect clinical disease progression, and is of help to stratify populations for clinical trials.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk Factors Associated with Cortical Thickness and White Matter Hyperintensities in Dementia Free Okinawan Elderly. - Silbert, Lisa C; Lahna, David; Promjunyakul, Nutta-On; Boespflug, Erin; Ohya, Yusuke; Higashiuesato, Yasushi; Nishihira, Junko; Katsumata, Yuriko; Tokashiki, Takashi; Dodge, Hiroko H (J Alzheimers Dis, 2018)
BACKGROUND: Cortical gray matter (GM) and white matter (WM) deterioration are signals of neurodegeneration and increased dementia risk; however, their specific etiologies in dementia-free aging is unclear. OBJECTIVE: The objective of this study was to examine potentially modifiable risk factors of GM and WM degeneration in a well-characterized cohort of dementia-free elderly. METHODS: 96 Okinawan elderly participants (age 83.6) from the Keys to Optimal Cognitive Aging Project (KOCOA) underwent MRI and cognitive evaluation. Serum markers of inflammation (interleukin-6 (IL-6), high sensitivity C-reactive protein), cerebrovascular disease (systolic blood pressure (SBP) 140+, hemoglobin A1C (HgbA1C), total cholesterol), and essential minerals (copper (Cu), magnesium, and calcium) were examined in relation to mean cortical thickness (MCT) and white matter hyperintensities (WMH), adjusting for age and gender. Voxel-based morphometry (VBM) analyses identified relationships between regional GM density and the above markers. RESULTS: Decreased MCT was associated with SBP 140 + (p = 0.029) and increased serum IL-6 (p = 0.036), HgbA1C (p = 0.002), and Cu (p = 0.025). In VBM analyses, increased IL-6, HgbA1C, and Cu were associated with decreased GM density in temporal lobe regions. HgbA1C (p = 0.004) was associated with greater WMH volume. CONCLUSIONS: Peripheral markers of Cu, CVD risk, and inflammation are associated with MRI-markers of decreased brain health in dementia-free Okinawan elderly, with regional cortical thinning in areas involved in early accumulation of Alzheimer's disease pathology. Results identify potentially modifiable biomarkers as targets in the prevention of dementia in older individuals.

Risk of Alzheimer's Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging. - Elias, Alby; Cummins, Tia; Tyrrell, Regan; Lamb, Fiona; Doré, Vincent; Williams, Robert; Rosenfeld, J V; Hopwood, Malcolm; Villemagne, Victor L; Rowe, Christopher C (J Alzheimers Dis, 2018)
BACKGROUND: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-β and tau deposition in this syndrome. OBJECTIVE: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. METHODS: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsychological battery measured cognitive function. Positron emission tomography (PET) was used to measure standardized uptake value ratio (SUVR) of 18F-florbetaben and 18F-AV1451, to quantify amyloid and tau burden. RESULTS: 119 male Vietnam veterans completed assessment. Impairment in visual attention and processing speed and increased body mass index (BMI) were seen in subjects with OSA compared with those without a diagnosis OSA. The cortical uptake of 18F-florbetaben was higher in the OSA group than in the control group (SUVR: 1.35±0.21 versus 1.27±0.16, p = 0.04). There were more apolipoprotein E ɛ4 allele (APOE ɛ4) carriers in the OSA group than in the control group. In multilinear regression analysis, the significance of OSA in predicting 18F-florbetaben uptake remained independent of age and vascular risk factors but not when BMI or APOE ɛ4 was adjusted. The reported use of CPAP (n = 14) had no effect on cognitive or amyloid PET findings. There was no significant difference in 18F-AV1451 uptake between the two groups. CONCLUSIONS: Obstructive sleep apnea is associated with Alzheimer's disease pathology, but this relationship is moderated by APOE ɛ4 and BMI.

Risk of Conversion to Dementia in a Mild Behavioral Impairment Group Compared to a Psychiatric Group and to a Mild Cognitive Impairment Group. - Taragano, Fernando E; Allegri, Ricardo F; Heisecke, Silvina L; Martelli, María I; Feldman, Mónica L; Sánchez, Viviana; García, Virginia A; Tufro, Graciela; Castro, Diego M; Leguizamón, Patricio Perez; Guelar, Verónica; Ruotolo, Eva; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is insufficient available information on behavioral changes in the absence of cognitive impairment as factors increasing the risk of conversion to dementia. OBJECTIVE: To observe and analyze patients with mild behavioral impairment (MBI), mild cognitive impairment (MCI), and a psychiatry group (PG) to compare the risk of progression to dementia. METHODS: From 677 initially assessed ≥60-year-old patients, a series of 348 patients was studied for a five-year period until censoring or conversion to dementia: 96 with MBI, 87 with MCI, and 165 with general psychiatry disorders, including 4 subgroups: Anxiety, Depression, Psychosis and Others. All patients were assessed with clinical, psychiatric, neurological, neuropsychological, and neuroimaging studies. RESULTS: From 348 patients, 126 evolved to dementia (36.2%). Conversion was significantly higher in MBI (71.5%), followed by the MCI-MBI overlap (59.6%) and MCI (37.8%) groups, compared to PG (13.9%) (Log-rank p < 0.001). MCI patients mostly converted to Alzheimer's dementia, while MBI converted to frontotemporal dementia and Lewy body dementia. Patients in PG converted to Lewy body dementia and frontotemporal dementia. CONCLUSION: Conversion to dementia is significantly higher in patients with neuropsychiatric symptoms. The MBI concept generates a new milestone in the refining of diagnosis of neurodegenerative diseases and the possibility of creating neuropsychiatric profiles. Its earlier identification will allow new possibilities for therapeutic intervention.

Role of Amyloid-β and Tau Proteins in Alzheimer's Disease: Confuting the Amyloid Cascade. - Gulisano, Walter; Maugeri, Daniele; Baltrons, Marian A; Fà, Mauro; Amato, Arianna; Palmeri, Agostino; D'Adamio, Luciano; Grassi, Claudio; Devanand, D P; Honig, Lawrence S; Puzzo, Daniela; Arancio, Ottavio (J Alzheimers Dis, 2018)
The "Amyloid Cascade Hypothesis" has dominated the Alzheimer's disease (AD) field in the last 25 years. It posits that the increase of amyloid-β (Aβ) is the key event in AD that triggers tau pathology followed by neuronal death and eventually, the disease. However, therapeutic approaches aimed at decreasing Aβ levels have so far failed, and tau-based clinical trials have not yet produced positive findings. This begs the question of whether the hypothesis is correct. Here we have examined literature on the role of Aβ and tau in synaptic dysfunction, memory loss, and seeding and spreading of AD, highlighting important parallelisms between the two proteins in all of these phenomena. We discuss novel findings showing binding of both Aβ and tau oligomers to amyloid-β protein precursor (AβPP), and the requirement for the presence of this protein for both Aβ and tau to enter neurons and induce abnormal synaptic function and memory. Most importantly, we propose a novel view of AD pathogenesis in which extracellular oligomers of Aβ and tau act in parallel and upstream of AβPP. Such a view will call for a reconsideration of therapeutic approaches directed against Aβ and tau, paving the way to an increased interest toward AβPP, both for understanding the pathogenesis of the disease and elaborating new therapeutic strategies.

Secular Trends in Dementia Prevalence and Incidence Worldwide: A Systematic Review. - Stephan, Blossom C M; Birdi, Ratika; Tang, Eugene Yee Hing; Cosco, Theodore D; Donini, Lorenzo M; Licher, Silvan; Ikram, M Arfan; Siervo, Mario; Robinson, Louise (J Alzheimers Dis, 2018)
BACKGROUND: Time trends for dementia prevalence and incidence rates have been reported over the past seven decades in different countries and some have reported a decline. OBJECTIVE: To undertake a systematic review to critically appraise and provide an evidence-based summary of the magnitude and direction of the global changes in dementia prevalence and incidence across time. METHODS: Medline, EMBASE, and PsychINFO were searched for studies focused on secular trends in dementia prevalence and/or incidence until 18 December 2017. In total, 10,992 articles were identified and 43 retained. RESULTS: Overall, prevalence rates are largely increasing (evidence primarily from record-based surveys and cohort studies in Japan, Canada, and France) or have remained stable (evidence primarily from cohort studies in Sweden, Spain and China). A significant decline in prevalence has however been reported in more recent studies (i.e., from 2010 onwards) from Europe (e.g., UK and Sweden) and the USA. Incidence rates have generally remained stable or decreased in China, Canada, France, Germany, Denmark, Sweden, the Netherlands, UK, and USA. An increase has only been reported in five countries: Italy, Japan, Wales, Germany, and the Netherlands. Only one study reported findings (stability in incidence) from a low and middle-income country using data from Nigeria. CONCLUSIONS: The evidence on secular trends in the prevalence and incidence of dementia is mixed including contradictory findings using different (and in some cases the same) datasets in some countries (e.g., the USA, UK, and Sweden). This making it difficult to draw concrete conclusions. However, declining trends recently observed in some high-income Western countries in the most recent two decades including the UK, USA, and Sweden are encouraging. Updated dementia prevalence and incidence estimates will inform public health and financial planning as well as development of prevention strategies.

Self-Reported Physical Activity is Associated with Tau Burden Measured by Positron Emission Tomography. - Brown, Belinda M; Rainey-Smith, Stephanie R; Doré, Vincent; Peiffer, Jeremiah J; Burnham, Samantha C; Laws, Simon M; Taddei, Kevin; Ames, David; Masters, Colin L; Rowe, Christopher C; Martins, Ralph N; Villemagne, Victor L (J Alzheimers Dis, 2018)
Numerous animal studies have reported exercise reduces the accumulation of Alzheimer's disease pathology, including amyloid-β (Aβ) and tau. Furthermore, we previously reported a relationship between higher levels of physical activity (PA) and lower brain Aβ burden in a human population. The recent advent of tau positron emission tomography (PET) tracers enables us to extend our investigations into the evaluation of the relationship between PA and brain tau burden. Utilizing data from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, we have examined the cross-sectional relationship between habitual PA and PET-quantified tau burden. Forty-three cognitively healthy older adults were categorized into low-moderate PA (LMPA; n = 16) or high PA (HPA; n = 27), based on self-reported PA levels. Tau PET imaging with the AV1451 tracer was conducted on all participants. The LMPA group had significantly higher neocortical tau burden (presented as a z-score; 1.22±1.98), compared to the HPA group (z-score: - 0.28±1.18). The difference between the LMPA and HPA groups was also evident when examining regional tau burden in the temporoparietal cortex and the prefrontal cortex. Our results suggest an association between self-reported PA level and brain tau burden. Future longitudinal and interventional studies utilizing larger samples sizes are vital to further investigate the nature of the relationship between tau and PA.

Serotonin Selective Reuptake Inhibitor Treatment Improves Cognition and Grey Matter Atrophy but not Amyloid Burden During Two-Year Follow-Up in Mild Cognitive Impairment and Alzheimer's Disease Patients with Depressive Symptoms. - Brendel, Matthias; Sauerbeck, Julia; Greven, Sonja; Kotz, Sebastian; Scheiwein, Franziska; Blautzik, Janusch; Delker, Andreas; Pogarell, Oliver; Ishii, Kazunari; Bartenstein, Peter; Rominger, Axel (J Alzheimers Dis, 2018)
Late-life depression, even when of subsyndromal severity, has shown strong associations with mild cognitive impairment (MCI) and Alzheimer's disease (AD). Preclinical studies have suggested that serotonin selective reuptake inhibitors (SSRIs) can attenuate amyloidogenesis. Therefore, we aimed to investigate the effect of SSRI medication on amyloidosis and grey matter volume in subsyndromal depressed subjects with MCI and AD during an interval of two years. 256 cognitively affected subjects (225 MCI/ 31 AD) undergoing [18F]-AV45-PET and MRI at baseline and 2-year follow-up were selected from the ADNI database. Subjects with a positive depression item (DEP(+); n = 73) in the Neuropsychiatric Inventory Questionnaire were subdivided to those receiving SSRI medication (SSRI(+); n = 24) and those without SSRI treatment (SSRI(-); n = 49). Longitudinal cognition (Δ-ADAS), amyloid deposition rate (standardized uptake value, using white matter as reference region (SUVRWM), and changes in grey matter volume were compared using common covariates. Analyses were performed separately in all subjects and in the subgroup of amyloid-positive subjects. Cognitive performance in DEP(+)/SSRI(+) subjects (Δ-ADAS: -5.0%) showed less deterioration with 2-year follow-up when compared to DEP(+)/SSRI(-) subjects (Δ-ADAS: +18.6%, p < 0.05), independent of amyloid SUVRWM at baseline. With SSRI treatment, the progression of grey matter atrophy was reduced (-0.9% versus -2.7%, p < 0.05), notably in fronto-temporal cortex. A slight trend towards lower amyloid deposition rate was observed in DEP(+)/SSRI(+) subjects versus DEP(+)/SSRI(-). Despite the lack of effect to amyloid PET, SSRI medication distinctly rescued the declining cognitive performance in cognitively affected patients with depressive symptoms, and likewise attenuated grey matter atrophy.

Sex Influences the Accuracy of Subjective Memory Complaint Reporting in Older Adults. - Sundermann, Erin E; Edmonds, Emily C; Delano-Wood, Lisa; Galasko, Douglas R; Salmon, David P; Rubin, Leah H; Bondi, Mark W (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) are required when diagnosing amnestic mild cognitive impairment (aMCI), although their relationship with objective memory performance and Alzheimer's disease (AD) pathology remains unclear. We investigated whether the sex of the patient/participant moderates these associations. Participants were 940 normal control (NC) and aMCI participants from the Alzheimer's Disease Neuroimaging Initiative. SMC were assessed via the memory scale of the Everyday Cognition questionnaire. Discrepancy scores were calculated between self- and informant-reports and categorized into "overestimates," "comparable estimates", and "underestimates" of SMC. We conducted linear and logistic regressions to examine the interaction of sex with self- and informant-reported SMC and discrepancy group on the Rey Auditory Verbal Learning Test (RAVLT) Immediate and Delayed Recall and on PET measures of amyloid-β (Aβ) positivity. Diagnosis-stratified analyses were also conducted. Overall, there were sex by self- and informant-reported SMC interactions for Immediate and Delayed Recall. Despite a higher proportion of "overestimates" in women, greater self- and informant-reported SMC showed a stronger relationship to poorer RAVLT scores in women versus men. Diagnosis-stratified analyses revealed that results were driven by aMCI participants. Conversely, overall, greater self- and informant-reported SMC related to greater odds of Aβ positivity regardless of sex. In diagnosis-stratified analyses, only informant-reported SMC related to Aβ positivity in aMCI. Relative to "comparable estimates," "underestimates" of SMC were associated with poorer RAVLT scores across sexes in the overall sample and in aMCI. The predictive utility of self-report SMC may be limited to women in aMCI. Sex differences should be considered when evaluating SMC.
Keywords: Aged; Cognitive Dysfunction; Female; Humans; Logistic Models; Male; Memory Disorders; Mental Recall; Neuropsychological Tests; Self Report; Sex Factors

Single Subject Classification of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Using Anatomical, Diffusion Tensor, and Resting-State Functional Magnetic Resonance Imaging. - Bouts, Mark J R J; Möller, Christiane; Hafkemeijer, Anne; van Swieten, John C; Dopper, Elise; van der Flier, Wiesje M; Vrenken, Hugo; Wink, Alle Meije; Pijnenburg, Yolande A L; Scheltens, Philip; Barkhof, Frederik; Schouten, Tijn M; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Overlapping clinical symptoms often complicate differential diagnosis between patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Magnetic resonance imaging (MRI) reveals disease specific structural and functional differences that aid in differentiating AD from bvFTD patients. However, the benefit of combining structural and functional connectivity measures to-on a subject-basis-differentiate these dementia-types is not yet known. METHODS: Anatomical, diffusion tensor (DTI), and resting-state functional MRI (rs-fMRI) of 30 patients with early stage AD, 23 with bvFTD, and 35 control subjects were collected and used to calculate measures of structural and functional tissue status. All measures were used separately or selectively combined as predictors for training an elastic net regression classifier. Each classifier's ability to accurately distinguish dementia-types was quantified by calculating the area under the receiver operating characteristic curves (AUC). RESULTS: Highest AUC values for AD and bvFTD discrimination were obtained when mean diffusivity, full correlations between rs-fMRI-derived independent components, and fractional anisotropy (FA) were combined (0.811). Similarly, combining gray matter density (GMD), FA, and rs-fMRI correlations resulted in highest AUC of 0.922 for control and bvFTD classifications. This, however, was not observed for control and AD differentiations. Classifications with GMD (0.940) and a GMD and DTI combination (0.941) resulted in similar AUC values (p = 0.41). CONCLUSION: Combining functional and structural connectivity measures improve dementia-type differentiations and may contribute to more accurate and substantiated differential diagnosis of AD and bvFTD patients. Imaging protocols for differential diagnosis may benefit from also including DTI and rs-fMRI.

Social Dysfunction in Older Age and Relationships with Cognition, Depression, and Apathy: The GreatAGE Study. - Lozupone, Madia; Panza, Francesco; Piccininni, Marco; Copetti, Massimiliano; Sardone, Rodolfo; Imbimbo, Bruno P; Stella, Eleonora; D'Urso, Francesca; Barulli, Maria Rosaria; Battista, Petronilla; Grasso, Alessandra; Tortelli, Rosanna; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most studies focused on only one measure of social dysfunction in older age, without proper validation and distinction across different dimensions including subjectivity, structural, and functional aspects. OBJECTIVE: We sought to validate the Social Dysfunction Rating Scale (SDRS) and its factorial structure, also determining the association of SDRS with cognitive functions, global psychopathology, and social deprivation. METHODS: The SDRS was administered to 484 Italian community-dwelling elderly, recruited in the GreatAGE study, a population-based study on aging conducted in Castellana Grotte, Bari, Southern Italy. We determined objective and subjective psychometric properties of SDRS against the gold standard evaluation of social dysfunction according to the Semi-structured Clinical Diagnostic Interview for DSM-IV-TR Axis I Disorders (SCID-I) criterion. RESULTS: The SDRS showed a moderate accuracy with an optimal cut-off of 26 maximized with higher sensitivity (0.74,95% CI:0.63-0.84) than specificity (0.57,95% CI:0.50-0.64). A five-factor structure was carried out and five dimensions of SDRS were identified (loneliness; social isolation; feeling of contribution/uselessness; lack of leisure activities; anxiety for the health). Education and global cognitive functions were inversely correlated to SDRS, while a direct association with global psychopathology, depression, and apathy was found. The prevalence of higher SDRS scores was major in subjects with current psychiatric disorders versus other subjects.∥Conclusion: The SDRS could be a valid instrument to capture both size and quality of social dysfunction, both in subjects with psychiatric disorders and in normal subjects. Several categories of social dysfunction differed only in the degree of health deprivation, not in social or material deprivation.

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Spatial Navigation in the Elderly with Alzheimer's Disease: A Cross-Sectional Study. - Zanco, Marcos; Plácido, Jessica; Marinho, Valeska; Ferreira, José Vinicius; de Oliveira, Felipe; Monteiro-Junior, Renato; Barca, Maria; Engedal, Knut; Laks, Jerson; Deslandes, Andrea (J Alzheimers Dis, 2018)
BACKGROUND: Spatial navigation is a fundamental cognitive ability that allows an individual to maintain independence by facilitating the safe movement from one place to another. It emerges as one of the first deficits in patients with Alzheimer's disease (AD). OBJECTIVE: To compare spatial navigation performance in the healthy elderly and AD patients through use of the Floor Maze Test (FMT)- an easy-to-apply two-dimensional (2D) maze- and determine which cognitive and functional capacities were associated with performance in this task. METHODS: The FMT was administered to 24 AD patients and 36 healthy controls. Spatial navigation was evaluated through the FMT. Functional capacity was evaluated through the Senior Fitness Test battery of tests. Cognitive functions were evaluated through the Mini-Mental State Examination (MMSE), verbal fluency, digit span test, and the Rey Auditory Verbal Learning Test (RAVLT). RESULTS: The group with AD was significantly slower and presented more errors at all stages of the FMT. Planning Time (PT) performance was associated with cardiorespiratory resistance (Step test) and delayed memory according to the RAVLT (R2 = 0.395, p < 0.001). Performance in the Immediate Maze Time (IMT) and Delayed Maze Time (DMT) was associated with global cognitive status (MMSE) (R2 = 0.509) and delayed memory (R2 = 0.540). CONCLUSION: Patients with AD present significant spatial navigation deficits. Their performance on the FMT is influenced by cardiorespiratory capacity, memory, and global cognitive function. As exercise helps to improve executive function and functional capacity, future intervention studies should be carried out to analyze the possible effects of physical exercise on spatial navigation.

Stimulation of SIRT1 Attenuates the Level of Oxidative Stress in the Brains of APP/PS1 Double Transgenic Mice and in Primary Neurons Exposed to Oligomers of the Amyloid-β Peptide. - Dong, Yang-Ting; Cao, Kun; Tan, Long-Chun; Wang, Xiao-Ling; Qi, Xiao-Lan; Xiao, Yan; Guan, Zhi-Zhong (J Alzheimers Dis, 2018)
In the study, we examined whether the silent information regulator 1 (SIRT1) can attenuate oxidative stress in the brains of mice carrying the APP/PS1 double mutation and/or in primary neonatal rat neurons exposed to oligomers of amyloid-β peptide (AβOs). Starting at 4 or 8 months of age, the transgenic mice were treated with resveratrol (RSV, a stimulator of SIRT1) or suramin (an inhibitor) (each 20 mg/kg BW/day) for two months. The primary neurons were exposed to AβOs (0.5 μM) for 48 h and thereafter RSV (20 μM) or suramin (300 mg/ml) for 24 h. Cell viability was assessed by the CCK-8 assay; SIRT1 protein and mRNA determined by western blotting and real-time PCR, respectively; senile plaques examined immunohistochemically; ROS monitored by flow cytometry; and the contents of OH-, H2O2, O2·-, and MDA, and the activities of SOD and GSH-Px measured by standard biochemical procedures. In comparison to wild-type mice or untreated primary neurons, the expression of SIRT1 was significantly lower in the brains of APP/PS1 mice or neurons exposed to AβOs. In these same systems, increased numbers of senile plaques and a high level of oxidative stress were apparent. Interestingly, these two latter changes were attenuated by treatment with RSV, but enhanced by suramin. These findings indicate that SIRT1 may be neuroprotective.

Structural Anatomical Investigation of Long-Term Memory Deficit in Behavioral Frontotemporal Dementia. - Bertoux, Maxime; Flanagan, Emma C; Hobbs, Matthew; Ruiz-Tagle, Amparo; Delgado, Carolina; Miranda, Marcelo; Ibáñez, Agustín; Slachevsky, Andrea; Hornberger, Michael (J Alzheimers Dis, 2018)
Although a growing body of work has shown that behavioral variant frontotemporal dementia (bvFTD) could present with severe amnesia in approximately half of cases, memory assessment is currently the clinical standard to distinguish bvFTD from Alzheimer's disease (AD). Thus, the concept of "relatively preserved episodic memory" in bvFTD remains the basis of its clinical distinction from AD and a criterion for bvFTD's diagnosis. This view is supported by the idea that bvFTD is not characterized by genuine amnesia and hippocampal degeneration, by contrast to AD. In this multicenter study, we aimed to investigate the neural correlates of memory performance in bvFTD as assessed by the Free and Cued Selective Reminding Test (FCSRT). Imaging explorations followed a two-step procedure, first relying on a visual rating of atrophy of 35 bvFTD and 34 AD patients' MRI, contrasted with 29 controls; and then using voxel-based morphometry (VBM) in a subset of bvFTD patients. Results showed that 43% of bvFTD patients presented with a genuine amnesia. Data-driven analysis on visual rating data showed that, in bvFTD, memory recall & storage performances were significantly predicted by atrophy in rostral prefrontal and hippocampal/perihippocampal regions, similar to mild AD. VBM results in bvFTD (pFWE<0.05) showed similar prefrontal and hippocampal regions in addition to striatal and lateral temporal involvement. Our findings showed the involvement of prefrontal as well as medial/lateral temporal atrophy in memory deficits of bvFTD patients. This contradicts the common view that only frontal deficits explain memory impairment in this disease and plead for an updated view on memory dysfunctions in bvFTD.

A Study of Amyloid-β and Phosphotau in Plaques and Neurons in the Hippocampus of Alzheimer's Disease Patients. - Furcila, Diana; DeFelipe, Javier; Alonso-Nanclares, Lidia (J Alzheimers Dis, 2018)
The main pathological hallmarks in Alzheimer's disease (AD) are the presence of extracellular amyloid plaques, primarily consisting of amyloid-β (Aβ) peptide, and the accumulation of paired helical filaments of hyperphosphorylated tau protein (PHF-Tau) within neurons. Since CA1 is one of the most affected regions in AD, mainly at early stages, we have performed a detailed analysis of the CA1 region from 11 AD patients (demented and clinically similar; Braak stages IV-VI) to better understand the possible relationship between the presence and distribution of different neurochemical types of Aβ plaques and PHF-Tau immunoreactive  (- ir)  neurons. Hence, we have examined hippocampal sections in confocal microscopy images from double and triple-immunostained sections, to study labeled plaques and PHF-Tau-ir neurons using specific software tools. There are four main findings in the present study. First, the pyramidal layer of proximal CA1 (close to CA2) contains the smallest number of both plaques and PHF-Tau-ir neurons. Second, a large proportion of Aβ-ir plaques were also characterized by the presence of PHF-Tau-ir. Third, all plaques containing one of the two PHF-Tau isoforms also express the other isoform, that is, if a plaque contains PHFpS396, it also contains PHFAT8, and vice versa. Fourth, the coexpression study of both PHF-Tau isoforms in CA1 neurons revealed that most of the labeled neurons express only PHFpS396. Our findings further support the idea that AD is not a unique entity even within the same neuropathological stage, since the microanatomical/neurochemical changes that occur in the hippocampus greatly vary from one patient to another.

Subjective Cognitive Decline Is Associated with Greater White Matter Hyperintensity Volume. - van Rooden, Sanneke; van den Berg-Huysmans, Annette A; Croll, Pauline H; Labadie, Gerda; Hayes, Jessica M; Viviano, Raymond; van der Grond, Jeroen; Rombouts, Serge A R B; Damoiseaux, Jessica S (J Alzheimers Dis, 2018)
BACKGROUND: Research in older adults with subjective cognitive decline (SCD) has mainly focused on Alzheimer's disease (AD)-related MRI markers, such as hippocampal volume. However, small vessel disease (SVD) is currently established as serious comorbidity in dementia and its preliminary stages. It is therefore important to examine SVD markers in addition to AD markers in older adults presenting with SCD. OBJECTIVE: The aim of our study was to elucidate the role of SVD markers in late middle-aged to older adults with and without SCD in addition to the commonly found role of AD markers (hippocampal volume). METHODS: 67 healthy late middle-aged to older adults participated in this study (mean age 68 years); 25 participants with SCD and 42 participants without SCD. We evaluated quantitative as well as qualitative AD markers (i.e., hippocampal volume and medial temporal lobe atrophy (MTA) scale) and SVD markers (i.e., white matter hyperintensities (WMH) volume, Fazekas scale, microbleeds, and lacunar infarcts), and neuropsychological function and amount of memory complaints. RESULTS: We found a significant effect of SCD on hippocampal atrophy, as assessed using the MTA scale, but not on hippocampal volume. In addition, we found a significant effect of SCD, and amount of memory complaints, on WMH volume and Fazekas score, suggesting larger WMH volumes in participants with SCD. CONCLUSION: SVD MRI markers are related to amount of memory complaints, in addition to the commonly observed AD MRI markers, as demonstrated by the greater WMHs in healthy late middle-aged to older adults with SCD.

Subjective Cognitive Decline Prediction of Mortality: Results from the Einstein Aging Study. - Katz, Mindy J; Wang, Cuiling; Derby, Carol A; Lipton, Richard B; Zimmerman, Molly E; Sliwinski, Martin J; Rabin, Laura A (J Alzheimers Dis, 2018)
BACKGROUND: The relation of pre-dementia stages to mortality has not been fully explored. Previous work examining subjective cognitive decline (SCD) and mortality is limited and mixed regarding methods used and consistency of findings. OBJECTIVE: To examine SCD and mortality in a longitudinal, community-based cohort, using item response theory (IRT) methodology to form a composite SCD measure. Also, to assess whether this relationship was independent of clinical cognitive status. METHODS: The Einstein Aging Study is a diverse longitudinal cohort of adults aged ≥70. SCD items were extracted from baseline CERAD questionnaires and a composite score was formed using IRT methodology. A total of 1,741 participants with complete data were clinically diagnosed as cognitively normal, or as having amnestic mild cognitive impairment (aMCI), nonamnestic mild cognitive impairment (naMCI), or dementia. 645 deaths occurred over a period of 8,912 person-years of follow-up. Cox proportional hazard models predicted time to death adjusting for covariates. RESULTS: A one standard deviation unit increase in level of SCD was associated with >20% higher risk of mortality. However, when models were adjusted for clinical cognitive status, the association was no longer significant. Both dementia and aMCI predicted mortality. Furthermore, when analyses focused only on those without cognitive impairment, SCD level did not predict mortality. CONCLUSIONS: The association of SCD with mortality may be due to the association of SCD with clinical cognitive status. Thus, SCD may be used as a community-based screen to initially identify those with cognitive impairment who may be at greatest risk for death.

A Systematic Review and Meta-Analysis on the Prevalence of Dementia in Europe: Estimates from the Highest-Quality Studies Adopting the DSM IV Diagnostic Criteria. - Bacigalupo, Ilaria; Mayer, Flavia; Lacorte, Eleonora; Di Pucchio, Alessandra; Marzolini, Fabrizio; Canevelli, Marco; Di Fiandra, Teresa; Vanacore, Nicola (J Alzheimers Dis, 2018)
BACKGROUND: Dementia, including Alzheimer's disease (AD), is one of the most burdensome medical conditions. Usually, the reviews that aim at calculating the prevalence of dementia include estimates from studies without assessing their methodological quality. Alzheimer's Disease International (ADI) proposed a score to assess the methodological quality of population-based studies aimed at estimating the prevalence of dementia. During the last three years, the European Commission has funded three projects (Eurodem, EuroCoDe, and ALCOVE) in order to estimate the prevalence of dementia in Europe. OBJECTIVE: The aim of this study was to perform a systematic review and meta-analysis of data on the prevalence of dementia in Europe derived from studies that included only subjects with a diagnosis of dementia according to the DSM IV criteria, and that had a high quality score according to ADI criteria. METHODS: We considered the studies selected by the two projects EuroCoDe (1993-2007) and Alcove (2008-2011), and we performed a new bibliographic search. For the systematic review, we only selected the subset of articles that included subjects with a diagnosis of dementia according to the DSM IV criteria. The studies were qualitatively assessed using the ADI tool. RESULTS: The meta-analysis considered 9 studies that were carried out in Europe between 1993 and 2018 including a total of 18,263 participants, of which 2,137 were diagnosed with dementia. The prevalence rate standardized for age and sex resulted 7.1%. DISCUSSION: This is the first systematic review on the prevalence of dementia in Europe considering only high-quality studies adopting the same diagnostic criteria (i.e., DSM IV).

Targeting Insulin for Alzheimer's Disease: Mechanisms, Status and Potential Directions. - Lee, Jung Hyun; Jahrling, Jordan B; Denner, Larry; Dineley, Kelly T (J Alzheimers Dis, 2018)
Insulin resistance can occur when the body is unable to respond to insulin even in excess. In the brain, insulin manages glucose metabolism in regions such as the hippocampus and plays a key role in directly regulating ERK, a kinase required for the type of memory compromised in early Alzheimer's disease (AD). Human imaging studies show that brain glucose utilization declines with age and is notably impaired in subjects with early AD. Likewise, animal models of AD or insulin resistance, or both, demonstrate that dysfunctional insulin signaling and insulin resistance in the brain have reciprocity with neuroinflammation and aberrant accumulation of amyloid-β (Aβ), pathological hallmarks in AD. As such, the association between brain insulin activity and AD has led to clinical trials testing the efficacy of insulin and insulin-sensitizing drugs to intervene in AD. Based on recent inquiries to ClinicalTrials.gov, we evaluated thirty-three clinical studies related to AD and insulin. The search filtered for interventional clinical trials to test FDA-approved drugs or substances that impinge upon the insulin signaling pathway. Insulin, metformin, and thiazolidinediones were the three main interventions assessed. Overall, these strategies are expected to negate the effects of brain insulin resistance by targeting insulin signaling pathways involved in neuroinflammation, metabolic homeostasis, synaptic functional and structural integrity. The goal of this review is to provide an update on insulin and ERK signaling in relation to memory, its decline in early AD, and provide an overview of clinical trials related to insulin for early AD intervention.

TDP-43 and Alzheimer's Disease Pathologic Subtype in Non-Amnestic Alzheimer's Disease Dementia. - Sahoo, Aradhana; Bejanin, Alexandre; Murray, Melissa E; Tosakulwong, Nirubol; Weigand, Stephen D; Serie, Amanda M; Senjem, Matthew L; Machulda, Mary M; Parisi, Joseph E; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: TDP-43 has been shown to be strongly associated with memory loss, smaller hippocampal volumes, and faster rates of hippocampal atrophy in Alzheimer's disease (AD) patients with an amnestic presentation. Whether TDP-43 has any clinical or anatomical associations in AD patients with non-amnestic phenotype is unknown. OBJECTIVE: To determine whether TDP-43 plays a significant role in the clinic-anatomic features of non-amnestic AD. METHODS: All cases with pathologically confirmed intermediate-high probability AD from 1996-2012 were identified and retrospectively sub-classified into amnestic versus non-amnestic dementia at the time of presentation. Neurofibrillary tangle counts were performed in those with a non-amnestic presentation using thioflavin-S microscopy in the hippocampus and three neocortical regions, and all cases were subtyped into hippocampal-sparing, limbic-predominant, and typical AD pathology. TDP-43 immunoreactivity was used to assess for the presence of TDP-43. Statistical analyses helped determine whether pathologic subtype or TDP-43 was more strongly associated with clinico-imaging features. RESULTS: Out of 172 pathologically confirmed AD cases, 36 (19%) were classified as non-amnestic. Twenty-five of these 36 (69%) had typical pathology, 0 limbic-predominant pathology, and 11 (31%) hippocampal-sparing pathology. Eleven (44%) of the 25 cases with typical pathology were TDP-43+. Of the 11 cases with hippocampal-sparing pathology, 4 (36%) were TDP-43+. There were no differences in demographic, clinical, or neuroimaging features in those with TDP-43 versus those without except for older age at onset (p = 0.02) and age at death (p = 0.02) in those with TDP-43. AD pathological subtype accounted for slightly more of the variances in the neocortex than TDP-43. CONCLUSION: In non-amnestic AD, we find little evidence that clinical or anatomical features of the disease are related to TDP-43.

Testamentary Capacity Assessment Tool (TCAT): A Brief Instrument for Patients with Dementia. - Papageorgiou, Sokratis G; Voskou, Panagiota; Economou, Alexandra; Beratis, Ion; Douzenis, Athanasios (J Alzheimers Dis, 2018)
BACKGROUND: In current practice, it is common for the medical practitioner to assess a person's testamentary capacity (TC) and give evidence to the Courts about a potential will contest. TC is an advanced cognitive activity that is both situation- and task-specific. OBJECTIVE: The aim of the present study was the development of a brief, specialized instrument for TC assessment in patients with dementia. METHOD: We developed a short tool consisting of four subtests, assessing the person's core functions which are required for TC: memory (orientation, autobiographical memory and realistic perception of beneficiaries), absence of serious psychopathology, knowledge of financial parameters (value of assets, everyday life products, bills), and intention (vignettes, theory of mind). For its validation, we examined 64 outpatients from the Cognitive Disorders/Dementia Unit, 2nd Department of Behavioral Neurology, University of Athens. The decision of the expert served as the gold standard for the evaluation of TC. RESULTS: Of the 64 participants, 39 were judged by the expert as capable of TC and the remaining 25 as incapable. For the total scale (maximum score of 48), the best combination of sensitivity (82.6%) and specificity (100%) was obtained for a cut-off score of 32/33. Cronbach's alpha showed high levels of internal reliability for the scale (α= 0.86) and the point-biserial correlation coefficients showed high levels of criterion-related validity (rbp = 0.797, p < 0.001). CONCLUSION: The new instrument appears to be a reliable screening tool for the evaluation of TC in dementia, which can be used by both the expert and the non-expert. Further research is needed to confirm these promising findings.
Keywords: Adult; Aged; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Mental Competency; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Sensitivity and Specificity; Wills

Testing Hippocampal Memory in Prodromal Dementia with Lewy Bodies. - Bussè, Cinzia; Caffarra, Paolo; Rossi, Alice; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Pompanin, Sara; Di Bernardo, Gian Antonio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding test (FCSRT) was used to assess memory in 19 patients with prodromal dementia with Lewy bodies (DLB) and 25 Alzheimer's disease (AD) patients. DLB scored better than AD in selective measures of the FCSRT: immediate total recall (p = 0.01) and index of sensitivity of cueing (p = 0.001), while free delayed and total memory scores were similarly impaired. The index of sensitivity of cueing held a sensitivity of 76% and specificity of 79% in distinguishing DLB. FCSRT could help in disentangling hippocampal memory deficits from memory impairment due to ineffective recall strategies.

TLR4 Gene Expression and Pro-Inflammatory Cytokines in Alzheimer's Disease and in Response to Hippocampal Deafferentation in Rodents. - Miron, Justin; Picard, Cynthia; Frappier, Josée; Dea, Doris; Théroux, Louise; Poirier, Judes (J Alzheimers Dis, 2018)
One important aspect in Alzheimer's disease pathology is the presence of chronic inflammation. Considering its role as a key receptor in the microglial innate immune system, TLR4 was shown to regulate the binding and phagocytosis of amyloid plaques by microglia in several mouse models of amyloidosis, as well as the production of pro-inflammatory cytokines. To our knowledge, TLR4 and its association with cytokines have not been thoroughly examined in the brains of subjects affected with Alzheimer's disease. Using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in postmortem human brains, we observed increased expression for the TLR4 and TNF genes (p = 0.001 and p = 0.025, respectively), as well as a trend for higher IL6 gene expression in the frontal cortex of AD subjects when compared to age-matched controls. Similarly, using a mouse model of hippocampal deafferentation without amyloidosis, (i.e., the entorhinal cortex lesioned mouse), we observed significant increases in the expression of both the Tlr4 (p = 0.0367 and p = 0.0193 compared to sham-lesioned mice or to the contralateral side, respectively) and Il1b (p = 0.0055 and p = 0.0066 compared to sham-lesioned mice or to the contralateral side, respectively) genes in the deafferentation phase, but not during the ensuing reinnervation process. In conclusion, we suggest that the modulation of cytokines by TLR4 is differentially regulated whether by the presence of amyloid plaques or by the ongoing deafferentation process.

Tocotrienol-Rich Fraction of Palm Oil Improves Behavioral Impairments and Regulates Metabolic Pathways in AβPP/PS1 Mice. - Durani, Lina Wati; Hamezah, Hamizah Shahirah; Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Nasaruddin, Muhammad Luqman; Mori, Masaki; Azizan, Kamalrul Azlan; Damanhuri, Hanafi Ahmad; Makpol, Suzana; Wan Ngah, Wan Zurinah; Tooyama, Ikuo (J Alzheimers Dis, 2018)
We have recently shown that the tocotrienol-rich fraction (TRF) of palm oil, a mixture of vitamin E analogs, improves amyloid pathology in vitro and in vivo. However, precise mechanisms remain unknown. In this study, we examined the effects of long-term (10 months) TRF treatment on behavioral impairments and brain metabolites in (15 months old) AβPP/PS1 double transgenic (Tg) Alzheimer's disease (AD) mice. The open field test, Morris water maze, and novel object recognition tasks revealed improved exploratory activity, spatial learning, and recognition memory, respectively, in TRF-treated Tg mice. Brain metabolite profiling of wild-type and Tg mice treated with and without TRF was performed using ultrahigh performance liquid chromatography (UHPLC) coupled to high-resolution accurate mass (HRAM)-orbitrap tandem mass spectrometry (MS/MS). Metabolic pathway analysis found perturbed metabolic pathways that linked to AD. TRF treatment partly ameliorated metabolic perturbations in Tg mouse hippocampus. The mechanism of this pre-emptive activity may occur via modulation of metabolic pathways dependent on Aβ interaction or independent of Aβ interaction.

Translational Research in Alzheimer's and Prion Diseases. - Di Fede, Giuseppe; Giaccone, Giorgio; Salmona, Mario; Tagliavini, Fabrizio (J Alzheimers Dis, 2018)
Translational neuroscience integrates the knowledge derived by basic neuroscience with the development of new diagnostic and therapeutic tools that may be applied to clinical practice in neurological diseases. This information can be used to improve clinical trial designs and outcomes that will accelerate drug development, and to discover novel biomarkers which can be efficiently employed to early recognize neurological disorders and provide information regarding the effects of drugs on the underlying disease biology. Alzheimer's disease (AD) and prion disease are two classes of neurodegenerative disorders characterized by incomplete knowledge of the molecular mechanisms underlying their occurrence and the lack of valid biomarkers and effective treatments. For these reasons, the design of therapies that prevent or delay the onset, slow the progression, or improve the symptoms associated to these disorders is urgently needed. During the last few decades, translational research provided a framework for advancing development of new diagnostic devices and promising disease-modifying therapies for patients with prion encephalopathies and AD. In this review, we provide present evidence of how supportive can be the translational approach to the study of dementias and show some results of our preclinical studies which have been translated to the clinical application following the 'bed-to-bench-and-back' research model.

TTC7 and Hyccin Regulate Neuronal Aβ42 Accumulation and its Associated Neural Deficits in Aβ42-Expressing Drosophila. - Sun, Minghao; Zhao, Yinghui; Han, Men; Zhang, Baozhu; Zhang, Xiao; Zhang, Qichao; Lim, Nastasia K-H; Wang, Wen-An; Huang, Fu-De (J Alzheimers Dis, 2018)
Neuronal amyloid-β (Aβ) accumulation plays an important role in the pathogenesis of Alzheimer's disease (AD). The conformation and toxicity of Aβ are regulated by lipids on the plasma membrane. Previously, we found downregulation of Rolling Blackout (RBO) or phosphatidylinositol-4-kinase type IIIα (PI4KIIIα) reduces neuronal Aβ accumulation and associated neural deficits in a Drosophila model expressing Aβ42. In mammals, the homologs of RBO and PI4KIIIα were reported to form a plasma membrane-localized complex with a scaffold protein TTC7 and cytosolic protein Hyccin/FAM126A to tightly control the plasmalemmal level of phosphatidylinositol-4-phosphate. Here, we show genetic downregulation of Drosophila TTC7 and Hyccin also reduces neuronal Aβ accumulation and associated synaptic and motor defects as well as premature death in Aβ42-expressing flies, while overexpression of TTC7 and Hyccin produced the opposite effect. These results, together with our previous study, demonstrate that RBO/TTC7/PI4KIIIα/Hyccin regulate neuronal Aβ accumulation and associated neural deficits in the Drosophila model, further supporting the RBO/Efr3-PI4KIIIα complex as a potential therapeutic target for AD.

Underlying Biological Processes in Mild Cognitive Impairment: Amyloidosis Versus Neurodegeneration. - Santana, Isabel; Baldeiras, Ines; Santiago, Beatriz; Duro, Diana; Freitas, Sandra; Pereira, Miguel Tábuas; Almeida, Maria Rosário; Oliveira, Catarina Resende (J Alzheimers Dis, 2018)
The amyloid cascade hypothesis proposes amyloid-β (Aβ) as the earliest and key pathological hallmark of Alzheimer's disease (AD), but this mandatory "amyloid-first pathway" has been contested. Longitudinal studies of mild cognitive impairment (MCI) patients represent an opportunity to investigate the intensity of underlying biological processes (amyloidosis versus neurodegeneration) and their relevance for progression to AD. We re-examined our cohort of amnestic MCI, grouped according to cerebrospinal fluid (CSF) biomarkers, aiming at establishing their prognostic value for Alzheimer-type dementia and testing the hypothetical model of biomarkers sequence, based on the amyloid cascade. Our baseline population consisted of 217 MCI patients, 63% with neurodegeneration markers and 47% with amyloidosis. Within the longitudinal study-group (n = 165), 85 progressed to AD and 80 remained cognitively stable. Age, CSF Aβ42, and t-Tau were identified as the best single predictors of conversion to AD. Regarding MCI classification according to the NIA-AA criteria, the high-AD-likelihood group (HL-both amyloid and neurodegeneration markers) was the most frequent (42%); followed by the Suspected Non-Alzheimer Pathophysiology group (SNAP-26%), the low-AD-likelihood group (LL-negative biomarkers-22%), and the Isolated Amyloid Pathology group (IAP-10%). Risk of progression to AD was higher in HL in relation to the LL group (HR = 6.1, 95% CI = 2.1-18.0, p = 0.001). SNAP and IAP groups were equivalent in terms of risk of progression to AD (IAP: HR = 2.6, 95% CI = 0.7-9.3, p = 0.141; SNAP: HR = 3.1, 95% CI = 1.1-9.6; p = 0.046), but only SNAP was significantly different from the LL group. These results support different neurobiological pathways to AD beyond the amyloid hypothesis, highlighting the alternative "neurodegeneration-first pathway" for further investigation.

Urine-Based Biomarkers for Alzheimer's Disease Identified Through Coupling Computational and Experimental Methods. - Yao, Fang; Hong, Xiaoyu; Li, Shuiming; Zhang, Yan; Zhao, Qing; Du, Wei; Wang, Yong; Ni, Jiazuan (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder contributing to nearly 70% of dementia cases. However, no diagnostic protein biomarkers are available in urine. In this study, we combined computational and experimental methods to identify urinary biomarkers for AD. First, by analyzing brain tissue-based gene expression data of AD, 2,754 differentially expressed genes were identified, 559 of which were predicted to encode urine-excretory proteins that might act as candidate protein biomarkers of AD. GO enrichment analyses implied that they were mainly involved in microtubule-based process, myelin sheath, and calcium ion binding, suggesting that they might be associated with AD pathogenesis. In order to verify these proteins in urine, an iTRAQ experiment was carried out to analyze urine samples from AD patients and healthy controls, and 15 proteins were detected. Based on the expression changes of these proteins, 4 proteins were chosen for further validation by ELISA experiment, and SPP1, GSN, and IGFBP7 were found to be differentially expressed in the urine of AD patients. After a literature survey, we found that they were involved in AD pathophysiology and might serve as new urine biomarkers for AD. To our knowledge, this is the first time that urine biomarkers for AD were identified by combining computational and experimental methods. Furthermore, this is the first time SPP1, GSN, and IGFBP7 have been reported as potential urine protein biomarkers for AD. Therefore, our findings might provide significant guidance for finding early biomarkers of AD in urine.

The Use of Mobile Games to Assess Cognitive Function of Elderly with and without Cognitive Impairment. - Bonnechère, Bruno; Van Vooren, Mélissa; Bier, Jean-Christophe; De Breucker, Sandra; Van Hove, Olivier; Van Sint Jan, Serge; Feipel, Véronique; Jansen, Bart (J Alzheimers Dis, 2018)
BACKGROUND: In the past few years numerous mobile games have been developed to train the brain. There is a lack of information about the relation between the scores obtained in these games and the cognitive abilities of the patients. OBJECTIVE: The aim of this study was to determine whether or not mobile games can be used to assess cognitive abilities of elderly. METHODS: Twenty healthy young adults, 29 old patients with cognitive impairments (Mini-Mental State Exam (MMSE) [20- 24]) and 27-aged controls participated in this study. Scores obtained in 7 mobile games were correlated with MMSE and the Addenbrooke's Cognitive Evaluation revised (ACE-R). RESULTS: Statistically significant differences were found for all games between patients with cognitive impairments and the aged controls. Correlations between the average scores of the games and the MMSE and ACE-R are significant (R = 0.72 [p < 0.001] and R = 0.81 [p < 0.001], respectively). CONCLUSION: Scores of cognitive mobile games could be used as an alternative to MMSE and ACE-R to evaluate cognitive function of aged people with and without cognitive impairment at least when MMSE is higher than 20/30.

Utility of Amyloid PET Scans in the Evaluation of Patients Presenting with Diverse Cognitive Complaints. - Shea, Yat-Fung; Barker, Warren; Greig-Gusto, Maria T; Loewenstein, David A; DeKosky, Steven T; Duara, Ranjan (J Alzheimers Dis, 2018)
BACKGROUND: The impact of amyloid positron emission tomography (Aβ-PET) in a "real-world" memory disorders clinic remains poorly studied. OBJECTIVE: We studied the impact of Aβ-PET in diagnosis and management in the memory clinic and factors making the most impact in diagnosis and management. METHODS: We studied 102 patients who had presented at a memory disorders clinic (the Wien Center for Alzheimer's Disease and Memory Disorders, Miami Beach, FL) and had a diagnostic work-up for cognitive complaints, including Aβ-PET scans. RESULTS: Following Aβ-PET, changes were made in diagnosis (37.3%), in specific treatments for Alzheimer's disease (26.5%) and in psychiatric treatments (25.5%). The agreement between diagnosis pre-Aβ-PET versus post-Aβ-PET diagnosis was only fair, with a Cohen's kappa of 0.23 (95% CI 0-0.42). Patients with MRI findings suggestive of AD (medial temporal and/or parietal atrophy) were more frequently amyloid positive than amyloid negative (66.2% versus 33.8%, p = 0.04). Among patients with atypical clinical features for AD, but with MRI findings suggestive of AD, an amyloid negative PET scan had a greater impact than an amyloid positive PET scan on diagnosis (84.2% versus 17.1%, p < 0.001), management (84.2% versus 40%, p < 0.01) and discussion of results and advice on lifestyle (73.7% versus 22.9%, p < 0.001). CONCLUSIONS: We conclude that MRI features suggestive of AD predict a positive amyloid PET scan. However, among those with MRI features suggestive of AD but with atypical clinical features of AD, the clinical impact on diagnosis and management is greater for an amyloid negative than an amyloid positive Aβ-PET scans.

Utility of the LIBRA Index in Relation to Cognitive Functioning in a Clinical Health Seeking Sample. - Pons, Anke; LaMonica, Haley M; Mowszowski, Loren; Köhler, Sebastian; Deckers, Kay; Naismith, Sharon L (J Alzheimers Dis, 2018)
BACKGROUND: Dementia prevalence is expected to increase substantially over the next few decades. Since there is currently no cure for dementia available, there is an urgent need for the early identification of individuals at high risk for dementia, so that primary and secondary prevention strategies can be implemented. Recently, the LIfestyle for BRAin health (LIBRA) index was developed as a new dementia risk algorithm. It specifically focuses on modifiable risk and protective factors that can be targeted in midlife. OBJECTIVE: The objective of this study was to evaluate the LIBRA index in relation to markers of cognitive functioning in a clinical, health-seeking sample of community-based older adults. METHODS: 484 participants (mean age 62.7 years) were recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney. Participants underwent comprehensive clinical and neuropsychological assessment and completed a self-report survey pack. Participants were rated via consensus as having either subjective cognitive complaints (SCC) or meeting criteria for mild cognitive impairment (MCI). The LIBRA score was calculated based on 11 available risk and protective factors. RESULTS: 65.4% of the sample met criteria for MCI. People with MCI showed a significantly higher LIBRA score compared to people with SCC. Furthermore, multiple cognitive domains, in particular executive functioning, were associated with a higher LIBRA score, with stronger correlations in people with MCI. CONCLUSION: The LIBRA index might be a useful tool to determine lifestyle-attributable risk of cognitive decline in an older health-seeking population, including people with MCI.

The Vascular Hypothesis of Alzheimer's Disease: A Key to Preclinical Prediction of Dementia Using Neuroimaging. - de la Torre, Jack (J Alzheimers Dis, 2018)
The vascular hypothesis of Alzheimer's disease (VHAD) was proposed 24 years ago from observations made in our laboratory using aging rats subjected to chronic brain hypoperfusion. In recent years, VHAD has become a mother-lode to numerous neuroimaging studies targeting cerebral hemodynamic changes, particularly brain hypoperfusion in elderly patients at risk of developing Alzheimer's disease (AD). There is a growing consensus among neuroradiologists that brain hypoperfusion is likely involved in the pathogenesis of AD and that disturbed cerebral blood flow (CBF) can serve as a key biomarker for predicting conversion of mild cognitive impairment to AD. The use of cerebral hypoperfusion as a preclinical predictor of AD is becoming decisive in stratifying low and high risk patients that may develop cognitive decline and for assessing the effectiveness of therapeutic interventions. There is currently an international research drive from neuroimaging groups to seek new perspectives that can broaden our understanding of AD and improve lifestyle. Diverse neuroimaging methods are currently being used to monitor normal and dyscognitive brain activity. Some techniques are very powerful and can detect, diagnose, quantify, prognose, and predict cognitive decline before AD onset, even from a healthy cognitive state. Multimodal imaging offers new insights in the treatment and prevention of cognitive decline during advanced aging and better understanding of the functional and structural organization of the human brain. This review discusses the impact the VHAD and CBF are having on the neuroimaging technology that can usher practical strategies to help prevent AD.

Ventral Tegmental Area in Prodromal Alzheimer's Disease: Bridging the Gap between Mice and Humans. - D'Amelio, Marcello; Serra, Laura; Bozzali, Marco (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a progressive neurological disorder characterized by several cognitive and non-cognitive symptoms, with episodic memory being the earliest and most prominently impaired cognitive function. Dopaminergic signals are required for encoding hippocampal memory for new events and the ventral tegmental area (VTA), together with the locus coeruleus, are the primary sources of dopamine acting on dopaminergic receptors in the hippocampus. With this in mind, a recent study on a validated mouse model of AD highlighted on the hippocampal dysfunction and its correlation with an early degeneration of dopaminergic neurons in the VTA. In this issue, De Marco and Venneri test the hypothesis that the volume of the VTA nucleus in humans might be associated with cognitive features of AD.

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.

Volume and Connectivity of the Ventral Tegmental Area are Linked to Neurocognitive Signatures of Alzheimer's Disease in Humans. - De Marco, Matteo; Venneri, Annalena (J Alzheimers Dis, 2018)
BACKGROUND: There is an urgent need to identify the earliest biological changes within the neuropathological cascade of Alzheimer's disease (AD) processes. Recent findings in a murine model of AD showed significant preclinical loss of dopaminergic neurons in the ventral tegmental area (VTA), accompanied by reduced hippocampal innervation and declining memory. It is unknown if these observations can be translated in humans. OBJECTIVE: We tested the hypothesis that VTA volume is associated with the typical clinical markers of AD in a cohort of patients and healthy controls. METHODS: Structural and resting state functional MRI scans, and neuropsychological scores were acquired for 51 healthy adults, 30 patients with a diagnosis of mild cognitive impairment, and 29 patients with a diagnosis of AD dementia. VTA volume was quantified together with other control nuclei. The association between nuclei volume, hippocampal size, memory performance, and linguistic-executive skills was tested. The effect of VTA functional connectivity was also tested. RESULTS: VTA size, but not of control nuclei, yielded a strong association with both hippocampal size and memory competence (but not linguistic-executive performance), and this was particularly strong in healthy adults. In addition, functional connectivity between the VTA and hippocampus was significantly associated with both markers of AD. CONCLUSION: Diminished dopaminergic VTA activity may be crucial for the earliest pathological features of AD and might suggest new strategies for early treatment. Memory encoding processes may represent cognitive operations susceptible to VTA neurodegeneration.

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

A 3-Month Aerobic Training Program Improves Brain Energy Metabolism in Mild Alzheimer's Disease: Preliminary Results from a Neuroimaging Study. - Castellano, Christian-Alexandre; Paquet, Nancy; Dionne, Isabelle J; Imbeault, Hélène; Langlois, Francis; Croteau, Etienne; Tremblay, Sébastien; Fortier, Mélanie; Matte, J Jacques; Lacombe, Guy; Fülöp, Tamás; Bocti, Christian; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Aerobic training has some benefits for delaying the onset or progression of Alzheimer's disease (AD). Little is known about the implication of the brain's two main fuels, glucose and ketones (acetoacetate), associated with thesebenefits. OBJECTIVE: To determine whether aerobic exercise training modifies brain energy metabolism in mild AD. METHODS: In this uncontrolled study, ten patients with mild AD participated in a 3-month, individualized, moderate-intensity aerobic training on a treadmill (Walking). Quantitative measurement of brain uptake of glucose (CMRglu) and acetoacetate (CMRacac) using neuroimaging and cognitive testing were done before and after the Walking program. RESULTS: Four men and six women with an average global cognitive score (MMSE) of 26/30 and an average age of 73 y completed the Walking program. Average total distance and treadmill speed were 8 km/week and 4 km/h, respectively. Compared to the Baseline, after Walking, CMRacac was three-fold higher (0.6±0.4 versus 0.2±0.1 μmol/100 g/min; p = 0.01). Plasma acetoacetate concentration and the blood-to-brain acetoacetate influx rate constant were also increased by 2-3-fold (all p≤0.03). CMRglu was unchanged after Walking (28.0±0.1 μmol/100 g/min; p = 0.96). There was a tendency toward improvement in the Stroop-color naming test (-10% completion time, p = 0.06). Performance on the Trail Making A&B tests was also directly related to plasma acetoacetate and CMRacac (all p≤0.01). CONCLUSION: In mild AD, aerobic training improved brain energy metabolism by increasing ketone uptake and utilization while maintaining brain glucose uptake, and could potentially be associated with some cognitive improvement.

A 9-microRNA Signature in Serum Serves as a Noninvasive Biomarker in Early Diagnosis of Alzheimer's Disease. - Guo, Rui; Fan, Gang; Zhang, Jian; Wu, Chunxiao; Du, Yifeng; Ye, Hui; Li, Zhang; Wang, Lili; Zhang, Zhihui; Zhang, Lu; Zhao, Yueran; Lu, Zhiming (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of age-related neurodegenerative disorder; nevertheless, nowadays there are no reliable biomarkers or non-invasive techniques available for its early detection. Recent studies have indicated that the circulating level profiles of microRNAs (miRNAs) have the potential to be used as valuable biomarkers for diagnosis, staging, and progress monitoring of various diseases. Here we report a novel 9-miRNA signature (hsa-miR-26a-5p, hsa-miR-181c-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-148b-5p, hsa-miR-106b-3p, hsa-miR-6119-5p, hsa-miR-1246, and hsa-miR-660-5p) that can be utilized as biomarker for detecting AD. We respectively profiled the serum miRNAs from 19 AD patients and 9 healthy control (HC) participants using the Next-Generation Sequencing (NGS). The NGS results were validated by quantitative real-time polymerase chain reaction (qRT-PCR) on a larger cohort of 121 AD and 86 HC cases. All the patients were divided into three groups (mild, moderate, and severe AD) based on the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). Our research indicates that abnormal expression of distinct serum miRNAs occurs at different stages of AD. The difference of the area under the receiver operator characteristics curve (AUC) between the AD and the HC is between 70% and 85%. Among the 9 miRNAs, hsa-miR-22-3p has the best sensitivity (81.8%) and specificity (70.9%). The miRNA-panel is more valuable for AD diagnosis. The data suggest that the differentially expressed serum miRNAs could be used as biomarkers to improve the diagnosis of AD, particularly at the early stage, and to classify its clinical stages.

Aberrant Co-localization of Synaptic Proteins Promoted by Alzheimer's Disease Amyloid-β Peptides: Protective Effect of Human Serum Albumin. - Domínguez-Prieto, Marta; Velasco, Ana; Vega, Lourdes; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2017)
Amyloid-β (Aβ), Aβ40, Aβ42, and, recently, Aβ25-35 have been directly implicated in the pathogenesis of Alzheimer's disease. We have studied the effects of Aβ on neuronal death, reactive oxygen species (ROS) production, and synaptic assembling in neurons in primary culture. Aβ25-35, Aβ40, and Aβ42 significantly decreased neuronal viability, although Aβ25-35 showed a higher effect. Aβ25-35 showed a more penetrating ability to reach mitochondria while Aβ40 did not enter the neuronal cytosol and Aβ42 was scarcely internalized. We did not observe a direct correlation between ROS production and cell death because both Aβ40 and Aβ42 decreased neuronal viability but Aβ40 did not change ROS production. Rather, ROS production seems to correlate with the penetrating ability of each Aβ. No significant differences were found between Aβ40 and Aβ42 regarding the extent of the deleterious effects of both peptides on neuronal viability or synaptophysin expression. However, Aβ40 elicited a clear delocalization of PSD-95 and synaptotagmin from prospective synapsis to the neuronal soma, suggesting the occurrence of a crucial effect of Aβ40 on synaptic disassembling. The formation of Aβ40- or Aβ42-serum albumin complexes avoided the effects of these peptides on neuronal viability, synaptophysin expression, and PSD-95/synaptotagmin disarrangement suggesting that sequestration of Aβ by albumin prevents deleterious effects of these peptides. We can conclude that Aβ borne by albumin can be safely transported through body fluids, a fact that may be compulsory for Aβ disposal by peripheral tissues.

Abnormalities of Cortical Neural Synchronization Mechanisms in Subjects with Mild Cognitive Impairment due to Alzheimer's and Parkinson's Diseases: An EEG Study. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Cordone, Susanna; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2017)
The aim of this retrospective and exploratory study was that the cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms might reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and Parkinson's disease (PDMCI) as compared to healthy subjects. Clinical and rsEEG data of 75 ADMCI, 75 PDMCI, and 75 cognitively normal elderly (Nold) subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) was matched between the ADMCI and PDMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROC) classified these sources across individuals. Results showed that compared to the Nold group, the posterior alpha2 and alpha3 source activities were more abnormal in the ADMCI than the PDMCI group, while the parietal delta source activities were more abnormal in the PDMCI than the ADMCI group. The parietal delta and alpha sources correlated with MMSE score and correctly classified the Nold and diseased individuals (area under the ROC = 0.77-0.79). In conclusion, the PDMCI and ADMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test these rsEEG markers for clinical applications and drug discovery.

Acceleration of Amyloidosis by Inflammation in the Amyloid-Beta Marmoset Monkey Model of Alzheimer's Disease. - Philippens, Ingrid H; Ormel, Paul R; Baarends, Guus; Johansson, Maja; Remarque, Ed J; Doverskog, Magnus (J Alzheimers Dis, 2017)
BACKGROUND: The immune system is increasingly mentioned as a potential target for Alzheimer's disease (AD) treatment. OBJECTIVE: In the present pilot study, the effect of (neuro)inflammation on amyloidopathy was investigated in the marmoset monkey, which has potential as an AD animal model due to its natural cerebral amyloidosis similar to humans. METHODS: Six adult/aged marmosets (Callithrix jacchus) were intracranial injected with amyloid-beta (Aβ) fibrils at three cortical locations in the right hemisphere. Additionally, in half of the monkeys, lipopolysaccharide (LPS) was co-injected with the Aβ fibrils and injected in the other hemisphere without Aβ fibrils. The other three monkeys received phosphate buffered saline instead of LPS, as a control for the inflammatory state. The effect of inflammation on amyloidopathy was also investigated in an additional monkey that suffered from chronic inflammatory wasting syndrome. Mirror histology sections were analyzed to assess amyloidopathy and immune reaction, and peripheral blood for AD biomarker expression. RESULTS: All LPS-injected monkeys showed an early AD immune blood cell expression profile on CD95 and CD45RA. Two out of three monkeys injected with Aβ and LPS and the additional monkey, suffering from chronic inflammation, developed plaques. None of the controls, injected with Aβ only, developed any plaques. CONCLUSION: This study shows the importance of immune modulation on the susceptibility for amyloidosis, a hallmark of AD, which offers new perspectives for disease modifying approaches in AD.

Activation of Macrophages and Microglia by Interferon-γ and Lipopolysaccharide Increases Methylglyoxal Production: A New Mechanism in the Development of Vascular Complications and Cognitive Decline in Type 2 Diabetes Mellitus? - Dhananjayan, Karthik; Gunawardena, Dhanushka; Hearn, Nerissa; Sonntag, Tanja; Moran, Chris; Gyengesi, Erika; Srikanth, Velandai; Münch, Gerald (J Alzheimers Dis, 2017)
Methylglyoxal (MGO), a dicarbonyl compound derived from glucose, is elevated in diabetes mellitus and contributes to vascular complications by crosslinking collagen and increasing arterial stiffness. It is known that MGO contributes to inflammation as it forms advanced glycation end products (AGEs), which activate macrophages via the receptor RAGE. The aim of study was to investigate whether inflammatory activation can increase MGO levels, thereby completing a vicious cycle. In order to validate this, macrophage (RAW264.7, J774A.1) and microglial (N11) cells were stimulated with IFN-γ and LPS (5 + 5 and 10 + 10 IFN-γ U/ml or μg/ml LPS), and extracellular MGO concentration was determined after derivatization with 5,6-Diamino-2,4-dihydroxypyrimidine sulfate by HPLC. MGO levels in activated macrophage cells (RAW264.7) peaked at 48 h, increasing 2.86-fold (3.14±0.4 μM) at 5 U/ml IFN-γ+5 μg/ml LPS, and 4.74-fold (5.46±0.30 μM) at 10 U/ml IFN-γ+10 μg/ml LPS compared to the non-activated controls (1.15±0.02 μM). The other two cell lines, J774A.1 macrophages and N11 microglia, showed a similar response. We suggest that inflammation increases MGO production, possibly exacerbating arterial stiffness, cardiovascular complications, and diabetes-related cognitive decline.

Adult-Onset Epilepsy in Presymptomatic Alzheimer's Disease: A Retrospective Study. - DiFrancesco, Jacopo C; Tremolizzo, Lucio; Polonia, Valeria; Giussani, Giorgia; Bianchi, Elisa; Franchi, Carlotta; Nobili, Alessandro; Appollonio, Ildebrando; Beghi, Ettore; Ferrarese, Carlo (J Alzheimers Dis, 2017)
BACKGROUND: The prevalence of epilepsy with onset in adulthood increases with age, mainly due to the accumulation of brain damage. However, a significant proportion of patients experience seizures of unknown cause. Alzheimer's disease (AD) is associated with an increased risk of seizures. Seizure activity is interpreted as a secondary event related to hyperexcitability caused by amyloid-β aggregation. OBJECTIVE: Since neurodegenerative processes begin several years before clinical symptoms, epilepsy could be more frequent in the presymptomatic stages of dementia. METHODS: We retrospectively reviewed the prevalence of epilepsy of unknown origin with adult onset before cognitive decline in a large cohort of AD patients (EPS-AD) recruited based on clinical and neuropsychological data. Data of patients with epilepsy followed by AD were compared with two control groups: patients with AD without seizures (no EPS-AD) and a large reference population (RP). RESULTS: In AD patients, the prevalence of epilepsy of unknown origin, with onset in the adulthood before cognitive decline is 17.1 times higher compared with the RP (95% CI: 10.3-28.3). In EPS-AD, seizures begin on average 4.6 years (median 2.0) before the onset of cognitive symptoms and cognitive decline starts 3.6 years earlier compared with noEPS-AD. CONCLUSIONS: Neurodegenerative processes of dementia could play a key role in the pathogenesis of epilepsy in a subgroup of individuals intended to develop cognitive decline. Adult-onset epilepsy of undefined cause could thus represent a risk factor for the ongoing neurodegenerative damage, even preceding by years the onset of clinical symptoms of dementia.

Aerosol Delivery of Curcumin Reduced Amyloid-β Deposition and Improved Cognitive Performance in a Transgenic Model of Alzheimer's Disease. - McClure, Richard; Ong, Henry; Janve, Vaibhab; Barton, Shawn; Zhu, Meiying; Li, Bo; Dawes, Mary; Jerome, W Gray; Anderson, Adam; Massion, Pierre; Gore, John C; Pham, Wellington (J Alzheimers Dis, 2017)
We report a novel approach for the delivery of curcumin to the brain via inhalation of the aerosol for the potential treatment of Alzheimer's disease. The percentage of plaque fraction in the subiculum and hippocampus reduced significantly when young 5XFAD mice were treated with inhalable curcumin over an extended period of time compared to age-matched nontreated counterparts. Further, treated animals demonstrated remarkably improved overall cognitive function, no registered systemic or pulmonary toxicity associated with inhalable curcumin observed during the course of this work.

Age and Graphomotor Decision Making Assessed with the Digital Clock Drawing Test: The Framingham Heart Study. - Piers, Ryan J; Devlin, Kathryn N; Ning, Boting; Liu, Yulin; Wasserman, Ben; Massaro, Joseph M; Lamar, Melissa; Price, Catherine C; Swenson, Rod; Davis, Randall; Penney, Dana L; Au, Rhoda; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Digital Clock Drawing Test (dCDT) technology enables the examination of detailed neurocognitive behavior as behavior unfolds in real time; a capability that cannot be obtained using a traditional pen and paper testing format. OBJECTIVE: Parameters obtained from the dCDT were used to investigate neurocognitive constructs related to higher-order neurocognitive decision making and information processing speed. The current research sought to determine the effect of age as related to combined motor and non-motor components of drawing, and higher-order decision making latencies. METHODS: A large group of stroke- and dementia- free Framingham Heart Study participants were administered the dCDT to command and copy with hands set for "10 after 11". Six age groups (age range 28-98) were constructed. RESULTS: Differences between age groups were found for total time to completion, total pen stroke count, and higher-order decision making latencies in both command and copy test conditions. CONCLUSION: Longer age-related decision making latencies may reflect a greater need for working memory and increased self-monitoring in older subjects. These latency measures have potential to serve as neurocognitive biomarkers of Alzheimer's disease and other insidious neurodegenerative disorders.

Alterations in the Peripheral Immune System in Dementia. - Busse, Mandy; Michler, Enrico; von Hoff, Franz; Dobrowolny, Henrik; Hartig, Roland; Frodl, Thomas; Busse, Stefan (J Alzheimers Dis, 2017)
Alterations in the immune response that result in inflammation might play a role in the pathology of dementias. In order to analyze changes of the peripheral immune system associated with different types of dementias, we determined several innate and adaptive cell populations in whole blood using flow cytometry. We included patients with Alzheimer's disease (AD; n = 60), vascular dementia (VaD; n = 20), and frontotemporal dementia (FTD; n = 12) at the time point of diagnosis and 24 age-matched neuropsychiatric healthy persons. Monocytes and NK cells were diminished in VaD, but not in AD and FTD. B cell and T cell numbers were decreased in all investigated forms of dementia. Changes in the contribution of naïve/memory T cells were only present in AD. Correlation and regression analyses revealed associations between altered immune cell populations and Q Albumin as marker for the integrity of the blood-cerebrospinal fluid-barrier, Mini-Mental State Examination values, and age. The peripheral immune system is altered in AD, VaD, and FTD. However, each disorder presents unique changes in the investigated cell types indicating different mechanisms underlying the pathology.

Altered Sphingolipid Balance in Capillary Cerebral Amyloid Angiopathy. - de Wit, Nienke M; Snkhchyan, Hripsime; den Hoedt, Sandra; Wattimena, Darcos; de Vos, Rob; Mulder, Monique T; Walter, Jochen; Martinez-Martinez, Pilar; Hoozemans, Jeroen J; Rozemuller, Annemieke J; De Vries, Helga E (J Alzheimers Dis, 2017)
BACKGROUND: The majority of patients with Alzheimer's disease (AD) exhibit amyloid-β (Aβ) deposits at the brain vasculature, a process referred to as cerebral amyloid angiopathy (CAA). In over 51% of AD cases, Aβ also accumulates in cortical capillaries, which is termed capillary CAA (capCAA). It has been postulated that the presence of capCAA in AD is a specific subtype of AD, although underlying mechanisms are not yet fully understood. Sphingolipids (SLs) are implicated in neurodegenerative disorders, including AD. However, to date it remains unknown whether alterations in the SL pathway are involved in capCAA pathogenesis and if these differ from AD. OBJECTIVE: To determine whether AD cases with capCAA have an altered SL profile compared to AD cases without capCAA. METHODS: Immunohistochemistry was performed to assess the expression and localization of ceramide, acid sphingomyelinase (ASM), and sphingosine-1-phosphate receptors (S1P1, S1P3). In addition, we determined the concentrations of S1P as well as different chain-lengths of ceramides using HPLC-MS/MS. RESULTS: Immunohistochemical analysis revealed an altered expression of ceramide, ASM, and S1P receptors by reactive astrocytes and microglial cells specifically associated with capCAA. Moreover, a shift in the balance of ceramides with different chain-lengths and S1P content is observed in capCAA. CONCLUSION: Here we provide evidence of a deregulated SL balance in capCAA. The increased levels of ASM and ceramide in activated glia cells suggest that the SL pathway is involved in the neuroinflammatory response in capCAA pathogenesis. Future research is needed to elucidate the role of S1P in capCAA.

Alzheimer's Disease Biomarkers and Future Decline in Cognitive Normal Older Adults. - Dumurgier, Julien; Hanseeuw, Bernard J; Hatling, Frances B; Judge, Kelly A; Schultz, Aaron P; Chhatwal, Jasmeer P; Blacker, Deborah; Sperling, Reisa A; Johnson, Keith A; Hyman, Bradley T; Gómez-Isla, Teresa (J Alzheimers Dis, 2017)
BACKGROUND: Identifying older adults at risk of cognitive decline represents a challenge as Alzheimer's disease (AD) modifying therapies move toward preclinical stages. OBJECTIVE: To investigate the relationship between AD biomarkers and subsequent change in cognition in a cohort of cognitively intact older adults. METHODS: 84 cognitively normal subjects (mean age 72.0 years, 59% women) were recruited through the Massachusetts Alzheimer's Disease Research Center and the Harvard Aging Brain Study and followed over 3 years. Measurements of amyloid-β 1-42 (Aβ42), total Tau (t-Tau), and Tau phosphorylated at threonine 181 (p-Tau181) in the cerebrospinal fluid (CSF) at study entry were available in all cases. Baseline brain MRI, FDG-PET, and PiB-PET data were available in the majority of participants. Relationship between baseline AD biomarkers and longitudinal change in cognition was assessed using Cox proportional hazard regression and linear mixed models. RESULTS: 14% participants increased their global Clinical Dementia Rating (CDR) score from 0 to 0.5 during follow-up. A CDR score increase was associated with higher baseline CSF t-Tau and p-Tau181, higher global cortical PiB retention, and lower hippocampal volume. The combination of high CSF t-Tau and low Aβ42 or low hippocampal volume was more strongly related to cognitive outcome than each single biomarker. Higher CSF t-Tau was the only biomarker associated with subsequent decline in MMSE score. CONCLUSIONS: Baseline CSF t-Tau and p-Tau181, in vivo amyloid load, and hippocampal volume were all independently associated with future decline in cognition. The discriminatory ability of these biomarkers to predict risk of cognitive decline, however, was only modest.

Alzheimer's Disease Biomarkers Interactively Influence Physical Activity, Mobility, and Cognition Associations in a Non-Demented Aging Population. - Thibeau, Sherilyn; McFall, G Peggy; Camicioli, Richard; Dixon, Roger A (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) risk-reduction strategies (e.g., increasing physical activity, improving mobility) have garnered increasing attention in the literature. However, the effect of such modifiable factors on the preclinical trajectories of brain and cognitive health may be moderated by non-modifiable biomarkers associated with AD. OBJECTIVE: In a longitudinal sample of non-demented older adults, we examine the independent predictors everyday physical activity (EPA) and mobility on executive function (EF) performance and change. Next, we test whether these predictions are modified by interactions between age and AD genetic risk. METHODS: This accelerated longitudinal design included adults (n = 532, M age = 70.4, age range 53-95) from the Victoria Longitudinal Study. We tested the independent effects of EPA and Mobility (i.e., gait, balance), moderation by Apolipoprotein E (i.e., APOEɛ4+, ɛ4-) and age (young-old, middle-old, old-old), and interactions between APOE and age on performance and 9-year change in an EF latent variable. RESULTS: First, higher levels of both EPA and Mobility were associated with better EF performance and less decline. Second, the interaction between age and APOE showed that low EPA and older age was associated with poorer EF performance and steeper EF decline for APOEɛ4 + carriers, and low mobility was associated with poorer EF performance and steeper EF decline for APOEɛ4 + carriers than the non-risk carriers. CONCLUSION: In non-demented older adults, age moderated the effects of both EPA and Mobility on EF performance and change. However, this moderation occurs differentially across APOE4 status.

Alzheimer's Disease Diagnosis Relies on a Twofold Clinical-Biological Algorithm: Three Memory Clinic Case Reports. - Levy Nogueira, Marcel; Samri, Dalila; Epelbaum, Stéphane; Lista, Simone; Suppa, Per; Spies, Lothar; Hampel, Harald; Dubois, Bruno; Teichmann, Marc (J Alzheimers Dis, 2017)
The International Working Group recently provided revised criteria of Alzheimer's disease (AD) proposing that the diagnosis of typical amnesic AD should be established by a clinical-biological signature, defined by the phenotype of an "amnesic syndrome of the hippocampal type" (ASHT) combined with positive in vivo evidence of AD pathophysiology in the cerebrospinal fluid (CSF) or on amyloid PET imaging. The application and clinical value of this refined diagnostic algorithm, initially intended for research purposes, is explored in three memory clinic cases presenting with different cognitive profiles including an ASHT, hippocampal atrophy, and CSF AD-biomarker data. The case reports highlight that the isolated occurrence of one of the two proposed AD criteria, ASHT or positive pathophysiological markers, does not provide a reliable diagnosis of typical AD. It is proposed that the twofold diagnostic IWG algorithm can be applied and operationalized in memory clinic settings to improve the diagnostic accuracy of typical amnesic AD in clinical practice.

Alzheimer's Disease Severity is Not Significantly Associated with Short Sleep: Survey by Actigraphy on 208 Mild and Moderate Alzheimer's Disease Patients. - Leger, Damien; Elbaz, Maxime; Dubois, Alexandre; Rio, Stéphane; Mezghiche, Hocine; Carita, Paulo; Stemmelin, Jeanne; Strauss, Melanie (J Alzheimers Dis, 2017)
BACKGROUND: In epidemiological surveys, cognitive decline has been found to be associated with both short and long sleep duration. OBJECTIVE: Our goal was to objectively determine how total sleep time (TST) at night was associated or not with apathy or severity scores in patients with Alzheimer 's disease (AD). METHODS: During an observational first step of a clinical trial, sleep was assessed in institutionalized patients with mild or moderate AD using actigraphy (MW8, Camtech, Cambridge, UK) for 14 consecutive 24-hour periods. Sleep parameters analyzed were: TST, time in bed (TIB), wake after sleep onset (WASO), sleep efficiency (SE) defined by the ratio TST/TIB, in percentage), the number and length of awakenings, the night fragmentation index, the interdaily stability, and intradaily variability indexes. Statistical association analyses were tested between these values and AD apathy and severity scores. RESULTS: 208 individuals coming from 82 centers worldwide (France, Germany, Spain, Italy, Portugal, Poland, United States, Canada, and Australia) and≥50 years old participated. Their average TST was 7 hours and 35 minutes and the average WASO 58 minutes. TST and SE were significantly higher in patients with apathy and the number of awakenings was significantly lower. TST was also positively associated with functional disability (ADCS-ADL scores), but it was not found significantly greater in patients with a moderate AD severity compared to the mild. CONCLUSION: Despite several and long awakenings, TST was not shorter in patients with AD. TST was even significantly increased with disability and apathy.

Amyloid-Related Imaging Abnormalities in an Aged Squirrel Monkey with Cerebral Amyloid Angiopathy. - Heuer, Eric; Jacobs, Jessica; Du, Rebecca; Wang, Silun; Keifer, Orion P; Cintron, Amarallys F; Dooyema, Jeromy; Meng, Yuguang; Zhang, Xiaodong; Walker, Lary C (J Alzheimers Dis, 2017)
Amyloid-related imaging abnormalities (ARIA) in magnetic resonance imaging scans have emerged as indicators of potentially serious side effects in clinical trials of therapeutics for Alzheimer's disease. These anomalies include an edematous type (ARIA-E) that appears as hyperintense (bright) regions by T2-weighted MRI, and a type characterized by the deposition of hemosiderin (ARIA-H) that elicits a hypointense signal, especially in T2* susceptibility weighted images. ARIA in general has been linked to the presence of amyloid-β (Aβ)-type cerebral amyloid angiopathy, an accumulation of misfolded Aβ protein in the vascular wall that impairs the integrity of brain blood vessels. However, the pathobiology of ARIA remains poorly understood, in part due to the absence of an animal model of the disorder that would enable a contemporaneous analysis of tissue integrity in the affected region. Here we describe both ARIA-E and ARIA-H in an aged squirrel monkey (Saimiri sciureus), a nonhuman primate model of naturally occurring cerebral amyloid angiopathy. Histopathologic examination of the anomalous region revealed reactive astrocytosis and microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition. The disruption of axons in particular suggests that ARIA-E could have functional consequences for affected regions. The squirrel monkey model can be useful for studying the pathogenesis and long-term effects of ARIA, and for testing the safety and efficacy of emerging therapies for Alzheimer's disease.

Anesthesia/Surgery Induces Cognitive Impairment in Female Alzheimer's Disease Transgenic Mice. - Zhang, Ce; Zhang, Yiying; Shen, Yuan; Zhao, Guoqing; Xie, Zhongcong; Dong, Yuanlin (J Alzheimers Dis, 2017)
Anesthesia and/or surgery may promote Alzheimer's disease (AD) by accelerating its neuropathogenesis. Other studies showed different findings. However, the potential sex difference among these studies has not been well considered, and it is unknown whether male or female AD patients are more vulnerable to develop postoperative cognitive dysfunction. We therefore set out to perform a proof of concept study to determine whether anesthesia and surgery can have different effects in male and female AD transgenic (Tg) mice, and in female AD Tg plus Cyclophilin D knockout (CypD KO) mice. The mice received an abdominal surgery under sevoflurane anesthesia (anesthesia/surgery). Fear Conditioning System (FCS) was used to assess the cognitive function. Hippocampal levels of synaptic marker postsynaptic density 95 (PSD-95) and synaptophysin (SVP) were measured using western blot analysis. Here we showed that the anesthesia/surgery decreased the freezing time in context test of FCS at 7 days after the anesthesia/surgery in female, but not male, mice. The anesthesia/surgery reduced hippocampus levels of synaptic marker PSD-95 and SVP in female, but not male, mice. The anesthesia/surgery induced neither reduction in freezing time in FCS nor decreased hippocampus levels of PSD-95 and SVP in the AD Tg plus CypD KO mice. These data suggest that the anesthesia/surgery induced a sex-dependent cognitive impairment and reduction in hippocampus levels of synaptic markers in AD Tg mice, potentially via a mitochondria-associated mechanism. These findings could promote clinical investigations to determine whether female AD patients are more vulnerable to the development of postoperative cognitive dysfunction.

Anomalous White Matter Structure and the Effect of Age in Down Syndrome Patients. - Fenoll, Raquel; Pujol, Jesus; Esteba-Castillo, Susanna; de Sola, Susana; Ribas-Vidal, Núria; García-Alba, Javier; Sánchez-Benavides, Gonzalo; Martínez-Vilavella, Gerard; Deus, Joan; Dierssen, Mara; Novell-Alsina, Ramón; de la Torre, Rafael (J Alzheimers Dis, 2017)
BACKGROUND: Neural tissue alterations in Down syndrome are fully expressed at relatively late developmental stages. In addition, there is an early presence of neurodegenerative changes in the late life stages. OBJECTIVE: The aims of this study were both to characterize white matter abnormalities in the brain of adult Down syndrome patients using diffusion tensor imaging (DTI) and to investigate whether degenerative alterations in white matter structure are detectable before dementia is clinically evident. METHODS: Forty-five adult non-demented Down syndrome patients showing a wide age range (18-52 years) and a matched 45-subject control group were assessed. DTI fractional anisotropy (FA) brain maps were generated and selected cognitive tests were administered. RESULTS: Compared with healthy controls, non-demented Down syndrome patients showed lower DTI FA in white matter involving the major pathways, but with more severe alterations in the frontal-subcortical circuits. White matter FA decreased with age at a similar rate in both DS and control groups. CONCLUSIONS: Our results contribute to characterizing the expression of white matter structural alterations in adult Down syndrome. However, an accelerated aging effect was not demonstrated, which may suggest that the FA measurements used are not sufficiently sensitive or, alternatively, age-related white matter neurodegeneration is not obvious prior to overt clinical dementia.

The Anti-Amyloid-β and Neuroprotective Properties of a Novel Tricyclic Pyrone Molecule. - Maezawa, Izumi; Zou, Bende; Di Lucente, Jacopo; Cao, William S; Pascual, Conrado; Weerasekara, Sahani; Zhang, Man; Xie, Xinmin Simon; Hua, Duy H; Jin, Lee-Way (J Alzheimers Dis, 2017)
There is an urgent unmet need for new therapeutics for Alzheimer's disease (AD), the most common cause of dementia in the elderly. Therapeutic approaches targeting amyloid-β (Aβ) and its downstream toxicities have become major strategies in AD drug development. We have taken a rational design approach and synthesized a class of tricyclic pyrone (TP) compounds that show anti-Aβ and other neuroprotective actions. The in vivo efficacy of a lead TP named CP2 to ameliorate AD-like pathologies has been shown in mouse models. Here we report the selection and initial characterization of a new lead TP70, which exhibited an anti-Aβ therapeutic index even higher than CP2. Moreover, TP70 was able to reduce oxidative stress, inhibit acyl-coenzyme A:cholesterol acyltransferase (ACAT), and upregulate the expression of ATP-binding cassette subfamily A, member 1 (ABCA1), actions considered neuroprotective in AD. TP70 further showed excellent pharmacokinetic properties, including brain penetration and oral availability. When administered to 5xFAD mice via intraperitoneal or oral route, TP70 enhanced the overall solubility and decreased the level of cerebral Aβ, including both fibrillary and soluble Aβ species. Interestingly, TP70 enhanced N-methyl-D-aspartate (NMDA) receptor-mediated excitatory post-synaptic potential (EPSP) in the hippocampal CA1 area, increased the magnitude of NMDA-dependent hippocampal long-term potentiation (LTP), a cellular model of learning and memory, and prevented the Aβ oligomer-impaired LTP. Significantly, a single dose of TP70 administered to aged 5xFAD mice was effective in mitigating the impaired LTP induction, recorded at 24 h after administration. Our results support a potential of TP70 in clinical development for AD in view of its synergistic neuroprotective actions, ability to positively modulate NMDA receptor-mediated hippocampal plasticity, and favorable pharmacokinetic properties in rodents.

Antibodies to Signaling Molecules and Receptors in Alzheimer's Disease are Associated with Psychomotor Slowing, Depression, and Poor Visuospatial Function. - Giil, Lasse M; Vedeler, Christian A; Kristoffersen, Einar K; Nordrehaug, Jan Erik; Heidecke, Harald; Dechend, Ralf; Schulze-Forster, Kai; Muller, Dominik N; von Goetze, Victoria S; Cabral-Marques, Otavio; Riemekasten, Gabriela; Vogelsang, Petra; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with several antibodies as well as signaling molecules and receptors. These may be detrimental in the presence of a disrupted blood-brain barrier (BBB). OBJECTIVE: To investigate whether the levels of antibodies toward 33 signaling molecules involved in neurotransmitter, vascular, and immune functions were associated with AD and, within the AD group; cognitive function and mood. METHODS: Antibodies in sera from patients with mild AD [(n = 91) defined as a Mini-Mental State Examination ≥ 20 or a Clinical Dementia Rating Scale≤1] and healthy controls (n = 102) were measured with enzyme-linked immunosorbent assays. Levels in AD and controls were compared by Mann-Whitney test. In the AD group, associations between antibodies and psychometric test scores were analyzed by robust regression. The false discovery threshold was set to 0.05. RESULTS: Antibodies to serotonin receptors [5-HT2AR (effect size (r) = 0.21, p = 0.004), 5-HT2CR (r = 0.25, p = 0.0005) and 5-HT7R (r = 0.21, p = 0.003)], vascular endothelial growth factor receptor 1 [VEGFR1 (r = 0.29, p < 0.001)] and immune-receptors (Stabilin-1 (r = 0.23, p = 0.001) and C5aR1 (r = 0.21, p = 0.004) were higher in AD. Psychomotor speed was associated with D1R-abs (β 0.49, p < 0.001), depression with ETAR-abs (β 0.31, p < 0.001), and visuospatial function with 5-HT1AR-abs (β 0.27, p = 0.004) despite similar antibody levels compared to controls. CONCLUSIONS: Antibody levels to VEGFR1, serotonergic receptors, and receptors in the immune system were increased in AD. Antibodies at similar levels as in controls were associated cognitive dysfunction and depression in AD.

APOE ε4 Modulation of Training Outcomes in Several Cognitive Domains in a Sample of Cognitively Intact Older Adults. - López-Higes, Ramón; Rodríguez-Rojo, Inmaculada C; Prados, José M; Montejo, Pedro; Del-Río, David; Delgado-Losada, María Luisa; Montenegro, Mercedes; López-Sanz, David; Barabash, Ana (J Alzheimers Dis, 2017)
BACKGROUND: Most research points to the ɛ4 allele of the apolipoprotein E (APOE) gene as the most recognizable genetic risk factor associated with Alzheimer's disease pathogenesis. It has been also suggested that the APOEɛ4 allele has a negative influence on cognitive functioning, which begins long before cognitive impairment becomes manifest. However, still, little is known about the APOEɛ4 interaction with cognitive intervention programs. OBJECTIVE: The main goal of this study was to explore whether there was a differential APOE genotype modulation effect after cognitive training in different domains, such as language comprehension, executive functions, and memory. Contrary to other studies, hippocampal volume was controlled for. METHODS: Fifty older adults (65+ years; 30 women and 20 men) participated in a multi-domain cognitive training that involved 30 sessions taking place over 12 weeks. Half of the participants were APOEɛ4 carriers. The control group was matched in age, gender, normalized hippocampal volume, cognitive reserve, Mini-Mental State Examination score, and Geriatric Depression Scale-Short Version. RESULTS: The study revealed that there were consistent treatment benefits in complex sentence comprehension (noncanonical sentences and sentences with two propositions), a domain that was not directly trained, but only in the A POEɛ4 noncarrier group. CONCLUSION: Genetic profile modulates training outcomes in sentence comprehension.

Apolipoprotein E Isoforms Differentially Regulate Alzheimer's Disease and Amyloid-β-Induced Inflammatory Response in vivo and in vitro. - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (J Alzheimers Dis, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer's disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.

Apolipoprotein E4, Gender, Body Mass Index, Inflammation, Insulin Resistance, and Air Pollution Interactions: Recipe for Alzheimer's Disease Development in Mexico City Young Females. - Calderón-Garcidueñas, Lilian; de la Monte, Suzanne M (J Alzheimers Dis, 2017)
Given the epidemiological trends of increasing Alzheimer's disease (AD) and growing evidence that exposure and lifestyle factors contribute to AD risk and pathogenesis, attention should be paid to variables such as air pollution, in order to reduce rates of cognitive decline and dementia. Exposure to fine particulate matter (PM2.5) and ozone (O3) above the US EPA standards is associated with AD risk. Mexico City children experienced pre- and postnatal high exposures to PM2.5, O3, combustion-derived iron-rich nanoparticles, metals, polycyclic aromatic hydrocarbons, and endotoxins. Exposures are associated with early brain gene imbalance in oxidative stress, inflammation, innate and adaptive immune responses, along with epigenetic changes, accumulation of misfolded proteins, cognitive deficits, and brain structural and metabolic changes. The Apolipoprotein E (APOE) 4 allele, the most prevalent genetic risk for AD, plays a key role in the response to air pollution in young girls. APOE 4 heterozygous females with >75% to <94% BMI percentiles are at the highest risk of severe cognitive deficits (1.5-2 SD from average IQ). This review focused on the relationships between gender, BMI, systemic and neural inflammation, insulin resistance, hyperleptinemia, dyslipidemia, vascular risk factors, and central nervous system involvement in APOE4 urbanites exposed to PM2.5 and magnetite combustion-derived iron-rich nanoparticles that can reach the brain. APOE4 young female heterozygous carriers constitute a high-risk group for a fatal disease: AD. Multidisciplinary intervention strategies could be critical for prevention or amelioration of cognitive deficits and long-term AD progression in young individuals at high risk.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

Are Major Dementias Triggered by Poor Blood Flow to the Brain? Theoretical Considerations. - de la Torre, Jack C (J Alzheimers Dis, 2017)
There is growing evidence that chronic brain hypoperfusion plays a central role in the development of Alzheimer's disease (AD) long before dyscognitive symptoms or amyloid-β accumulation in the brain appear. This commentary proposes that dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and Creutzfeldt-Jakob disease (CJD) may also develop from chronic brain hypoperfusion following a similar but not identical neurometabolic breakdown as AD. The argument to support this conclusion is that chronic brain hypoperfusion, which is found at the early stages of the three dementias reviewed here, will reduce oxygen delivery and lower oxidative phosphorylation promoting a steady decline in the synthesis of the cell energy fuel adenosine triphosphate (ATP). This process is known to lead to oxidative stress. Virtually all neurodegenerative diseases, including FTD, DLB, and CJD, are characterized by oxidative stress that promotes inclusion bodies which differ in structure, location, and origin, as well as which neurological disorder they typify. Inclusion bodies have one thing in common; they are known to diminish autophagic activity, the protective intracellular degradative process that removes malformed proteins, protein aggregates, and damaged subcellular organelles that can disrupt neuronal homeostasis. Neurons are dependent on autophagy for their normal function and survival. When autophagic activity is diminished or impaired in neurons, high levels of unfolded or misfolded proteins overwhelm and downregulate the neuroprotective activity of unfolded protein response which is unable to get rid of dysfunctional organelles such as damaged mitochondria and malformed proteins at the synapse. The endpoint of this neuropathologic process results in damaged synapses, impaired neurotransmission, cognitive decline, and dementia.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Association of Central Arterial Stiffness and Pressure Pulsatility with Mild Cognitive Impairment and Dementia: The Atherosclerosis Risk in Communities Study-Neurocognitive Study (ARIC-NCS). - Meyer, Michelle L; Palta, Priya; Tanaka, Hirofumi; Deal, Jennifer A; Wright, Jacqueline; Knopman, David S; Griswold, Michael E; Mosley, Thomas H; Heiss, Gerardo (J Alzheimers Dis, 2017)
BACKGROUND: The association of central arterial stiffness and pressure pulsatility with mild cognitive impairment (MCI) and dementia is not well characterized in the population-based setting. OBJECTIVE: The aim of this study was to quantify the cross-sectional association of arterial stiffness and pressure pulsatility with MCI and dementia among 4,461 older white and black adults from the population-based Atherosclerosis Risk in Communities Study-Neurocognitive Study. METHODS: We used race-stratified multinomial logistic regression to evaluate associations of percentile cut points of carotid-femoral pulse wave velocity, central systolic blood pressure, central pulse pressure, and pulse pressure amplification with MCI and dementia versus no cognitive impairment. RESULTS: Among whites, those with carotid-femoral pulse wave velocity or central systolic blood pressure ≥75th percentile had a higher prevalence of MCI compared to participants <75th percentile (conditional odds ratio (OR); 95% confidence interval (CI): 1.27 (1.02, 1.56) and 1.28 (1.04, 1.57), respectively) and those with central pulse pressure ≥75th percentile had a higher prevalence of MCI (OR 1.27 (95% CI: 1.03, 1.58)) and dementia (OR 1.76 (95% CI: 1.06, 2.92) compared to participants <75th percentile. Also among whites, those with pulse pressure amplification ≤25th percentile had a higher prevalence of dementia compared to participants >25th percentile (OR 1.65; (95% CI: 1.01, 2.70). Weaker associations were seen among black participants. CONCLUSION: Higher arterial stiffness and pulsatility were associated with MCI and dementia in white participants. Longitudinal characterization of the observed associations is warranted to assess whether arterial stiffness and pressure pulsatility predict MCI and dementia among older adults.

Association of Gait Speed, Psychomotor Speed, and Dementia. - Kuate-Tegueu, Callixte; Avila-Funes, José-Alberto; Simo, Nadine; Le Goff, Mélanie; Amiéva, Hélène; Dartigues, Jean-François; Tabue-Teguo, Maturin (J Alzheimers Dis, 2017)
BACKGROUND: Gait speed (GS) and psychomotor speed (PS) could be considered as two different dimensions of age-related slowness and both measures are associated with higher risk of adverse health-related outcomes among elderly people. OBJECTIVE: To determine the association between GS, PS, and incident dementia among community-dwelling older adults. METHODS: Twelve-year longitudinal study of 1,265 participants in the Bordeaux Three-City Study, a French prospective cohort designed to determine the risk of dementia and cognitive impairment attributable to cardiovascular risk factors. Participants completed a battery of cognitive tests, including time to complete the Trail Making Test A, and a walking speed test. The incidence of dementia was determined over the 12-year follow-up period. Cox proportional hazards models with delayed entry were used to estimate the cumulative risk of dementia and were adjusted for sex, education, and ApoE4 genotype. RESULTS: Mean age of participants was 74.0 years (SD 4.8). Over the 12-year follow-up, 203 participants developed dementia. GS and PS were both independent predictors of incident all-cause dementia after 12 years of follow-up. For a one SD increase of either GS or PS, the hazard ratio (HR) for Alzheimer's disease was 1.2 (95% CI = 1.02-1.32) and 1.4 (95% CI = 1.2-1.61), respectively; whereas for incident vascular dementia, the HR was 1.3 (95% CI = 1.05-1.71) and 1.5 (95% CI = 1.16-2.08), respectively. No significant interaction between GS and PS was observed. CONCLUSIONS: In older French people aged 65+, our findings showed that both low GS and PS were independently associated with risk of incident Alzheimer's disease and vascular dementia.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

BACE1 Dynamics Upon Inhibition with a BACE Inhibitor and Correlation to Downstream Alzheimer's Disease Markers in Elderly Healthy Participants. - Timmers, Maarten; Barão, Soraia; Van Broeck, Bianca; Tesseur, Ina; Slemmon, John; de Waepenaert, Katja; Bogert, Jennifer; Shaw, Leslie M; Engelborghs, Sebastiaan; Moechars, Dieder; Mercken, Marc; Van Nueten, Luc; et al. (J Alzheimers Dis, 2017)
The β-site amyloid-β protein precursor (AβPP) cleaving enzyme-1 (BACE1) is the rate limiting enzyme in the generation of amyloid-β peptide (Aβ) from AβPP, one of the major pathways in Alzheimer's disease (AD) pathology. Increased BACE1 levels and activity have been reported in the brain of patients with sporadic AD. Therefore, changes of BACE1 levels in the cerebrospinal fluid (CSF) have also been investigated as a possible biomarker of the disease. We analyzed BACE1 levels in CSF of elderly healthy participants before and after chronic treatment with a BACE inhibitor (BACEi) and evaluated the correlation between BACE1 levels and downstream AD markers. Overall, BACE1 CSF levels showed strong correlations to all downstream AD markers investigated. This is the first reported finding that shows BACE1 levels in CSF were well correlated to its end product Aβ1 - 42. As previously described, BACE1 levels were strongly correlated to total-tau and phosphorylated tau levels in CSF. Generally, chronic BACE inhibition did not influence BACE1 CSF protein levels. Follow-up studies including early-stage AD pathophysiology and prodromal AD patients will help to understand the importance of measuring BACE1 routinely in daily clinical practice and AD clinical trials.

BDNF Responses in Healthy Older Persons to 35 Minutes of Physical Exercise, Cognitive Training, and Mindfulness: Associations with Working Memory Function. - Håkansson, Krister; Ledreux, Aurélie; Daffner, Kirk; Terjestam, Yvonne; Bergman, Patrick; Carlsson, Roger; Kivipelto, Miia; Winblad, Bengt; Granholm, Ann-Charlotte; Mohammed, Abdul Kadir H (J Alzheimers Dis, 2017)
Brain-derived neurotrophic factor (BDNF) has a central role in brain plasticity by mediating changes in cortical thickness and synaptic density in response to physical activity and environmental enrichment. Previous studies suggest that physical exercise can augment BDNF levels, both in serum and the brain, but no other study has examined how different types of activities compare with physical exercise in their ability to affect BDNF levels. By using a balanced cross over experimental design, we exposed nineteen healthy older adults to 35-minute sessions of physical exercise, cognitive training, and mindfulness practice, and compared the resulting changes in mature BDNF levels between the three activities. We show that a single bout of physical exercise has significantly larger impact on serum BDNF levels than either cognitive training or mindfulness practice in the same persons. This is the first study on immediate BDNF effects of physical activity in older healthy humans and also the first study to demonstrate an association between serum BDNF responsivity to acute physical exercise and working memory function. We conclude that the BDNF increase we found after physical exercise more probably has a peripheral than a central origin, but that the association between post-intervention BDNF levels and cognitive function could have implications for BDNF responsivity in serum as a potential marker of cognitive health.

Benefits of Occupational Therapy in Dementia Patients: Findings from a Real-World Observational Study. - Pimouguet, Clément; Le Goff, Mélanie; Wittwer, Jérôme; Dartigues, Jean-François; Helmer, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: There is a growing interest in developing non-pharmacological approaches in dementia. Clinical efficacy of occupational therapy (OT) under routine care conditions has not been investigated yet. OBJECTIVE: To analyze the short-term effects of OT in patients with dementia; and to identify factors related to greater benefit. METHODS: Patients referred to OT were evaluated before starting a 3-month intervention and at 3 and 6 months later. Measures included: Mini-Mental State Examination (MMSE), Disability Assessment in Dementia (DAD), Neuropsychiatric Inventory (NPI) Questionnaire, patients' quality of life (EQ 5D-VAS), caregivers' burden (Zarit scale), and amount of informal care. Linear mixed models were used to analyze trajectories of outcomes. Logistic regressions with stepwise descending selection were used to study factors associated with benefits. RESULTS: 421 dementia patients benefited from OT (mean MMSE = 17.3). Patients remained cognitively stable over time. Functional performances also remained stable at 3 months and significantly decreased at 6 months (crude reduction of 2.8 points, p < 0.01). Behavioral troubles were significantly reduced over the intervention period and remained stable after (p < 0.01). Patients' quality of life increased over the 3-month intervention (p = 0.16) and significantly decreased thereafter. Caregivers' burden and informal care significantly decreased over the 3-month intervention and remained stable thereafter. Patients who benefited from OT with regard to function were less educated and had higher cognitive level. CONCLUSION: OT may be an effective intervention to maintain cognition and functionality and to reduce psychiatric symptoms in dementia patients. Mild stages of dementia could gain more benefits from OT with regard to functional decline.

Bilingualism and Cognitive Decline: A Story of Pride and Prejudice. - Woumans, Evy; Versijpt, Jan; Sieben, Anne; Santens, Patrick; Duyck, Wouter (J Alzheimers Dis, 2017)
In a recent review, Mukadam, Sommerlad, and Livingston (2017) argue that bilingualism offers no protection against cognitive decline. The authors examined the results of 13 studies (five prospective, eight retrospective) in which monolinguals and bilinguals were compared for cognitive decline and onset of dementia symptoms. Analysis of four of the five prospective studies resulted in the conclusion that there was no difference between monolinguals and bilinguals, whereas seven of the eight retrospective studies actually showed bilingualism to result in a four-to-five year delay of symptom onset. The authors decided to ignore the results from the retrospective studies in favor of those from the prospective studies, reasoning that the former may be confounded by participants' cultural background and education levels. In this commentary, we argue that most of these studies actually controlled for these two variables and still found a positive effect of bilingualism. Furthermore, we argue that the meta-analysis of the prospective studies is not complete, lacking the results of two crucial reports. We conclude that the literature offers substantial evidence for a bilingual effect on the development of cognitive decline and dementia.

Bipolar Disorder and Frontotemporal Dementia: An Intriguing Association. - Papazacharias, Apostolos; Lozupone, Madia; Barulli, Maria Rosaria; Capozzo, Rosa; Imbimbo, Bruno P; Veneziani, Federica; De Blasi, Roberto; Nardini, Marcello; Seripa, Davide; Panza, Francesco; Logroscino, Giancarlo (J Alzheimers Dis, 2017)
Bipolar disorder (BD) could represent a prodromal state of frontotemporal dementia (FTD). Two patients affected by lifelong BD with a progressive decline of cognitive functions, behavioral, and neurological signs, reached the early diagnosis of FTD before the age of 60. They were diagnosed as affected by primary progressive aphasia and FTD with parkinsonism, respectively. A diagnosis of FTD should therefore be taken into account, in case of unexpected cognitive and behavioral decline in patients with a long history of BD. Follow-up studies with genetic, neuropsychological, and neuroimaging markers of these BD/FTD patients could further explore some of the underlying association, opening new viable therapeutic options.

Blood Pressure and Hispanic/Latino Cognitive Function: Hispanic Community Health Study/Study of Latinos Results. - Tarraf, Wassim; Rodríguez, Carlos J; Daviglus, Martha L; Lamar, Melissa; Schneiderman, Neil; Gallo, Linda; Talavera, Gregory A; Kaplan, Robert C; Fornage, Myriam; Conceicao, Alan; González, Hector M (J Alzheimers Dis, 2017)
BACKGROUND: Hispanics/Latinos are at increased risk for cardiovascular disease and cognitive decline and dementias. High blood pressure (BP) has been implicated in both stroke and dementias. Associations between BP and cognition among diverse Latinos are still unpublished. OBJECTIVE: We examined associations between cognition and four BP based measures among diverse Hispanics/Latinos. We hypothesized that higher BP, particularly systolic pressure, and increased arterial stiffness (i.e., pulse pressure), would be associated with lower cognitive function. METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; n = 9,019; ages 45-74 years) data to examine cognition in relation to BP measures. RESULTS: In age, sex, and education adjusted models, systolic, pulse, and mean arterial pressure were consistently negatively associated with executive function, psychomotor speed and sustained attention, verbal episodic learning and memory, speech fluency, and mental status measures. These associations were attenuated but remained statistically significant in fully adjusted models. CONCLUSION: Among middle-aged and older diverse Hispanics/Latinos, we found modest but consistent associations between indicators of arterial stiffness, and compromised blood flow and lower cognitive function. Clinical management and public health interventions to raise awareness and enhance BP management beginning in midlife could reduce disparities and improve population health by reducing cognitive decline burdens.

Body Mass Index, Height, and Socioeconomic Position in Adolescence, Their Trajectories into Adulthood, and Cognitive Function in Midlife. - Cohen-Manheim, Irit; Doniger, Glen M; Sinnreich, Ronit; Simon, Ely S; Murad, Havi; Pinchas-Mizrachi, Ronit; Kark, Jeremy D (J Alzheimers Dis, 2017)
BACKGROUND: Whether life course anthropometric indices relate to cognitive function in midlife remains insufficiently explored. Rarely was socioeconomic position (SEP) adequately accounted for. OBJECTIVE: To examine the association of the cumulative life course burden of high-ranked body mass index (BMI), its trajectory, and stature with cognitive function in midlife. METHODS: Weight and height were measured from age 17 across a 33-year follow-up. 507 individuals completed a NeuroTrax computerized cognitive assessment at ages 48-52. Life course SEP was assessed by multiple methods. Using mixed models we calculated the area under the curve (AUC), representing both the life-course burden of BMI (total AUC) and trends in BMI (incremental AUC) from age 17 to midlife. The associations of BMI and height with global cognition and its five component domains were assessed by multiple regression. RESULTS: Higher BMI in late adolescence and total AUC over the life course were associated with poorer global cognition (Standardized beta (Beta) = -0.111, p = 0.005 and Beta = -0.105, p = 0.018, respectively), adjusted for childhood and adulthood SEP, and demographic characteristics. The associations with higher adolescent and midlife BMI were both restricted to those with low childhood SEP (p < 0.05 for interaction). Short adolescent stature was related to poorer cognition (Beta = 0.084, p = 0.044), whereas late final growth in women was associated with better cognition (Beta = 0.213, p = 0.007). CONCLUSION: An adverse association of higher BMI with cognitive function began in adolescence and was restricted to low childhood SEP. Taller stature in both sexes and late growth in women were associated with better midlife cognitive performance.

Brain Regions Involved in Arousal and Reward Processing are Associated with Apathy in Alzheimer's Disease and Frontotemporal Dementia. - Huey, Edward D; Lee, Seonjoo; Cheran, Gayathri; Grafman, Jordan; Devanand, Davangere P (J Alzheimers Dis, 2017)
BACKGROUND: Apathy is a common and problematic symptom of several neurodegenerative illnesses, but its neuroanatomical bases are not understood. OBJECTIVE: To determine the regions associated with apathy in subjects with mild Alzheimer's disease (AD) using a method that accounts for the significant co-linearity of regional atrophy and neuropsychiatric symptoms. METHODS: We identified 57 subjects with mild AD (CDR = 1) and neuropsychiatric symptoms in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. We performed a multivariate multiple regression with LASSO regularization on all symptom subscales of the Neuropsychiatric Inventory and the whole-brain ROI volumes calculated from their baseline MRIs with FreeSurfer. We compared our results to those from a previous study using the same method in patients with frontotemporal dementia (FTD) and corticobasal syndrome (CBS). RESULTS: Of neuropsychiatric symptoms, apathy showed the most robust neuroanatomical associations in the AD subjects. Atrophy of the following regions were independently associated with apathy: the ventromedial prefrontal cortex; ventrolateral prefrontal cortex; posterior cingulate cortex and adjacent lateral cortex; and the bank of the superior temporal sulcus. These results replicate previous studies using FTD and CBS patients, mostly agree with the previous literature on apathy in AD, and correspond to the Medial and Orbital Prefrontal Cortex networks identified in non-human primates. CONCLUSION: The current study, previous studies from our laboratory, and the previous literature suggest that impairment of the same brain networks involved in arousal, threat response, and reward processing are associated with apathy in AD and FTD.

Can Musical or Painting Interventions Improve Chronic Pain, Mood, Quality of Life, and Cognition in Patients with Mild Alzheimer's Disease? Evidence from a Randomized Controlled Trial. - Pongan, Elodie; Tillmann, Barbara; Leveque, Yohana; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Dauphinot, Virginie; El Haouari, Hanane; Navez, Malou; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Among non-pharmacological therapies, musical intervention is often used for patients with Alzheimer's disease (AD) and patients presenting chronic pain. However, their efficacy is still under debate. OBJECTIVE: Our aim was to determine the efficacy of choral singing versus painting sessions on chronic pain, mood, quality of life, and cognition in AD patients. METHODS: In this multicenter randomized controlled trial, 59 mild AD patients were randomized to a 12-week singing (SG; n = 31) or painting group (PG; n = 28). Chronic pain, anxiety, depression, and quality of life were assessed before, after, and 1 month after the sessions. Cognitive abilities were assessed before and after interventions. The evolution of these different measures was assessed with mixed linear models. The primary data analysis was by intention-to-treat, and completed by a 'per protocol' approach. RESULTS: Both singing and painting interventions led to significant pain reduction (Time effect: F = 4.71; p = 0.01), reduced anxiety (Time effect: F = 10.74; p < 0.0001), improved Quality of Life (Time effect: F = 6.79; p = 0.002), improved digit span (F = 12.93; p = 0.001), and inhibitory processes (Time effect: F = 4.93; p = 0.03). Depression was reduced over time in PG only (Time x Group effect: F = 4.53; p = 0.01). Verbal Memory performance remained stable over time in SG, but decreased in PG (Time x group effect: F = 9.29; p = 0.004). CONCLUSION: Findings suggest that singing and painting interventions may reduce pain and improve mood, quality of life, and cognition in patients with mild AD, with differential effects of painting for depression and singing for memory performance.

Capsaicin Attenuates Amyloid-β-Induced Synapse Loss and Cognitive Impairments in Mice. - Chen, Long; Huang, Zhilin; Du, Yehong; Fu, Min; Han, Huili; Wang, Yutian; Dong, Zhifang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of progressive cognitive impairment in the aged. The aggregation of the amyloid β-protein (Aβ) is a hallmark of AD and is linked to synapse loss and cognitive impairment. Capsaicin, a specific agonist of the transient receptor potential vanilloid 1 (TRPV1), has been proven to ameliorate stress-induced AD-like pathological and cognitive impairments, but it is unclear whether TRPV1 activation can affect cognitive and synaptic functions in Aβ-induced mouse model of AD. In this study, we investigated the effects of TRPV1 activation on spatial memory and synaptic plasticity in mice treated with Aβ. To induce AD-like pathological and cognitive impairments, adult C57Bl/6 mice were microinjected with Aβ42 (100 μM, 2.5 μl/mouse, i.c.v.). Two weeks after Aβ42 microinjection, spatial learning and memory as well as hippocampal long-term potentiation (LTP) were examined. The results showed that Aβ42 microinjection significantly impaired spatial learning and memory in the Morris water maze and novel object recognition tests compared with controls. These behavioral changes were accompanied by synapse loss and impaired LTP in the CA1 area of hippocampus. More importantly, daily capsaicin (1 mg/kg, i.p.) treatment throughout the experiment dramatically improved spatial learning and memory and synaptic function, as reflected by enhanced hippocampal LTP and reduced synapse loss, whereas the TRPV1 antagonist capsazepine (1 mg/kg, i.p.) treatment had no effects on cognitive and synaptic function in Aβ42-treated mice. These results indicate that TRPV1 activation by capsaicin rescues cognitive deficit in the Aβ42-induced mouse model of AD both structurely and functionally.

Central Review of Amyloid-Related Imaging Abnormalities in Two Phase III Clinical Trials of Bapineuzumab in Mild-To-Moderate Alzheimer's Disease Patients. - Ketter, Nzeera; Brashear, H Robert; Bogert, Jennifer; Di, Jianing; Miaux, Yves; Gass, Achim; Purcell, Derk D; Barkhof, Frederik; Arrighi, H Michael (J Alzheimers Dis, 2017)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) consist of ARIA-E (with effusion or edema) and ARIA-H (hemosiderin deposits [HDs]). OBJECTIVES: To address accurate ascertainment of ARIA identification, a final magnetic resonance imaging (MRI) reading was performed on patients with mild-to-moderate Alzheimer's disease randomized to bapineuzumab IV or placebo during two Phase III trials (APOE ɛ4 allele carriers or noncarriers). METHODS: Final MRI central review consisted of a systematic sequential locked, adjudicated read in 1,331 APOE ɛ4 noncarriers and 1,121 carriers by independent neuroradiologists. Assessment of ARIA-E, ARIA-H, intracerebral hemorrhages, and age-related white matter changes is described. RESULTS: In the Final Read, treatment-emergent ARIA-E were identified in 242 patients including 76 additional cases not noted previously in real time. Overall, incidence proportion of ARIA-E was higher in carriers (active 21.2%; placebo 1.1%) than in noncarriers (pooled active 11.3%; placebo 0.6%), and was more often identified in homozygote APOE ɛ4 carriers than heterozygotes (34.5% versus 16.9%). Incidence rate of ARIA-E increased with increased dose in noncarriers. Frequency of ARIA-E first episodes was highest after the first and second bapineuzumab infusion and declined after repeated infusions. Incidence of total HDs <10 mm (cerebral microhemorrhages) was higher in active groups versus placebo. CONCLUSION: ARIA was detected more often on MRI scans when every scan was reviewed by trained neuroradiologists and results adjudicated. There was increased incidence of ARIA-E in bapineuzumab-treated carriers who had a microhemorrhage at baseline. ARIA-E was a risk factor for incident ARIA-H and late onset ARIA-E was milder radiologically. Age-related white matter changes did not progress during the study.

The Cerebrospinal Fluid Aβ1-42/Aβ1-40 Ratio Improves Concordance with Amyloid-PET for Diagnosing Alzheimer's Disease in a Clinical Setting. - Niemantsverdriet, Ellis; Ottoy, Julie; Somers, Charisse; De Roeck, Ellen; Struyfs, Hanne; Soetewey, Femke; Verhaeghe, Jeroen; Van den Bossche, Tobi; Van Mossevelde, Sara; Goeman, Johan; De Deyn, Peter Paul; Mariën, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Evidence suggests that the concordance between amyloid-PET and cerebrospinal fluid (CSF) amyloid-β (Aβ) increases when the CSF Aβ1-42/Aβ1-40 ratio is used as compared to CSF Aβ1-42 levels alone. OBJECTIVE: In order to test this hypothesis, we set up a prospective longitudinal study comparing the concordance between different amyloid biomarkers for Alzheimer's disease (AD) in a clinical setting. METHODS: Seventy-eight subjects (AD dementia (n = 17), mild cognitive impairment (MCI, n = 48), and cognitively healthy controls (n = 13)) underwent a [18F]Florbetapir ([18F]AV45) PET scan, [18F]FDG PET scan, MRI scan, and an extensive neuropsychological examination. In a large subset (n = 67), a lumbar puncture was performed and AD biomarkers were analyzed (Aβ1-42, Aβ1-40, T-tau, P-tau181). RESULTS: We detected an increased concordance in the visual and quantitative (standardized uptake value ratio (SUVR) and total volume of distribution (VT)) [18F]AV45 PET measures when the CSF Aβ1-42/Aβ1-40 was applied compared to Aβ1-42 alone. CSF biomarkers were stronger associated to [18F]AV45 PET for SUVR values when considering the total brain white matter as reference region instead of cerebellar grey matterConclusions:The concordance between CSF Aβ and [18F]AV45 PET increases when the CSF Aβ1-42/Aβ1-40 ratio is applied. This finding is of most importance for the biomarker-based diagnosis of AD as well as for selection of subjects for clinical trials with potential disease-modifying therapies for AD.

Cerebrospinal Fluid Aβ42/Aβ40 as a Means to Limiting Tube- and Storage-Dependent Pre-Analytical Variability in Clinical Setting. - Gervaise-Henry, Christelle; Watfa, Gasshan; Albuisson, Eliane; Kolodziej, Allan; Dousset, Brigitte; Olivier, Jean-Luc; Jonveaux, Thérèse Rivasseau; Malaplate-Armand, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers have recently been included in the criteria for AD diagnosis. Unfortunately, their wider use in routine and interpretation require more standardization, particularly for the pre-analytical steps. In particular, amyloid-β (Aβ)42 peptide measurement is strongly influenced by the type of collection tube and by repeated freeze/thaw cycles. OBJECTIVE: The objectives of this study were to compare, in clinical setting, the impact of collection tubes and the repetition of freeze/thaw cycles on Aβ42 and Aβ40 concentrations and consequently determine if the Aβ42/Aβ40 ratio could resolve the diagnosis difficulties related to these pre-analytical parameters. METHODS: CSF from 35 patients was collected in different polypropylene (PP) and stored at - 80°C after sampling. For CSF collected in the reference tube, three successive freeze-thaw cycles were done. Aβ42 and Aβ40 concentrations were determined in each condition in order to calculate the Aβ42/Aβ40 ratio. RESULTS: Our results showed that CSF Aβ42 and Aβ40 values were significantly different according to the type of collection tube and the number of freeze/thaw cycles. Although the calculation of the Aβ42/Aβ40 ratio eliminated the effect of PP tube-dependent variation, this was not the case for freeze-thaw cycle-associated variation. CONCLUSION: The use of Aβ42/Aβ40 ratio rather than Aβ42 alone could contribute toward pre-analytical standardization, thus allowing the general use of CSF AD biomarkers in routine practice.

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A View of the Regulatory Science Qualification Landscape from the Coalition Against Major Diseases CSF Biomarker Team. - Arnerić, Stephen P; Batrla-Utermann, Richard; Beckett, Laurel; Bittner, Tobias; Blennow, Kaj; Carter, Leslie; Dean, Robert; Engelborghs, Sebastiaan; Genius, Just; Gordon, Mark Forrest; Hitchcock, Janice; Kaplow, June; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) drug development is burdened with the current requirement to conduct large, lengthy, and costly trials to overcome uncertainty in patient progression and effect size on treatment outcome measures. There is an urgent need for the discovery, development, and implementation of novel, objectively measured biomarkers for AD that would aid selection of the appropriate subpopulation of patients in clinical trials, and presumably, improve the likelihood of successfully evaluating innovative treatment options. Amyloid deposition and tau in the brain, which are most commonly assessed either in cerebrospinal fluid (CSF) or by molecular imaging, are consistently and widely accepted. Nonetheless, a clear gap still exists in the accurate identification of subjects that truly have the hallmarks of AD. The Coalition Against Major Diseases (CAMD), one of 12 consortia of the Critical Path Institute (C-Path), aims to streamline drug development for AD and related dementias by advancing regulatory approved drug development tools for clinical trials through precompetitive data sharing and adoption of consensus clinical data standards. This report focuses on the regulatory process for biomarker qualification, briefly comments on how it contrasts with approval or clearance of companion diagnostics, details the qualifications currently available to the field of AD, and highlights the current challenges facing the landscape of CSF biomarkers qualified as hallmarks of AD. Finally, it recommends actions to accelerate regulatory qualification of CSF biomarkers that would, in turn, improve the efficiency of AD therapeutic development.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Change in Odor Identification Impairment is Associated with Improvement with Cholinesterase Inhibitor Treatment in Mild Cognitive Impairment. - Devanand, D P; Lentz, Cody; Chunga, Richard E; Ciarleglio, Adam; Scodes, Jennifer M; Andrews, Howard; Schofield, Peter W; Stern, Yaakov; Huey, Edward D; Bell, Karen; Pelton, Gregory H (J Alzheimers Dis, 2017)
BACKGROUND: Anticholinergic challenge can induce odor identification impairment that indicates Alzheimer's disease pathology. OBJECTIVE: To determine if decline in odor identification ability with anticholinergic challenge can predict improvement with donepezil, a cholinesterase inhibitor (ChEI), in patients with mild cognitive impairment (MCI). METHODS: At baseline, the University of Pennsylvania Smell identification Test (UPSIT) was administered before and after an anticholinergic atropine nasal spray challenge. Donepezil was started at 5 mg daily, increased to 10 mg daily if tolerated, and then the dose was kept constant for 52 weeks. Main outcomes were change in Selective Reminding Test (SRT) total immediate recall and ADAS-Cog total score from baseline to 26 and 52 weeks. RESULTS: In 37 participants, mean age 70.4 (SD 9.8) y, greater atropine-induced decrease in UPSIT score at baseline was associated with greater improvement in SRT total recall score from baseline to 26 and 52 weeks (p < 0.03). This effect remained after adjusting for time, age, education, gender, APOE ɛ4 status, and baseline cognitive score (p < 0.05). Decrease in UPSIT score was associated with global improvement (CIBIC-plus) over 52 weeks (p < 0.02). After excluding patients with congential anosmia, increase in UPSIT score from 0 to 8 weeks showed a trend-level association with improvement on the ADAS-Cog (p = 0.07). CONCLUSIONS: Anticholinergic challenge-induced odor identification decline was associated with cognitive improvement, and short-term improvement in odor identification tended to predict longer term cognitive improvement. These simple inexpensive strategies have the potential to improve selection of patients with MCI for ChEI treatment.

Chinese Calligraphy Writing for Augmenting Attentional Control and Working Memory of Older Adults at Risk of Mild Cognitive Impairment: A Randomized Controlled Trial. - Chan, Sam C C; Chan, Chetwyn C H; Derbie, Abiot Y; Hui, Irene; Tan, Davynn G H; Pang, Marco Y C; Lau, Stephen C L; Fong, Kenneth N K (J Alzheimers Dis, 2017)
BACKGROUND: Nonpharmacological intervention for individuals with mild cognitive impairment (MCI) needs further investigation. OBJECTIVE: Test efficacy of an eight-week Chinese calligraphy writing training course in improving attentional control and working memory. METHODS: Ninety-nine participants with MCI were randomized into the eight-week calligraphy writing (n = 48) or control (tablet computer) training (n = 51). Outcomes of the interventions were attentional control, working memory, visual scan and processing speed. They were measured at baseline, post-training, and six-month follow-up. RESULTS: Calligraphy writing, when compared with control, significantly improved working memory as reflected from DST-Backward sequence (p = 0.009) and span scores (p = 0.002), and divided attention as reflected from CTT2 (p < 0.001), and at the post-training. The unique improvement in working memory (span: p < 0.001; sequence: p = 0.008) of the intervention group was also found at follow-up when comparing with those at baseline. Changes in the other outcome measures were not statistically significant. CONCLUSION: The findings provide support that Chinese calligraphy writing training for eight weeks using a cognitive approach would improve working memory and to a lesser extent attentional control functions of patients with early MCI. They also demonstrate the usefulness of using mind-and-body practice for improving specific cognitive functions.

Chronic Lithium Treatment in a Rat Model of Basal Forebrain Cholinergic Depletion: Effects on Memory Impairment and Neurodegeneration. - Gelfo, Francesca; Cutuli, Debora; Nobili, Annalisa; De Bartolo, Paola; D'Amelio, Marcello; Petrosini, Laura; Caltagirone, Carlo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is an age-related neurodegenerative disorder with multifactorial etiopathogenesis, characterized by progressive loss of memory and other cognitive functions. A fundamental neuropathological feature of AD is the early and severe brain cholinergic neurodegeneration. Lithium is a monovalent cation classically utilized in the treatment of mood disorders, but recent evidence also advances a beneficial potentiality of this compound in neurodegeneration. Interestingly, lithium acts on several processes whose alterations characterize the brain cholinergic impairment at short and long term. On this basis, the aim of the present research was to evaluate the potential beneficial effects of a chronic lithium treatment in preventing the damage that a basal forebrain cholinergic neurodegeneration provokes, by investigating memory functions and neurodegeneration correlates. Adult male rats were lesioned by bilateral injections of the immunotoxin 192 IgG-Saporin into the basal forebrain. Starting 7 days before the surgery, the animals were exposed to a 30-day lithium treatment, consisting of a 0.24% Li2CO3 diet. Memory functions were investigated by the open field test with objects, the sociability and preference for social novelty test, and the Morris water maze. Hippocampal and neocortical choline acetyltransferase (ChAT) levels and caspase-3 activity were determined. Cholinergic depletion significantly impaired spatial and social recognition memory, decreased hippocampal and neocortical ChAT levels and increased caspase-3 activity. The chronic lithium treatment significantly rescued memory performances but did not modulate ChAT availability and caspase-3 activity. The present findings support the lithium protective effects against the cognitive impairment that characterizes the brain cholinergic depletion.

Chronotropic Response and Cognitive Function in a Cohort at Risk for Alzheimer's Disease. - Law, Lena L; Schultz, Stephanie A; Boots, Elizabeth A; Einerson, Jean A; Dougherty, Ryan J; Oh, Jennifer M; Korcarz, Claudia E; Edwards, Dorothy F; Koscik, Rebecca L; Dowling, N Maritza; Gallagher, Catherine L; Bendlin, Barbara B; et al. (J Alzheimers Dis, 2017)
The objective of this study was to examine the association of chronotropic response (CR) and heart rate (HR) recovery- two indices of cardiovascular function within the context of a graded exercise test- with cognitive performance in a cognitively healthy, late-middle-aged cohort at risk for Alzheimer's disease (AD). Ninety participants (age = 63.52±5.86 years; 65.6% female) from the Wisconsin Registry for Alzheimer's Prevention participated in this study. They underwent graded exercise testing and a comprehensive neuropsychological assessment that assessed the following four cognitive domains: Immediate Memory, Verbal & Learning Memory, Working Memory, and Speed & Flexibility. Regression analyses, adjusted for age, sex, and education, were used to examine the association between CR, HR recovery, and cognition. We found significant associations between CR and cognitive performance in the domains of Immediate Memory, Verbal Learning & Memory, and Speed & Flexibility. In contrast, HR recovery was not significantly associated with cognitive function. The association between CR and cognition persisted even after controlling for HR recovery. Together, these findings indicatethat, in a cognitively normal, late-middle-aged cohort, CR is a stronger correlate of cognitive performance than HR recovery. Overall, this study reinforces the idea that cardiovascular health plays an important role in cognitive function, specifically in a cohort at risk for AD; and that interventions that promote vascular health may be a viable pathway to preventing or slowing cognitive decline due to AD.

Classification of Alzheimer's Disease and Prediction of Mild Cognitive Impairment Conversion Using Histogram-Based Analysis of Patient-Specific Anatomical Brain Connectivity Networks. - Beheshti, Iman; Maikusa, Norihide; Daneshmand, Morteza; Matsuda, Hiroshi; Demirel, Hasan; Anbarjafari, Gholamreza (J Alzheimers Dis, 2017)
In this study, we investigated the early detection of Alzheimer's disease (AD) and mild cognitive impairment (MCI) conversion to AD through individual structural connectivity networks using structural magnetic resonance imaging (sMRI) data. In the proposed method, the cortical morphometry of individual gray matter images were used to construct structural connectivity networks. A statistical feature generation approach based on histogram-based feature generation procedure was proposed to represent a statistical-pattern of connectivity networks from a high-dimensional space into low-dimensional feature vectors. The proposed method was evaluated on numerous samples including 61 healthy controls (HC), 42 stable-MCI (sMCI), 45 progressive-MCI (pMCI), and 83 AD subjects at the baseline from the J-ADNI data-set using support vector machine classifier. The proposed method yielded a classification accuracy of 84.17%, 70.38%, and 61.05% in identifying AD/HC, MCIs/HCs, and sMCI/pMCI, respectively. The experimental results show that the proposed method performed in a comparable way to alternative methods using MRI data.

Clinical Effectiveness and Tolerability of Electroconvulsive Therapy in Patients with Neuropsychiatric Symptoms of Dementia. - Isserles, Moshe; Daskalakis, Zafiris J; Kumar, Sanjeev; Rajji, Tarek K; Blumberger, Daniel M (J Alzheimers Dis, 2017)
BACKGROUND: Dementia frequently presents with aggression, agitation, and disorganized behavior for which current treatment is partially effective and is associated with significant adverse effects. OBJECTIVE: The aim of this study was to retrospectively assess the clinical effectiveness and tolerability of electroconvulsive therapy (ECT) in a sample of patients with neuropsychiatric symptoms of dementia (NPS) and to explore factors associated with response and with cognitive adverse effects. METHODS: We examined the clinical records of 25 patients with dementia and a pre-existing psychiatric disorder treated with ECT at an academic mental health hospital between April 1, 2010 and January 28, 2016. Twenty-nine acute ECT courses and fifteen maintenance courses were reviewed. We assessed treatment effectiveness and cognitive adverse effects as well as factors associated with response to treatment, including pre-existing psychiatric disorders, concomitant pharmacological treatment and types of dementia. RESULTS: ECT resulted in a clinically meaningful response in 72% of acute treatment courses. Cognitive adverse effects affecting functioning were reported in 7% of the acute treatment courses. Maintenance treatment was effective in sustaining the response in 87% of treatment courses with two reports of significant cognitive adverse effects. One patient fell and experienced a hip fracture a day after treatment. Use of antipsychotic or antidepressant medications, pre-existing psychiatric disorder, or gender were not associated with response. CONCLUSION: This study shows meaningful clinical effectiveness and good tolerability of ECT in patients with severe NPS of dementia. Furthermore, maintenance ECT was effective in sustaining treatment response.

The Clinical Use of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease Diagnosis: The Italian Selfie. - Sancesario, Giulia M; Toniolo, Sofia; Chiasserini, Davide; Di Santo, Simona G; Zegeer, Josh; Bernardi, Gaetano; Musicco, Massimo; Caltagirone, Carlo; Parnetti, Lucilla; Bernardini, Sergio (J Alzheimers Dis, 2017)
Although the use of cerebrospinal fluid (CSF) amyloid β1-42 (Aβ42), tau (T-tau), and phosphorylated tau (p-tau181) gives added diagnostic and prognostic values, the diffusion is still limited in clinical practice and only a restricted number of patients receive an integrated clinico-biological diagnosis. By a survey, we aimed to do a "selfie" of the use and diffusion of CSF biomarkers of dementia in Italy, the standardization of pre-analytical procedures, the harmonization of ranges, and the participation to Quality Control programs. An online questionnaire was sent to the members of SIBioC and SINdem-ITALPLANED and to main neurological clinics all over Italy. In Italy, 25 laboratories provide biomarkers analysis in addition to a network of 15 neighboring hospitals. In sum, 40 neurological centers require CSF analyses. 7/20 regions (35%) lack CSF laboratories. Standardization of pre-analytical procedures is present in 62.02% of the laboratories; only 56.00% of the laboratories participate in International Quality Control. There is no harmonization of cut-offs. In Italy, the use of CSF biomarkers is still limited in clinical practice. Standardization and harmonization of normal ranges are needed. To optimize and expand the use of CSF biomarkers, a cost-benefit analysis should be promoted by scientific societies and national health services.

Cognitive Change in Rehabilitation Patients with Dementia: Prevalence and Association with Rehabilitation Success. - Dutzi, Ilona; Schwenk, Michael; Kirchner, Marietta; Bauer, Jürgen M; Hauer, Klaus (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is a frequent diagnosis in geriatric rehabilitation. Studies in patients with dementia on the development of their cognitive status during rehabilitation and its relation to functional outcomes have been scarce. OBJECTIVES: To describe the changes in cognitive status in patients with dementia during inpatient rehabilitation and to determine its association with patient characteristics and rehabilitation outcome. METHODS: Cohort study in a geriatric rehabilitation center with data collection at admission and discharge. Outcome measures were change in global and domain-related cognitive functioning and its association with activities of daily living (ADL) and discharge home. RESULTS: 154 patients (mean age 83.7 years) diagnosed with mild to moderate dementia were included. Cognitive performance significantly improved from admission to discharge for all cognitive variables tested (p < 0.001 to 0.03). Change in global cognitive functioning, executive functions, and episodic memory were positively associated with ADL recovery. Change in global cognitive functioning predicted ADL improvements (β= 0.32; p = 0.006). Only 7.8% of patients, characterized by worse ADL and motor abilities as well as higher frailty scores at admission, deteriorated in global cognitive scores. In comparison to patients with stable or improved cognition, these patients showed least improvements in ADL-scores (4.1 versus 12.5) and a trend for higher institutionalization (50% versus 26.5%). CONCLUSIONS: The findings highlight the potential of patients with dementia to recover cognitive functioning during rehabilitation. Cognitive change represents an independent rehabilitation outcome and a prognostic factor for successful rehabilitation suggesting that specific interventions are indicated to maintain and enhance cognitive functioning in these highly vulnerable patients.

Cognitive Efficiency in Alzheimer's Disease is Associated with Increased Occipital Connectivity. - De Marco, Matteo; Duzzi, Davide; Meneghello, Francesca; Venneri, Annalena (J Alzheimers Dis, 2017)
There are cognitive domains which remain fully functional in a proportion of Alzheimer's disease (AD) patients. It is unknown, however, what distinctive mechanisms sustain such efficient processing. The concept of "cognitive efficiency" was investigated in these patients by operationalizing it as a function of the level of performance shown on the Letter Fluency test, on which, very often, patients in the early stages of AD show unimpaired performance. Forty-five individuals at the prodromal/early stage of AD (diagnosis supported by subsequent clinical follow-ups) and 45 healthy controls completed a battery of neuropsychological tests and an MRI protocol which included resting state acquisitions. The Letter Fluency test was the only task on which no between-group difference in performance was found. Participants were divided into "low-performing" and "high-performing" according to the global median. Dual-regression methods were implemented to compute six patterns of network connectivity. The diagnosis-by-level of performance interaction was inferred on each pattern to determine the network distinctiveness of efficient performance in AD. Significant interactions were found in the anterior default mode network, and in both left and right executive control networks. For all three circuits, high-performing patients showed increased connectivity within the ventral and dorsal part of BA19, as confirmed by post hoc t tests. Peristriate remapping is suggested to play a compensatory role. Since the occipital lobe is the neurophysiological source of long-range cortical connectivity, it is speculated that the physiological mechanisms of functional connectivity might sustain occipital functional remapping in early AD, particularly for those functions which are sustained by areas not excessively affected by the prodromal disease.

Cognitive Event-Related Potential, an Early Diagnosis Biomarker in Frail Elderly Subjects: The ERP-MAPT-PLUS Ancillary Study. - Bennys, Karim; Gabelle, Audrey; Berr, Claudine; De Verbizier, Delphine; Andrieu, Sandrine; Vellas, Bruno; Touchon, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: By analyzing brain synaptic function, cognitive event-related potentials (ERPs) could provide powerful and innovative tools for early Alzheimer's disease (AD) diagnosis. OBJECTIVE: We investigated the relevance of the ERP-P300 component as a potential diagnosis marker in elderly subjects at risk of developing AD. METHODS: ERP-P300 was analyzed on 85 subjects recruited from the Multidomain Alzheimer Preventive Trial (MAPT). PET-AV45 brain imaging was available from 36 subjects. RESULTS: Two ERP-P300 subgroups were identified according to their PET-AV45 status: PET-Aβ positive (n = 15) and PET-Aβ negative (n = 21). In the amyloid positive group, we observed a highly significant increase in P3b latency in parietal brain regions (p = 0.0052). P3b in parietal regions correctly categorized 69.4% elderly subjects from the P300-PET Aβ positive group. Combined analysis of parietal P3b latencies and category fluency correctly classified 75% subjects from the P300-PET Aβ positive group. CONCLUSIONS: The P300 ERP presents good predictive measure of brain amyloid load and has the potential to be used as a screening instrument for preclinical AD. The incorporation of P3b latency may be used as an adjunctive tool with neuropsychological assessment (i.e., verbal category fluency) as a specific and sensitive method for preclinical assessment of AD.

Cognitive-Enhancing Effects of a Polyphenols-Rich Extract from Fruits without Changes in Neuropathology in an Animal Model of Alzheimer's Disease. - Dal-Pan, Alexandre; Dudonné, Stéphanie; Bourassa, Philippe; Bourdoulous, Morgane; Tremblay, Cyntia; Desjardins, Yves; Calon, Frederic (J Alzheimers Dis, 2017)
No effective preventive treatment is available for age-related cognitive decline and Alzheimer's disease (AD). Epidemiological studies indicate that a diet rich in fruit is associated with cognitive improvement. It was thus proposed that high polyphenol concentrations found in berries can prevent cognitive impairment associated with aging and AD. Therefore, the Neurophenols project aimed at investigating the effects of a polyphenolic extract from blueberries and grapes (PEBG) in the triple-transgenic (3xTg-AD) mouse model of AD, which develops AD neuropathological markers, including amyloid-β plaques and neurofibrillary tangles, leading to memory deficits. In this study, 12-month-old 3xTg-AD and NonTg mice were fed a diet supplemented with standardized PEBG (500 or 2500 mg/kg) for 4 months (n = 15-20/group). A cognitive evaluation with the novel object recognition test was performed at 15 months of age and mice were sacrificed at 16 months of age. We observed that PEBG supplementation with doses of 500 or 2500 mg/kg prevented the decrease in novel object recognition observed in both 15-month-old 3xTg-AD mice and NonTg mice fed a control diet. Although PEBG treatment did not reduce Aβ and tau pathologies, it prevented the decrease in mature BDNF observed in 16-month-old 3xTg-AD mice. Finally, plasma concentrations of phenolic metabolites, such as dihydroxyphenyl valerolactone, a microbial metabolite of epicatechin, positively correlated with memory performances in supplemented mice. The improvement in object recognition observed in 3xTg-AD mice after PEBG administration supports the consumption of polyphenols-rich extracts to prevent memory impairment associated with age-related disease, without significant effects on classical AD neuropathology.

Comprehensive Screening for Disease Risk Variants in Early-Onset Alzheimer's Disease Genes in African Americans Identifies Novel PSEN Variants. - N'Songo, Aurelie; Carrasquillo, Minerva M; Wang, Xue; Nguyen, Thuy; Asmann, Yan; Younkin, Steven G; Allen, Mariet; Duara, Ranjan; Custo, Maria T Greig; Graff-Radford, Neill; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2017)
We conducted a comprehensive screening of rare coding variants in an African American cohort to identify novel pathogenic mutations within the early-onset Alzheimer's disease (EOAD) genes (APP, PSEN1, and PSEN2) in this understudied population. Whole-exome sequencing of 238 African American subjects identified 6 rare missense variants within the EOAD genes, which were observed in AD cases but never among controls. These variants were analyzed in an independent cohort of 300 African American subjects in which PSEN2:NM_000447:exon5:c.T331C:p.Phe111Leu and PSEN1-minilin rs777923890 variants were again not observed, indicating that these novel rare variants, may contribute to AD risk in this population.

Copy Number Variants in Alzheimer's Disease. - Cuccaro, Denis; De Marco, Elvira Valeria; Cittadella, Rita; Cavallaro, Sebastiano (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a devastating disease mainly afflicting elderly people, characterized by decreased cognition, loss of memory, and eventually death. Although risk and deterministic genes are known, major genetics research programs are underway to gain further insights into the inheritance of AD. In the last years, in particular, new developments in genome-wide scanning methodologies have enabled the association of a number of previously uncharacterized copy number variants (CNVs, gain or loss of DNA) in AD. Because of the exceedingly large number of studies performed, it has become difficult for geneticists as well as clinicians to systematically follow, evaluate, and interpret the growing number of (sometime conflicting) CNVs implicated in AD. In this review, after a brief introduction of this type of structural variation, and a description of available databases, computational analyses, and technologies involved, we provide a systematic review of all published data showing statistical and scientific significance of pathogenic CNVs and discuss the role they might play in AD.

Cortical Thickness and Microstructural White Matter Changes Detect Amnestic Mild Cognitive Impairment. - Wang, Zan; Dai, Zhengjia; Shu, Hao; Liu, Duan; Guo, Qihao; He, Yong; Zhang, Zhijun (J Alzheimers Dis, 2017)
Both the apolipoprotein E (APOE) ɛ4 allele and amnestic mild cognitive impairment (aMCI) are considered to be risk factors for Alzheimer's disease (AD). The primary aim of this study was to determine whether the aMCI-related abnormality in gray matter (GM) cortical thickness and white matter (WM) tracts integrity would be modified by the APOE genotype. A total of 146 older adults, including 64 aMCI patients (28 ɛ4 carriers and 36 non-carriers) and 82 healthy controls (39 ɛ4 carriers and 43 non-carriers), underwent a standardized clinical interview, neuropsychological battery assessment, and multi-modal brain magnetic resonance imaging scans. Compared with control subjects, the patients with aMCI showed significantly reduced cortical thickness bilaterally in the parahippocampal gyrus and disrupted WM integrity in the limbic tracts (e.g., increased mean diffusivity in the right parahippocampal cingulum and bilateral uncinate fasciculus). However, no significant main effects of the APOE genotype and diagnosis-by-genotype interaction on GM thickness and WM integrity were observed. Further, diffusivity measures of the limbic WM tracts were significantly correlated with the parahippocampal atrophy in aMCI. Importantly, the parahippocampal thickness and diffusivity measures of the limbic WM tracts were significantly correlated with the cognitive performance (i.e., episodic memory Z score) in patients with aMCI. These results demonstrate that WM microstructural disruptions in the limbic tracts are present at the early stage of AD in an APOE-independent manner; and this degeneration may occur progressively, in parallel with parahippocampal atrophy, and may specifically contribute to early initial impairment in episodic memory.

Cost-Utility of Using Alzheimer's Disease Biomarkers in Cerebrospinal Fluid to Predict Progression from Mild Cognitive Impairment to Dementia. - Handels, Ron L H; Wimo, Anders; Dodel, Richard; Kramberger, Milica G; Visser, Pieter Jelle; Molinuevo, José Luis; Verhey, Frans R J; Winblad, Bengt (J Alzheimers Dis, 2017)
BACKGROUND: Diagnostic research criteria for Alzheimer's disease support the use of biomarkers in the cerebrospinal fluid (CSF) to improve the accuracy of the prognosis regarding progression to dementia for people with mild cognitive impairment (MCI). OBJECTIVE: The aim of this study was to estimate the potential incremental cost-effectiveness ratio of adding CSF biomarker testing to the standard diagnostic workup to determine the prognosis for patients with MCI. METHODS: In an early technology assessment, a mathematical simulation model was built, using available evidence on added prognostic value as well as expert opinion to estimate the incremental costs and quality-adjusted life years (QALYs) of 20,000 virtual MCI patients with (intervention strategy) and without (control strategy) relying on CSF, from a health-care sector perspective and with a 5-year time horizon. RESULTS: Adding the CSF test improved the accuracy of prognosis by 11%. This resulted in an average QALY gain of 0.046 and € 432 additional costs per patient, representing an incremental cost-effectiveness ratio of € 9,416. CONCLUSION: The results show the potential of CSF biomarkers in current practice from a health-economics perspective. This result was, however, marked by a high degree of uncertainty, and empirical research is required into the impact of a prognosis on worrying, false-positive/negative prognosis, and stigmatization.

Cyclic cis-Locked Phospho-Dipeptides Reduce Entry of AβPP into Amyloidogenic Processing Pathway. - Fisher, Carolyn L; Resnick, Ross J; De, Soumya; Acevedo, Lucila A; Lu, Kun Ping; Schroeder, Frank C; Nicholson, Linda K (J Alzheimers Dis, 2017)
The cis/trans isomerization of X-Pro peptide bonds in proteins in some instances acts as a molecular switch in biological pathways. Our prior work suggests that the cis isomer of the phospho-Thr668-Pro669 motif, located in the cytoplasmic domain of the amyloid-β protein precursor (AβPP), is correlated with an increase in amyloidogenic processing of AβPP and production of amyloid-beta (Aβ), the neurotoxic peptide fragment in Alzheimer's disease (AD). We designed a 100% cis-locked cyclic dipeptide composed of cyclized phospho-Thr-Pro (pCDP) as a mimic for this putative pathological conformation, and three phosphate-blocked derivatives (pCDP-diBzl, pCDP-Bzl, and pCDP-diPOM). Two H4 neuroglioma cell lines were established as AD cell models for use in testing these compounds: H4-AβPP695 for stable overexpression of wild-type AβPP695, and H4-BACE1 for stable overexpression of β-site AβPP cleaving enzyme-1 (BACE1). The level of the secreted AβPP fragment resulting from BACE1 activity, sAβPPβ, served as a key proxy for amyloidogenic processing, since cleavage of AβPP by BACE1 is a requisite first step in Aβ production. Of the compounds tested, pCDP-diBzl decreased sAβPPβ levels in both cell lines, while pCDP-diPOM decreased sAβPPβ levels in only H4-BACE1 cells, all with similar dose-dependences and patterns of proteolytic AβPP fragments. Enzymatic assays showed that none of the pCDP derivatives directly inhibit BACE1 catalytic activity. These results suggest a model in which pCDP-diBzl and pCDP-diPOM act at a common point to inhibit entry of AβPP into the amyloidogenic AβPP processing pathway but through different targets, and provide important insights for the development of novel AD therapeutics.

Cyclophilin D Promotes Brain Mitochondrial F1FO ATP Synthase Dysfunction in Aging Mice. - Gauba, Esha; Guo, Lan; Du, Heng (J Alzheimers Dis, 2017)
Brain aging is the known strongest risk factor for Alzheimer's disease (AD). In recent years, mitochondrial deficits have been proposed to be a common mechanism linking brain aging to AD. Therefore, to elucidate the causative mechanisms of mitochondrial dysfunction in aging brains is of paramount importance for our understanding of the pathogenesis of AD, in particular its sporadic form. Cyclophilin D (CypD) is a specific mitochondrial protein. Recent studies have shown that F1FO ATP synthase oligomycin sensitivity conferring protein (OSCP) is a binding partner of CypD. The interaction of CypD with OSCP modulates F1FO ATP synthase function and mediates mitochondrial permeability transition pore (mPTP) opening. Here, we have found that increased CypD expression, enhanced CypD/OSCP interaction, and selective loss of OSCP are prominent brain mitochondrial changes in aging mice. Along with these changes, brain mitochondria from the aging mice demonstrated decreased F1FO ATP synthase activity and defective F1FO complex coupling. In contrast, CypD deficient mice exhibited substantially mitigated brain mitochondrial F1FO ATP synthase dysfunction with relatively preserved mitochondrial function during aging. Interestingly, the aging-related OSCP loss was also dramatically attenuated by CypD depletion. Therefore, the simplest interpretation of this study is that CypD promotes F1FO ATP synthase dysfunction and the resultant mitochondrial deficits in aging brains. In addition, in view of CypD and F1FO ATP synthase alterations seen in AD brains, the results further suggest that CypD-mediated F1FO ATP synthase deregulation is a shared mechanism linking mitochondrial deficits in brain aging and AD.

Dementia Prevalence in a Rural Region of South Africa: A Cross-Sectional Community Study. - de Jager, Celeste A; Msemburi, William; Pepper, Katy; Combrinck, Marc I (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is a growing concern for low- and middle-income countries where longevity is increasing and service provision is poor. Global prevalence estimates vary from 2% to 8.5% for those aged 60 years and older. There have been few dementia studies in sub-Saharan Africa, and prevalence data are lacking for South Africa. OBJECTIVE: To conduct a large dementia prevalence study in a low income rural population in South Africa. METHODS: 1,394 Xhosa-speaking community dwellers, aged ≥60 y (mean age±sd 71.3±8.3 y), in three clinic catchment areas, were screened at home. Trained community health workers administered the brief Community Screening Instrument for Dementia (CSID) to participants and informants to assess cognitive and functional capacity. Depressive symptoms were assessed with three questions from the EURO-D. RESULTS: The prevalence estimate using published CSID sensitivity/specificity values was 0.8 (95% CI: 0.06-0.09). Using CSID cut-off scores the estimated prevalence was 0.12 (95% CI: 0.10-0.13), with 161 screen-positives. Both methods gave a rate of 0.11 (95% CI: 0.09-0.13) for those over 65 years (n = 1051). 68.6% of participants were female and 69.8% had less than 7 years of education. Dementia risk was associated with older age and symptoms of depression, but not with sex. The association with education was not significant when controlled for by age. CONCLUSIONS: Dementia prevalence estimates were higher than expected for this low-income rural community. There is a need for increased dementia awareness and feasible support interventions. We also need further studies of regional prevalences, dementia subtypes, and modifiable risk factors in South Africa.

Depressive Symptoms and Tau Accumulation in the Inferior Temporal Lobe and Entorhinal Cortex in Cognitively Normal Older Adults: A Pilot Study. - Gatchel, Jennifer R; Donovan, Nancy J; Locascio, Joseph J; Schultz, Aaron P; Becker, J Alex; Chhatwal, Jasmeer; Papp, Kathryn V; Amariglio, Rebecca E; Rentz, Dorene M; Blacker, Deborah; Sperling, Reisa A; Johnson, Keith A; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Depressive symptoms are common in older adults and associated with increased morbidity and cognitive decline. These symptoms occur during preclinical and prodromal stages of Alzheimer's disease (AD), but their relationship to tau, one of the main AD proteinopathies, is poorly understood. OBJECTIVE: The objective of this study was to investigate the cross-sectional association between depressive symptoms and cerebral tau [18F T807 (also known as 18F-AV-1451) tau positron emission tomography (PET) imaging] in cognitively normal (CN) older adults. METHODS: We measured depressive symptoms using the Geriatric Depression Scale (GDS), and in vivo cerebral tau using T807 PET in 111 CN older adults. We employed general linear regression models to evaluate the relationship of GDS score regressed on entorhinal cortex (EC) or inferior temporal (IT) tau in separate backward elimination models. Other predictors included age, sex, and in secondary analyses, amyloid (Pittsburgh Compound B PET). RESULTS: Higher GDS was significantly associated with greater IT tau (partial r = 0.188, p = 0.050) and marginally associated with greater EC tau (partial r = 0.183, p = 0.055). In additional analyses including both linear and quadratic age terms, we found a significant U-shaped relation of GDS to age (p = 0.001). CONCLUSIONS: Results suggest that IT and EC tau are modestly associated with depressive symptoms in CN older adults. Findings suggest a link between depressive symptoms and tau-mediated neurodegeneration in a region vulnerable in AD. Future longitudinal studies examining the association of more severe depressive symptoms and cerebral tau accumulation are needed to substantiate this finding and to guide prevention and treatment in AD.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.

Discriminative Properties of Hippocampal Hypoperfusion in Marijuana Users Compared to Healthy Controls: Implications for Marijuana Administration in Alzheimer's Dementia. - Amen, Daniel G; Darmal, Borhan; Raji, Cyrus A; Bao, Weining; Jorandby, Lantie; Meysami, Somayeh; Raghavendra, Cauligi S (J Alzheimers Dis, 2017)
BACKGROUND: Few studies have evaluated the impact of marijuana use on regional cerebral blood flow. OBJECTIVE: To determine whether perfusion in specific brain regions on functional neuroimaging, including those affected by Alzheimer's disease pathology, are abnormal in marijuana users compared to controls. METHOD: Persons with a diagnosis of cannabis use disorder by DSM-IV and DSM-V criteria (n = 982) were compared to controls (n = 92) with perfusion neuroimaging with SPECT at rest and at a concentration task. Perfusion estimates were quantified using a standard atlas. Cerebral perfusion differences were calculated using one-way ANOVA. Diagnostic separation was determined with discriminant analysis of all subjects. Feature selection with a minimum redundancy maximum relevancy (mRMR) identified predictive regions in a subset of marijuana users (n = 436) with reduced psychiatric co-morbidities. RESULTS: Marijuana users showed lower cerebral perfusion on average (p < 0.05). Discriminant analysis distinguished marijuana users from controls with correct classification of 96% and leave one out cross-validation of 92%. With concentration SPECT regions, there was correct classification of 95% with a leave-one-out cross validation of 90%. AUC analysis for concentration SPECT regions showed 95% accuracy, 90% sensitivity, and 83% specificity. The mRMR analysis showed right hippocampal hypoperfusion on concentration SPECT imaging was the most predictive in separating marijuana subjects from controls. CONCLUSION: Multiple brain regions show low perfusion on SPECT in marijuana users. The most predictive region distinguishing marijuana users from healthy controls, the hippocampus, is a key target of Alzheimer's disease pathology. This study raises the possibility of deleterious brain effects of marijuana use.

Disinhibition in Alzheimer's Disease is Associated with Reduced Right Frontal Pole Cortical Thickness. - Finger, Elizabeth; Zhang, Jing; Dickerson, Bradford; Bureau, Yves; Masellis, Mario (J Alzheimers Dis, 2017)
Neuropsychiatric symptoms in Alzheimer's disease are among the most disabling and difficult aspects for caregivers and treating health professionals to manage. Despite the high prevalence of these behaviors, little is known about the factors which lead some patients to develop florid behavioral symptoms while others may progress to severe dementia without such phenomenon. We examined whether regional brain volumes as measured by cortical thickness would predict the presence or absence of disinhibition in patients with Alzheimer's disease. Using data from the ADNI, we identified 758 patients with caregiver ratings on the Neuropsychiatric Inventory and a volumetric MRI scan with cortical thickness measurements completed in FreeSurfer by the UCSF core. Of these, 177 patients were found to have disinhibition. Logistic regression models demonstrated that reduced cortical thickness in the right frontal pole was associated with the presence of disinhibition even when controlling for age, disease severity, total intracranial volume, gender, and APOE genotype. The results are considered in the context of leading models of the functions of frontopolar cortex.

Diverging Progression of Network Disruption and Atrophy in Alzheimer's Disease and Semantic Dementia. - Andreotti, Jennifer; Dierks, Thomas; Wahlund, Lars-Olof; Grieder, Matthias (J Alzheimers Dis, 2017)
The progression of cognitive deficits in Alzheimer's disease and semantic dementia is accompanied by grey matter atrophy and white matter deterioration. The impact of neuronal loss on the structural network connectivity in these dementia subtypes is, however, not well understood. In order to gain a more refined knowledge of the topological organization of white matter alterations in dementia, we used a network-based approach to analyze the brain's structural connectivity network. Diffusion-weighted and anatomical MRI images of groups with eighteen Alzheimer's disease and six semantic dementia patients, as well as twenty-one healthy controls were recorded to reconstruct individual connectivity networks. Additionally, voxel-based morphometry, using grey and white matter volume, served to relate atrophy to altered structural connectivity. The analyses showed that Alzheimer's disease is characterized by decreased connectivity strength in various cortical regions. An overlap with grey matter loss was found only in the inferior frontal and superior temporal areas. In semantic dementia, significantly reduced network strength was found in the temporal lobes, which converged with grey and white matter atrophy. Therefore, this study demonstrated that the structural disconnection in early Alzheimer's disease goes beyond grey matter atrophy and is independent of white matter volume loss, an observation that was not found in semantic dementia.

Does Functional Connectivity Provide a Marker for Cognitive Rehabilitation Effects in Alzheimer's Disease? An Interventional Study. - Ochmann, Sina; Dyrba, Martin; Grothe, Michel J; Kasper, Elisabeth; Webel, Steffi; Hauenstein, Karlheinz; Teipel, Stefan J (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive rehabilitation (CR) is a cognitive intervention for patients with Alzheimer's disease (AD) that aims to maintain everyday competences. The analysis of functional connectivity (FC) in resting-state functional MRI has been used to investigate the effects of cognitive interventions. OBJECTIVES: We evaluated the effect of CR on the default mode network FC in a group of patients with mild AD, compared to an active control group. METHODS: We performed a three-month interventional study including 16 patients with a diagnosis of AD. The intervention group (IG) consisted of eight patients, performing twelve sessions of CR. The active control group (CG) performed a standardized cognitive training. We used a seed region placed in the posterior cingulate cortex (PCC) for FC analysis, comparing scans acquired before and after the intervention. Effects were thresholded at a significance of p < 0.001 (uncorrected) and a minimal cluster size of 50 voxels. RESULTS: The interaction of group by time showed a higher increase of PCC connectivity in IG compared to CG in the bilateral cerebellar cortex. CG revealed widespread, smaller clusters of higher FC increase compared with IG. Across all participants, an increase in quality of life was associated with connectivity increase over time in the bilateral precuneus. CONCLUSIONS: CR showed an effect on the FC of the DMN in the IG. These effects need further study in larger samples to confirm if FC analysis may suit as a surrogate marker for the effect of cognitive interventions in AD.

Down Syndrome, Partial Trisomy 21, and Absence of Alzheimer's Disease: The Role of APP. - Doran, Eric; Keator, David; Head, Elizabeth; Phelan, Michael J; Kim, Ron; Totoiu, Minodora; Barrio, Jorge R; Small, Gary W; Potkin, Steven G; Lott, Ira T (J Alzheimers Dis, 2017)
Overexpression of the amyloid precursor protein (APP) gene on chromosome 21 in Down syndrome (DS) has been linked to increased brain amyloid levels and early-onset Alzheimer's disease (AD). An elderly man with phenotypic DS and partial trisomy of chromosome 21 (PT21) lacked triplication of APP affording an opportunity to study the role of this gene in the pathogenesis of dementia. Multidisciplinary studies between ages 66-72 years comprised neuropsychological testing, independent neurological exams, amyloid PET imaging with 11C-Pittsburgh compound-B (PiB), plasma amyloid-β (Aβ) measurements, and a brain autopsy examination. The clinical phenotype was typical for DS and his intellectual disability was mild in severity. His serial neuropsychological test scores showed less than a 3% decline as compared to high functioning individuals with DS who developed dementia wherein the scores declined 17-28% per year. No dementia was detected on neurological examinations. On both PiB-PET scans, the patient with PT21 had lower PiB standard uptake values than controls with typical DS or sporadic AD. Plasma Aβ42 was lower than values for demented or non-demented adults with DS. Neuropathological findings showed only a single neuritic plaque and neurofibrillary degeneration consistent with normal aging but not AD. Taken together the findings in this rare patient with PT21 confirm the obligatory role of APP in the clinical, biochemical, and neuropathological findings of AD in DS.

Early Evidence of Low Bone Density and Decreased Serotonergic Synthesis in the Dorsal Raphe of a Tauopathy Model of Alzheimer's Disease. - Dengler-Crish, Christine M; Smith, Matthew A; Wilson, Gina N (J Alzheimers Dis, 2017)
Reduced bone mineral density (BMD) and its clinical sequelae, osteoporosis, occur at a much greater rate in patients with Alzheimer's disease (AD), often emerging early in the disease before significant cognitive decline is seen. Reduced BMD translates to increased bone fracture risk, decreased quality of life, and increased mortality for AD patients. However, the mechanism responsible for this observation is unclear. We hypothesize that bone loss is an additional component of an AD prodrome-changes that emerge prior to dementia and are mediated by dysfunction of the central serotonergic pathways. We characterized the skeletal phenotype of htau mice that express human forms of the microtubule-associated protein tau that become pathologically hyperphosphorylated in AD. Using radiographic densitometry, we measured BMD in female and male htau mice from 2-6 months of age-time-points prior to the presence of significant tauopathy in the hippocampal/entorhinal regions characteristic of this model. We found a significantly reduced BMD phenotype in htau mice that was most pronounced in males. Using western blotting and immunofluorescence, we showed overall reduced tryptophan hydroxylase (TPH) protein in htau brainstem and a 70% reduction in TPH-positive cells in the dorsal raphe nucleus (DRN)-a pivotal structure in the regulation of the adult skeleton. Elevations of hyperphosphorylated tau (ptau) proteins were also measured in brainstem, and co-labeled immunofluorescence studies showed presence of ptau in TPH-positive cells of the DRN as early as 4 months of age in htau mice. Together, these findings demonstrate that reduced BMD occurs earlier than overt degeneration in a tau-based AD model and that pathological changes in tau phosphorylation occur in the serotonin-producing neurons of the brainstem raphe in these mice. This illuminates a need to define a mechanistic relationship between bone loss and serotonergic deficits in early AD.

EEG Dominant Frequency Peak Differentiates Between Alzheimer's Disease and Frontotemporal Lobar Degeneration. - Goossens, Joery; Laton, Jorne; Van Schependom, Jeroen; Gielen, Jeroen; Struyfs, Hanne; Van Mossevelde, Sara; Van den Bossche, Tobi; Goeman, Johan; De Deyn, Peter Paul; Sieben, Anne; Martin, Jean-Jacques; Van Broeckhoven, Christine; et al. (J Alzheimers Dis, 2017)
We investigated the power of EEG as biomarker in differential diagnosis of Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). EEG was recorded from 106 patients with AD or FTLD, of which 37 had a definite diagnosis, and 40 controls. Dominant frequency peaks were extracted for all 19 channels, for each subject. The average frequency of the largest dominant frequency peaks (maxpeak) was significantly lower in AD than FTLD patients and controls. Based on ROC analysis, classification could be made with diagnostic accuracy of 78.9%. Our findings show that quantitative analysis of EEG maxpeak frequency is an easy and useful measure for differential dementia diagnosis.

Effect of Attention Training in Mild Cognitive Impairment Patients with Subcortical Vascular Changes: The RehAtt Study. - Pantoni, Leonardo; Poggesi, Anna; Diciotti, Stefano; Valenti, Raffaella; Orsolini, Stefano; Della Rocca, Eleonora; Inzitari, Domenico; Mascalchi, Mario; Salvadori, Emilia (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: Mild cognitive impairment (MCI) patients with small vessel disease (SVD) are at high dementia risk. We tested the effects of cognitive rehabilitation in these patients using the Attention Process Training-II (APT-II) program in a single-blinded, randomized clinical trial. METHODS: Patients were randomized to APT-II or standard care and evaluated at baseline, 6, and 12 months with functional, quality of life, cognitive tests, and resting state functional MRI (rsfMRI). RESULTS: Forty-six patients were enrolled and 43 (mean±SD age 75.1±6.8) completed the study. No change was seen in functionality and quality of life between treated and non-treated patients. However, the Rey Auditory-Verbal Learning Test immediate recall showed a significant improvement in treated compared to non-treated group (change score 6 versus 12 months: 1.8±4.9 and -1.4±3.8, p = 0.021; baseline versus 12 months: 3.8±6.1 and 0.2±4.4, p = 0.032). A higher proportion of treated patients had stable/better evaluation compared to non-treated group on Visual search test (6 versus 12 months: 95% versus 71%, p = 0.038) and Rey-Osterrieth Complex Figure copy (6 versus 12 months: 95% versus 67%, p = 0.027). RsfMRI, performed in a subsample, showed that the difference between follow-up and baseline in synchronization of activity in cerebellar areas was significantly greater in treated than in non-treated patients. CONCLUSION: We were unable to show a significant effect in quality of life or functional status in treated patients with MCI and SVD. However, APT-II produces some beneficial effects in focused attention and working memory and seems to increase activity in brain circuits involved in cognitive processes.

Effect of Vascular Risk Factors on the Progression of Mild Alzheimer's Disease and Lewy Body Dementia. - Bergland, Anne Katrine; Dalen, Ingvild; Larsen, Alf Inge; Aarsland, Dag; Soennesyn, Hogne (J Alzheimers Dis, 2017)
BACKGROUND: Vascular risk factors (VRF) are associated with an increased risk of neurodegenerative disease. OBJECTIVE: To examine the association between VRF and cognitive decline in patients with Alzheimer's disease (AD) and Lewy body dementia (LBD). METHODS: We included consecutive referrals with mild AD or LBD to dementia clinics in western Norway from 2005 to 2013. The Mini-Mental Status Exam (MMSE) and Clinical Dementia Rating Scale Sum of Boxes (CDR-SB) were administered at baseline and then annually for up to five years. The VRF include diabetes mellitus, hypertension, hypercholesterolemia, overweight and smoking. Generalized Estimating Equations (GEE) were used to examine the potential association between VRF scores and the change in MMSE and CDR-SB scores, adjusting for age, sex, and the apolipoprotein ɛ4 allele (APOE4). RESULTS: A total of 200 patients were included (113 AD, 87 LBD) (mean age 76 years, mean baseline MMSE 24.0, mean follow-up time 3.5 years). Smoking was the only VRF significantly associated with a more rapid cognitive decline, however only in the AD group. Being overweight at baseline was associated with a slower cognitive decline. Moreover, hypertension at baseline predicted a slower decline in MMSE scores. In the LBD group diabetes mellitus was found to be associated with a slower increase in CDR-SB scores. CONCLUSION: With the exception of smoking, VRF at time of dementia diagnosis were not associated with a more rapid cognitive decline.

Effects of Healthy Aging and Mild Cognitive Impairment on a Real-Life Decision-Making Task. - Pertl, Marie-Theres; Benke, Thomas; Zamarian, Laura; Delazer, Margarete (J Alzheimers Dis, 2017)
In this study, we investigated the effects of age and of mild cognitive impairment (MCI) on decision making under risk by adopting a task representing real-life health-related situations and involving complex numerical information. Moreover, we assessed the relationship of real-life decision making to other cognitive functions such as number processing, executive functions, language, memory, and attention. For this reason, we compared the performance of 19 healthy, relatively younger adults with that of 18 healthy older adults and the performance of the 18 healthy older adults with that of 17 patients with MCI. Results indicated difficulties in real-life decision making for the healthy older adults compared with the healthy, relatively younger adults. Difficulties of patients with MCI relative to the healthy older adults arose in particular in difficult items requiring processing of frequencies and fractions. Significant effects of age and of MCI in processing frequencies were also evident in a ratio number comparison task. Decision-making performance of healthy participants and of the patient group correlated significantly with number processing. There was a further significant correlation with executive functions for the healthy participants and with reading comprehension for the patients. Our results suggest that healthy older individuals and patients with MCI make less advantageous decisions when the information is complex and high demands are put on executive functions and numerical abilities. Moreover, we show that executive functions and numerical abilities are not only essential in laboratory gambling tasks but also in more realistic and ecological decision situations within the health context.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Efficacy and Safety of Donepezil in Chinese Patients with Severe Alzheimer's Disease: A Randomized Controlled Trial. - Jia, Jianping; Wei, Cuibai; Jia, Longfei; Tang, Yi; Liang, Junhua; Zhou, Aihong; Li, Fangyu; Shi, Lu; Doody, Rachelle S (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil has been used worldwide for the treatment of severe Alzheimer's disease (AD). Whether it is also appropriate for severe AD in Chinese patients remains unknown. OBJECTIVE: To determine whether donepezil is effective and tolerable for Chinese patients with severe AD. METHODS: The present study was a 24-week, multicenter, double-blind, randomized, placebo-controlled, parallel-group study conducted at 38 investigational hospitals in China. Patients with severe AD were enrolled in this trial. Patients were randomly assigned in a 1:1 ratio to receive either donepezil or placebo (5 mg for 6 weeks and10 mg for the remaining 18 weeks). The efficacy for donepezil were evaluated by the SIB, the Clinician's Interview-Based Impression of Change-Plus caregiver input (CIBIC-plus) and the MMSE. Safety parameters were monitored throughout. RESULTS: A total of 313 patients included the donepezil (n = 157) and the placebo groups (n = 156). Donepezil group improved more in SIB scores (least squares [LS] mean difference: 4.8, 95% CI 1.56 to 8.08, p = 0.004) and CIBIC-plus scores (drug-placebo difference: -0.4, 95% CI -0.66 to 0.03, p = 0.04) than placebo groups at Week 24. The MMSE scores between drug and placebo groups did not differ significantly. Twenty-nine patients with serious adverse events (SAEs) were reported in donepezil (n = 11) and placebo groups (n = 18) (p = 0.08). Most SAEs were not considered drug-related. CONCLUSION: Donepezil for 24 weeks was more effective than placebo and showed good safety and tolerability in Chinese patients with severe AD. This study supports utility of the drug in severe stages of AD in the Chinese population.

Evidence that the Human Innate Immune Peptide LL-37 may be a Binding Partner of Amyloid-β and Inhibitor of Fibril Assembly. - De Lorenzi, Ersilia; Chiari, Marcella; Colombo, Raffaella; Cretich, Marina; Sola, Laura; Vanna, Renzo; Gagni, Paola; Bisceglia, Federica; Morasso, Carlo; Lin, Jennifer S; Lee, Moonhee; McGeer, Patrick L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Identifying physiologically relevant binding partners of amyloid-β (Aβ) that modulate in vivo fibril formation may yield new insights into Alzheimer's disease (AD) etiology. Human cathelicidin peptide, LL-37, is an innate immune effector and modulator, ubiquitous in human tissues and expressed in myriad cell types. OBJECTIVE: We present in vitro experimental evidence and discuss findings supporting a novel hypothesis that LL-37 binds to Aβ42 and can modulate Aβ fibril formation. METHODS: Specific interactions between LL-37 and Aβ (with Aβ in different aggregation states, assessed by capillary electrophoresis) were demonstrated by surface plasmon resonance imaging (SPRi). Morphological and structural changes were investigated by transmission electron microscopy (TEM) and circular dichroism (CD) spectroscopy. Neuroinflammatory and cytotoxic effects of LL-37 alone, Aβ42 alone, and LL-37/Aβ complexes were evaluated in human microglia and neuroblastoma cell lines (SH-SY5Y). RESULTS: SPRi shows binding specificity between LL-37 and Aβ, while TEM shows that LL-37 inhibits Aβ42 fibril formation, particularly Aβ's ability to form long, straight fibrils characteristic of AD. CD reveals that LL-37 prevents Aβ42 from adopting its typical β-type secondary structure. Microglia-mediated toxicities of LL-37 and Aβ42 to neurons are greatly attenuated when the two peptides are co-incubated prior to addition. We discuss the complementary biophysical characteristics and AD-related biological activities of these two peptides. CONCLUSION: Based on this body of evidence, we propose that LL-37 and Aβ42 may be natural binding partners, which implies that balanced (or unbalanced) spatiotemporal expression of the two peptides could impact AD initiation and progression.

Failure to Recover from Proactive Semantic Interference and Abnormal Limbic Connectivity in Asymptomatic, Middle-Aged Offspring of Patients with Late-Onset Alzheimer's Disease. - Sánchez, Stella M; Abulafia, Carolina; Duarte-Abritta, Barbara; de Guevara, M Soledad Ladrón; Castro, Mariana N; Drucaroff, Lucas; Sevlever, Gustavo; Nemeroff, Charles B; Vigo, Daniel E; Loewenstein, David A; Villarreal, Mirta F; Guinjoan, Salvador M (J Alzheimers Dis, 2017)
BACKGROUND: We have obtained previous evidence of limbic dysfunction in middle-aged, asymptomatic offspring of late-onset Alzheimer's disease (LOAD) patients, and failure to recover from proactive semantic interference has been shown to be a sensitive cognitive test in other groups at risk for LOAD. OBJECTIVE: To assess the effects of specific proactive semantic interference deficits as they relate to functional magnetic resonance imaging (fMRI) neocortical and limbic functional connectivity in middle aged offspring of individuals with LOAD (O-LOAD) and age-equivalent controls. METHODS: We examined 21 O-LOAD and 20 controls without family history of neurodegenerative disorders (CS) on traditional measures of cognitive functioning and the LASSI-L, a novel semantic interference test uniquely sensitive to the failure to recover from proactive interference (frPSI). Cognitive tests then were correlated to fMRI connectivity of seeds located in entorhinal cortex and anterodorsal thalamic nuclei among O-LOAD and CS participants. RESULTS: Relative to CS, O-LOAD participants evidenced lower connectivity between entorhinal cortex and orbitofrontal, anterior cingulate, and anterior temporal cortex. In the offspring of LOAD patients, LASSI-L measures of frPSI were inversely associated with connectivity between anterodorsal thalamus and contralateral posterior cingulate. Intrusions on the task related to frPSI were inversely correlated with a widespread connectivity network involving hippocampal, insular, posterior cingulate, and dorsolateral prefrontal cortices, along with precunei and anterior thalamus in this group. Different patterns of connectivity associated with frPSI were observed among controls. CONCLUSION: The present results suggest that both semantic interference deficits and connectivity abnormalities might reflect limbic circuit dysfunction as a very early clinical signature of LOAD pathology, as previously demonstrated for other limbic phenotypes, such as sleep and circadian alterations.

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Finger-to-Nose Test Findings in Alzheimer's Disease. - Bergeron, David; Vermette, Antoine; De La Sablonnière, Justine; Cayer, Anne-Marie; Laforce, Robert; Bouchard, Rémi W (J Alzheimers Dis, 2017)
The finger-to-nose test is routinely performed during the clinical assessment of patients with cognitive impairments. Although widely known to screen for cerebellar dysfunction by unmasking appendicular ataxia, we have found that this test could also be interpreted from a cognitive perspective. We describe two typical signs observed at the finger-to-nose test in Alzheimer's disease (AD) patients: the "second finger syndrome" and the "distal pressure sign". By retrospectively reviewing the medical records 461 patients followed at our academic memory clinic, we found that these signs are commonplace in AD, but not in vascular dementia or subjective cognitive impairment.

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer's Disease. - Reiter, Katherine; Nielson, Kristy A; Durgerian, Sally; Woodard, John L; Smith, J Carson; Seidenberg, Michael; Kelly, Dana A; Rao, Stephen M (J Alzheimers Dis, 2017)
Neuropathological changes associated with Alzheimer's disease (AD) precede symptom onset by more than a decade. Possession of an apolipoprotein E (APOE) ɛ4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ɛ4 carriers (ɛ4+) compared to ɛ4 non-carriers (ɛ4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ɛ4+ and ɛ4- individuals. The current five-year study examined global and regional volumes of cortical and subcortical grey and white matter and ventricular size in 42 ɛ4+ and 30 ɛ4- individuals. Cognitively intact participants, ages 65-85 at study entry, underwent repeat anatomical MRI scans on three occasions: baseline, 1.5, and 4.75 years. Results indicated no between-group volumetric differences at baseline. Over the follow-up interval, the ɛ4+ group experienced a greater rate of volume loss in total grey matter, bilateral hippocampi, right hippocampal subfields, bilateral lingual gyri, bilateral parahippocampal gyri, and right lateral orbitofrontal cortex compared to the ɛ4- group. Greater loss in grey matter volumes in ɛ4+ participants were accompanied by greater increases in lateral, third, and fourth ventricular volumes. Rate of change in white matter volumes did not differentiate the groups. The current results indicate that longitudinal measurements of brain atrophy can serve as a sensitive biomarker for identifying neuropathological changes in persons at genetic risk for AD and potentially, for assessing the efficacy of treatments designed to slow or prevent disease progression during the preclinical stage of AD.

Frontotemporal Dementia due to the Novel GRN Arg161GlyfsX36 Mutation. - Gazzina, Stefano; Archetti, Silvana; Alberici, Antonella; Bonomi, Elisa; Cosseddu, Maura; Di Lorenzo, Diego; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2017)
Progranulin is a multifunctional growth factor mainly expressed in neurons and microglia. Loss-of-function mutations in the Granulin (GRN) gene are causative of frontotemporal dementia with TAR DNA-binding protein-43 inclusions. We reported the case of a 51-year-old male patient affected by sporadic agrammatic variant of primary progressive aphasia, in whom we identified a novel heterozygous deletion in the exon 6 (g.10338_39delAG, p.Arg161GlyfsX36). Plasma progranulin levels were significantly reduced and in silico analysis predicted a premature termination codon. This case expands our knowledge on GRN mutations in frontotemporal dementia.

Functional Connectivity in the Default Mode Network is Reduced in Association with Nocturnal Awakening in Mild Cognitive Impairment. - McKinnon, Andrew C; Duffy, Shantel L; Cross, Nathan E; Terpening, Zoe; Grunstein, Ron R; Lagopoulos, Jim; Batchelor, Jennifer; Hickie, Ian B; Lewis, Simon J G; Shine, James M; Naismith, Sharon L (J Alzheimers Dis, 2017)
BACKGROUND: Sleep disturbance is prevalent in MCI, and is a risk factor for cognitive deterioration. OBJECTIVE: To identify functional connectivity deficits in the default mode network (DMN) in patients with mild cognitive impairment (MCI) and sleep disturbance, relative to MCIs with intact sleep. METHODS: Participants comprised 47 adults aged 55 years and over, recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney, Australia. This sample contained 15 controls and 32 participants meeting criteria for MCI. Participants underwent resting-state fMRI and actigraphy, along with comprehensive neuropsychological, medical and psychiatric assessment. MCIs were split into two groups according to average wake after sleep onset (WASO) per night. WASO equal to or greater than 1 standard deviation (SD) above the control mean was deemed to reflect disturbed sleep. There were 11 patients in the MCI sleep-disturbed group, and 21 in the MCI sleep-intact group. RESULTS: Relative to controls, MCIs demonstrated significant connectivity reductions between parietal and temporoparietal regions, and between temporal regions. Relative to MCIs with intact sleep, MCIs with sleep disturbance demonstrated reductions in functional connectivity between temporal and parietal regions, and between temporal and temporoparietal regions. CONCLUSIONS: MCIs with nocturnal awakenings demonstrate reductions in DMN connectivity. These reductions comprise brain regions that are crucially involved in sleep and memory processes. These results strengthen our previous findings, which found reduced connectivity in MCIs with self-reported sleep disturbances. Future studies may build on these findings through incorporating complementary neuroimaging techniques and experimental manipulations of sleep.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

Genetic Stratification to Identify Risk Groups for Alzheimer's Disease. - Marioni, Riccardo E; Campbell, Archie; Hagenaars, Saskia P; Nagy, Reka; Amador, Carmen; Hayward, Caroline; Porteous, David J; Visscher, Peter M; Deary, Ian J (J Alzheimers Dis, 2017)
Stratification by genetic risk factors for Alzheimer's disease (AD) may help identify groups with the greatest disease risk. Biological changes that cause late-onset AD are likely to occur years, if not decades prior to diagnosis. Here, we select a subset of the Generation Scotland: Scottish Family Health Study cohort in a likely preclinical age-range of 60-70 years (subset n = 3,495 with cognitive and genetic data). We test for cognitive differences by polygenic risk scores for AD. The polygenic scores are constructed using all available SNPs, excluding those within a 500 kb distance of the APOE locus. Additive and multiplicative effects of APOE status on these associations are investigated. Small memory decrements were observed in those with high polygenic risk scores for AD (standardized beta -0.04, p = 0.020). These associations were independent of APOE status. There was no difference in AD polygenic scores across APOE haplotypes (p = 0.72). Individuals with high compared to low polygenic risk scores for AD (top and bottom 5% of the distribution) show cognitive decrements, albeit much smaller than for APOE ɛ4ɛ4 compared to ɛ3ɛ3 individuals (2.3 versus 3.5 fewer points on the processing speed test, and 1.8 versus 2.8 fewer points on the memory test). Polygenic risk scores for AD may help identify older individuals at greatest risk of cognitive decline and preclinical AD.

High Sensitivity Cardiac Troponin T and Cognitive Function in the Oldest Old: The Leiden 85-Plus Study. - Bertens, Anne Suzanne; Sabayan, Behnam; de Craen, Anton J M; Van der Mast, Roos C; Gussekloo, Jacobijn (J Alzheimers Dis, 2017)
BACKGROUND: Impaired cardiac function has been related to accelerated cognitive decline in late-life. OBJECTIVE: To investigate whether higher levels of high sensitivity cardiac troponin T (hs-cTnT), a sensitive marker for myocardial injury, are associated with worse cognitive function in the oldest old. METHODS: In 455 participants of the population-based Leiden 85-plus Study, hs-cTnT was measured at 86 years. Cognitive function was measured annually during four years with the Mini-Mental State Examination (MMSE). RESULTS: Participants in the highest gender-specific tertile of hs-cTnT had a 2.0-point lower baseline MMSE score than participants in the lowest tertile (95% confidence interval (CI) (95% CI 0.73-3.3), and had a 0.58-point steeper annual decline in MMSE during follow-up (95% CI 0.06-1.1). The associations remained after adjusting for sociodemographic and cardiovascular risk factors excluding those without a history of overt cardiac disease. CONCLUSION: In a population-based sample of the oldest old, higher levels of hs-cTnT were associated with worse cognitive function and faster cognitive decline, independently from cardiovascular risk factors and a history of overt cardiac disease.

A High-Cholesterol Diet Increases 27-Hydroxycholesterol and Modifies Estrogen Receptor Expression and Neurodegeneration in Rabbit Hippocampus. - Brooks, Sylwia W; Dykes, Ava C; Schreurs, Bernard G (J Alzheimers Dis, 2017)
Hypercholesterolemia has been implicated in numerous health problems from cardiovascular disease to neurodegeneration. High serum cholesterol levels in midlife have been associated with an increased risk of developing Alzheimer's disease (AD) later in life which suggests that the pathways leading to AD pathology might be activated decades before the symptoms of the disease are detected. Cholesterol-fed animals, particularly cholesterol-fed rabbits, exhibit brain pathology similar to the changes found in brains of AD patients. Dietary cholesterol, which cannot pass the blood-brain barrier, is thought to influence central nervous system homeostasis by increased transport of its circulatory breakdown product, 27-hydroxycholesterol (27-OHC), into the brain. 27-OHC is an endogenous selective estrogen receptor modulator. Estrogen-mediated non-reproductive functions require estrogen receptors (ERs) and include modulation of mitochondrial function and structure, as well as regulation of synaptogenesis in the brain. ERs are located in brain areas affected early in AD pathogenesis, including the hippocampus. Here we report that increase in serum cholesterol, induced by feeding rabbits a high-cholesterol diet, is associated with higher levels of 27-OHC in the brain as well as increased levels of neurodegeneration in the hippocampus. Furthermore, these results are accompanied by changes in expression of ERs in the hippocampus as well as a decrease in hippocampal mitochondria. These findings provide an important insight into one of the possible mechanisms involved in the development of AD, and shed light on the processes that may antedate amyloid-β and tau phosphorylation changes currently hypothesized to cause AD symptomology and pathology.

Histogram-Based Feature Extraction from Individual Gray Matter Similarity-Matrix for Alzheimer's Disease Classification. - Beheshti, Iman; Maikusa, Norihide; Matsuda, Hiroshi; Demirel, Hasan; Anbarjafari, Gholamreza (J Alzheimers Dis, 2017)
Automatic computer-aided diagnosis (CAD) systems have been widely used in classification of patients who suffer from Alzheimer's disease (AD). This paper presents an automatic CAD system based on histogram feature extraction from single-subject gray matter similarity-matrix for classifying the AD patients from healthy controls (HC) using structural magnetic resonance imaging (MRI) data. The proposed CAD system is composed of five stages. In the first stage, segmentation is employed to perform pre-processing on the MRI images, and segment into gray matter, white matter, and cerebrospinal fluid using the voxel-based morphometric toolbox procedure. In the second stage, gray matter MRI scans are used to construct similarity-matrices. In the third stage, a novel statistical feature-generation process is proposed, utilizing the histogram of the individual similarity-matrix to represent statistical patterns of the respective similarity-matrices of different size and order into fixed-size feature-vectors. In the fourth stage, we propose to combine MRI measures with a neuropsychological test, the Functional Assessment Questionnaire (FAQ), to improve the classification accuracy. Finally, the classification is performed using a support vector machine and evaluated with the 10-fold cross-validation strategy. We evaluated the proposed method on 99 AD and 102 HC subjects from the J-ADNI. The proposed CAD system yields an 84.07% classification accuracy using MRI measures and 97.01% for combining MRI measures with FAQ scores, respectively. The experimental results indicate that the performance of the proposed system is competitive with respect to state-of-the-art techniques reported in the literature.

Home-Based Exercise Program Improves Balance and Fear of Falling in Community-Dwelling Older Adults with Mild Alzheimer's Disease: A Pilot Study. - Padala, Kalpana P; Padala, Prasad R; Lensing, Shelly Y; Dennis, Richard A; Bopp, Melinda M; Roberson, Paula K; Sullivan, Dennis H (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Balance problems are common in older adults with Alzheimer's disease (AD). The objective was to study the effects of a Wii-Fit interactive video-game-led physical exercise program to a walking program on measures of balance in older adults with mild AD. METHODS: A prospective randomized controlled parallel-group trial (Wii-Fit versus walking) was conducted in thirty community-dwelling older adults (73±6.2 years) with mild AD. Home-based exercises were performed under caregiver supervision for 8 weeks. Primary (Berg Balance Scale, BBS) and secondary outcomes (fear of falls and quality of life) were measured at baseline, 8 weeks (end of intervention), and 16 weeks (8-weeks post-intervention). RESULTS: At 8 weeks, there was a significantly greater improvement (average inter-group difference [95% CI]) in the Wii-Fit group compared to the walking group in BBS (4.8 [3.3-6.2], p < 0.001), after adjusting for baseline. This improvement was sustained at 16 weeks (3.5 [2.0-5.0], p < 0.001). Analyses of the secondary outcome measures indicated that there was a significantly greater improvement in the Wii-Fit group compared to walking group in Activity-specific Balance Confidence scale (6.5 [3.6-9.4], p < 0.001) and Falls Efficacy Scale (-4.8 [-7.6 to -2.0], p = 0.002) at 8 weeks. However, this effect was not sustained at 16 weeks. Quality of life improved in both groups at 8 weeks; however, there were no inter-group differences (p = 0.445). CONCLUSION: Home-based, caregiver-supervised Wii-Fit exercises improve balance and may reduce fear of falling in community-dwelling older adults with mild AD.

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

The Impact of Alzheimer's Disease on the Resting State Functional Connectivity of Brain Regions Modulating Pain: A Cross Sectional Study. - Monroe, Todd B; Beach, Paul A; Bruehl, Stephen P; Dietrich, Mary S; Rogers, Baxter P; Gore, John C; Atalla, Sebastian W; Cowan, Ronald L (J Alzheimers Dis, 2017)
BACKGROUND: It is currently unknown why people with Alzheimer's disease (AD) receive less pain medication and report pain less frequently. OBJECTIVE: The purpose of this study was to determine the impact of AD on thermal psychophysics and resting-state functional connectivity (RSFC) among sensory, affective, descending modulatory, and default mode structures. METHODS: Controls (n = 23, 13 = female) and age-matched people with AD (n = 23, 13 = females) underwent psychophysical testing to rate perceptions of warmth, mild, and moderate pain and then completed resting-state fMRI. Between groups analysis in psychophysics and RSFC were conducted among pre-defined regions of interest implicated in sensory and affective dimensions of pain, descending pain modulation, and the default mode network. RESULTS: People with AD displayed higher thermal thresholds for warmth and mild pain but similar moderate pain thresholds to controls. No between-group differences were found for unpleasantness at any percept. Relative to controls, people with AD demonstrated reduced RSFC between the right posterior insula and left anterior cingulate and also between right amygdala and right secondary somatosensory cortex. Moderate pain unpleasantness reports were associated with increased RSFC between right dorsolateral prefrontal cortex and left ACC in controls only. CONCLUSIONS: While AD had little effect on unpleasantness, people with AD had increased thermal thresholds, altered RSFC, and no association of psychophysics with RSFC in pain regions. Findings begin to elucidate that in people with AD, altered integration of pain sensation, affect, and descending modulation may, in part, contribute to decreased verbal pain reports and thus decreased analgesic administration.

Impact of Recruitment Methods in Subjective Cognitive Decline. - Abdelnour, Carla; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Valero, Sergi; Moreno-Grau, Sonia; Sanabria, Ángela; Hernandez, Isabel; Rosende-Roca, Maitee; Vargas, Liliana; Mauleón, Ana; Sánchez, Domingo; Espinosa, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recruitment methods can determine sample characteristics in mild cognitive impairment and Alzheimer's disease dementia, but little is known about its influence in subjective cognitive decline (SCD). OBJECTIVE: To determine the influence of two types of recruitment methods in the characteristics of individuals with SCD. METHODS: We select and compare clinical and neuropsychological features, and frequency of APOE ɛ4 allele of 326 subjects with SCD from two cohorts: Open House Initiative (OHI) versus Memory Unit (MU). A logistic regression analysis (LRA), using gender and years of education as covariates, was used to examine the neuropsychological variables. RESULTS: The OHI sample were mostly women (75.9% versus 64.5%, p < 0.05), with higher educational level (12.15 [3.71] versus 10.70 [3.80] years, p = 0.001), and more family history of dementia (138 [62.7%] versus 44 [41.5%], p < 0.001) than the MU sample. Also, the OHI sample showed better overall neuropsychological performance than the MU sample, and after a LRA, this trend continued in automatic response inhibition capacity, abstract reasoning, and recognition memory. We did not find differences in age, depression history, and/or APOE ɛ4 allele frequency. CONCLUSION: SCD subjects showed different demographic and neuropsychological characteristics depending on the recruitment method, which should be taken into account in the design of research studies with this target population.

Impaired Processing of Serial Order Determines Working Memory Impairments in Alzheimer's Disease. - De Belder, Maya; Santens, Patrick; Sieben, Anne; Fias, Wim (J Alzheimers Dis, 2017)
BACKGROUND: Working memory (WM) problems are commonly observed in Alzheimer's disease (AD), but the affected mechanisms leading to impaired WM are still insufficiently understood. The ability to efficiently process serial order in WM has been demonstrated to be fundamental to fluent daily life functioning. The decreased capability to mentally process serial position in WM has been put forward as the underlying explanation for generally compromised WM performance. OBJECTIVE: Determine which mechanisms, such as order processing, are responsible for deficient WM functioning in AD. METHOD: A group of AD patients (n = 32) and their partners (n = 25), assigned to the control group, were submitted to an extensive battery of neuropsychological and experimental tasks, assessing general cognitive state and functioning of several aspects related to serial order WM. RESULTS: The results revealed an impaired ability to bind item information to serial position within WM in AD patients compared to controls. It was additionally observed that AD patients experienced specific difficulties with directing spatial attention when searching for item information stored in WM. CONCLUSION: The processing of serial order and the allocation of attentional resources are both disrupted, explaining the generally reduced WM functioning in AD patients. Further studies should now clarify whether this observation could explain disease-related problems for other cognitive functions such as verbal expression, auditory comprehension, or planning.

Improved Brain Insulin/IGF Signaling and Reduced Neuroinflammation with T3D-959 in an Experimental Model of Sporadic Alzheimer's Disease. - de la Monte, Suzanne M; Tong, Ming; Schiano, Irio; Didsbury, John (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with progressive impairments in brain insulin, insulin-like growth factor (IGF), and insulin receptor substrate (IRS) signaling through Akt pathways that regulate neuronal growth, survival, metabolism, and plasticity. The intracerebral streptozotocin (i.c. STZ) model replicates the full range of abnormalities in sporadic AD. T3D-959, an orally active PPAR-delta/gamma agonist remediates neurocognitive deficits and AD neuropathology in the i.c. STZ model. OBJECTIVE: This study characterizes the effects of T3D-959 on AD biomarkers, insulin/IGF/IRS signaling through Akt pathways, and neuroinflammation in an i.c. STZ model. METHODS: Long Evans rats were treated with i.c. STZ or saline, followed by daily oral doses of T3D-959 (1 mg/kg) or saline initiated 1 day (T3D-959-E) or 7 days (T3D-959-L) later through Experimental Day 28. Protein and phospho-protein expression and pro-inflammatory cytokine activation were measured in temporal lobe homogenates by duplex or multiplex bead-based ELISAs. RESULTS: i.c. STZ treatments caused neurodegeneration with increased pTau, AβPP, Aβ42, ubiquitin, and SNAP-25, and reduced levels of synaptophysin, IGF-1 receptor (R), IRS-1, Akt, p70S6K, mTOR, and S9-GSK-3β. i.c. STZ also broadly increased neuroinflammation. T3D-959 abrogated or reduced most of the AD neuropathological and biomarker abnormalities, increased/normalized IGF-1R, IRS-1, Akt, p70S6K, and S9-GSK-3β, and decreased expression of multiple pro-inflammatory cytokines. T3D-959-E or -L effectively restored insulin/IGF signaling, whereas T3D-959-L more broadly resolved neuroinflammation. CONCLUSION: AD remediating effects of T3D-959 are potentially due to enhanced expression of key insulin/IGF signaling proteins and inhibition of GSK-3β and neuroinflammation. These effects lead to reduced neurodegeneration, cognitive impairment, and AD biomarker levels in the brain.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

In Vivo Detection of Gray Matter Neuropathology in the 3xTg Mouse Model of Alzheimer's Disease with Diffusion Tensor Imaging. - Snow, Wanda M; Dale, Ryan; O'Brien-Moran, Zoe; Buist, Richard; Peirson, Danial; Martin, Melanie; Albensi, Benedict C (J Alzheimers Dis, 2017)
A diagnosis of Alzheimer's disease (AD), a neurodegenerative disorder accompanied by severe functional and cognitive decline, is based on clinical findings, with final confirmation of the disease at autopsy by the presence of amyloid-β (Aβ) plaques and neurofibrillary tangles. Given that microstructural brain alterations occur years prior to clinical symptoms, efforts to detect brain changes early could significantly enhance our ability to diagnose AD sooner. Diffusion tensor imaging (DTI), a type of MRI that characterizes the magnitude, orientation, and anisotropy of the diffusion of water in tissues, has been used to infer neuropathological changes in vivo. Its utility in AD, however, is still under investigation. The current study used DTI to examine brain regions susceptible to AD-related pathology; the cerebral cortex, entorhinal cortex, and hippocampus, in 12-14-month-old 3xTg AD mice that possess both Aβ plaques and neurofibrillary tangles. Mean diffusivity did not differ between 3xTg and control mice in any region. Decreased fractional anisotropy (p < 0.01) and axial diffusivity (p < 0.05) were detected only in the hippocampus, in which both congophilic Aβ plaques and hyperphosphorylated tau accumulation, consistent with neurofibrillary tangle formation, were detected. Pathological tau accumulation was seen in the cortex. The entorhinal cortex was largely spared from AD-related neuropathology. This is the first study to demonstrate DTI abnormalities in gray matter in a mouse model of AD in which both pathological hallmarks are present, suggesting the feasibility of DTI as a non-invasive means of detecting brain pathology in vivo in early-stage AD.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Incident Cerebral Microbleeds Detected by Susceptibility Weight-Imaging Help to Identify Patients with Mild Cognitive Impairment Progressing to Alzheimer's Disease. - Basselerie, Hubert; Bracoud, Luc; Zeestraten, Eva; Bouguen, Eva; Kiyasova, Vera; Pueyo, Maria; Cognard, Christophe; Dumas, Hervé; Gramada, Raluca; Ousset, Pierre Jean; Vellas, Bruno; Bonneville, Fabrice (J Alzheimers Dis, 2017)
BACKGROUND: The relationship between cerebral microbleeds (CMB) and Alzheimer's disease (AD) has not yet been clearly determined, particularly with susceptibility weight-imaging (SWI). OBJECTIVE: To evaluate the SWI sequence using 3T MRI for the detection of CMB, and its ability to differentiate elderly control subjects (CS), stable mild cognitive impairment patients (MCI-s), MCI patients progressing to AD (MCI-p), and AD patients. METHODS: It was a prospective, monocentric, observational study that took place in Toulouse, France. Participants were 65 years and older, enrolled in three groups: CS, MCI, and AD. Based on the longitudinal analysis of cognitive decline, MCI subjects were retrospectively classified as MCI-s or MCI-p. Each patient had a 4-year follow-up with MRI at baseline (MRI#1) and during the fourth year (MRI#3). CMB were counted on native SWI images juxtaposed to minIP reformatted images. RESULTS: 150 patients were enrolled: 48 CS, 25 MCI-s, 18 MCI-p, 59 AD. At MRI#1 and at MRI#3, there was no significant difference in the prevalence of CMB between groups (p = 0.75 and p = 0.87). In the MCI-p + AD group, significantly more subjects had≥4 incident CMB compared to the CS + MCI-s group (p = 0.016). In the MCI-p + AD group, the prevalence of patients with >4 CMB was significantly higher at MRI#3 than at MRI#1 (p = 0.008). CONCLUSION: Using SWI, AD and MCI-p patients had developed significantly more new CMB than CS and MCI-s patients during the follow-up. Incident CMB might be suggested as a potential imaging marker of AD progression.

Information and Communication Technologies for the Activities of Daily Living in Older Patients with Dementia: A Systematic Review. - D'Onofrio, Grazia; Sancarlo, Daniele; Ricciardi, Francesco; Panza, Francesco; Seripa, Davide; Cavallo, Filippo; Giuliani, Francesco; Greco, Antonio (J Alzheimers Dis, 2017)
BACKGROUND: Significant innovations have been introduced in recent years in the application of information and communication technologies (ICTs) to support healthcare for patients with dementia. OBJECTIVE: In the present systematic review, our goal is to keep track of ICT concepts and approaches to support the range of activities of daily living for people with dementia and to provide a snapshot of the effect that technology is having on patients' self-reliance. METHODS: We reviewed the literature and identified systematic reviews of cohort studies and other authoritative reports. Our selection criteria included: (1) activities of daily living, (2) ICT, and (3) dementia. RESULTS: We identified 56 studies published between 2000 and 2015, of which 26 met inclusion criteria. The present systematic review revealed many ICT systems that could purportedly support the range of activities of daily living for patients with dementia. The results showed five research bodies: 1) technologies used by patients with dementia, 2) technologies used by caregivers, 3) monitoring systems, 4) ambient assistive living with ICTs, and 5) tracking and wayfinding. CONCLUSIONS: There is a potential for ICTs to support dementia care at home and to improve quality of life for caregivers, reducing healthcare costs and premature institutional care for these patients.
Keywords: Activities of Daily Living; Aging; Databases, Bibliographic; Dementia; Humans; Medical Informatics; Self-Help Devices

Intensive 'Brain Training' Intervention Fails to Reduce Amyloid Pathologies or Cognitive Deficits in Transgenic Mouse Models of Alzheimer's Disease. - Anderson, Maria; Xu, Feng; Ou-Yang, Ming-Hsuan; Davis, Judianne; Van Nostrand, William E; Robinson, John K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is the leading cause of dementia in the elderly. Amyloid-β protein (Aβ) depositions in both the brain parenchyma and the cerebral vasculature are recognized as important pathological components that contribute to the cognitive impairments found in individuals with AD. Because pharmacological options have been minimally effective in treating cognitive impairment to date, interest in the development of preventative lifestyle intervention strategies has increased in the field. One controversial strategy, cognitive-specific stimulation, has been studied previously in human participants and has been widely commercialized in the form of 'brain-training games.' In the present study, we developed a highly controlled, isolated cognitive training intervention program for mice. Two transgenic mouse lines, one that develops Aβ deposition largely in brain parenchyma, and another in the cerebral microvasculature, progressed through a series of domain-specific tasks for an average of 4 months. Despite the high intensity and duration of the intervention, we found little evidence of positive benefits for AD amyloid pathologies and post-training cognitive testing in these two models. Taken together, these results support the current evidence in human studies that cognitive-specific stimulation does not lead to a measurable reduction in AD pathology or an improvement in general brain health.

Intrahippocampal Pathways Involved in Learning/Memory Mechanisms are Affected by Intracerebral Infusions of Amyloid-β25-35 Peptide and Hydrated Fullerene C60 in Rats. - Gordon, Rita; Podolski, Igor; Makarova, Ekaterina; Deev, Alexander; Mugantseva, Ekaterina; Khutsyan, Sergey; Sengpiel, Frank; Murashev, Arkady; Vorobyov, Vasily (J Alzheimers Dis, 2017)
Primary memory impairments associated with increased level of amyloid-β (Aβ) in the brain have been shown to be linked, partially, with early pathological changes in the entorhinal cortex (EC) which spread on the whole limbic system. While the hippocampus is known to play a key role in learning and memory mechanisms, it is as yet unclear how its structures are involved in the EC pathology. In this study, changes in memory and neuronal morphology in male Wistar rats intrahippocampally injected with Aβ25-35 were correlated on days 14 and 45 after the injection to reveal specific cognitive-structural associations. The main focus was on the dentate gyrus (DG) and hippocampal areas of CA1 and CA3 because of their involvement in afferent flows from EC to the hippocampus through tri-synaptic (EC → DG → CA3 → CA1) and/or mono-synaptic (EC → CA1) pathways. Evident memory impairments were observed at both time points after Aβ25-35 injection. However, on day 14, populations of morphological intact neurons were decreased in CA3 and, drastically, in CA1, and the DG supramedial bundle was significantly damaged. On day 45, this bundle largely and CA1 neurons partially recovered, whereas CA3 neurons remained damaged. We suggest that Aβ25-35 primarily affects the tri-synaptic pathway, destroying the granular cells in the DG supramedial area and neurons in CA3 and, through the Schaffer collaterals, in CA1. Intrahippocampal pretreatment with hydrated fullerene C60 allows the neurons and their connections to survive the amyloidosis, thus supporting the memory mechanisms.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

Late Onset Alzheimer's Disease Risk Variants in Cognitive Decline: The PATH Through Life Study. - Andrews, Shea J; Das, Debjani; Anstey, Kaarin J; Easteal, Simon (J Alzheimers Dis, 2017)
Recent genome wide association studies have identified a number of single nucleotide polymorphisms associated with late onset Alzheimer's disease (LOAD). We examined the associations of 24 LOAD risk loci, individually and collectively as a genetic risk score, with cognitive function. We used data from 1,626 non-demented older Australians of European ancestry who were examined up to four times over 12 years on tests assessing episodic memory, working memory, vocabulary, and information processing speed. Linear mixed models were generated to examine associations between genetic factors and cognitive performance. Twelve SNPs were significantly associated with baseline cognitive performance (ABCA7, MS4A4E, SORL1), linear rate of change (APOE, ABCA7, INPP5D, ZCWPW1, CELF1), or quadratic rate of change (APOE, CLU, EPHA1, HLA-DRB5, INPP5D, FERMT2). In addition, a weighted genetic risk score was associated with linear rate of change in episodic memory and information processing speed. Our results suggest that a minority of AD related SNPs may be associated with non-clinical cognitive decline. Further research is required to verify these results and to examine the effect of preclinical AD in genetic association studies of cognitive decline. The identification of LOAD risk loci associated with non-clinical cognitive performance may help in screening for individuals at greater risk of cognitive decline.

Left Frontal Hub Connectivity during Memory Performance Supports Reserve in Aging and Mild Cognitive Impairment. - Franzmeier, Nicolai; Hartmann, Julia C; Taylor, Alexander N W; Araque Caballero, Miguel Á; Simon-Vermot, Lee; Buerger, Katharina; Kambeitz-Ilankovic, Lana M; Ertl-Wagner, Birgit; Mueller, Claudia; Catak, Cihan; Janowitz, Daniel; Stahl, Robert; et al. (J Alzheimers Dis, 2017)
Reserve in aging and Alzheimer's disease (AD) is defined as maintaining cognition at a relatively high level in the presence of neurodegeneration, an ability often associated with higher education among other life factors. Recent evidence suggests that higher resting-state functional connectivity within the frontoparietal control network, specifically the left frontal cortex (LFC) hub, contributes to higher reserve. Following up these previous resting-state fMRI findings, we probed memory-task related functional connectivity of the LFC hub as a neural substrate of reserve. In elderly controls (CN, n = 37) and patients with mild cognitive impairment (MCI, n = 17), we assessed global connectivity of the LFC hub during successful face-name association learning, using generalized psychophysiological interaction analyses. Reserve was quantified as residualized memory performance, accounted for gender and proxies of neurodegeneration (age, hippocampus atrophy, and APOE genotype). We found that greater education was associated with higher LFC-connectivity in both CN and MCI during successful memory. Furthermore, higher LFC-connectivity predicted higher residualized memory (i.e., reserve). These results suggest that higher LFC-connectivity contributes to reserve in both healthy and pathological aging.

Left Ventricular Hypertrophy and Cognitive Decline in Old Age. - Mahinrad, Simin; Vriend, Annelotte E; Jukema, J Wouter; van Heemst, Diana; Sattar, Naveed; Blauw, Gerard Jan; Macfarlane, Peter W; Clark, Elaine N; de Craen, Anton J M; Sabayan, Behnam (J Alzheimers Dis, 2017)
BACKGROUND: Patients with advanced heart failure run a greater risk of dementia. Whether early cardiac structural changes also associate with cognitive decline is yet to be determined. OBJECTIVE: We tested whether left ventricular hypertrophy (LVH) derived from electrocardiogram associates with cognitive decline in older subjects at risk of cardiovascular disease. METHODS: We included 4,233 participants (mean age 75.2 years, 47.8% male) from PROSPER (PROspective Study of Pravastatin in the Elderly at Risk). LVH was assessed from baseline electrocardiograms by measuring the Sokolow-Lyon index. Higher levels of Sokolow-Lyon index indicate higher degrees of LVH. Cognitive domains involving selective attention, processing speed, and immediate and delayed memory were measured at baseline and repeated during a mean follow-up of 3.2 years. RESULTS: At baseline, LVH was not associated with worse cognitive function. During follow-up, participants with higher levels of LVH had a steeper decline in cognitive function including in selective attention (p = 0.009), processing speed (p = 0.010), immediate memory (p < 0.001), and delayed memory (p = 0.002). These associations were independent of cardiovascular risk factors, co-morbidities, and medications. CONCLUSION: LVH assessed by electrocardiogram associates with steeper decline in cognitive function of older subjects independent of cardiovascular risk factors and co-morbidities. This study provides further evidence on the link between subclinical cardiac structural changes and cognitive decline in older subjects.

The level of 24-Hydroxycholesteryl Esters is an Early Marker of Alzheimer's Disease. - Benussi, Luisa; Ghidoni, Roberta; Dal Piaz, Fabrizio; Binetti, Giuliano; Di Iorio, Giuseppe; Abrescia, Paolo (J Alzheimers Dis, 2017)
Cholesterol (C) brain accumulation seems to play a role in the Alzheimer's disease (AD) pathogenesis. 24(S)-hydroxycholesterol (24OH-C) is the predominant metabolite of brain C and its synthesis is believed to represent a way to remove excess C from neurons. Previous studies showed that 24OH-C level is altered in patients with neurodegenerative diseases, including AD. Only one study demonstrated that 24OH-C esterification is altered in neurodegenerative diseases, i.e., amyotrophic lateral sclerosis. Herein we analyzed the level of 24OH-C esters (% 24OH-CE) in i) cerebrospinal fluid (CSF) and homologous serum of AD (n = 13) and controls (n = 8); ii) plasma from AD (n = 30), controls (n = 30), mild cognitive impairment (MCI) converting to AD (n = 34), and stable MCI (n = 40). The % 24OH-CE in CSF positively correlated with that in homologous serum and was lower in both CSF and blood from AD patients as compared to controls; moreover, the plasma value of % 24OH-CE was lower in MCI conv-AD than in non-converters. Kaplan Meier Survival curves revealed a significant anticipation of the disease onset in AD and MCI conv-AD subjects with the lowest % 24OH-CE values. In conclusion, the reduction of % 24OH-CE in AD and MCI conv-AD, as well as the anticipation of the disease in patients with the lowest % 24OH-CE, support a role of the cholesterol/lecithin-cholesterol acyltransferase axis in AD onset/progression. Thus, targeting brain cholesterol metabolism could be a valuable strategy to prevent AD associated cognitive decline.

A Lipidomics Approach to Assess the Association Between Plasma Sphingolipids and Verbal Memory Performance in Coronary Artery Disease Patients Undertaking Cardiac Rehabilitation: A C18:0 Signature for Cognitive Response to Exercise. - Saleem, Mahwesh; Herrmann, Nathan; Dinoff, Adam; Mielke, Michelle M; Oh, Paul I; Shammi, Prathiba; Cao, Xingshan; Venkata, Swarajya Lakshmi Vattem; Haughey, Norman J; Lanctôt, Krista L (J Alzheimers Dis, 2017)
BACKGROUND: Early subtle deficits in verbal memory, which may indicate early neural risk, are common in patients with coronary artery disease (CAD). While exercise can improve cognition, cognitive response to exercise is heterogeneous. Sphingolipids have been associated with the development and progression of CAD, and impairments in sphingolipid metabolism may play roles in neurodegeneration and in the neural adaptation response to exercise. OBJECTIVE: In this study, change in plasma concentrations of sphingolipids was assessed in relation to change in verbal memory performance and in other cognitive domains among CAD subjects undertaking a 6-month cardiac rehabilitation (CR) program. METHODS: Patients with CAD (n = 120, mean age = 64±6 y, 84% male, years of education = 16±3) underwent CR with neuropsychological assessments and blood collected at baseline, 3-, and 6-months. Z-scores based on age, gender, and education were combined for verbal memory, visuospatial memory, processing speed, executive function, and global cognition tasks to calculate cognitive domain Z-scores. Plasma sphingolipid concentrations were measured from fasting blood samples using high performance liquid chromatography coupled electrospray ionization tandem mass spectrometry (LC/MS/MS). Mixed models were used to identify sphingolipids significantly associated with performance in verbal memory and other cognitive domains, adjusting for potential confounders. RESULTS: A decrease in ceramide C18:0 concentration was significantly associated with improvement in verbal memory performance (b[SE] = -0.51 [0.25], p = 0.04), visuospatial memory (b[SE] = -0.44 [0.22], p = 0.05), processing speed (b[SE] = -0.89 [0.32], p = 0.007), and global cognition (b[SE] = -1.47 [0.59], p = 0.01) over 6 months of CR. CONCLUSIONS: Plasma ceramide C18:0 concentrations may be a sensitive marker of cognitive response to exercise in patients with CAD.

Localization and Processing of the Amyloid-β Protein Precursor in Mitochondria-Associated Membranes. - Del Prete, Dolores; Suski, Jan M; Oulès, Bénédicte; Debayle, Delphine; Gay, Anne Sophie; Lacas-Gervais, Sandra; Bussiere, Renaud; Bauer, Charlotte; Pinton, Paolo; Paterlini-Bréchot, Patrizia; Wieckowski, Mariusz R; Checler, Frédéric; et al. (J Alzheimers Dis, 2017)
Alteration of mitochondria-associated membranes (MAMs) has been proposed to contribute to the pathogenesis of Alzheimer's disease (AD). We studied herein the subcellular distribution, the processing, and the protein interactome of the amyloid-β protein precursor (AβPP) and its proteolytic products in MAMs. We reveal that AβPP and its catabolites are present in MAMs in cellular models overexpressing wild type AβPP or AβPP harboring the double Swedish or London familial AD mutations, and in brains of transgenic mice model of AD. Furthermore, we evidenced that both β- and γ-secretases are present and harbor AβPP processing activities in MAMs. Interestingly, cells overexpressing APPswe show increased ER-mitochondria contact sites. We also document increased neutral lipid accumulation linked to Aβ production and reversed by inhibiting β- or γ-secretases. Using a proteomic approach, we show that AβPP and its catabolites interact with key proteins of MAMs controlling mitochondria and ER functions. These data highlight the role of AβPP processing and proteomic interactome in MAMs deregulation taking place in AD.

A Longitudinal Study on Resting State Functional Connectivity in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease. - Hafkemeijer, Anne; Möller, Christiane; Dopper, Elise G P; Jiskoot, Lize C; van den Berg-Huysmans, Annette A; van Swieten, John C; van der Flier, Wiesje M; Vrenken, Hugo; Pijnenburg, Yolande A L; Barkhof, Frederik; Scheltens, Philip; van der Grond, Jeroen; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. We applied longitudinal resting state functional magnetic resonance imaging (fMRI) to delineate functional brain connections relevant for disease progression and diagnostic accuracy. METHODS: We used two-center resting state fMRI data of 20 AD patients (65.1±8.0 years), 12 bvFTD patients (64.7±5.4 years), and 22 control subjects (63.8±5.0 years) at baseline and 1.8-year follow-up. We used whole-network and voxel-based network-to-region analyses to study group differences in functional connectivity at baseline and follow-up, and longitudinal changes in connectivity within and between groups. RESULTS: At baseline, connectivity between paracingulate gyrus and executive control network, between cuneal cortex and medial visual network, and between paracingulate gyrus and salience network was higher in AD compared with controls. These differences were also present after 1.8 years. At follow-up, connectivity between angular gyrus and right frontoparietal network, and between paracingulate gyrus and default mode network was lower in bvFTD compared with controls, and lower compared with AD between anterior cingulate gyrus and executive control network, and between lateral occipital cortex and medial visual network. Over time, connectivity decreased in AD between precuneus and right frontoparietal network and in bvFTD between inferior frontal gyrus and left frontoparietal network. Longitudinal changes in connectivity between supramarginal gyrus and right frontoparietal network differ between both patient groups and controls. CONCLUSION: We found disease-specific brain regions with longitudinal connectivity changes. This suggests the potential of longitudinal resting state fMRI to delineate regions relevant for disease progression and for diagnostic accuracy, although no group differences in longitudinal changes in the direct comparison of AD and bvFTD were found.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Low Cognitive Awareness, but Not Complaint, is a Good Marker of Preclinical Alzheimer's Disease. - Cacciamani, Federica; Tandetnik, Caroline; Gagliardi, Geoffroy; Bertin, Hugo; Habert, Marie-Odile; Hampel, Harald; Boukadida, Laurie; Révillon, Marie; Epelbaum, Stéphane; Dubois, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may result from many conditions, including Alzheimer's disease (AD). OBJECTIVE: In this study, we searched for a specific pattern of SCD in asymptomatic individuals at risk for AD. METHODS: Cognitively normal older adults (N = 318) reporting SCD and their informants were enrolled in the INSIGHT-PreAD cohort. We examined the relationship between six SCD measures and both cognitive scores and AD neuroimaging markers (amyloid burden, hippocampal atrophy and brain hypometabolism). An awareness of cognitive decline index (ACDI) has been introduced based on the subject-informant discrepancy in a questionnaire of SCD and participants with low versus high awareness were compared. RESULTS: Scores in the INSIGHT-PreAD SCD questionnaires did not correlate with AD neuroimaging markers. As well, no correlation has been found between SCD measures and cognitive scores. Comparing subjects with a low (n = 19) and high (n = 86) level of awareness, no significant difference in terms of demography, neuropsychiatric symptoms, autonomy, quality of life, cognition, and hippocampal volume was found. However, the "low awareness" group showed greater amyloid burden and lower cortical metabolism, compared to the "high awareness" group. CONCLUSION: This study provided additional evidence that reporting SCD by itself is not a specific symptom of preclinical AD. Conversely, a low cognitive awareness (namely, when subjects report fewer difficulties than their relatives do) may represent a very early form of anosognosia and serve as a specific indicator of preclinical AD. This finding is of key importance as an enrichment factor to consider in both clinical practice and research trials.

Low Erythrocyte Levels of Proteasome and Acyl-Peptide Hydrolase (APEH) Activities in Alzheimer's Disease: A Sign of Defective Proteostasis? - Palmieri, Gianna; Cocca, Ennio; Gogliettino, Marta; Valentino, Roberta; Ruvo, Menotti; Cristofano, Gloria; Angiolillo, Antonella; Balestrieri, Marco; Rossi, Mosè; Di Costanzo, Alfonso (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive, multifactorial neurodegenerative disorder that is the main cause of dementia. To date, there are no definitive diagnostic tests that can predict or assess onset and progression of the disease. Blood biomarkers for AD are being sought for many years but their identification remains a challenging task. In this study, we investigated the potential relationship between AD and levels of acyl-peptide hydrolase (APEH) and proteasome in erythrocyte samples of 52 participants (26 AD and 26 cognitively healthy controls). A statistically significant decrease in proteasome and exopeptidase/endopeptidase APEH activities was found in AD samples compared to those of healthy controls. Moreover, in contrast to what was observed for proteasome transcripts, APEH activities reduction in AD patients was unrelated to its gene expression levels, suggesting the occurrence of posttranslational modifications or the expression of endogenous inhibitors that might impair enzyme activity. These preliminary data further support a relationship between the APEH-proteasome system and AD molecular players, providing the first evidence of its potential use as a novel blood-based indicator for the routine detection of AD.

Low Prevalence and Clinical Effect of Vascular Risk Factors in Early-Onset Alzheimer's Disease. - Chen, Yaohua; Sillaire, Adeline Rollin; Dallongeville, Jean; Skrobala, Emilie; Wallon, David; Dubois, Bruno; Hannequin, Didier; Pasquier, Florence (J Alzheimers Dis, 2017)
BACKGROUND: Determinants of early-onset Alzheimer's disease (EOAD) are not well known. In late-onset AD, vascular risk factors (VRFs) are associated with earlier clinical manifestation. OBJECTIVE: The objective of this study was to assess the putative association between VRFs and EOAD. METHODS: We studied participants with dementia meeting criteria for EOAD (recruited into the French CoMAJ prospective cohort study from 1 June 2009 to 28 February 2014) and age-, gender-matched controls (ratio 1:3, drawn randomly from the French MONA-LISA population-based survey between 2005 and 2007). Demographic data, VRFs, comorbidities, treatments, and APOE genotypes were compared in multivariable logistic regression analyses. RESULTS: We studied 102 participants with dementia (mean±standard deviation age: 59.5±3.8; women: 59.8%) and 306 controls. Compared with controls, EOAD participants had spent less time in formal education (9.9±2.9 versus 11.7±3.8 y; p < 0.0001), were less likely to be regular alcohol consumers (p < 0.0001), had a lower body mass index (-2 kg/m2; p < 0.0004), and a lower mean systolic blood pressure (-6.2 mmHg; p = 0.0036). The prevalence of APOE ɛ4 allele was higher in participants with dementia than in controls (50% versus 29.4%; p = 0.0002), as was the prevalence of depression (48% versus 32%; p < 0.001). Similar results were observed in multivariable analysis. Compared with EOAD participants lacking VRFs, EOAD participants with at least one VRF had a higher prevalence of depression (29.6% versus 53.3%, respectively; p = 0.03). CONCLUSION: The prevalence of VRFs is not elevated in EOAD patients (in contrast to older AD patients). Extensive genetic testing should be considered more frequently in the context of EOAD.

Magnetic Resonance Imaging and Anatomical Correlation of Human Temporal Lobe Landmarks, in 3D Euclidean Space: A Study of Control and Alzheimer's Disease Subjects. - Delgado-González, José-Carlos; Florensa-Vila, José; Mansilla-Legorburo, Francisco; Insausti, Ricardo; Artacho-Pérula, Emilio (J Alzheimers Dis, 2017)
BACKGROUND: The medial temporal lobe (MTL), and in particular the hippocampal formation, is essential in the processing and consolidation of declarative memory. The 3D environment of the anatomical structures contained in the MTL is an important issue. OBJECTIVE: Our aim was to explore the spatial relationship of the anatomical structures of the MTL and changes in aging and/or Alzheimer's disease (AD). METHODS: MTL anatomical landmarks are identified and registered to create a 3D network. The brain network is quantitatively described as a plane, rostrocaudally-oriented, and presenting Euclidean/real distances. Correspondence between 1.5T RM, 3T RM, and histological sections were assessed to determine the most important recognizable changes in AD, based on statistical significance. RESULTS: In both 1.5T and 3T RM images and histology, inter-rater reliability was high. Sex and hemisphere had no influence on network pattern. Minor changes were found in relation to aging. Distances from the temporal pole to the dentate gyrus showed the most significant differences when comparing control and AD groups. The best discriminative distance between control and AD cases was found in the temporal pole/dentate gyrus rostrocaudal length in histological sections. Moreover, more distances between landmarks were required to obtain 100% discrimination between control (divided into <65 years or >65 years) and AD cases. DISCUSSION: Changes in the distance between MTL anatomical landmarks can successfully be detected by using measurements of 3D network patterns in control and AD cases.

Memory Complaints and Cognitive Decline: Data from the GUIDAGE Study1. - Dardenne, Sophie; Delrieu, Julien; Sourdet, Sandrine; Cantet, Christelle; Andrieu, Sandrine; Mathiex-Fortunet, Hélène; Fougère, Bertrand; Vellas, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may be a very early symptom of Alzheimer's disease (AD) and may be associated with a cognitive decline in a cognitively normal population. The McNair and Kahn Scale was used to assess memory complaints in the GuidAge study. OBJECTIVE: Our objectives were to examine if the McNair and Kahn Scale can predict cognitive decline and to screen which (if any) of the question(s) of this scale would better predict this cognitive decline. METHODS: The GuidAge study was a phase III, multicenter, randomized, double blind, placebo-controlled study. Individuals aged 70 years and older, without cognitive impairment (Clinical Dementia Rate (CDR = 0)) at baseline who had spontaneously reported SCD were included in this study. The 20-item version of the McNair and Kahn Scale was used to assess SCD and a standardized neuropsychological assessment was used to assess the cognitive status. RESULTS: 1,307 patients with SCD and with CDR = 0 at baseline were included. During the 5 years of follow-up, 519 patients showed cognitive decline. Incidence of aggravation score of CDR was 13.40% person years (95% CI [12.24-14.56]). Results showed a significant relationship between the McNair and Kahn Scale score and decline in cognitive performance (HR 1.012; 95% CI [1.002-1.021]; p = 0.0156). Among the 20 items, 5 were statistically significant to predict cognitive decline after adjustment. CONCLUSION: SCD is a promising indicator of memory impairment. Our study found that using the McNair and Kahn scale can predict cognitive decline. A 5-item version of this scale could be used to screen patients in clinical practice and in clinical research.

Memory is Not Enough: The Neurobiological Substrates of Dynamic Cognitive Reserve. - Serra, Laura; Bruschini, Michela; Di Domenico, Carlotta; Gabrielli, Giulia Bechi; Marra, Camillo; Caltagirone, Carlo; Cercignani, Mara; Bozzali, Marco (J Alzheimers Dis, 2017)
Changes in the residual memory variance are considered as a dynamic aspect of cognitive reserve (d-CR). We aimed to investigate for the first time the neural substrate associated with changes in the residual memory variance overtime in patients with amnestic mild cognitive impairment (aMCI). Thirty-four aMCI patients followed-up for 36 months and 48 healthy elderly individuals (HE) were recruited. All participants underwent 3T MRI, collecting T1-weighted images for voxel-based morphometry (VBM). They underwent an extensive neuropsychological battery, including six episodic memory tests. In patients and controls, factor analyses were used on the episodic memory scores to obtain a composite memory score (C-MS). Partial Least Square analyses were used to decompose the variance of C-MS in latent variables (LT scores), accounting for demographic variables and for the general cognitive efficiency level; linear regressions were applied on LT scores, striping off any contribution of general cognitive abilities, to obtain the residual value of memory variance, considered as an index of d-CR. LT scores and d-CR were used in discriminant analysis, in patients only. Finally, LT scores and d-CR were used as variable of interest in VBM analysis. The d-CR score was not able to correctly classify patients. In both aMCI patients and HE, LT1st and d-CR scores showed correlations with grey matter volumes in common and in specific brain areas. Using CR measures limited to assess memory function is likely less sensitive to detect the cognitive decline and predict the evolution of Alzheimer's disease. In conclusion, d-CR needs a measure of general cognition to identify conversion to Alzheimer's disease efficiently.

Meta-Analysis of Parkinson's Disease and Alzheimer's Disease Revealed Commonly Impaired Pathways and Dysregulation of NRF2-Dependent Genes. - Wang, Qian; Li, Wen-Xing; Dai, Shao-Xing; Guo, Yi-Cheng; Han, Fei-Fei; Zheng, Jun-Juan; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2017)
Many lines of evidence suggest that Parkinson's disease (PD) and Alzheimer's disease (AD) have common characteristics, such as mitochondrial dysfunction and oxidative stress. As the underlying molecular mechanisms are unclear, we perform a meta-analysis with 9 microarray datasets of PD studies and 7 of AD studies to explore it. Functional enrichment analysis revealed that PD and AD both showed dysfunction in the synaptic vesicle cycle, GABAergic synapses, phagosomes, oxidative phosphorylation, and TCA cycle pathways, and AD had more enriched genes. Comparing the differentially expressed genes between AD and PD, we identified 54 common genes shared by more than six tissues. Among them, 31 downregulated genes contained the antioxidant response element (ARE) consensus sequence bound by NRF2. NRF2 is a transcription factor, which protects cells against oxidative stress through coordinated upregulation of ARE-driven genes. To our surprise, although NRF2 was upregulated, its target genes were all downregulated. Further exploration found that MAFF was upregulated in all tissues and significantly negatively correlated with the 31 NRF2-dependent genes in diseased conditions. Previous studies have demonstrated over-expressed small MAFs can form homodimers and act as transcriptional repressors. Therefore, MAFF might play an important role in dysfunction of NRF2 regulatory network in PD and AD.

Metabolic and Growth Rate Alterations in Lymphoblastic Cell Lines Discriminate Between Down Syndrome and Alzheimer's Disease. - Coskun, Pinar; Helguera, Pablo; Nemati, Zahra; Bohannan, Ryan C; Thomas, Jean; Samuel, Schriner E; Argueta, Jocelyn; Doran, Eric; Wallace, Douglas C; Lott, Ira T; Busciglio, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Deficits in mitochondrial function and oxidative stress play pivotal roles in Down syndrome (DS) and Alzheimer's disease (AD) and these alterations in mitochondria occur systemically in both conditions. OBJECTIVE: We hypothesized that peripheral cells of elder subjects with DS exhibit disease-specific and dementia-specific metabolic features. To test this, we performed a comprehensive analysis of energy metabolism in lymphoblastic-cell-lines (LCLs) derived from subjects belonging to four groups: DS-with-dementia (DSAD), DS-without-dementia (DS), sporadic AD, and age-matched controls. METHODS: LCLs were studied under regular or minimal feeding regimes with galactose or glucose as primary carbohydrate sources. We assessed metabolism under glycolysis or oxidative phosphorylation by quantifying cell viability, oxidative stress, ATP levels, mitochondrial membrane potential (MMP), mitochondrial calcium uptake, and autophagy. RESULTS: DS and DSAD LCLs showed slower growth rates under minimal feeding. DS LCLs mainly dependent on mitochondrial respiration exhibited significantly slower growth and higher levels of oxidative stress compared to other groups. While ATP levels (under mitochondrial inhibitors) and mitochondrial calcium uptake were significantly reduced in DSAD and AD cells, MMP was decreased in DS, DSAD, and AD LCLs. Finally, DS LCLs showed markedly reduced levels of the autophagy marker LC3-II, underscoring the close association between metabolic dysfunction and impaired autophagy in DS. CONCLUSION: There are significant mitochondrial functional changes in LCLs derived from DS, DSAD, and AD patients. Several parameters analyzed were consistently different between DS, DSAD, and AD lines suggesting that metabolic indicators between LCL groups may be utilized as biomarkers of disease progression and/or treatment outcomes.

Methionine Sulfoxide Reductase-B3 (MsrB3) Protein Associates with Synaptic Vesicles and its Expression Changes in the Hippocampi of Alzheimer's Disease Patients. - Adams, Stephanie L; Benayoun, Laurent; Tilton, Kathy; Chavez, Olivia R; Himali, Jayandra J; Blusztajn, Jan Krzysztof; Seshadri, Sudha; Delalle, Ivana (J Alzheimers Dis, 2017)
Genome-wide association studies (GWAS) identified susceptibility loci associated with decreased hippocampal volume, and found hippocampal subfield-specific effects at MSRB3 (methionine sulfoxide reductase-B3). The MSRB3 locus was also linked to increased risk for late onset Alzheimer's disease (AD). In this study, we uncovered novel sites of MsrB3 expression in CA pyramidal layer and arteriolar walls by using automated immunohistochemistry on hippocampal sections from 23 individuals accompanied by neuropathology reports and clinical dementia rating scores. Controls, cognitively intact subjects with no hippocampal neurofibrillary tangles, exhibited MsrB3 signal as distinct but rare puncta in CA1 pyramidal neuronal somata. In CA3, however, MsrB3-immunoreactivity was strongest in the neuropil of the pyramidal layer. These patterns were replicated in rodent hippocampi where ultrastructural and immunohistofluorescence analysis revealed MsrB3 signal associated with synaptic vesicles and colocalized with mossy fiber terminals. In AD subjects, the number of CA1 pyramidal neurons with frequent, rather than rare, MsrB3-immunoreactive somatic puncta increased in comparison to controls. This change in CA1 phenotype correlated with the occurrence of AD pathological hallmarks. Moreover, the intensity of MsrB3 signal in the neuropil of CA3 pyramidal layer correlated with the signal pattern in neurons of CA1 pyramidal layer that was characteristic of cognitively intact individuals. Finally, MsrB3 signal in the arteriolar walls in the hippocampal white matter decreased in AD patients. This characterization of GWAS-implicated MSRB3 protein expression in human hippocampus suggests that patterns of neuronal and vascular MsrB3 protein expression reflect or underlie pathology associated with AD.

Midlife Metabolic Profile and the Risk of Late-Life Cognitive Decline. - Tortelli, Rosanna; Lozupone, Madia; Guerra, Vito; Barulli, Maria Rosaria; Imbimbo, Bruno P; Capozzo, Rosa; Grasso, Alessandra; Tursi, Marianna; Di Dio, Cristina; Sardone, Rodolfo; Giannelli, Gianluigi; Seripa, Davide; et al. (J Alzheimers Dis, 2017)
Among metabolic syndrome components, the effects of higher plasma glucose levels on cognitive decline (CD) have been considered in few studies. We evaluated the associations among midlife glycemia, total cholesterol, high-density lipoprotein cholesterol, triglycerides, midlife insulin resistance [homeostasis model assessment for insulin resistance (HOMA-index)], and CD in the older subjects of the population-based MICOL Study (Castellana Grotte, Italy) at baseline (M1) and at follow-ups seven (M2) and twenty years later (M3). At M1, a dementia risk score and a composite cardiovascular risk score for dementia were calculated. For 797 subjects out of 833, we obtained a Mini-Mental State Examination (MMSE) score at M3, subdividing these subjects in three cognitive functioning subgroups: normal cognition, mild CD, and moderate-severe CD. Mean fasting glycemia at baseline was significantly higher in moderate-severe CD subgroup (114.6±71.4 mg/dl) than in the normal cognition subgroup (101.2±20.6). Adjusting for gender, age, and other metabolic components, higher fasting glycemia values both at M1 [odds ratio (OR) = 1.31; 95% confidence interval (CI): 1.08-1.59] and M2 (OR = 1.26; 95% CI: 1.01-1.57) were associated with an increased risk of moderate-severe CD. Mean HOMA index value was significantly higher in the moderate-severe CD subgroup (5.7±9.4) compared to the normal cognition subgroup (2.9±1.4) at M1. The dementia risk probability (MMSE < 24) increased moving through higher categories of the dementia risk score and decreased as long as the cardiovascular score increased. The present findings highlighted the indication to control blood glucose levels, regardless of a diagnosis of diabetes mellitus, as early as midlife for prevention of late-life dementia.

Mitochondrial Dysfunction and Synaptic Transmission Failure in Alzheimer's Disease. - Guo, Lan; Tian, Jing; Du, Heng (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder, in which multiple risk factors converge. Despite the complexity of the etiology of the disease, synaptic failure is the pathological basis of cognitive impairment, the cardinal sign of AD. Decreased synaptic density, compromised synaptic transmission, and defected synaptic plasticity are hallmark synaptic pathologies accompanying AD. However, the mechanisms by which synapses are injured in AD-related conditions have not been fully elucidated. Mitochondria are a critical organelle in neurons. The pivotal role of mitochondria in supporting synaptic function and the concomitant occurrence of mitochondrial dysfunction with synaptic stress in postmortem AD brains as well as AD animal models seem to lend the credibility to the hypothesis that mitochondrial defects underlie synaptic failure in AD. This concept is further strengthened by the protective effect of mitochondrial medicine on synaptic function against the toxicity of amyloid-β, a key player in the pathogenesis of AD. In this review, we focus on the association between mitochondrial dysfunction and synaptic transmission deficits in AD. Impaired mitochondrial energy production, deregulated mitochondrial calcium handling, excess mitochondrial reactive oxygen species generation and release play a crucial role in mediating synaptic transmission deregulation in AD. The understanding of the role of mitochondrial dysfunction in synaptic stress may lead to novel therapeutic strategies for the treatment of AD through the protection of synaptic transmission by targeting to mitochondrial deficits.

Mitochondrial Dysfunction Triggers Synaptic Deficits via Activation of p38 MAP Kinase Signaling in Differentiated Alzheimer's Disease Trans-Mitochondrial Cybrid Cells. - Yu, Qing; Du, Fang; Douglas, Justin T; Yu, Haiyang; Yan, Shirley ShiDu; Yan, Shi Fang (J Alzheimers Dis, 2017)
Loss of synapse and synaptic dysfunction contribute importantly to cognitive impairment in Alzheimer's disease (AD). Mitochondrial dysfunction and oxidative stress are early pathological features in AD-affected brain. However, the effect of AD mitochondria on synaptogenesis remains to be determined. Using human trans-mitochondrial "cybrid" (cytoplasmic hybrid) neuronal cells whose mitochondria were transferred from platelets of patients with sporadic AD or age-matched non-AD subjects with relatively normal cognition, we provide the first evidence of mitochondrial dysfunction compromises synaptic development and formation of synapse in AD cybrid cells in response to chemical-induced neuronal differentiation. Compared to non-AD control cybrids, AD cybrid cells showed synaptic loss which was evidenced by a significant reduction in expression of two synaptic marker proteins: synaptophysin (presynaptic marker) and postsynaptic density protein-95, and neuronal proteins (MAP-2 and NeuN) upon neuronal differentiation. In parallel, AD-mediated synaptic deficits correlate to mitochondrial dysfunction and oxidative stress as well as activation of p38 MAP kinase. Notably, inhibition of p38 MAP kinase by pharmacological specific p38 inhibitor significantly increased synaptic density, improved mitochondrial function, and reduced oxidative stress. These results suggest that activation of p38 MAP kinase signaling pathway contributes to AD-mediated impairment in neurogenesis, possibly by inhibiting the neuronal differentiation. Our results provide new insight into the crosstalk of dysfunctional AD mitochondria to synaptic formation and maturation via activation of p38 MAP kinase. Therefore, blockade of p38 MAP kinase signal transduction could be a potential therapeutic strategy for AD by alleviating loss of synapses.

Modeling the Distress of Spousal Caregivers of People with Dementia. - Wawrziczny, Emilie; Berna, Guillaume; Ducharme, Francine; Kergoat, Marie-Jeanne; Pasquier, Florence; Antoine, Pascal (J Alzheimers Dis, 2017)
BACKGROUND: The progressive mobilization of spouse caregivers who take care of a person with dementia (PWD) can lead to situations of distress. OBJECTIVE: The current study sought to investigate the influence of the characteristics of the caregiving context on spousal caregiver distress. METHODS: 125 spousal caregivers participated in this study. The characteristics of the caregiving context were assessed using questionnaires. We examined a moderated-mediator model (Step 1) in which we hypothesized that PWD and caregiver characteristics and dyadic determinants contribute to spousal caregiver distress. This model was compared based on the age at onset of the disease and the gender of the caregiver (Step 2). RESULTS: The model revealed that poor self-rated health and a lack of family support accentuated spousal caregiver distress, whereas the feeling of being prepared and level of confidence decreased spousal caregiver distress. Moreover, the quality of couple adjustment affected spousal caregiver distress, and this effect was mediated by the severity of the PWD's symptoms. Regarding the age at onset of the disease, the path between Couple Adjustment and the Care recipient's impairments was more important for caregivers of person with early-onset dementia (PEOD). Female caregivers who reported poor self-rated health experienced greater distress. CONCLUSIONS: It would be interesting to create a support program that would incorporate these three areas of intervention regarding the progression of the disease: first, "preparedness modules"; second, "dyadic modules" (especially for caregivers of PEOD); and third, "family modules". Specific attention should be given to female caregivers who report poor self-rated health.

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

Moderate Physical Activity is Associated with Cerebral Glucose Metabolism in Adults at Risk for Alzheimer's Disease. - Dougherty, Ryan J; Schultz, Stephanie A; Kirby, Taylor K; Boots, Elizabeth A; Oh, Jennifer M; Edwards, Dorothy; Gallagher, Catherine L; Carlsson, Cynthia M; Bendlin, Barbara B; Asthana, Sanjay; Sager, Mark A; Hermann, Bruce P; et al. (J Alzheimers Dis, 2017)
The objective of this study was to investigate the relationship between accelerometer-measured physical activity (PA) and glucose metabolism in asymptomatic late-middle-aged adults. Ninety-three cognitively healthy late-middle-aged adults from the Wisconsin Registry for Alzheimer's Prevention participated in this cross-sectional study. They underwent 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging and wore an accelerometer (ActiGraph GT3X+) to measure free-living PA. Accelerometer data yielded measures of light (LPA), moderate (MPA), and vigorous (VPA) intensity PA. FDG-PET images were scaled to the cerebellum and pons, and cerebral glucose metabolic rate was extracted from specific regions of interest (ROIs) known to be hypometabolic in AD, i.e., hippocampus, posterior cingulate, inferior temporal cortex, and angular gyrus. Regression analyses were utilized to examine the association between PA and glucose metabolism, while adjusting for potential confounds. There were associations between MPA and glucose metabolism in all ROIs examined. In contrast, LPA was not associated with glucose uptake in any ROI and VPA was only associated with hippocampal FDG uptake. Secondary analyses did not reveal associations between sedentary time and glucose metabolism in any of the ROIs. Exploratory voxel-wise analysis identified additional regions where MPA was significantly associated with glucose metabolism including the precuneus, supramarginal gyrus, amygdala, and middle frontal gyrus. These findings suggest that the intensity of PA is an important contributor to neuronal function in a late-middle-aged cohort, with MPA being the most salient. Prospective studies are necessary for fully elucidating the link between midlife engagement in PA and later life development of AD.

Modifiable Risk Factors for Prevention of Dementia in Midlife, Late Life and the Oldest-Old: Validation of the LIBRA Index. - Vos, Stephanie J B; van Boxtel, Martin P J; Schiepers, Olga J G; Deckers, Kay; de Vugt, Marjolein; Carrière, Isabelle; Dartigues, Jean-François; Pérès, Karine; Artero, Sylvaine; Ritchie, Karen; Galluzzo, Lucia; Scafato, Emanuele; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recently, the LIfestyle for BRAin health (LIBRA) index was developed to assess an individual's prevention potential for dementia. OBJECTIVE: We investigated the predictive validity of the LIBRA index for incident dementia in midlife, late life, and the oldest-old. METHODS: 9,387 non-demented individuals were recruited from the European population-based DESCRIPA study. An individual's LIBRA index was calculated solely based on modifiable risk factors: depression, diabetes, physical activity, hypertension, obesity, smoking, hypercholesterolemia, coronary heart disease, and mild/moderate alcohol use. Cox regression was used to test the predictive validity of LIBRA for dementia at follow-up (mean 7.2 y, range 1-16). RESULTS: In midlife (55-69 y, n = 3,256) and late life (70-79 y, n = 4,320), the risk for dementia increased with higher LIBRA scores. Individuals in the intermediate- and high-risk groups had a higher risk of dementia than those in the low-risk group. In the oldest-old (80-97 y, n = 1,811), higher LIBRA scores did not increase the risk for dementia. CONCLUSION: LIBRA might be a useful tool to identify individuals for primary prevention interventions of dementia in midlife, and maybe in late life, but not in the oldest-old.

Motoric Cognitive Risk Syndrome: Association with Incident Dementia and Disability. - Doi, Takehiko; Shimada, Hiroyuki; Makizako, Hyuma; Tsutsumimoto, Kota; Verghese, Joe; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: It is important to examine the etiology of motoric cognitive risk syndrome (MCR) and its association with dementia and disability to obtain biological insights and to develop preventive strategies. OBJECTIVE: This study aimed to examine the association of MCR with incidence of dementia and disability in a Japanese community-dwelling sample of older adults. METHODS: Participants were 4,235 older adults (50% women, mean age: 72.0 years). MCR was diagnosed at baseline using established criteria in non-demented seniors with self-reported cognitive complaints and slow gait. Incident cases of dementia were identified from insurance data monthly. Disability was regarded as certification by long-term care insurance. RESULTS: At baseline, 265 participants (6.3%) met criteria for MCR. During follow-up (mean duration: 29 months), there were 138 incident cases of dementia (3.3%) and 207 incident cases of disability (4.9%). Cox-proportional hazards models, adjusted for demographical data, lifestyle, and medical conditions, showed that presence of MCR at baseline was a major risk factor for developing dementia (HR 2.49, 95% CI 1.52-4.10, p < 0.001). MCR also predicted risk for disability (HR 1.69, 95% CI 1.08-2.02, p < 0.001). CONCLUSIONS: MCR is helpful in the short-term prediction of risk for dementia and disability in the elderly Japanese population. Identification of seniors with MCR is recommended for early detection and instituting preventive measures for reducing the risk of dementia and disability.

mTORC2 (Rictor) in Alzheimer's Disease and Reversal of Amyloid-β Expression-Induced Insulin Resistance and Toxicity in Rat Primary Cortical Neurons. - Lee, Han-Kyu; Kwon, Bumsup; Lemere, Cynthia A; de la Monte, Suzanne; Itamura, Kyohei; Ha, Austin Y; Querfurth, Henry W (J Alzheimers Dis, 2017)
Mammalian target of rapamycin complex 1 (mTORC1), a nutrient sensor and central controller of cell growth and proliferation, is altered in various models of Alzheimer's disease (AD). Even less studied or understood in AD is mammalian target of rapamycin complex 2 (mTORC2) that influences cellular metabolism, in part through the regulations of Akt/PKB and SGK. Dysregulation of insulin/PI3K/Akt signaling is another important feature of AD pathogenesis. We found that both total mTORC1 and C2 protein levels and individual C1 and C2 enzymatic activities were decreased in human AD brain samples. In two rodent AD models, mTORC1 and C2 activities were also decreased. In a neuronal culture model of AD characterized by accumulation of cellular amyloid-β (Aβ)42, mTORC1 activity was reduced. Autophagic vesicles and markers were correspondingly increased and new protein synthesis was inhibited, consistent with mTORC1 hypofunction. Interestingly, mTORC2 activity in neural culture seemed resistant to the effects of intracellular amyloid. In various cell lines, Aβ expression provoked insulin resistance, characterized by inhibition of stimulated Akt phosphorylation, and an increase in negative mTORC1 regular, p-AMPK, itself a nutrient sensor. Rapamycin decreased phospho-mTOR and to lesser degree p-Rictor. This further suppression of mTORC1 activity protected cells from Aβ-induced toxicity and insulin resistance. More striking, Rictor over-expression fully reversed the Aβ-effects on primary neuronal cultures. Finally, using in vitro assay, Rictor protein addition completely overcame oligomeric Aβ-induced inhibition of the PDK-Akt activation step. We conclude that striking a new balance by restoring mTORC2 abundance and/or inhibition of mTORC1 has therapeutic potential in AD.

A Multifunctional Biocompatible Drug Candidate is Highly Effective in Delaying Pathological Signs of Alzheimer's Disease in 5XFAD Mice. - Segal-Gavish, Hadar; Danino, Ortal; Barhum, Yael; Ben-Zur, Tali; Shai, Ella; Varon, David; Offen, Daniel; Fischer, Bilha (J Alzheimers Dis, 2017)
BACKGROUND: Metal-ion-chelation was suggested to prevent zinc and copper ions-induced amyloid-β (Aβ) aggregation and oxidative stress, both implicated in the pathophysiology of Alzheimer's disease (AD). In a quest for biocompatible metal-ion chelators potentially useful for AD therapy, we previously tested a series of nucleoside 5'-phosphorothioate derivatives as agents for decomposition of Cu(I)/Cu(II)/Zn(II)-Aβ-aggregates, and as inhibitors of OH radicals formation in Cu(I) or Fe(II) /H2O2 solution. Specifically, in our recent study we have identified 2-SMe-ADP(α-S), designated as SAS, as a most promising neuroprotectant. OBJECTIVE: To further explore SAS ability to protect the brain from Aβ toxicity both in vitro and in vivo. METHODS: We evaluated SAS ability to decompose or inhibit the formation of Aβ42-M(II) aggregates, and rescue primary neurons and astrocytes from Aβ42 toxicity. Furthermore, we aimed at exploring the therapeutic effect of SAS on behavioral and cognitive deficits in the 5XFAD mouse model of AD. RESULTS: We found that SAS can rescue primary culture of neurons and astrocytes from Aβ42 toxicity and to inhibit the formation and dissolve Aβ42-Zn(II)/Cu(II) aggregates. Furthermore, we show that SAS treatment can prevent behavioral disinhibition and ameliorate spatial working memory deficits in 5XFAD mice. Notably, the mice were treated at the age of 2 months, before the onset of AD symptoms, for a duration of 2 months, while the effect was demonstrated at the age of 6 months. CONCLUSION: Our results indicate that SAS has the potential to delay progression of core pathological characteristics of AD in the 5XFAD mouse model.

Network-Based Substrate of Cognitive Reserve in Alzheimer's Disease. - Serra, Laura; Mancini, Matteo; Cercignani, Mara; Di Domenico, Carlotta; Spanò, Barbara; Giulietti, Giovanni; Koch, Giacomo; Marra, Camillo; Bozzali, Marco (J Alzheimers Dis, 2017)
Cognitive reserve (CR) is known to modulate the clinical features of Alzheimer's disease (AD). This concept may be critical for the development of non-pharmacological interventions able to slow down patients' cognitive decline in the absence of disease-modifying treatments. We aimed at identifying the neurobiological substrates of CR (i.e., neural reserve) over the transition between normal aging and AD, by assessing the underlying brain networks and their topological properties. A cohort of 154 participants (n = 68 with AD, n = 61 with amnestic mild cognitive impairment (aMCI), and 25 healthy subjects) underwent resting-state functional MRI and neuropsychological testing. Within each group, participants were classified as having high or low CR, and functional connectivity measures were compared, within group, between high and low CR individuals. Network-based statistics and topological network properties derived from graph theory were explored. Connectivity differences between high and low CR were evident only for aMCI patients, with participants with high CR showing a significant increase of connectivity in a network involving mainly fronto-parietal nodes. Conversely, they showed significantly decreased connectivity in a network involving fronto-temporo-cerebellar nodes. Consistently, changes to topological measures were observed in either direction, and were associated with measures of global cognitive function. These findings support the hypothesis that CR impacts on neurodegenerative process in the early phase of AD only. In addition, they fit with the existence of a "neural reserve", characterized by specific neural networks and their efficiency. It remains to be demonstrated whether interventions later in life can modulate this "neural reserve".

Neural Correlates of Self-Reference Effect in Early Alzheimer's Disease. - Gaubert, Malo; Villain, Nicolas; Landeau, Brigitte; Mézenge, Florence; Egret, Stéphanie; Perrotin, Audrey; Belliard, Serge; de la Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice; Chételat, Gaël; Rauchs, Géraldine (J Alzheimers Dis, 2017)
Information that is processed with reference to the self (i.e., self-referential processing, SRP) is generally associated with better remembering than information processed in a semantic condition. This benefit of self on memory performance is called self-reference effect (SRE). In the present study, we assessed changes in the SRE and SRP-related brain activity in patients diagnosed with mild cognitive impairment or early Alzheimer's disease (MCI/AD). Fifteen patients with confirmed amyloid-β deposits (positive florbetapir-PET scan) and 28 healthy controls (negative florbetapir-PET scan) were included. Participants either had to judge personality trait adjectives with reference to themselves (self condition) or to a celebrity (other condition), or determine whether these adjectives were positive or not (semantic condition). These adjectives were then presented with distractors in a surprise recognition task. Functional MRI data were acquired during both the judgment and recognition tasks. The SRE was observed in controls, but reduced in patients. Both controls and patients activated cortical midline structures when judging items with reference to themselves, but patients exhibited reduced activity in the angular gyrus. In patients, activity at encoding in the angular gyrus positively correlated with subsequent recognition accuracy in the self condition (self accuracy). This region also exhibited significant hypometabolism and Aβ burden, both related to self accuracy. By contrast, there were no differences in brain activity during recognition, either between the self and semantic conditions, or between groups. These results highlight SRE impairment in patients with MCI/AD, despite intact activity in cortical midline structures, and suggest that dysfunction of the angular gyrus is related to this impairment.

Neurocognitive and Behavioral Indexes for Identifying the Amnestic Subtypes of Mild Cognitive Impairment. - Cid-Fernández, Susana; Lindín, Mónica; Díaz, Fernando (J Alzheimers Dis, 2017)
Early identification of amnestic mild cognitive impairment (aMCI) subtypes is important for early diagnosis and prognosis of Alzheimer's disease. Healthy, single-domain (sdaMCI) and multiple-domain aMCI (mdaMCI) participants performed an auditory-visual distraction-attention task. Event-related brain potentials (ERPs) were recorded while the participants performed the task to evaluate Go/NoGo N2 and P3 ERP components. The results showed the expected behavioral and cognitive decline in mdaMCI participants relative to controls (fewer hits, longer reaction times [RTs], slightly smaller Go-N2 and NoGo-N2 amplitudes), while sdaMCI participants showed some decline (slightly longer RTs, smaller Go- and NoGo-N2 amplitudes) along with some unexpected results (a late positive slow wave, PSW) and good levels of execution. In addition, some of these parameters proved to be useful markers. Thus, the number of hits was the best marker for diagnosing mdaMCI participants (distinguishing them from controls, from sdaMCI participants, and from both groups together), while the PSW amplitude was the best marker for diagnosing sdaMCI participants (distinguishing them from controls, and from control & mdaMCI participants).

Neurons Derived from Induced Pluripotent Stem Cells of Patients with Down Syndrome Reproduce Early Stages of Alzheimer's Disease Type Pathology in vitro. - Dashinimaev, Erdem B; Artyuhov, Alexander S; Bolshakov, Alexey P; Vorotelyak, Ekaterina A; Vasiliev, Andrey V (J Alzheimers Dis, 2017)
People with Down syndrome (DS) are at high risk of developing pathology similar to Alzheimer's disease (AD). Modeling of this pathology in vitro may be useful for studying this phenomenon. In this study, we analyzed three different cultures of neural cells carrying trisomy of chromosome 21, which were generated by directed differentiation from induced pluripotent stem cells (iPS cells). We report here that in vitro generated DS neural cells have abnormal metabolism of amyloid-β (Aβ) manifested by increased secretion and accumulation of Aβ granules of Aβ42 pathological isoform with upregulated expression of the APP gene. Additionally, we found increased expression levels of genes that are considered to be associated with AD (BACE2, RCAN1, ETS2, TMED10), as compared to healthy controls. Thus, the neural cells generated from induced pluripotent stem cells with DS reproduce initial cellular signs of AD-type pathology and can be useful tools for modeling and studying this variant of AD in vitro.

Neutrophil Gelatinase-Associated Lipocalin and its Receptors in Alzheimer's Disease (AD) Brain Regions: Differential Findings in AD with and without Depression. - Dekens, Doortje W; Naudé, Petrus J W; Engelborghs, Sebastiaan; Vermeiren, Yannick; Van Dam, Debby; Oude Voshaar, Richard C; Eisel, Ulrich L M; De Deyn, Peter P (J Alzheimers Dis, 2017)
Co-existing depression worsens Alzheimer's disease (AD) pathology. Neutrophil gelatinase-associated lipocalin (NGAL) is a newly identified (neuro)inflammatory mediator in the pathophysiologies of both AD and depression. This study aimed to compare NGAL levels in healthy controls, AD without depression (AD-D), and AD with co-existing depression (AD+D) patients. Protein levels of NGAL and its receptors, 24p3R and megalin, were assessed in nine brain regions from healthy controls (n = 19), AD-D (n = 19), and AD+D (n = 21) patients. NGAL levels in AD-D patients were significantly increased in brain regions commonly associated with AD. In the hippocampus, NGAL levels were even further increased in AD+D subjects. Unexpectedly, NGAL levels in the prefrontal cortex of AD+D patients were comparable to those in controls. Megalin levels were increased in BA11 and amygdala of AD+D patients, while no changes in 24p3R were detected. These findings indicate significant differences in neuroimmunological regulation between AD patients with and without co-existing depression. Considering its known effects, elevated NGAL levels might actively promote neuropathological processes in AD with and without depression.

New Gold in Them Thar Hills: Testing a Novel Supply Route for Plant-Derived Galanthamine. - Fraser, Mariecia D; Davies, John R T; Chang, Xianmin (J Alzheimers Dis, 2017)
Many secondary plant compounds are synthesized in response to stressed growing conditions. We tested the feasibility of exploiting this feature in a novel strategy for the commercial production of the plant alkaloid galanthamine. Experimental lines of Narcissus pseudonarcissus were established under marginal upland permanent pasture at four different sites. Over 80% of bulbs successfully established at each site. There was no effect of altitude or planting density on galanthamine concentrations within vegetative tissues, which were higher than anticipated. The results confirm that planting N. pseudonarcissus under grass competition in upland areas could offer a novel and sustainable source of plant-derived galanthamine.

Novel Phospho-Tau Monoclonal Antibody Generated Using a Liposomal Vaccine, with Enhanced Recognition of a Conformational Tauopathy Epitope. - Theunis, Clara; Adolfsson, Oskar; Crespo-Biel, Natalia; Piorkowska, Kasia; Pihlgren, Maria; Hickman, David T; Gafner, Valerie; Borghgraef, Peter; Devijver, Herman; Pfeifer, Andrea; Van Leuven, Fred; Muhs, Andreas (J Alzheimers Dis, 2017)
The microtubule-associated protein Tau is an intrinsically unfolded, very soluble neuronal protein. Under still unknown circumstances, Tau protein forms soluble oligomers and insoluble aggregates that are closely linked to the cause and progression of various brain pathologies, including Alzheimer's disease. Previously we reported the development of liposome-based vaccines and their efficacy and safety in preclinical mouse models for tauopathy. Here we report the use of a liposomal vaccine for the generation of a monoclonal antibody with particular characteristics that makes it a valuable tool for fundamental studies as well as a candidate antibody for diagnostic and therapeutic applications. The specificity and affinity of antibody ACI-5400 were characterized by a panel of methods: (i) measuring the selectivity for a specific phospho-Tau epitope known to be associated with tauopathy, (ii) performing a combination of peptide and protein binding assays, (iii) staining of brain sections from mouse preclinical tauopathy models and from human subjects representing six different tauopathies, and (iv) evaluating the selective binding to pathological epitopes on extracts from tauopathy brains in non-denaturing sandwich assays. We conclude that the ACI-5400 antibody binds to protein Tau phosphorylated at S396 and favors a conformation that is typically present in the brain of tauopathy patients, including Alzheimer's disease.

A Novel PSEN1 K311R Mutation Discovered in Chinese Families with Late-Onset Alzheimer's Disease Affects Amyloid-β Production and Tau Phosphorylation. - Dong, Jing; Qin, Wei; Wei, Cuibai; Tang, Yi; Wang, Qi; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) is the most frequently mutated gene in familial Alzheimer's disease (AD), whereas only several novel mutations have been reported in China and functional studies were seldom conducted. OBJECTIVE: We describe a novel PSEN1 K311R mutation in two Chinese families with late-onset AD and its functional impact on amyloid-β protein precursor (AβPP) processing and tau phosphorylation. METHODS: The mutation was detected by direct sequencing of PSEN1 exon 9. HEK293 cells stably expressing wild-type APP695 (HEK293-APP695wt) were transfected with plasmids containing human wild-type PSEN1, PSEN1 K311R mutation, and PSEN1 E280A mutation to compare the K311R mutation's effects on AβPP processing with other groups. In addition, each group of cells were co-transfected with plasmids harboring PSEN1 and human wild-type MAPT complementary DNA to study the mutation's impacts on tau phosphorylation. RESULTS: The K311R mutation was detected in probands of two late-onset AD families. Expression of the K311R or E280A mutation increased amyloid-β (Aβ)42 levels but decreased Aβ40 levels, resulting in an overall increase in the Aβ42/Aβ40 ratio compared to those in wild-type PSEN1 transfected cells (p < 0.05). The K311R or E280A mutation also increased the levels of phosphorylated tau compared to wild-type PSEN1 (p < 0.05). CONCLUSION: The K311R mutation might contribute to AD pathogenesis by overproducing toxic Aβ species and enhancing tau phosphorylation. Further in-depth studies are needed to decipher the pathogenic mechanisms of the K311R mutation in terms of AβPP cleavage, tau phosphorylation, and other presenilin-1 mediated functional pathways.

N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Passive Assessment of Routine Driving with Unobtrusive Sensors: A New Approach for Identifying and Monitoring Functional Level in Normal Aging and Mild Cognitive Impairment. - Seelye, Adriana; Mattek, Nora; Sharma, Nicole; Witter, Phelps; Brenner, Ariella; Wild, Katherine; Dodge, Hiroko; Kaye, Jeffrey (J Alzheimers Dis, 2017)
BACKGROUND: Driving is a key functional activity for many older adults, and changes in routine driving may be associated with emerging cognitive decline due to early neurodegenerative disease. Current methods for assessing driving such as self-report are inadequate for identifying and monitoring subtle changes in driving patterns that may be the earliest signals of functional change in developing mild cognitive impairment (MCI). OBJECTIVE: This proof of concept study aimed to establish the feasibility of continuous driving monitoring in a sample of cognitively normal and MCI older adults for an average of 206 days using an unobtrusive driving sensor and demonstrate that derived sensor-based driving metrics could effectively discriminate between MCI and cognitively intact groups. METHODS: Novel objective driving measures derived from 6 months of routine driving monitoring were examined in older adults with intact cognition (n = 21) and MCI (n = 7) who were enrolled in the Oregon Center for Aging and Technology (ORCATECH) longitudinal assessment program. RESULTS: Unobtrusive continuous monitoring of older adults' routine driving using a driving sensor was feasible and well accepted. MCI participants drove fewer miles and spent less time on the highway per day than cognitively intact participants. MCI drivers showed less day-to-day fluctuations in their driving habits than cognitively intact drivers. CONCLUSION: Sensor-based driving measures are objective, unobtrusive, and can be assessed every time a person drives his or her vehicle to identify clinically meaningful changes in daily driving. This novel methodology has the potential to be useful for the early detection and monitoring of changes in daily functioning within individuals.

Pathway-Specific Polygenic Risk Scores as Predictors of Amyloid-β Deposition and Cognitive Function in a Sample at Increased Risk for Alzheimer's Disease. - Darst, Burcu F; Koscik, Rebecca L; Racine, Annie M; Oh, Jennifer M; Krause, Rachel A; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Christian, Bradley T; Bendlin, Barbara B; Okonkwo, Ozioma C; Hogan, Kirk J; et al. (J Alzheimers Dis, 2017)
Polygenic risk scores (PRSs) have been used to combine the effects of variants with small effects identified by genome-wide association studies. We explore the potential for using pathway-specific PRSs as predictors of early changes in Alzheimer's disease (AD)-related biomarkers and cognitive function. Participants were from the Wisconsin Registry for Alzheimer's Prevention, a longitudinal study of adults who were cognitively asymptomatic at enrollment and enriched for a parental history of AD. Using genes associated with AD in the International Genomics of Alzheimer's Project's meta-analysis, we identified clusters of genes that grouped into pathways involved in amyloid-β (Aβ) deposition and neurodegeneration: Aβ clearance, cholesterol metabolism, and immune response. Weighted pathway-specific and overall PRSs were developed and compared to APOE alone. Mixed models were used to assess whether each PRS was associated with cognition in 1,200 individuals, cerebral Aβ deposition measured using amyloid ligand (Pittsburgh compound B) positron emission imaging in 168 individuals, and cerebrospinal fluid Aβ deposition, neurodegeneration, and tau pathology in 111 individuals, with replication performed in an independent sample. We found that PRSs including APOE appeared to be driven by the inclusion of APOE, suggesting that the pathway-specific PRSs used here were not more predictive than an overall PRS or APOE alone. However, pathway-specific PRSs could prove to be useful as more knowledge is gained on the genetic variants involved in specific biological pathways of AD.

PET Imaging of Tau Pathology and Relationship to Amyloid, Longitudinal MRI, and Cognitive Change in Down Syndrome: Results from the Down Syndrome Biomarker Initiative (DSBI). - Rafii, Michael S; Lukic, Ana S; Andrews, Randolph D; Brewer, James; Rissman, Robert A; Strother, Stephen C; Wernick, Miles N; Pennington, Craig; Mobley, William C; Ness, Seth; Matthews, Dawn C (J Alzheimers Dis, 2017)
BACKGROUND: Adults with Down syndrome (DS) represent an enriched population for the development of Alzheimer's disease (AD), which could aid the study of therapeutic interventions, and in turn, could benefit from discoveries made in other AD populations. OBJECTIVES: 1) Understand the relationship between tau pathology and age, amyloid deposition, neurodegeneration (MRI and FDG PET), and cognitive and functional performance; 2) detect and differentiate AD-specific changes from DS-specific brain changes in longitudinal MRI. METHODS: Twelve non-demented adults, ages 30 to 60, with DS were enrolled in the Down Syndrome Biomarker Initiative (DSBI), a 3-year, observational, cohort study to demonstrate the feasibility of conducting AD intervention/prevention trials in adults with DS. We collected imaging data with 18F-AV-1451 tau PET, AV-45 amyloid PET, FDG PET, and volumetric MRI, as well as cognitive and functional measures and additional laboratory measures. RESULTS: All amyloid negative subjects imaged were tau-negative. Among the amyloid positive subjects, three had tau in regions associated with Braak stage VI, two at stage V, and one at stage II. Amyloid and tau burden correlated with age. The MRI analysis produced two distinct volumetric patterns. The first differentiated DS from normal (NL) and AD, did not correlate with age or amyloid, and was longitudinally stable. The second pattern reflected AD-like atrophy and differentiated NL from AD. Tau PET and MRI atrophy correlated with several cognitive and functional measures. CONCLUSIONS: Tau accumulation is associated with amyloid positivity and age, as well as with progressive neurodegeneration measurable using FDG and MRI. Tau correlates with cognitive decline, as do AD-specific hypometabolism and atrophy.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Phenotype-Dependent Interactions between N-acetyl-L-Aspartate and Acetyl-CoA in Septal SN56 Cholinergic Cells Exposed to an Excess of Zinc. - Zyśk, Marlena; Bielarczyk, Hanna; Gul-Hinc, Sylwia; Dyś, Aleksandra; Gapys, Beata; Ronowska, Anna; Sakowicz-Burkiewicz, Monika; Szutowicz, Andrzej (J Alzheimers Dis, 2017)
Pyruvate dehydrogenase reaction utilizing glucose-derived pyruvate is an almost exclusive source of acetyl-CoA in different cell mitochondrial compartments of the brain. In neuronal mitochondria, the largest fraction of acetyl-CoA is utilized for energy production and the much smaller one for N-acetyl-L-aspartate (NAA) synthesis. Cholinergic neurons, unlike others, require additional amounts of acetyl-CoA for acetylcholine synthesis. Therefore, several neurotoxic signals, which inhibit pyruvate dehydrogenase, generate deeper shortages of acetyl-CoA and greater mortality of cholinergic neurons than noncholinergic ones. NAA is considered to be a marker of neuronal energy status in neuropathic brains. However, there is no data on putative differential fractional distribution of the acetyl-CoA pool between energy producing and NAA or acetylcholine synthesizing pathways in noncholinergic and cholinergic neurons, respectively. Therefore, the aim of this study was to investigate whether zinc-excess, a common excitotoxic signal, may evoke differential effects on the NAA metabolism in neuronal cells with low and high expression of the cholinergic phenotype. Differentiated SN56 neuronal cells, displaying a high activity of choline acetyltransferase and rates of acetylcholine synthesis, contained lower levels of acetyl-CoA and NAA, being more susceptible to ZnCl2 exposition that the nondifferentiated SN56 or differentiated dopaminergic SHSY5Y neuronal and astroglial C6 cells. Differentiated SN56 accumulated greater amounts of Zn2 + from extracellular space than the other ones, and displayed a stronger suppression of pyruvate dehydrogenase complex activity and acetyl-CoA, NAA, ATP, acetylcholine levels, and loss of viability. These data indicate that the acetyl-CoA synthesizing system in neurons constitutes functional unity with energy generating and NAA or acetylcholine pathways of its utilization, which are uniformly affected by neurotoxic conditions.

Phospho-Tau Accumulation and Structural Alterations of the Golgi Apparatus of Cortical Pyramidal Neurons in the P301S Tauopathy Mouse Model. - Antón-Fernández, Alejandro; Merchán-Rubira, Jesús; Avila, Jesús; Hernández, Félix; DeFelipe, Javier; Muñoz, Alberto (J Alzheimers Dis, 2017)
The Golgi apparatus (GA) is a highly dynamic organelle involved in the processing and sorting of cellular proteins. In Alzheimer's disease (AD), it has been shown to decrease in size and become fragmented in neocortical and hippocampal neuronal subpopulations. This fragmentation and decrease in size of the GA in AD has been related to the accumulation of hyperphosphorylated tau. However, the involvement of other pathological factors associated with the course of the disease, such as the extracellular accumulation of amyloid-β (Aβ) aggregates, cannot be ruled out, since both pathologies are present in AD patients. Here we use the P301S tauopathy mouse model to examine possible alterations of the GA in neurons that overexpress human tau (P301S mutated gene) in neocortical and hippocampal neurons, using double immunofluorescence techniques and confocal microscopy. Quantitative analysis revealed that neurofibrillary tangle (NFT)-bearing neurons had important morphological alterations and reductions in the surface area and volume of the GA compared with NFT-free neurons. Since in this mouse model there are no Aβ aggregates typical of AD, the present findings support the idea that the progressive accumulation of phospho-tau is associated with structural alterations of the GA, and that these changes may occur in the absence of Aβ pathology.

The Pitfall of Behavioral Variant Frontotemporal Dementia Mimics Despite Multidisciplinary Application of the FTDC Criteria. - Krudop, Welmoed A; Dols, Annemieke; Kerssens, Cora J; Eikelenboom, Piet; Prins, Niels D; Möller, Christiane; Schouws, Sigfried; Rhebergen, Didi; van Exel, Eric; van der Flier, Wiesje M; Sikkes, Sietske; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The behavioral variant of frontotemporal dementia (bvFTD) has a broad differential diagnosis including other neurological and psychiatric disorders. Psychiatric misdiagnoses occur in up to 50% of bvFTD patients. Numbers on misdiagnosis of bvFTD in psychiatric disorders are lacking. OBJECTIVE: The aim of our study was to investigate the frequency and characteristics of bvFTD misdiagnoses in psychiatric disorders and other neurologic disorders. METHODS: Thirty-five patients with a (possible or probable) bvFTD diagnosis made by specialized memory clinic neurologists were included. Change in diagnosis after consulting a psychiatrist at baseline was recorded as well as change in diagnosis after two years of multidisciplinary neuropsychiatric follow-up. Differences in cognitive and behavioral profiles were investigated per diagnostic group after follow-up (bvFTD, psychiatry, other neurologic disorders). Clinical profiles are described in detail. RESULTS: In 17 patients (48.5%), the bvFTD baseline diagnosis changed: Two at baseline after psychiatric consultation, and 15 after two years of multidisciplinary follow-up. Eleven (64.5%) of these 17 patients (31.5% of total) were reclassified with a psychiatric diagnosis. We found no differences for cognitive baseline profiles between patients with bvFTD versus psychiatric diagnoses. CONCLUSION: In almost half of cases, the initial bvFTD diagnosis was changed after follow-up, most often into a psychiatric disorder. A multidisciplinary neuropsychiatric approach in the diagnostic process of bvFTD results in the identification of treatable disorders. Our findings illustrate a limited specificity of the [18F]FDG-PET-scan and the bvFTD criteria in a neuropsychiatric cohort, especially combined with certain clinical symptoms, like disinhibition, apathy, or loss of empathy.

Plasma Amyloid-β Peptides in Type 2 Diabetes: A Matched Case-Control Study. - Peters, Kirsten E; Davis, Wendy A; Taddei, Kevin; Martins, Ralph N; Masters, Colin L; Davis, Timothy M E; Bruce, David G (J Alzheimers Dis, 2017)
BACKGROUND: Plasma amyloid-β (Aβ) levels have rarely been investigated in type 2 diabetes despite its known associations with Alzheimer's disease. OBJECTIVE: To compare blood plasma Aβ concentrations (Aβ40 and Aβ42) in cognitively normal individuals with and without type 2 diabetes. METHODS: Plasma Aβ40 and Aβ42 were measured in 194 participants with diabetes recruited from the community-based Fremantle Diabetes Study Phase II cohort (mean age 71 years, 59% males) and 194 age-, sex-, and APOEɛ4 allele-matched, control subjects without diabetes from the Australian Imaging, Biomarkers and Lifestyle Study using a multiplex microsphere-based immunoassay. RESULTS: Plasma Aβ40 and Aβ42 were normally distributed in the controls but were bimodal in the participants with diabetes. Median Aβ40 and Aβ42 concentrations were significantly lower in those with type 2 diabetes (Aβ40 median [inter-quartile range]: 125.0 [52.6-148.3] versus 149.3 [134.0-165.6] pg/mL; Aβ42: 26.9 [14.5-38.3] versus 33.6 [28.0-38.9] pg/mL, both p < 0.001) while the ratio Aβ42:Aβ40 was significantly higher (0.26 [0.23-0.32] versus 0.22 [0.19-0.25], p < 0.001). After adjustment, participants with diabetes and plasma Aβ40 levels in the low peak of the bimodal distribution were significantly more likely to have normal to high estimated glomerular filtration rates (odds ratio (95% CI): 2.40 (1.20-4.80), p = 0.013) although the group with diabetes had lower renal function overall. CONCLUSION: Type 2 diabetes is associated with altered plasma concentrations of Aβ peptides and is an important source of variation that needs to be taken into account when considering plasma Aβ peptides as biomarkers for Alzheimer's disease.

Plasma Proteomic Profiles of Cerebrospinal Fluid-Defined Alzheimer's Disease Pathology in Older Adults. - Dayon, Loïc; Wojcik, Jérôme; Núñez Galindo, Antonio; Corthésy, John; Cominetti, Ornella; Oikonomidi, Aikaterini; Henry, Hugues; Migliavacca, Eugenia; Bowman, Gene L; Popp, Julius (J Alzheimers Dis, 2017)
BACKGROUND: Cerebrospinal fluid (CSF) biomarkers of the beta-amyloid and microtubule associated protein tau metabolism have proven the capacity to improve classification of subjects developing Alzheimer's disease (AD). The blood plasma proteome was characterized to further elaborate upon the mechanisms involved and identify proteins that may improve classification of older adults developing an AD dementia. OBJECTIVE: Identify and describe plasma protein expressions that best classify subjects with CSF-defined presence of AD pathology and cerebral amyloidosis. METHODS: We performed a cross-sectional analysis of samples collected from community-dwelling elderly with (n = 72) or without (n = 48) cognitive impairment. CSF Aβ1-42, tau, and phosphorylated tau (P-tau181) were measured using ELISA, and mass spectrometry quantified the plasma proteomes. Presence of AD pathology was defined as CSF P-tau181/Aβ1-42 > 0.0779, and presence of amyloidosis was defined as CSF Aβ1-42 < 724 pg/mL. RESULTS: Two hundred and forty-eight plasma proteins were quantified. Plasma proteins did not improve classification of the AD CSF biomarker profile in the whole sample. When the analysis was separately performed in the cognitively impaired individuals, the diagnosis accuracy of AD CSF profile was 88.9% with 19 plasma proteins included. Within the full cohort, there were 16 plasma proteins that improved diagnostic accuracy of cerebral amyloidosis to 92.4%. CONCLUSION: Plasma proteins improved classification accuracy of AD pathology in cognitively-impaired older adults and appeared representative of amyloid pathology. If confirmed, those candidates could serve as valuable blood biomarkers of the preclinical stages of AD or risk of developing AD.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Pleiotropic Effect of Human ApoE4 on Cerebral Ceramide and Saturated Fatty Acid Levels. - den Hoedt, Sandra; Janssen, Carola I F; Astarita, Giuseppe; Piomelli, Daniele; Leijten, Frank P J; Crivelli, Simone M; Verhoeven, Adrie J M; De Vries, Helga E; Walter, Jochen; Martinez-Martinez, Pilar; Sijbrands, Eric J G; Kiliaan, Amanda J; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) is known for its role in lipid trafficking and the ɛ4 allele is a risk factor for late onset Alzheimer's disease (AD). Recently, aberrant ceramide and fatty acid (FA) levels have been implicated in AD. OBJECTIVE: To determine the specific effects of human ApoE4 (hE4) on cerebral ceramide and FA content during chow or a high fat/high cholesterol (HFHC) diet. METHODS: Cerebral ceramide and FA profiles were determined by LC-MSMS in 15-month-old female wild-type (WT), ApoE-knockout (E0), and hE4-knockin mice fed chow or a HFHC diet for 3 months. mRNA levels of genes involved in ceramide and FA metabolism were determined by qPCR. RESULTS: Similar to E0, hE4 mice displayed lower cerebral total ceramide, Cer16 : 0, and Cer24 : 1 levels than WT mice on both diets. Akin to WT mice, hE4 mice had lower total and saturated FA levels on chow than E0 mice. The HFHC diet significantly increased total and saturated FA levels in hE4 mice. Chow-fed hE4 mice showed lower mRNA levels of ceramide synthase (CerS) 6, acid sphingomyelinase, and of most ceramide and FA transporters than WT and E0 mice. The HFHC diet downregulated the expression of CerSs in hE4 and WT mice, and of ceramide and FA transporters in WT mice, but not in E0 mice. CONCLUSION: hE4 reduced cerebral ceramide levels to levels observed in E0 mice independent of diet. The HFHC diet increased cerebral FA levels in hE4 mice. This was associated with alterations in the expression of ceramide and FA transporters specifically in hE4 mice.

Polymorphonuclear Neutrophil Functions are Differentially Altered in Amnestic Mild Cognitive Impairment and Mild Alzheimer's Disease Patients. - Le Page, Aurélie; Lamoureux, Julie; Bourgade, Karine; Frost, Eric H; Pawelec, Graham; Witkowski, Jacek M; Larbi, Anis; Dupuis, Gilles; Fülöp, Tamás (J Alzheimers Dis, 2017)
The mechanisms of neurodegeneration in Alzheimer's disease (AD) remain under investigation. Alterations in the blood-brain barrier facilitate exchange of inflammatory mediators and immune cells between the brain and the periphery in AD. Here, we report analysis of phenotype and functions of polymorphonuclear neutrophils (PMN) in peripheral blood from patients with amnestic mild cognitive impairment (aMCI, n = 13), patients with mild AD (mAD, n = 15), and healthy elderly controls (n = 13). Results showed an increased expression of CD177 in mAD but not in healthy or aMCI patients. IL-8 stimulated increased expression of the CD11b integrin in PMN of healthy subjects in vitro but PMN of aMCI and mAD patients failed to respond. CD14 and CD16 expression was lower in PMN of mAD but not in aMCI individuals relative to controls. Only PMN of aMCI subjects expressed lower levels of CD88. Phagocytosis toward opsonized E. coli was differentially impaired in PMN of aMCI and mAD subjects whereas the capacity to ingest Dextran particles was absent only in mAD subjects. Killing activity was severely impaired in aMCI and mAD subjects whereas free radical production was only impaired in mAD patients. Inflammatory cytokine (TNFα, IL-6, IL-1β, IL-12p70) and chemokine (MIP-1α, MIP-1β, IL-8) production in response to LPS stimulation was very low in aMCI and nearly absent in mAD subjects. TLR2 expression was low only in aMCI. Our data showed a differentially altered capacity of PMN of aMCI and mAD subjects to respond to pathological aggression that may impact impaired responses associated with AD development.

Precuneus Failures in Subjects of the PSEN1 E280A Family at Risk of Developing Alzheimer's Disease Detected Using Quantitative Electroencephalography. - Ochoa, John Fredy; Alonso, Joan Francesc; Duque, Jon Edinson; Tobón, Carlos Andrés; Baena, Ana; Lopera, Francisco; Mañanas, Miguel Angel; Hernández, Alher Mauricio (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) mutations are the most common cause of familial early onset Alzheimer's disease (AD). The PSEN1 E280A (E280A) mutation has an autosomal dominant inheritance and is involved in the production of amyloid-β. The largest family group of carriers with E280A mutation is found in Antioquia, Colombia. The study of mutation carriers provides a unique opportunity to identify brain changes in stages previous to AD. Electroencephalography (EEG) is a low cost and minimally invasiveness technique that enables the following of brain changes in AD. OBJECTIVE: To examine how previous reported differences in EEG for Theta and Alpha-2 rhythms in E280A subjects are related to specific regions in cortex and could be tracked across different ages. METHODS: EEG signals were acquired during resting state from non-carriers and carriers, asymptomatic and symptomatic subjects from E280A kindred from Antioquia, Colombia. Independent component analysis (ICA) and inverse solution methods were used to locate brain regions related to differences in Theta and Alpha-2 bands. RESULTS: ICA identified two components, mainly related to the Precuneus, where the differences in Theta and Alpha-2 exist simultaneously at asymptomatic and symptomatic stages. When the ratio between Theta and Alpha-2 is used, significant correlations exist with age and a composite cognitive scale. CONCLUSION: Theta and Alpha-2 rhythms are altered in E280A subjects. The alterations are possible to track at Precuneus regions using EEG, ICA, and inverse solution methods.

Predicting Development of Amyotrophic Lateral Sclerosis in Frontotemporal Dementia. - Van Langenhove, Tim; Piguet, Olivier; Burrell, James R; Leyton, Cristian; Foxe, David; Abela, Melissa; Bartley, Lauren; Kim, Woojin S; Jary, Eve; Huang, Yue; Dobson-Stone, Carol; Kwok, John B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: A proportion of patients with frontotemporal dementia (FTD) also develop amyotrophic lateral sclerosis (ALS). OBJECTIVE: We aimed to establish the risk of developing ALS in patients presenting with FTD and to identify the relevant clinical variables associated with progression from FTD to FTD-ALS. METHODS: Of 218 consecutive patients with FTD, 10.1% had a dual FTD-ALS diagnosis at presentation. The remaining 152 FTD patients with follow-up of at least 12 months were included in the present study. We calculated the rate of progression to FTD-ALS and compared the baseline characteristics of FTD patients who developed ALS to those who did not develop ALS. RESULTS: Five percent of FTD patients developed ALS. The incidence rate of ALS was 6.7/100 patient-years in patients with FTD symptoms since 1 year, which declined with duration of FTD symptoms. No FTD patients developed ALS after 5 years. Five out of 8 FTD patients who developed ALS had presented with a mixed behavioral variant FTD and progressive non-fluent aphasia (bvFTD+PNFA) phenotype, 2 with bvFTD, and 1 with PNFA. Progression to FTD-ALS was significantly more frequent in patients with bvFTD+PNFA compared to those without this phenotype (p < 0.0001, OR 38.3, 95% CI: 7.3 to 199.2), and in FTD patients who carried the C9orf72 repeat expansion compared to those without the repeat expansion (p = 0.02, OR 8.0, 95% CI: 1.7 to 38.6). CONCLUSIONS: FTD patients with a mixed bvFTD+PNFA phenotype and with a C9orf72 repeat expansion should be closely monitored for the possible development of ALS. The risk of developing ALS in FTD appears to decline with the duration of FTD symptoms.

Prediction of Conversion to Alzheimer's Disease with Longitudinal Measures and Time-To-Event Data. - Li, Kan; Chan, Wenyaw; Doody, Rachelle S; Quinn, Joseph; Luo, Sheng (J Alzheimers Dis, 2017)
BACKGROUND: Identifying predictors of conversion to Alzheimer's disease (AD) is critically important for AD prevention and targeted treatment. OBJECTIVE: To compare various clinical and biomarker trajectories for tracking progression and predicting conversion from amnestic mild cognitive impairment to probable AD. METHODS: Participants were from the ADNI-1 study. We assessed the ability of 33 longitudinal biomarkers to predict time to AD conversion, accounting for demographic and genetic factors. We used joint modelling of longitudinal and survival data to examine the association between changes of measures and disease progression. We also employed time-dependent receiver operating characteristic method to assess the discriminating capability of the measures. RESULTS: 23 of 33 longitudinal clinical and imaging measures are significant predictors of AD conversion beyond demographic and genetic factors. The strong phenotypic and biological predictors are in the cognitive domain (ADAS-Cog; RAVLT), functional domain (FAQ), and neuroimaging domain (middle temporal gyrus and hippocampal volume). The strongest predictor is ADAS-Cog 13 with an increase of one SD in ADAS-Cog 13 increased the risk of AD conversion by 2.92 times. CONCLUSION: Prediction of AD conversion can be improved by incorporating longitudinal change information, in addition to baseline characteristics. Cognitive measures are consistently significant and generally stronger predictors than imaging measures.

Predictors of Discharge Destinations and Three-Month Evolution of Patients Initially Hospitalized in a Cognitive Behavioral Unit. - Pongan, Elodie; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Federico, Denis; Sellier, Claire; Auguste, Nicolas; Fabre, Florence; Laurent, Bernard; Trombert-Paviot, Béatrice; Rouch, Isabelle (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies showed that a third of patients living at home entered an institution after hospitalization in Cognitive and Behavioral Units (CBUs). OBJECTIVE: The main objective of this study was to identify predictors of discharge destination for these patients. The secondary objective was to estimate whether institutionalization can have an impact on a patient's long-term prognosis. METHODS: The study population was selected from the EVITAL study and included 140 participants living at home before hospitalization in CBUs. Factors favoring nursing-home admission were investigated and the impact of discharge destinations (i.e., home or nursing home) on patients' prognosis was examined. RESULTS: Institutionalized patients were more likely to be women (F = 4.7; p = 0.03), with a higher dementia severity (F = 9.82; p = 0.007), often living alone (F = 19.69; p = 0.001), with a caregiver other than spouse (F = 8.93; p = 0.003), and with a higher patient quality of life (QoL) according to the caregiver (F = 11.73; p = 0.001). When using multivariate logistic linear regressions, we showed a relationship between marital status (OR = 0.19, 95% CI: 0.08-0.43, p < 0.001), dementia severity (OR = 0.15, 95% CI: 0.03-0.79, p = 0.03), QoL (OR = 0.88, 95% CI: 0.79-0.98, p = 0.017), and institutionalization. At three months, a higher overall rate of rehospitalization (F = 12.21; p < 0.001) and rehospitalization for behavioral and psychological symptoms of dementia (F = 6.76; p = 0.006) were observed for patients staying at home after CBU discharge. CONCLUSION: Our study allows for a better understanding of the institutionalization risk factors of the patients hospitalized in CBUs. Identification of these factors could help clinicians to better support patients and to help the transition to be smoother. Moreover, our results suggest that prognosis of institutionalized patients is not unfavorable when compared with patients staying at home.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Prevalence, Risk Factors, and Complaints Screening Tool Exploration of Subjective Cognitive Decline in a Large Cohort of the Chinese Population. - Hao, Lixiao; Wang, Xiaoni; Zhang, Ling; Xing, Yue; Guo, Qihao; Hu, Xiaochen; Mu, Bin; Chen, Yili; Chen, Guanqun; Cao, Jing; Zhi, Xiaodong; Liu, Jiaojiao; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Substantial studies have reported the prevalence and the affecting factors of subjective cognitive decline (SCD). The complaints screening scale has also been used for probing. However, little is known in China. OBJECTIVE: To investigate the prevalence and risk factors of SCD, and explore an SCD complaints screening scale in China. METHODS: Stratified cluster random sampling was conducted. 2,689 residents aged 60-80 years completed questionnaire 1. 814 residents were included for clinical and neuropsychological evaluations. Two standards were used to make the diagnosis of mild cognitive impairment (MCI) and SCD, and a preliminary screening rate comparison was carried out. Finally, we assessed the risk factors of SCD and the correlation between the SCD-questionnaire 9 (SCD-Q9) and the Auditory Verbal Learning Test-Long Delay Free Recall (AVLT-LR). RESULTS: 1) Standard 1 (ADNI2): the prevalence of SCD was 18.8% (95% CI = 14.7-22.9%) and zero conformed to six criteria (SCD plus). 2) Standard 2 (Jak/Bondi): the prevalence of SCD was 14.4% (95% CI = 10.7-18.1%). 3) Standard 1 had a relatively higher "false" positive rate, whereas Standard 2 had higher "false" negative rate. 4) Age, low education, fewer close friends, and daily drinking were independent risk factors for SCD progressing to MCI. 5) Total points of SCD-Q9 were negatively correlated to the value of AVLT-LR. CONCLUSIONS: The prevalence of SCD is high in the ShunYi District in Beijing, China. Age, low education, less social support, and daily drinking are independent risk factors. The brief SCD-Q9 can be used as a reference.

proBDNF Accelerates Brain Amyloid-β Deposition and Learning and Memory Impairment in APPswePS1dE9 Transgenic Mice. - Chen, Jia; Zhang, Tao; Jiao, Shusheng; Zhou, Xinfu; Zhong, Jinhua; Wang, Yanjiang; Liu, Juan; Deng, Juan; Wang, Shuiping; Xu, Zhiqiang (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is pathologically known for the amyloid-β (Aβ) deposition, neurofibrillary tangles, and neuronal loss in the brain. The precursor of brain-derived neurotrophic factor (proBDNF) before proteolysis has opposing functions to its mature form in neuronal survival and neurite growth. However, the role of proBDNF in the pathogenesis of AD remains unclear. OBJECTIVE: To investigate the effects of proBDNF on neurons in vitro, and on learning and memory impairment and brain Aβ production in a transgenic AD mouse model (APPswePS1dE9). METHODS: We here examined the effects of proBDNF on the viability (MTT assay) and neurite growth (morphologic measurement) of the primary neurons in vitro. After the intracerebroventricular injection of adeno-associated virus-proBDNF (AAV-proBDNF), we then investigated the learning and memory impairment (Morris water maze) and Aβ deposition in the brains of the AD mice. RESULTS: The results showed that proBDNF could inhibit neuronal viability and neurite growth in vitro, enhance Aβ levels, and accelerate its deposition in the brain, which was consistent with the learning and memory impairment of AD mice, likely dependent on the membrane receptor of p75NTR. CONCLUSIONS: Our findings suggest that proBDNF may exert a crucially negative effect during AD pathogenesis andprogression.

Protein Phosphorylation is a Key Mechanism in Alzheimer's Disease. - Oliveira, Joana; Costa, Márcio; de Almeida, Maria Soares Cachide; da Cruz E Silva, Odete A B; Henriques, Ana Gabriela (J Alzheimers Dis, 2017)
Altered protein phosphorylation states of several proteins are closely associated with Alzheimer's disease (AD). Among these are the amyloid-β protein precursor (AβPP) and the tau protein. In fact, altered protein phosphorylation states already provide strong biomarkers for AD diagnosis, as is the case with hyperphosphorylated tau. It follows that modulating signaling cascades provides an attractive avenue for exploring novel therapeutic strategies. This review focuses on some of the major protein kinases and protein phosphatases relevant to AD. Of particular relevance, posttranslational modifications dynamically regulate protein activity, subcellular localization, and stability. Protein phosphorylation states can mediate complex formation as well as regulate protein function, and this is important for cellular physiology but can likewise contribute to the development of neuropathological conditions. Furthermore, applying a system approach provides a more comprehensive understanding of the signaling events associated with AD and highlights possible convergence points that may contribute to the different AD pathological hallmarks.

Quantification of Butyrylcholinesterase Activity as a Sensitive and Specific Biomarker of Alzheimer's Disease. - Macdonald, Ian R; Maxwell, Selena P; Reid, George A; Cash, Meghan K; DeBay, Drew R; Darvesh, Sultan (J Alzheimers Dis, 2017)
Amyloid-β (Aβ) plaques are a neuropathological hallmark of Alzheimer's disease (AD); however, a significant number of cognitively normal older adults can also have Aβ plaques. Thus, distinguishing AD from cognitively normal individuals with Aβ plaques (NwAβ) based on Aβ plaque detection is challenging. It has been observed that butyrylcholinesterase (BChE) accumulates in plaques preferentially in AD. Thus, detecting BChE-associated plaques has the potential as an improved AD biomarker. We present Aβ, thioflavin-S, and BChE quantification of 26 postmortem brain tissues; AD (n = 8), NwAβ (n = 6), cognitively normal without plaques (n = 8), and other common dementias including corticobasal degeneration, frontotemporal dementia with tau, dementia with Lewy bodies, and vascular dementia. Pathology burden in the orbitofrontal cortex, entorhinal cortex, amygdala, and hippocampal formation was determined and compared. The predictive value of Aβ and BChE quantification was determined, via receiver-operating characteristic plots, to evaluate their AD diagnostic performance using sensitivity, specificity, and area under curve (AUC) metrics. In general, Aβ and BChE-associated pathology were greater in AD, particularly in the orbitofrontal cortex. In this region, the largest increase (9.3-fold) was in BChE-associated pathology, observed between NwAβ and AD, due to the virtual absence of BChE-associated plaques in NwAβ brains. Furthermore, BChE did not associate with pathology of the other dementias. In this sample, BChE-associated pathology provided better diagnostic performance (AUC = 1.0, sensitivity/specificity = 100% /100%) when compared to Aβ (AUC = 0.98, 100% /85.7%). These findings highlight the predictive value of BChE as a biomarker for AD that could facilitate timely disease diagnosis and management.

Radiological-Pathological Correlation in Alzheimer's Disease: Systematic Review of Antemortem Magnetic Resonance Imaging Findings. - Dallaire-Théroux, Caroline; Callahan, Brandy L; Potvin, Olivier; Saikali, Stéphan; Duchesne, Simon (J Alzheimers Dis, 2017)
BACKGROUND: The standard method of ascertaining Alzheimer's disease (AD) remains postmortem assessment of amyloid plaques and neurofibrillary degeneration. Vascular pathology, Lewy bodies, TDP-43, and hippocampal sclerosis are frequent comorbidities. There is therefore a need for biomarkers that can assess these etiologies and provide a diagnosis in vivo. OBJECTIVE: We conducted a systematic review of published radiological-pathological correlation studies to determine the relationship between antemortem magnetic resonance imaging (MRI) and neuropathological findings in AD. METHODS: We explored PubMed in June-July 2015 using "Alzheimer's disease" and combinations of radiological and pathological terms. After exclusion following screening and full-text assessment of the 552 extracted manuscripts, three others were added from their reference list. In the end, we report results based on 27 articles. RESULTS: Independently of normal age-related brain atrophy, AD pathology is associated with whole-brain and hippocampal atrophy and ventricular expansion as observed on T1-weighted images. Moreover, cerebral amyloid angiopathy and cortical microinfarcts are also related to brain volume loss in AD. Hippocampal sclerosis and TDP-43 are associated with hippocampal and medial temporal lobe atrophy, respectively. Brain volume loss correlates more strongly with tangles than with any other pathological finding. White matter hyperintensities observed on proton density, T2-weighted and FLAIR images are strongly related to vascular pathologies, but are also associated with other histological changes such as gliosis or demyelination. CONCLUSION: Cerebral atrophy and white matter changes in the living brain reflect underlying neuropathology and may be detectable using antemortem MRI. In vivo MRI may therefore be an avenue for AD pathological staging.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study of Oral ELND005 (scyllo-Inositol) in Young Adults with Down Syndrome without Dementia. - Rafii, Michael S; Skotko, Brian G; McDonough, Mary Ellen; Pulsifer, Margaret; Evans, Casey; Doran, Eric; Muranevici, Gabriela; Kesslak, Patrick; Abushakra, Susan; Lott, Ira T (J Alzheimers Dis, 2017)
BACKGROUND: ELND005 (scyllo-Inositol; cyclohexane-1,2,3,4,5,6-hexol) has been evaluated as a potential disease-modifying treatment for Alzheimer's disease (AD). Individuals with Down syndrome (DS) have an increased risk for developing AD dementia. OBJECTIVE: To evaluate the safety and tolerability of ELND005 and to determine its pharmacokinetics (PK) and relationship between PK parameters, safety outcome measures, and exploratory efficacy outcome measures in young adults with DS without dementia. METHODS: This was a prospective, randomized, double-blind, placebo-controlled, parallel-group, three-arm, multicenter Phase II study of the safety and pharmacokinetics of ELND005 administered orally for 4 weeks (ClinicalTrials.gov NCT01791725). Participants who met study eligibility criteria were randomly assigned in a 2 : 1:1 ratio to receive ELND005 at either 250 mg twice daily (BID) or 250 mg once daily (QD) or matching placebo for 4 weeks. RESULTS: There were no apparent treatment group-related trends on cognitive or behavioral measures and there were no SAEs and no deaths in the study. Overall, mean changes from baseline in clinical laboratory parameters, vital sign measurements, electrocardiogram results, and other physical findings were unremarkable. ELND005 accumulation averaged approximately 2-fold with QD dosing, and 3- to 4-fold with BID dosing. CONCLUSION: Overall, treatment of adults with DS with ELND005 at both doses was well tolerated, achieved measurable blood levels and demonstrated no safety findings. Further studies will be needed to test efficacy.

Recovery from Proactive Semantic Interference and MRI Volume: A Replication and Extension Study. - Loewenstein, David A; Curiel, Rosie E; DeKosky, Steven; Rosselli, Monica; Bauer, Russell; Grieg-Custo, Maria; Penate, Ailyn; Li, Chunfei; Lizagarra, Gabriel; Golde, Todd; Adjouadi, Malek; Duara, Ranjan (J Alzheimers Dis, 2017)
BACKGROUND: The rise in incidence of Alzheimer's disease (AD) has led to efforts to advance early detection of the disease during its preclinical stages. To achieve this, the field needs to develop more sensitive cognitive tests that relate to biological markers of disease pathology. Failure to recover from proactive interference (frPSI) is one such cognitive marker that is associated with volumetric reductions in the hippocampus, precuneus, and other AD-prone regions, and to amyloid load in the brain. OBJECTIVE: The current study attempted to replicate and extend our previous findings that frPSI is a sensitive marker of early AD, and related to a unique pattern of volumetric loss in AD prone areas. METHODS: Three different memory measures were examined relative to volumetric loss and cortical thickness among 45 participants with amnestic mild cognitive impairment. RESULTS: frPSI was uniquely associated with reduced volumes in the hippocampus (r = 0.50) precuneus (r = 0.41), and other AD prone regions, replicating previous findings. Strong associations between frPSI and lower entorhinal cortex volumes and cortical thickness (r≥0.60) and precuneus (r = 0.50) were also observed. CONCLUSION: Unique and strong associations between volumetric reductions and frPSI as observed by Loewenstein and colleagues were replicated. Together with cortical thickness findings, these results indicate that frPSI is worthy of further study as a sensitive and early cognitive marker of AD.

Recovery from Proactive Semantic Interference in Mild Cognitive Impairment and Normal Aging: Relationship to Atrophy in Brain Regions Vulnerable to Alzheimer's Disease. - Loewenstein, David A; Curiel, Rosie E; Wright, Clinton; Sun, Xiaoyan; Alperin, Noam; Crocco, Elzabeth; Czaja, Sara J; Raffo, Arlene; Penate, Ailyn; Melo, Jose; Capp, Kimberly; Gamez, Monica; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is growing evidence that proactive semantic interference (PSI) and failure to recover from PSI may represent early features of Alzheimer's disease (AD). OBJECTIVE: This study investigated the association between PSI, recovery from PSI, and reduced MRI volumes in AD signature regions among cognitively impaired and unimpaired older adults. METHODS: Performance on the LASSI-L (a novel test of PSI and recovery from PSI) and regional brain volumetric measures were compared between 38 cognitively normal (CN) elders and 29 older participants with amnestic mild cognitive impairment (MCI). The relationship between MRI measures and performance on the LASSI-L as well as traditional memory and non-memory cognitive measures was also evaluated in both diagnostic groups. RESULTS: Relative to traditional neuropsychological measures, MCI patients' failure to recover from PSI was associated with reduced volumes in the hippocampus (rs = 0.48), precuneus (rs = 0.50); rostral middle frontal lobules (rs = 0.54); inferior temporal lobules (rs = 0.49), superior parietal lobules (rs = 0.47), temporal pole (rs = 0.44), and increased dilatation of the inferior lateral ventricle (rs = -0.49). For CN elders, only increased inferior lateral ventricular size was associated with vulnerability to PSI (rs = -0.49), the failure to recover from PSI (rs = -0.57), and delayed recall on the Hopkins Verbal Learning Test-Revised (rs = -0.48). DISCUSSION: LASSI-L indices eliciting failure to recover from PSI were more highly associated with more MRI regional biomarkers of AD than other traditional cognitive measures. These results as well as recent amyloid imaging studies with otherwise cognitively normal subjects, suggest that recovery from PSI may be a sensitive marker of preclinical AD and deserves further investigation.

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI. - de Eulate, Reyes García; Goñi, Irene; Galiano, Alvaro; Vidorreta, Marta; Recio, Miriam; Riverol, Mario; Zubieta, José L; Fernández-Seara, María A (J Alzheimers Dis, 2017)
There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast velocity mapping by MRI offers a non-invasive means of quantifying the total inflow of blood to the brain. This quantitative parameter could be a sensitive indicator of vascular disease at early stages of AD. In this work, phase contrast MRI was used to evaluate cerebral hemodynamics in patients with subjective memory complaints, amnestic mild cognitive impairment, and mild to moderate AD, and compare them with control subjects. Results showed that blood flow and velocity were decreased in the patients with cognitive dysfunction and the decrease correlated with the degree of cognitive impairment as assessed by means of neuropsychological tests. Total cerebral blood flow measurements were clearly reduced in AD patients, but more importantly appeared to be sensitive enough to distinguish between healthy subjects and those with mild cognitive impairment. A quantitative measurement of total brain blood flow could potentially predict vascular dysfunction and compromised brain perfusion in early stages of AD.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

The Relationship between Markers of Inflammation and Degeneration in the Central Nervous System and the Blood-Brain Barrier Impairment in Alzheimer's Disease. - Muszyński, Paweł; Kulczyńska-Przybik, Agnieszka; Borawska, Renata; Litman-Zawadzka, Ala; Słowik, Agnieszka; Klimkowicz-Mrowiec, Aleksandra; Pera, Joanna; Dziedzic, Tomasz; Mroczko, Barbara (J Alzheimers Dis, 2017)
BACKGROUND: It is known that YKL-40- a marker of glial inflammation, and VILIP-1- a marker of neuronal injury, reflect functional and structural changes in AD brains, although there is limited data concerning their potential influence on blood-brain barrier (BBB) homeostasis. OBJECTIVE: Therefore, the aim of our study was to investigate the relationship between markers of inflammation and degeneration in the central nervous system (CNS) of patients with AD and mild cognitive impairment (MCI) as well as immunological response in CNS and BBB function. METHODS: Cerebrospinal fluid (CSF) concentrations of proteins tested were determined in 45 AD patients, 18 MCI subjects, and 23 non-demented controls using ELISA method. RESULTS: CSF concentrations of YKL-40 were significantly higher in MCI and AD patients, whereas CSF levels of VILIP-1 were statistically higher in the AD group as compared to the subjects without cognitive deficits. Elevated concentrations of YKL-40 correlated significantly with increased albumin quotient and decreased Aβ42/40 ratio in AD patients and with IgG quotient in the total study group. We did not find a relationship between VILIP-1 and immunological parameters reflecting BBB dysfunction and humoral immune response. CONCLUSION: Our findings indicate that YKL-40 may contribute to decreased stability and increased permeability of BBB in AD patients. It is assumed that YKL-40 is implicated in the development of brain barriers, although its precise mechanism of action in the BBB disruption remains unrevealed. Further studies on larger groups of patients are required to confirm our hypothesis.

The Relationship of Brain Amyloid Load and APOE Status to Regional Cortical Thinning and Cognition in the ADNI Cohort. - Li, Chunfei; Loewenstein, David A; Duara, Ranjan; Cabrerizo, Mercedes; Barker, Warren; Adjouadi, Malek (J Alzheimers Dis, 2017)
BACKGROUND: Both amyloid (Aβ) load and APOE4 allele are associated with neurodegenerative changes in Alzheimer's disease (AD) prone regions and with risk for cognitive impairment. OBJECTIVE: To evaluate the unique and independent contribution of APOE4 allele status (E4+∖E4-), Aβ status (Amy+∖Amy-), and combined APOE4 and Aβ status on regional cortical thickness (CoTh) and cognition among participants diagnosed as cognitively normal (CN, n = 251), early mild cognitive impairment (EMCI, n = 207), late mild cognitive impairment (LMCI, n = 196), and mild AD (n = 162) from the ADNI. METHODS: A series of two-way ANCOVAs with post-hoc Tukey HSD tests, controlling independently for Aβ and APOE4 status and age were examined. RESULTS: Among LMCI and AD participants, cortical thinning was widespread in association with Amy+ status, whereas in association with E4+ status only in the inferior temporal and medial orbito-frontal regions. Among CN and EMCI participants, E4+ status, but not Amy+ status, was independently associated with increased CoTh, especially in limbic regions [e.g., in the entorhinal cortex, CoTh was 0.123 mm greater (p = 0.002) among E4+ than E4-participants]. Among CN and EMCI, both E4+ and Amy+ status were independently associated with cognitive impairment, which was greatest among those with combined E4 + and Amy+ status. CONCLUSION: Decreased CoTh is independently associated with Amy+ status in many brain regions, but with E4+ status in very restricted number of brain regions. Among CN and EMCI participants, E4 + status is associated with increased CoTh, in medial and inferior temporal regions, although cognitive impairment at this state is independently associated with Amy+ and E4 + status. These findings imply a unique pathophysiological mechanism for E4 + status in AD and its progression.

The Relationships Between Components of Metabolic Syndrome and Mild Cognitive Impairment Subtypes: A Cross-Sectional Study of Japanese Older Adults. - Bae, Seongryu; Shimada, Hiroyuki; Lee, Sangyoon; Makizako, Hyuma; Lee, Sungchul; Harada, Kazuhiro; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Park, Hyuntae; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: The associations between components of metabolic syndrome (MetS) and mild cognitive impairment (MCI) subtypes remain unclear. OBJECTIVE: The study aim was to identify the prevalence of MetS for MCI subtypes and to investigate sex differences in the association between MetS and MCI subtypes in older Japanese adults. METHODS: The study analyzed data from 3,312 men and women aged 70 years or more. MetS was diagnosed according to International Diabetes Federation criteria. Participants completed cognitive tests and were categorized into normal cognition, amnestic MCI (aMCI), and non-amnestic MCI (naMCI). The associations between MetS and its components and MCI subtypes were analyzed using multiple logistic regression. RESULTS: MetS prevalence was greater in participants with naMCI (men: p = 0.030; women: p = 0.040). Participants with naMCI showed higher odds ratios (OR) of MetS (men: 2.45, 95% confidence intervals (CI): 1.13-5.32; women: OR: 1.94, 95% CI: 1.12-3.39) compared with participants with normal cognition. MetS was not associated with aMCI. Analysis of MetS components showed that raised glucose (OR: 1.62, 95% CI: 1.19-2.22) and reduced high-density lipoprotein cholesterol (OR: 1.97, 95% CI: 1.25-3.12) were associated with naMCI in men. In women, raised blood pressure (OR: 1.42, 95% CI: 1.03-1.94) and raised glucose (OR: 1.32, 95% CI: 1.02-1.71) were associated with naMCI. CONCLUSION: MetS was associated only with naMCI regardless of sex, which suggests etiologic differences in MCI subtypes. We also found sex differences in the relationship between naMCI risk and MetS and its components.

Relationships of Dietary Patterns, Foods, and Micro- and Macronutrients with Alzheimer's Disease and Late-Life Cognitive Disorders: A Systematic Review. - Solfrizzi, Vincenzo; Custodero, Carlo; Lozupone, Madia; Imbimbo, Bruno P; Valiani, Vincenzo; Agosti, Pasquale; Schilardi, Andrea; D'Introno, Alessia; La Montagna, Maddalena; Calvani, Mariapaola; Guerra, Vito; Sardone, Rodolfo; et al. (J Alzheimers Dis, 2017)
In the last decade, the association between diet and cognitive function or dementia has been largely investigated. In the present article, we systematically reviewed observational studies published in the last three years (2014-2016) on the relationship among dietary factors and late-life cognitive disorders at different levels of investigation (i.e., dietary patterns, foods and food-groups, and dietary micro- and macronutrients), and possible underlying mechanisms of the proposed associations. From the reviewed evidence, the National Institute on Aging-Alzheimer's Association guidelines for Alzheimer's disease (AD) and cognitive decline due to AD pathology introduced some evidence suggesting a direct relation between diet and changes in the brain structure and activity. There was also accumulating evidence that combinations of foods and nutrients into certain patterns may act synergistically to provide stronger health effects than those conferred by their individual dietary components. In particular, higher adherence to a Mediterranean-type diet was associated with decreased cognitive decline. Moreover, also other emerging healthy dietary patterns such as the Dietary Approach to Stop Hypertension (DASH) and the Mediterranean-DASH diet Intervention for Neurodegenerative Delay (MIND) diets were associated with slower rates of cognitive decline and significant reduction of AD rate. Furthermore, some foods or food groups traditionally considered harmful such as eggs and red meat have been partially rehabilitated, while there is still a negative correlation of cognitive functions with saturated fatty acids and a protective effect against cognitive decline of elevated fish consumption, high intake of monounsaturated fatty acids and polyunsaturated fatty acids (PUFA), particularly n-3 PUFA.

Relative Incidence of Seizures and Myoclonus in Alzheimer's Disease, Dementia with Lewy Bodies, and Frontotemporal Dementia. - Beagle, Alexander J; Darwish, Sonja M; Ranasinghe, Kamalini G; La, Alice L; Karageorgiou, Elissaios; Vossel, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: Patients with Alzheimer's disease (AD) are more prone to seizures and myoclonus, but relative risk of these symptoms among other dementia types is unknown. OBJECTIVE: To determine incidence of seizures and myoclonus in the three most common neurodegenerative dementias: AD, dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD). METHODS: Our institution's medical records were reviewed for new-onset unprovoked seizures and myoclonus in patients meeting criteria for AD (n = 1,320), DLB (n = 178), and FTD (n = 348). Cumulative probabilities of developing seizures and myoclonus were compared between diagnostic groups, whereas age-stratified incidence rates were determined relative to control populations. RESULTS: The cumulative probability of developing seizures after disease onset was 11.5% overall, highest in AD (13.4%) and DLB (14.7%) and lowest in FTD (3.0%). The cumulative probability of developing myoclonus was 42.1% overall, highest in DLB (58.1%). The seizure incidence rates, relative to control populations, were nearly 10-fold in AD and DLB, and 6-fold in FTD. Relative seizure rates increased with earlier age-at-onset in AD (age <50, 127-fold; 50-69, 21-fold; 70+, 2-fold) and FTD (age <50, 53-fold; 50-69, 9-fold), and relative myoclonus rates increased with earlier age-at-onset in all groups. Seizures began an average of 3.9 years after the onset of cognitive or motor decline, and myoclonus began 5.4 years after onset. CONCLUSIONS: Seizures and myoclonus occur with greater incidence in patients with AD, DLB, and FTD than in the general population, but rates vary with diagnosis, suggesting varied pathomechanisms of network hyperexcitability. Patients often experience these symptoms early in disease, suggesting hyperexcitability could be an important target for interventions.

Retrograde Amnesia for Episodic and Semantic Memories in Amnestic Mild Cognitive Impairment. - De Simone, Maria Stefania; Fadda, Lucia; Perri, Roberta; De Tollis, Massimo; Aloisi, Marta; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (J Alzheimers Dis, 2017)
Retrograde amnesia (RA), which includes loss of memory for past personal events (autobiographical RA) and for acquired knowledge (semantic RA), has been largely documented in patients with amnestic mild cognitive impairment (aMCI). However, previous studies have produced controversial results particularly concerning the temporal extent of memory impairment. Here we investigated whether, with the onset of hippocampal pathology, age of memory acquisition and retrieval frequency play different roles in modulating the progressive loss of semantic and episodic contents of retrograde memory respectively. For this purpose, aMCI patients and healthy controls were tested for the ability to recall semantic and autobiographical information related to famous public events as a function of both age of acquisition and retrieval frequency. In aMCI patients, we found that the impairment in recollecting past personal incidents was modulated by the combined action of memory age and retrieval frequency, because older and more frequently retrieved episodes are less susceptible to loss than more recent and less frequently retrieved ones. On the other side, we found that the loss of semantic information depended only on memory age, because the remoteness of the trace allows for better preservation of the memory. Our results provide evidence that the loss of the two components of retrograde memory is regulated by different mechanisms. This supports the view that diverse neural mechanisms are involved in episodic and semantic memory trace storage and retrieval, as postulated by the Multiple Trace Theory.

Rhamnolipids, Microbial Virulence Factors, in Alzheimer's Disease. - Andreadou, Eleni; Pantazaki, Anastasia A; Daniilidou, Makrina; Tsolaki, Magda (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) has been attributed to chronic bacterial infections. The recognition of human microbiota as a substantial contributor to health and disease is relatively recent and growing. During evolution, mammals live in a symbiotic state with myriads of microorganisms that survive at a diversity of tissue micro-surroundings. Microbes produce a plethora of secretory products [amyloids, lipopolysaccharides, virulence factors rhamnolipids (RLs), toxins, and a great number of neuroactive compounds]. The contribution of infectious microbial components to the pathophysiology of the human central nervous system including AD is considered potentially substantial, but the involvement of the RLs has never been reported. Here, RLs were isolated from serum and identified through various conventional methods including the colorimetric orcinol method, thin-layer chromatography, attenuated total reflection Fourier transform infrared (ATR-FTIR), and dot blot using antibodies against RLs. Dot blot demonstrated elevated RL levels in sera of AD patients compared to controls (p = 0.014). Moreover, ELISA showed similarly elevated RL levels in cerebrospinal fluid of both AD (0.188 versus 0.080) (p = 0.04) and mild cognitive impairment (0.188 versus 0.129) (p = 0.088) patients compared to healthy, and are well-correlated with the AD stages severity assessed using the Mini-Mental State Examination. These results provide conclusive evidence for the newly-reported implication of RLs in AD, adding it to the list of bacterial components, opening new avenues for AD investigation. Moreover, they strengthen and vindicate the divergence of research toward the exploration of bacterial involvement in AD generation and progression.

Risk Factors, Neuroanatomical Correlates, and Outcome of Neuropsychiatric Symptoms in Alzheimer's Disease. - Poulin, Stéphane P; Bergeron, David; Dickerson, Bradford C (J Alzheimers Dis, 2017)
BACKGROUND: An integrative model of neuropsychiatric symptoms (NPS) in Alzheimer's disease (AD) is lacking. OBJECTIVE: In this study, we investigated the risk factors, anatomy, biology, and outcomes of NPS in AD. METHODS: 181 subjects were included from the Alzheimer's Disease Neuroimaging Study (ADNI). NPS were assessed with the Neuropsychiatric Inventory Questionnaire at baseline and 6 months. NPI >3 was used as a threshold for NPS positivity. Three NPS courses were characterized: 1) minimal/absent (negative at 0 and 6 months, n = 77); 2) fluctuating (positive only at one time point, n = 53); 3) persistent (positive at both time points, n = 51). We examined the association between NPS course and family history of dementia, personal history of psychiatric disorders, cerebrospinal fluid biomarkers, atrophy patterns, as well as longitudinal cognitive and functional measures at 12 and 24 months (MMSE, CDR-SOB, FAQ). RESULTS: AD subjects with absent, fluctuating, or persistent NPS had similar CSF amyloid-β and tau levels. AD subjects with minimal/absent NPS had less personal history of psychiatric disorders (35%) than those with fluctuating (57%; p = 0.015) or persistent NPS (47%, not significant). At 24 months, AD subjects with persistent NPS had worse cognitive (MMSE; p = 0.05) and functional (CDR-SOB; p = 0.016) outcomes. Dorsolateral prefrontal atrophy was seen in persistent NPS, but not in fluctuating NPS. CONCLUSIONS: Our results suggest that individuals with personal history of psychiatric disorders might be more vulnerable to develop NPS throughout the course of AD. The worst cognitive and functional outcomes associated with NPS in AD underscores the importance of monitoring NPS early in the disease course.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

The Role of Single-Subject Brain Metabolic Patterns in the Early Differential Diagnosis of Primary Progressive Aphasias and in Prediction of Progression to Dementia. - Cerami, Chiara; Dodich, Alessandra; Greco, Lucia; Iannaccone, Sandro; Magnani, Giuseppe; Marcone, Alessandra; Pelagallo, Elisabetta; Santangelo, Roberto; Cappa, Stefano F; Perani, Daniela (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: Primary progressive aphasia (PPA) is a clinical syndrome due to different neurodegenerative conditions in which an accurate early diagnosis needs to be supported by a reliable diagnostic tool at the individual level. In this study, we investigated in PPA the FDG-PET brain metabolic patterns at the single-subject level, in order to assess the case-to-case variability and its relationship with clinical-neuropsychological findings. MATERIAL AND METHODS: 55 patients (i.e., 11 semantic variant/sv-PPA, 19 non fluent variant/nfv-PPA, 17 logopenic variant/lv-PPA, 3 slowly progressive anarthria/SPA, and 5 mixed PPA/m-PPA) were included. Clinical-neuropsychological information and FDG-PET data were acquired at baseline. A follow-up of 27.4±12.55 months evaluated the clinical progression. Brain metabolism was analyzed using an optimized and validated voxel-based SPM method at the single-subject level. RESULTS: FDG-PET voxel-wise metabolic assessment revealed specific metabolic signatures characterizing each PPA variant at the individual level, reflecting the underlying neurodegeneration in language networks. Notably, additional dysfunctional patterns predicted clinical progression to specific dementia conditions. In the case of nfv-PPA, a metabolic pattern characterized by involvement of parietal, subcortical and brainstem structures predicted progression to a corticobasal degeneration syndrome or to progressive supranuclear palsy. lv-PPA and sv-PPA cases who progressed to Alzheimer's disease and frontotemporal dementia at the follow-up presented with extended bilateral patterns at baseline. DISCUSSION: Our results indicate that FDG-PET voxel-wise imaging is a valid biomarker for the early differential diagnosis of PPAs and for the prediction of progression to specific dementia condition. This study supports the use of FDG-PET imaging quantitative assessment in clinical settings for a better characterization of PPA individuals and prognostic definition of possible endo-phenotypes.

Selenoprotein S Reduces Endoplasmic Reticulum Stress-Induced Phosphorylation of Tau: Potential Role in Selenate Mitigation of Tau Pathology. - Rueli, Rachel H L H; Torres, Daniel J; Dewing, Andrea S T; Kiyohara, Arlene C; Barayuga, Stephanie M; Bellinger, Miyoko T; Uyehara-Lock, Jane H; White, Lon R; Moreira, Paula I; Berry, Marla J; Perry, George; Bellinger, Frederick P (J Alzheimers Dis, 2017)
Previous studies demonstrated that selenium in the form of sodium selenate reduces neurofibrillary tangle formation in Alzheimer's disease models. Hyperphosphorylation of tau, which leads to formation of neurofibrillary tangles in Alzheimer's disease, is increased by endoplasmic reticulum (ER) stress. Selenoprotein S (SelS) is part of an ER membrane complex that removes misfolded proteins from the ER as a means to reduce ER stress. Selenate, as with other forms of selenium, will increase selenoprotein expression. We therefore proposed that increased SelS expression by selenate would contribute to the beneficial actions of selenate in Alzheimer's disease. SelS expression increased with ER stress and decreased under conditions of elevated glucose concentrations in the SH-SY5Y neuronal cell line. Reducing expression of SelS with siRNA promoted cell death in response to ER stress. Selenate increased SelS expression, which significantly correlated with decreased tau phosphorylation. Restricting SelS expression during ER stress conditions increased tau phosphorylation, and also promoted aggregation of phosphorylated tau in neurites and soma. In human postmortem brain, SelS expression coincided with neurofibrillary tangles, but not with amyloid-β plaques. These results indicate that selenate can alter phosphorylation of tau by increasing expression of SelS in Alzheimer's disease and potentially other neurodegenerative disorders.

Sembragiline in Moderate Alzheimer's Disease: Results of a Randomized, Double-Blind, Placebo-Controlled Phase II Trial (MAyflOwer RoAD). - Nave, Stephane; Doody, Rachelle S; Boada, Merce; Grimmer, Timo; Savola, Juha-Matti; Delmar, Paul; Pauly-Evers, Meike; Nikolcheva, Tania; Czech, Christian; Borroni, Edilio; Ricci, Benedicte; Dukart, Juergen; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sembragiline is a potent, selective, long-acting, and reversible MAO-B inhibitor developed as a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To evaluate the safety, tolerability, and efficacy of sembragiline in patients with moderate AD. METHODS: In this Phase II study (NCT01677754), 542 patients with moderate dementia (MMSE 13-20) on background acetylcholinesterase inhibitors with/without memantine were randomized (1:1:1) to sembragiline 1 mg, 5 mg, or placebo once daily orally for 52 weeks. RESULTS: No differences between treated groups and placebo in adverse events or in study completion. The primary endpoint, change from baseline in ADAS-Cog11, was not met. At Week 52, the difference between sembragiline and placebo in ADAS-Cog11 change from baseline was - 0.15 (p = 0.865) and 0.90 (p = 0.312) for 1 and 5 mg groups, respectively. Relative to placebo at Week 52 (but not at prior assessment times), the 1 mg and 5 mg sembragiline groups showed differences in ADCS-ADL of 2.64 (p = 0.051) and 1.89 (p = 0.160), respectively. A treatment effect in neuropsychiatric symptoms (as assessed by the difference between sembragiline and placebo on BEHAVE-AD-FW) was also seen at Week 52 only: - 2.80 (p = 0.014; 1 mg) and - 2.64 (p = 0.019; 5 mg), respectively. A post hoc subgroup analysis revealed greater treatment effects on behavior and functioning in patients with more severe baseline behavioral symptoms (above the median). CONCLUSIONS: This study showed that sembragiline was well-tolerated in patients with moderate AD. The study missed its primary and secondary endpoints. Post hoc analyses suggested potential effect on neuropsychiatric symptoms and functioning in more behaviorally impaired study population at baseline.

Sensing of Alzheimer's Disease and Multiple Sclerosis Using Nano-Bio Interfaces. - Hajipour, Mohammad Javad; Ghasemi, Forough; Aghaverdi, Haniyeh; Raoufi, Mohammad; Linne, Uwe; Atyabi, Fatemeh; Nabipour, Iraj; Azhdarzadeh, Morteza; Derakhshankhah, Hossein; Lotfabadi, Alireza; Bargahi, Afshar; Alekhamis, Zahra; et al. (J Alzheimers Dis, 2017)
It is well understood that patients with different diseases may have a variety of specific proteins (e.g., type, amount, and configuration) in their plasmas. When nanoparticles (NPs) are exposed to these plasmas, the resulting coronas may incorporate some of the disease-specific proteins. Using gold (Au) NPs with different surface properties and corona composition, we have developed a colorimetric sensor array for the discrimination and detection of two neurodegenerative diseases, Alzheimer's disease (AD) and multiple sclerosis (MS). Applying a variety of techniques, including UV-visible spectra, array response analyses and liquid chromatography-tandem mass spectrometry, we found the corona-NP complexes, obtained from different human serums, had distinct protein composition, including some specific proteins that are known as AD and MS biomarkers. The array responses, analyzed by chemometrics and statistical methods, demonstrate promising capabilities of the sensor to unambiguously identify and discriminate AD and MS. The developed sensor array might enable a simple, inexpensive and rapid detection/discrimination of neurodegenerative diseases.

Serum SHBG Levels are not Associated with Longitudinal Cognitive Decline in Mild Cognitive Impairment. - Lin, Katherine Amy; Rundel, Colin; Doraiswamy, P Murali (J Alzheimers Dis, 2017)
BACKGROUND: Prior studies have noted gender differences in cognition, imaging, and pathological markers in mild cognitive impairment (MCI) subjects. Sex hormone-binding globulin (SHBG), a major controlling factor in the proportion of bioavailable versus bound testosterone and estrogen, has been proposed to contribute to links between hormones and dementia, but has not yet been investigated fully in a prospective biomarker trial. OBJECTIVE: This study examined whether, among subjects with MCI, SHBG levels predict future rate of cognitive decline. METHODS: We examine the effect of gender on cognitive decline and factors modulating potential gender differences in 378 MCI subjects (134 females, 244 males) in the Alzheimer's Disease Neuroimaging Initiative-1 (ADNI-1), followed for up to 8 years (mean ± SE, 4.0 ± 0.1 years). Cognition was assessed using the ADAS-cog-11. Multivariate models examined the effect of gender covarying for age, ApoE4, baseline cognition, years of education, and SHBG levels. RESULTS: MCI women declined significantly faster than men in cognition over the follow up period. Baseline SHBG levels differed significantly between men and women (p < 0.0001), and by age in men, but not by ApoE4 status. In the multivariate models, SHBG levels were not a significant predictor of cognitive decline in men or women but ApoE4 status, baseline cognition, years of education, and female gender were. CONCLUSION: SHBG levels did not influence the rate of cognitive decline in MCI. Further studies to confirm these findings and uncover other potential mechanisms of gender differences in the risk for AD may be warranted.

Severity of Depression Impacts Imminent Conversion from Mild Cognitive Impairment to Alzheimer's Disease. - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Fleischhacker, Walter Wolfgang; Blasko, Imrich; Deisenhammer, Eberhard A (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) has been suggested to represent a prodromal stage of dementia and to confer a high risk for conversion to dementia Alzheimer's type (DAT). OBJECTIVES: In this study, we examined the predictive value of depressive symptoms and neuropsychological variables on conversion of MCI to DAT. METHODS: Neuropsychological and clinical follow-up data of 260 MCI patients seen at the Psychiatric Memory Clinic of the Medical University of Innsbruck between 2005 and 2015 were analyzed retrospectively. Depression was assessed using the Geriatric Depression Scale (GDS). Potential predictors of conversion from MCI to DAT were analyzed by logistic regression analyses and additional survival-analytic methods. RESULTS: Of the 260 patients (mean age 71.5±7.7 years), 83 (32%) converted to DAT within a mean follow-up time of 3.2±2.2 years and estimated one-year conversion rate of 10.1%. The univariate analysis showed with few exceptions (gender, use of antidepressants, low GDS score) group differences at baseline in patients converted to DAT compared to stable MCI patients. Logistic regression analysis as well as survival analysis revealed moderate to severe depression together with higher age and specific cognitive deficits as predictors of conversion from MCI to DAT. CONCLUSION: Our results support the predictive value of different neuropsychological measures on the progression of DAT. In addition, we found a strong negative influence of depression on conversion to DAT in MCI patients. These results emphasize the importance of assessing depressive symptoms in the early stages of DAT when evaluating the conversion from MCI to DAT.

Sex Difference in Aerobic Exercise Efficacy to Improve Cognition in Older Adults with Vascular Cognitive Impairment: Secondary Analysis of a Randomized Controlled Trial. - Barha, Cindy K; Hsiung, Ging-Yuek R; Best, John R; Davis, Jennifer C; Eng, Janice J; Jacova, Claudia; Lee, Philip E; Munkacsy, Michelle; Cheung, Winnie; Liu-Ambrose, Teresa (J Alzheimers Dis, 2017)
Aerobic training (AT) is a promising, non-pharmacological intervention to mitigate the deleterious effects of aging and disease on brain health. However, a large amount of variation exists in its efficacy. This is a secondary analysis of a randomized controlled trial of AT in 71 older adults with subcortical ischemic vascular cognitive impairment (NCT01027858). Specifically, we investigated: 1) whether sex moderates the relationship between AT and executive functions, and 2) the role of brain derived neurotrophic factor (BDNF) and gains in functional fitness capacity. Older adults were randomly assigned to either 6-month, thrice-weekly AT or to usual care plus education (CON). At baseline, trial completion, and 6-month follow-up, executive functions were assessed with the Trail Making Test (A & B), verbal digits forward and backward test, and the Stroop Test. Functional fitness capacity was assessed with the 6-Minute Walk Test. Compared with CON, AT significantly improved Trail Making Test performance in females but not males, an effect that was retained at follow-up. AT significantly increased BDNF levels in females but decreased levels in males. On the other hand, AT led to significant gains in functional fitness capacity in males only. This study provides evidence that sex differences exist in AT efficacy on brain health as well as in the biological mechanisms subserving AT.

Sex Differences in the Psychophysical Response to Contact Heat in Moderate Cognitive Impairment Alzheimer's Disease: A Cross-Sectional Brief Report. - Cowan, Ronald L; Beach, Paul A; Atalla, Sebastian W; Dietrich, Mary S; Bruehl, Stephen P; Deng, Jie; Wang, Jinjiao; Newhouse, Paul A; Gore, John C; Monroe, Todd B (J Alzheimers Dis, 2017)
BACKGROUND: People with Alzheimer's disease (AD) report pain less frequently and receive less pain medication than people without AD. Recent studies have begun to elucidate how pain may be altered in those with AD. However, potential sex differences in pain responsiveness have never been explored in these patients. It is unclear whether sex differences found in prior studies of healthy young and older individuals extend to people with AD. OBJECTIVE: The purpose of this study was to examine sex differences in the psychophysical response to experimental thermal pain in people with AD. METHODS: Cross-sectional analysis of 14 male and 14 female age-matched (≥65 years of age, median = 74) and AD severity-matched (Mini-Mental State Exam score <24, median = 16) communicative people who completed thermal psychophysics. RESULTS: There was a statistically significant main effect of sex for both temperature and unpleasantness ratings that persisted after controlling for average and current pain (mixed-effects general liner model: temperature: p = 0.004, unpleasantness: p < 0.001). Females reported sensing mild pain and moderate pain percepts at markedly lower temperatures than did males (mild: Cohen's d = 0.72, p = 0.051, moderate: Cohen's d = 0.80, p = 0.036). By contrast, males rated mild and moderate thermal pain stimuli as more unpleasant than did females (mild: Cohen's d = 0.80, p = 0.072, moderate: Cohen's d = 1.32, p = 0.006). There were no statistically significant correlations of temperature with perceived unpleasantness for mild or moderate pain (rs = 0.29 and rs = 0.20 respectively, p > 0.05). CONCLUSIONS: Results suggest experimental pain-related sex differences persist in older adults with AD in a different manner than those previously demonstrated in cognitively intact older adults. These findings could potentially aid in developing targeted pain management approaches in this vulnerable population. Further studies are warranted to replicate the findings from this pilot work.

Sex Impact on Tau-Aggregation and Postsynaptic Protein Levels in the P301L Mouse Model of Tauopathy. - Buccarello, Lucia; Grignaschi, Giuliano; Castaldo, Anna Maria; Di Giancamillo, Alessia; Domeneghini, Cinzia; Melcangi, Roberto Cosimo; Borsello, Tiziana (J Alzheimers Dis, 2017)
P301L transgenic (tg) mice well mimic features of human tauopathies and provide a good model for investigating the role of tau in neurodegenerative events. We here analyzed the possible interactions among phosphorylation of tau (p-tau), spine injury, neuronal death, and sex in the P301L mouse model of tauopathy. When compared to control mice (ctr), P301L transgenic mice (tg) presented a lower body weight, reduced survival rate, hyperphosphorylated tau, spine injury, and neuronal loss in both cerebral cortex and hippocampus at 15 months of age. Importantly, we found that pathological features were more pronounced in female than male tg mice. Recent reports underline that tau may be localized within both pre- and post-synaptic compartments, suggesting that it may possibly induce or contribute to synaptic dysfunction. Therefore, we focused our attention on tau localization at dendritic spines. We detected high levels of both tau and p-tau in dendritic spine of P301L transgenic mice. In addition, p-tau correlated with a significant reduction of post-synaptic markers, such as GluN2A, GluN2B, GluA1, GluA2, Drebrin, and PSD-95, in P301L mice. The p-tau levels are higher in female than in male mice, and the increased p-tau was consistent with a proportional decrease in the post-synaptic marker levels analyzed. The P301L-tg females showed a more severe synaptopathy compared to males. Future investigations on the postsynaptic role of p-tau will be necessary to understand its toxic effects and provide insights into new therapeutic targets for maintaining spine integrity, highlighting the importance of tau toxicity as well as the impact of sex on tau-pathology.

Sildenafil Improves Vascular and Metabolic Function in Patients with Alzheimer's Disease. - Sheng, Min; Lu, Hanzhang; Liu, Peiying; Li, Yang; Ravi, Harshan; Peng, Shin-Lei; Diaz-Arrastia, Ramon; Devous, Michael D; Womack, Kyle B (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the leading cause of degenerative dementia in the aging population. Patients with AD have alterations in cerebral hemodynamic function including reduced cerebral blood flow (CBF) and cerebral metabolic rate. Therefore, improved cerebrovascular function may be an attractive goal for pharmaceutical intervention in AD. OBJECTIVE: We wished to observe the acute effects of sildenafil on cerebrovascular function and brain metabolism in patients with AD. METHODS: We used several novel non-invasive MRI techniques to investigate the alterations of CBF, cerebral metabolic rate of oxygen (CMRO2), and cerebrovascular reactivity (CVR) after a single dose of sildenafil administration in order to assess its physiological effects in patients with AD. CBF, CMRO2, and CVR measurements using MRI were performed before and one hour after the oral administration of 50 mg sildenafil. Baseline Montreal Cognitive Assessment score was also obtained. RESULTS: Complete CBF and CMRO2 data were obtained in twelve patients. Complete CVR data were obtained in eight patients. Global CBF and CMRO2 significantly increased (p = 0.03, p = 0.05, respectively) following sildenafil administration. Voxel-wise analyses of CBF maps showed that increased CBF was most pronounced in the bilateral medial temporal lobes. CVR significantly decreased after administration of sildenafil. CONCLUSION: Our data suggest that a single dose of sildenafil improves cerebral hemodynamic function and increases cerebral oxygen metabolism in patients with AD.

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Social Cognition in the Frontal Variant of Alzheimer's Disease: A Case Study. - Duclos, Harmony; de la Sayette, Vincent; Bonnet, Anne-Laure; Viard, Armelle; Eustache, Francis; Desgranges, Béatrice; Laisney, Mickaël (J Alzheimers Dis, 2017)
Although frontal presentations of Alzheimer's disease (fv-AD) have already been described in the literature, we still know little about patients' social cognitive abilities, especially their theory of mind (ToM). We report the case of FT, a 61-year-old woman who was diagnosed with fv-AD. Two assessments of social cognition, using a false-belief task, the Reading the Mind in the Eyes test, and a task probing knowledge of social norms, were performed one year apart. FT exhibited cognitive ToM and social knowledge deficits from the onset. Affective ToM was initially preserved, but deteriorated as the disease progressed.

Spatial Patterns of Longitudinal Gray Matter Change as Predictors of Concurrent Cognitive Decline in Amyloid Positive Healthy Subjects. - Araque Caballero, Miguel Ángel; Klöppel, Stefan; Dichgans, Martin; Ewers, Michael (J Alzheimers Dis, 2017)
A substantial proportion of cognitively healthy elders (HC) show abnormally high amyloid-β (Aβ) deposition, a major pathology of Alzheimer's disease (AD). These subjects are at increased risk of Alzheimer's disease (AD) dementia, and biomarkers are needed to predict their cognitive deterioration. Here we used relevance vector regression (RVR), a pattern-recognition method, to predict concurrent cognitive decline on the basis of longitudinal gray matter (GM) changes, within two a priori, meta-analytically defined functional networks subserving episodic memory and executive function. Ninety-six HC subjects were assessed annually for three years with structural MRI and cognitive tests within the Alzheimer's Disease Neuroimaging Initiative. Presence of abnormal biomarker values of Aβ (Aβ+) were determined with cerebrospinal fluid and amyloid-PET (HC-Aβ+, n=30; with n=66 for normal HC-Aβ-). Using leave-one-out cross-validation, we found that in HC-Aβ+ patterns of GM changes within both networks predicted decline in episodic memory (r=0.61, p<0.001; r=0.40, p=0.03), but not executive function. In HC-Aβ-, GM changes within the executive function network predicted decline in executive function (r=0.44, p<0.001). Previously established region-of-interest (ROI)-based predictors such as changes in hippocampal volume, within an AD-signature multi-ROI, or total GM volume were not predictive of cognitive decline in any group or cognitive domain. RVR analyses unrestricted to the a priori networks yielded compatible results with the restricted case. In conclusion, RVR-derived patterns of subtle cortical GM changes are biomarker candidates of concurrent cognitive decline in aging and subjects at risk for AD.

Specific Verbal Memory Measures May Distinguish Alzheimer's Disease from Dementia with Lewy Bodies. - Bussè, Cinzia; Anselmi, Pasquale; Pompanin, Sara; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Di Bernardo, Gian Antonio; Semenza, Carlo; Caffarra, Paolo; Cagnin, Annachiara (J Alzheimers Dis, 2017)
BACKGROUND: Standard measures of commonly used memory tests may not be appropriate to distinguish different neurodegenerative diseases affecting memory. OBJECTIVE: To study whether specific measures of verbal memory obtained with the Rey Auditory Verbal Learning test (RAVLT) could help distinguish dementia with Lewy bodies (DLB) from Alzheimer's disease (AD). METHODS: Twenty-nine DLB and 32 AD patients participated in the study and were followed longitudinally for 3 years until the diagnosis was confirmed according to standard clinical criteria. Twenty-eight healthy elderly subjects served as controls. The following verbal memory measures were evaluated: verbal learning (VL), verbal forgetting (VF), percentage of verbal forgetting (VF%), and serial position effects of the immediate recall performance. RESULTS: DLB and AD groups have comparable performances at the RAVLT immediate and delayed recall tasks. However, VL was higher in DLB than AD while VF% was greater in AD. With a VF% cut-off ≥75%, AD and DLB patients were differently distributed, with 58% of AD versus 21% of DLB above this cut-off. The recency effect was significant higher in AD than DLB. DISCUSSION: DLB patients had a better performance in VL than AD, but worse VF and recency effect. These specific measures of verbal memory could be used as cognitive markers in the differential diagnosis between these two conditions.

Sphingolipid-Enriched Extracellular Vesicles and Alzheimer's Disease: A Decade of Research. - Dinkins, Michael B; Wang, Guanghu; Bieberich, Erhard (J Alzheimers Dis, 2017)
Extracellular vesicles (EVs), particularly exosomes, have emerged in the last 10 years as a new player in the progression of Alzheimer's disease (AD) with high potential for being useful as a diagnostic and treatment tool. Exosomes and other EVs are enriched with the sphingolipid ceramide as well as other more complex glycosphingolipids such as gangliosides. At least a subpopulation of exosomes requires neutral sphingomyelinase activity for their biogenesis and secretion. As ceramide is often elevated in AD, exosome secretion may be affected as well. Here, we review the available data showing that exosomes regulate the aggregation and clearance of amyloid-beta (Aβ) and discuss the differences in data from laboratories regarding Aβ binding, induction of aggregation, and glial clearance. We also summarize available data on the role of exosomes in extracellular tau propagation, AD-related exosomal mRNA/miRNA cargo, and the use of exosomes as biomarker and gene therapy vehicles for diagnosis and potential treatment.

Sporadic Cases with Novel Mutations and Pedigree in Hereditary Leukoencephalopathy with Axonal Spheroids. - Wu, Liyong; Liu, Jia; Sha, Longze; Wang, Xianling; Li, Jieying; Dong, Jing; Jia, Jianping (J Alzheimers Dis, 2017)
Hereditary diffuse leukoencephalopathy with spheroids (HDLS) is an autosomal dominant hereditary disease, featured by cerebral white matter degeneration with demyelination and axonal spheroids. We collected three gene-confirmed HDLS cases in our neurodegenerative clinic. Two HDLS cases were sporadic with novel mutations, while another case had a family history with previously described mutations. All three cases suffered memory problems with white matter lesions and pyramid signs. No obvious clinical differences were observed between sporadic and familial HDLS cases. Distinct features, such as subcortical calcification in brain computed tomography and asymmetric abnormal MRI signal along the pyramid tracts throughout brainstem and spinal cord (cervical, thoracic, and lumbar segments), were observed in one sporadic case with novel mutation. Therefore, the interactions of genotype-phenotype still need to be further investigated.

Successful Object Encoding Induces Increased Directed Connectivity in Presymptomatic Early-Onset Alzheimer's Disease. - Ochoa, John Fredy; Alonso, Joan Francesc; Duque, Jon Edinson; Tobón, Carlos Andrés; Mañanas, Miguel Angel; Lopera, Francisco; Hernández, Alher Mauricio (J Alzheimers Dis, 2017)
BACKGROUND: Recent studies report increases in neural activity in brain regions critical to episodic memory at preclinical stages of Alzheimer's disease (AD). Although electroencephalography (EEG) is widely used in AD studies, given its non-invasiveness and low cost, there is a need to translate the findings in other neuroimaging methods to EEG. OBJECTIVE: To examine how the previous findings using functional magnetic resonance imaging (fMRI) at preclinical stage in presenilin-1 E280A mutation carriers could be assessed and extended, using EEG and a connectivity approach. METHODS: EEG signals were acquired during resting and encoding in 30 normal cognitive young subjects, from an autosomal dominant early-onset AD kindred from Antioquia, Colombia. Regions of the brain previously reported as hyperactive were used for connectivity analysis. RESULTS: Mutation carriers exhibited increasing connectivity at analyzed regions. Among them, the right precuneus exhibited the highest changes in connectivity. CONCLUSION: Increased connectivity in hyperactive cerebral regions is seen in individuals, genetically-determined to develop AD, at preclinical stage. The use of a connectivity approach and a widely available neuroimaging technique opens the possibility to increase the use of EEG in early detection of preclinical AD.

Synthesis, Radiosynthesis, and Preliminary in vitro and in vivo Evaluation of the Fluorinated Ceramide Trafficking Inhibitor (HPA-12) for Brain Applications. - Crivelli, Simone M; Paulus, Andreas; Markus, Jozef; Bauwens, Matthias; Berkes, Dusan; De Vries, Helga E; Mulder, Monique T; Walter, Jochen; Mottaghy, Felix M; Losen, Mario; Martinez-Martinez, Pilar (J Alzheimers Dis, 2017)
Ceramide levels are increased in blood and brain tissue of Alzheimer's disease (AD) patients. Since the ceramide transporter protein (CERT) is the only known protein able to mediate non-vesicular transfer of ceramide between organelle membranes, the modulation of CERT function may impact on ceramide accumulation. The competitive CERT inhibitor N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl) dodecanamide (HPA-12) interferes with ceramide trafficking. To understand the role of ceramide/CERT in AD, HPA-12 can be a useful tool to modulate ceramide trafficking. Here we first report the synthesis and in vitro properties of HPA-12 radiolabeled with fluorine-18 and present preliminary in vitro and in vivo positron emission tomography (PET) imaging and biodistribution data. In vitro results demonstrated that the fluorination did not alter the biological properties of HPA-12 since the [fluorine-19]HPA-12, interferes with 5-DMB-ceramide trafficking in HeLa cells. Radiolabeled HPA-12, [fluorine-18]HPA-12, was obtained with a radiochemical yield of 90% and a specific activity of 73 MBq/μmol. PET imaging on wild-type mice showed hepatobiliary clearance and a brain uptake on the order of 0.3 standard uptake value (SUV) one hour post injection. Furthermore, the biodistribution data showed that after removal of the blood by intracardial perfusion, radioactivity was still measurable in the brain demonstrating that the [fluorine-18]HPA-12 crosses the blood brain barrier and is retained in the brain.

A Systematic Review of Longitudinal Studies Which Measure Alzheimer's Disease Biomarkers. - Lawrence, Emma; Vegvari, Carolin; Ower, Alison; Hadjichrysanthou, Christoforos; De Wolf, Frank; Anderson, Roy M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive and fatal neurodegenerative disease, with no effective treatment or cure. A gold standard therapy would be treatment to slow or halt disease progression; however, knowledge of causation in the early stages of AD is very limited. In order to determine effective endpoints for possible therapies, a number of quantitative surrogate markers of disease progression have been suggested, including biochemical and imaging biomarkers. The dynamics of these various surrogate markers over time, particularly in relation to disease development, are, however, not well characterized. We reviewed the literature for studies that measured cerebrospinal fluid or plasma amyloid-β and tau, or took magnetic resonance image or fluorodeoxyglucose/Pittsburgh compound B-positron electron tomography scans, in longitudinal cohort studies. We summarized the properties of the major cohort studies in various countries, commonly used diagnosis methods and study designs. We have concluded that additional studies with repeat measures over time in a representative population cohort are needed to address the gap in knowledge of AD progression. Based on our analysis, we suggest directions in which research could move in order to advance our understanding of this complex disease, including repeat biomarker measurements, standardization and increased sample sizes.

Targeted Metabolomic Analysis of Soluble Lysates from Platelets of Patients with Mild Cognitive Impairment and Alzheimer's Disease Compared to Healthy Controls: Is PC aeC40:4 a Promising Diagnostic Tool? - Oberacher, Herbert; Arnhard, Kathrin; Linhart, Caroline; Diwo, Angela; Marksteiner, Josef; Humpel, Christian (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder of the central nervous system. The use of biological fluids in AD diagnosis remains limited to the analysis of specific protein biomarkers in cerebrospinal fluid. However, metabolomic analysis has recently revealed several metabolites in plasma, especially phosphatidylcholines (PC), as putative biomarkers specific for AD. Following on previous reports of platelet abnormalities in AD, we hypothesized that platelets metabolites released in plasma may offer new biomarkers in AD. The aim of the present study was to apply targeted metabolomics to compare metabolites in soluble lysates of platelets from healthy controls (CO), patients with mild cognitive impairment (MCI), and patients with AD in a cohort of 90 subjects. We could target 163 metabolites and quantitative data were obtained for 91 metabolites. Among these, the lipid PC aeC40:4 significantly differentiated AD from CO (p = 0.0009), while four other lipids (PC aaC32:0, PC ae C32:2, PC aeC34:1, and SM(OH)C14:1) differentiated patients with MCI from CO. The combination of three phosphatidylcholines (PC aeC32:2, PC aeC34:1, PCaaC36:5), two lyso-phosphatidylcholines (lysoPC aC18:1, lysoPC aC16:0), and one sphingomyelin (SM(OH) C14:1) constructed a valuable prediction model using the C4.5 decision tree. The diagnosis accuracy for AD versus CO and MCI was 85%. In a blinded follow up conversion study (10 patients with a second blood collection after 9 months), we could verify the clinical diagnosis in 19 out of 20 cases. We propose that soluble platelet PCaeC40:4 is a promising marker to diagnose AD with a cut-off of <0.30μM and that platelets undergo metabolic processes during AD progression.

Tau Platelets Correlate with Regional Brain Atrophy in Patients with Alzheimer's Disease. - Slachevsky, Andrea; Guzmán-Martínez, Leonardo; Delgado, Carolina; Reyes, Pablo; Farías, Gonzalo A; Muñoz-Neira, Carlos; Bravo, Eduardo; Farías, Mauricio; Flores, Patricia; Garrido, Cristian; Becker, James T; Lopez, Oscar L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Intracellular neurofibrillary tangles are part of the core pathology of Alzheimer's disease (AD), which are mainly composed of hyperphosphorylated tau protein. OBJECTIVES: The purpose of this study is to determine whether high molecular weight (HMW) or low molecular weight (LMW) tau protein levels, as well as the ratio HMW/LMW, present in platelets correlates with brain magnetic resonance imaging (MRI) structural changes in normal and cognitively impaired subjects. METHODS: We examined 53 AD patients and 37 cognitively normal subjects recruited from two Memory Clinics at the Universidad de Chile. Tau levels in platelets were determined by immunoreactivity and the MRI scans were analyzed using voxel-based morphometry in 41 AD patients. RESULTS: The HMW/LMW tau ratio was statistically different between controls and AD patients, and no associations were noted between HMW or LMW tau and MRI structures. In a multivariate analysis controlled for age and education level, the HMW/LMW tau ratio was associated with reduced volume in the left medial and right anterior cingulate gyri, right cerebellum, right thalamus (pulvinar), left frontal cortex, and right parahippocampal region. CONCLUSIONS: This exploratory study showed that HMW/LMW tau ratio is significantly higher in AD patients than control subjects, and that it is associated with specific brain regions atrophy. Determination of peripheral markers of AD pathology can help understanding the pathophysiology of neurodegeneration in AD.

Tocotrienol-Rich Fraction Modulates Amyloid Pathology and Improves Cognitive Function in AβPP/PS1 Mice. - Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Durani, Lina Wati; Hamezah, Hamizah Shahirah; Damanhuri, Hanafi Ahmad; Wan Ngah, Wan Zurinah; Tsuji, Mayumi; Kiuchi, Yuji; Ono, Kenjiro; Tooyama, Ikuo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia. The cardinal neuropathological characteristic of AD is the accumulation of amyloid-β (Aβ) into extracellular plaques that ultimately disrupt neuronal function and lead to neurodegeneration. One possible therapeutic strategy therefore is to prevent Aβ aggregation. Previous studies have suggested that vitamin E analogs slow AD progression in humans. In the present study, we investigated the effects of the tocotrienol-rich fraction (TRF), a mixture of vitamin E analogs from palm oil, on amyloid pathology in vitro and in vivo. TRF treatment dose-dependently inhibited the formation of Aβ fibrils and Aβ oligomers in vitro. Moreover, daily TRF supplementation to AβPPswe/PS1dE9 double transgenic mice for 10 months attenuated Aβ immunoreactive depositions and thioflavin-S-positive fibrillar type plaques in the brain, and eventually improved cognitive function in the novel object recognition test compared with control AβPPswe/PS1dE9 mice. The present result indicates that TRF reduced amyloid pathology and improved cognitive functions, and suggests that TRF is a potential therapeutic agent for AD.

Topological Alterations and Symptom-Relevant Modules in the Whole-Brain Structural Network in Semantic Dementia. - Ding, Junhua; Chen, Keliang; Zhang, Weibin; Li, Ming; Chen, Yan; Yang, Qing; Lv, Yingru; Guo, Qihao; Han, Zaizhu (J Alzheimers Dis, 2017)
BACKGROUND: Semantic dementia (SD) is characterized by a selective decline in semantic processing. Although the neuropsychological pattern of this disease has been identified, its topological global alterations and symptom-relevant modules in the whole-brain anatomical network have not been fully elucidated. OBJECTIVE: This study aims to explore the topological alteration of anatomical network in SD and reveal the modules associated with semantic deficits in this disease. METHODS: We first constructed the whole-brain white-matter networks of 20 healthy controls and 19 patients with SD. Then, the network metrics of graph theory were compared between these two groups. Finally, we separated the network of SD patients into different modules and correlated the structural integrity of each module with the severity of the semantic deficits across patients. RESULTS: The network of the SD patients presented a significantly reduced global efficiency, indicating that the long-distance connections were damaged. The network was divided into the following four distinctive modules: the left temporal/occipital/parietal, frontal, right temporal/occipital, and frontal/parietal modules. The first two modules were associated with the semantic deficits of SD. CONCLUSION: These findings illustrate the skeleton of the neuroanatomical network of SD patients and highlight the key role of the left temporal/occipital/parietal module and the left frontal module in semantic processing.

Translational MRI Volumetry with NeuroQuant: Effects of Version and Normative Data on Relationships with Memory Performance in Healthy Older Adults and Patients with Mild Cognitive Impairment. - Stelmokas, Julija; Yassay, Lance; Giordani, Bruno; Dodge, Hiroko H; Dinov, Ivo D; Bhaumik, Arijit; Sathian, K; Hampstead, Benjamin M (J Alzheimers Dis, 2017)
NeuroQuant (NQ) is a fully-automated program that overcomes several existing limitations in the clinical translation of MRI-derived volumetry. The current study characterized differences between the original (NQ1) and an updated NQ version (NQ2) by 1) replicating previously identified relationships between neuropsychological test performance and medial temporal lobe volumes, 2) evaluating the level of agreement between NQ versions, and 3) determining if the addition of NQ2 age-/sex-based z-scores hold greater clinical utility for prediction of memory impairment than standard percent of intracranial volume (% ICV) values. Sixty-seven healthy older adults and 65 mild cognitive impairment patients underwent structural MRI and completed cognitive testing, including the Immediate and Delayed Memory indices from the Repeatable Battery for the Assessment of Neuropsychological Status. Results generally replicated previous relationships between key medial temporal lobe regions and memory test performance, though comparison of NQ regions revealed statistically different values that were biased toward one version or the other depending on the region. NQ2 hippocampal z-scores explained additional variance in memory performance relative to % ICV values. Findings indicate that NQ1/2 medial temporal lobe volumes, especially age- and sex-based z-scores, hold clinical value, though caution is warranted when directly comparing volumes across NQ versions.

Transport of Non-Transferrin Bound Iron to the Brain: Implications for Alzheimer's Disease. - Tripathi, Ajai K; Karmakar, Shilpita; Asthana, Abhishek; Ashok, Ajay; Desai, Vilok; Baksi, Shounak; Singh, Neena (J Alzheimers Dis, 2017)
A direct correlation between brain iron and Alzheimer's disease (AD) raises questions regarding the transport of non-transferrin-bound iron (NTBI), a toxic but less researched pool of circulating iron that is likely to increase due to pathological and/or iatrogenic systemic iron overload. Here, we compared the distribution of radiolabeled-NTBI (59Fe-NTBI) and transferrin-bound iron (59Fe-Tf) in mouse models of iron overload in the absence or presence of inflammation. Following a short pulse, most of the 59Fe-NTBI was taken up by the liver, followed by the kidney, pancreas, and heart. Notably, a strong signal of 59Fe-NTBI was detected in the brain ventricular system after 2 h, and the brain parenchyma after 24 h. 59Fe-Tf accumulated mainly in the femur and spleen, and was transported to the brain at a much slower rate than 59Fe-NTBI. In the kidney, 59Fe-NTBI was detected in the cortex after 2 h, and outer medulla after 24 hours. Most of the 59Fe-NTBI and 59Fe-Tf from the kidney was reabsorbed; negligible amount was excreted in the urine. Acute inflammation increased the uptake of 59Fe-NTBI by the kidney and brain from 2-24 hours. Chronic inflammation, on the other hand, resulted in sequestration of iron in the liver and kidney, reducing its transport to the brain. These observations provide direct evidence for the transport of NTBI to the brain, and reveal a complex interplay between inflammation and brain iron homeostasis. Further studies are necessary to determine whether transient increase in NTBI due to systemic iron overload is a risk factor for AD.

Treadmill Exercise Exerts Neuroprotection and Regulates Microglial Polarization and Oxidative Stress in a Streptozotocin-Induced Rat Model of Sporadic Alzheimer's Disease. - Lu, Yujiao; Dong, Yan; Tucker, Donovan; Wang, Ruimin; Ahmed, Mohammad Ejaz; Brann, Darrell; Zhang, Quanguang (J Alzheimers Dis, 2017)
Recent work has suggested that exercise may be beneficial in preventing or ameliorating symptoms of several neurological disorders, although the mechanism is not entirely understood. The current study was designed to examine the potential beneficial effect of treadmill exercise upon cognitive function in a streptozotocin (STZ)-induced rat model of Alzheimer's disease (AD). Animals underwent treadmill exercise (30 min/day, 5 days/week) for 4 weeks after bilateral STZ intracerebroventricular injection (2.4 mg/kg). We demonstrated that treadmill exercise significantly attenuated STZ-induced neurodegeneration in the rat hippocampal CA1 region and strongly preserved hippocampal-dependent cognitive functioning. Further mechanistic investigation displayed a marked suppression of STZ-induced amyloid-β accumulation and tau phosphorylation. Intriguingly, treadmill exercise remarkably inhibited reactive gliosis following STZ insult and effectively shifted activated microglia from a pro-inflammatory M1 to an anti-inflammatory M2 phenotype, which was correlated with a significantly reduced expression of pro-inflammatory mediators and a corresponding enhancement of anti-inflammatory cytokine expression in the hippocampus. Furthermore, treadmill exercise caused a robust suppression of oxidative damage as evidenced by significantly reduced peroxynitrite production, lipid peroxidation, and oxidized DNA damage. Finally, treadmill exercise strongly attenuated STZ-induced mitochondrial dysfunction manifested by a dramatically elevated intra-mitochondrial cytochrome c oxidase activity and ATP synthesis, and markedly inhibited neuronal apoptosis in the hippocampus. These findings demonstrate that treadmill exercise has a multifactorial effect to attenuate many of the pathological processes that play a key role in AD, and provide further support for the beneficial role of exercise as a potential therapeutic option in AD treatment.

Use of Analgesics (Opioids and Nonsteroidal Anti-Inflammatory Drugs) and Dementia-Related Neuropathology in a Community-Based Autopsy Cohort. - Dublin, Sascha; Walker, Rod L; Gray, Shelly L; Hubbard, Rebecca A; Anderson, Melissa L; Yu, Onchee; Montine, Thomas J; Crane, Paul K; Sonnen, Josh A; Larson, Eric B (J Alzheimers Dis, 2017)
BACKGROUND: Opioids may influence the development of Alzheimer's disease (AD). Some studies have observed AD pathology in the brains of opioid abusers. No study has examined the association between prescription opioid use and dementia-related neuropathologic changes. OBJECTIVE: To examine the relationship between prescription opioid or NSAID use and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N = 420), we ascertained opioid and nonsteroidal anti-inflammatory drug (NSAID) use over a 10-year period from automated pharmacy data and calculated total standardized daily doses (TSDDs). A neuropathologist assessed outcomes including neuritic plaques, neurofibrillary tangles, and macroscopic infarcts. Outcome measures were dichotomized using established cutpoints. We used modified Poisson regression to calculate adjusted relative risks (RR) and 95% confidence intervals (CI), accounting for participant characteristics and using weighting to account for possible selection bias related to selection into the autopsy sample. RESULTS: Heavier opioid exposure was not associated with greater neuropathologic changes. For neuritic plaques, the adjusted RR [95% CI] was 0.99 [0.64-1.47] for 91+ TSDDs of opioids versus little to no use, and for neurofibrillary tangles, 0.97 [0.49-1.78]. People with heavy NSAID use had higher risk of neuritic plaques (RR 1.39 [1.01-1.89]) than those with little to no use, as we have previously reported. Neither opioid nor NSAID use was associated with higher risk of macroscopic infarcts or with Lewy body disease. CONCLUSION: Prescription opioid use is not associated with dementia-related neuropathologic changes, but heavy NSAID use may be. More research is needed examining chronic pain, its pharmacologic treatments, and neuropathologic changes.

The Use of Music Playlists for People with Dementia: A Critical Synthesis. - Garrido, Sandra; Dunne, Laura; Chang, Esther; Perz, Janette; Stevens, Catherine J; Haertsch, Maggie (J Alzheimers Dis, 2017)
The use of pre-recorded music to ease behavioral and psychological symptoms associated with dementia is popular in health-care contexts in both formal music therapy settings and in non-therapist led interventions. However, further understanding of how non-therapist led interventions compare to therapist led interventions is needed. This paper reviews 28 studies that used pre-recorded music with people with dementia using a critical interpretive synthesis model. Results revealed that pre-recorded music can be effective in reducing a variety of affective and behavioral symptoms, in particular agitation, even where a trained music therapist is not present. However, the results are not universally positive, suggesting the need for further clarification of protocols for music use and closer investigation of variables that influence individual responseto music.

Utility of Molecular and Structural Brain Imaging to Predict Progression from Mild Cognitive Impairment to Dementia. - Lan, Martin J; Ogden, R Todd; Kumar, Dileep; Stern, Yaakov; Parsey, Ramin V; Pelton, Gregory H; Rubin-Falcone, Harry; Pradhaban, Gnanavalli; Zanderigo, Francesca; Miller, Jeffrey M; Mann, J John; Devanand, D P (J Alzheimers Dis, 2017)
This project compares three neuroimaging biomarkers to predict progression to dementia in subjects with mild cognitive impairment (MCI). Eighty-eight subjects with MCI and 40 healthy controls (HCs) were recruited. Subjects had a 3T magnetic resonance imaging (MRI) scan, and two positron emission tomography (PET) scans, one with Pittsburgh compound B ([11C]PIB) and one with fluorodeoxyglucose ([18F]FDG). MCI subjects were followed for up to 4 y and progression to dementia was assessed on an annual basis. MCI subjects had higher [11C]PIB binding potential (BPND) than HCs in multiple brain regions, and lower hippocampus volumes. [11C]PIB BPND, [18F]FDG standard uptake value ratio (SUVR), and hippocampus volume were associated with time to progression to dementia using a Cox proportional hazards model. [18F]FDG SUVR demonstrated the most statistically significant association with progression, followed by [11C]PIB BPND and then hippocampus volume. [11C]PIB BPND and [18F]FDG SUVR were independently predictive, suggesting that combining these measures is useful to increase accuracy in the prediction of progression to dementia. Hippocampus volume also had independent predictive properties to [11C]PIB BPND, but did not add predictive power when combined with the [18F]FDG SUVR data. This work suggests that PET imaging with both [11C]PIB and [18F]FDG may help to determine which MCI subjects are likely to progress to AD, possibly directing future treatment options.

Varying Degrees of Temporoparietal Hypometabolism on FDG-PET Reveal Amyloid-Positive Logopenic Primary Progressive Aphasia is not a Homogeneous Clinical Entity. - Krishnan, Kamini; Machulda, Mary M; Whitwell, Jennifer L; Butts, Alissa M; Duffy, Joseph R; Strand, Edythe A; Senjem, Matthew L; Spychalla, Anthony J; Jack, Clifford R; Lowe, Val J; Josephs, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: The logopenic variant of primary progressive aphasia (lvPPA) manifests due to a breakdown of the language network with prominent hypometabolism of the left temporoparietal region. LvPPA is strongly associated with amyloid deposition, yet there is question as to whether it is a homogeneous clinical entity. OBJECTIVE: This study investigated whether differences in temporoparietal metabolic patterns on 18F fludeoxyglucose positron emission tomography (FDG-PET) could elucidate brain regions preferentially affected in lvPPA. METHOD: We used differences in FDG-PET metabolic z-scores relative to controls for means of left lateral temporal, left inferior parietal, and left superior parietal regions to classify 53 amyloid-positive lvPPA patients into temporal, parietal, or temporoparietal predominate groups. Clinical features and FDG-PET regions of hypometabolism outside of the temporoparietal region were then compared across the three groups; the latter using statistical parametric mapping. RESULTS: Of the 53 lvPPA patients, 15 were classified as temporal, 14 as temporoparietal, and 22 as parietal predominate. There were no significant differences between the groups on demographic measures, language evaluation, or apolipoprotein E genotype. Compared to the other two groups, individuals with the parietal predominate pattern had extensive hypometabolism in left frontal lobe and the precuneus. Furthermore, this group had greater behavioral dyscontrol and deficits in executive function, visuospatial skills, visual memory retention, working memory, and cognitive flexibility (Bonferronip < 0.05). CONCLUSIONS: This study demonstrates that there is clinical heterogeneity within amyloid-positive lvPPA. Patients with lvPPA with predominant parietal hypometabolism, unlike those with temporal or temporoparietal predominant hypometabolism, demonstrated widespread cognitive and behavioral changes.

Visit-to-Visit Blood Pressure Variability and Alzheimer's Disease: Links and Risks. - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Kagawa, Eisuke; Nakano, Yoshinori; Yamane, Aya; Higashihara, Tasuku; Miyauchi, Shunsuke; Tsuchiya, Akane (J Alzheimers Dis, 2017)
While hypertension has been shown to be a risk factor for vascular dementia, several studies have also demonstrated that hypertension also increases the risk of Alzheimer's disease (AD). Although the relationship between visit-to-visit blood pressure variability (VVV) and cognitive impairment, including AD, have been provided, the mechanisms remain poorly understood. This review paper focuses on the relationship of VVV with AD and summarizes the pathophysiology underlying that relationship, which appears to be mediated by arterial stiffness.

Visuospatial Functioning in Cerebral Amyloid Angiopathy: A Pilot Study. - Valenti, Raffaella; Charidimou, Andreas; Xiong, Li; Boulouis, Gregoire; Fotiadis, Panagiotis; Ayres, Alison; Riley, Grace; Kuijf, Hugo J; Reijmer, Yael D; Pantoni, Leonardo; Gurol, M Edip; Davidsdottir, Sigurros; et al. (J Alzheimers Dis, 2017)
Cerebral amyloid angiopathy (CAA) is a contributor to cognitive impairment in the elderly. We hypothesized that the posterior cortical predilection of CAA would cause visual-processing impairment. We systematically evaluated visuospatial abilities in 22 non-demented CAA patients. Neurocognitive evaluation demonstrated visuoperceptual impairment (23% on Benton Facial Recognition Test [BFRT] and 13.6% on Benton Judgment of Line Orientation Test [BJLO]). BFRT was inversely correlated with white matter hyperintensities volume and BJLO with parietal cerebral microbleeds. This pilot study highlights the presence of visual-processing deficits in CAA. The impairment could be related to global disease severity in addition to local brain injury.

Vitamin D and the Risk of Dementia: The Rotterdam Study. - Licher, Silvan; de Bruijn, Renée F A G; Wolters, Frank J; Zillikens, M Carola; Ikram, M Arfan; Ikram, M Kamran (J Alzheimers Dis, 2017)
BACKGROUND: Vitamin D has gained interest as a potentially modifiable risk factor for dementia because of its putative neuroprotective effects. However, longitudinal studies examining the association between vitamin D and dementia have provided inconsistent results. OBJECTIVE: To determine the relationship of serum vitamin D with prevalent and incident dementia in the general population. METHODS: Within the prospective Rotterdam Study, we measured serum 25-hydroxyvitamin D concentrations between 1997 and 2001 using electrochemiluminescence-immunoassay in 6220 participants 55 years or older. We assessed dementia at baseline and continuously during follow-up until 1 January 2015. We used appropriate regression models to determine the relationship of vitamin D with prevalent and incident dementia, including Alzheimer's disease (AD). We adjusted models for age, sex, and season of blood collection. Additionally, we adjusted for ethnicity, education, cardiovascular risk factors, serum calcium, kidney function, depression, outdoor-activity and APOEɛ4 carriership. RESULTS: At baseline, 127 of 6,220 participants had dementia, of whom 97 had AD. Lower vitamin D concentrations were associated with a non-significantly higher prevalence of dementia (adjusted OR, per SD decrease 1.20, 95% CI 0.95;1.52), but not with AD (adjusted OR: 0.97, 95% CI 0.74;1.29). Among 6,087 non-demented participants with 68,884 person-years of follow-up, 795 participants developed dementia, of whom 641 had AD. Lower vitamin D concentrations were associated with higher risk of dementia (adjusted HR, per SD decrease 1.11, 95% CI 1.02;1.20) and AD (adjusted HR: 1.13, 95% CI 1.03;1.24). CONCLUSION: Lower serum vitamin D concentrations are associated with a higher incidence of dementia.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

Young to Middle-Aged Dogs with High Amyloid-β Levels in Cerebrospinal Fluid are Impaired on Learning in Standard Cognition tests. - Borghys, Herman; Van Broeck, Bianca; Dhuyvetter, Deborah; Jacobs, Tom; de Waepenaert, Katja; Erkens, Tim; Brooks, Melissa; Thevarkunnel, Sandy; Araujo, Joseph A (J Alzheimers Dis, 2017)
Understanding differences in Alzheimer's disease biomarkers before the pathology becomes evident can contribute to an improved understanding of disease pathogenesis and treatment. A decrease in amyloid-β (Aβ)42 in cerebrospinal fluid (CSF) is suggested to be a biomarker for Aβ deposition in brain. However, the relevance of CSF Aβ levels prior to deposition is not entirely known. Dogs are similar to man with respect to amyloid-β protein precursor (AβPP)-processing, age-related amyloid plaque deposition, and cognitive dysfunction. In the current study, we evaluated the relation between CSF Aβ42 levels and cognitive performance in young to middle-aged dogs (1.5-7 years old). Additionally, CSF sAβPPα and sAβPPβ were measured to evaluate AβPP processing, and CSF cytokines were measured to determine the immune status of the brain. We identified two groups of dogs showing consistently low or high CSF Aβ42 levels. Based on prior studies, it was assumed that at this age no cerebral amyloid plaques were likely to be present. The cognitive performance was evaluated in standard cognition tests. Low or high Aβ concentrations coincided with low or high sAβPPα, sAβPPβ, and CXCL-1 levels, respectively. Dogs with high Aβ concentrations showed significant learning impairments on delayed non-match to position (DNMP), object discrimination, and reversal learning compared to dogs with low Aβ concentrations. Our data support the hypothesis that high levels of CSF Aβ in dogs coincide with lower cognitive performance prior to amyloid deposition. Further experiments are needed to investigate this link, as well as the relevance with respect to Alzheimer's disease pathology progression.

Accurate Prediction of Conversion to Alzheimer's Disease using Imaging, Genetic, and Neuropsychological Biomarkers. - Dukart, Juergen; Sambataro, Fabio; Bertolino, Alessandro (J Alzheimers Dis, 2016)
A variety of imaging, neuropsychological, and genetic biomarkers have been suggested as potential biomarkers for the identification of mild cognitive impairment (MCI) in patients who later develop Alzheimer's disease (AD). Here, we systematically evaluated the most promising combinations of these biomarkers regarding discrimination between stable and converter MCI and reflection of disease staging. Alzheimer's Disease Neuroimaging Initiative data of AD (n = 144), controls (n = 112), stable (n = 265) and converter (n = 177) MCI, for which apolipoprotein E status, neuropsychological evaluation, and structural, glucose, and amyloid imaging were available, were included in this study. Naïve Bayes classifiers were built on AD and controls data for all possible combinations of these biomarkers, with and without stratification by amyloid status. All classifiers were then applied to the MCI cohorts. We obtained an accuracy of 76% for discrimination between converter and stable MCI with glucose positron emission tomography as a single biomarker. This accuracy increased to about 87% when including further imaging modalities and genetic information. We also identified several biomarker combinations as strong predictors of time to conversion. Use of amyloid validated training data resulted in increased sensitivities and decreased specificities for differentiation between stable and converter MCI when amyloid was included as a biomarker but not for other classifier combinations. Our results indicate that fully independent classifiers built only on AD and controls data and combining imaging, genetic, and/or neuropsychological biomarkers can more reliably discriminate between stable and converter MCI than single modality classifiers. Several biomarker combinations are identified as strongly predictive for the time to conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve; Sensitivity and Specificity

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

Active Cigarette Smoking in Cognitively-Normal Elders and Probable Alzheimer's Disease is Associated with Elevated Cerebrospinal Fluid Oxidative Stress Biomarkers. - Durazzo, Timothy C; Korecka, Magdalena; Trojanowski, John Q; Weiner, Michael W; O' Hara, Ruth; Ashford, John W; Shaw, Leslie M (J Alzheimers Dis, 2016)
Neurodegenerative diseases and chronic cigarette smoking are associated with increased cerebral oxidative stress (OxS). Elevated F2-isoprostane levels in biological fluid is a recognized marker of OxS. This study assessed the association of active cigarette smoking with F2-isoprostane in concentrations in cognitively-normal elders (CN), and those with mild cognitive impairment (MCI) and probable Alzheimer's disease (AD). Smoking and non-smoking CN (n = 83), MCI (n = 164), and probable AD (n = 101) were compared on cerebrospinal fluid (CSF) iPF2α-III and 8,12, iso-iPF2α-VI F2-isoprostane concentrations. Associations between F2-isoprostane levels and hippocampal volumes were also evaluated. In CN and AD, smokers had higher iPF2α-III concentration; overall, smoking AD showed the highest iPF2α-III concentration across groups. Smoking and non-smoking MCI did not differ on iPF2α-III concentration. No group differences were apparent on 8,12, iso-iPF2α-VI concentration, but across AD, higher 8,12, iso-iPF2α-VI level was related to smaller left and total hippocampal volumes. Results indicate that active cigarette smoking in CN and probable AD is associated with increased central nervous system OxS. Further investigation of factors mediating/moderating the absence of smoking effects on CSF F2-isoprostane levels in MCI is warranted. In AD, increasing magnitude of OxS appeared to be related to smaller hippocampal volume. This study contributes additional novel information to the mounting body of evidence that cigarette smoking is associated with adverse effects on the human central nervous system across the lifespan.

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Age-Related Changes in the Synaptic Density of Amyloid-β Protein Precursor and Secretases in the Human Cerebral Cortex. - Pliássova, Anna; Canas, Paula M; Xavier, Ana Carolina; da Silva, Beatriz S; Cunha, Rodrigo A; Agostinho, Paula (J Alzheimers Dis, 2016)
Amyloid-β protein precursor (AβPP) is involved in synaptic formation and function. In the human cingulate cortex, AβPP was preferentially located in the presynaptic active zone as in rodents, indicating a preserved subsynaptic AβPP distribution across species and brain regions. Synaptic AβPP immunoreactivity was decreased with aging in cortical samples collected from autopsies of males (20-80 years), whereas the synaptic levels of α-secretase (ADAM10) and β-secretase (BACE1) did not significantly change. Decreased AβPP levels may be related to lower allostasis of synapses in the aged brain and their greater susceptibility to dysfunction characteristic of the onset of neurodegenerative disorders.

Alcohol Consumption and Incident Dementia: Evidence from the Sydney Memory and Ageing Study. - Heffernan, Megan; Mather, Karen A; Xu, Jing; Assareh, Amelia A; Kochan, Nicole A; Reppermund, Simone; Draper, Brian; Trollor, Julian N; Sachdev, Perminder; Brodaty, Henry (J Alzheimers Dis, 2016)
Alcohol consumption is a potentially modifiable risk factor for dementia, but the literature is not completely consistent. This inconsistency may be partly due to an interaction with the apolipoprotein E (APOE) genotype, an established risk factor for Alzheimer's dementia. The aim of this study was to examine whether alcohol consumption is associated with incident dementia or decline in specific cognitive domains over 4 years, and if this effect is modified by APOEɛ4 status. Non-demented community dwelling older adults (70-90 years) from an ongoing longitudinal study were assessed for cognitive impairment in attention/processing speed, language, executive function, visuospatial ability, and memory. Incident dementia was diagnosed according to DSM-IV criteria. Compared to those who did not drink in the previous 12 months, neither low consumption (HR 0.64 95% CI 0.3-1.4) or risky consumption (HR 0.58 95% CI 0.2-1.5) was associated with incident dementia. Carriers of the APOEɛ4 allele were more likely to develop dementia, but there was no significant interaction with alcohol consumption.

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Anti-Correlated Cerebrospinal Fluid Biomarker Trajectories in Preclinical Alzheimer's Disease. - Gomar, Jesus J; Conejero-Goldberg, Concepcion; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2016)
BACKGROUND: The earliest stage of preclinical Alzheimer's disease (AD) is defined by low levels of cerebrospinal fluid (CSF) amyloid-β (Aβ42). However, covariance in longitudinal dynamic change of Aβ42 and tau in incipient preclinical AD is poorly understood. OBJECTIVE: To examine dynamic interrelationships between Aβ42 and tau in preclinical AD. METHODS: We followed 47 cognitively intact participants (CI) with available CSF data over four years in ADNI. Based on longitudinal Aβ42 levels in CSF, CI were classified into three groups: 1) Aβ42 stable with normal levels of Aβ42 over time (n = 15); 2) Aβ42 declining with normal Aβ42 levels at baseline but showing decline over time (n = 14); and 3) Aβ42 levels consistently abnormal (n = 18). RESULTS: In the Aβ42 declining group, suggestive of incipient preclinical AD, CSF phosphorylated tau (p-tau) showed a similar longitudinal pattern of increasing abnormality over time (p = 0.0001). Correlation between longitudinal slopes of Aβ42 and p-tau confirmed that both trajectories were anti-correlated (rho = -0.60; p = 0.02). Regression analysis showed that Aβ42 slope (decreasing Aβ42) predicted p-tau slope (increasing p-tau) (R2 = 0.47, p = 0.03). Atrophy in the hippocampus was predicted by the interaction of Aβ42 and p-tau slopes (p <  0.0001) only in this incipient preclinical AD group. In all groups combined, memory decline was predicted by p-tau. CONCLUSIONS: The evolution of Aβ42 and p-tau CSF biomarkers in CI subjects follows an anti-correlated trajectory, i.e., as Aβ42 declined, p-tau increased, and thus was suggestive of strong temporal coincidence. Rapid pathogenic cross-talk between Aβ42 and p-tau thus may be evident in very early stages of preclinical AD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Brain; Disease Progression; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Prodromal Symptoms; Regression Analysis; Statistics, Nonparametric; tau Proteins

The Anti-Prion Antibody 15B3 Detects Toxic Amyloid-β Oligomers. - Stravalaci, Matteo; Tapella, Laura; Beeg, Marten; Rossi, Alessandro; Joshi, Pooja; Pizzi, Erika; Mazzanti, Michele; Balducci, Claudia; Forloni, Gianluigi; Biasini, Emiliano; Salmona, Mario; Diomede, Luisa; et al. (J Alzheimers Dis, 2016)
15B3 is a monoclonal IgM antibody that selectively detects pathological aggregates of the prion protein (PrP). We report the unexpected finding that 15B3 also recognizes oligomeric but not monomeric forms of amyloid-β (Aβ)42, an aggregating peptide implicated in the pathogenesis of Alzheimer's disease (AD). The 15B3 antibody: i) inhibits the binding of synthetic Aβ42 oligomers to recombinant PrP and neuronal membranes; ii) prevents oligomer-induced membrane depolarization; iii) antagonizes the inhibitory effects of oligomers on the physiological pharyngeal contractions of the nematode Caenorhabditis elegans; and iv) counteracts the memory deficits induced by intracerebroventricular injection of Aβ42 oligomers in mice. Thus this antibody binds to pathologically relevant forms of Aβ, and offers a potential research, diagnostic, and therapeutic tool for AD.

Anti-Viral Properties of Amyloid-β Peptides. - Bourgade, Karine; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) peptides generated by the amyloidogenic pathway of amyloid-β protein precursor processing contribute significantly to neurodegeneration characteristic of Alzheimer's disease (AD). The involvement of Aβ peptides in the etiology of AD remains a subject of debate. Data published in the last 6 years by three different groups have added a new twist by revealing that Aβ peptides could act as antimicrobial peptides (AMP) in in vitro assays against some common and clinically relevant microorganisms, inhibit replication of seasonal and pandemic strains of influenza A and HSV-1 virus. These observations are of significance with respect to the notion that pathogens may be important contributors to the development of AD, particularly in the case of herpes simplex virus (HSV) infection, which often resides in the same cerebral sites where AD arises. Here, we review the data that support the interpretation that Aβ peptides behave as AMP, with an emphasis on studies concerning HSV-1 and a putative molecular mechanism that suggests that interactions between Aβ peptides and the HSV-1 fusogenic protein gB lead to impairment of HSV-1 infectivity by preventing the virus from fusing with the plasma membrane. A number of avenues for future research are suggested.

Apo J and Apo D: Complementary or Antagonistic Roles in Alzheimer's Disease? - Del Valle, Eva; Navarro, Ana; Martínez-Pinilla, Eva; Torices, Silvia; Tolivia, Jorge (J Alzheimers Dis, 2016)
Apolipoprotein D (Apo D) and Apolipoprotein J (Apo J) are among the only nine apolipoproteins synthesized in the nervous system. Apart from development, these apolipoproteins are implicated in the normal aging process as well as in different neuropathologies as Alzheimer's disease (AD), where a neuroprotective role has been postulated. Different authors have proposed that Apo D and Apo J could be biomarkers for AD but as far as we know, there are no studies about the relationship between them as well as their expression pattern along the progression of the disease. In this paper, using double immunohistochemistry techniques, we have demonstrated that Apo D is mainly located in glial cells while Apo J expression preferentially occurs in neurons; both proteins are also present in AD diffuse and mature senile plaques but without signal overlap. In addition, we have observed that Apo J and Apo D immunostaining shows a positive correlation with the progression of the disease and the Braak's stages. These results suggest complementary and cell-dependent neuroprotective roles for each apolipoprotein during AD progress.

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Physical Function with Clinical and Subclinical Brain Disease: The Framingham Offspring Study. - Camargo, Erica C; Weinstein, Galit; Beiser, Alexa S; Tan, Zaldy S; DeCarli, Charles; Kelly-Hayes, Margaret; Kase, Carlos; Murabito, Joanne M; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Handgrip strength and gait speed are simple measures of physical capability and have been associated with current and future health outcomes. However, studies on their associations with brain structure and function in middle-aged adults are lacking. OBJECTIVE: To assess the relationship of fast-paced walking speed and handgrip strength with risk of dementia, Alzheimer's disease (AD), and stroke, as well as the cross-sectional associations with cognitive and brain magnetic resonance imaging (MRI) measures in a middle-aged community sample. METHODS: Framingham Offspring (n = 2,176; mean age 62, 54% female) had physical function, brain MRI, and cognitive evaluations between 1999 and 2005 and were followed-up for incident dementia AD and stroke until 11 years later. We related walking speed and handgrip strength to incident dementia, AD, and stroke using Cox models, and to brain and cognitive measures using multivariable linear and logistic regression. Models were adjusted for age, sex, education, and vascular risk factors. RESULTS: Slow walking and weak handgrip were associated with more than 2.5-fold increase in risk of AD. Weaker handgrip was associated with an increased risk of incident stroke (HR 1.74, 95% CI: 1.12-2.70/SDU, p = 0.01) in persons ≥65 years. Both measures were associated with lower total brain volume and poorer performance on tests of visual memory, language, executive function, and visuoperceptual function. Slower gait was also related to poorer verbal memory, and weaker handgrip to poorer abstraction. CONCLUSION: Tests of walking speed and handgrip strength may serve as clinical markers of brain structure and function and may improve dementia risk prediction.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

The Associations between a Capsaicin-Rich Diet and Blood Amyloid-β Levels and Cognitive Function. - Liu, Cheng-Hui; Bu, Xian-Le; Wang, Jun; Zhang, Tao; Xiang, Yang; Shen, Lin-Lin; Wang, Qing-Hua; Deng, Bo; Wang, Xin; Zhu, Chi; Yao, Xiu-Qing; Zhang, Meng; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Capsaicin-rich diets are common worldwide. Capsaicin has been shown to have favorable effects on various diseases including atherosclerosis, cardiovascular diseases, stroke, obesity, hypertension, cancer, and gastrointestinal and inflammatory diseases. The impact of capsaicin on Alzheimer's disease (AD), which is the most common form of dementia in the elderly, remains unknown. OBJECTIVE: To investigate the correlations of capsaicin intake with cognition and blood markers of AD. METHODS: A total of 338 participants aged 40 years or older were enrolled from communities. Dietary habits regarding chili pepper consumption were collected using a Food Frequency Questionnaire (FFQ). Cognitive function was measured using the Chinese version of the Mini-Mental State Examination (MMSE). Blood amyloid-β (Aβ)40 and Aβ42 were measured with ELISA kits. RESULTS: In univariate analysis, MMSE scores (r = 0.209, p < 0.001), serum Aβ40 levels (r = -0.149, p = 0.006), the ratio of Aβ42/Aβ40 (r = 0.11, p = 0.043) and total serum Aβ levels (r = -0.097, p = 0.075), but not serum Aβ42 levels (r = 0.17, p = 0.757), were significantly correlated with total capsaicin diet scores. In multivariate analysis, total capsaicin diet scores were positively associated with MMSE scores and inversely associated with serum Aβ40 levels, and total serum Aβ levels, but not serum Aβ42 levels and the ratio of Aβ42/Aβ40, after adjustment for age, gender, educational level, smoking history, alcohol consumption, body mass index (BMI) and comorbidities. CONCLUSION: These findings suggest that a capsaicin-rich diet may exert favorable effects on AD blood biomarkers and cognitive function in middle-aged and elderly adults.

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Attitudes and Perceptions of Research in Aging and Dementia in an Urban Minority Population. - Neugroschl, Judith; Sewell, Margaret; De La Fuente, Angelica; Umpierre, Mari; Luo, Xiaodong; Sano, Mary (J Alzheimers Dis, 2016)
In dementia trials, minority participation is low. We assessed attitudes toward research in a community based urban poor minority sample of elderly adults attending senior center talks using the 7-item Research Attitudes Questionnaire (RAQ). Presentations on cognitive aging were given at senior centers, and 123 attendees completed the RAQ-7. On trust and safety questions, a significant minority (42-48%) responded neutrally or negatively. Encouragingly, on questions concerning the importance of research, 72-81% answered positively. More work can be done to capitalize on these findings to engage and foster trust, and this can be a focus of outreach.

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Biochemical and Radiological Markers of Alzheimer's Disease Progression. - Dziedzic, Tomasz; Pera, Joanna; Klimkowicz-Mrowiec, Aleksandra; Mroczko, Barbara; Slowik, Agnieszka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative, inevitably progressive disease with a rate of cognitive, functional, and behavioral decline that varies highly from patient to patient. Although several clinical predictors of AD progression have been identified, to our mind in clinical practice there is a lack of a reliable biomarker that enables one to stratify the risk of deterioration. Identification of biomarkers that allow the monitoring of AD progression could change the way physicians and caregivers make treatment decisions. This review summarizes the results of studies on potential biochemical and radiological markers related to AD progression.
Keywords: Alzheimer Disease; Biomarkers; Disease Progression; Humans; Neuroimaging; Radionuclide Imaging

Bioenergetic Impairment in Animal and Cellular Models of Alzheimer's Disease: PARP-1 Inhibition Rescues Metabolic Dysfunctions. - Martire, Sara; Fuso, Andrea; Mosca, Luciana; Forte, Elena; Correani, Virginia; Fontana, Mario; Scarpa, Sigfrido; Maras, Bruno; d'Erme, Maria (J Alzheimers Dis, 2016)
Amyloid-beta peptide accumulation in the brain is one of the main hallmarks of Alzheimer's disease. The amyloid aggregation process is associated with the generation of free radical species responsible for mitochondrial impairment and DNA damage that in turn activates poly(ADP-ribose)polymerase 1 (PARP-1). PARP-1 catalyzes the poly(ADP-ribosylation), a post-translational modification of proteins, cleaving the substrate NAD+ and transferring the ADP-ribose moieties to the enzyme itself or to an acceptor protein to form branched polymers of ADP-ribose. In this paper, we demonstrate that a mitochondrial dysfunction occurs in Alzheimer's transgenic mice TgCRND8, in SH-SY5Y treated with amyloid-beta and in 7PA2 cells. Moreover, PARP-1 activation contributes to the functional energetic decline affecting cytochrome oxidase IV protein levels, oxygen consumption rates, and membrane potential, resulting in cellular bioenergetic deficit. We also observed, for the first time, an increase of pyruvate kinase 2 expression, suggesting a modulation of the glycolytic pathway by PARP-1. PARP-1 inhibitors are able to restore both mitochondrial impairment and pyruvate kinase 2 expression. The overall data here presented indicate a pivotal role for this enzyme in the bioenergetic network of neuronal cells and open new perspectives for investigating molecular mechanisms underlying energy charge decline in Alzheimer's disease. In this scenario, PARP-1 inhibitors might represent a novel therapeutic intervention to rescue cellular energetic metabolism.

Blockade of the Interaction of Calcineurin with FOXO in Astrocytes Protects Against Amyloid-β-Induced Neuronal Death. - Fernandez, Ana M; Hervas, Ruben; Dominguez-Fraile, Manuel; Garrido, Victoria Navarro; Gomez-Gutierrez, Patricia; Vega, Miguel; Vitorica, Javier; Perez, Juan J; Torres Aleman, Ignacio (J Alzheimers Dis, 2016)
Astrocytes actively participate in neuro-inflammatory processes associated to Alzheimer's disease (AD), and other brain pathologies. We recently showed that an astrocyte-specific intracellular signaling pathway involving an interaction of the phosphatase calcineurin with the transcription factor FOXO3 is a major driver in AD-associated pathological inflammation, suggesting a potential new druggable target for this devastating disease. We have now developed decoy molecules to interfere with calcineurin/FOXO3 interactions, and tested them in astrocytes and neuronal co-cultures exposed to amyloid-β (Aβ) toxicity. We observed that interference of calcineurin/FOXO3 interactions exerts a protective action against Aβ-induced neuronal death and favors the production of a set of growth factors that we hypothesize form part of a cytoprotective pathway to resolve inflammation. Furthermore, interference of the Aβ-induced interaction of calcineurin with FOXO3 by decoy compounds significantly decreased amyloid-β protein precursor (AβPP) synthesis, reduced the AβPP amyloidogenic pathway, resulting in lower Aβ levels, and blocked the expression of pro-inflammatory cytokines TNFα and IL-6 in astrocytes. Collectively, these data indicate that interrupting pro-inflammatory calcineurin/FOXO3 interactions in astrocytes triggered by Aβ accumulation in brain may constitute an effective new therapeutic approach in AD. Future studies with intranasal delivery, or brain barrier permeable decoy compounds, are warranted.

Brain Atrophy of Secondary REM-Sleep Behavior Disorder in Neurodegenerative Disease. - Kim, Hee-Jin; Im, Hyung Kyun; Kim, Juhan; Han, Jee-Young; de Leon, Mony; Deshpande, Anup; Moon, Won-Jin (J Alzheimers Dis, 2016)
BACKGROUND: Rapid eye movement sleep behavior disorder (RBD) may present as an early manifestation of an evolving neurodegenerative disorder with alpha-synucleinopathy. OBJECTIVE: We investigated that dementia with RBD might show distinctive cortical atrophic patterns. METHODS: A total of 31 patients with idiopathic Parkinson's disease (IPD), 23 with clinically probable Alzheimer's disease (AD), and 36 healthy controls participated in this study. Patients with AD and IPD were divided into two groups according to results of polysomnography and rated with a validated Korean version of the RBD screening questionnaire (RBDSQ-K), which covers the clinical features of RBD. Voxel-based morphometry was adapted for detection of regional brain atrophy among groups of subjects. RESULTS: Scores on RBDSQ-K were higher in the IPD group (3.54 ± 2.8) than in any other group (AD, 2.94 ± 2.4; healthy controls, 2.31 ± 1.9). Atrophic changes according to RBDSQ-K scores were characteristically in the posterior part of the brain and brain stem, including the hypothalamus and posterior temporal region including the hippocampus and bilateral occipital lobe. AD patients with RBD showed more specialized atrophic patterns distributed in the posterior and inferior parts of the brain including the bilateral temporal and occipital cortices compared to groups without RBD. The IPD group with RBD showed right temporal cortical atrophic changes. CONCLUSION: The group of patients with neurodegenerative diseases and RBD showed distinctive brain atrophy patterns, especially in the posterior and inferior cortices. These results suggest that patients diagnosed with clinically probable AD or IPD might have mixed pathologies including α-synucleinopathy.

Brain Serotonergic and Noradrenergic Deficiencies in Behavioral Variant Frontotemporal Dementia Compared to Early-Onset Alzheimer's Disease. - Vermeiren, Yannick; Janssens, Jana; Aerts, Tony; Martin, Jean-Jacques; Sieben, Anne; Van Dam, Debby; De Deyn, Peter P (J Alzheimers Dis, 2016)
Routinely prescribed psychoactive drugs in behavioral variant frontotemporal dementia (FTD) for improvement of (non)cognitive symptoms are primarily based on monoamine replacement or augmentation strategies. These were, however, initially intended to symptomatically treat other degenerative, behavioral, or personality disorders, and thus lack disease specificity. Moreover, current knowledge on brain monoaminergic neurotransmitter deficiencies in this presenile disorder is scarce, particularly with reference to changes in Alzheimer's disease (AD). The latter hence favors neurochemical comparison studies in order to elucidate the monoaminergic underpinnings of FTD compared to early-onset AD, which may contribute to better pharmacotherapy. Therefore, frozen brain samples, i.e., Brodmann area (BA) 6/8/9/10/11/12/22/24/46, amygdala, and hippocampus, of 10 neuropathologically confirmed FTD, AD, and control subjects were analyzed by means of reversed-phase high-performance liquid chromatography. Levels of serotonergic, dopaminergic, and noradrenergic compounds were measured. In nine brain areas, serotonin (5-HT) concentrations were significantly increased in FTD compared to AD patients, while 5-hydroxyindoleacetic acid/5-HT ratios were decreased in eight regions, also compared to controls. Furthermore, in all regions, noradrenaline (NA) levels were significantly higher, and 3-methoxy-4-hydroxyphenylglycol/NA ratios were significantly lower in FTD than in AD and controls. Contrarily, significantly higher dopamine (DA) levels and reduced homovanillic acid/DA ratios were only found in BA12 and BA46. Results indicate that FTD is defined by distinct serotonergic and noradrenergic deficiencies. Additional research regarding the interactions between both monoaminergic networks is required. Similarly, clinical trials investigating the effects of 5-HT1A receptor antagonists or NA-modulating agents, such as α1/2/β1-blockers, seem to have a rationale and should be considered.

Brain-Specific Basal and Novelty-Induced Alternations in PI3K-Akt and MAPK/ERK Signaling in a Middle-Aged AβPP/PS1 Mouse Model of Alzheimer's Disease. - Guillot, Florence; Kemppainen, Susanna; Lavasseur, Gregoire; Miettinen, Pasi O; Laroche, Serge; Tanila, Heikki; Davis, Sabrina (J Alzheimers Dis, 2016)
Although it is well established that insulin/IGF and BDNF signaling are dysfunctionally regulated in Alzheimer's disease, there are very few studies documenting changes in major target proteins in different murine models of the disease. We investigated a panel of proteins in the PI3K-Akt and MAPK/ERK cascades in parietal cortex, dentate gyrus and CA1 in 13-month-old AβPP/PS1 transgenic mice to determine whether amyloid pathology is associated with basal dysregulation of these proteins or following exposure to novelty. The most striking effect we found was that there was little common regulation of proteins either by pathology alone or exposure to novelty across the three structures, suggesting dysfunctional mechanisms that occur simultaneously have important structure specificity. CA1 shared certain dysfunctional regulation of proteins in the MAPK/ERK cascade, but shared dysfunctional regulation of the PI3K/Akt cascade with the dentate gyrus. Changes in ERK/CREB in transgenic mice did not result in coordinated dysfunction of the downstream transcription factor, Egr1, as it was overexpressed in a normal manner following exposure to novelty. In the PI3K-Akt cascade, there was a flagrant increase in the levels of proteins associated with inflammation, such as NFκB, and structure specific regulation of proteins associated with autophagy, such as mTOR and FOXO1 and lack of regulation of Beclin-1. Finally, Beclin-1 was increased by novelty in wild-type mice but deficient in transgenic mice. Results are interpreted in terms of structure-specific dysfunctional regulation of signaling mechanisms associated with Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Gene Expression Regulation; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mitogen-Activated Protein Kinase Kinases; Mutation; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Presenilin-1; Signal Transduction

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

A Brief Computerized Paired Associate Test for the Detection of Mild Cognitive Impairment in Community-Dwelling Older Adults. - Curiel, Rosie E; Crocco, Elizabeth; Rosado, Marian; Duara, Ranjan; Greig, Maria T; Raffo, Arlene; Loewenstein, David A (J Alzheimers Dis, 2016)
BACKGROUND: Semantic memory interference has been found to be a predictive cognitive marker of incipient AD. This is relevant given that developing assessment paradigms to identify subtle cognitive and functional deficits is a priority in preclinical Alzheimer's disease research. OBJECTIVE: To examine the utility of a novel computerized paired associate test in distinguishing between mild cognitive impairment (MCI) and cognitively normal (CN) groups of older adults residing in the community. METHODS: Participants that were CN (n = 64) or MCI (n = 34) were administered the Miami Test of Semantic Interference and Learning (MITSI-L). This novel instrument is a brief, computerized paired associate test that measured the strength of memory binding of semantically related word pairs and introduced a proactive semantic interference condition which required participants to make different associations between semantically similar targets. A series of ANOVAs explored differences on MITSI-L performance. Logistic regression and receiver operator curves (ROC) analyses were employed to further determine discriminative validity. RESULTS: MCI participants had lower scores on all indices relative to CN elders. A composite of two subscores correctly classified 85.3% of MCI and 84.4% of CN participants. Area under the ROC was higher relative to the MMSE, immediate memory for passages, and several subtests of a sensitive memory measure, the LASSI-L. CONCLUSIONS: The MITSI-L is a computerized test that can successfully differentiate MCI from CN participants. Area under the ROC curve exceeded that of global mental status and other memory measures. The effectiveness of the MITSI-L in detecting MCI, and its brief administration and portability render it worthy of further research.

Butyrylcholinesterase K and Apolipoprotein E-ɛ4 Reduce the Age of Onset of Alzheimer's Disease, Accelerate Cognitive Decline, and Modulate Donepezil Response in Mild Cognitively Impaired Subjects. - De Beaumont, Louis; Pelleieux, Sandra; Lamarre-Théroux, Louise; Dea, Doris; Poirier, Judes (J Alzheimers Dis, 2016)
BACKGROUND: Genetic heterogeneity in amnestic mild cognitively impaired (aMCI) subjects could lead to variations in progression rates and response to cholinomimetic agents. Together with the apolipoprotein E4 (APOE-ɛ4) gene, butyrylcholinesterase (BCHE) has become recently one of the few Alzheimer's disease (AD) susceptibility genes with distinct pharmacogenomic properties. OBJECTIVE: To validate candidate genes (APOE/BCHE) which display associations with age of onset of AD and donepezil efficacy in aMCI subjects. METHODS: Using the Petersen et al. (2005) study on vitamin E and donepezil efficacy in aMCI, we contrasted the effects of BCHE and APOE variants on donepezil drug response using the Alzheimer's Disease Assessment Score-Cognition (ADAS-Cog) scale. Independently, we assessed the effects of APOE/BCHE genotypes on age of onset and cortical choline acetyltransferase activity in autopsy-confirmed AD and age-matched control subjects. RESULTS: Statistical analyses revealed a significant earlier age of onset in AD for APOE-ɛ4, BCHE-K*, and APOE-ɛ4/BCHE-K* carriers. Among the carriers of APOE-ɛ4 and BCHE-K*, the benefit of donepezil was evident at the end of the three-year follow-up. The responder's pharmacogenomic profile is consistent with reduced brain cholinergic activity measured in APOE-ɛ4 and BCHE-K* positive subjects. CONCLUSIONS: APOE-ɛ4 and BCHE-K* positive subjects display an earlier age of onset of AD, an accelerated cognitive decline and a greater cognitive benefits to donepezil therapy. These results clearly emphasize the necessity of monitoring potential pharmacogenomic effects in this population of subjects, and suggest enrichment strategies for secondary prevention trials involving prodromal AD subjects.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Isolated Supratentorial Cortical Superficial Siderosis. - Renard, Dimitri; Gabelle, Audrey; Hirtz, Christophe; Demattei, Christophe; Thouvenot, Eric; Lehmann, Sylvain (J Alzheimers Dis, 2016)
We evaluated cerebrospinal fluid amyloid-β 1-40 (Aβ40), amyloid-β 1-42 (Aβ42), total and phosphorylated-tau (t-tau and p-tau) in patients with symptomatic isolated cortical supratentorial superficial siderosis (SS), by prospectively recruiting ten patients with SS in the absence of pre-existing cognitive dysfunction, and comparing biomarkers with lobar hematoma cerebral amyloid angiopathy patients (LH-CAA, n = 13), Alzheimer's disease patients (AD, n = 42), and controls (n = 16). Compared to controls, SS patients showed statistically significant higher t-tau (p = 0.019) and lower Aβ42 (p = 0.0084). Compared to other groups, SS showed statistically significant lower t-tau, p-tau, and Aβ40 compared to AD (p = 0.0063, p = 0.0004, and p = 0022, respectively), and higher p-tau compared to LH-CAA (p = 0.012).

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Characterizing Aging, Mild Cognitive Impairment, and Dementia with Blood-Based Biomarkers and Neuropsychology. - Kleinschmidt, Martin; Schoenfeld, Robby; Göttlich, Claudia; Bittner, Daniel; Metzner, Jürgen Erich; Leplow, Bernd; Demuth, Hans-Ulrich (J Alzheimers Dis, 2016)
BACKGROUND: Current treatment in Alzheimer's disease (AD) is initiated at a stage where the brain already has irreversible structural deteriorations. Therefore, the concept of treatment prior to obvious cognitive deficits has become widely accepted, and simple biochemical tests to discriminate normal aging from prodromal or demented stages are now common practice. OBJECTIVE: The objective of the study was the differentiation of controls, mild cognitive impairment (MCI) and AD patients by novel blood-based assays in combination with neuropsychological tests. METHODS: In a cross-sectional study, 143 subjects aged 18 to 85 years were recruited. All participants were classified by a comprehensive neuropsychological assessment. Blood samples were analyzed for several amyloid-β (Aβ) species, pro-inflammatory markers, anti-Aβ autoantibodies, and ApoE allele status, respectively. RESULTS: Plasma Aβ1-42 was significantly decreased in MCI and AD compared to age-matched controls, whereas Aβ1-40 did not differ, but increases with age in healthy controls. The Aβ1-42 to Aβ1-40 ratio was stepwise decreased from age-matched controls via MCI to AD, and shows a clear correlation with memory scores. Reduced Aβ1-42 and Aβ1-42 to Aβ1-40 ratio have strongly correlated with carrying ApoE ɛ4 allele. Autoantibodies against pyroglutamate-modified Aβ, but only a certain subclass, were significantly decreased in AD compared to MCI and age-matched controls, whereas autoantibodies against the unmodified N-terminus of Aβ did not differ. CONCLUSION: Comprehensive sample preparation and assay standardization enable reliable usage of plasma Aβ for diagnosis of MCI and AD. Anti-pGlu-Aβ autoantibodies correlate with cognition, but not with ApoE, supporting the associated plasma Aβ analysis with additional and independent information.
Keywords: Activities of Daily Living; Adolescent; Adult; Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Analysis of Variance; Apolipoproteins E; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Cytokines; Dementia; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; Young Adult

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Chocolate Consumption is Associated with a Lower Risk of Cognitive Decline. - Moreira, Afonso; Diógenes, Maria José; de Mendonça, Alexandre; Lunet, Nuno; Barros, Henrique (J Alzheimers Dis, 2016)
Cocoa-related products like chocolate have taken an important place in our food habits and culture. In this work, we aim to examine the relationship between chocolate consumption and cognitive decline in an elderly cognitively healthy population. In the present longitudinal prospective study, a cohort of 531 participants aged 65 and over with normal Mini-Mental State Examination (MMSE; median 28) was selected. The median follow-up was 48 months. Dietary habits were evaluated at baseline. The MMSE was used to assess global cognitive function at baseline and at follow-up. Cognitive decline was defined by a decrease ≥ 2 points in the MMSE score between evaluations. Relative risk (RR) and 95% confidence interval (95% CI) estimates were adjusted for age, education, smoking, alcohol drinking, body mass index, hypertension, and diabetes. Chocolate intake was associated with a lower risk of cognitive decline (RR = 0.59, 95% CI 0.38-0.92). This protective effect was observed only among subjects with an average daily consumption of caffeine lower than 75 mg (69% of the participants; RR = 0.50, 95% CI 0.31-0.82). To our knowledge, this is the first prospective cohort study to show an inverse association between regular long-term chocolate consumption and cognitive decline in humans.

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Clinical Application of Automatic Segmentation of Medial Temporal Lobe Subregions in Prodromal and Dementia-Level Alzheimer's Disease. - Gertje, Eske Christiane; Pluta, John; Das, Sandhitsu; Mancuso, Lauren; Kliot, Dasha; Yushkevich, Paul; Wolk, David (J Alzheimers Dis, 2016)
BACKGROUND: Volumetry of medial temporal lobe (MTL) structures to diagnose Alzheimer's disease (AD) in its earliest symptomatic stage could be of great importance for interventions or disease modifying pharmacotherapy. OBJECTIVE: This study aimed to demonstrate the first application of an automatic segmentation method of MTL subregions in a clinical population. Automatic segmentation of magnetic resonance images (MRIs) in a research population has previously been shown to detect evidence of neurodegeneration in MTL subregions and to help discriminate AD and mild cognitive impairment (MCI) from a healthy comparison group. METHODS: Clinical patients were selected and T2-weighted MRI scan quality was checked. An automatic segmentation method of hippocampal subfields (ASHS) was applied to scans of 67 AD patients, 38 amnestic MCI patients, and 57 healthy controls. Hippocampal subfields, entorhinal cortex (ERC), and perirhinal cortex were automatically labeled and subregion volumes were compared between groups. RESULTS: One fourth of all scans were excluded due to bad scan quality. There were significant volume reductions in all subregions, except BA36, in aMCIs (p < 0.001), most prominently in Cornu Ammonis 1 (CA1) and ERC, and in all subregions in AD. However, sensitivity of CA1 and ERC hardly differed from sensitivity of WH in aMCI and AD. CONCLUSION: Applying automatic segmentation of MTL subregions in a clinical setting as a potential biomarker for prodromal AD is feasible, but issues of image quality due to motion remain to be addressed. CA1 and ERC provided strongest group discrimination in differentiating aMCIs from controls, but discriminatory power of different subfields was low overall.

Clinical utility of the informant AD8 as a dementia case finding instrument in primary healthcare. - Chan, Qun Lin; Xu, Xin; Shaik, Muhammad Amin; Chong, Steven Shih Tsze; Hui, Richard Jor Yeong; Chen, Christopher Li-Hsian; Dong, YanHong (J Alzheimers Dis, 2016)
The informant AD8 has excellent discriminant ability for dementia case finding in tertiary healthcare settings. However, its clinical utility for dementia case finding at the forefront of dementia management, primary healthcare, is unknown. Therefore, we recruited participants from two primary healthcare centers in Singapore and measured their performance on the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Clinical Dementia Rating (CDR), and a local formal neuropsychological battery, in addition to the AD8. Logistic regression was conducted to examine the associations between demographic factors and dementia. Area under the receiver operating characteristics (ROC) curve analysis was used to establish the optimal cut-off points for dementia case finding. Of the 309 participants recruited, 243 (78.7%) had CDR = 0, 22 (7.1%) CDR = 0.5, and 44 (14.2%) CDR ≥1. Age was strongly associated with dementia, and the optimal age for dementia case finding in primary healthcare settings was ≥75 years. In this age group, the AD8 has excellent dementia case finding capability and was superior to the MMSE and equivalent to the MoCA [AD8 AUC (95% CI): 0.95 (0.91-0.99), cut-off: ≥3, sensitivity: 0.90, specificity: 0.88, PPV: 0.79 and NPV: 0.94; MMSE AUC (95% CI): 0.87 (0.79-0.94), p = 0.04; MoCA AUC (95% CI): 0.88 (0.82-0.95), p = 0.06]. In conclusion, the AD8 is well suited for dementia case finding in primary healthcare settings.
Keywords: Aged; Aged, 80 and over; Dementia; Female; Humans; Language; Logistic Models; Male; Mass Screening; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; ROC Curve; Sensitivity and Specificity; Singapore; Surveys and Questionnaires

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Community-Dwelling People Screened Positive for Dementia in Primary Care: A Comprehensive, Multivariate Descriptive Analysis Using Data from the DelpHi-Study. - Thyrian, Jochen René; Eichler, Tilly; Michalowsky, Bernhard; Wucherer, Diana; Reimann, Melanie; Hertel, Johannes; Richter, Steffen; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: Efficient help and care for people with dementia (PWD) is dependent on knowledge about PWD in primary care. OBJECTIVE: This analysis comprehensively describes community-dwelling PWD in primary care with respect to various dementia care specific variables. METHODS: The analyses are based on baseline data of the ongoing general practitioner-based, randomized, controlled intervention trial DelpHi-MV (Dementia: life- and person-centered help). 6,838 patients were screened for dementia in 136 GP practices; 17.1% were screened positive, 54.4% of those agreed to participate and data could be assessed in n = 516 subjects. We assessed age, sex, living situation, cognitive status, functional status, level of impairment, comorbidities, formal diagnosis of dementia, depression, neuropsychiatric symptoms, quality of life, utilization of medical support, and pharmacological therapy. RESULTS: Concerning clinical-, dementia-, and health-related variables, the sample under examination was on average mildly cognitively and functionally impaired (MMSE, m = 22.2; BADL, m = 3.7). A level of care was assigned in 38.0%. Depression was identified in 15.4% and other frequent comorbidities were high blood pressure (83.3%), coronary heart diseases (37.1%), cerebrovascular diseases (22.3%), among others. In 48.6%, neuropsychiatric symptoms were present in a clinically relevant severity. Pharmacological treatment with antidementia medication was received by 25.8% and antidepressant medication by 14.0%. Utilization of services was generally low. CONCLUSION: The comprehensive description of people screened positive for dementia in primary care reveals a complex and unique population of patients. They are considerably underdiagnosed and in their majority mildly to moderately affected. More in-depth analyses are needed to study relations, associations and interactions between different variables.

Comorbid Mild Cognitive Impairment and Depressive Symptoms Predict Future Dementia in Community Older Adults: A 24-Month Follow-Up Longitudinal Study. - Makizako, Hyuma; Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Makino, Keitaro; Suzuki, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Older adults with mild cognitive impairment (MCI) are non-demented, but demonstrate cognitive dysfunction, and have significantly higher risk of progressing to dementia. A better understanding of more sensitive risk factors, such as combination of cognitive and psychological status, for progression of MCI to dementia may be crucial for prevention of development of dementia. OBJECTIVE: To examine MCI, depressive symptoms, and comorbid MCI and depressive symptoms as risk factors for development of dementia. METHODS: A total of 3,663 community-dwelling older people were included in this prospective longitudinal study. MCI was determined by age- and education-adjusted objective cognitive impairment using computerized comprehensive cognitive measures including memory, attention/executive function, and processing speed. Depressive symptoms were measured using the 15-item Geriatric Depression Scale (GDS) and defined by a GDS score of 6 or more. RESULTS: During the 24-month follow-up period, 72 participants (2.0%) developed dementia. Baseline MCI was significantly associated with an increased risk of incident dementia (hazard ratio [HR], 3.2; 95% confidence interval [CI], 1.8-5.5) but depressive symptoms were not (2.0; 1.0-4.2) after adjusting for age, sex, education, prescribed medications, and walking speed. Participants with comorbid MCI and depressive symptoms at baseline had a higher risk of developing dementia (HR, 4.8; 2.3-10.5). CONCLUSION: Although MCI and depressive symptoms may be associated with increased risk for incident dementia independently, comorbid MCI and depressive symptoms have a significantly greater impact on dementia development among community-dwelling older adults.

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial. - Sánchez, Alba; Maseda, Ana; Marante-Moar, M Pilar; de Labra, Carmen; Lorenzo-López, Laura; Millán-Calenti, José Carlos (J Alzheimers Dis, 2016)
The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitation (Cohen-Mansfield Agitation Inventory, CMAI), mood (Cornell Scale for Depression in Dementia, CSDD), anxiety (Rating Anxiety in Dementia, RAID), cognitive function (Severe Mini-Mental State Examination, SMMSE), and the overall severity of dementia (Bedford Alzheimer Nursing Severity Scale, BANS-S). They were assessed at baseline (pre-trial), in the middle (mid-trial), at the end of the intervention (post-trial), and 8 weeks after the intervention (follow-up). Patients in the MSSE group showed significant improvement in their RAID and BANS-S scores compared with the individualized music group post- versus pre-trial. With regard to agitation, there was improvement during the intervention in both the MSSE and individualized music groups in the CMAI total score after 16 weeks of intervention, with no significant differences between the groups. The results suggest that MSSE could have better effects on anxiety symptoms and dementia severity in comparison with individualized music sessions in elderly patients with severe dementia.
Keywords: Affect; Aged; Aged, 80 and over; Anxiety; Cognition; Dementia; Environment; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Music Therapy; Precision Medicine; Sensory Art Therapies; Severity of Illness Index; Treatment Outcome

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Complement Biomarkers as Predictors of Disease Progression in Alzheimer's Disease. - Hakobyan, Svetlana; Harding, Katharine; Aiyaz, Mohammed; Hye, Abdul; Dobson, Richard; Baird, Alison; Liu, Benjamine; Harris, Claire Louise; Lovestone, Simon; Morgan, Bryan Paul (J Alzheimers Dis, 2016)
There is a critical unmet need for reliable markers of disease and disease course in mild cognitive impairment (MCI) and early Alzheimer's disease (AD). The growing appreciation of the importance of inflammation in early AD has focused attention on inflammatory biomarkers in cerebrospinal fluid or plasma; however, non-specific inflammation markers have disappointed to date. We have adopted a targeted approach, centered on an inflammatory pathway already implicated in the disease. Complement, a core system in innate immune defense and potent driver of inflammation, has been implicated in pathogenesis of AD based on a confluence of genetic, histochemical, and model data. Numerous studies have suggested that measurement of individual complement proteins or activation products in cerebrospinal fluid or plasma is useful in diagnosis, prediction, or stratification, but few have been replicated. Here we apply a novel multiplex assay to measure five complement proteins and four activation products in plasma from donors with MCI, AD, and controls. Only one complement analyte, clusterin, differed significantly between control and AD plasma (controls, 295 mg/l; AD, 388 mg/l: p < 10- 5). A model combining clusterin with relevant co-variables was highly predictive of disease. Three analytes (clusterin, factor I, terminal complement complex) were significantly different between MCI individuals who had converted to dementia one year later compared to non-converters; a model combining these three analytes with informative co-variables was highly predictive of conversion. The data confirm the relevance of complement biomarkers in MCI and AD and build the case for using multi-parameter models for disease prediction and stratification.

Cortical Amyloid Burden Differences Across Empirically-Derived Mild Cognitive Impairment Subtypes and Interaction with APOE ɛ4 Genotype. - Bangen, Katherine J; Clark, Alexandra L; Werhane, Madeline; Edmonds, Emily C; Nation, Daniel A; Evangelista, Nicole; Libon, David J; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
We examined cortical amyloid-β (Aβ) levels and interactions with apolipoprotein (APOE) ɛ4 genotype status across empirically-derived mild cognitive impairment (MCI) subgroups and cognitively normal older adults. Participants were 583 ADNI participants (444 MCI, 139 normal controls [NC]) with baseline florbetapir positron emission tomography (PET) amyloid imaging and neuropsychological testing. Of those with ADNI-defined MCI, a previous cluster analysis [1] classified 51% (n = 227) of the current sample as amnestic MCI, 8% (n = 37) as dysexecutive/mixed MCI, and 41% (n = 180) as cluster-derived normal (cognitively normal). Results demonstrated that the dysexecutive/mixed and amnestic MCI groups showed significantly greater levels of amyloid relative to the cluster-derived normal and NC groups who did not differ from each other. Additionally, 78% of the dysexecutive/mixed, 63% of the amnestic MCI, 42% of the cluster-derived normal, and 34% of the NC group exceeded the amyloid positivity threshold. Finally, a group by APOE genotype interaction demonstrated that APOE ɛ4 carriers within the amnestic MCI, cluster-derived normal, and NC groups showed significantly greater amyloid accumulation compared to non-carriers of their respective group. Such an interaction was not revealed within the dysexecutive/mixed MCI group which was characterized by both greater cognitive impairment and amyloid accumulation compared to the other participant groups. Our results from the ADNI cohort show considerable heterogeneity in Aβ across all groups studied, even within a group of robust NC participants. Findings suggest that conventional criteria for MCI may be susceptible to false positive diagnostic errors, and that onset of Aβ accumulation may occur earlier in APOE ɛ4 carriers compared to non-carriers.

Cycloheximide Treatment Causes a ZVAD-Sensitive Protease-Dependent Cleavage of Human Tau in Drosophila Cells. - Geng, Junhua; Xia, Lu; Li, Wanjie; Zhao, Changqi; Dou, Fei (J Alzheimers Dis, 2016)
Neurofibrillary tangles are the main pathological feature of Alzheimer's disease. Insoluble tau protein is the major component of neurofibrillary tangles. Defects in the tau protein degradation pathway in neurons can lead to the accumulation of tau and its subsequent aggregation. Currently, contradictory results on the tau degradation pathway have been reported by different groups. This discrepancy is most likely due to different cell lines and methods used in those studies. In this study, we found that cycloheximide treatment induced mild activation of a ZVAD-sensitive protease in Drosophila Kc cells, resulting in cleavage of tau at its C-terminus; this cleavage could generate misleading tau protein degradation pattern results depending on the antibodies used in the assay. Because cycloheximide is a broadly used chemical reagent for the study of protein degradation, the unexpected artificial effect we observed here indicates that cycloheximide is not suitable for the study of tau degradation. Other methods, such as inducible expression systems and pulse-chase assays, may be more appropriate for studying tau degradation under physiological conditions.
Keywords: Animals; Apoptosis; Caspase 3; Cell Line; Cycloheximide; Drosophila; Drosophila Proteins; Drug Evaluation, Preclinical; Humans; Oligopeptides; Peptide Hydrolases; Protease Inhibitors; Protein Synthesis Inhibitors; tau Proteins; Time

Daily Function as Predictor of Dementia in Cognitive Impairment, No Dementia (CIND) and Mild Cognitive Impairment (MCI): An 8-Year Follow-Up in the ILSA Study. - Di Carlo, Antonio; Baldereschi, Marzia; Lamassa, Maria; Bovis, Francesca; Inzitari, Marco; Solfrizzi, Vincenzo; Panza, Francesco; Galluzzo, Lucia; Scafato, Emanuele; Inzitari, Domenico (J Alzheimers Dis, 2016)
BACKGROUND: Preclinical cognitive changes may predict an increased risk of dementia, allowing selection of subgroups as possible targets for preventive or therapeutic interventions. OBJECTIVE: To evaluate the predictive effect of daily functioning and motor performance (MP) on the progression to dementia in normal cognition, cognitive impairment, no dementia (CIND), and mild cognitive impairment (MCI). METHODS: The Italian Longitudinal Study on Aging is a large population-based survey on age-related diseases of the cardiovascular and nervous systems. After the baseline assessment, to detect prevalent cases of cognitive impairment and dementia, participants were re-examined at 4-year and 8-year follow-ups. Functional independence was evaluated using the Index of Activities of Daily Living (ADL) and the Instrumental Activities of Daily Living (IADL) Scale. A six-test battery was used to assess MP. RESULTS: Overall, 2,386 individuals were included, for a total of 16,545 person-years. Eight-year incidence of dementia (per 1,000 person-years) was 12.69 in total sample, 9.86 in subjects with normal cognition at baseline, 22.99 in CIND, and 21.43 in MCI. Progression to dementia was significantly higher with increasing baseline ADL and IADL impairment, and with a worse MP. In Cox regression analyses controlled for demographics and major age-related conditions, increased IADL impairment was the stronger predictor of progression to dementia (p < 0.001), with HR ranging from 2.16 (95% CI, 0.82-5.70) to 9.57 (95% CI, 3.40-26.91) in subjects with MCI at baseline. CONCLUSIONS: Inclusion of IADL in the MCI construct significantly improves the prediction of dementia. Individuation of different transition rates is required to plan cost-effective interventions.

A Decade of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Belgium. - Somers, Charisse; Struyfs, Hanne; Goossens, Joery; Niemantsverdriet, Ellis; Luyckx, Jill; De Roeck, Naomi; De Roeck, Ellen; De Vil, Bart; Cras, Patrick; Martin, Jean-Jacques; De Deyn, Peter-Paul; Bjerke, Maria; et al. (J Alzheimers Dis, 2016)
During the past ten years, over 5,000 cerebrospinal fluid (CSF) samples were analyzed at the Reference Center for Biological Markers of Dementia (BIODEM), UAntwerp, for core Alzheimer's disease (AD) CSF biomarkers: amyloid-β peptide of 42 amino acids (Aβ1-42), total tau protein (T-tau), and tau phosphorylated at threonine 181 (P-tau181P). CSF biomarker analyses were performed using single-analyte ELISA kits. In-house validated cutoff values were applied: Aβ1-42 <638.5 pg/mL, T-tau >296.5 pg/mL, P-tau181P >56.5 pg/mL. A CSF biomarker profile was considered to be suggestive for AD if the CSF Aβ1-42 concentration was below the cutoff, in combination with T-tau and/or P-tau181P values above the cutoff (IWG2 criteria for AD). Biomarker analyses were requested for following clinical indications: 1) neurochemical confirmation of AD in case of clinical AD, 2) neurochemical confirmation of AD in case of doubt between AD and a non-AD dementia, 3) neurochemical diagnosis of prodromal AD in case of mild cognitive impairment, 4) neurochemical confirmation of AD in case of psychiatric symptoms (like depression, psychosis), or 5) other clinical indications. During these ten years, the number of yearly referred samples increased by 238% and clinical indications for referral showed a shift from neurochemical confirmation of AD in case of clinical AD to differential dementia diagnosis in case of doubt between AD and a non-AD dementia. Four percent of the patients also had a postmortem neuropathological examination. Together, these biomarker data were the basis for several research papers, and significantly contributed to the validation of these biomarkers in autopsy-confirmed subjects.

Delusions in Patients with Alzheimer's Disease: A Multidimensional Approach. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Paris, Francesco F; Cascavilla, Leandro; Mangiacotti, Antonio; Lauriola, Michele; Paroni, Giulia H; Seripa, Davide; Greco, Antonio (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) patients with delusions, clinical outcomes and mortality result from a combination of psychological, biological, functional, and environmental factors. We determined the effect of delusions on mortality risk, clinical outcomes linked to comprehensive geriatric assessment (CGA), cognitive, depressive, and neuropsychiatric symptoms (NPS) in 380 consecutive AD patients with Mini-Mental State Examination, Clinical Dementia Rating scale, 15-item Geriatric Depression Scale, and Neuropsychiatric Inventory (NPI), assessing one-year mortality risk using the Multidimensional Prognostic Index (MPI). We included 121 AD patients with delusions (AD-D) and 259 AD patients without delusions (AD-noD). AD-D patients were significantly older, with higher age at onset and cognitive impairment, a more severe stage of dementia, and more depressive symptoms than AD-noD patients. Disease duration was slightly higher in AD-D patients than in those without delusions, although this difference was not statistically significant. At CGA, AD-D patients showed a higher grade of disability in basic and instrumental activities of daily living, and an increased risk of malnutrition and bedsores. The two groups of patients significantly differed in MPI score (AD-D: 0.65 versus AD-noD: 0.51, p <  0.0001) and MPI grade. AD-D patients showed also a significant higher score in NPI of the following NPS than AD-noD patients: hallucinations, agitation/aggression, depression mood, apathy, irritability/lability, aberrant motor activity, sleep disturbances, and eating disorders. Therefore, AD-D patients showed higher dementia severity, and higher impairment in cognitive and depressive symptoms, and several neuropsychiatric domains than AD-noD patients, and this appeared to be associated with higher multidimensional impairment and increased risk of mortality.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Delusions; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prognosis; Risk; Severity of Illness Index; Time Factors

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

A Depressive Endophenotype for Predicting Cognitive Decline among Mexican American Adults and Elders. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Edwards, Melissa; Hall, James; Weiser, Brent; Yadav, Menaka; Dickensheets, Tony; O'Bryant, Sid E (J Alzheimers Dis, 2016)
BACKGROUND: Late life depression is a prodromal feature and a risk factor for Alzheimer's disease (AD) and mild cognitive impairment (MCI). We identified five items in the Geriatric Depression scale (DepE) that are important as a risk for MCI and AD: memory problems, feeling blue, crying, feeling worthless, and trouble concentrating. OBJECTIVE: Our goal was to examine the relationship between DepE and cognition in a cohort of Mexican Americans. METHODS: Data from 317 Mexican Americans from the HABLE study were analyzed. DepE scores were dichotomized into two groups: endorsement of 1 item or less, and endorsement of 2 or more items. Cognition was assessed via neuropsychological tests, and diagnosis was based on consensus review. We utilized linear regression to examine the association between DepE and cognitive performance, and logistic regression to examine the utility of DepE in predicting MCI. To examine the impact of DepE on memory over 12 months, we performed ANOVA analysis. RESULTS: Elevated DepE scores were associated with poorer performance on various measures of memory and cognition, but not executive or visual spatial skills. Over 12 months, we found a decline in immediate memory among women but not men. Those with high scores were 4 times more likely to have MCI. ANOVA of total scores revealed differences between groups on immediate memory (p < 0.05) in women, with no significant differences on delay recall in either gender. CONCLUSION: DepE can be utilized in Mexican Americans to identify those at risk of memory related cognitive decline.

Describing the Sequence of Cognitive Decline in Alzheimer's Disease Patients: Results from an Observational Study. - Henneges, Carsten; Reed, Catherine; Chen, Yun-Fei; Dell'Agnello, Grazia; Lebrec, Jeremie (J Alzheimers Dis, 2016)
BACKGROUND: Improved understanding of the pattern of cognitive decline in Alzheimer's disease (AD) would be useful to assist primary care physicians in explaining AD progression to patients and caregivers. OBJECTIVE: To identify the sequence in which cognitive abilities decline in community-dwelling patients with AD. METHODS: Baseline data were analyzed from 1,495 patients diagnosed with probable AD and a Mini-Mental State Examination (MMSE) score ≤ 26 enrolled in the 18-month observational GERAS study. Proportional odds logistic regression models were applied to model MMSE subscores (orientation, registration, attention and concentration, recall, language, and drawing) and the corresponding subscores of the cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog), using MMSE total score as the index of disease progression. Probabilities of impairment start and full impairment were estimated at each MMSE total score level. RESULTS: From the estimated probabilities for each MMSE subscore as a function of the MMSE total score, the first aspect of cognition to start being impaired was recall, followed by orientation in time, attention and concentration, orientation in place, language, drawing, and registration. For full impairment in subscores, the sequence was recall, drawing, attention and concentration, orientation in time, orientation in place, registration, and language. The sequence of cognitive decline for the corresponding ADAS-cog subscores was remarkably consistent with this pattern. CONCLUSION: The sequence of cognitive decline in AD can be visualized in an animation using probability estimates for key aspects of cognition. This might be useful for clinicians to set expectations on disease progression for patients and caregivers.

Development of a Proxy-Free Objective Assessment Tool of Instrumental Activities of Daily Living in Mild Cognitive Impairment Using Smart Home Technologies. - Jekel, Katrin; Damian, Marinella; Storf, Holger; Hausner, Lucrezia; Frölich, Lutz (J Alzheimers Dis, 2016)
BACKGROUND: The assessment of activities of daily living (ADL) is essential for dementia diagnostics. Even in mild cognitive impairment (MCI), subtle deficits in instrumental ADL (IADL) may occur and signal a higher risk of conversion to dementia. Thus, sensitive and reliable ADL assessment tools are important. Smart homes equipped with sensor technology and video cameras may provide a proxy-free assessment tool for the detection of IADL deficits. OBJECTIVE: The aim of this paper is to investigate the potential of a smart home environment for the assessment of IADL in MCI. METHOD: The smart home consisted of a two-room flat equipped with activity sensors and video cameras. Participants with either MCI or healthy controls (HC) had to solve a standardized set of six tasks, e.g., meal preparation, telephone use, and finding objects in the flat. RESULTS: MCI participants needed more time (1384 versus 938 seconds, p <  0.001) and scored less total points (48 versus 57 points, p <  0.001) while solving the tasks than HC. Analyzing the subtasks, intergroup differences were observed for making a phone call, operating the television, and retrieving objects. MCI participants showed more searching and task-irrelevant behavior than HC. Task performance was correlated with cognitive status and IADL questionnaires but not with participants' age. CONCLUSION: This pilot study showed that smart home technologies offer the chance for an objective and ecologically valid assessment of IADL. It can be analyzed not only whether a task is successfully completed but also how it is completed. Future studies should concentrate on the development of automated detection of IADL deficits.

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Diagnostic Accuracy of MRI and Additional [18F]FDG-PET for Behavioral Variant Frontotemporal Dementia in Patients with Late Onset Behavioral Changes. - Vijverberg, Everard G B; Wattjes, Mike P; Dols, Annemiek; Krudop, Welmoed A; Möller, Christiane; Peters, Anne; Kerssens, Cora J; Gossink, Flora; Prins, Niels D; Stek, Max L; Scheltens, Philip; van Berckel, Bart N M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Neuroimaging has a reasonable accuracy to differentiate behavioral variant frontotemporal dementia (bvFTD) from other neurodegenerative disorders, its value for the differentiation of bvFTD among subjects with acquired behavioral disturbances is unknown. OBJECTIVE: To determine the diagnostic accuracy of MRI, additional [18F]FDG-PET, and their combination for bvFTD among subjects with late onset behavioral changes. METHODS: Patients with late onset behavioral changes referred to a memory clinic or psychiatric services were included. At baseline, 111 patients had a brain MRI scan and 74 patients received an additional [18F]FDG-PET when the MRI was inconclusive. The consensus diagnosis after two-year-follow-up was used as the gold standard to calculate sensitivity and specificity for baseline neuroimaging. RESULTS: 27 patients had probable/definite bvFTD and 84 patients had a non-bvFTD diagnosis (primary psychiatric diagnosis or other neurological disorders). MRI had a sensitivity of 70% (95% CI 52-85%) with a specificity of 93% (95% CI 86-97%). Additional [18F]FDG-PET had a sensitivity of 90% (95% CI 66-100%) with a specificity of 68% (95% CI 56-79%). The sensitivity of combined neuroimaging was 96% (95% CI 85-100%) with a specificity of 73% (95% CI 63-81%). In 66% of the genetic FTD cases, MRI lacked typical frontotemporal atrophy. 40% of cases with a false positive [18F]FDG-PET scan had a primary psychiatric diagnosis. CONCLUSION: A good diagnostic accuracy was found for MRI and additional [18F]FDG-PET for bvFTD in patients with late onset behavioral changes. Caution with the interpretation of neuroimaging results should especially be taken in cases with a genetic background and in cases with a primary psychiatric differential diagnosis where [18F]FDG-PET is the only abnormal investigation.

Diagnostic Distortions: A Case Report of Progressive Apraxia of Speech. - Brodtmann, Amy; Pemberton, Hugh; Darby, David; Vogel, Adam P (J Alzheimers Dis, 2016)
Apraxia of speech (AOS) can be the presenting symptom of neurodegenerative disease. The position of primary progressive AOS in the nosology of the dementias is still controversial. Despite seeing many specialists, patients are often misdiagnosed, in part due to a lack of quantitative measures of speech dysfunction. We present a single case report of a patient presenting with AOS, including acoustic analysis, language assessment, and brain imaging. A 52-year-old woman presenting with AOS had remained undiagnosed for 6 years despite seeing 8 specialists. Results of her MRI scans, genetic testing, and computerized speech analysis are provided. AOS is an underdiagnosed clinical syndrome causing great distress to patients and families. Using acoustic analysis of speech may lead to improved diagnostic accuracy. AOS is a complex entity with an expanding phenotype, and quantitative clinical measures will be critical for detection and to assess progression.

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Diagnostic Value of Cerebrospinal Fluid Biomarkers (Phospho-Tau181, total-Tau, Aβ42, and Aβ40) in Prodromal Stage of Alzheimer's Disease and Dementia with Lewy Bodies. - Bousiges, Olivier; Cretin, Benjamin; Lavaux, Thomas; Philippi, Nathalie; Jung, Barbara; Hezard, Sylvie; Heitz, Camille; Demuynck, Catherine; Gabel, Aurelia; Martin-Hunyadi, Catherine; Blanc, Frédéric (J Alzheimers Dis, 2016)
BACKGROUND: Dementia with Lewy bodies (DLB) symptoms are close to those of Alzheimer's disease (AD), and the differential diagnosis is difficult especially early in the disease. Unfortunately, AD biomarkers in cerebrospinal fluid (CSF), and more particularly Aβ1 - 42, appear to be altered in dementia with Lewy bodies (DLB). However, the level of these biomarkers has never been studied in the prodromal stage of the disease. OBJECTIVE: To compare these biomarkers between DLB and AD, with a particular focus on the prodromal stage. METHODS: A total of 166 CSF samples were collected at the memory clinic of Strasbourg. They were obtained from prodromal DLB (pro-DLB), DLB dementia, prodromal AD (pro-AD), and AD dementia patients, and elderly controls. Phospho-Tau181, total-Tau, Aβ42, and Aβ40 were measured in the CSF. RESULTS: At the prodromal stage, contrary to AD patients, DLB patients' biomarker levels in the CSF were not altered. At the demented stage of DLB, Aβ42 levels were reduced as well as Aβ40 levels. Thus, the Aβ42/Aβ40 ratio remained unchanged between the prodromal and demented stages, contrary to what was observed in AD. Tau and Phospho-Tau181 levels were unaltered in DLB patients. CONCLUSIONS: We have shown that at the prodromal stage the DLB patients had no pathological profile. Consequently, CSF AD biomarkers are extremely useful for differentiating AD from DLB patients particularly at this stage when the clinical diagnosis is difficult. Thus, these results open up new perspectives on the interpretation of AD biomarkers in DLB.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Middle Aged; Peptide Fragments; Prodromal Symptoms; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Impairment of Cognitive and Affective Mentalizing Abilities in Neurodegenerative Dementias: Evidence from Behavioral Variant of Frontotemporal Dementia, Alzheimer's Disease, and Mild Cognitive Impairment. - Dodich, Alessandra; Cerami, Chiara; Crespi, Chiara; Canessa, Nicola; Lettieri, Giada; Iannaccone, Sandro; Marcone, Alessandra; Cappa, Stefano F; Cacioppo, John T (J Alzheimers Dis, 2016)
Cognitive and affective theory of mind (ToM) can be impaired in the course of neurodegenerative dementias. Experimental tests based on different task conditions and/or complexity may fail to capture disease-specific patterns of impairments. In this study, we assessed with a single task both the affective and the cognitive facets of ToM ability in a sample of 47 patients (i.e., 12 AD, 20 bvFTD, and 15 aMCI fulfilling IWG criteria for AD in predementia phase) and 65 healthy controls. Subjects were administered the Story-based Empathy task (SET), a non-verbal task measuring the ability to infer others' intentions (IA) and emotions (EA) compared to a control condition (causal inferences, CI). Global and single sub-condition scores were evaluated with a vectorial method, analyzing the relationship between social abilities and basic cognitive functioning by means of two indices representing the basic ability to perform the task and the balance between basic functions and ToM skills.Dementia (AD and bvFTD) patients showed impaired performances on all SET sub-conditions, whereas aMCI subjects' performance was not different from healthy controls. Vectorial analysis revealed a specific change in the balance between EA and CI conditions only in the bvFTD group, supporting a disproportionate deficit in mental states attribution based on affective cues. The overall deficit in the task in AD appears to be more general and related to the severity of dementia. This latter finding is further supported by the normal performance of the prodromal AD group.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Emotions; Female; Frontotemporal Dementia; Humans; Male; Theory of Mind

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Drivers: A Biologically Contextualized, Cross-Inferential View of the Epidemiology of Neurodegenerative Disorders. - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Alcalde-Cabero, Enrique; José García López, Fernando; Almazán-Isla, Javier; Ruiz-Tovar, María; Medrano, Maria-José; Avellanal, Fuencisla; Calero, Olga; Calero, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Sutherland et al. (2011) suggested that, instead of risk factors for single neurodegenerative disorders (NDDs), there was a need to identify specific "drivers", i.e., risk factors with impact on specific deposits, such as amyloid-β, tau, or α-synuclein, acting across entities. OBJECTIVES AND METHODS: Redefining drivers as "neither protein/gene- nor entity-specific features identifiable in the clinical and general epidemiology of conformational NDDs (CNDDs) as potential footprints of templating/spread/transfer mechanisms", we conducted an analysis of the epidemiology of ten CNDDs, searching for patterns. RESULTS: We identified seven potential drivers, each of which was shared by at least two CNDDs: 1) an age-at-exposure-related susceptibility to Creutzfeldt-Jakob disease (CJD) and several late-life CNDDs; 2) a relationship between age at onset, survival, and incidence; 3) shared genetic risk factors for CJD and late-life CNNDs; 4) partly shared personal (diagnostic, educational, behavioral, and social risk factors) predating clinical onset of late-life CNDDs; 5) two environmental risk factors, namely, surgery for sporadic CJD and amyotrophic lateral sclerosis, and Bordetella pertussis infection for Parkinson's disease; 6) reticulo-endothelial system stressors or general drivers (andropause or premenopausal estrogen deficiency, APOEɛ4, and vascular risk factors) for late-life CNDDs such as dementia/Alzheimer's disease, type-2 diabetes mellitus, and some sporadic cardiac and vascular degenerative diseases; and 7) a high, invariant incidence ratio of sporadic to genetic forms of mid- and late-life CNDDs, and type-2 diabetes mellitus. CONCLUSION: There might be a systematic epidemiologic pattern induced by specific proteins (PrP, TDP-43, SOD1, α-synuclein, amyloid-β, tau, Langerhans islet peptide, and transthyretin) or established combinations of these.
Keywords: Age Factors; Aging; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Creutzfeldt-Jakob Syndrome; Environment; Female; Humans; Incidence; Male; Neurodegenerative Diseases; Personality; Risk Factors; Vascular Diseases

Dysregulation of Elongation Factor 1A Expression is Correlated with Synaptic Plasticity Impairments in Alzheimer's Disease. - Beckelman, Brenna C; Day, Stephen; Zhou, Xueyan; Donohue, Maggie; Gouras, Gunnar K; Klann, Eric; Keene, C Dirk; Ma, Tao (J Alzheimers Dis, 2016)
Synaptic dysfunction may represent an early and crucial pathophysiology in Alzheimer's disease (AD). Recent studies implicate a connection between synaptic plasticity deficits and compromised capacity of de novo protein synthesis in AD. The mRNA translational factor eukaryotic elongation factor 1A (eEF1A) is critically involved in several forms of long-lasting synaptic plasticity. By examining postmortem human brain samples, a transgenic mouse model, and application of synthetic human Aβ42 on mouse hippocampal slices, we demonstrated that eEF1A protein levels were significantly decreased in AD, particularly in the hippocampus. In contrast, brain levels of eukaryotic elongation factor 2 were unaltered in AD. Further, upregulation of eEF1A expression by the adenylyl cyclase activator forskolin, which induces long-lasting synaptic plasticity, was blunted in hippocampal slices derived from Tg2576 AD model mice. Finally, Aβ-induced hippocampal long-term potentiation defects were alleviated by upregulation of eEF1A signaling via brain-specific knockdown of the gene encoding tuberous sclerosis 2. In summary, our findings suggest a strong correlation between the dysregulation of eEF1A synthesis and AD-associated synaptic failure. These findings provide insights into the understanding of molecular mechanisms underlying AD etiology and may aid in identification of novel biomarkers and therapeutic targets.

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

Effect of Normal Aging and of Mild Cognitive Impairment on Event-Related Potentials to a Stroop Color-Word Task. - Ramos-Goicoa, Marta; Galdo-Álvarez, Santiago; Díaz, Fernando; Zurrón, Montserrat (J Alzheimers Dis, 2016)
Event-related potentials (ERPs) were recorded from 84 adults (51 to 87 years old) with the aim of exploring the effects of aging (middle-aged and older groups) and cognitive status (healthy or with amnestic mild cognitive impairment, aMCI) on the neural functioning associated with stimulus and response processing in a Stroop color-word task. An interference (or Stroop) effect was observed in the Reaction Time (RT), and the RT and number of errors results were consistent with the age-related decline in performance. Cognitive status did not affect the behavioral performance of the task, but age and cognitive status affected several ERP parameters. Aging was associated with a) slowing of the neural processing of the stimuli (P150, N2, and P3b latencies were longer), b) greater activation of the motor cortex for response preparation (LRP-R amplitude was larger), and c) use of more neural resources for cognitive control of stimuli (N2 amplitude was larger to the congruent and incongruent stimuli than to the colored X-strings, in the older group). Independent of age, aMCI dedicated more neural resources to processing the irrelevant dimension of the stimulus (they showed a greater difference than the control participants between the P3b amplitude to the colored X-strings and to the congruent/incongruent stimuli) and showed a deficit in the selection and preparation of the motor response (with smaller LRP-S and LRP-R amplitudes). Furthermore, the middle-aged aMCI participants evaluated and classified both congruent and incongruent stimuli more slowly (they showed longer P3b latencies) relative to middle-aged controls.

Efficacy and Safety of Crocus sativus L. in Patients with Mild Cognitive Impairment: One Year Single-Blind Randomized, with Parallel Groups, Clinical Trial. - Tsolaki, Magda; Karathanasi, Elina; Lazarou, Ioulietta; Dovas, Kostas; Verykouki, Eleni; Karacostas, Anastasios; Georgiadis, Kostas; Tsolaki, Anthoula; Adam, Katerina; Kompatsiaris, Ioannis; Sinakos, Zacharias (J Alzheimers Dis, 2016)
There is evidence to suggest the efficacy of Crocus (saffron) in the management of cognitive decline. This study examined the efficacy of Crocus in patients with amnesic and multi domain MCI (aMCImd). The participants included 17 patients on Crocus and 18 on a waiting list, who were examined with a short neuropsychological battery, MRI 3T, while some patients were examined via 256-channel electroencephalogram (HD-EEG) at baseline and after 12 months. The results showed that patients on Crocus had improved Mini-Mental State Examination scores (p = 0.015), while the control group deteriorated. Also, MRI, EEG, and ERP showed improvement in specific domains. This led us to conclude that Crocus is a good choice for management of aMCImd.

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Epileptic Prodromal Alzheimer's Disease, a Retrospective Study of 13 New Cases: Expanding the Spectrum of Alzheimer's Disease to an Epileptic Variant? - Cretin, Benjamin; Sellal, François; Philippi, Nathalie; Bousiges, Olivier; Di Bitonto, Laure; Martin-Hunyadi, Catherine; Blanc, Frédéric (J Alzheimers Dis, 2016)
BACKGROUND: Aside from rare case reports, only one study, with 12 patients, has addressed the phenotypic presentation of epilepsy in clinically defined amnestic mild cognitive impairment (aMCI, presumed to correspond to the AD prodromal stage): the authors highlighted a pharmacosensitive non-convulsive partial epileptic syndrome most probably related to the temporal or temporo-frontal cortices. OBJECTIVE: The objective of this study was to verify the existence and the syndromic features of epileptic prodromal AD in a tertiary Memory Clinic. METHODS: We conducted a retrospective, single-center study of the electro-radio-clinical features of 13 cases of epileptic prodromal AD patients (3.1% of a cohort of MCI, n = 430 subjects), selected on both clinical criteria and CSF biomarkers. RESULTS: In our patients, a pharmacosensitive temporal lobe epilepsy syndrome, inaugurating prodromal AD, started at a mean age of 63 years (±12.8 years) and preceded MCI diagnosis by 4 to 7 years. At the stage of aMCI, median MMSE score was 26 and imaging showed mild hippocampal atrophy. After almost one year under treatment, cognitive complaints were not relieved but the MMSE score remained stable at 26 for 11 patients (2 patients were excluded from analysis because of the onset of aphasic or neurovisual symptoms altering MMSE scoring). CONCLUSION: Our data, in conjunction with those of the 12 previously described subjects, suggest the existence of a currently unrecognized inaugural epilepsy syndrome of sporadic AD. Such a syndrome could be called the epileptic variant of AD because seizures are its sole feature for more than 2.5 years.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Celine; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Evolution of the Antidepressant Prescribing in Alzheimer's Disease and Related Disorders Between 2010 and 2014: Results from the French National Database on Alzheimer's Disease (BNA). - David, Renaud; Manera, Valeria; Fabre, Roxane; Pradier, Christian; Robert, Philippe; Tifratene, Karim (J Alzheimers Dis, 2016)
BACKGROUND: Safety warnings from health authorities are currently intended to limit the use of psychotropic agents in dementia-related conditions. Evidence concerning the use of antidepressants in dementia is, however, scarce and contradictory. OBJECTIVE: To evaluate antidepressant use among individuals with Alzheimer's disease (AD) and related disorders in the French population between 2010 and 2014. METHOD: Antidepressant prescriptions in individuals with AD, mixed dementia (MD), and vascular dementia (VaD) in the French National Alzheimer Database between 2010 and 2014 were analyzed (N = 199,544). RESULTS: Multivariate analysis showed an annual significant increase (p < 0.001) in the prescription rate of antidepressants from 26% (2010) to 31% (2014), and identified female gender, younger age, higher education, living in long-term facilities, more severe cognitive decline, and presence of vascular signs (VaD and MD) as associated factors for antidepressant prescribing. CONCLUSION: The annual increase of antidepressant prescribing among individuals with AD, MD, and VaD in French specialized settings may be partially related to the lack of current valuable medications for dementia-related behavioral symptoms.

Excess Costs Associated with Possible Misdiagnosis of Alzheimer's Disease Among Patients with Vascular Dementia in a UK CPRD Population. - Happich, Michael; Kirson, Noam Y; Desai, Urvi; King, Sarah; Birnbaum, Howard G; Reed, Catherine; Belger, Mark; Lenox-Smith, Alan; Price, David (J Alzheimers Dis, 2016)
BACKGROUND: Prior diagnosis of Alzheimer's disease (AD) among patients later diagnosed with vascular dementia (VaD) has been associated with excess costs, suggesting potential benefits of earlier rule-out of AD diagnosis. OBJECTIVE: To investigate whether prior diagnosis with AD among patients with VaD is associated with excess costs in the UK. METHODS: Patients with a final VaD diagnosis, continuous data visibility for≥6 months prior to index date, and linkage to Hospital Episode Statistics data were retrospectively selected from de-identified Clinical Practice Research Datalink data. Patients with AD diagnosis before a final VaD diagnosis were matched to similar patients with no prior AD diagnosis using propensity score methods. Annual excess healthcare costs were calculated for 5 years post-index, stratified by time to final diagnosis. RESULTS: Of 9,311 patients with VaD, 508 (6%) had prior AD diagnosis with a median time to VaD diagnosis exceeding 2 years from index date. Over the entire follow-up period, patients with prior AD diagnosis had accumulated healthcare costs that were approximately GBP2,000 higher than those for matched counterparts (mostly due to higher hospitalization costs). Cost differentials peaked particularly in the period including the final VaD diagnosis, with excess costs quickly declining thereafter. CONCLUSION: Potential misdiagnosis of AD among UK patients with VaD resulted in substantial excess costs. The decline in excess costs following a final VaD diagnosis suggests potential benefits from earlier rule-out of AD.

Exercise Plus Cognitive Performance Over and Above Exercise Alone in Subjects with Mild Cognitive Impairment. - Sacco, Guillaume; Caillaud, Corinne; Ben Sadoun, Gregory; Robert, Philippe; David, Renaud; Brisswalter, Jeanick (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies highlight the relevance of regular exercise interventions to enhance or maintain neurocognitive function in subjects with cognitive impairments. OBJECTIVES: The aim of this study was to ascertain the effect of aerobic exercise associated with cognitive enrichment on cognitive performance in subjects with mild cognitive impairment (MCI). METHOD: Eight participants with MCI (72 ± 2 years) were enrolled in a 9-month study that consisted of two 3-months experimental interventions separated by a training cessation period of 3 months. The interventions included either aerobic exercise alone or aerobic exercise combined with cognitive enrichment. The exercise program involved two 20-min cycling exercise bouts per week at an intensity corresponding to 60% of the heart rate reserve. Cognitive performance was assessed using a task of single reaction time (SRT) and an inhibition task (Go-no-Go) before, immediately after, and 1 month after each intervention. RESULTS: The exercise intervention improved the speed of responses during the Go-no-Go task without any increase in errors. This improvement was enhanced by cognitive enrichment (6 ± 1% ; p >  0.05), when compared with exercise alone (4 ± 0.5% ,). Following exercise cessation, this positive effect disappeared. No effect was observed on SRT performance. CONCLUSION: Regular aerobic exercise improved cognitive performance in MCI subjects and the addition of cognitive tasks during exercise potentiated this effect. However, the influence of aerobic exercise on cognitive performance did not persist after cessation of training. Studies involving a larger number of subjects are necessary to confirm these results.
Keywords: Aged; Analysis of Variance; Cognitive Dysfunction; Cognitive Therapy; Exercise; Exercise Therapy; Female; Humans; Inhibition (Psychology); Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Reaction Time; Retrospective Studies; Treatment Outcome

Expression of the Alzheimer's Disease Mutations AβPP695sw and PSEN1M146I in Double-Transgenic Göttingen Minipigs. - Jakobsen, Jannik E; Johansen, Marianne G; Schmidt, Mette; Liu, Ying; Li, Rong; Callesen, Henrik; Melnikova, Margarita; Habekost, Mette; Matrone, Carmela; Bouter, Yvonne; Bayer, Thomas A; Nielsen, Anders Lade; et al. (J Alzheimers Dis, 2016)
Mutations in the amyloid-β protein precursor gene (AβPP), the presenilin 1 gene (PSEN1) or the presenilin 2 gene (PSEN2) that increase production of the AβPP-derived peptide Aβ42 cause early-onset Alzheimer's disease. Rodent models of the disease show that further increase in Aβ42 production and earlier brain pathology can be obtained by coexpressing AβPP and PSEN1 mutations. To generate such elevated Aβ42 level in a large animal model, we produced Göttingen minipigs carrying in their genome one copy of a human PSEN1 cDNA with the Met146Ile (PSEN1M146I) mutation and three copies of a human AβPP695 cDNA with the Lys670Asn/Met671Leu (AβPPsw) double-mutation. Both transgenes were expressed in fibroblasts and in the brain, and their respective proteins were processed normally. Immunohistochemical staining with Aβ42-specific antibodies detected intraneuronal accumulation of Aβ42 in brains from a 10- and an 18-month-old pig. Such accumulation may represent an early event in the pathogenesis of Alzheimer's disease.

Extracellular Tau Paired Helical Filaments Differentially Affect Tau Pathogenic Mechanisms in Mitotic and Post-Mitotic Cells: Implications for Mechanisms of Tau Propagation in the Brain. - Varghese, Merina; Santa-Maria, Ismael; Ho, Lap; Ward, Libby; Yemul, Shrishailam; Dubner, Lauren; Księżak-Reding, Hanna; Pasinetti, Giulio Maria (J Alzheimers Dis, 2016)
The release of paired helical filaments (PHFs) from neurons into the extracellular space may contribute to the propagation of tau pathology across brain regions in Alzheimer's disease (AD) and other tauopathies. The majority of available mechanistic studies exploring the pathologic role of extracellular PHFs are conducted in proliferating cell lines. Here, we compare how extracellular PHFs induce tauopathy in mitotic cells and in post-mitotic brain neurons. In a mitotic cell line (HEK 293T), extracellular exposure to AD PHFs leads to an intracellular "aggresomal" type deposition of tau, coincidental with redistribution of dynein, a retrograde motor protein. We also observed that PHFs impaired proteasome degradation, but not autophagy. Exposure of cells to proteasome inhibitors was sufficient to induce intracellular tau aggregate formation as well as reorganization of dynein and the intermediate filament protein, vimentin. Thus, in mitotic cells, extracellular PHFs promote cellular tau aggregation, in part, by interfering with cellular proteasome degradation processes. In contrast with our observations with proliferating cells, exposure of post-mitotic primary neuronal cultures to AD PHFs did not promote "aggresomal" tau deposition, but instead resulted in a widespread accumulation of phosphorylated tau-immunoreactive swellings in neuritic processes, characterized by disturbed cytoskeletal organization of dynein and vimentin. Collectively, our observations suggest that extracellular PHFs may contribute to the propagation of tau pathology by independent mechanisms in post-mitotic and mitotic brain cells. These outcomes indicate that in addition to post-mitotic brain neurons, mitotic brain cells should also be considered as targets for therapeutic interventions to attenuate propagation of tauopathy.

Fibrillar Amyloid-β Accumulation Triggers an Inflammatory Mechanism Leading to Hyperphosphorylation of the Carboxyl-Terminal End of Tau Polypeptide in the Hippocampal Formation of the 3×Tg-AD Transgenic Mouse. - Ontiveros-Torres, Miguel Ángel; Labra-Barrios, María Luisa; Díaz-Cintra, Sofía; Aguilar-Vázquez, Azucena Ruth; Moreno-Campuzano, Samadhi; Flores-Rodríguez, Paola; Luna-Herrera, Claudia; Mena, Raúl; Perry, George; Florán-Garduño, Benjamín; Luna-Muñoz, José; Luna-Arias, Juan Pedro (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a degenerative and irreversible disorder whose progressiveness is dependent on age. It is histopathologically characterized by the massive accumulation of insoluble forms of tau and amyloid-β (Aβ) asneurofibrillary tangles and neuritic plaques, respectively. Many studies have documented that these two polypeptides suffer several posttranslational modifications employing postmortem tissue sections from brains of patients with AD. In order to elucidate the molecular mechanisms underlying the posttranslational modifications of key players in this disease, including Aβ and tau, several transgenic mouse models have been developed. One of these models is the 3×Tg-AD transgenic mouse, carrying three transgenes encoding APPSWE, S1M146V, and TauP301L proteins. To further characterize this transgenicmouse, we determined the accumulation of fibrillar Aβ as a function of age in relation to the hyperphosphorylation patterns of TauP301L at both its N- and C-terminus in the hippocampal formation by immunofluorescence and confocal microscopy. Moreover, we searched for the expression of activated protein kinases and mediators of inflammation by western blot of wholeprotein extracts from hippocampal tissue sections since 3 to 28 months as well. Our results indicate that the presence of fibrillar Aβ deposits correlates with a significant activation of astrocytes and microglia in subiculum and CA1 regions of hippocampus. Accordingly, we also observed a significant increase in the expression of TNF-α associated to neuritic plaques and glial cells. Importantly, there is an overexpression of the stress activated protein kinases SAPK/JNK and Cdk-5 in pyramidal neurons, which might phosphorylate several residues at the C-terminus of TauP301L. Therefore, the accumulation of Aβ oligomers results in an inflammatory environment that upregulates kinases involved in hyperphosphorylation of TauP301L polypeptide.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Hippocampus; Humans; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroglia; Phosphorylation; Plaque, Amyloid; Presenilin-1; Pyramidal Cells; tau Proteins

Fluoxetine Treatment Induces Seizure Behavior and Premature Death in APPswe/PS1dE9 Mice. - Sierksma, Annerieke S R; de Nijs, Laurence; Hoogland, Govert; Vanmierlo, Tim; van Leeuwen, Fred W; Rutten, Bart P F; Steinbusch, Harry W M; Prickaerts, Jos; van den Hove, Daniel L A (J Alzheimers Dis, 2016)
Treatment of Alzheimer's disease (AD) patients with the antidepressant fluoxetine is known to improve memory and cognitive function. However, the mechanisms underlying these effects are largely unknown. To unravel these mechanisms, we aimed to treat APPswe/PS1dE9 mice with fluoxetine. Unexpectedly, with time, an increased number of animals displayed seizure behavior and died. Although spontaneous behavioral seizures have been reported previously in this mouse model, the observation of seizures and death consequential to fluoxetine treatment is new. Our results warrant further research on the underlying mechanisms as this may refine the treatment of AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anticonvulsants; Body Weight; Disease Models, Animal; Fluoxetine; Humans; Logistic Models; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Presenilin-1; Seizures

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

FTIR and Raman Spectroscopy Applied to Dementia Diagnosis Through Analysis of Biological Fluids. - Lopes, Jéssica; Correia, Marta; Martins, Ilka; Henriques, Ana Gabriela; Delgadillo, Ivonne; da Cruz E Silva, Odete; Nunes, Alexandra (J Alzheimers Dis, 2016)
To date, it is still difficult to perform an early and accurate diagnosis of dementia, therefore significant research has focused on finding new dementia biomarkers that can aid in this respect. There is an urgent need for non-invasive, rapid, and relatively inexpensive procedures for early diagnostics. Studies have demonstrated that of spectroscopic techniques, such as Fourier Transform Infrared Spectroscopy (FTIR) and Raman Spectroscopy could be a useful and accurate procedure to diagnose dementia. Given that several biochemical mechanisms related to neurodegeneration and dementia can lead to changes in plasma components and others peripheral body fluids; blood-based samples coupled to spectroscopic analyses can be used as a simple and less invasive approach.

Functional Connectivity of Ventral and Dorsal Visual Streams in Posterior Cortical Atrophy. - Migliaccio, Raffaella; Gallea, Cécile; Kas, Aurélie; Perlbarg, Vincent; Samri, Dalila; Trotta, Laura; Michon, Agnès; Lacomblez, Lucette; Dubois, Bruno; Lehéricy, Stéphane; Bartolomeo, Paolo (J Alzheimers Dis, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) induces progressive dysfunction of ventral and dorsal visual networks. Little is known, however, about corresponding changes in functional connectivity (FC). OBJECTIVES: To investigate FC changes in the visual networks, their relationship with cortical atrophy, and the association with Alzheimer's disease (AD) pathology. METHODS: Ten PCA patients and 28 age-matched controls participated in the study. Using resting state fMRI, we measured FC in ventral and dorsal cortical visual networks, defined on the basis of a priori knowledge of long-range white matter connections. To assess the relationships with AD, we determined AD biomarkers in cerebrospinal fluid and FC in the default mode network (DMN), which is vulnerable to AD pathology. Voxel-based morphometry analysis assessed the pattern of grey matter (GM) atrophy. RESULTS: PCA patients showed GM atrophy in bilateral occipital and inferior parietal regions. PCA patients had lower FC levels in a ventral network than controls, but higher FC in inferior components of the dorsal network. In particular, the increased connectivity correlated with greater GM atrophy in occipital regions. All PCA patients had positive cerebrospinal fluid biomarkers for AD; however, FC in global DMN did not differ from controls. CONCLUSIONS: FC in PCA reflects brain structure in a non-univocal way. Hyperconnectivity of dorsal networks may indicate aberrant communication in response to posterior brain atrophy or processes of neural resilience during the initial stage of brain dysfunction. The lack of difference from controls in global DMN FC highlights the atypical nature of PCA with respect to typical AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Case-Control Studies; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Oxygen; Visual Pathways

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Halting of Caspase Activity Protects Tau from MC1-Conformational Change and Aggregation. - Mead, Emma; Kestoras, Dimitra; Gibson, Yolanda; Hamilton, Lucy; Goodson, Ross; Jones, Sophie; Eversden, Sarah; Davies, Peter; O'Neill, Michael; Hutton, Michael; Szekeres, Philip; Wolak, Joanna (J Alzheimers Dis, 2016)
Intracellular neurofibrillary tangles (NFTs) are the hallmark of Alzheimer's disease and other tauopathies in which tau, a microtubule-associated protein, loses its ability to stabilize microtubules. Several post-translational modifications including phosphorylation and truncation increase tau's propensity to aggregate thus forming NFTs; however, the mechanisms underlying tau conformational change and aggregation still remain to be defined. Caspase activation and subsequent proteolytic cleavage of tau is thought to be a potential trigger of this disease-related pathological conformation. The aim of this work was to investigate the link between caspase activation and a disease-related conformational change of tau in a neuroblastoma cell-based model of spontaneous tau aggregation. We demonstrated that caspase induction initiates proteolytic cleavage of tau and generation of conformationally altered and aggregated tau recognized by the MC1 conformational antibody. Most importantly, these events were shown to be attenuated with caspase inhibitors. This implies that therapeutics aimed at inhibiting caspase-mediated tau cleavage may prove beneficial in slowing cleavage and aggregation, thus potentially halting tau pathology and disease progression.

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Hierarchical Distribution of the Tau Cytoskeletal Pathology in the Thalamus of Alzheimer's Disease Patients. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Del Turco, Domenico; Ghebremedhin, Estifanos; Seidel, Kay; den Dunnen, Wilfred; Korf, Horst-Werner (J Alzheimers Dis, 2016)
In spite of considerable progress in neuropathological research on Alzheimer's disease (AD), knowledge regarding the exact pathoanatomical distribution of the tau cytoskeletal pathology in the thalamus of AD patients in the advanced Braak and Braak AD stages V or VI of the cortical cytoskeletal pathology is still fragmentary. Investigation of serial 100 μm-thick brain tissue sections through the thalamus of clinically diagnosed AD patients with Braak and Braak AD stage V or VI cytoskeletal pathologies immunostained with the anti-tau AT8 antibody, along with the affection of the extraterritorial reticular nucleus of the thalamus, reveals a consistent and severe tau immunoreactive cytoskeletal pathology in the limbic nuclei of the thalamus (e.g., paraventricular, anterodorsal and laterodorsal nuclei, limitans-suprageniculate complex). The thalamic nuclei integrated into the associative networks of the human brain (e.g., ventral anterior and mediodorsal nuclei) are only mildly affected, while its motor precerebellar (ventral lateral nucleus) and sensory nuclei (e.g., lateral and medial geniculate bodies, ventral posterior medial and lateral nuclei, parvocellular part of the ventral posterior medial nucleus) are more or less spared. The highly stereotypical and characteristic thalamic distribution pattern of the AD-related tau cytoskeletal pathology represents an anatomical mirror of the hierarchical topographic distribution of the cytoskeletal pathology in the interconnected regions of the cerebral cortex of AD patients. These pathoanatomical parallels support the pathophysiological concept of a transneuronal spread of the disease process of AD along anatomical pathways. The AD-related tau cytoskeletal pathology in the thalamus most likely contributes substantially to the neuropsychiatric disease symptoms (e.g., dementia), attention deficits, oculomotor dysfunctions, altered non-discriminative aspects of pain experience of AD patients, and the disruption of their waking and sleeping patterns.
Keywords: Alzheimer Disease; Cytoskeleton; Humans; tau Proteins; Thalamus

High-Throughput Screening for Identification of Blood-Brain Barrier Integrity Enhancers: A Drug Repurposing Opportunity to Rectify Vascular Amyloid Toxicity. - Qosa, Hisham; Mohamed, Loqman A; Al Rihani, Sweilem B; Batarseh, Yazan S; Duong, Quoc-Viet; Keller, Jeffrey N; Kaddoumi, Amal (J Alzheimers Dis, 2016)
The blood-brain barrier (BBB) is a dynamic interface that maintains brain homeostasis and protects it from free entry of chemicals, toxins, and drugs. The barrier function of the BBB is maintained mainly by capillary endothelial cells that physically separate brain from blood. Several neurological diseases, such as Alzheimer's disease (AD), are known to disrupt BBB integrity. In this study, a high-throughput screening (HTS) was developed to identify drugs that rectify/protect BBB integrity from vascular amyloid toxicity associated with AD progression. Assessing Lucifer Yellow permeation across in-vitro BBB model composed from mouse brain endothelial cells (bEnd3) grown on 96-well plate inserts was used to screen 1280 compounds of Sigma LOPAC®1280 library for modulators of bEnd3 monolayer integrity. HTS identified 62 compounds as disruptors, and 50 compounds as enhancers of the endothelial barrier integrity. From these 50 enhancers, 7 FDA approved drugs were identified with EC50 values ranging from 0.76-4.56 μM. Of these 7 drugs, 5 were able to protect bEnd3-based BBB model integrity against amyloid toxicity. Furthermore, to test the translational potential to humans, the 7 drugs were tested for their ability to rectify the disruptive effect of Aβ in the human endothelial cell line hCMEC/D3. Only 3 (etodolac, granisetron, and beclomethasone) out of the 5 effective drugs in the bEnd3-based BBB model demonstrated a promising effect to protect the hCMEC/D3-based BBB model integrity. These drugs are compelling candidates for repurposing as therapeutic agents that could rectify dysfunctional BBB associated with AD.

Hippocampal Lipid Homeostasis in APP/PS1 Mice is Modulated by a Complex Interplay Between Dietary DHA and Estrogens: Relevance for Alzheimer's Disease. - Díaz, Mario; Fabelo, Noemí; Casañas-Sánchez, Verónica; Marin, Raquel; Gómez, Tomás; Quinto-Alemany, David; Pérez, José A (J Alzheimers Dis, 2016)
Current evidence suggests that lipid homeostasis in the hippocampus is affected by different genetic, dietary, and hormonal factors, and that its deregulation may be associated with the onset and progression of Alzheimer's disease (AD). However, the precise levels of influence of each of these factors and their potential interactions remain largely unknown, particularly during neurodegenerative processes. In the present study, we have performed multifactorial analyses of the combined effects of diets containing different doses of docosahexaenoic acid (DHA), estrogen status (ovariectomized animals receiving vehicle or 17β-estradiol), and genotype (wild-type or transgenic APP/PS1 mice) in hippocampal lipid profiles. We have observed that the three factors affect lipid classes and fatty acid composition to different extents, and that strong interactions between these factors exist. The most aberrant lipid profiles were observed in APP/PS1 animals receiving DHA-poor diets and deprived of estrogens. Conversely, wild-type animals under a high-DHA diet and receiving estradiol exhibited a lipid profile that closely resembled that of the hippocampus of control animals. Interestingly, though the lipid signatures of APP/PS1 hippocampi markedly differed from wild-type, administration of a high-DHA diet in the presence of estrogens gave rise to a lipid profile that approached that of control animals. Paralleling changes in lipid composition, patterns of gene expression of enzymes involved in lipid biosynthesis were also altered and affected by combination of experimental factors. Overall, these results indicate that hippocampal lipid homeostasis is strongly affected by hormonal and dietary conditions, and that manipulation of these factors might be incorporated in AD therapeutics.
Keywords: Acyl Coenzyme A; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Disease Models, Animal; Docosahexaenoic Acids; Dose-Response Relationship, Drug; Estrogens; Gene Expression Regulation; Hippocampus; Homeostasis; Humans; Lipid Metabolism; Mice; Mice, Transgenic; Mutation; Presenilin-1; RNA, Messenger

Human ApoE ɛ2 Promotes Regulatory Mechanisms of Bioenergetic and Synaptic Function in Female Brain: A Focus on V-type H+-ATPase. - Woody, Sarah K; Zhou, Helen; Ibrahimi, Shaher; Dong, Yafeng; Zhao, Liqin (J Alzheimers Dis, 2016)
Humans possess three major isoforms of the apolipoprotein E (ApoE) gene encoded by three alleles: ApoE ɛ2 (ApoE2), ApoE ɛ3 (ApoE3), and ApoE ɛ4 (ApoE4). It is established that the three ApoE isoforms confer differential susceptibility to Alzheimer's disease (AD); however, an in-depth molecular understanding of the underlying mechanisms is currently unavailable. In this study, we examined the cortical proteome differences among the three ApoE isoforms using 6-month-old female, human ApoE2, ApoE3, and ApoE4 gene-targeted replacement mice and two-dimensional proteomic analyses. The results reveal that the three ApoE brains differ primarily in two areas: cellular bioenergetics and synaptic transmission. Of particular significance, we show for the first time that the three ApoE brains differentially express a key component of the catalytic domain of the V-type H+-ATPase (Atp6v), a proton pump that mediates the concentration of neurotransmitters into synaptic vesicles and thus is crucial in synaptic transmission. Specifically, our data demonstrate that ApoE2 brain exhibits significantly higher levels of the B subunit of Atp6v (Atp6v1B2) when compared to both ApoE3 and ApoE4 brains, with ApoE4 brain exhibiting the lowest expression. Our additional analyses show that Atp6v1B2 is significantly impacted by aging and AD pathology and the data suggest that Atp6v1B2 deficiency could be involved in the progressive loss of synaptic integrity during early development of AD. Collectively, our findings indicate that human ApoE isoforms differentially modulate regulatory mechanisms of bioenergetic and synaptic function in female brain. A more efficient and robust status in both areas-in which Atp6v may play a role-could serve as a potential mechanism contributing to the neuroprotective and cognition-favoring properties associated with the ApoE2 genotype.

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

Immunization Against Specific Fragments of Neurotrophin p75 Receptor Protects Forebrain Cholinergic Neurons in the Olfactory Bulbectomized Mice. - Bobkova, Natalia; Vorobyov, Vasily; Medvinskaya, Natalia; Nesterova, Inna; Tatarnikova, Olga; Nekrasov, Pavel; Samokhin, Alexander; Deev, Alexander; Sengpiel, Frank; Koroev, Dmitry; Volpina, Olga (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by progressive cognitive impairment associated with marked cholinergic neuron loss and amyloid-β (Aβ) peptide accumulation in the brain. The cytotoxicity in AD is mediated, at least in part, by Aβ binding with the extracellular domain of the p75 neurotrophin receptor (p75NTR), localized predominantly in the membranes of acetylcholine-producing neurons in the basal forebrain. Hypothesizing that an open unstructured loop of p75NTR might be the effective site for Aβ binding, we have immunized both olfactory bulbectomized (OBX) and sham-operated (SO) mice (n = 82 and 49, respectively) with synthetic peptides, structurally similar to different parts of the loops, aiming to block them by specific antibodies. OBX-mice have been shown in previous studies, and confirmed in the present one, to be characterized by typical behavioral, morphological, and biochemical AD hallmarks, including cholinergic deficits in forebrain neurons. Immunization of OBX- or SO-mice with KLH conjugated fragments of p75NTR induced high titers of specific serum antibodies for each of nine chosen fragments. However, maximal protective effects on spatial memory, evaluated in a Morris water maze, and on activity of choline acetyltransferase in forebrain neurons, detected by immunoreactivity to specific antibodies, were revealed only for peptides with amino acid residue sequences of 155-164 and 167-176. We conclude that the approach based on immunological blockade of specific p75NTR sites, linked with the cytotoxicity, is a useful and effective tool for study of AD-associated mechanisms and for development of highly selective therapy of cholinergic malfunctioning in AD patients.

Immunization with Small Amyloid-β-derived Cyclopeptide Conjugates Diminishes Amyloid-β-Induced Neurodegeneration in Mice. - Mulder, Cornelis K; Dong, Yun; Brugghe, Humphrey F; Timmermans, Hans A M; Tilstra, Wichard; Westdijk, Janny; van Riet, Elly; van Steeg, Harry; Hoogerhout, Peter; Eisel, Ulrich L M (J Alzheimers Dis, 2016)
BACKGROUND: Soluble oligomeric (misfolded) species of amyloid-β (Aβ) are the main mediators of toxicity in Alzheimer's disease (AD). These oligomers subsequently form aggregates of insoluble fibrils that precipitate as extracellular and perivascular plaques in the brain. Active immunization against Aβ is a promising disease modifying strategy. However, eliciting an immune response against Aβ in general may interfere with its biological function and was shown to cause unwanted side-effects. Therefore, we have developed a novel experimental vaccine based on conformational neo-epitopes that are exposed in the misfolded oligomeric Aβ, inducing a specific antibody response. OBJECTIVE: Here we investigate the protective effects of the experimental vaccine against oligomeric Aβ1-42-induced neuronal fiber loss in vivo. METHODS: C57BL/6 mice were immunized or mock-immunized. Antibody responses were measured by enzyme-linked immunosorbent assay. Next, mice received a stereotactic injection of oligomeric Aβ1-42 into the nucleus basalis of Meynert (NBM) on one side of the brain (lesion side), and scrambled Aβ1-42 peptide in the contralateral NBM (control side). The densities of choline acetyltransferase-stained cholinergic fibers origination from the NBM were measured in the parietal neocortex postmortem. The percentage of fiber loss in the lesion side was determined relative to the control side of the brain. RESULTS: Immunized responders (79%) showed 23% less cholinergic fiber loss (p = 0.01) relative to mock-immunized mice. Moreover, fiber loss in immunized responders correlated negatively with the measured antibody responses (R2 = 0.29, p = 0.02). CONCLUSION: These results may provide a lead towards a (prophylactic) vaccine to prevent or at least attenuate (early onset) AD symptoms.

Impaired Parahippocampus Connectivity in Mild Cognitive Impairment and Alzheimer's Disease. - Liu, Jieqiong; Zhang, Xinqing; Yu, Chunshui; Duan, Yunyun; Zhuo, Junjie; Cui, Yue; Liu, Bing; Li, Kuncheng; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
BACKGROUND: The parahippocampal gyrus (PHG) is an important region of the limbic system that plays an important role in episodic memory. Elucidation of the PHG connectivity pattern will aid in the understanding of memory deficits in neurodegenerative diseases. OBJECTIVE: To investigate if disease severity associated altered PHG connectivity in Alzheimer's disease (AD) exists. METHODS: We evaluated resting-state functional magnetic resonance imaging data from 18 patients with amnestic mild cognitive impairment (MCI), 35 patients with AD, and 21 controls. The PHG connectivity pattern was examined by calculating Pearson's correlation coefficients between the bilateral PHG and whole brain. Group comparisons were performed after controlling for the effects of age and gender. The functional connectivity strength in each identified region was correlated with the MMSE score to evaluate the relationship between connectivity and cognitive ability. RESULTS: Several brain regions of the default mode network showed reduced PHG connectivity in the AD patients, and PHG connectivity was associated with disease severity in the MCI and AD subjects. More importantly, correlation analyses showed that there were positive correlations between the connectivity strengths of the left PHG-PCC/Pcu and left PHG-left MTG and the Mini-Mental State Examination, indicating that with disease progression from MCI to severe AD, damage to the functional connectivity of the PHG becomes increasingly severe. CONCLUSIONS: These results indicate that disease severity is associated with altered PHG connectivity, contributing to knowledge about the reduction in cognitive ability and impaired brain activity that occur in AD/MCI. These early changes in the functional connectivity of the PHG might provide some potential clues for identification of imaging markers for the early detection of MCI and AD.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Brain Mapping; Cognitive Dysfunction; Female; Hippocampus; Humans; Limbic System; Magnetic Resonance Imaging; Male; Mental Status Schedule; Neural Pathways; Rest; Severity of Illness Index

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Integrated Analysis of Alzheimer's Disease and Schizophrenia Dataset Revealed Different Expression Pattern in Learning and Memory. - Li, Wen-Xing; Dai, Shao-Xing; Liu, Jia-Qian; Wang, Qian; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) and schizophrenia (SZ) are both accompanied by impaired learning and memory functions. This study aims to explore the expression profiles of learning or memory genes between AD and SZ. We downloaded 10 AD and 10 SZ datasets from GEO-NCBI for integrated analysis. These datasets were processed using RMA algorithm and a global renormalization for all studies. Then Empirical Bayes algorithm was used to find the differentially expressed genes between patients and controls. The results showed that most of the differentially expressed genes were related to AD whereas the gene expression profile was little affected in the SZ. Furthermore, in the aspects of the number of differentially expressed genes, the fold change and the brain region, there was a great difference in the expression of learning or memory related genes between AD and SZ. In AD, the CALB1, GABRA5, and TAC1 were significantly downregulated in whole brain, frontal lobe, temporal lobe, and hippocampus. However, in SZ, only two genes CRHBP and CX3CR1 were downregulated in hippocampus, and other brain regions were not affected. The effect of these genes on learning or memory impairment has been widely studied. It was suggested that these genes may play a crucial role in AD or SZ pathogenesis. The different gene expression patterns between AD and SZ on learning and memory functions in different brain regions revealed in our study may help to understand the different mechanism between two diseases.
Keywords: Adult; Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Bayes Theorem; Brain; Datasets as Topic; Gene Expression Profiling; Humans; Learning; Memory; Microarray Analysis; Middle Aged; Schizophrenia; Schizophrenic Psychology; Young Adult

Interaction Between Midlife Blood Glucose and APOE Genotype Predicts Later Alzheimer's Disease Pathology. - Bangen, Katherine J; Himali, Jayandra J; Beiser, Alexa S; Nation, Daniel A; Libon, David J; Fox, Caroline S; Seshadri, Sudha; Wolf, Philip A; McKee, Ann C; Au, Rhoda; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
Elevated blood glucose and the apolipoprotein (APOE) ɛ4 allele have both been associated with increased dementia risk; however, the neuropathological mechanisms underlying these associations remain unclear. We examined the impact of APOE genotype and midlife blood glucose on post-mortem vascular and Alzheimer's disease (AD) neuropathology. Ninety-four participants from the Framingham Heart Study without diagnosed diabetes underwent health examination at midlife and brain autopsy at death. Histopathological measures of vascular and AD neuropathology were obtained and analyzed. Results demonstrated that, among APOE ɛ4 carriers, elevated blood glucose was associated with more severe AD pathology. There was no such relationship with vascular pathology. In a relatively healthy sample with low vascular risk burden, midlife elevated blood glucose was associated with greater AD pathology among APOE ɛ4 carriers. A better understanding of interactive effects of APOE genotype and vascular risk on neuropathology has implications for identification of individuals at risk for decline and long-term preventive treatment.

Intraneuronal Amylin Deposition, Peroxidative Membrane Injury and Increased IL-1β Synthesis in Brains of Alzheimer's Disease Patients with Type-2 Diabetes and in Diabetic HIP Rats. - Verma, Nirmal; Ly, Han; Liu, Miao; Chen, Jing; Zhu, Haining; Chow, Martin; Hersh, Louis B; Despa, Florin (J Alzheimers Dis, 2016)
Amylin is a hormone synthesized and co-secreted with insulin by pancreatic β-cells that crosses the blood-brain barrier and regulates satiety. Amylin from humans (but not rodents) has an increased propensity to aggregate into pancreatic islet amyloid deposits that contribute to β-cell mass depletion and development of type-2 diabetes by inducing oxidative stress and inflammation. Recent studies demonstrated that aggregated amylin also accumulates in brains of Alzheimer's disease (AD) patients, preponderantly those with type-2 diabetes. Here, we report that, in addition to amylin plaques and mixed amylin-Aβ deposits, brains of diabetic patients with AD show amylin immunoreactive deposits inside the neurons. Neuronal amylin formed adducts with 4-hydroxynonenal (4-HNE), a marker of peroxidative membrane injury, and increased synthesis of the proinflammatory cytokine interleukin (IL)-1β. These pathological changes were mirrored in rats expressing human amylin in pancreatic islets (HIP rats) and mice intravenously injected with aggregated human amylin, but not in hyperglycemic rats secreting wild-type non-amyloidogenic rat amylin. In cultured primary hippocampal rat neurons, aggregated amylin increased IL-1β synthesis via membrane destabilization and subsequent generation of 4-HNE. These effects were blocked by membrane stabilizers and lipid peroxidation inhibitors. Thus, elevated circulating levels of aggregated amylin negatively affect the neurons causing peroxidative membrane injury and aberrant inflammatory responses independent of other confounding factors of diabetes. The present results are consistent with the pathological role of aggregated amylin in the pancreas, demonstrate a novel contributing mechanism to neurodegeneration, and suggest a direct, potentially treatable link of type-2 diabetes with AD.

Iron Regulates Apolipoprotein E Expression and Secretion in Neurons and Astrocytes. - Xu, He; Perreau, Victoria M; Dent, Krista A; Bush, Ashley I; Finkelstein, David I; Adlard, Paul A (J Alzheimers Dis, 2016)
BACKGROUND: There is strong evidence that iron homeostasis is impaired in the aging and Alzheimer's disease (AD) brain and that this contributes to neurodegeneration. Apolipoprotein E (APOE) has been identified as the strongest genetic risk factor for AD. However, the interaction between the two has yet to be fully explored. OBJECTIVE: This study aimed to investigate the relationship between exogenous iron levels and ApoE in neurons and astrocytes. METHODS: Our study used primary cultured cortical neurons and astrocytes to investigate the changes in ApoE caused by iron. Western blot and RT-PCR were used to measure ApoE. RESULTS: We observed that iron upregulated intracellular ApoE levels in both neurons and astrocytes at the post-transcriptional and transcriptional level, respectively. However, there was less full-length ApoE secreted by neurons and astrocytes after iron treatment. We speculate that this might impair brain lipid metabolism and amyloid-β clearance. In terms of ApoE receptors, we observed that neuronal LRP-1 levels were increased by the addition of exogenous iron, which could contribute to AβPP endocytosis in neurons. However, there were no significant changes in neuronal LDLR, astrocyte LDLR, or astrocyte LRP-1. CONCLUSION: Our study reveals that iron may contribute to the pathogenesis of AD by affecting ApoE and its receptors and supports the notion that iron chelation should be investigated as a therapeutic strategy for AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Blotting, Western; Cell Survival; Cells, Cultured; Cerebral Cortex; Copper; Ferritins; Immunohistochemistry; Iron; Mice, Inbred C57BL; Neurons; Polymerase Chain Reaction; Reactive Oxygen Species; Receptors, LDL; RNA, Messenger; Tumor Suppressor Proteins; Zinc

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

A Late Life Risk Index for Severe Cognitive Impairment in Mexico. - Downer, Brian; Veeranki, Sreenivas P; Wong, Rebeca (J Alzheimers Dis, 2016)
BACKGROUND: Several dementia risk indices have been developed for older adults in high-income countries. However, no index has been developed for populations in low- or middle-income countries. OBJECTIVE: To create a risk index for predicting severe cognitive impairment among adults aged ≥60 in Mexico and to compare the accuracy of this index to the Dementia Screening Indicator (DSI). METHODS: This study included 3,002 participants from the Mexican Health and Aging Study (MHAS) interviewed in 2001 and 2012. The MHAS risk index included sociodemographic, health, and functional characteristics collected in 2001. A point value based on the beta coefficients from a multivariable logistic regression model was assigned to each risk factor and the total score was calculated. RESULTS: The MHAS risk index (AUC = 0.74 95% CI = 0.70-0.77) and DSI (AUC = 0.72 95% CI = 0.69-0.77) had similar accuracy for discriminating between participants who developed severe cognitive impairment from those who did not. A score of ≥16 on the MHAS risk index had a sensitivity of 0.69 (95% CI = 0.64-0.70) and specificity of 0.67 (95% CI = 0.66-0.69). A score of ≥23 on the DSI had a sensitivity of 0.56 (95% CI = 0.50-0.63) and specificity of 0.78 (95% CI = 0.76-0.79). DISCUSSION: The MHAS risk index and DSI have moderate accuracy for predicting severe cognitive impairment among older adults in Mexico. This provides evidence that existing dementia risk indices may be applicable in low- and middle-income countries such as Mexico. Future research should seek to identify additional risk factors that can improve the accuracy of the MHAS risk index.
Keywords: Age Factors; Aged; Cognitive Dysfunction; Female; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Mexico; Middle Aged; Multivariate Analysis; Risk Factors; Social Behavior; Socioeconomic Factors

Less Daily Computer Use is Related to Smaller Hippocampal Volumes in Cognitively Intact Elderly. - Silbert, Lisa C; Dodge, Hiroko H; Lahna, David; Promjunyakul, Nutta-On; Austin, Daniel; Mattek, Nora; Erten-Lyons, Deniz; Kaye, Jeffrey A (J Alzheimers Dis, 2016)
BACKGROUND: Computer use is becoming a common activity in the daily life of older individuals and declines over time in those with mild cognitive impairment (MCI). The relationship between daily computer use (DCU) and imaging markers of neurodegeneration is unknown. OBJECTIVE: The objective of this study was to examine the relationship between average DCU and volumetric markers of neurodegeneration on brain MRI. METHODS: Cognitively intact volunteers enrolled in the Intelligent Systems for Assessing Aging Change study underwent MRI. Total in-home computer use per day was calculated using mouse movement detection and averaged over a one-month period surrounding the MRI. Spearman's rank order correlation (univariate analysis) and linear regression models (multivariate analysis) examined hippocampal, gray matter (GM), white matter hyperintensity (WMH), and ventricular cerebral spinal fluid (vCSF) volumes in relation to DCU. A voxel-based morphometry analysis identified relationships between regional GM density and DCU. RESULTS: Twenty-seven cognitively intact participants used their computer for 51.3 minutes per day on average. Less DCU was associated with smaller hippocampal volumes (r = 0.48, p = 0.01), but not total GM, WMH, or vCSF volumes. After adjusting for age, education, and gender, less DCU remained associated with smaller hippocampal volume (p = 0.01). Voxel-wise analysis demonstrated that less daily computer use was associated with decreased GM density in the bilateral hippocampi and temporal lobes. CONCLUSIONS: Less daily computer use is associated with smaller brain volume in regions that are integral to memory function and known to be involved early with Alzheimer's pathology and conversion to dementia. Continuous monitoring of daily computer use may detect signs of preclinical neurodegeneration in older individuals at risk for dementia.

Life's Simple 7's Cardiovascular Health Metrics are Associated with Hispanic/Latino Neurocognitive Function: HCHS/SOL Results. - González, Hector M; Tarraf, Wassim; Gouskova, Natalia; Rodríguez, Carlos J; Rundek, Tatjana; Grober, Ellen; Pirzada, Amber; González, Patricia; Lutsey, Pamela L; Camacho, Alvaro; Daviglus, Martha L; Wright, Clinton; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Hispanics/Latinos are purportedly at increased risk for neurocognitive decline and dementias. Without dementia cures, low-cost, well-tolerated public health means for mitigating neurocognitive decline are needed. OBJECTIVE: We examined associations between neurocognition and cardiovascular health (CVH) metrics (Life's Simple 7; LS7) among diverse Hispanics/Latinos. We hypothesized that higher LS7 would be associated with healthier brain function (neurocognitive performance). METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; N = 9,623; ages 45-74 years) to examine neurocognition in relation to CVH LS7 scores. RESULTS: In age and sex adjusted models, a one unit LS7 score increase (range = 0-14) was associated with higher neurocognitive function on the B-SEVLT sum (0.23 [p < 0.01]; range = 3-42), B-SEVLT recall (0.12 [p < 0.01]; range = 0-15), Word Fluency (phonemic; 0.46 (p < 0.01); range = 0-49), and Digit Symbol Substitution (0.49 (p < 0.01); range = 0-83) tests, respectively. Stated differently, a change from the minimum LS7 (0) to maximum LS7 (14) score corresponded to higher scores on verbal learning (4.62) and memory (2.24), verbal fluency (7.0), and psychomotor processing speed (12). In fully adjusted models the associations were attenuated, but remained statistically significant. Incremental adjustments indicated that Latino background and, to a lesser extent, education were primary contributors to the evinced attenuations. CONCLUSIONS: We found that higher neurocognitive function was associated with better LS7 CVH metrics among middle-aged and older Hispanics/Latinos. Associations between neurocognitive function and LS7 were strongest among two at-risk groups for neurocognitive decline and dementia, women and Hispanics/Latinos with lower education. Public health efforts to reduce cardiovascular disease morbidity and mortality may have additional neurocognitive benefits among at-risk Hispanics/Latinos.

Limiting Factors of Brain Donation in Neurodegenerative Diseases: The Example of French Memory Clinics. - Le Bouc, Raphael; Marelli, Cecilia; Beaufils, Emilie; Berr, Claudine; Hommet, Caroline; Touchon, Jacques; Pasquier, Florence; Deramecourt, Vincent (J Alzheimers Dis, 2016)
Postmortem neuropathological examination of the brain is essential in neurodegenerative diseases, to ensure accurate diagnosis, to obtain an a posteriori critical assessment of the adequacy of clinical care, and to validate new biomarkers, but is only rarely performed. The purpose of this study was to assess factors limiting brain donation, such as reluctance of physicians to seek donation consent, opposition from patients and families, and organizational constraints. We conducted a survey across French memory clinics and major neuropathological centers. Few postmortem examinations were performed annually, as less than one third of the centers had performed at least five autopsies, and 41% had performed none. The main limiting factor was the lack of donation requests made by physicians, as half of them never approach patients for brain donation. Reasons for not seeking donation consent often include discomfort broaching the subject and lack of awareness of the medical and scientific benefit of postmortems (77%), organizational constraints (61%), and overestimation of families' negative reaction (51%). Family refusals represented a second major obstacle, and were often caused by misconceptions. Identifying and addressing these biases early could help improve physicians' rate of making requests and the public's awareness about the importance of brain donation.
Keywords: Autopsy; Brain; France; Health Knowledge, Attitudes, Practice; Humans; Neurodegenerative Diseases; Physicians; Retrospective Studies

Living Alone with Dementia: Prevalence, Correlates and the Utilization of Health and Nursing Care Services. - Eichler, Tilly; Hoffmann, Wolfgang; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Dreier, Adina; Thyrian, Jochen René (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about the proportion and the characteristics of community-dwelling people with dementia (PWD) living alone in Germany. OBJECTIVES: To analyze the prevalence of PWD living alone (with and without the support of an informal caregiver) and socio-demographical and clinical characteristics as well as health and nursing care utilization associated with living alone. METHODS: DelpHi-MV (Dementia: Life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, randomized controlled intervention trial. The present analyses are based on baseline data of 511 patients (≥70 years, community-dwelling) who had screened positive for dementia (DemTect <9). RESULTS: N = 251 (51%) of the patients lived alone. PWD living alone were statistically significantly more often female, older, and more often widowed than those not living alone. About 9% of the patients (n = 24) were not supported by any informal caregiver. Regarding the clinical variables (cognitive and functional impairment, depression, falls, number of drug-related problems, malnutrition, quality of life), there were no statistically significant group differences. Patients living alone utilized professional services such as home care, help with medication, home-delivered meals, or housekeeping assistance significantly more often. Multivariate analyses confirmed these findings. CONCLUSION: Our results reveal the high proportion of PWD living alone in Germany. PWD living alone did not seem to be at an increased health risk. Our findings indicate that living alone with dementia is possible. In order to ensure the sufficient provision of health and nursing care services for PWD living alone, providers should consider the present results for future planning.

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Looking for Neuroimaging Markers in Frontotemporal Lobar Degeneration Clinical Trials: A Multi-Voxel Pattern Analysis Study in Granulin Disease. - Premi, Enrico; Cauda, Franco; Costa, Tommaso; Diano, Matteo; Gazzina, Stefano; Gualeni, Vera; Alberici, Antonella; Archetti, Silvana; Magoni, Mauro; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
In light of future pharmacological interventions, neuroimaging markers able to assess the response to treatment would be crucial. In Granulin (GRN) disease, preclinical data will prompt pharmacological trials in the future. Two main points need to be assessed: (1) to identify target regions in different disease stages and (2) to determine the most accurate functional and structural neuroimaging index to be used. To this aim, we have taken advantage of the multivariate approach of multi-voxel pattern analysis (MVPA) to explore the information of brain activity patterns in a cohort of GRN Thr272fs carriers at different disease stages (14 frontotemporal dementia (FTD) patients and 17 asymptomatic carriers) and a group of 33 healthy controls. We studied structural changes by voxel-based morphometry (VBM), functional connectivity by assessing salience, default mode, fronto-parietal, dorsal attentional, executive networks, and local connectivity by regional homogeneity, amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), degree centrality, and voxel-mirrored homotopic connectivity. In FTD patients with GRN mutation, the most predictive measure was VBM structural analysis, while in asymptomatic carriers the best predictor marker was the local connectivity measure (fALFF). Altogether, all indexes demonstrated fronto-temporo-parietal damage in GRN pathology, with widespread structural damage of fronto-parietal and temporal regions when disease is overt. MVPA could be of aid in identifying the most accurate neuroimaging marker for clinical trials. This approach was able to identify both the target region and the best neuroimaging approach, which would be specific in the different disease stages. Further studies are needed to simultaneously integrate multimodal indexes in a classifier able to trace the disease progression moving from preclinical to clinical stage of the disease.
Keywords: Adult; Aged; Brain; Brain Mapping; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Humans; Image Processing, Computer-Assisted; Intercellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Neural Pathways; Oxygen; Phenylalanine; Threonine

Low Plasma Cholinesterase Activities are Associated with Deficits in Spatial Orientation, Reduced Ability to Perform Basic Activities of Daily Living, and Low Body Mass Index in Patients with Progressed Alzheimer's Disease. - Dingova, Dominika; Fazekas, Tomas; Okuliarova, Petra; Strbova, Jaroslava; Kucera, Matej; Hrabovska, Anna (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder characterized by a central cholinergic deficit. Non-neuronal cholinergic changes are, however, described as well. Here we focused on possible changes in the activity of the plasma cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), in hospitalized AD patients. We analyzed plasma AChE and BChE activities with regards to age, gender, body mass index (BMI), cognitive functions, and ability to perform activities of daily living in AD patients in comparison to healthy subjects. We observed lower AChE activity and trend toward lower BChE activity in AD patients, which both correlated with low BMI. AD patients unable to perform basic activities of daily living (feeding, bathing, dressing, and grooming) showed reduced plasma AChE activities, while worse spatial orientation was linked to lower BChE activities. Three out of four AD patients with the lowest BChE activities died within one year. In conclusion, progressed AD was accompanied by lower plasma AChE activity and trend toward lower BChE activity, which correlated with BMI and deficits in different components of the AD.
Keywords: Acetylcholinesterase; Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Blood Chemical Analysis; Body Mass Index; Butyrylcholinesterase; Female; Hospitalization; Humans; Male; Middle Aged; Orientation, Spatial

Low Serum Insulin-Like Growth Factor-I Predicts Cognitive Decline in Alzheimer's Disease. - Vidal, Jean-Sébastien; Hanon, Olivier; Funalot, Benoît; Brunel, Nadège; Viollet, Cécile; Rigaud, Anne-Sophie; Seux, Marie-Laure; le-Bouc, Yves; Epelbaum, Jacques; Duron, Emmanuelle (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between the insulin-like growth factor-I (IGF-I) system and Alzheimer's disease (AD) is mostly based on transversal studies. It remains, however, to demonstrate whether IGF-I is associated with cognitive decline over time in AD. OBJECTIVE: The objective of the study was to analyze the course of cognitive decline of AD subjects over a 24-month period in relation to serum IGF-I and insulin-like growth factor binding protein-3 (IGFBP-3) measured at baseline. METHODS: Data are from the SIGAL follow-up study. IGF-I and IGFBP-3 were measured in AD subjects who performed a Mini-Mental State Examination (MMSE) every 6 months for 2 years. MMSE course was analyzed using a mixed model with random intercept and slope function. RESULTS: Among the 200 AD participants, 146 (mean age = 81.1 (standard deviation (SD) = 5.9) years, 62.6% of women) had at least one follow-up visit. Mean IGF-I at baseline was 147.8 (74.2) ng/mL. Hundred forty-six participants (62.6%) had at least one follow-up visit. Mean MMSE was 21.7 (4.7)/30 and dropped on average by 2.28 points per year. MMSE decline was steeper among participants with lower IGF-I. For each decrease of 1 SD of IGF-I, subjects lost an additional 0.63 points per year in MMSE, e.g., participants with IGF-I level of 74 ng/mL lost 2.91 MMSE points per year whereas participants with IGF-I of 222 ng/mL lost 1.65 MMSE points per year. There was no association between IGFBP-3 and cognitive decline. CONCLUSION: Lower baseline serum IGF-I was associated with faster cognitive decline in AD over a 2-year period.

Lower Late-Life Body-Mass Index is Associated with Higher Cortical Amyloid Burden in Clinically Normal Elderly. - Hsu, David C; Mormino, Elizabeth C; Schultz, Aaron P; Amariglio, Rebecca E; Donovan, Nancy J; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2016)
BACKGROUND: Lower body-mass index (BMI) in late life has been associated with an increased risk of dementia, and weight loss has been associated with more rapid decline in Alzheimer's disease (AD) dementia. OBJECTIVE: To explore the association between BMI and cortical amyloid burden in clinically normal (CN) elderly at risk for AD dementia. METHODS: Cross-sectional analyses were completed using baseline data from the Harvard Aging Brain Study, consisting of 280 community-dwelling CN older adults aged 62-90. Assessments included medical histories and physical exam, Pittsburgh compound B (PiB) positron emission tomography (PET) amyloid imaging, and apolipoprotein E ɛ4 (APOE4) genotyping. For the primary analysis, a general linear regression model was used to evaluate the association of BMI with PiB retention. Covariates included age, sex, years of education, and APOE4 carrier status. Secondary analyses were performed for BMI subdivisions (normal, overweight, obese), APOE4 carriers, and BMI×APOE4 interaction. RESULTS: In the primary analysis, greater PiB retention was associated with lower BMI (β  =  -0.14, p = 0.02). In the secondary analyses, APOE4 carrier status (β= -0.27, p = 0.02) and normal BMI (β= -0.25, p = 0.01), as opposed to overweight or obese BMI, were associated with greater PiB retention. The BMI×APOE4 interaction was also significant (β= -0.14, p = 0.04). CONCLUSIONS: This finding offers new insight into the role of BMI at the preclinical stage of AD, wherein lower BMI late in life is associated with greater cortical amyloid burden. Future studies are needed to elucidate the mechanism behind this association, especially in those with lower BMI who are APOE4 carriers.

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

The Mechanism Underlying Amyloid Polymorphism is Opened for Alzheimer's Disease Amyloid-β Peptide. - Selivanova, Olga M; Surin, Alexey K; Marchenkov, Victor V; Dzhus, Ulyana F; Grigorashvili, Elizaveta I; Suvorina, Mariya Yu; Glyakina, Anna V; Dovidchenko, Nikita V; Galzitskaya, Oxana V (J Alzheimers Dis, 2016)
It has been demonstrated using Aβ40 and Aβ42 recombinant and synthetic peptides that their fibrils are formed of complete oligomer ring structures. Such ring structures have a diameter of about 8-9 nm, an oligomer height of about 2- 4 nm, and an internal diameter of the ring of about 3-4 nm. Oligomers associate in a fibril in such a way that they interact with each other, overlapping slightly. There are differences in the packing of oligomers in fibrils of recombinant and synthetic Aβ peptides. The principal difference is in the degree of orderliness of ring-like oligomers that leads to generation of morphologically different fibrils. Most ordered association of ring-like structured oligomers is observed for a recombinant Aβ40 peptide. Less ordered fibrils are observed with the synthetic Aβ42 peptide. Fragments of fibrils the most protected from the action of proteases have been determined by tandem mass spectrometry. It was shown that unlike Aβ40, fibrils of Aβ42 are more protected, showing less ordered organization compared to that of Aβ40 fibrils. Thus, the mass spectrometry data agree with the electron microscopy data and structural models presented here.

The Memory Binding Test: Development of Two Alternate Forms into Spanish and Catalan. - Gramunt, Nina; Sánchez-Benavides, Gonzalo; Buschke, Herman; Diéguez-Vide, Faustino; Peña-Casanova, Jordi; Masramon, Xavier; Fauria, Karine; Gispert, Juan D; Molinuevo, José L (J Alzheimers Dis, 2016)
BACKGROUND: The Memory Binding Test (MBT) is emerging as a promising tool for the detection of subtle memory impairment suggestive of Alzheimer's disease (AD). For such a test to be widely accessed and used, the availability of both alternate forms and language adaptations is required. OBJECTIVES: To develop a thorough methodology for obtaining alternate forms (A and B) of the MBT in Spanish and Catalan and to assess their equivalence. METHOD: According to the original development of the test, frequency was taken as the lexical variable of reference for the Spanish and Catalan adaptations. A crossed design protocol by form and language was used to compare the MBT results in a sample of 290 cognitively normal middle-aged participants. Pairwise Intraclass Correlation Coefficients (ICCs) were calculated among the six possible combinations. RESULTS: The Spanish and Catalan lists of words for the MBT A and B resulting from the adaptation process as well as the original lists in English are presented. ICC indices for the comparisons between forms and languages ranged from 0.56 to 0.82. CONCLUSION: The MBT A and B in Spanish and Catalan showed similar outcomes and can be considered equivalent. Moreover, the thorough methodology presented here for the transcultural adaptation and equivalence study, could serve as a model for future adaptations of the MBT and other verbal tests.

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

Metformin in Amnestic Mild Cognitive Impairment: Results of a Pilot Randomized Placebo Controlled Clinical Trial. - Luchsinger, Jose A; Perez, Thania; Chang, Helena; Mehta, Pankaj; Steffener, Jason; Pradabhan, Gnanavalli; Ichise, Masanori; Manly, Jennifer; Devanand, Davangere P; Bagiella, Emilia (J Alzheimers Dis, 2016)
Diabetes and hyperinsulinemia may be risk factors for Alzheimer's disease (AD). We conducted a pilot study of metformin, a medication efficacious in treating and preventing diabetes while reducing hyperinsulinemia, among persons with amnestic mild cognitive impairment (aMCI) with the goal of collecting preliminary data on feasibility, safety, and efficacy. Participants were 80 men and women aged 55 to 90 years with aMCI, overweight or obese, without treated diabetes. We randomized participants to metformin 1000 mg twice a day or matching placebo for 12 months. The co-primary clinical outcomes were changes from baseline to 12 months in total recall of the Selective Reminding Test (SRT) and the score of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). The secondary outcome was change in relative glucose uptake in the posterior cingulate-precuneus in brain fluorodeoxyglucose positron emission tomography. Change in plasma Aβ42 was an exploratory outcome. The mean age of participants was 65 years. Fifty percent of participants were women. The only baseline variable that was different between the arms was the ADAS-Cog. Metformin could not be tolerated by 7.5% of participants; 15% tolerated 500 mg/day, 35% tolerated 1000 mg/day, 32.5% tolerated 1500 mg/day, and only 10% tolerated the maximum dose. There were no serious adverse events related to metformin. The 7.5% of persons who did not tolerate metformin reported gastrointestinal symptoms. After adjusting for baseline ADAS-cog, changes in total recall of the SRT favored the metformin group (9.7±8.5 versus 5.3±8.5; p = 0.02). Differences for other outcomes were not significant. A larger trial seems warranted to evaluate the efficacy and cognitive safety of metformin in prodromal AD.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Double-Blind Method; Female; Follow-Up Studies; Glucose; Humans; Male; Metformin; Middle Aged; Nootropic Agents; Overweight; Peptide Fragments; Pilot Projects; Positron-Emission Tomography; Psychological Tests; Severity of Illness Index; Treatment Outcome

MicroRNAs as Therapeutic Targets for Alzheimer's Disease. - Di Meco, Antonio; Praticò, Domenico (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common cause of dementia in the elderly. With increasing longevity and the absence of a cure, AD has become not only a major health problem but also a heavy social and economic burden worldwide. Given this public health challenge, and that the current approved therapy for AD is limited to symptomatic treatment (i.e., cholinesterase inhibitors and NMDA receptor antagonists), exploration of new molecular pathways as novel therapeutic targets remains an attractive option for disease modifying drug development. microRNAs (miRNAs) are short non-coding RNA that control gene expression at the post-translational level by inhibiting translation of specific mRNAs or degrading them. Dysregulation of several miRNAs has been described in AD brains. Interestingly, their molecular targets are pathways that are well-established functional players in the onset and development of AD pathogenesis. Today several molecular tools have been developed to modulate miRNA levels in vitro and in vivo. These scientific advancements are affording us for the first time with the real possibility of targeting in vivo these dysregulated miRNAs as a novel therapeutic approach against AD.

Mindfulness in the Maintenance of Cognitive Capacities in Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Miró-Barrachina, María T; Ibáñez-Fernández, Ignacio J; Pino, Angelo Santana-Del; Quintana-Montesdeoca, María P; Rodríguez-de Vera, Bienvenida; Morales-Casanova, David; Pérez-Vieitez, María Del Carmen; Rodríguez-García, Javier; Bravo-Caraduje, Noelia (J Alzheimers Dis, 2016)
BACKGROUND: The Canary Islands longitudinal study on non-pharmacological treatments showed the overall effectiveness of mindfulness in Alzheimer's disease (AD). However, no specific data on the maintenance of cognitive capacities were presented. OBJECTIVE: To determine whether the practice of mindfulness modifies the course of cognitive impairment in AD. METHODS: DESIGN: Longitudinal, non-inferiority and equivalence, randomized clinical trial, repeated-measures design, with three experimental groups and one control group. PARTICIPANTS: Patients with AD who voluntarily attended the Lidia García Foundation (n = 502). Only those who were treated with donepezil and MMSE ≥18 were included (n = 120). INTERVENTION: Over a two-year period, each group carried out three weekly sessions of stimulation based on mindfulness, cognitive stimulation therapy, and progressive muscle relaxation. MEASURES: Cognitive assessment CAMDEX-R (MMSE and CAMCOG). STATISTICAL ANALYSIS: Repeated-measures ANOVA (p <  0.05) and the effect size Cohen's d were performed. RESULTS: The mindfulness group showed significant scores compared with the control and muscle relaxation groups (p <  0.05), while mindfulness and cognitive stimulation therapy were equivalent (p≥0.05). Group cognitive stimulation evolved better than the control (p <  0.05) group but not better than the muscle relaxation group (p≥0.05). The effect size compared over two years was large for the mindfulness group (p≥0.80), moderate for the relaxation group (p≥0.50), and low for the cognitive stimulation group (p≥0.20). CONCLUSION: The practice of mindfulness maintained cognitive function over a period of two years. This longitudinal study suggests that mindfulness can be used as a non-pharmacological treatment to slow cognitive impairment in AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Double-Blind Method; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Mindfulness; Neuropsychological Tests; Treatment Outcome

"Missed" Mild Cognitive Impairment: High False-Negative Error Rate Based on Conventional Diagnostic Criteria. - Edmonds, Emily C; Delano-Wood, Lisa; Jak, Amy J; Galasko, Douglas R; Salmon, David P; Bondi, Mark W (J Alzheimers Dis, 2016)
Mild cognitive impairment (MCI) is typically diagnosed using subjective complaints, screening measures, clinical judgment, and a single memory score. Our prior work has shown that this method is highly susceptible to false-positive diagnostic errors. We examined whether the criteria also lead to "false-negative" errors by diagnostically reclassifying 520 participants using novel actuarial neuropsychological criteria. Results revealed a false-negative error rate of 7.1%. Participants' neuropsychological performance, cerebrospinal fluid biomarkers, and rate of decline provided evidence that an MCI diagnosis is warranted. The impact of "missed" cases of MCI has direct relevance to clinical practice, research studies, and clinical trials of prodromal Alzheimer's disease.

Modulation of Amyloid-β1-40 Transport by ApoA1 and ApoJ Across an in vitro Model of the Blood-Brain Barrier. - Merino-Zamorano, Cristina; Fernández-de Retana, Sofía; Montañola, Alex; Batlle, Aina; Saint-Pol, Julien; Mysiorek, Caroline; Gosselet, Fabien; Montaner, Joan; Hernández-Guillamon, Mar (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) accumulation in Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) is likely caused by the impairment of its brain clearance that partly occurs through the blood-brain barrier (BBB). In this context, an in vitro BBB model is a valuable tool for studying the molecular mechanisms that regulate this process. This study assessed brain Aβ elimination across the BBB and its modulation by the natural chaperones Apolipoprotein A1 (ApoA1) and Apolipoprotein J/Clusterin (ApoJ). The model was based on primary cerebral endothelial cells that were cultured on Matrigel-coated Transwells and treated with fluorescently labeled-Aβ1-40 to track its efflux across the BBB, which corresponds to trafficking from the basolateral (brain) to apical (blood) compartments. We observed that the transport of basolateral Aβ1-40 was enhanced when it was complexed to rApoJ, whereas the complex formed with rApoA1 did not influence Aβ1-40 efflux. However, the presence of rApoA1 in the apical compartment was able to mobilize Aβ1-40 from the basolateral side. We also observed that both rApoA1 and rApoJ moderately crossed the monolayer (from blood to brain) through a mechanism involving the LDL receptor-related protein family. In contrast to the increased rApoJ efflux when complexed to Aβ1-40, rApoA1 trafficking was restricted when it was bound to the Aβ peptide. In summary, the present study highlights the role of ApoJ and ApoA1 in the in vitro modulation of Aβ elimination across the BBB.

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Molecular Signaling Mechanisms of Natural and Synthetic Retinoids for Inhibition of Pathogenesis in Alzheimer's Disease. - Chakrabarti, Mrinmay; McDonald, Alexander J; Will Reed, J; Moss, Melissa A; Das, Bhaskar C; Ray, Swapan K (J Alzheimers Dis, 2016)
Retinoids, which are vitamin A derivatives, interact through retinoic acid receptors (RARs) and retinoid X receptors (RXRs) and have profound effects on several physiological and pathological processes in the brain. The presence of retinoic acid signaling is extensively detected in the adult central nervous system, including the amygdala, cortex, hypothalamus, hippocampus, and other brain areas. Retinoids are primarily involved in neural patterning, differentiation, and axon outgrowth. Retinoids also play a key role in the preservation of the differentiated state of adult neurons. Impairment in retinoic acid signaling can result in neurodegeneration and progression of Alzheimer's disease (AD). Recent studies demonstrated severe deficiencies in spatial learning and memory in mice during retinoic acid (vitamin A) deprivation indicating its significance in preserving memory function. Defective cholinergic neurotransmission plays an important role in cognitive deficits in AD. All-trans retinoic acid is known to enhance the expression and activity of choline acetyltransferase in neuronal cell lines. Activation of RAR and RXR is also known to impede the pathogenesis of AD in mice by inhibiting accumulation of amyloids. In addition, retinoids have been shown to inhibit the expression of chemokines and pro-inflammatory cytokines in microglia and astrocytes, which are activated in AD. In this review article, we have described the chemistry and molecular signaling mechanisms of natural and synthetic retinoids and current understandings of their therapeutic potentials in prevention of AD pathology.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Mice; Neurons; Retinoid X Receptors; Retinoids; Signal Transduction; Tretinoin

Netrin-1 Interrupts Amyloid-β Amplification, Increases sAβPPα in vitro and in vivo, and Improves Cognition in a Mouse Model of Alzheimer's Disease. - Spilman, Patricia R; Corset, Veronique; Gorostiza, Olivia; Poksay, Karen S; Galvan, Veronica; Zhang, Junli; Rao, Rammohan; Peters-Libeu, Clare; Vincelette, Jon; McGeehan, Andrew; Dvorak-Ewell, Melita; Beyer, Janine; et al. (J Alzheimers Dis, 2016)
Recent studies have shown that inoculation of susceptible mice with amyloid-β (Aβ) peptides accelerates Aβ deposition in the brain, supporting the idea that Aβ may be self-amplifying; however, the exact mechanism is not understood. Here we provide evidence that Aβ may self-amplify, in part, by inhibiting α-secretase ADAM10 (a disintegrin and metalloprotease) cleavage of full-length Aβ precursor protein (FL AβPP) and therefore allow greater β-secretase processing, and that Aβ itself is a substrate for ADAM10. Exposure of primary neuronal cultures from PDAβPP mice to exogenous rat Aβ1- 40 resulted in increased de novo human Aβ1-42 production and exposure of cells to Aβ decreased production of ADAM10 cleavage product soluble AβPPα (sAβPPα). In a cell-free assay, Aβ decreased ADAM10 cleavage of the chimeric substrate MBP-AβPPC125 and Aβ itself was apparently cleaved by the enzyme. The axonal guidance and trophic factor netrin-1, however, reduced the Aβ1- 40-induced Aβ1-42 increase, increased sAβPPα, and reversed the Aβ-induced sAβPPα decrease in vitro. In vivo, induction of netrin-1 expression in PDAβPPSwe/Ind transgenic mice resulted in reductions in both Aβ1-42 and Aβ1- 40, and ICV delivery of netrin-1 to PDAβPPSwe/Ind mice increased sAβPPα, decreased Aβ, and improved working memory. Finally, to support further study of netrin-1's potential as a therapeutic for Alzheimer's disease, pilot gene therapy studies were performed and a netrin mimetic peptide synthesized and tested that, like netrin, can increase sAβPPα and decrease Aβ1-42in vitro. Taken together, these data provide mechanistic insights into Aβ self-amplification and the ability of netrin-1 to disrupt it.

Neuroimaging Correlates of Frontotemporal Dementia Associated with SQSTM1 Mutations. - Luis, Elkin; Ortiz, Alexandra; Eudave, Luis; Ortega-Cubero, Sara; Borroni, Barbara; van der Zee, Julie; Gazzina, Stefano; Caroppo, Paola; Rubino, Elisa; D'Agata, Federico; Le Ber, Isabelle; Santana, Isabel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Frontotemporal lobar degeneration (FTLD) is a progressive dementia characterized by focal atrophy of frontal and/or temporal lobes caused by mutations in the gene coding for sequestosome 1 (SQSTM1), among other genes. Rare SQSTM1 gene mutations have been associated with Paget's disease of bone, amyotrophic lateral sclerosis, and, more recently, frontotemporal lobar degeneration (FTLD). OBJECTIVE: The aim of the study was to determine whether a characteristic pattern of grey and white matter loss is associated with SQSTM1 dysfunction. METHODS: We performed a voxel-based morphometry (VBM) study in FTD subjects carrying SQSTM1 pathogenic variants (FTD/SQSTM1 mutation carriers; n = 10), compared with FTD subjects not carrying SQSTM1 mutations (Sporadic FTD; n = 20) and healthy controls with no SQSTM1 mutations (HC/SQSTM1 noncarriers; n = 20). The groups were matched according to current age, disease duration, and gender. RESULTS: After comparing FTD/SQSTM1 carriers with Sporadic FTD, a predominantly right cortical atrophy pattern was localized in the inferior frontal, medial orbitofrontal, precentral gyri, and the anterior insula. White matter atrophy was found in both medial and inferior frontal gyri, pallidum, and putamen. FTD/SQSTM1 carriers compared with HC/SQSTM1 noncarriers showed atrophy at frontal, temporal, and parietal lobes of both hemispheres whereas the MRI pattern found in Sporadic FTD compared with controls was frontal and left temporal lobe atrophy, extending toward parietal and occipital lobes of both hemispheres. CONCLUSIONS: These results suggest that fronto-orbito-insular regions including corticospinal projections as described in ALS are probably more susceptible to the damaging effect of SQSTM1 mutations delineatinga specific gene-linked atrophy pattern.

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Novel Mutation (Gly212Val) in the PS2 Gene Associated with Early-Onset Familial Alzheimer's Disease. - Marín-Muñoz, Juan; Noguera-Perea, Ma Fuensanta; Gómez-Tortosa, Estrella; López-Motos, David; Antequera-Torres, Martirio; Martínez-Herrada, Begoña; Manzanares-Sánchez, Salvadora; Vivancos-Moreau, Laura; Legaz-García, Agustina; Rábano-Gutiérrez Del Arroyo, Alberto; Antúnez-Almagro, Carmen (J Alzheimers Dis, 2016)
Mutations in the presenilin 2 gene (PS2) are an extremely rare cause of early-onset autosomal dominant Alzheimer's disease (AD), accounting for only 5% of these families. These cases represent a particular model of AD, and the scarcity of reports on their clinical phenotypes makes them of great interest. We report a family with early-onset autosomal dominant AD in four members, where the two living siblings were found to carry the novel PS2 mutation Gly212Val (exon 7, transmembrane domain IV) with highly predicted pathogenicity. Age at onset ranged from 60 to 65 years and three of the cases died between ages 74 and 76 years. Clinical phenotype was quite homogeneous among affected members of the family, and overall features, including cognitive decline, tau/p-tau and amyloid-β cerebrospinal fluid markers, neuroimaging, and neuropathology were consistent with typical AD. Lewy bodies were present but restricted to the amygdala.

Nutritional Status of Patients with Alzheimer's Disease and Their Caregivers. - Tombini, Mario; Sicari, Maura; Pellegrino, Giovanni; Ursini, Francesca; Insardá, Pasqualina; Di Lazzaro, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Malnutrition is one of the most important conditions that negatively affects the health of elder people, particularly in patients with dementia. OBJECTIVE: To provide an assessment of nutritional status of patients affected by Alzheimer's disease (AD) living at home and of their caregivers by means of Mini Nutritional Assessment (MNA), and to explore the influence of different factors on nutrition. METHODS: 90 patients affected by AD living at home and 90 age- and sex-matched caregivers were enrolled. Patients and caregivers, coming from an urban-rural fringe of Southern Italy, were assessed using full MNA, Mini-Mental State Examination, Geriatric Depression Scale- short form, Activity of Daily Living, and Instrumental Activities of Daily Living scales. RESULTS: Malnutrition was found with high prevalence in patients affected by AD of different severity (more than 95% of patients were malnourished or at risk of malnutrition), and associated with reduced functional status. An altered nutrition was also recognized with high rate in the group of caregivers (23.3% were malnourished and 41.1% at risk of malnutrition) and the worse nutritional condition was correlated with higher age and lower functional and cognitive status and education. A positive correlation between MNA score of AD patients and caregivers was found. CONCLUSION: Corrective measures should be taken in order to early identify nutritional deficiencies and risk of malnutrition observed with high rate in both groups of AD patients and their caregivers; in these subjects a nutrition education program and intervention policies are mandatory to restore nutritional status.

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

Optimized Standard Operating Procedures for the Analysis of Cerebrospinal Fluid Aβ42 and the Ratios of Aβ Isoforms Using Low Protein Binding Tubes. - Vanderstichele, Hugo Marcel Johan; Janelidze, Shorena; Demeyer, Leentje; Coart, Els; Stoops, Erik; Herbst, Victor; Mauroo, Kimberley; Brix, Britta; Hansson, Oskar (J Alzheimers Dis, 2016)
BACKGROUND: Reduced cerebrospinal fluid (CSF) concentration of amyloid-β1-42 (Aβ1-42) reflects the presence of amyloidopathy in brains of subjects with Alzheimer's disease (AD). OBJECTIVE: To qualify the use of Aβ1-42/Aβ1-40 for improvement of standard operating procedures (SOP) for measurement of CSF Aβ with a focus on CSF collection, storage, and analysis. METHODS: Euroimmun ELISAs for CSF Aβ isoforms were used to set up a SOP with respect to recipient properties (low binding, polypropylene), volume of tubes, freeze/thaw cycles, addition of detergents (Triton X-100, Tween-20) in collection or storage tubes or during CSF analysis. Data were analyzed with linear repeated measures and mixed effects models. RESULTS: Optimization of CSF analysis included a pre-wash of recipients (e.g., tubes, 96-well plates) before sample analysis. Using the Aβ1-42/Aβ1-40 ratio, in contrast to Aβ1-42, eliminated effects of tube type, additional freeze/thaw cycles, or effect of CSF volumes for polypropylene storage tubes. 'Low binding' tubes reduced the loss of Aβ when aliquoting CSF or in function of additional freeze/thaw cycles. Addition of detergent in CSF collection tubes resulted in an almost complete absence of variation in function of collection procedures, but affected the concentration of Aβ isoforms in the immunoassay. CONCLUSION: The ratio of Aβ1-42/Aβ1-40 is a more robust biomarker than Aβ1-42 toward (pre-) analytical interfering factors. Further, 'low binding' recipients and addition of detergent in collection tubes are able to remove effects of SOP-related confounding factors. Integration of the Aβ1-42/Aβ1-40 ratio and 'low-binding tubes' into guidance criteria may speed up worldwide standardization of CSF biomarker analysis.

Oral Infections and Cytokine Levels in Patients with Alzheimer's Disease and Mild Cognitive Impairment Compared with Controls. - Cestari, José Augusto Ferrari; Fabri, Gisele Maria Campos; Kalil, Jorge; Nitrini, Ricardo; Jacob-Filho, Wilson; de Siqueira, José Tadeu Tesseroli; Siqueira, Silvia Regina D T (J Alzheimers Dis, 2016)
BACKGROUND: Oral infections are prevalent in the adult population. Their impact includes the implication as a risk factor for Alzheimer's disease (AD), altering its progression. One of the potential mechanisms involves immune mediators such as circulating cytokines. OBJECTIVE: The goal of the present study was to investigate the prevalence of oral infections and blood levels of IL-1β, TNF-α, and IL-6 in patients with AD, mild cognitive impairment (MCI), and controls. METHODS: Sixty-five elderly were evaluated (25 AD, 19 MCI, and 21 controls) by the following methods: Mini Mental State Exam, Questionnaire of Functional Activities, periodontal and oral evaluation, and blood concentrations of IL-1β, TNF-α and IL-6. RESULTS: Patients with AD had high serum IL-6 levels (p = 0.029), and patients with periodontitis had high serum TNF-α levels (p = 0.005). There was an association between IL-6 and TNF-α in patients with AD/MCI and periodontitis (p = 0.023). CONCLUSION: The increased levels of TNF-α and IL-6 in this study suggests their implication in the overlapping mechanisms between oral infections and AD. Longitudinal studies are necessary for further investigation.

Overexpression of Metallothionein-1 Modulates the Phenotype of the Tg2576 Mouse Model of Alzheimer's Disease. - Manso, Yasmina; Comes, Gemma; López-Ramos, Juan C; Belfiore, Mónica; Molinero, Amalia; Giralt, Mercedes; Carrasco, Javier; Adlard, Paul A; Bush, Ashley I; Delgado-García, José María; Hidalgo, Juan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most commonly diagnosed dementia, where signs of neuroinflammation and oxidative stress are prominent. In this study we intend to further characterize the roles of the antioxidant, anti-inflammatory, and heavy metal binding protein, metallothionein-1 (MT-1), by crossing Mt1 overexpressing mice with a well-known mouse model of AD, Tg2576 mice, which express the human amyloid-β protein precursor (hAβPP) with the Swedish K670N/M671L mutations. Mt1 overexpression increased overall perinatal survival, but did not affect significantly hAβPP-induced mortality and weight loss in adult mice. Amyloid plaque burden in ∼14-month-old mice was increased by Mt1 overexpression in the hippocampus but not the cortex. Despite full length hAβPP levels and amyloid plaques being increased by Mt1 overexpression in the hippocampus of both sexes, oligomeric and monomeric forms of Aβ, which may contribute more to toxicity, were decreased in the hippocampus of females and increased in males. Several behavioral traits such as exploration, anxiety, and learning were altered in Tg2576 mice to various degrees depending on the age and the sex. Mt1 overexpression ameliorated the effects of hAβPP on exploration in young females, and potentiated those on anxiety in old males, and seemed to improve the rate of spatial learning (Morris water maze) and the learning elicited by a classical conditioning procedure (eye-blink test). These results clearly suggest that MT-1 may be involved in AD pathogenesis.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anxiety; Disease Models, Animal; Exploratory Behavior; Female; Gene Expression Regulation; Humans; Male; Matrix Metalloproteinase 16; Maze Learning; Metallothionein; Mice; Mice, Inbred C57BL; Mice, Transgenic; Motor Activity; Mutation; Phenotype; Psychomotor Disorders

Pain Assessment in Elderly with Behavioral and Psychological Symptoms of Dementia. - Malara, Alba; De Biase, Giuseppe Andrea; Bettarini, Francesco; Ceravolo, Francesco; Di Cello, Serena; Garo, Michele; Praino, Francesco; Settembrini, Vincenzo; Sgrò, Giovanni; Spadea, Fausto; Rispoli, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Pain is under-detected and undertreated in people with dementia. The present study investigates the prevalence of pain in people with dementia hospitalized in nursing homes that are members of National Association of Third Age Residences (ANASTE) Calabria, and evaluates the association among pain, mood, and behavioral and psychological symptoms of dementia (BPSD). OBJECTIVE: The aim of this study is to define the prevalence of pain in people with dementia in long term care facilities using scales of self-reporting and observational tools and, particularly, to study the relationship between pain and BPSD. METHODS: A prospective observational study was carried out on 233 patients. Pain assessment was performed using self-reporting tools such as the Numeric Rating Scale (NRS) for patients with slight cognitive impairment or no cognitive impairment and observational tools such as Pain Assessment In Advanced Dementia Scale (PAINAD) for patients with moderate or severe cognitive impairment. Mood was evaluated through the Cornell Scale for Depression in Dementia (CSDD) while behavioral problems were assessed through the Cohen-Mansfield Agitation Inventory (CMAI) and Neuropsychiatric Inventory (NPI). RESULTS: Only 42.5% of patients evaluated by NRS provided a reliable answer; of these, 20.4% reported no pain. The percentage of pain evaluated by PAINAD was 51.8% . Analysis of data showed a statistically significant correlation between diagnosis of pain and depressive symptoms, assessed with CSDD (p = 0.0113), as well as by single items of NPI, such as anxiety (p = 0.0362) and irritability (p = 0.0034), and F1 profile (Aggression) of CMAI (p = 0.01). CONCLUSION: This study confirms that self-report alone is not sufficient to assess pain in elderly people with dementia; the observational tool is a necessary and suitable way of assessing pain in patients with cognitive impairment. If not adequately treated, chronic pain can cause depression, agitation, and aggression in patients with dementia.
Keywords: Affect; Aged, 80 and over; Analgesics; Anxiety; Dementia; Depression; Female; Humans; Italy; Logistic Models; Long-Term Care; Male; Multivariate Analysis; Nursing Homes; Pain; Pain Measurement; Prevalence; Prospective Studies; Psychiatric Status Rating Scales; Self Report; Severity of Illness Index

Palmomental Reflex a Relevant Sign in Early Alzheimer's Disease Diagnosis? - Gabelle, Audrey; Gutierrez, Laure-Anne; Dartigues, Jean-François; Ritchie, Karen; Touchon, Jacques; Berr, Claudine (J Alzheimers Dis, 2016)
BACKGROUND: Sophisticated and expensive biomarkers are proposed for the diagnostic of Alzheimer's disease (AD). The amyloid process seems to be early in AD, and brain amyloid load affects the frontal lobe. OBJECTIVE: To determine if certain simple clinical signs, especially frontal-related signs, could help reach an earlier and better diagnosis. METHODS: In the frame of the 3-City cohort, we conducted a nested case-control study comparing incident cases of AD to controls matched for age, gender, and education. The standardized neurological exam included extrapyramidal signs (akinesia, rigidity, rest tremor), pyramidal symptoms (spastic rigidity, Babinski reflex), primitive reflexes (snout, palmomental reflex grasping), and tremor (essential, intentional, head) at the time of diagnosis and two years before. RESULTS: We compared 106 incident AD subjects (mean age at diagnosis 82.2 (SD = 5.9); median MMSE at diagnosis = 23) to 208 matched controls. In patients younger than 80, palmomental reflexes were more frequent in AD than controls, two years before diagnosis (25.0 versus 7.0% , p = 0.03) and at time of diagnosis (30.3 versus 12.3% , p = 0.02). No difference was observed for other signs two years before diagnosis or for patients older than 80. CONCLUSION: Before diagnosis, the clinical examination of AD patients is not strictly normal; the primitive reflexes appear to be pathological. It might be in connection with the frontal amyloid load at an early stage of the disease. Clinical examination can reveal simple and interesting signs that deserve consideration as well as the other more invasive and expensive biomarkers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Early Diagnosis; Female; Follow-Up Studies; France; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Reflex

Partial Amelioration of Synaptic and Cognitive Deficits by Inhibiting Cofilin Dephosphorylation in an Animal Model of Alzheimer's Disease. - Deng, Yulei; Wei, Jing; Cheng, Jia; Zhong, Ping; Xiong, Zhe; Liu, Aiyi; Lin, Lin; Chen, Shengdi; Yan, Zhen (J Alzheimers Dis, 2016)
The loss of synaptic structure and function has been linked to the cognitive impairment of Alzheimer's disease (AD). Dysregulation of the actin cytoskeleton, which plays a key role in regulating the integrity of synapses and the transport of synaptic proteins, has been suggested to contribute to the pathology of AD. In this study, we found that glutamate receptor surface expression and synaptic function in frontal cortical neurons were significant diminished in a familial AD (FAD) model, which was correlated with the reduction of phosphorylated cofilin, a key protein regulating the dynamics of actin filaments. Injecting a cofilin dephosphorylation inhibitory peptide to FAD mice led to the partial rescue of the surface expression of AMPA and NMDA receptor subunits, as well as the partial restoration of AMPAR- and NMDAR-mediated synaptic currents. Moreover, the impaired working memory and novel object recognition memory in FAD mice were partially ameliorated by injections of the cofilin dephosphorylation inhibitory peptide. These results suggest that targeting the cofilin-actin signaling holds promise to mitigate the physiological and behavioral abnormality in AD.

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patients with Amyloid-Negative Mild Cognitive Impairment have Cortical Hypometabolism but the Hippocampus is Preserved. - Hanseeuw, Bernard; Dricot, Laurence; Lhommel, Renaud; Quenon, Lisa; Ivanoiu, Adrian (J Alzheimers Dis, 2016)
BACKGROUND: Patients with mild cognitive impairment (MCI) are at risk for Alzheimer's dementia but the presence of amyloid (Aβ) strongly increases this risk. In clinical settings, when Aβ status is not available, different neurodegenerative markers are used to characterize MCI. The accuracy of these markers to discriminate between Aβ-and Aβ+ MCI is not yet determined. OBJECTIVE: To compare different markers of neurodegeneration in Aβ-and Aβ+ MCI, with an Aβ-elderly control (EC) group. METHODS: Patients with MCI (n = 39) and EC (n = 28) underwent MRI, 18F-FDG PET, and Aβ PET (18F-flutemetamol). We compared FDG and MRI biomarker values in cortical and hippocampal regions of interest, and using voxel-wise surface maps. We computed ROC curves discriminating between the three groups for each biomarker. RESULTS: All biomarker values were reduced in Aβ+ MCI compared to EC (p < 0.001). Aβ-MCI had low cortical metabolism (p = 0.002), but hippocampal volume, cortical thickness, and hippocampal metabolism were not significantly different between Aβ-MCI and EC (p > 0.40). Cortical metabolism best discriminated between MCI and EC (AUC = 0.92/0.86, Aβ+/Aβ-) while hippocampal volume best discriminated between Aβ-MCI and Aβ+ MCI (AUC = 0.79). CONCLUSIONS: Cortical hypometabolism was observed in both Aβ-MCI and Aβ+ MCI whereas hippocampal atrophy was mostly found in Aβ+ MCI. For MCI patients without available Aβ information, hippocampal atrophy is thus more informative about Aβ status than cortical hypometabolism.

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Performance on Specific Cognitive Domains and Cause of Death: A Prospective Population-Based Study in Non-Demented Older Adults (NEDICES). - Benito-León, Julián; Contador, Israel; Mitchell, Alex J; Domingo-Santos, Ángela; Bermejo-Pareja, Félix (J Alzheimers Dis, 2016)
Evidence regarding the relationship between performance on specific cognitive domains and cause of death is scarce. We assessed whether specific cognitive domains predicted mortality and the presence of any association with specific causes of death in a population-dwelling sample of non-demented older adults. In this population-based, prospective study (NEDICES), 2,390 non-demented subjects ≥65 years completed a brief neuropsychological battery. Cox's proportional hazards models, adjusted by sociodemographic and comorbidity factors, global cognitive performance, educational level, and premorbid intelligence were used to assess the risk of death. Participants were followed for a median of 9.2 years (range 0.01-10.7), after which the death certificates of those who died were examined. 880 (36.8%) of 2,390 participants died over a median follow-up of 5.5 years (range 0.01-10.5). Using adjusted Cox regression models, we found that hazard ratios for mortality in participants within the lowest tertiles (worse performance) were 1.31 (speed of cognitive processing, p = 0.03); 1.22 (semantic fluency, p = 0.04), 1.32 (delayed free recall, p = 0.003), and 1.23 (delayed logical memory, p = 0.03). Poor performance on delayed recall and speed of cognitive processing tests were associated with dementia and cerebrovascular disease mortality, respectively. Further, poor performance on semantic fluency was associated with decreased cancer mortality. In this study of community dwelling non-demented older adults, worse neuropsychological performance was associated with increased risk of mortality. Performance on specific cognitive domains were related to different causes of death. Of particular note there appears to be an inverse association between poor semantic fluency and cancer mortality.
Keywords: Aged; Cause of Death; Cerebrovascular Disorders; Cognitive Aging; Dementia; Educational Status; Female; Follow-Up Studies; Humans; Intelligence; Longitudinal Studies; Male; Neuropsychological Tests; Prospective Studies; Risk; Spain

Perlecan Domain V Inhibits Amyloid-β Induced Activation of the α2β1 Integrin-Mediated Neurotoxic Signaling Cascade. - Parham, Christi L; Shaw, Courtney; Auckland, Lisa D; Dickeson, S Kent; Griswold-Prenner, Irene; Bix, Gregory (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by neuronal death, neurofibrillary tangles, and senile plaques. Amyloid-beta (Aβ) is the major component of plaques and consists of two prominent isoforms, Aβ40 and Aβ42. As many risk factors for AD are vascular in origin and blood vessel defects in clearing Aβ from the brain are a potential key component of AD pathology, we have focused on the neuron-blood vessel interface, and in particular, the vascular basement membrane, which coats blood vessels and physically separates them from neurons. A prominent component of the vascular basement membrane is the extracellular matrix proteoglycan perlecan. Domain V (DV) is the C-terminal domain and is generated by perlecan proteolysis. DV interacts with the α2 integrin and Aβ is a ligand for both α2β1 and αvβ1. Due to the known interaction of DV with α2β1 and α2β1's requirement for Aβ deposition and neurotoxicity, we hypothesized that DV and/or its C-terminal domain, LG3, might alter neurotoxic signaling pathways by directly blocking or otherwise interfering with α2β1 binding by Aβ. Our study suggests that α2β1 mediates Aβ-induced activation of c-Jun and caspase-3, key components of the neurotoxic pathway, in primary cortical and hippocampal neurons. We further demonstrate that DV and/or LG3 may therapeutically modulate these α2β1 mediated neurotoxic effects suggesting that they or other α2β1 integrin modulators could represent a novel approach to treat AD. Finally, our results suggest different neurotoxicity susceptibilities between cortical and hippocampal neurons to Aβ40 and Aβ42 as further underscored by differing neuroprotective potencies of LG3 in each cell type.

A Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Safety, Pharmacokinetics, and Biomarker Results of Subcutaneous Bapineuzumab in Patients with mild to moderate Alzheimer's disease. - Brody, Mark; Liu, Enchi; Di, Jianing; Lu, Ming; Margolin, Richard A; Werth, John L; Booth, Kevin; Shadman, Anna; Brashear, H Robert; Novak, Gerald (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, a humanized monoclonal antibody, targets amyloid-β (Aβ1-40/1 -42) that is believed to play a key role in the pathogenesis of Alzheimer disease (AD). OBJECTIVES: To assess the effects of monthly subcutaneous (SC) bapineuzumab versus placebo on cerebral amyloid signal in amyloid-positive patients with mild to moderate AD. The incidence of amyloid-related imaging abnormalities-edema/effusion (ARIA-E), pharmacokinetics, pharmacodynamics, immunogenicity, and other safety aspects of bapineuzumab were also evaluated. METHODS: In this multicenter, double-blind study, 146 patients were randomized (1 : 1:1 : 1) to SC bapineuzumab 2, 7, or 20 mg/month or placebo. Lack of efficacy of intravenous (IV) bapineuzumab in Phase III studies led to truncation of the treatment duration from 24 months to 12 months. Primary endpoint: change from baseline to month 12 in brain amyloid signal as measured by standardized uptake value ratio (SUVR) using florbetapir positron emission tomography (PET). RESULTS: Florbetapir PET SUVR decreased significantly (p = 0.038) from baseline to month 12 for the bapineuzumab 7 mg/month group only; reductions versus placebo were not significant for any dosage. One patient each in bapineuzumab 2 mg/month and 20 mg/month groups had ARIA-E. The percentages of patients with treatment-emergent adverse events were similar in placebo (77.8%) and bapineuzumab 2 mg/month (78.4%) group, but higher in 7 mg/month (94.4%) and 20 mg/month (89.2%) groups. CONCLUSION: Bapineuzumab SC once-monthly did not demonstrate significant treatment difference over placebo on cerebral amyloid signal at one year but was well-tolerated. There was less ARIA-E than had been expected based on prior experience with comparable exposure on IV bapineuzumab.

A Phase II Study of Fornix Deep Brain Stimulation in Mild Alzheimer's Disease. - Lozano, Andres M; Fosdick, Lisa; Chakravarty, M Mallar; Leoutsakos, Jeannie-Marie; Munro, Cynthia; Oh, Esther; Drake, Kristen E; Lyman, Christopher H; Rosenberg, Paul B; Anderson, William S; Tang-Wai, David F; Pendergrass, Jo Cara; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Deep brain stimulation (DBS) is used to modulate the activity of dysfunctional brain circuits. The safety and efficacy of DBS in dementia is unknown. OBJECTIVE: To assess DBS of memory circuits as a treatment for patients with mild Alzheimer's disease (AD). METHODS: We evaluated active "on" versus sham "off" bilateral DBS directed at the fornix-a major fiber bundle in the brain's memory circuit-in a randomized, double-blind trial (ClinicalTrials.gov NCT01608061) in 42 patients with mild AD. We measured cognitive function and cerebral glucose metabolism up to 12 months post-implantation. RESULTS: Surgery and electrical stimulation were safe and well tolerated. There were no significant differences in the primary cognitive outcomes (ADAS-Cog 13, CDR-SB) in the "on" versus "off" stimulation group at 12 months for the whole cohort. Patients receiving stimulation showed increased metabolism at 6 months but this was not significant at 12 months. On post-hoc analysis, there was a significant interaction between age and treatment outcome: in contrast to patients  CONCLUSION: DBS for AD was safe and associated with increased cerebral glucose metabolism. There were no differences in cognitive outcomes for participants as a whole, but participants aged≥65 years may have derived benefit while there was possible worsening in patients below age 65 years with stimulation.

A Phase IIa Randomized Control Trial of VEL015 (Sodium Selenate) in Mild-Moderate Alzheimer's Disease. - Malpas, Charles B; Vivash, Lucy; Genc, Sila; Saling, Michael M; Desmond, Patricia; Steward, Christopher; Hicks, Rodney J; Callahan, Jason; Brodtmann, Amy; Collins, Steven; Macfarlane, Stephen; Corcoran, Niall M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is increasing interest in targeting hyperphosphorylated tau (h-tau) as a disease modifying approach for Alzheimer's disease (AD). Sodium selenate directly stimulates the activity of PP2A, the main enzyme responsible for h-tau dephosphorylation in the brain. OBJECTIVE: This study assessed the safety and tolerability of 24-week treatment with VEL015 (sodium selenate) in AD. Investigating the effects of VEL015 on cognitive, CSF, and neuroimaging biomarkers of AD were secondary, exploratory objectives. Data were used to identify biomarkers showing most promise for use in subsequent efficacy trials. METHODS: A 24-week, multicenter, Phase IIa, double-blinded randomized controlled trial. Forty patients aged ≥55 y with mild-moderate AD (MMSE 14-26) were randomized to supranutritional (VEL015 10 mg tds [n = 20]) and control (VEL015 320μg tds [n = 10] or placebo [n = 10]) groups. Patients were regularly monitored for safety, adverse events (AEs), and protocol compliance. Exploratory biomarkers included cognitive tests, neuroimaging (diffusion MR), and CSF (p-tau, t-tau, and Aβ1-42). RESULTS: Thirty-six (90%; [supranutritional n = 18, control/placebo n = 18]) patients completed the trial. There were no differences in the incidence of specific AEs between groups. Only one secondary biomarker, diffusion MR measures, showed group differences, with less deterioration in the supranutritional group (p < 0.05). CONCLUSION: Treatment with VEL015 at doses up to 30 mg per day for 24 weeks was safe and well-tolerated in patients with AD. Diffusion MR measures appear to be the most sensitive biomarkers to assess disease progression over 24 weeks.

Physical and Cognitive Stimulation Using an Exergame in Subjects with Normal Aging, Mild and Moderate Cognitive Impairment. - Ben-Sadoun, Grégory; Sacco, Guillaume; Manera, Valeria; Bourgeois, Jérémy; König, Alexandra; Foulon, Pierre; Fosty, Baptiste; Bremond, François; d'Arripe-Longueville, Fabienne; Robert, Philippe (J Alzheimers Dis, 2016)
BACKGROUND: The use of Serious exerGames (SeG) as enriched environments (EE), which promotes cognitive simulation with physical activity in a positive emotional context, has been proposed to represent a powerful method to slow down the decline due to neurodegenerative diseases (ND), such as Alzheimer's disease (AD). However, so far, no SeG targeting EE has been tested in ND subjects. OBJECTIVE: This study aimed at evaluating the usability and short-term training effects of X-Torp, an action SeG designed for elderly ND subjects with mild cognitive impairment (MCI) and AD. METHODS: X-Torp is a SeG played using the Microsoft® Kinect™. 10 ND subjects and 8 healthy elderly controls (HEC) were enrolled in a 1-month program with three training sessions per week. Usability was evaluated through game time, game performance, the aerobic intensity level reached, perceived emotions, and perceived usability. RESULTS: All participants successfully completed the training program. ND subjects played less and had a lower game performance compared to HEC. During the sessions, ND subjects maintained a light intensity of aerobic activity, while HEC maintained a moderate intensity. Both groups experienced only positive emotions, and reported a 'moderate' to 'high' perceived competence, a 'moderate' game difficulty, and a 'high' interest in the game. CONCLUSION: Usability results suggest that X-Torp represents a usable EE for healthy subjects and persons with MCI and AD. However, in order to reach moderate or high intensity of aerobic activity, X-Torp control modes should be adapted to become more physically stimulating.

Potentially Inappropriate Prescribing Among People with Dementia in Primary Care: A Retrospective Cross-Sectional Study Using the Enhanced Prescribing Database. - Barry, Heather E; Cooper, Janine A; Ryan, Cristín; Passmore, A Peter; Robinson, A Louise; Molloy, Gerard J; Darcy, Carmel M; Buchanan, Hilary; Hughes, Carmel M (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about prescribing appropriateness for community-dwelling people with dementia (PWD). OBJECTIVE: To estimate potentially inappropriate prescribing (PIP) prevalence among PWD in primary care in Northern Ireland, and to investigate associations between PIP, polypharmacy, age, and gender. METHODS: A retrospective cross-sectional study was conducted, using data from the Enhanced Prescribing Database. Patients were eligible if a medicine indicated for dementia management was dispensed to them during 1 January 2013-31 December 2013. Polypharmacy was indicated by use of ≥4 repeat medications from different drug groups. A subset of the Screening Tool of Older Persons Potentially Inappropriate Prescriptions (STOPP) criteria, comprising 36 indicators, was applied to the dataset. Overall prevalence of PIP and the prevalence per each STOPP criterion was calculated as a proportion of all eligible persons in the dataset. Logistic regression was used to investigate associations between PIP, polypharmacy, age, and gender. RESULTS: The study population comprised 6826 patients. Polypharmacy was observed in 81.5% (n = 5564) of patients. PIP prevalence during the study period was 64.4% (95% CI 63.2- 65.5; n = 4393). The most common instance of PIP was the use of anticholinergic/antimuscarinic medications (25.2%; 95% CI 24.2-26.2; n = 1718). In multivariable analyses, both polypharmacy and gender (being female) were associated with PIP, with odds ratios of 7.6 (95% CI 6.6-8.7) and 1.3 (95% CI 1.2-1.4), respectively. No association was observed between PIP and age, after adjustments for gender and polypharmacy. CONCLUSION: This study identified a high prevalence of PIP in community-dwelling PWD. Future interventions may need to focus on certain therapeutic categories and polypharmacy.

Predictive Value of Cerebrospinal Fluid Visinin-Like Protein-1 Levels for Alzheimer's Disease Early Detection and Differential Diagnosis in Patients with Mild Cognitive Impairment. - Babić Leko, Mirjana; Borovečki, Fran; Dejanović, Nenad; Hof, Patrick R; Šimić, Goran (J Alzheimers Dis, 2016)
Visinin-like protein 1 (VILIP-1) recently emerged as a potential biomarker of Alzheimer's disease (AD). This neuronal calcium sensor protein previously used as a marker of acute ischemic stroke is elevated in the cerebrospinal fluid (CSF) of AD patients. The goal of this study was to assess CSF VILIP-1 potential in early AD diagnosis and in differentiating mild cognitive impairment (MCI) patients with and without risk of AD. Additionally, we tested VILIP-1 ability to differentiate AD from other primary causes of dementia, and predict the progression of AD-related cognitive decline. VILIP-1 levels were compared with five CSF AD biomarkers (t-tau, Aβ1-42, p-tau181, p-tau199, and p-tau231). VILIP-1 successfully differentiated two MCI patient groups characterized by absence or presence of pathological levels of these CSF biomarkers, except for t-tau. VILIP-1/Aβ(1-42) and VILIP-1/p-tau181 ratios also differentiated MCI patients with pathological CSF biomarker levels. However, there was no difference in VILIP-1 levels between AD and MCI patients. VILIP-1/Aβ(1-42) and VILIP-1/p-tau231 ratios reached high sensitivities (above 70%) and very high specificities (above 85%) in differentiating AD patients from HC. Additionally, VILIP-1 differentiated AD from patients with Lewy body disease with 77.1% sensitivity and 100% specificity. VILIP-1 potential as a prognostic biomarker of cognitive decline in AD was also proved since VILIP-1/t-tau, VILIP-1/p-tau181, and VILIP-1/p-tau231 ratios correlated with MMSE scores. These data indicate that VILIP-1 alone or in combination with other AD CSF biomarkers represent a valuable marker for the early diagnosis of AD, recognition of MCI patients at higher risk to develop dementia, and in differentiating AD from LBD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Diagnosis, Differential; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neurocalcin; Peptide Fragments; Predictive Value of Tests; ROC Curve; Statistics as Topic; tau Proteins

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

Primary Progressive Orofacial Apraxia: A Ten-Year Long Follow-Up Case Report. - Trebbastoni, Alessandro; D'Antonio, Fabrizia; de Lena, Carlo; Onesti, Emanuela; John, Bev; Inghilleri, Maurizio (J Alzheimers Dis, 2016)
Orofacial apraxia (OA) as the main symptom in neurodegenerative disorders has not been yet reported. We present the case of a woman with a 22-month long history of isolated OA, studied with cerebrospinal fluid biomarkers and repeated clinical, neuropsychological, and morpho-functional evaluations. Baseline morpho-functional neuroimages revealed a left frontal operculum hypoperfusion with a widespread fronto-temporal involvement at follow-up. Cerebrospinal fluid concentrations of tau and amyloid-β were normal. The ten-year long clinical observation disclosed progressive OA worsening and the late onset of frontal functions impairment and extrapyramidal signs. The early and late stages of a neurodegenerative syndrome with OA as the main clinical feature were characterized.

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Promising Role of Neuromodulation in Predicting the Progression of Mild Cognitive Impairment to Dementia. - Naro, Antonino; Corallo, Francesco; De Salvo, Simona; Marra, Angela; Di Lorenzo, Giuseppe; Muscarà, Nunzio; Russo, Margherita; Marino, Silvia; De Luca, Rosaria; Bramanti, Placido; Calabrò, Rocco Salvatore (J Alzheimers Dis, 2016)
The differential diagnosis of mild cognitive impairment (MCI) and Alzheimer's disease (AD) is not always straightforward, and the rate of progression of MCI to dementia is not negligible. Thus, there is a need for para-clinical approaches that can improve the differential diagnosis and identify patients that are at risk of progression. There is a growing interest, at present, in the role of the deterioration of brain oscillations as a predictor of MCI-to-AD conversion. For this reason, we experimentally modulated γ-band oscillations (GBO) in a sample of MCI and AD patients and an age-matched healthy elderly group, using a transcranial alternating current stimulation (tACS) protocol that was applied to different cortical sites. We correlated the after-effects of tACS on the GBO and the neuropsychological data, in an attempt to differentiate MCI from AD patients and identify, among the MCI patients, those that could be at potential risk of MCI-to-dementia conversion. MCI patients showed a partial GBO increase and improvement in some neuropsychological tests whereas AD individuals did not show significant tACS after-effects. Notably, some MCI subjects lacked significant neuropsychological and electrophysiological after-effects, similar to AD individuals. In a two-year follow-up, such MCI individuals had converted into AD. Therefore, our data suggest that tACS may support the clinical differential diagnosis of MCI and AD and identify MCI patients who could be at risk of developing dementia. This prediction index may help the clinician to adopt a better prevention/follow-up strategy in such a disabling neurodegenerative disease.

Prospective Memory Impairments in Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia: Clinical and Neural Correlates. - Dermody, Nadene; Hornberger, Michael; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Prospective memory (PM) refers to a future-oriented form of memory in which the individual must remember to execute an intended action either at a future point in time (Time-based) or in response to a specific event (Event-based). Lapses in PM are commonly exhibited in neurodegenerative disorders including Alzheimer's disease (AD) and frontotemporal dementia (FTD), however, the neurocognitive mechanisms driving these deficits remain unknown. OBJECTIVE: To investigate the clinical and neural correlates of Time- and Event-based PM disruption in AD and the behavioral-variant FTD (bvFTD). METHODS: Twelve AD, 12 bvFTD, and 12 healthy older Control participants completed a modified version of the Cambridge Prospective Memory test, which examines Time- and Event-based aspects of PM. All participants completed a standard neuropsychological assessment and underwent whole-brain structural MRI. RESULTS: AD and bvFTD patients displayed striking impairments across Time- and Event-based PM relative to Controls, however, Time-based PM was disproportionately affected in the AD group. Episodic memory dysfunction and hippocampal atrophy were found to correlate strongly with PM integrity in both patient groups, however, dissociable neural substrates were also evident for PM performance across dementia syndromes. CONCLUSION: Our study reveals the multifaceted nature of PM dysfunction in neurodegenerative disorders, and suggests common and dissociable neurocognitive mechanisms, which subtend these deficits in each patient group. Future studies of PM disturbance in dementia syndromes will be crucial for the development of successful interventions to improve functional independence in the patient's daily life.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Female; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model. - Bourgade, Karine; Le Page, Aurélie; Bocti, Christian; Witkowski, Jacek M; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether this could result in protective anti-viral activity against HSV-1 infection. Results showed that H4 cells secreted Aβ42 in response to HSV-1 challenge and that U118-MG cells could rapidly internalize Aβ42. Production of pro-inflammatory cytokines TNFα and IL-1β by H4 and U118-MG cells occurred under basal conditions but infection of the cells with HSV-1 did not significantly upregulate production. Both cell lines produced low levels of IFNα. However, extraneous Aβ42 induced strong production of these cytokines. A combination of Aβ42 and HSV-1 induced production of pro-inflammatory cytokines TNFα and IL-1β, and IFNα in the cell lines. The reported anti-viral protection of Aβ42 was revealed in transfer experiments involving conditioned medium (CM) of HSV-1-infected H4 cells. CM conferred Aβ-dependent protection against HSV-1 replication in de novo cultures of H4 cells challenged with HSV-1. Type 1 interferons did not play a role in these assays. Our data established that H4 neuroglioma cells produced Aβ42 in response to HSV-1 infection thus inhibiting secondary replication. This mechanism may play a role in the etiology of AD.
Keywords: Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Cell Line, Tumor; Coculture Techniques; Culture Media, Conditioned; Herpes Simplex; Herpesvirus 1, Human; Humans; Interferon-alpha; Interleukin-1beta; Neuroglia; Neurons; Peptide Fragments; Tumor Necrosis Factor-alpha; Virus Replication

Puerarin Ameliorates D-Galactose Induced Enhanced Hippocampal Neurogenesis and Tau Hyperphosphorylation in Rat Brain. - Hong, Xiao-Ping; Chen, Tao; Yin, Ni-Na; Han, Yong-Ming; Yuan, Fang; Duan, Yan-Jun; Shen, Feng; Zhang, Yan-Hong; Chen, Ze-Bin (J Alzheimers Dis, 2016)
Enhanced neurogenesis has been reported in the hippocampus of patients with Alzheimer's disease (AD), the most common neurodegenerative disorder characterized with amyloid-β (Aβ) aggregation, tau hyperphosphorylation, and progressive neuronal loss. Previously we reported that tau phosphorylation played an essential role in adult hippocampal neurogenesis, and activation of glycogen synthase kinase (GSK-3), a crucial tau kinase, could induce increased hippocampal neurogenesis. In the present study, we found that treatment of D-galactose rats with Puerarin could significantly improve behavioral performance and ameliorate the enhanced neurogenesis and microtubule-associated protein tau hyperphosphorylation in the hippocampus of D-galactose rat brains. FGF-2/GSK-3 signaling pathway might be involved in the effects of Puerarin on hippocampal neurogenesis and tau hyperphosphorylation. Our finding provides primary in vivo evidence that Puerarin can attenuate AD-like enhanced hippocampal neurogenesis and tau hyperphosphorylation. Our finding also suggests Puerarin can be served as a treatment for age-related neurodegenerative disorders, such as AD.
Keywords: Animals; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factor 2; Galactose; Glycogen Synthase Kinase 3; Hippocampus; Isoflavones; Male; Maze Learning; Neurogenesis; Neurons; Neuroprotective Agents; Phosphorylation; Random Allocation; Rats, Sprague-Dawley; Signal Transduction; Spatial Memory; tau Proteins

Purported Interactions of Amyloid-β and Glucocorticoids in Cytotoxicity and Genotoxicity: Implications in Alzheimer's Disease. - Bengoetxea, Xabier; de Cerain, Adela López; Azqueta, Amaya; Ramirez, Maria J (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the presence of aggregates of the amyloid-β peptide (Aβ) that are believed to be neurotoxic. One of the purposed damaging mechanisms of Aβ is oxidative insult, which eventually could damage the cellular genome. Stress and associated increases in glucocorticoids (GCs) have been described as a risk factor for the development of AD, although the purported genotoxic effects of GCs have not been fully characterized. Therefore, it is possible to speculate about purported synergistic effects of GCs on the Aβ-driven genotoxic damage. This in vitro study addresses the single and combined cyto/genotoxic effects of Aβ and GCs in SH-SY5Y cells. Cytotoxicity was determined by the MTT assay, and the genotoxic effects were studied using the comet assay. A comet assay derivation allows for measuring the presence of the FPG-sensitive sites (mainly 8-oxoguanines) in the DNA, apart from the DNA strand breaks. Treatment with Aβ (10 μM, 72 h) induced cytotoxicity (35% decrease in cell viability) and DNA strand breaks, but had no significant effect on oxidative DNA damage (FPG sites). Corticosterone showed no effect on cell viability, genotoxicity, or reparation processes. Corticosterone was unable to neither reverse nor potentiate Aβ driven effects. The present results suggest the existence of alternative mechanisms for the Aβ driven damage, not involving oxidative damage of DNA. In addition, could be suggested that the interaction between Aβ and GCs in AD does not seem to involve DNA damage.

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

Reduction of Blood Amyloid-β Oligomers in Alzheimer's Disease Transgenic Mice by c-Abl Kinase Inhibition. - Estrada, Lisbell D; Chamorro, David; Yañez, María José; Gonzalez, Marcelo; Leal, Nancy; von Bernhardi, Rommy; Dulcey, Andrés E; Marugan, Juan; Ferrer, Marc; Soto, Claudio; Zanlungo, Silvana; Inestrosa, Nibaldo C; et al. (J Alzheimers Dis, 2016)
One of the pathological hallmarks of Alzheimer's disease (AD) is the presence of amyloid plaques, which are deposits of misfolded and aggregated amyloid-beta peptide (Aβ). The role of the c-Abl tyrosine kinase in Aβ-mediated neurodegeneration has been previously reported. Here, we investigated the therapeutic potential of inhibiting c-Abl using imatinib. We developed a novel method, based on a technique used to detect prions (PMCA), to measure minute amounts of misfolded-Aβ in the blood of AD transgenic mice. We found that imatinib reduces Aβ-oligomers in plasma, which correlates with a reduction of AD brain features such as plaques and oligomers accumulation, neuroinflammation, and cognitive deficits. Cells exposed to imatinib and c-Abl KO mice display decreased levels of β-CTF fragments, suggesting that an altered processing of the amyloid-beta protein precursor is the most probable mechanism behind imatinib effects. Our findings support the role of c-Abl in Aβ accumulation and AD, and propose AD-PMCA as a new tool to evaluate AD progression and screening for drug candidates.

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data. - Gomm, Willy; von Holt, Klaus; Thomé, Friederike; Broich, Karl; Maier, Wolfgang; Weckbecker, Klaus; Fink, Anne; Doblhammer, Gabriele; Haenisch, Britta (J Alzheimers Dis, 2016)
BACKGROUND: While acute detrimental effects of benzodiazepine (BDZ), and BDZ and related z-substance (BDZR) use on cognition and memory are known, the association of BDZR use and risk of dementia in the elderly is controversially discussed. Previous studies on cohort or claims data mostly show an increased risk for dementia with the use of BDZs or BDZRs. For Germany, analyses on large population-based data sets are missing. OBJECTIVE: To evaluate the association between regular BDZR use and incident any dementia in a large German claims data set. METHODS: Using longitudinal German public health insurance data from 2004 to 2011 we analyzed the association between regular BDZR use (versus no BDZR use) and incident dementia in a case-control design. We examined patient samples aged≥60 years that were free of dementia at baseline. To address potential protopathic bias we introduced a lag time between BDZR prescription and dementia diagnosis. Odds ratios were calculated applying conditional logistic regression, adjusted for potential confounding factors such as comorbidities and polypharmacy. RESULTS: The regular use of BDZRs was associated with a significant increased risk of incident dementia for patients aged≥60 years (adjusted odds ratio [OR] 1.21, 95% confidence interval [CI] 1.13-1.29). The association was slightly stronger for long-acting substances than for short-acting ones. A trend for increased risk for dementia with higher exposure was observed. CONCLUSION: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer's Disease and Mild Cognitive Impairment Patients. - Rai, Nitish; Kumar, Rahul; Desai, Gaurav Rajesh; Venugopalan, G; Shekhar, Shashank; Chatterjee, Prasun; Tripathi, Manjari; Upadhyay, Ashish Datt; Dwivedi, Sadanand; Dey, Aparajit B; Dey, Sharmistha (J Alzheimers Dis, 2016)
Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups was determined by real time polymerase chain reaction. The results showed significant overexpression of serum sesn2 protein and mRNA levels in the AD group compared to MCI and elderly control groups. A difference in serum sesn2 concentration between MCI and the control group was also evident. ROC analysis showed highly sensitive, selective cutoff values for sens2 in the differentiation of AD, MCI, and controls. No significant difference in sesn1 level was observed among the study groups. This study highlights the important role of sesn2 in the progression of the AD, indicating its potential utility as a protein marker in this devastating disease.

Reliability and Validity of a Novel Internet-Based Battery to Assess Mood and Cognitive Function in the Elderly. - Myers, Candice A; Keller, Jeffrey N; Allen, H Raymond; Brouillette, Robert M; Foil, Heather; Davis, Allison B; Greenway, Frank L; Johnson, William D; Martin, Corby K (J Alzheimers Dis, 2016)
Dementia is a chronic condition in the elderly and depression is often a concurrent symptom. As populations continue to age, accessible and useful tools to screen for cognitive function and its associated symptoms in elderly populations are needed. The aim of this study was to test the reliability and validity of a new internet-based assessment battery for screening mood and cognitive function in an elderly population. Specifically, the Helping Hand Technology (HHT) assessments for depression (HHT-D) and global cognitive function (HHT-G) were evaluated in a sample of 57 elderly participants (22 male, 35 female) aged 59-85 years. The study sample was categorized into three groups: 1) dementia (n = 8; Mini-Mental State Exam (MMSE) score 10-24), 2) mild cognitive impairment (n = 24; MMSE score 25-28), and 3) control (n = 25; MMSE score 29-30). Test-retest reliability (Pearson correlation coefficient, r) and internal consistency reliability (Cronbach's alpha, α) of the HHT-D and HHT-G were assessed. Validity of the HHT-D and HHT-G was tested via comparison (Pearson r) to commonly used pencil-and-paper based assessments: HHT-D versus the Geriatric Depression Scale (GDS) and HHT-G versus the MMSE. Good test-retest (r = 0.80; p < 0.0001) and acceptable internal consistency reliability (α= 0.73) of the HHT-D were established. Moderate support for the validity of the HHT-D was obtained (r = 0.60 between the HHT-D and GDS; p < 0.0001). Results indicated good test-retest (r = 0.87; p < 0.0001) and acceptable internal consistency reliability (α= 0.70) of the HHT-G. Validity of the HHT-G was supported (r = 0.71 between the HHT-G and MMSE; p < 0.0001). In summary, the HHT-D and HHT-G were found to be reliable and valid computerized assessments to screen for depression and cognitive status, respectively, in an elderly sample.

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

Risk Assessment of Alzheimer's Disease using the Information Diffusion Model from Structural Magnetic Resonance Imaging. - Beheshti, Iman; Olya, Hossain G T; Demirel, Hasan (J Alzheimers Dis, 2016)
BACKGROUND: Recently, automatic risk assessment methods have been a target for the detection of Alzheimer's disease (AD) risk. OBJECTIVE: This study aims to develop an automatic computer-aided AD diagnosis technique for risk assessment of AD using information diffusion theory. METHODS: Information diffusion is a fuzzy mathematics logic of set-value that is used for risk assessment of natural phenomena, which attaches fuzziness (uncertainty) and incompleteness. Data were obtained from voxel-based morphometry analysis of structural magnetic resonance imaging. RESULTS AND CONCLUSION: The information diffusion model results revealed that the risk of AD increases with a reduction of the normalized gray matter ratio (p > 0.5, normalized gray matter ratio <40%). The information diffusion model results were evaluated by calculation of the correlation of two traditional risk assessments of AD, the Mini-Mental State Examination and the Clinical Dementia Rating. The correlation results revealed that the information diffusion model findings were in line with Mini-Mental State Examination and Clinical Dementia Rating results. Application of information diffusion model contributes to the computerization of risk assessment of AD, which has a practical implication for the early detection of AD.

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Serum Uric Acid and Its Association with Longitudinal Cognitive Change Among Urban Adults. - Beydoun, May A; Canas, Jose-Atilio; Dore, Gregory A; Beydoun, Hind A; Rostant, Ola S; Fanelli-Kuczmarski, Marie T; Evans, Michele K; Zonderman, Alan B (J Alzheimers Dis, 2016)
Uric acid, a waste metabolite among humans, was linked to various cognitive outcomes. We describe sex and age-group specific associations of baseline serum uric acid (SUAbase) and significant change in SUA (ΔSUA: 1 versus 0 = decrease versus no change; 2 versus 0 = increase versus no change) with longitudinal annual rate of cognitive change among a large sample of urban adults. Data from the Healthy Aging in Neighborhoods of Diversity across the Life Span study, 2004-2009 (visit 1) and 2009-2013 (visit 2) were used. Of 3,720 adults selected at baseline (age range: 30-64 y), complete data were available for N = 1,487-1,602 with a mean repeat of 1.5-1.7 visits/participant. Cognitive test domains spanned attention, processing speed, learning/memory, executive function, visuo-spatial/visuo-construction ability, language/verbal, and global cognitive function. SUA was measured at both visits. Multiple mixed-effects regression analyses were conducted. In the total population, a higher SUAbase was associated with a faster annual rate of decline on a measure of visual memory/visuo-construction ability (the Benton Visual Retention Test) by γ= 0.07 with a standard error of 0.02, p < 0.001. Among older men, a significant increase in SUA was associated with slower decline on a test of attention/processing speed, namely Trailmaking test, Part A, measured in seconds to completion (γ= -6.91 ± 1.73, p < 0.001). In sum, a higher SUAbase was associated with faster cognitive decline over-time in a visual memory/visuo-construction ability test. ΔSUA had particular beneficial effects of an increasing ΔSUA on the domain of attention/processing speed among older men. More longitudinal studies are needed to examine cognitive domain-specific effects of over-time change in SUA within sex and age groups.

So Close Yet So Far: Executive Contribution to Memory Processing in Behavioral Variant Frontotemporal Dementia. - Bertoux, Maxime; Ramanan, Siddharth; Slachevsky, Andrea; Wong, Stephanie; Henriquez, Fernando; Musa, Gada; Delgado, Carolina; Flanagan, Emma; Bottlaender, Michel; Sarazin, Marie; Hornberger, Michael; Dubois, Bruno (J Alzheimers Dis, 2016)
BACKGROUND: Memory impairment in behavioral variant frontotemporal dementia (bvFTD) is traditionally considered to be mild and attributed to prefrontal cortex dysfunction. Recent studies, however, indicated that some patients can present with a memory impairment of the hippocampal type, showing storage and consolidation deficits in addition to the more executive/prefrontal related encoding and strategic difficulties. OBJECTIVE: This study aimed to study the relationship between executive functions (EF) and memory processes in bvFTD via a data-driven approach. METHOD: Participants consisted of 71 bvFTD (among which 60.6% had a lumbar puncture showing non-Alzheimer biomarker profile) and 60 controls (among which 45% had amyloid imaging showing a normal profile). EF were assessed by the Frontal Assessment Battery, semantic/lexical verbal fluency tests, and forward/backward digit spans. Patients were split into amnestic (n = 33) and non-amnestic (n = 38) subgroups based on normative data (total recall score) from the Free and Cued Selective Reminding Test (FCSRT). Relationships between FCSRT subscores and EF measures were explored through hierarchical clustering analysis, partial correlation analysis with an EF component, and automated linear modeling. RESULTS: Convergent findings across the statistical approaches show that, overall, memory performance was independent from EF in bvFTD whereas the relationship was stronger in controls. Indeed, in bvFTD, memory performance did not cluster with EF, was not correlated with the EF component, and was only partially (4% - 12.7%) predicted by EF. DISCUSSION: These findings show that executive dysfunctions cannot solely explain the memory deficits occurring in bvFTD. Indeed, some patients present with a genuine amnesia affecting storage and consolidation abilities, which are independent from executive dysfunctions. On the clinical level, this study highlights the importance of revising the neuropsychological diagnosis criteria for bvFTD.

Social Cognition Deficits: The Key to Discriminate Behavioral Variant Frontotemporal Dementia from Alzheimer's Disease Regardless of Amnesia? - Bertoux, Maxime; de Souza, Leonardo Cruz; O'Callaghan, Claire; Greve, Andrea; Sarazin, Marie; Dubois, Bruno; Hornberger, Michael (J Alzheimers Dis, 2016)
Relative sparing of episodic memory is a diagnostic criterion of behavioral variant frontotemporal dementia (bvFTD). However, increasing evidence suggests that bvFTD patients can show episodic memory deficits at a similar level as Alzheimer's disease (AD). Social cognition tasks have been proposed to distinguish bvFTD, but no study to date has explored the utility of such tasks for the diagnosis of amnestic bvFTD. Here, we contrasted social cognition performance of amnestic and non-amnestic bvFTD from AD, with a subgroup having confirmed in vivo pathology markers. Ninety-six participants (38 bvFTD and 28 AD patients as well as 30 controls) performed the short Social-cognition and Emotional Assessment (mini-SEA). BvFTD patients were divided into amnestic versus non-amnestic presentation using the validated Free and Cued Selective Reminding Test (FCSRT) assessing episodic memory. As expected, the accuracy of the FCSRT to distinguish the overall bvFTD group from AD was low (69.7% ) with ∼50% of bvFTD patients being amnestic. By contrast, the diagnostic accuracy of the mini-SEA was high (87.9% ). When bvFTD patients were split on the level of amnesia, mini-SEA diagnostic accuracy remained high (85.1% ) for amnestic bvFTD versus AD and increased to very high (93.9% ) for non-amnestic bvFTD versus AD. Social cognition deficits can distinguish bvFTD and AD regardless of amnesia to a high degree and provide a simple way to distinguish both diseases at presentation. These findings have clear implications for the diagnostic criteria of bvFTD. They suggest that the emphasis should be on social cognition deficits with episodic memory deficits not being a helpful diagnostic criterion in bvFTD.
Keywords: Aged; Alzheimer Disease; Amnesia; Cognition; Diagnosis, Differential; Emotions; Female; Frontotemporal Dementia; Humans; Male; Memory, Episodic; Neuropsychological Tests; Social Perception

Spatial Memory Impairment is Associated with Intraneural Amyloid-β Immunoreactivity and Dysfunctional Arc Expression in the Hippocampal-CA3 Region of a Transgenic Mouse Model of Alzheimer's Disease. - Morin, Jean-Pascal; Cerón-Solano, Giovanni; Velázquez-Campos, Giovanna; Pacheco-López, Gustavo; Bermúdez-Rattoni, Federico; Díaz-Cintra, Sofía (J Alzheimers Dis, 2016)
Dysfunction of synaptic communication in cortical and hippocampal networks has been suggested as one of the neuropathological hallmarks of the early stages of Alzheimer's disease (AD). Also, several lines of evidence have linked disrupted levels of activity-regulated cytoskeletal associated protein (Arc), an immediate early gene product that plays a central role in synaptic plasticity, with AD "synaptopathy". The mapping of Arc expression patterns in brain networks has been extensively used as a marker of memory-relevant neuronal activity history. Here we evaluated basal and behavior-induced Arc expression in hippocampal networks of the 3xTg-AD mouse model of AD. The basal percentage of Arc-expressing cells in 10-month-old 3xTg-AD mice was higher than wild type in CA3 (4.88% versus 1.77% , respectively) but similar in CA1 (1.75% versus 2.75% ). Noteworthy, this difference was not observed at 3 months of age. Furthermore, although a Morris water maze test probe induced a steep (∼4-fold) increment in the percentage of Arc+ cells in the CA3 region of the 10-month-old wild-type group, no such increment was observed in age-matched 3xTg-AD, whereas the amount of Arc+ cells in CA1 increased in both groups. Further, we detected that CA3 neurons with amyloid-β were much more likely to express Arc protein under basal conditions. We propose that in 3xTg-AD mice, intraneuronal amyloid-β expression in CA3 could increase unspecific neuronal activation and subsequent Arc protein expression, which might impair further memory-stabilizing processes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Benzeneacetamides; CA3 Region, Hippocampal; Cytoskeletal Proteins; Disease Models, Animal; Gene Expression Regulation; Humans; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurons; Presenilin-1; Pyridines; tau Proteins

Specific Triazine Herbicides Induce Amyloid-β42 Production. - Portelius, Erik; Durieu, Emilie; Bodin, Marion; Cam, Morgane; Pannee, Josef; Leuxe, Charlotte; Mabondzo, Aloϊse; Oumata, Nassima; Galons, Hervé; Lee, Jung Yeol; Chang, Young-Tae; Stϋber, Kathrin; et al. (J Alzheimers Dis, 2016)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by secretases leads to extracellular release of amyloid-β (Aβ) peptides. Increased production of Aβ42 over Aβ40 and aggregation into oligomers and plaques constitute an Alzheimer's disease (AD) hallmark. Identifying products of the 'human chemical exposome' (HCE) able to induce Aβ42 production may be a key to understanding some of the initiating causes of AD and to generate non-genetic, chemically-induced AD animal models. A cell model was used to screen HCE libraries for Aβ42 inducers. Out of 3500+ compounds, six triazine herbicides were found that induced a β- and γ-secretases-dependent, 2-10 fold increase in the production of extracellular Aβ42 in various cell lines, primary neuronal cells, and neurons differentiated from human-induced pluripotent stem cells (iPSCs). Immunoprecipitation/mass spectrometry analyses show enhanced production of Aβ peptides cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and lower, a characteristic of AD. Neurons derived from iPSCs obtained from a familial AD (FAD) patient (AβPP K724N) produced more Aβ42 versus Aβ40 than neurons derived from healthy controls iPSCs (AβPP WT). Triazines enhanced Aβ42 production in both control and AD iPSCs-derived neurons. Triazines also shifted the cleavage pattern of alcadeinα, another γ-secretase substrate, suggesting a direct effect of triazines on γ-secretase activity. In conclusion, several widely used triazines enhance the production of toxic, aggregation prone Aβ42/Aβ43 amyloids, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in late-onset AD.

Stability of Progranulin Under Pre-Analytical Conditions in Serum and Cerebrospinal Fluid. - Willemse, Eline A J; Durieux-Lu, Sisi; van der Flier, Wiesje M; Pijnenburg, Yolande A L; de Jonge, Robert; Teunissen, Charlotte E (J Alzheimers Dis, 2016)
Progranulin (PGRN) levels in blood and cerebrospinal fluid (CSF) are increasingly studied as potential markers for neurodegenerative disorders. We aimed to 1) characterize two commercially available PGRN ELISAs on several assay validation parameters, 2) assess the stability of PGRN in serum and CSF under pre-analytical conditions, and 3) compare stability in the two assays. Intra- and inter-assay variation, inter-lot variation, linearity, lower limit of detection, and kit correlations were assessed for the Adipogen and R&D PGRN ELISA kits. Blood and serum samples were experimentally exposed to ≤9 freeze/thaw cycles, delayed processing for ≤24 h at room temperature and 4°C, and to temperature stability tests for ≤3 weeks at -20°C, 4°C, room temperature, and 37°C. Both commercial PGRN ELISA kits showed acceptable ranges for intra- and inter-assay variation, where the R&D kit performed more accurate than the Adipogen kit, especially for inter-assay variation (intra-assay serum: 6.7 and 8.3%, respectively; inter-assay serum: 9.2 and 21.0%; intra-assay CSF: 3.6 and 12.0%; inter-assay CSF: 16.0 and 44.5%). Absolute serum PGRN concentrations were 1.9-fold higher in Adipogen than R&D (p < 0.001) and strongly correlated between both kits (ρ= 0.86, p < 0.0001) and CSF PGRN levels were on the borderline of detection in both kits. PGRN was typically stable under all pre-analytical conditions addressed, although two weeks at 37°C resulted in decreased PGRN concentrations in CSF, only when using the Adipogen kit. These results support further examination of PGRN as a potential marker in neurodegenerative diseases, since PGRN is stable in serum and CSF and can be measured using ELISA kits from several providers.

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

T3D-959: A Multi-Faceted Disease Remedial Drug Candidate for the Treatment of Alzheimer's Disease. - Tong, Ming; Deochand, Chetram; Didsbury, John; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: T3D-959, a dual PPAR-δ/PPAR γ nuclear receptor agonist and former diabetes drug candidate, has been repositioned as an Alzheimer's disease (AD)-modifying therapy. OBJECTIVE: This study examines the effectiveness and mechanisms of T3D-959's therapeutic effects using in vivo and ex vivo rat models of sporadic AD. METHODS: A sporadic AD model was generated by intracerebral (i.c.) administration of streptozotocin (STZ). Control and i.c. STZ treated rats were gavaged with saline or T3D-959 (0.3 to 3.0 mg/kg/day) for 28 days. Spatial learning and memory were evaluated using the Morris water maze test. Frontal lobe slice cultures generated 24 hours after i.c. STZ or vehicle were used to study early effects of T3D-959 (0.5-1.0 μM) on viability and molecular markers of AD. RESULTS: T3D-959 significantly improved spatial learning and memory in i.c STZ-treated rats. Mechanistically, T3D-959 significantly improved culture viability and brain morphology, reduced levels of oxidative stress and Aβ, and normalized expression of phospho-tau, choline acetyltransferase, and myelin-associated glycoprotein. Protective effects occurred even at the lowest tested dose of T3D-959. CONCLUSIONS: Pre-clinical proof of concept has been demonstrated that T3D-959 can improve multiple pathologies of AD resulting in significant improvements in cognitive function and molecular and biochemical indices of neurodegeneration. These results support the theses that (1) effective disease modification in AD can be achieved by targeting relevant nuclear receptors, and (2) treating AD as a metabolic disease has the potential to be disease remedial. A Phase 2a trial of T3D-959 in mild-to-moderate AD patients has been initiated (ClinicalTrials.gov identifier NCT02560753).
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Antibiotics, Antineoplastic; Antipsychotic Agents; Blood Glucose; Body Weight; Brain; Choline O-Acetyltransferase; Disease Models, Animal; Dose-Response Relationship, Drug; Glial Fibrillary Acidic Protein; Glucosephosphate Dehydrogenase; In Vitro Techniques; Maze Learning; Myelin Basic Protein; Neurotoxicity Syndromes; Organ Culture Techniques; PPAR delta; PPAR gamma; Rats; Rats, Long-Evans; Spatial Learning; Streptozocin

Targretin Improves Cognitive and Biological Markers in a Patient with Alzheimer's Disease. - Pierrot, Nathalie; Lhommel, Renaud; Quenon, Lisa; Hanseeuw, Bernard; Dricot, Laurence; Sindic, Christian; Maloteaux, Jean-Marie; Octavea, Jean-Noël; Ivanoiu, Adrian (J Alzheimers Dis, 2016)
We present the effects of Targretin® (bexarotene) on cognition and biomarkers in a patient with mild Alzheimer's disease (AD). Targretin® is a Retinoic X Receptor (RXR) agonist shown to improve synaptic and cognitive functions in animal models of AD by increasing neuronal cholesterol efflux. After 6 months of treatment with Targretin® 300 mg/day, memory improved by about 40% and the tau protein in the cerebrospinal fluid decreased by about 20% . No significant side effects were noticed. This observation in a single patient indicates that Targretin® may improve memory performance and biological markers at an early stage of AD.
Keywords: Aged; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Cognition Disorders; Humans; Male; Mental Recall; Neuropsychological Tests; Receptors, Retinoic Acid; tau Proteins; Tetrahydronaphthalenes

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Time Orientation and 10 Years Risk of Dementia in Elderly Adults: The Three-City Study. - Dumurgier, Julien; Dartigues, Jean-François; Gabelle, Audrey; Paquet, Claire; Prevot, Magali; Hugon, Jacques; Tzourio, Christophe (J Alzheimers Dis, 2016)
Time disorientation is commonly observed in dementia, however very little is known about the pathological significance of minor time errors in community-dwelling population. Our objective was to investigate the relationship between time orientation and risk of dementia in a population of older adults. Analyses relies on 8611 dementia-free subjects from the Three-City Study, France. Participants were followed up for 10 years for incident dementia. Time orientation was assessed by asking for the date, the day of the week, the month, the season and the year. At baseline, 905 subjects made at least one error in time orientation. During 57,073 person-years of follow-up, 827 participants developed dementia. After controlling for age, gender and education level, subjects with one error in time had a greater risk of dementia (hazard ratio [HR] 1.44 [1.18-1.77]), while those with at least 2 errors had a more than three-fold increased risk (HR 3.10 [1.98-4.83]). This association was particularly marked for the diagnosis of probable Alzheimer's disease. Time disorientation was associated with an increased risk of dementia in a large population of cognitively normal older people followed during up to 10 years and should not be underestimated in clinical setting.

Timely Diagnosis for Alzheimer's Disease: A Literature Review on Benefits and Challenges. - Dubois, Bruno; Padovani, Alessandro; Scheltens, Philip; Rossi, Andrea; Dell'Agnello, Grazia (J Alzheimers Dis, 2016)
BACKGROUND: Timely diagnosis of Alzheimer's disease (AD) refers to a diagnosis at the stage when patients come to the attention of clinicians because of concerns about changes in cognition, behavior, or functioning and can be still free of dementia and functionally independent. OBJECTIVES: To comprehensively review existing scientific evidence on the benefits and potential challenges of making a timely diagnosis of AD. METHODS: Relevant studies were identified by searching electronic databases (Medline, Embase) and bibliographies for studies published in English between 1 January 2000 and 2 June 2014 on the consequences of a timely diagnosis of AD. RESULTS: Nine studies were identified that investigated the consequences of diagnosing AD at the initial stages; none were specifically focused on prodromal AD. A timely diagnosis potentially offers the opportunities of early intervention, implementation of coordinated care plans, better management of symptoms, patient safety, cost savings, and postponement of institutionalization. Barriers to making a timely diagnosis include stigma, suicide risk, lack of training, diagnostic uncertainty, shortage of specialized diagnostic services, and the reluctance of healthcare providers to make a diagnosis when no effective disease-modifying options are available. CONCLUSIONS: Despite its potential benefits, few published studies have explored the advantages or risks of a timely diagnosis of AD. In light of the cultural shift toward diagnosis at the initial stage of the disease continuum, when the patient does not yet have dementia, more investigations are needed to evaluate the benefits and address the barriers that may impede making a timely AD diagnosis.
Keywords: Alzheimer Disease; Databases, Bibliographic; Humans; Time Factors

Tobacco Smoke Exposure Impairs Brain Insulin/IGF Signaling: Potential Co-Factor Role in Neurodegeneration. - Deochand, Chetram; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Human studies suggest tobacco smoking is a risk factor for cognitive impairment and neurodegeneration, including Alzheimer's disease (AD). However, experimental data linking tobacco smoke exposures to underlying mediators of neurodegeneration, including impairments in brain insulin and insulin-like growth factor (IGF) signaling in AD are lacking. OBJECTIVE: This study tests the hypothesis that cigarette smoke (CS) exposures can impair brain insulin/IGF signaling and alter expression of AD-associated proteins. METHODS: Adult male A/J mice were exposed to air for 8 weeks (A8), CS for 4 or 8 weeks (CS4, CS8), or CS8 followed by 2 weeks recovery (CS8+R). Gene expression was measured by qRT-PCR analysis and proteins were measured by multiplex bead-based or direct binding duplex ELISAs. RESULTS: CS exposure effects on insulin/IGF and insulin receptor substrate (IRS) proteins and phosphorylated proteins were striking compared with the mRNA. The main consequences of CS4 or CS8 exposures were to significantly reduce insulin R, IGF-1R, IRS-1, and tyrosine phosphorylated insulin R and IGF-1R proteins. Paradoxically, these effects were even greater in the CS8+R group. In addition, relative levels of S312-IRS-1, which inhibits downstream signaling, were increased in the CS4, CS8, and CS8+R groups. Correspondingly, CS and CS8+R exposures inhibited expression of proteins and phosphoproteins required for signaling through Akt, PRAS40, and/or p70S6K, increased AβPP-Aβ, and reduced ASPH protein, which is a target of insulin/IGF-1 signaling. CONCLUSION: Secondhand CS exposures caused molecular and biochemical abnormalities in brain that overlap with the findings in AD, and many of these effects were sustained or worsened despite short-term CS withdrawal.
Keywords: Animals; Brain; Insulin; Male; Mice; Nerve Degeneration; Neurons; Phosphorylation; Receptor, IGF Type 1; Signal Transduction; Somatomedins; Tobacco Smoke Pollution

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration. - Yu, Rosa; Deochand, Chetram; Krotow, Alexander; Leão, Raiane; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis studies showed that smokers have increased risk for developing Alzheimer's disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. OBJECTIVE: The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. METHODS: Adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). The frontal lobes were used for histology and qRT-PCR analysis. RESULTS: Luxol fast blue, Hematoxylin and Eosin stained histological sections revealed CS-associated reductions in myelin staining intensity and narrowing of the corpus callosum. CS exposures broadly decreased mRNA levels of immature and mature oligodendrocyte myelin-associated, neuroglial, and oligodendrocyte-related transcription factors. These effects were more prominent in the CS8 compared with CS4 group, suggesting that molecular abnormalities linked to white matter atrophy and myelin loss worsen with duration of CS exposure. Recovery normalized or upregulated less than 25% of the suppressed genes; in most cases, inhibition of gene expression was either sustained or exacerbated. CONCLUSION: CS exposures broadly inhibit expression of genes needed for myelin synthesis and maintenance. These adverse effects often were not reversed by short-term CS withdrawal. The results support the hypothesis that smoking contributes to white matter degeneration, and therefore could be a key risk factor for a number of neurodegenerative diseases, including AD.
Keywords: 2',3'-Cyclic-Nucleotide Phosphodiesterases; AC133 Antigen; Animals; Antigens, CD; Brain; Disease Models, Animal; Galactosylceramides; Gene Expression Regulation; Glycoproteins; Leukoencephalopathies; Male; Mice; Nerve Degeneration; Nerve Tissue Proteins; Neuroglia; Neurons; Oligodendroglia; Papain; Peptides; Smoking; Tobacco; Transcription Factors

Towards a Pathway Inventory of the Human Brain for Modeling Disease Mechanisms Underlying Neurodegeneration. - Iyappan, Anandhi; Gündel, Michaela; Shahid, Mohammad; Wang, Jiali; Li, Hui; Mevissen, Heinz-Theodor; Müller, Bernd; Fluck, Juliane; Jirsa, Viktor; Domide, Lia; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2016)
Molecular signaling pathways have been long used to demonstrate interactions among upstream causal molecules and downstream biological effects. They show the signal flow between cell compartments, the majority of which are represented as cartoons. These are often drawn manually by scanning through the literature, which is time-consuming, static, and non-interoperable. Moreover, these pathways are often devoid of context (condition and tissue) and biased toward certain disease conditions. Mining the scientific literature creates new possibilities to retrieve pathway information at higher contextual resolution and specificity. To address this challenge, we have created a pathway terminology system by combining signaling pathways and biological events to ensure a broad coverage of the entire pathway knowledge domain. This terminology was applied to mining biomedical papers and patents about neurodegenerative diseases with focus on Alzheimer's disease. We demonstrate the power of our approach by mapping literature-derived signaling pathways onto their corresponding anatomical regions in the human brain under healthy and Alzheimer's disease states. We demonstrate how this knowledge resource can be used to identify a putative mechanism explaining the mode-of-action of the approved drug Rasagiline, and show how this resource can be used for fingerprinting patents to support the discovery of pathway knowledge for Alzheimer's disease. Finally, we propose that based on next-generation cause-and-effect pathway models, a dedicated inventory of computer-processable pathway models specific to neurodegenerative diseases can be established, which hopefully accelerates context-specific enrichment analysis of experimental data with higher resolution and richer annotations.

Uncovering the Neural Bases of Cognitive and Affective Empathy Deficits in Alzheimer's Disease and the Behavioral-Variant of Frontotemporal Dementia. - Dermody, Nadene; Wong, Stephanie; Ahmed, Rebekah; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2016)
Loss of empathy is a core presenting feature of the behavioral-variant of frontotemporal dementia (bvFTD), resulting in socioemotional difficulties and behavioral transgressions. In contrast, interpersonal functioning remains relatively intact in Alzheimer's disease (AD), despite marked cognitive decline. The neural substrates mediating these patterns of loss and sparing in social functioning remain unclear, yet are relevant for our understanding of the social brain. We investigated cognitive versus affective aspects of empathy using the Interpersonal Reactivity Index (IRI) in 25 AD and 24 bvFTD patients and contrasted their performance with 22 age- and education-matched controls. Cognitive empathy was comparably compromised in AD and bvFTD, whereas affective empathy was impaired exclusively in bvFTD. While controlling for overall cognitive dysfunction ameliorated perspective-taking deficits in AD, empathy loss persisted across cognitive and affective domains in bvFTD. Voxel-based morphometry analyses revealed divergent neural substrates of empathy loss in each patient group. Perspective-taking deficits correlated with predominantly left-sided temporoparietal atrophy in AD, whereas widespread bilateral frontoinsular, temporal, parietal, and occipital atrophy was implicated in bvFTD. Reduced empathic concern in bvFTD was associated with atrophy in the left orbitofrontal, inferior frontal, and insular cortices, and the bilateral mid-cingulate gyrus. Our findings suggest that social cognitive deficits in AD arise largely as a consequence of global cognitive dysfunction, rather than a loss of empathy per se. In contrast, loss of empathy in bvFTD reflects the deterioration of a distributed network of frontoinsular and temporal structures that appear crucial for monitoring and processing social information.

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Validation of microRNAs in Cerebrospinal Fluid as Biomarkers for Different Forms of Dementia in a Multicenter Study. - Müller, Mareike; Kuiperij, H Bea; Versleijen, Alexandra A M; Chiasserini, Davide; Farotti, Lucia; Baschieri, Francesca; Parnetti, Lucilla; Struyfs, Hanne; De Roeck, Naomi; Luyckx, Jill; Engelborghs, Sebastiaan; Claassen, Jurgen A; et al. (J Alzheimers Dis, 2016)
MicroRNAs (miRNAs) regulate translational inhibition of proteins, but are also detected in body fluids, including cerebrospinal fluid (CSF), where they may serve as disease-specific biomarkers. Previously, we showed differential expression of miR-146a, miR-29a, and miR-125b in the CSF of Alzheimer's disease (AD) patients versus controls. In this study, we aim to confirm these findings by using larger, independent sample cohorts of AD patients and controls from three different centers. Furthermore, we aim to identify confounding factors that possibly arise using such a multicenter approach. The study was extended by including patients diagnosed with mild cognitive impairment due to AD, frontotemporal dementia and dementia with Lewy bodies. Previous results of decreased miR-146a levels in AD patients compared to controls were confirmed in one center. When samples from all three centers were combined, several confounding factors were identified. After controlling for these factors, we did not identify differences in miRNA levels between the different groups. However, we provide suggestions to circumvent various pitfalls when measuring miRNAs in CSF to improve future studies.

Validation of the Spanish version of the Baylor Profound Mental Status Examination. - Salmerón, Sergio; Huedo, Isabel; López-Utiel, Melisa; Soler-Moratalla, Isabel; Flores-Ruano, Teresa; Fernández-Sánchez, Miguel; Noguerón, Alicia; Doody, Rachelle S; Abizanda, Pedro (J Alzheimers Dis, 2016)
BACKGROUND: There are no short valid instruments to evaluate cognitive status in severe Alzheimer's disease (AD) patients in the Spanish language. OBJECTIVE: To validate the Spanish version of the Baylor Profound Mental Status Examination (BPMSE-Sp). METHODS: The Baylor Profound Mental Status Examination (BPMSE) was translated to Spanish and back translated. Validation was conducted in 100 patients with severe probable AD with a Mini-Mental State Examination (MMSE) <12. We assessed internal consistency (Cronbach's alpha), concurrent validity (Pearson's correlations) with the MMSE, Severe Impairment Battery (SIB), Neuropsychiatric Inventory Short Form (NPI-Q) and the Functional Assessment Staging and reliability. RESULTS: The mean age of patients was 84.9; 74% were female; 64% were institutionalized. The mean MMSE was 5.6; the mean BPMSE-Sp was 13.6; the mean BPMSE-Sp behavior was 1.2; the mean SIB was 42.2; and the mean NPI-Q was 4.7. BPMSE-Sp presented good internal consistency (Cronbach α= 0.84). There were significant correlations between the BPMSE-Sp and MMSE (r = 0.86, p <  0.001), and between the BPMSE-Sp and SIB (r = 0.92, p <  0.001). Inter-rater and test-retest reliability were in both cases excellent, ranging between 0.96 and 0.99 (p <  0.001). BPMSE-Sp had fewer floor and ceiling effects than the MMSE. CONCLUSIONS: The BPMSE-Sp is a valid tool for use in daily practice and research in the evaluation of cognitive function of patients with severe AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognition Disorders; Female; Humans; Language; Male; Mental Status Schedule; Neuropsychological Tests; Reproducibility of Results; Severity of Illness Index; Spain

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vascular Contributions in Alzheimer's Disease-Related Neuropathological Changes: First Autopsy Evidence from a South Asian Aging Population. - Wijesinghe, Printha; Shankar, S K; Yasha, T C; Gorrie, Catherine; Amaratunga, Dhammika; Hulathduwa, Sanjayah; Kumara, K Sunil; Samarasinghe, Kamani; Suh, Yoo-Hun; Steinbusch, Harry W M; De Silva, K Ranil D (J Alzheimers Dis, 2016)
BACKGROUND: Evidence from various consortia on vascular contributions has been inconsistent in determining the etiology of sporadic Alzheimer's disease (AD). OBJECTIVE: To investigate vascular risk factors and cerebrovascular pathologies associated in manifestation of AD-related neuropathological changes of an elderly population. METHODS: Postmortem brain samples from 76 elderly subjects (≥50 years) were used to study genetic polymorphisms, intracranial atherosclerosis of the circle of Willis (IASCW), and microscopic infarcts in deep white matters. From this cohort, 50 brains (≥60 years) were subjected to neuropathological diagnosis using immunohistopathological techniques. RESULTS: Besides the association with age, the apolipoprotein E ɛ4 allele was significantly and strongly associated with Thal amyloid-β phases ≥1 [odds ratio (OR) = 6.76, 95% confidence interval (CI) 1.37-33.45] and inversely with Braak neurofibrillary tangle (NFT) stages ≥III (0.02, 0.0-0.47). Illiterates showed a significant positive association for Braak NFT stages ≥IV (14.62, 1.21-176.73) and a significant negative association for microscopic infarcts (0.15, 0.03-0.71) in deep white matters. With respect to cerebrovascular pathologies, cerebral small vessel lesions (white matter hyperintensities and cerebral amyloid angiopathy) showed a higher degree of associations among them and with AD-related neuropathological changes (p < 0.05) compared to large vessel pathology (IASCW), which showed a significant association only with Braak NFT stages ≥I (p = 0.050). CONCLUSION: These findings suggest that besides age, education, and genetic factors, other vascular risk factors were not associated with AD-related neuropathological changes and urge prompt actions be taken against cerebral small vessel diseases since evidence for effective prevention is still lacking.

Ventilatory Response to Hypercapnia Predicts Dementia with Lewy Bodies in Late-Onset Major Depressive Disorder. - Takahashi, Sho; Mizukami, Katsuyoshi; Arai, Tetsuaki; Ogawa, Ryoko; Kikuchi, Norihiro; Hattori, Satoshi; Darby, David; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: Studies have shown that developing major depressive disorder (MDD) at 50 years of age or older can predict dementia. Depression is particularly common in dementia with Lewy bodies (DLB), and occasionally occurs before the onset of extrapyramidal symptoms. Moreover, systemic autonomic dysfunction, including an abnormal ventilatory response to hypercapnia (VRH), is common in patients with DLB. OBJECTIVE: Here, we aimed to determine whether the VRH is useful for distinguishing depression that is predictive of DLB from other types of MDD. METHODS: Participants were 35 consecutive patients with first onset MDD at 50 years or older with bradykinesia. After diagnosing the clinical subtype of MDD according to DSM-IV criteria, each subject underwent a battery of psychological tests, autonomic examinations including VRH, brain magnetic resonance imaging, and 123I-meta-iodobenzylguanidine scintigraphy. RESULTS: Longitudinal follow-up showed that all 18 patients with abnormal VRH results developed DLB, whereas none of the 17 patients with normal VRH results converted to DLB within the study period (sensitivity: 100% , specificity: 100%). Additionally, over half of the DLB converters showed abnormalities on other autonomic examinations. For converters, the most common MDD subtype had psychotic and melancholic features simultaneously. The frequency of hypersensitivity to psychotropics was higher in converters than it was in non-converters. CONCLUSION: In the present study, patients with abnormal VRH results were very likely to develop DLB. Thus, for patients with late-onset MDD accompanied by bradykinesia, the VRH in combination with the clinical subtype of MDD or hypersensitivity to psychotropics may be useful for diagnosing prodromal DLB.
Keywords: 3-Iodobenzylguanidine; Aged; Aged, 80 and over; Depressive Disorder, Major; Follow-Up Studies; Heart Rate; Humans; Hypercapnia; Hypotension, Orthostatic; Kaplan-Meier Estimate; Lewy Body Disease; Middle Aged; Partial Pressure; Psychiatric Status Rating Scales; Retrospective Studies; Ventilators, Mechanical

Vitamin D and Memory Decline: Two Population-Based Prospective Studies. - Kuźma, Elżbieta; Soni, Maya; Littlejohns, Thomas J; Ranson, Janice M; van Schoor, Natasja M; Deeg, Dorly J H; Comijs, Hannie; Chaves, Paulo H M; Kestenbaum, Bryan R; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vitamin D deficiency has been linked with dementia risk, cognitive decline, and executive dysfunction. However, the association with memory remains largely unknown. OBJECTIVE: To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. METHODS: We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid vitamin D measurements, and follow-up memory assessments. The Benton Visual Retention Test (in the CHS) and Rey's Auditory Verbal Learning Test (in the LASA) were used to assess visual and verbal memory, respectively. RESULTS: In the CHS, those moderately and severely deficient in serum 25(OH)D changed -0.03 SD (95% CI: -0.06 to 0.01) and -0.10 SD (95% CI: -0.19 to -0.02) per year respectively in visual memory compared to those sufficient (p = 0.02). In the LASA, moderate and severe deficiency in serum 25(OH)D was associated with a mean change of 0.01 SD (95% CI: -0.01 to 0.02) and -0.01 SD (95% CI: -0.04 to 0.02) per year respectively in verbal memory compared to sufficiency (p = 0.34). CONCLUSIONS: Our findings suggest an association between severe vitamin D deficiency and visual memory decline but no association with verbal memory decline. They warrant further investigation in prospective studies assessing different memory subtypes.
Keywords: Humans; Memory Disorders; Netherlands; Prospective Studies; United States; Vitamin D; Vitamin D Deficiency

What are the Most Frequently Impaired Markers of Neurodegeneration in ADNI Subjects? - Andriuta, Daniela; Moullart, Véronique; Schraen, Susanna; Devendeville, Agnes; Meyer, Marc-Etienne; Godefroy, Olivier (J Alzheimers Dis, 2016)
The aim of this study was to examine the relationship between cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer's disease (AD) (Aβ1-42, t-tau, and p-tau) and 18Fluorodeoxyglucose positron emission tomography (FDG-PET) hypometabolism in subjects from the Alzheimer's Disease Neuroimaging Initiative, and specifically to determine which index of neurodegeneration was most frequently affected. The secondary objective was to determine the most frequently hypometabolic region in patients with a CSF AD signature (abnormal Aβ1-42 and abnormal p-tau). We included the 372 subjects (85 normal subjects, 212 patients with mild cognitive impairment, and 75 patients with AD) with a CSF biomarker dosage (Aβ1-42, t-tau, and p-tau) and brain FDG-PET. The relationship between FDG-PET metabolism (in five regions of interest (ROI) known to be damaged in AD) and CSF t-tau and p-tau levels was studied as a function of CSF Aβ1-42 status. FDG-PET hypometabolism and CSF t-tau and p-tau levels were correlated only in patients with an abnormal CSF Aβ1-42 level (t-tau: R2 = 0.044, p = 0.001; p-tau: R2 = 0.02, p = 0.03). In the latter patients, CSF p-tau was the most frequently (p = 0.0001) abnormal neurodegeneration marker (p-tau: 92.8%; FDG-PET: 56.5%; CSF t-tau: 59.1%). Within the five ROI of FDG PET, the angular gyrus metabolism (R2 = 0.149; p = 0.0001) was selected as the most tightly associated with CSF AD signature. The relation between CSF markers of neurodegeneration (p-tau and t-tau) and brain hypometabolism (in FDG-PET) is conditioned by presence of amyloid abnormality. This finding supports the current physiopathological model of AD. P-tau is the most frequently impaired biomarker. Using FDG PET angular gyrus hypometabolism is the most sensitive to CSF-biomarker-defined AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Cognitive Dysfunction; Databases, Factual; Female; Fluorodeoxyglucose F18; Humans; Male; Peptide Fragments; Phosphorylation; Positron-Emission Tomography; Radiopharmaceuticals; tau Proteins

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

Adipose Tissue Distribution in Patients with Alzheimer's Disease: A Whole Body MRI Case-Control Study. - Diehl-Wiesenecker, Eva; von Armin, Christine A F; Dupuis, Luc; Müller, Hans-Peter; Ludolph, Albert C; Kassubek, Jan (J Alzheimers Dis, 2015)
BACKGROUND: Total and central adiposity have been associated with increased risk of Alzheimer's disease (AD). Visceral and subcutaneous adipose tissues have different metabolic characteristics and could therefore be differentially associated with AD. OBJECTIVE: To compare regional fat distribution determined by magnetic resonance imaging (MRI) in AD patients and healthy controls and investigate associations with stage of the disease and chemical markers. The investigation was performed in a prospective case-control study. METHODS: We examined thirty patients with mild to moderate AD by whole-body MRI (1.5 T) and clinical questionnaires in comparison to thirty cognitively healthy age- and gender-matched study participants. Volumes of total, subcutaneous, and visceral body fat tissue were determined by an unbiased automatic analysis algorithm. Levels of leptin, ghrelin, and adiponectin were determined in serum, amyloid-β (Aβ)1-42 and tau protein levels in cerebrospinal fluid (CSF). RESULTS: Male AD patients displayed significantly more total fat tissue than male controls. This difference was not observed in women. We observed a trend toward higher volume of visceral fat tissue in all patients (p = 0.13). Severity of disease was not associated with fat distribution in our study. Increased leptin levels correlated with lower CSF Aβ 1-42 in female, but not in male, AD patients. CONCLUSIONS: Fat volume is increased in male, but not in female AD patients. Negative correlation of leptin levels and CSF Aβ 1-42 in females might be one co-factor for the increased AD risk of females. Further studies are required to confirm this gender difference in fat volume during AD and evaluate its pathophysiological importance.

Alzheimer's Disease Normative Cerebrospinal Fluid Biomarkers Validated in PET Amyloid-β Characterized Subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. - Li, Qiao-Xin; Villemagne, Victor L; Doecke, James D; Rembach, Alan; Sarros, Shannon; Varghese, Shiji; McGlade, Amelia; Laughton, Katrina M; Pertile, Kelly K; Fowler, Christopher J; Rumble, Rebecca L; Trounson, Brett O; et al. (J Alzheimers Dis, 2015)
BACKGROUND: The cerebrospinal fluid (CSF) amyloid-β (Aβ)1-42, total-tau (T-tau), and phosphorylated-tau (P-tau181P) profile has been established as a valuable biomarker for Alzheimer's disease (AD). OBJECTIVE: The current study aimed to determine CSF biomarker cut-points using positron emission tomography (PET) Aβ imaging screened subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, as well as correlate CSF analyte cut-points across a range of PET Aβ amyloid ligands. METHODS: Aβ pathology was determined by PET imaging, utilizing 11C-Pittsburgh Compound B, 18F-flutemetamol, or 18F-florbetapir, in 157 AIBL participants who also underwent CSF collection. Using an INNOTEST assay, cut-points were established (Aβ1-42 >544 ng/L, T-tau <407 ng/L, and P-tau181P <78 ng/L) employing a rank based method to define a "positive" CSF in the sub-cohort of amyloid-PET negative healthy participants (n = 97), and compared with the presence of PET demonstrated AD pathology. RESULTS: CSF Aβ1-42 was the strongest individual biomarker, detecting cognitively impaired PET positive mild cognitive impairment (MCI)/AD with 85% sensitivity and 91% specificity. The ratio of P-tau181P or T-tau to Aβ1-42 provided greater accuracy, predicting MCI/AD with Aβ pathology with ≥92% sensitivity and specificity. Cross-validated accuracy, using all three biomarkers or the ratio of P-tau or T-tau to Aβ1-42 to predict MCI/AD, reached ≥92% sensitivity and specificity. CONCLUSIONS: CSF Aβ1-42 levels and analyte combination ratios demonstrated very high correlation with PET Aβ imaging. Our study offers additional support for CSF biomarkers in the early and accurate detection of AD pathology, including enrichment of patient cohorts for treatment trials even at the pre-symptomatic stage.

Ankle-Brachial Index but Neither Intima Media Thickness Nor Coronary Artery Calcification is Associated With Mild Cognitive Impairment. - Weimar, Christian; Winkler, Angela; Dlugaj, Martha; Lehmann, Nils; Hennig, Frauke; Bauer, Marcus; Kröger, Knut; Kälsch, Hagen; Mahabadi, Amir-Abass; Dragano, Nico; Moebus, Susanne; Hoffmann, Barbara; et al. (J Alzheimers Dis, 2015)
BACKGROUND: Several studies have reported an association of atherosclerosis with mild cognitive impairment (MCI) and dementia independent of cardiovascular risk factors. OBJECTIVE: To compare the cross-sectional association of the ankle-brachial index (ABI), intima media thickness (IMT), and coronary artery calcification (CAC) with MCI and its subtypes, amnestic MCI (aMCI) and non-amnestic MCI (naMCI) in the population-based Heinz Nixdorf Recall cohort study. METHODS: 4,086 participants performed a validated brief cognitive assessment at the first follow-up examination (2006-2008). MCI was diagnosed according to previously published criteria. Prevalence ratio (PR) regression models adjusted for age, gender, education, cardiovascular risk factors, and APOE genotype were used to compare the association of the ABI, the CAC-Agatston score and the IMT with MCI and its subtypes. RESULTS: We identified 490 participants with MCI (mean age 66.1 ± 7.8, 46.9 % male, aMCI n = 249, naMCI n = 241) and 1,242 cognitively normal participants. A decreasing ABI (per 0.1) was significantly associated with a higher MCI prevalence in fully adjusted models (PR 1.06; 95% confidence interval (CI) 1.01-1.11), whereas an increasing CAC (log(CAC+1)) or IMT (per 0.1 mm) were not associated after adjustment. A decreasing ABI was also significantly associated with naMCI in fully adjusted models (PR 1.12; CI 1.03-1.21) but not with aMCI. CONCLUSIONS: Our data show that the degree of generalized atherosclerosis as measured by the ABI is associated with MCI and with naMCI in a population-based cohort.

APOE Affects the Volume and Shape of the Amygdala and the Hippocampus in Mild Cognitive Impairment and Alzheimer's Disease: Age Matters. - Tang, Xiaoying; Holland, Dominic; Dale, Anders M; Miller, Michael I (J Alzheimers Dis, 2015)
This paper examines how age intervenes in the effects of APOE ɛ4 allele on the volume and shape morphometrics of the hippocampus and the amygdala in mild cognitive impairment (MCI) and Alzheimer's disease. We evaluate the structural morphological differences between ɛ4 carriers and non-carriers in two age-dependent subgroups; younger than 75 years (Young-Old) and older than 80 years (Very-Old). While we show that the four structures of interest atrophy significantly in the ɛ4 carriers, relative to the non-carriers, of the Young-Old group, this effect is not observed in their Very-Old counterparts. The structures in the right hemisphere are found to be more affected by the APOE genotype than those in the left hemisphere and we identify the relevant regions in which significant atrophy occurs to be parts of the basolateral, centromedial, and lateral nucleus subregions of the amygdala and the CA1 and subiculum subregions of the hippocampus. We also observe that the APOE genotype only affects MCI patients that deteriorated to dementia within 3 years while leaving their "non-converting" counterparts unaffected.

Blood Protein Markers of Neocortical Amyloid-β Burden: A Candidate Study Using SOMAscan Technology. - Voyle, Nicola; Baker, David; Burnham, Samantha C; Covin, Antonia; Zhang, Zhanpan; Sangurdekar, Dipen P; Tan Hehir, Cristina A; Bazenet, Chantal; Lovestone, Simon; Kiddle, Steven; Dobson, Richard J B (J Alzheimers Dis, 2015)
BACKGROUND: Four previously reported studies have tested for association of blood proteins with neocortical amyloid-β burden (NAB). If shown to be robust, these proteins could have utility as a blood test for enrichment in clinical trials of Alzheimer's disease (AD) therapeutics. OBJECTIVE: This study aimed to investigate whether previously identified blood proteins also show evidence for association with NAB in serum samples from the Australian Imaging, Biomarker and Lifestyle Flagship Study of Ageing (AIBL). The study considers candidate proteins seen in cohorts other than AIBL and candidates previously discovered in the AIBL cohort. METHODS: Our study used the SOMAscan platform for protein quantification in blood serum. Linear and logistic regressions were used to model continuous NAB and dichotomized NAB respectively using single proteins as a predictor. Multiple protein models were built using stepwise regression techniques and support vectors machines. Age and APOE ε4 carriage were used as covariates for all analysis. RESULTS: Of the 41 proteins previously reported, 15 AIBL candidates and 20 non-AIBL candidates were available for testing. Of these candidates, pancreatic polypeptide (PPY) and IgM showed a significant association with NAB. Notably, IgM was found to associate with continuous NAB across cognitively normal control subjects. CONCLUSIONS: We have further demonstrated the association of PPY and IgM with NAB, despite technical differences between studies. There are several reasons for a lack of significance for the other candidates including platform differences and the use of serum rather than plasma samples. To investigate the possibility of technical differences causing lack of further replication, further studies are required.

Clinical Benefits for Older Alzheimer's Disease Patients: Okayama Late Dementia Study (OLDS). - Matsuzono, Kosuke; Yamashita, Toru; Ohta, Yasuyuki; Hishikawa, Nozomi; Sato, Kota; Kono, Syoichiro; Deguchi, Kentaro; Nakano, Yumiko; Abe, Koji (J Alzheimers Dis, 2015)
BACKGROUND/OBJECTIVE: There are few reports on the effects of anti-Alzheimer's disease (AD) drugs on older AD patients, and possible differences based on gender in a real world setting. METHODS: "Okayama Late Dementia Study (OLDS)" is a retrospective clinical cohort study focusing on older AD patients (n = 373; age≥75 years) treated with monotherapy donepezil (n = 55), galantamine (n = 222), rivastigmine (n = 63), or memantine (n = 33). The patients were evaluated as an entire group and separated by gender, using seven batteries for dementia assessment at baseline and at 3, 6, and 12 months of drug therapy. RESULTS: All four drugs preserved cognitive and affective functions until 12 months, except for Frontal Assessment Battery (FAB) with memantine ( *p <  0.05 versus baseline). Donepezil monotherapy significantly improved Hasegawa Dementia Rating Scale-Revised (HDS-R) at 3 months ( *p <  0.05), and memantine (3 and 6 months,  *p <  0.05) and rivastigmine (3 months,  **p <  0.01) improved Abe's Behavior and Psychological Symptom of Dementia Score (ABS), respectively. Activities of daily living (ADL) became significantly worse with galantamine at 12 months ( *p <  0.05). Male Mini-Mental State Examination scores became worse at 12 months with donepezil ( *p <  0.05), as did female Geriatric Depression Scale scores at 6 months ( *p <  0.05). Male HDS-R and ABS scores were preserved in the galantamine group until 12 months. Female ABS scores with memantine improved at 6 months ( *p <  0.05), while male ADL scores became worse with rivastigmine at 12 months ( *p <  0.05). CONCLUSION: OLDS revealed that anti-AD drugs were effective even for older AD patients, and the clinical benefits of each drug showed a small difference with regard to gender.

Cognitive Effects of Soy Isoflavones in Patients with Alzheimer's Disease. - Gleason, Carey E; Fischer, Barbara L; Dowling, N Maritza; Setchell, Kenneth D R; Atwood, Craig S; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2015)
BACKGROUND: In a previous trial, treatment with soy isoflavones was associated with improved nonverbal memory, construction abilities, verbal fluency, and speeded dexterity compared to treatment with placebo in cognitively healthy older adults. OBJECTIVE: The current trial aimed to examine the potential cognitive benefits of soy isoflavones in patients with Alzheimer's disease. METHODS: Sixty-five men and women over the age of 60 were treated with 100 mg/day soy isoflavones, or matching placebo capsules for six months. APOE genotype was determined for all participants. Cognitive outcomes and plasma isoflavone levels were measured at baseline, and at two additional time points: three and six months after baseline. RESULTS: Of the sixty-five participants enrolled, thirty-four (52.3% ) were women, and 31 (47.7% ) were APOEɛ4 positive. Average age was 76.3 (SD = 7.2) years. Fifty-nine (90.8% ) subjects completed all study visits. Plasma isoflavone levels increased in subjects treated with soy isoflavones compared to baseline and to placebo, although intersubject variability in plasma levels was large. No significant differences in treatment effects for cognition emerged between treatment groups or genders. Exploratory analyses of associations between changes in cognition and plasma isoflavone levels revealed an association between equol levels, and speeded dexterity and verbal fluency. CONCLUSIONS: Six months of 100 mg/day treatment with soy isoflavones did not benefit cognition in older men and women with Alzheimer's disease. However, our results suggest the need to examine the role of isoflavone metabolism, i.e., the ability to effectively metabolize soy isoflavones by converting daidzen to equol when attempting to fully clarify the cognitive effects of isoflavones.

Cognitive Function and Its Relationship with Macular Pigment Optical Density and Serum Concentrations of its Constituent Carotenoids. - Kelly, David; Coen, Robert F; Akuffo, Kwadwo Owusu; Beatty, Stephen; Dennison, Jessica; Moran, Rachel; Stack, Jim; Howard, Alan N; Mulcahy, Riona; Nolan, John M (J Alzheimers Dis, 2015)
BACKGROUND: Macular pigment (MP) levels correlate with brain concentrations of lutein (L) and zeaxanthin (Z), and have also been shown to correlate with cognitive performance in the young and elderly. OBJECTIVE: To investigate the relationship between MP, serum concentrations of L and Z, and cognitive function in subjects free of retinal disease with low MP (Group 1, n = 105) and in subjects with AMD (Group 2, n = 121). METHODS: MP was measured using customized heterochromatic flicker photometry and dual-wavelength autofluorescence; cognitive function was assessed using a battery of validated cognition tests; serum L and Z concentrations were determined by HPLC. RESULTS: Significant correlations were evident between MP and various measures of cognitive function in both groups (r = -0.273 to 0.261, p≤0.05, for all). Both serum L and Z concentrations correlated significantly (r = 0.187, p≤0.05 and r = 0.197, p≤0.05, respectively) with semantic (animal) fluency cognitive scores in Group 2 (the AMD study group), while serum L concentrations also correlated significantly with Verbal Recognition Memory learning slope scores in the AMD study group (r = 0.200, p = 0.031). Most of the correlations with MP, but not serum L or Z, remained significant after controlling for age, gender, diet, and education level. CONCLUSION: MP offers potential as a non-invasive clinical biomarker of cognitive health, and appears more successful in this role than serum concentrations of L or Z.

Correcting for the Absence of a Gold Standard Improves Diagnostic Accuracy of Biomarkers in Alzheimer's Disease. - Coart, Els; Barrado, Leandro García; Duits, Flora H; Scheltens, Philip; van der Flier, Wiesje M; Teunissen, Charlotte E; van der Vies, Saskia M; Burzykowski, Tomasz (J Alzheimers Dis, 2015)
BACKGROUND: Studies investigating the diagnostic accuracy of biomarkers for Alzheimer's disease (AD) are typically performed using the clinical diagnosis or amyloid-β positron emission tomography as the reference test. However, neither can be considered a gold standard or a perfect reference test for AD. Not accounting for errors in the reference test is known to cause bias in the diagnostic accuracy of biomarkers. OBJECTIVE: To determine the diagnostic accuracy of AD biomarkers while taking the imperfectness of the reference test into account. METHODS: To determine the diagnostic accuracy of AD biomarkers and taking the imperfectness of the reference test into account, we have developed a Bayesian method. This method establishes the biomarkers' true value in predicting the AD-pathology status by combining the reference test and the biomarker data with available information on the reliability of the reference test. The new methodology was applied to two clinical datasets to establish the joint accuracy of three cerebrospinal fluid biomarkers (amyloid-β1-42, Total tau, and P-tau181) by including the clinical diagnosis as imperfect reference test into the analysis. RESULTS: The area under the receiver-operating-characteristics curve to discriminate between AD and controls, increases from 0.949 (with 95% credible interval [0.935,0.960]) to 0.990 ([0.985,0.995]) and from 0.870 ([0.817,0.912]) to 0.975 ([0.943,0.990]) for the cohorts, respectively. CONCLUSIONS: Use of the Bayesian methodology enables an improved estimate of the exact diagnostic value of AD biomarkers and overcomes the lack of a gold standard for AD. Using the new method will increase the diagnostic confidence for early stages of AD.

Cortical Transcriptional Profiles in APOE4 Carriers with Alzheimer's Disease: Patterns of Protection and Degeneration. - Conejero-Goldberg, Concepcion; Hyde, Thomas M; Chen, Shufen; Herman, Mary M; Kleinman, Joel E; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2015)
Transcriptional profiling of postmortem Alzheimer's disease (AD) brain tissue has yielded important insights into disease. We recently described a novel approach to understand transcriptional changes in AD designed to identify both neurosusceptibility and intrinsic neuroprotective factors in young non-AD E4 carriers. Here we extend our work to APOE4-related AD itself. In temporal cortex (BA 21), a region known to be vulnerable to AD pathology, we identified over 1,400 transcripts that differed between APOE4 controls and APOE4 carriers diagnosed with AD. Results from somatosensory cortex (BA 1/2/3), a region relatively preserved in AD differed strikingly from temporal cortex in that differences were far fewer (37 versus 1,492). We also conducted another set of contrasts involving APOE3 AD cases and APOE4 AD cases to better understand what transcriptional differences were dependent on genotype, but independent of disease status. When analyzing interregional differences, ten pathways differed between both brain areas in the APOE4 AD cases to APOE4 controls contrast and two pathways differed between both brain areas in the APOE4 cases to APOE3 controls contrast. Base excision repair pathway was found in common for both contrasts. In summary, our results indicate that many of the molecular changes identified in the brains of patients with AD reflect the non-specific consequences of neurodegeneration, rather than causative processes. Additionally, the molecular signatures specific to somatosensory cortex may make it uniquely resistant to AD pathology and thereby could provide important leads for treatment.

Depressive Symptoms and Biomarkers of Alzheimer's Disease in Cognitively Normal Older Adults. - Donovan, Nancy J; Hsu, David C; Dagley, Alexander S; Schultz, Aaron P; Amariglio, Rebecca E; Mormino, Elizabeth C; Okereke, Olivia I; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2015)
Even low levels of depressive symptoms are associated with an increased risk of cognitive decline in older adults without overt cognitive impairment (CN). Our objective was to examine whether very low, "subthreshold symptoms of depression" are associated with Alzheimer's disease (AD) biomarkers of neurodegeneration in CN adults and whether these associations are specific to particular depressive symptoms. We analyzed data from 248 community-dwelling CN older adults, including measurements of cortical amyloid burden, neurodegeneration markers of hippocampal volume (HV) and cerebral 18F-fluorodeoxyglucose (FDG) metabolism in a composite of AD-related regions and the 30-item Geriatric Depression Scale (GDS). Participants with GDS >10 were excluded. General linear regression models evaluated the cross-sectional relations of GDS to HV or FDG in separate backward elimination models. Predictors included GDS total score, age, gender, premorbid intelligence, a binary amyloid variable and its interaction with GDS. Principal component analyses of GDS item scores revealed three factors (the Dysphoria, Apathy-Anhedonia, and Anxiety-Concentration Factors). In secondary analyses, GDS total score was replaced with the three factor scores in repeated models. Higher GDS score (p = 0.03) was significantly associated with lower HV and was marginally related (p = 0.06) to FDG hypometabolism. In secondary models, higher Dysphoria (p = 0.02) and Apathy-Anhedonia (p = 0.05) were related to lower HV while higher Apathy-Anhedonia (p = 0.003) was the sole factor related to FDG hypometabolism. Amyloid was not a significant predictor in any model. In conclusion, very low-level dysphoria, apathy and anhedonia may point to neurodegeneration in AD-related regions but this association appears to be independent of amyloid burden.

Diabetes is Associated with Worse Executive Function in Both Eastern and Western Populations: Shanghai Aging Study and Mayo Clinic Study of Aging. - Zhao, Qianhua; Roberts, Rosebud O; Ding, Ding; Cha, Ruth; Guo, Qihao; Meng, Haijiao; Luo, Jianfeng; Machulda, Mary M; Shane Pankratz, V; Wang, Bei; Christianson, Teresa J H; Aakre, Jeremiah A; et al. (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVES: It remains unknown whether the association between diabetes mellitus (DM) and cognitive function differs in Eastern and Western populations. This study aimed to elucidate whether DM is associated with worse cognitive performance in both populations. METHODS: The Shanghai Aging Study (SAS) and the Mayo Clinic Study of Aging (MCSA) are two population-based studies with similar design and methodology in Shanghai, China and Rochester, MN, USA. Non-demented participants underwent cognitive testing, and DM was assessed from the medical record. Separate analyses were performed in SAS and MCSA regarding the association between DM and cognitive performance. RESULTS: A total of 3,348 Chinese participants in the SAS and 3,734 American subjects in the MCSA were included. Compared with MCSA subjects, SAS participants were younger, less educated, and had lower frequency of vascular disease, APOE ɛ4 carriers and obesity. Participants with DM (compared to non-DM participants) performed significantly worse on all the cognitive domains in both the SAS and MCSA. After adjustment for age, gender, education, and vascular covariates, DM was associated with worse performance in executive function (β=-0.15, p = 0.001 for SAS, and β=-0.10, p = 0.008 for MCSA) in the total sample and in the cognitively normal sub-sample. Furthermore, DM was associated with poor performance in visuospatial skills, language, and memory in the SAS, but not in the MCSA. CONCLUSIONS: Diabetes is associated with cognitive dysfunction and, in particular, exerts a negative impact on executive function regardless of race, age, and prevalence of vascular risk factors.

Differential Effects of Meal Challenges on Cognition, Metabolism, and Biomarkers for Apolipoprotein E ɛ4 Carriers and Adults with Mild Cognitive Impairment. - Hanson, Angela J; Bayer, Jennifer L; Baker, Laura D; Cholerton, Brenna; VanFossen, Brian; Trittschuh, Emily; Rissman, Robert A; Donohue, Michael C; Moghadam, Setareh H; Plymate, Stephen R; Craft, Suzanne (J Alzheimers Dis, 2015)
BACKGROUND: High intake of saturated fat (SF) and glycemic index (GI) foods is a risk factor for sporadic Alzheimer's disease. Meal challenges may elucidate mechanisms that contribute to this risk, enabling development of targeted interventions. OBJECTIVE: To assess cognitive and metabolic changes after a meal high in SF and GI calories (HIGH) versus a meal low in these macronutrients (LOW) in older adults with and without cognitive impairment, and with and without the apolipoprotein E4 risk factor. METHODS: 46 adults with either cognitive impairment (CI) or normal cognition (NC) ingested a LOW (25% total fat, 7% SF, GI <55) and a HIGH meal (50% total fat, 25% SF, GI >70) in a blinded random fashion. Participants then underwent cognitive testing and blood sampling for metabolic and Alzheimer's disease biomarkers. Data were analyzed using repeated measures ANOVA and Spearman correlations. RESULTS: E4-adults with NC demonstrated lower delayed memory scores after the HIGH compared to the LOW meal, whereas normal E4+ and CI E4- groups had higher scores after the HIGH meal (ANOVA p = 0.03). These findings were associated with meal-induced changes in glucose (p = 0.05), insulin (p = 0.004), triglycerides (p <  0.01), and plasma Aβ42 (p = 0.05). CONCLUSIONS: These preliminary data suggest that cognitive performance of adults without CI may worsen following high SF and sugar meals, whereas adults with CI or those at risk for CI due to E4 status may benefit acutely from such meals. Furthermore, plasma Aβ was affected by meal type, suggesting a relationship between metabolic response and amyloid regulation.

The Multi-Target Drug M30 Shows Pro-Cognitive and Anti-Inflammatory Effects in a Rat Model of Alzheimer's Disease. - Pimentel, Luisa S; Allard, Simon; Do Carmo, Sonia; Weinreb, Orly; Danik, Marc; Hanzel, Cecilia E; Youdim, Moussa B; Cuello, A Claudio (J Alzheimers Dis, 2015)
Current therapies for Alzheimer's disease (AD) offer partial symptomatic relief and do not modify disease progression. There is substantial evidence indicating a disease onset years before clinical diagnosis, at which point no effective therapy has been found. In this study, we investigated the efficacy of a new multi-target drug, M30, at relatively early stages of the AD-like amyloid pathology in a robust rat transgenic model. McGill-R-Thy1-APP transgenic rats develop the full AD-like amyloid pathology in a progressive fashion, and have a minimal genetic burden. McGill rats were given 5 mg/kg M30 or vehicle per os, every 2 days for 4 months, starting at a stage where the transgenic animals suffer detectable cognitive impairments. At the completion of the treatment, cognitive functions were assessed with Novel Object Location and Novel Object Recognition tests. The brains were then analyzed to assess amyloid-β (Aβ) burden and the levels of key inflammatory markers. Long-term treatment with M30 was associated with both the prevention and the reversal of transgene-related cognitive decline. The effects on cognition were accompanied by a shift of the Aβ-immunoreactive material toward an amyloid plaque aggregated molecular form, diminished molecular signs of CNS inflammation and a change in microglia morphology toward a surveying phenotype. This study is the first to demonstrate the therapeutic potential of M30 in a rat model of the AD amyloid pathology. It provides a rationale for further investigations with M30 and with potential multi-target approaches to delay, prevent or reverse the progression the AD pathology at early disease-stages.

A Phase II Randomized Clinical Trial of a Nutritional Formulation for Cognition and Mood in Alzheimer's Disease. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Doshanjh, Laura; Fishman, Paul; Luo, Yuan; Smyers, Kathleen; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2015)
Background: Increasing evidence points toward the efficacy of nutritional modifications in delaying cognitive decline and mood/behavioral difficulties in Alzheimer's disease (AD). Nutritional supplementation with individual agents has shown varied results suggesting the need for combinatorial intervention. Objective: We set out to determine whether nutritional intervention could positively impact cognitive performance and behavioral difficulties for individuals diagnosed with AD. Methods: A double-blind, multi-site, phase II study (ClinicalTrials.gov NCT01320527; Alzheimer's Association Trialmatch) was conducted in which 106 individuals with AD were randomized to a nutraceutical formulation (NF; folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) or placebo for 3 or 6 months, followed by an open-label extension where participants received NF for 6 additional months. Results: The NF cohort improved versus the placebo cohort within 3 months (Clox-1 p = 0.0083, 95%CI [0.4481, 2.9343]; Dementia Rating Scale p = 0.0266, 95%CI [0.1722, 2.7171]). Caregivers reported non-significant improvements in Neuropsychiatric Inventory. Both cohorts improved or maintained baseline performance during open-label extensions. Activities of Daily Living did not change for either cohort. Conclusions: These findings extend phase I studies where NF maintained or improved cognitive performance and mood/behavior.

Subtle Cognitive Decline and Biomarker Staging in Preclinical Alzheimer's Disease. - Edmonds, Emily C; Delano-Wood, Lisa; Galasko, Douglas R; Salmon, David P; Bondi, Mark W (J Alzheimers Dis, 2015)
The NIA-AA criteria for "preclinical" Alzheimer's disease (AD) propose a staging method in which AD biomarkers follow an invariable temporal sequence in accordance with the amyloid cascade hypothesis. However, recent findings do not align with the proposed temporal sequence and "subtle cognitive decline," which has not been definitively operationalized, may occur earlier than suggested in preclinical AD. We aimed to define "subtle cognitive decline" using sensitive and reliable neuropsychological tests, and to examine the number and sequence of biomarker abnormalities in the Alzheimer's Disease Neuroimaging Initiative (ADNI). 570 cognitively normal ADNI participants were classified based on NIA-AA criteria and separately based on the number of abnormal biomarkers/cognitive markers associated with preclinical AD that each individual possessed. Results revealed that neurodegeneration alone was 2.5 times more common than amyloidosis alone at baseline. For those who demonstrated only one abnormal biomarker at baseline and later progressed to mild cognitive impairment/AD, neurodegeneration alone was most common, followed by amyloidosis alone or subtle cognitive decline alone, which were equally common. Findings suggest that most individuals do not follow the temporal order proposed by NIA-AA criteria. We provide an operational definition of subtle cognitive decline that captures both cognitive and functional decline. Additionally, we offer a new approach for staging preclinical AD based on number of abnormal biomarkers, without regard to their temporal order of occurrence. This method of characterizing preclinical AD is more parsimonious than the NIA-AA staging system and does not presume that all patients follow a singular invariant expression of the disease.

Tau and Amyloid-β Cerebrospinal Fluid Biomarkers have Differential Relationships with Cognition in Mild Cognitive Impairment. - Malpas, Charles B; Saling, Michael M; Velakoulis, Dennis; Desmond, Patricia; O'Brien, Terence J (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is characterized by two primary pathologies: tau-related neurofibrillary tangles and the extracellular accumulation of amyloid-β (Aβ). The development of these pathologies is topologically distinct early in the disease, with Aβ beginning to accumulate as a diffuse, neocortical pathology, while tau-related pathology begins to form in mesial temporal regions. This study investigated the hypothesis that, by virtue of this distinction, there exist preferential associations between the primary pathologies and aspects of the cognitive phenotype. We investigated the relationship between cerebrospinal fluid (CSF) biomarkers for tau and Aβ pathologies with neurocognitive measures in 191 patients with mild cognitive impairment (MCI). Participants completed cognitive tests of new learning, information processing speed, and working memory. Separate regression models were computed and then followed up with mediation analyses to examine the predictive status of CSF biomarkers. The effect of Aβ on learning was mediated by phospho-tau (p = 0.008). In contrast, Aβ had a direct effect on information processing speed that was not mediated by phospho-tau (p = 0.59). No predictors were significant for working memory. This study provided evidence for a differential relationship of Aβ and phospho-tau pathologies on the neurocognitive phenotype of MCI. This supports the proposition that these primary AD pathologies maximally affect different aspects of cognition, and has potential implications for cognitive assessments and the use of biomarkers in disease-modifyingtherapeutic trials.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

A paravascular pathway facilitates CSF flow through the brain parenchyma and the clearance of interstitial solutes, including amyloid β. - Iliff, Jeffrey J; Wang, Minghuan; Liao, Yonghong; Plogg, Benjamin A; Peng, Weiguo; Gundersen, Georg A; Benveniste, Helene; Vates, G Edward; Deane, Rashid; Goldman, Steven A; Nagelhus, Erlend A; Nedergaard, Maiken (Sci Transl Med, 2012)
Because it lacks a lymphatic circulation, the brain must clear extracellular proteins by an alternative mechanism. The cerebrospinal fluid (CSF) functions as a sink for brain extracellular solutes, but it is not clear how solutes from the brain interstitium move from the parenchyma to the CSF. We demonstrate that a substantial portion of subarachnoid CSF cycles through the brain interstitial space. On the basis of in vivo two-photon imaging of small fluorescent tracers, we showed that CSF enters the parenchyma along paravascular spaces that surround penetrating arteries and that brain interstitial fluid is cleared along paravenous drainage pathways. Animals lacking the water channel aquaporin-4 (AQP4) in astrocytes exhibit slowed CSF influx through this system and a ~70% reduction in interstitial solute clearance, suggesting that the bulk fluid flow between these anatomical influx and efflux routes is supported by astrocytic water transport. Fluorescent-tagged amyloid β, a peptide thought to be pathogenic in Alzheimer's disease, was transported along this route, and deletion of the Aqp4 gene suppressed the clearance of soluble amyloid β, suggesting that this pathway may remove amyloid β from the central nervous system. Clearance through paravenous flow may also regulate extracellular levels of proteins involved with neurodegenerative conditions, its impairment perhaps contributing to the mis-accumulation of soluble proteins.
Keywords: Amyloid beta-Peptides; Animals; Aquaporin 4; Astrocytes; Biological Transport; Brain; Cerebral Ventricles; Cerebrospinal Fluid; Extracellular Fluid; Imaging, Three-Dimensional; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence, Multiphoton; Water

Propagation of tau pathology in a model of early Alzheimer's disease. - de Calignon, Alix; Polydoro, Manuela; Suárez-Calvet, Marc; William, Christopher; Adamowicz, David H; Kopeikina, Kathy J; Pitstick, Rose; Sahara, Naruhiko; Ashe, Karen H; Carlson, George A; Spires-Jones, Tara L; Hyman, Bradley T (Neuron, 2012)
Neurofibrillary tangles advance from layer II of the entorhinal cortex (EC-II) toward limbic and association cortices as Alzheimer's disease evolves. However, the mechanism involved in this hierarchical pattern of disease progression is unknown. We describe a transgenic mouse model in which overexpression of human tau P301L is restricted to EC-II. Tau pathology progresses from EC transgene-expressing neurons to neurons without detectable transgene expression, first to EC neighboring cells, followed by propagation to neurons downstream in the synaptic circuit such as the dentate gyrus, CA fields of the hippocampus, and cingulate cortex. Human tau protein spreads to these regions and coaggregates with endogenous mouse tau. With age, synaptic degeneration occurs in the entorhinal target zone and EC neurons are lost. These data suggest that a sequence of progressive misfolding of tau proteins, circuit-based transfer to new cell populations, and deafferentation induced degeneration are part of a process of tau-induced neurodegeneration.
Keywords: Age Factors; Alzheimer Disease; Animals; Disease Models, Animal; Disease Progression; Entorhinal Cortex; Epitopes; Gene Expression Regulation; Glial Fibrillary Acidic Protein; Gliosis; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Degeneration; Neurofibrillary Tangles; Neurons; RNA, Messenger; Serine; tau Proteins; Tauopathies

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Stages of the pathologic process in Alzheimer disease: age categories from 1 to 100 years. - Braak, Heiko; Thal, Dietmar R; Ghebremedhin, Estifanos; Del Tredici, Kelly (J Neuropathol Exp Neurol, 2011)
Two thousand three hundred and thirty two nonselected brains from 1- to 100-year-old individuals were examined using immunocytochemistry (AT8) and Gallyas silver staining for abnormal tau; immunocytochemistry (4G8) and Campbell-Switzer staining were used for the detection ofβ-amyloid. A total of 342 cases was negative in the Gallyas stain but when restaged for AT8 only 10 were immunonegative. Fifty-eight cases had subcortical tau predominantly in the locus coeruleus, but there was no abnormal cortical tau (subcortical Stages a-c). Cortical involvement (abnormal tau in neurites) was identified first in the transentorhinal region (Stage 1a, 38 cases). Transentorhinal pyramidal cells displayed pretangle material (Stage 1b, 236 cases). Pretangles gradually became argyrophilic neurofibrillary tangles (NFTs) that progressed in parallel with NFT Stages I to VI. Pretangles restricted to subcortical sites were seen chiefly at younger ages. Of the total cases, 1,031 (44.2%) had β-amyloid plaques. The first plaques occurred in the neocortex after the onset of tauopathy in the brainstem. Plaques generally developed in the 40s in 4% of all cases, culminating in their tenth decade (75%). β-amyloid plaques and NFTs were significantly correlated (p < 0.0001). These data suggest that tauopathy associated with sporadic Alzheimer disease may begin earlier than previously thought and possibly in the lower brainstem rather than in the transentorhinal region.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Humans; Infant; Male; Middle Aged; Neurofibrillary Tangles; Neurons; Silver Staining; Statistics, Nonparametric; tau Proteins; Young Adult

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide

National Institutes of Health State-of-the-Science Conference statement: preventing alzheimer disease and cognitive decline. - Daviglus, Martha L; Bell, Carl C; Berrettini, Wade; Bowen, Phyllis E; Connolly, E Sander; Cox, Nancy Jean; Dunbar-Jacob, Jacqueline M; Granieri, Evelyn C; Hunt, Gail; McGarry, Kathleen; Patel, Dinesh; Potosky, Arnold L; et al. (Ann Intern Med, 2010)
The National Institute on Aging and the Office of Medical Applications of Research of the National Institutes of Health convened a State-of-the-Science Conference on 26-28 April 2010 to assess the available scientific evidence on prevention of cognitive decline and Alzheimer disease. This article provides the panel's assessment of the available evidence.
Keywords: Aged; Alzheimer Disease; Cognition Disorders; Evidence-Based Medicine; Humans; Risk Factors; Risk Reduction Behavior